Alzheimer's disease-related cortical proteins modify the association of brain insulin signaling with cognitive decline. - Tong, Han; Petyuk, Vladislav A; Sendtner, Michael; Sood, Ajay; Bennett, David A; Capuano, Ana W; Arvanitakis, Zoe (J Alzheimers Dis, 2025)
BackgroundBrain insulin signaling has been associated with both Alzheimer's disease (AD) pathology and cognitive decline, but the mechanisms remain unclear.ObjectiveTo examine whether AD-related cortically-expressed proteins modify the association of brain insulin signaling and cognitive decline.MethodsParticipants included 116 autopsied members of the Religious Orders Study (58 with diabetes matched to 58 without, by age at death, sex, and education) who had both postmortem brain (prefrontal cortex) insulin signaling (by ELISA and immunohistochemistry, including RAC-alpha serine/threonine-protein kinase or AKT1) and AD-related cortical protein measurements. Levels of five AD-related proteins including insulin-like growth factor-binding protein-5 (IGFBP-5) and inositol-tetrakisphosphate 1-kinase (ITPK1) were measured using quantitative proteomics. We conducted adjusted linear mixed model analyses to examine associations of insulin signaling measures and AD-related proteins with longitudinally assessed cognitive function.ResultsHigher levels of IGFBP-5 and lower levels of ITPK1 were each associated with higher levels of AKT1 phosphorylation (pTAKT1 /total AKT1). Additionally, higher levels of AKT1 phosphorylation were associated with faster decline in global cognition and most cognitive domains. IGFBP-5 partially mediated the association of AKT1 phosphorylation with the decline rate of global cognition and cognitive domains including perceptual speed and visuospatial abilities. Further, ITPK1 had an interaction with AKT1 phosphorylation on decline of global cognition and domains including episodic memory, perceptual speed, and visuospatial abilities.ConclusionsAD-related proteins IGFBP-5 and ITPK1 are each associated with insulin signaling AKT1 phosphorylation in the postmortem human brain. Moreover, IGFBP-5 mediates, while ITPK1 moderates, the association between AKT1 phosphorylation and late-life cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognitive Dysfunction; Female; Humans; Insulin; Insulin-Like Growth Factor Binding Protein 5; Male; Phosphorylation; Proto-Oncogene Proteins c-akt; Signal Transduction

Association among cardiorespiratory fitness, plasma biomarkers of pathology and astrocyte reactivity, and cognition in autosomal-dominant Alzheimer's disease. - Guzmán-Vélez, Edmarie; Aguillón, David; Rivera-Hernández, Angelys; Baena, Ana Y; Londoño-Sotomayor, Natalia; Picard, Glen; Kramer, Arthur F; Arnold, Steven E; Caraballo-Gracia, Domingo I; Taylor, J Andrew; Quiroz, Yakeel T (J Alzheimers Dis, 2025)
BackgroundHigh cardiorespiratory fitness has been associated with greater neuroplasticity, and slower neurodegeneration and cognitive decline in healthy adults. Yet, less is known about whether low-to-intermediate cardiorespiratory fitness is associated with lower markers of disease progression in the preclinical stage of Alzheimer's disease (AD).ObjectiveWe investigated whether cardiorespiratory fitness was associated with plasma biomarkers for AD-related pathology, neural injury and astrocyte reactivity, and episodic memory in Presenilin-1 E280A carriers without dementia from the world's largest kindred with autosomal-dominant AD.MethodsTwenty-seven mutation carriers (25 cognitively unimpaired, 2 with mild cognitive impairment; ages: μ=30.22 years, SD = 5.24; 74% female) participated in the study. Participants underwent a graded aerobic fitness test to assess cardiorespiratory fitness, measured in maximum metabolic equivalent of task (MET). Plasma biomarkers included amyloid 42/40, phosphorylated tau-181, neurofilament light chain, and glial fibrillary acidic protein. Participants completed the Consortium to Establish a Registry for AD word list learning and delayed recall. We conducted multiple linear regressions controlling for age, sex, and years of education.ResultsFourteen participants' MET values were indicative of low cardiorespiratory fitness (< MET), and 13 participants' MET values of intermediate cardiorespiratory fitness (9-14 MET). METs were not associated with age, biomarkers, or episodic memory.ConclusionsOur findings suggest that low-to-intermediate cardiorespiratory fitness may not be associated with biomarkers for AD-related pathology, neural injury and astrocyte reactivity, or memory in people at genetic risk for dementia. Longitudinal studies and randomized-controlled trials are needed to better understand the relationships among cardiorespiratory fitness and AD progression.

Associations of dietary protein and amino acid intakes with disability-adjusted life years for Alzheimer's disease in Japanese people. - Ishikawa-Takata, Kazuko; Fujiwara, Kazuki; Tanaka, Takayuki; Nakamura, Keiji; Kobayashi, Hisamine; Okada, Shinobu (J Alzheimers Dis, 2025)
BackgroundThe number of patients with dementia is increasing worldwide. In Japan, dementia is the most significant reason recognized for people requiring nursing care. Protein is one of the possible preventive nutrients for dementia; however, adequate intake levels can differ according to usual protein intakes and protein sources.ObjectiveThis study examined the relationships between disability-adjusted life years (DALYs) for Alzheimer's disease and protein or amino acid intakes.MethodsGlobal Burden of Disease Study data (DALYs for each sex and age group in each year) and de-identified individual records from the National Health and Nutrition Survey Japan (data from 46,831 subjects) from 2001 to 2019 were used. Multiple regression analyses were conducted to assess the relationships between DALYs and protein or amino acid intakes with lifestyle factors and sociodemographic index as confounding factors.ResultsHigher protein-to-energy ratios were correlated with lower DALYs in women in their 70 s (partial regression coefficient [Coeff.] = -349.488,  = 0.034), in men in their 60 s (Coeff. = -51.484), and in both sexes combined in their 60 s (Coeff. = -26.696,  = 0.015) even after adjusting for other possible nutrient intakes. Additionally, elevated isoleucine, lysine, tyrosine, histidine, arginine, alanine, asparagine, and glycine levels were correlated with lower DALYs in women in their 70 s (Coeff. = -2.752 to -0.141).ConclusionsAdequate protein and specific amino acid intakes may be associated with DALYs for Alzheimer's disease.

Baseline associations of office and ambulatory blood pressure monitoring with cognitive function and dementia prevalence. - Melgarejo, Jesus D; Patil, Dhrumil; Charisis, Sokratis; Vatcheva, Kristina P; Mejia-Arango, Silvia; Mena, Luis J; Satizabal, Claudia L; Gaona, Ciro; Silva, Egle; Manusov, Eron; Lee, Joseph H; Terwilliger, Joseph D; et al. (J Alzheimers Dis, 2025)
BackgroundHigh blood pressure has been associated with dementia prevalence and incident. However, it is unclear the relationship of office and ambulatory BP monitoring with cognitive function and dementia and in particular, it remains unknown whether ambulatory BP variability relates to dementia.ObjectiveTo investigate the associations of office and 24-h blood pressure (BP) with cognitive function and dementia prevalence.MethodsCross-sectional population-based study of 1435 participants aged ≥40 years with office BP/24-h BP, and cognitive assessments (Mini-Mental State Examination [MMSE] and Selective Reminding Test [SRT]). Dementia was diagnosed with a clinical dementia rating ≥1.0. Statistics included logistic and linear regression models.ResultsThe mean age was 63.8 ± 10.3 years old and 995 (69.3%) were women. Out of the 1435 participants, 46 (3.20%) had dementia at baseline. Office and 24-h BP levels were not associated with dementia but with one SRT. Increasing 24-h systolic BP variability was associated with lower MMSE (adjusted mean, -0.08; 95% confidence interval [CI], -0.13, -0.03), and SRT (adjusted means ranged from -0.13 to -0.06; 95% CI ranging from -0.19 to -0.01) scores and 1.48-fold greater odds of dementia (95% CI, 1.09-2.02) regardless of BP level.ConclusionsElevated 24-h BP variability, not the BP level, seems to have a stronger association with lower cognitive function and dementia prevalence. Prospective studies are needed to address whether 24-h BP variability relates to cognitive decline and dementia incidence.

Cost-effectiveness of diagnosing and treating patients with early Alzheimer's disease with anti-amyloid treatment in a clinical setting. - Wimo, Anders; Handels, Ron; Blennow, Kaj; Kirsebom, K Bjørn-Eivind; Selnes, Per; Bon, Jaka; Emersic, Andreja; Gonzalez-Ortiz, Fernando; Gregoric Kramberger, Milica; Sköldunger, Anders; Speh, Andreja; Timón-Reina, Santiago; et al. (J Alzheimers Dis, 2025)
BackgroundThe introduction of anti-amyloid treatments (AAT) for Alzheimer's disease (AD) has put the cost-effectiveness into focus.ObjectiveEstimate the potential cost-effectiveness of diagnostic pathways combined with AAT for early AD.MethodsDiagnostic accuracy of blood-based (BBM) and cerebrospinal fluid (CSF) biomarkers was obtained from Norwegian memory clinics using positron emission tomography (PET) as reference standard. In a health-economic model, the cost-effectiveness of three diagnostic strategies was estimated relying either on BBM (p-tau 217), CSF (Aβ ratio), and BBM with CSF confirmatory testing and compared with standard of care (SoC) and compared with CSF-AAT. The model consisted of a decision tree reflecting the diagnostic process and a subsequent Markov cohort model starting at mild cognitive impairment due to AD. All strategies except SoC were combined with AAT including costs of treatment (assumed €5000/year), infusions and monitoring.ResultsCompared with SoC all three strategies (CSF-AAT, BBM-AAT, and BBM-CSF-AAT) resulted in QALY gains at higher costs, with an incremental cost-effectiveness ratio (ICER) of 110k€, 141k€ and 110k€ respectively. Compared with CSF-AAT both BBM-AAT and BBM-CSF-AAT strategies resulted in QALYs lost at lower costs, with an ICER of 27k€ and 109k€ respectively. Results were particularly sensitive to the price of AAT and possible subcutaneous administration.ConclusionsCompared with SoC all three strategies are potentially not cost-effective as they exceeded the Swedish maximum willingness to pay threshold of €94,800 per QALY gained. BBM-CSF-AAT versus CSF-AAT is potentially cost-effective if willing to accept its QALY loss. Discussions on budget impact on different payers are needed after introducing AAT.

Down syndrome and Alzheimer's disease: Oxidative stress in the neurodegenerative process. - Cordeiro, Augusto Magno Tranquezi; Singulani, Monique Patricio; Talib, Leda Leme; Forlenza, Orestes Vicente (J Alzheimers Dis, 2025)
BACKGROUND: Individuals with Down syndrome (DS) generally show neuropathological features of Alzheimer disease (AD). The trisomy of chromosome 21 causes an imbalance of antioxidant systems, which can be linked to AD pathophysiology. OBJECTIVE: Verify the difference between the activity of antioxidant enzymes and products of the oxidation process in peripheral blood in non-trisomic (NT) and trisomic (DS) adults and elders and respective associations with cognitive impairment. METHODS: A total of 120 subjects were included in this study. Sociodemographic and clinical information were collected as per protocol for participants in DS and NT groups. The cognitive state of the DS participants was established according to the Brazilian version of the Cambridge Examination for Mental Disorders of Older People with Down's syndrome and Others with Intellectual Disabilities (CAMDEX-DS). The CAMDEX interview was used for this purpose for participants in the NT group. Plasma samples were collected to evaluate protein carbonyl content, superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT), malondialdehyde (MDA), and 4-hydroxy-2-nonenal (HNE). RESULTS: We found increased levels of SOD and CAT activity in the DS group. When the groups were stratified by cognitive decline, elevated levels of SOD and CAT activity were found both in DS groups with and without decline. The activity of GPx was similar between the groups, as well as MDA and HNE. CONCLUSION: The results suggest that alterations of the antioxidative processes can be implicated in the onset of neurodegeneration observed in individuals with DS.

Dynamic PET imaging in patients with unilateral carotid occlusion shows lateralized cerebral hypoperfusion, but no amyloid binding. - Starmans, Naomi Lp; Leeuwis, Anna E; Bennink, Edwin; Meyer Viol, Sebastiaan L; Golla, Sandeep Sv; Dankbaar, Jan Willem; Bron, Esther E; Biessels, Geert Jan; Kappelle, L Jaap; van der Flier, Wiesje M; Tolboom, Nelleke (J Alzheimers Dis, 2025)
BackgroundCarotid occlusive disease is a risk factor for cognitive decline. A possible underlying etiology is that hemodynamic impairment results in decreased cerebral perfusion, exacerbated amyloid-β accumulation (Aβ) and poorer cognitive performance.ObjectiveWe aimed to determine whether patients with unilateral internal carotid artery (ICA) occlusion have less cerebral perfusion and more Aβ in the ipsilateral than in the contralateral hemisphere, and whether perfusion and Aβ are associated with cognitive functioning.MethodsWe included 20 patients (age 67.2 ± 7.0 years, 8 females, MMSE 29 [27-29]) with unilateral ICA occlusion, which underwent neuropsychological assessment and dynamic F-Florbetaben positron emission tomography (PET). Global and regional relative perfusion (R) and binding potential (BP) were obtained from the PET-images using a simplified reference tissue model. We performed Wilcoxon signed-rank tests to examine differences between hemispheres within subjects and linear regression to investigate associations with cognitive functioning.ResultsMedian global R was 0.911 (0.883-0.950) and global BP was 0.172 (0.129-0.187). R was lower in the hemisphere ipsilateral to the ICA occlusion than in the contralateral hemisphere (0.899 [0.876-0.921] versus 0.935 [0.889-0.970]). BP did not differ significantly between hemispheres (ipsilateral 0.172 [0.124-0.181] versus contralateral 0.168 [0.137-0.191]). Neither cerebral perfusion nor Aβ burden were associated with cognitive functioning.ConclusionsPatients with unilateral ICA occlusion did not have more Aβ in the ipsilateral hemisphere than in the contralateral hemisphere despite ipsilateral hypoperfusion. Perfusion and Aβ were unrelated to cognitive functioning. This indicates that cognitive impairment in patients with ICA occlusion is not due to exacerbated Aβ accumulation.

EEG biomarkers for Alzheimer's disease: A novel automated pipeline for detecting and monitoring disease progression. - Simmatis, Leif Er; Russo, Emma E; Steininger, Tayo; Riddell, Haleigh; Chen, Evelyn; Chiu, Queenny; Lin, Michelle; Oh, Donghun; Taheri, Porsha; Harmsen, Irene E; Samuel, Nardin (J Alzheimers Dis, 2025)
BackgroundAlzheimer's disease (AD) is a neurodegenerative disorder that profoundly alters brain function and organization. Currently, there is a lack of validated functional biomarkers to aid in diagnosing and classifying AD. Therefore, there is a pressing need for early, accurate, non-invasive, and accessible methods to detect and characterize disease progression. Electroencephalography (EEG) has emerged as a minimally invasive technique to quantify functional changes in neural activity associated with AD. However, challenges such as poor signal-to-noise ratio-particularly for resting-state (rsEEG) recordings-and issues with standardization have hindered its broader application.ObjectiveTo conduct a pilot analysis of our custom automated preprocessing and feature extraction pipeline to identify indicators of AD and correlates of disease progression.MethodsWe analyzed data from 36 individuals with AD and 29 healthy participants recorded using a standard 19-channel EEG and features were processed using our custom end-t-end pipeline. Various features encompassing amplitude, power, connectivity, complexity, and microstates were extracted. Unsupervised machine learning (uniform manifold approximation and projection) and supervised learning (random forest classifiers with nested cross-validation) were used to characterize the dataset and identify differences between AD and healthy groups.ResultsOur pipeline successfully detected several new and previously established EEG-based measures indicative of AD status and progression, demonstrating strong external validity.ConclusionsOur findings suggest that this automated approach provides a promising initial framework for implementing EEG biomarkers in the AD patient population, paving the way for improved diagnostic and monitoring strategies.

Factors associated with a healthy diet and willingness to change dietary behavior in older adults at increased risk of dementia. - Blotenberg, Iris; Zülke, Andrea E; Luppa, Melanie; Wittmann, Felix; Fankhänel, Thomas; Weise, Solveig; Döhring, Juliane; Escales, Catharina; Kosilek, Robert P; Michel, Irina; Brettschneider, Christian; Oey, Anke; et al. (J Alzheimers Dis, 2025)
BackgroundHealthy dietary patterns have been linked to reduced risks for cardiovascular diseases and dementia, making nutrition an essential part of a comprehensive approach for dementia prevention. Knowledge about factors associated with a healthy diet in people with increased dementia risk is scarce.ObjectiveTo analyze dietary habits and associated factors in older adults with increased dementia risk in Germany.MethodsWe used baseline-data of the AgeWell.de-trial (n = 1001, %= 52.2, M= 69.0, SD = 4.9). Nutrition was assessed using a composite score, comprising 11 components covered by national recommendations for a healthy diet (range = 0-11 points). Linear regressions assessed associations of sociodemographic, social, health-related and psychological factors with consumption of a healthy diet. Further, we assessed stages of change based on the transtheoretical model of behavior change.ResultsConsumption of a healthy diet was moderate (Median = 4, IQR = 2). Female sex (b = 0.64, 95% CI: 0.41, 0.88), higher levels of motivation for healthy eating (b = 0.22, 95% CI: 0.10, 0.34) and higher self-efficacy (b = 0.33, 95% CI: 0.20, 0.46) were linked to a healthy diet. Regarding the stages of behavior change, the majority were in the maintenance stage (45.2%), followed by the contemplation (21.5%) and precontemplation (21.2%) stages.ConclusionsResults suggest room for improvement regarding a healthy diet in our sample. Lifestyle-based interventions in older adults should be tailored towards current levels of motivation and self-efficacy of participants. Including modules targeting motivation and self-efficacy might help maximize intervention effectiveness.

Impact of obesity on neuropsychiatric symptoms in Alzheimer's disease: Insights from the ADNI cohort. - Wang, Shuoshi; Ni, Jingnian; Wei, Mingqing; Li, Ting; Shi, Jing; Tian, Jinzhou (J Alzheimers Dis, 2025)
BackgroundObesity is a major global health issue linked to increased risks of dementia, including Alzheimer's disease (AD). While the association between obesity and neuropsychiatric symptoms (NPS) in AD remains underexplored, identifying these links could aid in weight management in AD patients.ObjectiveThis study investigates the relationship between body mass index (BMI) and NPS in AD dementia patients, focusing on the potential mediating role of systemic inflammation.MethodsWe employed Generalized Additive Models (GAMs) to explore the relationship between BMI and NPS, as measured by the Neuropsychiatric Inventory Questionnaire (NPI-Q). Participants were classified into ideal, overweight, and obese groups based on WHO criteria. Longitudinal analyses assessed the trajectory of NPI-Q scores in different groups over a one-year follow-up.ResultsBMI significantly affects NPI-Q total scores and specific symptoms, including delusions, hallucinations, agitation/aggression, elation/euphoria, disinhibition, irritability/lability, aberrant motor behavior, nighttime disturbances, and appetite/eating disturbances. Obese patients exhibited higher NPI-Q total scores and greater severity in symptoms such as hallucinations, agitation/aggression, elation/euphoria, apathy/indifference, disinhibition, aberrant motor behavior, and nighttime disturbances. Additionally, CRP and complement C3 were identified as mediators in the relationship between obesity and NPS, highlighting the role of systemic inflammation.ConclusionsThis study demonstrates that obesity is associated with a heightened burden of NPS in AD dementia patients. The identification of CRP and complement C3 as mediators suggests inflammation plays a crucial role in the association between obesity and NPS. These findings underscore the importance of addressing obesity and its inflammatory consequences in managing NPS among this vulnerable population.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Body Mass Index; Cohort Studies; Female; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Obesity

Increased risk of dementia associated with herpes simplex virus infections: Evidence from a retrospective cohort study using U.S. electronic health records. - Araya, Katherine; Watson, Riley; Khanipov, Kamil; Golovko, George; Taglialatela, Giulio (J Alzheimers Dis, 2025)
BACKGROUND: Alzheimer's disease is the most common age-related dementia. Recent compelling evidence from previous retrospective electronic health record (EHRs) studies suggests that herpes simplex virus (HSV) infections may be a risk factor for developing dementia. However, no age and propensity score matched studies have been published in a United States general population cohort study to date. OBJECTIVE: We aimed to identify whether HSV infection shows a significantly increased risk of the development of dementia in a sizable and heterogeneous cohort. We investigated whether herpes simplex virus type 1 (HSV1), herpes simplex virus type 2 (HSV2), or coinfections with both serotypes pose a greater risk of developing dementia across different biological sexes and racial groups. METHODS: EHRs from patients with a history of HSV or specific serotypes (HSV1 or HSV2) infection were selected for analysis. These records were compared to a propensity-matched control group and analyzed for hazard and odds ratios through TriNetX. RESULTS: There was a significant difference in dementia incidence in the HSV-infected group versus the control. Individuals with a history of HSV, HSV1, HSV2, and coinfection all showed a significant risk of developing dementia compared to controls. Males with HSV2 are at a higher risk of dementia outcome than females with HSV2. CONCLUSIONS: While consistent with previous reports, these findings are the first to establish a higher risk of developing dementia in patients who have any HSV diagnosis using a nationwide, population-based matched cohort study in the United States.

Increased unedited Alu RNA patterns found in cortex extracellular vesicles in Alzheimer's disease resemble hippocampus vasculature Alu RNA editing patterns but not cortex Alu RNA editing patterns. - Crooke, Philip S; Tossberg, John T; Aune, Thomas M (J Alzheimers Dis, 2025)
BACKGROUND: Endogenous Alu RNAs form double-stranded RNAs recognized by double-stranded RNA sensors and activate IRF and NF-kB transcriptional paths and innate immunity. Deamination of adenosines to inosines by the ADAR family of enzymes, a process termed A-to-I editing, disrupts double-stranded RNA structure and prevents innate immune activation. Innate immune activation is observed in Alzheimer's disease, the most common form of dementia. We have previously reported loss of A-to-I editing in hippocampus vasculature, but no change in cortex or cortex vasculature, associated with Alzheimer's disease. OBJECTIVE: Here, we investigated the status of Alu RNA A-to-I editing in cortex extracellular vesicles in Alzheimer's disease. METHODS: We used existing RNA-seq data sets and the SPRINT software package to determine levels of Alu RNA A-to-I editing in cortex extracellular vesicles in Alzheimer's disease and control groups and compared these editing profiles to those found in both total cortex and hippocampus vasculature. RESULTS: We find substantial loss of Alu A-to-I editing in cortex extracellular vesicles in Alzheimer's disease. By measuring editing patterns on a gene-by-gene basis, we determined that editing patterns in cortex extracellular vesicles resemble editing patterns in hippocampus vasculature rather than total cortex. CONCLUSIONS: We conclude that hippocampus vasculature unedited Alu RNAs are packaged in extracellular vesicles, travel to the cortex, deliver their cargo and stimulate innate immunity and alter other basic biological processes contributing to Alzheimer's disease progression.

Iron chelation by oral deferoxamine treatment decreased brain iron and iron signaling proteins. - Thorwald, Max A; Sta Maria, Naomi S; Chakhoyan, Ararat; O'Day, Peggy A; Jacobs, Russell E; Zlokovic, Berislav; Finch, Caleb E (J Alzheimers Dis, 2025)
BACKGROUND: Deferoxamine (DFO) and other iron chelators are clinically used for cancer and stroke. They may also be useful for Alzheimer's disease (AD) to diminish iron from microbleeds. DFO may also stimulate antioxidant membrane repair which is impaired during AD. DFO and other chelators do enter the brain despite some contrary reports. OBJECTIVE: Low dose, oral DFO was given in lab chow to wildtype (WT) C57BL/6 mice to evaluate potential impact on iron levels, iron-signaling and storage proteins, and amyloid-β protein precursor (AβPP) and processing enzymes. Young WT mice do not have microbleeds or disrupted blood-brain barrier of AD mice. METHODS: Iron was measured by MRI and chemically after two weeks of dietary DFO. Cerebral cortex was examined for changes in iron metabolism, antioxidant signaling, and AβPP processing by western blot. RESULTS: DFO decreased brain iron 18% ( < 0.01) estimated by R2 MRI and decreased seven major proteins that mediate iron metabolism by at least 25%. The iron storage proteins ferritin light and heavy chain decreased by at least 30%. AβPP and secretase enzymes also decreased by 30%. CONCLUSIONS: WT mice respond to DFO with decreased AβPP, amyloid processing enzymes, and antioxidant repair. Potential DFO treatment for early-stage AD by DFO should consider the benefits of lowered AβPP and secretase enzymes.

Leptin, adiponectin, body mass index, and incident cognitive impairment. - Thacker, Evan L; Karki, Reena; Gabor, Rachel; Blades, Natalie J; Sawyer, Russell P; Kouambo Beckodro, Cyrille N; Preece, Quinn; Prince, Samuel; Smith, McKay M; Gillett, Sarah R; Judd, Suzanne E; Kennedy, Richard E; et al. (J Alzheimers Dis, 2025)
BackgroundDisordered metabolism affects risk for cognitive decline, Alzheimer's disease, and other dementias, likely through pathways involving adipokines.ObjectiveAnalyze incident cognitive impairment in relation to leptin, adiponectin, body mass index, and other risk factors.MethodsNested case-control study within the Reasons for Geographic and Racial Differences in Stroke (REGARDS) cohort of 30,239 adults in the US. Cases with incident cognitive impairment (n = 489) scored >1.57 SD below demographically adjusted means on ≥2 of 3 cognitive tests: word list learning, word list delayed recall, and category fluency. Cognitively intact controls (n = 583) were randomly selected within demographic strata. Leptin and adiponectin were assayed in thawed blood that had been stored at baseline.ResultsIn participants with normal weight, lower leptin was associated with higher odds of cognitive impairment. Relative to leptin = 25 ng/mL, adjusted ORs were 1.5 (95% CI: 1.2, 1.9) at leptin = 15 ng/mL, 0.8 (0.8, 0.9) at leptin = 30 ng/mL, and 0.5 (0.4, 0.8) at leptin = 45 ng/mL. In participants with obesity, higher adiponectin was associated with higher odds of cognitive impairment. Relative to adiponectin = 25 ng/mL, adjusted ORs were 0.8 (95% CI: 0.7, 1.0) at adiponectin = 15 ng/mL, 1.1 (1.0, 1.2) at adiponectin = 30 ng/mL, and 1.3 (1.0, 1.7) at adiponectin = 45 ng/mL. Associations of adipokines with cognitive impairment varied across levels of other risk factors.ConclusionsAdipokines, in concert with body mass index, play complex roles in cognitive health, with many avenues open for further investigation.

Performance of a smell identification test versus the Mini-Mental Status Exam for the detection of dementia and cognitive impairment among persons with cognitive concerns in primary care. - Luchsinger, Jose A; Teresi, Jeanne A; Valdez, Lenfis; Rosario, Dahiana; de Miguel, Maria; Taylor, Delphine; Singer, Jessica; Chang, Nancy; Fuller, William S; Boquín, Cyrus; Silver, Stephanie; Eimicke, Joseph P; et al. (J Alzheimers Dis, 2025)
BackgroundOdor identification deficits predict Alzheimer's disease (AD) in epidemiological studies.ObjectiveTo compare the accuracy of a short odor identification test with a short cognitive screening test for the detection of dementia and cognitive impairment in elderly persons with cognitive concerns.MethodsThis was a cross-sectional study of 600 participants 65 years and older, without known mild cognitive impairment (MCI) or dementia, with cognitive concerns, attending primary care practices in New York City. The odor identification test was the Brief Smell Identification Test (BSIT). The comparator test was the Mini Mental Status Exam II (MMSE). Cognitive diagnoses were made using the National Alzheimer's Coordinating Center Uniform Data set (NACC-UDS) version 3 forms with slight modifications. Test performance was compared using Receiver Operating Characteristic analyses.ResultsThe mean age was 72.65 ± 6.31 years, 73.3% were female, 63.3% were Hispanic, 13.5% non-Hispanic Black, and 20.8% non-Hispanic White; 23.5% were classified as normal cognition, 27.7% as cognitive impairment-not mild cognitive impairment (MCI), 31.2% as amnestic MCI, 5.7% as non-amnestic MCI, and 12% as dementia. The MMSE was superior to the BSIT in detecting dementia and any cognitive impairment. Combining abnormal scores in the BSIT (≤8) to MMSE (≤24) improved the MMSE's specificity and positive predictive value (PPV) in detecting cognitive impairment.ConclusionsThe MMSE was superior to the BSIT in detecting dementia and cognitive impairment in primary care but using both tests improved specificity and PPV for identifying persons with subjective complaints needing further cognitive and biomarker evaluation.

White matter lesions rather than amyloid-β burden are associated with cognitive decline in Alzheimer's disease. - Kasahara, Hiroo; Ikeda, Masaki; Makioka, Kouki; Nakamura, Takumi; Takahashi, Ryoma; Kawarabayashi, Takeshi; Sanada, Etsuko; Suto, Takayuki; Higuchi, Tetsuya; Tsushima, Yoshito; Ikeda, Yoshio (J Alzheimers Dis, 2025)
We assessed the severity of amyloid-β accumulation and white matter lesions (WML) in the brain, and their association with cognitive decline, in patients (n = 47) with Alzheimer's disease (AD). The mean cortical standardized uptake value ratio (mcSUVR) was derived from amyloid positron emission tomography, while the percentage of WML area relative to brain parenchymal area was determined using magnetic resonance imaging. Cognitive decline was positively correlated with WML severity (= 0.50, = 0.042) but not mcSUVR (Aβ accumulation). Managing vascular risk factors can prevent cognitive decline in patients with AD.

Acute Hyperglycemia Induced by Hyperglycemic Clamp Affects Plasma Amyloid-β in Type 2 Diabetes. - Rolandsson, Olov; Tornevi, Andreas; Steneberg, Pär; Edlund, Helena; Olsson, Tommy; Andreasson, Ulf; Zetterberg, Henrik; Blennow, Kaj (J Alzheimers Dis, 2024)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of cognitive symptoms and Alzheimer's disease (AD). Mis-metabolism with aggregation of amyloid-β peptides (Aβ) play a key role in AD pathophysiology. Therefore, human studies on Aβ metabolism and T2D are warranted. OBJECTIVE: The objective of this study was to examine whether acute hyperglycemia affects plasma Aβ1-40 and Aβ1-42 concentrations in individuals with T2D and matched controls. METHODS: Ten participants with T2D and 11 controls (median age, 69 years; range, 66-72 years) underwent hyperglycemic clamp and placebo clamp (saline infusion) in a randomized order, each lasting 4 hours. Aβ1-40, Aβ1-42, and insulin-degrading enzyme (IDE) plasma concentrations were measured in blood samples taken at 0 and 4 hours of each clamp. Linear mixed-effect regression models were used to evaluate the 4-hour changes in Aβ1-40 and Aβ1-42 concentrations, adjusting for body mass index, estimated glomerular filtration rate, and 4-hour change in insulin concentration. RESULTS: At baseline, Aβ1-40 and Aβ1-42 concentrations did not differ between the two groups. During the hyperglycemic clamp, Aβ decreased in the control group, compared to the placebo clamp (Aβ1-40: p = 0.034, Aβ1-42: p = 0.020), IDE increased (p = 0.016) during the hyperglycemic clamp, whereas no significant changes in either Aβ or IDE was noted in the T2D group. CONCLUSIONS: Clamp-induced hyperglycemia was associated with increased IDE levels and enhanced Aβ40 and Aβ42 clearance in controls, but not in individuals with T2D. We hypothesize that insulin-degrading enzyme was inhibited during hyperglycemic conditions in people with T2D.
Keywords: Aged; Amyloid beta-Peptides; Blood Glucose; Diabetes Mellitus, Type 2; Female; Glucose Clamp Technique; Humans; Hyperglycemia; Insulysin; Male; Peptide Fragments

Agent Orange Herbicidal Toxin-Initiation of Alzheimer-Type Neurodegeneration. - de la Monte, Suzanne M; Tong, Ming (J Alzheimers Dis, 2024)
BACKGROUND: Agent Orange (AO) is a Vietnam War-era herbicide that contains a 1 : 1 ratio of 2,4-dichlorophenoxyacetic acid (2,4-D) and 2,4,5-trichlorophenoxyacetic acid (2,4,5-T). Emerging evidence suggests that AO exposures cause toxic and degenerative pathologies that may increase the risk for Alzheimer's disease (AD). OBJECTIVE: This study investigates the effects of the two main AO constituents on key molecular and biochemical indices of AD-type neurodegeneration. METHODS: Long Evans rat frontal lobe slice cultures treated with 250μg/ml of 2,4-D, 2,4,5-T, or both (D + T) were evaluated for cytotoxicity, oxidative injury, mitochondrial function, and AD biomarker expression. RESULTS: Treatment with the AO constituents caused histopathological changes corresponding to neuronal, white matter, and endothelial cell degeneration, and molecular/biochemical abnormalities indicative of cytotoxic injury, lipid peroxidation, DNA damage, and increased immunoreactivity to activated Caspase 3, glial fibrillary acidic protein, ubiquitin, tau, paired-helical filament phosphorylated tau, AβPP, Aβ, and choline acetyltransferase. Nearly all indices of cellular injury and degeneration were more pronounced in the D + T compared with 2,4-D or 2,4,5-T treated cultures. CONCLUSIONS: Exposures to AO herbicidal chemicals damage frontal lobe brain tissue with molecular and biochemical abnormalities that mimic pathologies associated with early-stage AD-type neurodegeneration. Additional research is needed to evaluate the long-term effects of AO exposures in relation to aging and progressive neurodegeneration in Vietnam War Veterans.
Keywords: 2,4,5-Trichlorophenoxyacetic Acid; Agent Orange; Alzheimer Disease; Animals; Herbicides; Rats; Rats, Long-Evans

Altered Neuronal Activity Patterns of the Prefrontal Cortex in Alzheimer's Disease After Transcranial Alternating Current Stimulation: A Resting-State fMRI Study. - Wang, Tao; Yan, Shaozhen; Shan, Yi; Xing, Yi; Bi, Sheng; Chen, Zhigeng; Xi, Hanyu; Xue, Hanxiao; Qi, Zhigang; Tang, Yi; Lu, Jie (J Alzheimers Dis, 2024)
BACKGROUND: Transcranial alternating current stimulation (tACS) could improve cognition in patients with Alzheimer's disease (AD). However, the effects of tACS on brain activity remain unclear. OBJECTIVE: The purpose is to investigate the change in regional neuronal activity after tACS in AD patients employing resting-state functional magnetic resonance imaging (rs-fMRI). METHODS: A total of 46 patients with mild AD were enrolled. Each patient received 30 one-hour sessions of real or sham tACS for three weeks (clinical trial: NCT03920826). The fractional amplitude of low-frequency fluctuations (fALFF) and the regional homogeneity (ReHo) measured by rs-fMRI were calculated to evaluate the regional brain activity. RESULTS: Compared to baseline, AD patients in the real group exhibited increased fALFF in the left middle frontal gyrus-orbital part and right inferior frontal gyrus-orbital part, as well as increased ReHo in the left precentral gyrus and right middle frontal gyrus at the end of intervention. At the 3-month follow-up, fALFF increased in the left superior parietal lobule and right inferior temporal gyrus, as well as ReHo, in the left middle frontal gyrus and right superior medial frontal gyrus. A higher fALFF in the right lingual gyrus and ReHo in the right parahippocampal gyrus were observed in the response group than in the nonresponse group. CONCLUSIONS: The findings demonstrated the beneficial effects of tACS on the neuronal activity of the prefrontal cortex and even more extensive regions and provided a neuroimaging biomarker of treatment response in AD patients.

Alzheimer's Disease and Cognitive Decline in Patients with Cardiovascular Diseases Along the Heart-Brain Axis. - Trieu, Calvin; Van Harten, Argonde C; Leeuwis, Anna E; Exalto, Lieza G; Hooghiemstra, Astrid M; Verberk, Inge M W; Allaart, Cor P; Brunner-La Rocca, Hans-Peter; Kappelle, L Jaap; van Oostenbrugge, Robert J; Biessels, Geert-Jan; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2024)
BACKGROUND: We hypothesize that Alzheimer's disease (AD)-related pathology may accelerate cognitive decline in patients with cardiovascular diseases. OBJECTIVE: To investigate the association between blood-based biomarkers of AD, astrocyte activation, and neurodegeneration and cognitive decline. METHODS: From the multi-center Heart-Brain study, we included 412 patients with heart failure, carotid occlusive disease or vascular cognitive impairment (age:68.6±9.0) and 128 reference participants (65.7±7.5). Baseline amyloid-β42/40 (Aβ42/40), phosphorylated-tau181 (pTau181), glial fibrillary acidic protein (GFAP), and neurofilament light (NfL) were determined using SiMoA (Quanterix). Memory, attention, language, and executive functioning were evaluated (follow-up:2.1±0.3 years). We applied linear mixed models with terms for biomarker, time and biomarker*time interactions, adjusted for age, sex, education, and site, to assess associations between biomarkers and cognitive decline. RESULTS: Among patients, Aβ42/40 was not associated with cognitive performance at baseline. However, lower Aβ42/40 was associated with steeper decline in global cognition (β±SE:0.04±0.02). Higher pTau181 was associated with worse baseline performance on global cognition (-0.14±0.04) and memory (-0.31±0.09) and with steeper decline in global cognition (-0.07±0.02), memory (-0.09±0.04), attention (-0.05±0.02), and language (-0.10±0.03). Higher GFAP was associated with worse baseline performance on global cognition (-0.22±0.05), memory (-0.43±0.10), attention (-0.14±0.06), language (-0.15±0.05), and executive functioning (-0.15±0.05) and steeper decline in global cognition (-0.05±0.01). Higher NfL was associated with worse baseline performance on global cognition (-0.16±0.04), memory (-0.28±0.09), attention (-0.20±0.06), and executive functioning (-0.10±0.04), but was not associated with performance over time. In reference participants, no associations were found. CONCLUSIONS: Our findings suggest that blood-based biomarkers of AD-related pathology predict cognitive decline in patients with cardiovascular diseases.

Associations of Physical Activity Engagement with Cerebral Amyloid-β and Tau from Midlife. - Gonzales, Mitzi M; Kojis, Daniel; Spartano, Nicole L; Thibault, Emma G; DeCarli, Charles S; El Fakhri, Georges; Johnson, Keith A; Beiser, Alexa S; Seshadri, Sudha (J Alzheimers Dis, 2024)
BACKGROUND: Higher midlife physical activity engagement has been associated with lower dementia risk in late life. However, the underlying mechanisms contributing to the protective effect remain unclear. OBJECTIVE: The goal of the current study was to evaluate the associations of physical activity with cerebral amyloid-β (Aβ) and tau in a predominately middle-aged community-based cohort, as well as to explore whether the associations differ by sex or age. METHODS: Participants from the Framingham Heart Study underwent 11C-Pittsburgh Compound B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging. Total physical activity levels were evaluated by self-report using the Physical Activity Index (PAI). Cross-sectional associations between total PAI with regional Aβ and tau PET retention were evaluated using linear regression models adjusted for demographic and cardiovascular risk factors. Interactions with sex and age group were examined and stratified analyses were performed when significant. FDR-correction for multiple comparisons was applied. RESULTS: The sample included 354 participants (mean age 53±8 years, 51% female). Higher total PAI scores were associated with lower entorhinal cortex tau PET binding (β (SE) = -0.021(0.008), p = 0.049). There were significant interactions with sex. In men alone, total PAI inversely associated with entorhinal cortex (β (SE) = -0.035(0.009), p = 0.001), inferior temporal (β (SE) = -0.029(0.010), p = 0.012), and rhinal cortex tau(β (SE) = -0.033(0.010), p = 0.002). CONCLUSIONS: The results suggest that higher midlife physical activity engagement may confer resistance to tau pathology. However, the effects may vary based on sex, highlighting the importance of better understanding and tailoring lifestyle interventions to address sex disparities.

Bisecting N-Acetylglucosamine Correlates with Phospho-Tau181 in Subjective Cognitive Decline but not in Control Cases. - Egebäck Arulf, Sofia; Ziyue Zhou, Robin; Kirsebom, Bjørn-Eivind; Jejcic, Alenka; Fladby, Tormod; Winblad, Bengt; Tjernberg, Lars; Schedin-Weiss, Sophia (J Alzheimers Dis, 2024)
BACKGROUND: The N-glycan structure bisecting N-acetylglucosamine (bisecting GlcNAc) is present on several N-glycans that are elevated in Alzheimer's disease (AD), and previous studies have shown that bisecting GlcNAc levels correlate with total tau and phospho-tau181 in cerebrospinal fluid at early stages of AD. A recent population-based study showed that bisecting GlcNAc correlates with total tau also in blood and that this correlation could predict conversion to dementia. OBJECTIVE: In this study, we have further investigated how bisecting GlcNAc relates to total tau and phospho-tau 181 in cerebrospinal fluid samples from controls and cases with early cognitive deficits, stratified by amyloid/tau status and gender. METHODS: Relative levels of bisecting GlcNAc in cerebrospinal fluid were measured by an enzyme-linked lectin assay in individuals with subjective cognitive decline, mild cognitive impairment and controls from the Norwegian Dementia Disease Initiation cohort. RESULTS: As in our previous study, the correlation between bisecting GlcNAc and total tau or phospho-tau181 was particularly strong in the subjective cognitive decline group. The correlation was observed in amyloid negative and tau negative as well as amyloid positive and tau positive individuals, both in females and in males. Interestingly, among the amyloid negative and tau negative individuals, the correlation was observed in individuals with subjective cognitive decline but not in the controls. CONCLUSIONS: Thus, bisecting GlcNAc could be a biomarker for early cognitive decline.

Causal Association Between Sepsis and Neurodegenerative Diseases: A Bidirectional Two-Sample Mendelian Randomization Study. - Zeng, Youjie; Cao, Si; Pang, Ke; Tang, Juan; Lin, Guoxin (J Alzheimers Dis, 2024)
BACKGROUND: Previous observational studies suggested an association between sepsis and neurodegenerative diseases, but causality remains unclear. OBJECTIVE: Determining the causal association between sepsis and four neurodegenerative diseases (Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, and Lewy body dementia) through bidirectional two-sample Mendelian randomization (MR) analysis. METHODS: Genome-wide association study summary statistics for all traits were obtained from publicly available databases. Inverse variance weighted (IVW) was the primary method for evaluating causal associations. In addition, three additional MR methods (MR-Egger, weighted median, and maximum likelihood method) were employed to supplement IVW. Furthermore, various sensitivity tests were conducted to assess the reliability: 1) Cochrane's Q test for assessing heterogeneity; 2) MR-Egger intercept test and MR-PRESSO global test for evaluating horizontal pleiotropy; 3) leave-one-out sensitivity test for determining the stability. RESULTS: The results of IVW indicated that sepsis significantly increased the risk of Alzheimer's disease (OR = 1.11, 95% CI: 1.01-1.21, p = 0.025). In addition, three additional MR methods suggested parallel results. However, no causal effect of sepsis on the three other neurodegenerative diseases was identified. Subsequently, reverse MR analysis indicated that the four neurodegenerative diseases do not causally affect sepsis. Furthermore, sensitivity tests demonstrated the reliability of the MR analyses, suggesting no heterogeneity or horizontal pleiotropy. CONCLUSIONS: The present study contributes to a deeper comprehension of the intricate interplay between sepsis and neurodegenerative disorders, thereby offering potential avenues for the development of therapeutic agents that can effectively mitigate the multifarious complications associated with sepsis.
Keywords: Alzheimer Disease; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Neurodegenerative Diseases; Reproducibility of Results; Sepsis

Cerebrospinal Fluid Proteomics Identifies Potential Biomarkers for Early-Onset Alzheimer's Disease. - Li, Dazhi; Xie, Qiang; Xie, Jikui; Ni, Ming; Wang, Jinliang; Gao, Yuru; Wang, Yaxin; Tang, Qiqiang (J Alzheimers Dis, 2024)
BACKGROUND: Early-onset Alzheimer's disease (EOAD) exhibits a notable degree of heterogeneity as compared to late-onset Alzheimer's disease (LOAD). The proteins and pathways contributing to the pathophysiology of EOAD still need to be completed and elucidated. OBJECTIVE: Using correlation network analysis and machine learning to analyze cerebrospinal fluid (CSF) proteomics data to identify potential biomarkers and pathways associated with EOAD. METHODS: We employed mass spectrometry to conduct CSF proteomic analysis using the data-independent acquisition method in a Chinese cohort of 139 CSF samples, including 40 individuals with normal cognition (CN), 61 patients with EOAD, and 38 patients with LOAD. Correlation network analysis of differentially expressed proteins was performed to identify EOAD-associated pathways. Machine learning assisted in identifying crucial proteins differentiating EOAD. We validated the results in an Western cohort and examined the proteins expression by enzyme-linked immunosorbent assay (ELISA) in additional 9 EOAD, 9 LOAD, and 9 CN samples from our cohort. RESULTS: We quantified 2,168 CSF proteins. Following adjustment for age and sex, EOAD exhibited a significantly greater number of differentially expressed proteins than LOAD compared to CN. Additionally, our data indicates that EOAD may exhibit more pronounced synaptic dysfunction than LOAD. Three potential biomarkers for EOAD were identified: SH3BGRL3, LRP8, and LY6 H, of which SH3BGRL3 also accurately classified EOAD in the Western cohort. LY6 H reduction was confirmed via ELISA, which was consistent with our proteomic results. CONCLUSIONS: This study provides a comprehensive profile of the CSF proteome in EOAD and identifies three potential EOAD biomarker proteins.

Cognitive Outcomes in Autosomal-Dominant Alzheimer's Disease: A Comprehensive Review from a Colombian Kindred with the Presenilin-1 E280A Mutation. - Giudicessi, Averi; McDowell, Celina Pluim; Martinez, Jairo E; Baena, Ana; Vila-Castelar, Clara; Norton, Daniel; Aguirre-Acevedo, Daniel C; Tirado, Victoria; Bocanegra, Yamile; Guzmán-Vélez, Edmarie; Lopera, Francisco; Cronin-Golomb, Alice; et al. (J Alzheimers Dis, 2024)
BACKGROUND: The largest identified kindred worldwide with a single mutation causing autosomal-dominant Alzheimer's disease (ADAD) is a family from Antioquia, Colombia, carrying the Presenilin-1 (PSEN1) E280A (Paisa) mutation. The majority of mutation carriers develop dementia, typically commencing in their late 30 s, with a median onset age of 49 years. Cognitive decline is a hallmark feature. OBJECTIVE: This review synthesizes the existing literature on neuropsychological assessments in PSEN1 E280A mutation carriers throughout their lifespan. We provide a comprehensive overview of cognitive outcomes in this unique population. METHODS: We reviewed and integrated the published research, analyzing studies on neuropsychological assessments in PSEN1 E280A carriers. Our focus was on measures of verbal, semantic, episodic, and spatial memory, and encompassed other cognitive domains such as language, attention, visuospatial memory, and executive functioning. RESULTS: Verbal, semantic, episodic, and spatial memory emerged as the most sensitive indicators of preclinical changes in PSEN1 E280A carriers. Inconsistencies were noted in findings from tests assessing language, attention, visuospatial memory, and executive functioning, suggesting potential limitations in detecting early cognitive changes in PSEN1 mutation carriers. Specific cognitive tasks developed for this population proved effective but underutilized. CONCLUSIONS: The review underscores the importance of continued test development tailored to detect early cognitive changes in PSEN1 E280A carriers, potentially enhancing ADAD screening. Furthermore, investigating ADAD mutations in children may identify early changes in AD and enhance our understanding of neuropsychological functioning across the lifespan. This synthesis provides valuable insights for researchers, clinicians, and policymakers engaged in the study and management of ADAD.

Comparative Efficacy, Tolerability, and Acceptability of Donanemab, Lecanemab, Aducanumab, Melatonin, and Aerobic Exercise for a Short Time on Cognitive Function in Mild Cognitive Impairment and Mild Alzheimer's Disease - Terao, Itsuki; Kodama, Wakako (J Alzheimers Dis, 2024)
BACKGROUND: The Food and Drug Administration (FDA) has approved lecanemab and aducanumab and is reviewing donanemab, but they have questionable efficacy, serious side effects and are costly, whereas melatonin administration and aerobic exercise for a short time may overcome these problems. OBJECTIVE: We aim to compare the efficacy on cognitive function, tolerability and acceptability of melatonin administration and aerobic exercise for a short time with donanemab, lecanemab, and aducanumab in people with mild AD and MCI. METHODS: We systematically reviewed relevant randomized placebo-controlled trials (RCTs) in PubMed, the Cochrane Library, CINHAL, and ClinicalTrials.gov and performed network meta-analyses. RESULTS: The analysis included 10 randomized placebo-controlled trials with 4,599 patients. Although melatonin and aerobic exercise for a short time were significantly more effective than donanemab, lecanemab, aducanumab and placebo in the primary analysis, there was significant heterogeneity. In the sensitivity analysis excluding exercise, melatonin was significantly more effective than donanemab, lecanemab, aducanumab and placebo, with no significant heterogeneity. Aerobic exercise for a short time was significantly less acceptable than donanemab, aducanumab and placebo. Donanemab, lecanemab, and aducanumab were significantly less tolerable than placebo and donanemab and lecanemab were significantly less acceptable than placebo. CONCLUSIONS: Melatonin may be a better potential disease-modifying treatment for cognitive decline in mild AD and MCI. Aerobic exercise for a short time might also be better than donanemab, lecanemab and aducanumab if continued, as it is well tolerated and more effective, although less valid due to heterogeneity. Another limitation is the small number of participants.
Keywords: Alzheimer Disease; Antibodies, Monoclonal, Humanized; Cognition; Cognitive Dysfunction; Exercise Therapy; Humans; Melatonin; Network Meta-Analysis; Randomized Controlled Trials as Topic; Treatment Outcome

Creating an Unprotected Class: Addressing Legal Risks in the Era of Biologically-Defined Alzheimer's Disease. - Vaishnav, Neil; Gonzalez, Rosa; Karunungan, Krystal; Tyler, Ana; Zheng, William; Arias, Jalayne J (J Alzheimers Dis, 2024)
BACKGROUND: Documentation of preclinical biomarker tests for Alzheimer's disease (AD) in the medical record may expose patients to employment and insurance discrimination risks. There is a gap in research describing clinicians' approaches to documenting biomarker results. OBJECTIVE: To evaluate discrimination risks faced by patients undergoing biomarker testing for AD through a qualitative analysis of clinician documentation practices. METHODS: Semi-structured interviews using hypothetical patient scenarios. The qualitative analysis focused on interviewees' responses related to documentation and disclosure of results. RESULTS: We collected and analyzed 17 interviews with dementia experts; and identified three approaches to documenting biomarkers as: an association with active AD, noninformative, and an increased susceptibility for AD. Those who associated biomarkers with active disease were more likely to favor disclosure to employers and insurers, which could increase discrimination risks. CONCLUSIONS: This study demonstrates the variety of documentation and disclosure practices likely to emerge for preclinical AD biomarker tests and highlights a need for guidelines in this area.
Keywords: Alzheimer Disease; Biomarkers; Disclosure; Humans

The Effects of Pomegranate Seed Oil on Mild Cognitive Impairment. - Chatzikostopoulos, Thanos; Gialaouzidis, Moses; Koutoupa, Anna; Tsolaki, Magda (J Alzheimers Dis, 2024)
BACKGROUND: In recent years, there has been a growing interest, supported by many experimental and clinical studies, about the benefits of pomegranate in preventing various pathologic conditions, including brain neurodegeneration. The pomegranate seed oil (PSO) contains high levels of fatty acids that have antioxidant and anti-inflammatory properties. OBJECTIVE: Due to the lack of clinical trials, the aim of the present study was to investigate the effects of PSO on cognition of people with mild cognitive impairment (MCI). METHODS: Eighty people with the diagnosis of MCI were randomized forty to take 5 drops of PSO and follow the Mediterranean Diet (MeDi) and forty just followed MeDi. All were examined with an extensive neuropsychological assessment before and after one year of treatment. RESULTS: The results showed that the participants who took the PSO had statistically significantly better global cognition (p = 0.004), verbal episodic memory (p = 0.009), and processing and executive functions (p < 0.001) in contrast with the participants who did not take it. CONCLUSIONS: In conclusion, the PSO can be beneficial for people with MCI as it is helpful for some important cognitive domains. As PSO is a natural product that does not burden the human body, it can be used by people with MCI and be a significant and promising part of holistic approaches for the prevention of dementia.
Keywords: Biological Products; Cognition; Cognitive Dysfunction; Humans; Neuropsychological Tests; Plant Oils; Pomegranate

Elevated Risk of Dementia Diagnosis in Older Adults with Low Frequencies and Durations of Social Conversation. - Shimada, Hiroyuki; Doi, Takehiko; Tsutsumimoto, Kota; Makino, Keitaro; Harada, Kenji; Tomida, Kouki; Arai, Hidenori (J Alzheimers Dis, 2024)
BACKGROUND: Social networks and social participation have protective effects on cognitive function maintenance and Alzheimer's disease and general dementia development. OBJECTIVE: We aimed to investigate the association between conversations and dementia incidence in older adults. METHODS: This longitudinal prospective cohort study used population data from the National Center for Geriatric and Gerontology-Study of Geriatric Syndromes (NCGG-SGS) from September 2015 to February 2017. The database included 4,167 individuals in Japan aged ≥60 years who were generally healthy and without major cognitive impairment. Participants were classified into two groups according to six daily conversation measures at baseline. The conversation index was calculated as a composite score for these measures. Participants were tracked monthly over 60 months for new-onset dementia. RESULTS: Data from 2,531 participants were analyzed (72.7±6.7 years; range: 60-96 years). Dementia incidence per 1,000 person-years was 15.7 (95% confidence interval, 13.6-18.1). The Youden index determined the cut-off point for dementia incidence, with a conversation index of 16/17 points. The low conversation group included more participants with new-onset dementia. Cox proportional hazards regression crude models showed remarkable relationships between dementia onset and specific conversation measurements, including conversation index. According to the Cox regression adjusted model, the cut-off point of the conversation index showed only a remarkable relationship with dementia onset. CONCLUSIONS: Dementia risk was extensively associated with low daily conversation statuses. The assessment of conversational factors may be useful as a risk indicator for the development of Alzheimer's disease and general dementia.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Dementia; Geriatrics; Humans; Prospective Studies

Epistatic Features and Machine Learning Improve Alzheimer's Disease Risk Prediction Over Polygenic Risk Scores. - Hermes, Stephen; Cady, Janet; Armentrout, Steven; O'Connor, James; Holdaway, Sarah Carlson; Cruchaga, Carlos; Wingo, Thomas; Greytak, Ellen McRae (J Alzheimers Dis, 2024)
BACKGROUND: Polygenic risk scores (PRS) are linear combinations of genetic markers weighted by effect size that are commonly used to predict disease risk. For complex heritable diseases such as late-onset Alzheimer's disease (LOAD), PRS models fail to capture much of the heritability. Additionally, PRS models are highly dependent on the population structure of the data on which effect sizes are assessed and have poor generalizability to new data. OBJECTIVE: The goal of this study is to construct a paragenic risk score that, in addition to single genetic marker data used in PRS, incorporates epistatic interaction features and machine learning methods to predict risk for LOAD. METHODS: We construct a new state-of-the-art genetic model for risk of Alzheimer's disease. Our approach innovates over PRS models in two ways: First, by directly incorporating epistatic interactions between SNP loci using an evolutionary algorithm guided by shared pathway information; and second, by estimating risk via an ensemble of non-linear machine learning models rather than a single linear model. We compare the paragenic model to several PRS models from the literature trained on the same dataset. RESULTS: The paragenic model is significantly more accurate than the PRS models under 10-fold cross-validation, obtaining an AUC of 83% and near-clinically significant matched sensitivity/specificity of 75%. It remains significantly more accurate when evaluated on an independent holdout dataset and maintains accuracy within APOE genotype strata. CONCLUSIONS: Paragenic models show potential for improving disease risk prediction for complex heritable diseases such as LOAD over PRS models.
Keywords: Aged; Alzheimer Disease; Apolipoproteins E; Epistasis, Genetic; Female; Genetic Predisposition to Disease; Genetic Risk Score; Genome-Wide Association Study; Humans; Machine Learning; Male; Models, Genetic; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Hypertension, Cognitive Decline, and Mild Cognitive Impairment Among Diverse Hispanics/Latinos: Study of Latinos-Investigation of Neurocognitive Aging Results (SOL-INCA). - Márquez, Freddie; Tarraf, Wassim; Stickel, Ariana M; Gonzalez, Kevin A; Testai, Fernando D; Cai, Jianwen; Gallo, Linda C; Talavera, Gregory A; Daviglus, Martha L; Wassertheil-Smoller, Sylvia; DeCarli, Charles; Schneiderman, Neil; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Hypertension can have deleterious effects on cognitive function; however, few studies have examined its effects on cognition among Hispanics/Latinos. OBJECTIVE: To assess associations between hypertension status with 1) change in cognitive performance, and 2) having mild cognitive impairment (MCI) among diverse Hispanics/Latinos. METHODS: This population-based, prospective cohort, multisite study included Hispanic/Latino adults aged 45 to 72 years in enrolled in the Hispanic Community Health Study/Study of Latinos at Visit 1 (2008-2011; mean age of 63.40±8.24 years), and the Study of Latinos-Investigation of Neurocognitive Aging at Visit 2 (2016-2018), with a mean follow-up duration of 7 years (n = 6,173). Hypertension status was assessed at both visits: normotension (no hypertension), incident hypertension (only at Visit 2), and persistent hypertension (at both visits). We examined change in cognitive performance and having MCI (only assessed at Visit 2) relative to hypertension status and adjusted for demographics and cardiovascular disease risk factors. RESULTS: Compared to normotension, persistent hypertension was associated with significantly increased decline in verbal fluency (β= -0.08; CI = [-0.16;-0.01]; p < 0.05), and processing speed (β= -0.11; CI = [-0.20;-0.02]; p < 0.05). Incident hypertension was not associated with significant change in cognitive performance. Both incident (OR = 1.70; CI = [1.16;2.50]; p < 0.01) and persistent hypertension (OR = 2.13; CI = [1.57;2.88]; p < 0.001) were associated with significantly higher odds ratios of having MCI. CONCLUSIONS: These findings indicate that persistent hypertension is associated with clinical impairment and domain-specific cognitive decline in middle-aged and older Hispanics/Latinos. It underscores the importance of monitoring blood pressure in routine healthcare visits beginning at midlife in this population to reduce the burden of cognitive decline.

The Inflammation-Induced Dysregulation of Reelin Homeostasis Hypothesis of Alzheimer's Disease. - Reive, Brady S; Lau, Victor; Sánchez-Lafuente, Carla L; Henri-Bhargava, Alexandre; Kalynchuk, Lisa E; Tremblay, Marie-Ève; Caruncho, Hector J (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) accounts for most dementia cases, but we lack a complete understanding of the mechanisms responsible for the core pathology associated with the disease (e.g., amyloid plaque and neurofibrillary tangles). Inflammation has been identified as a key contributor of AD pathology, with recent evidence pointing towards Reelin dysregulation as being associated with inflammation. Here we describe Reelin signaling and outline existing research involving Reelin signaling in AD and inflammation. Research is described pertaining to the inflammatory and immunological functions of Reelin before we propose a mechanism through which inflammation renders Reelin susceptible to dysregulation resulting in the induction and exacerbation of AD pathology. Based on this hypothesis, it is predicted that disorders of both inflammation (including peripheral inflammation and neuroinflammation) and Reelin dysregulation (including disorders associated with upregulated Reelin expression and disorders of Reelin downregulation) have elevated risk of developing AD. We conclude with a description of AD risk in various disorders involving Reelin dysregulation and inflammation.
Keywords: Alzheimer Disease; Animals; Cell Adhesion Molecules, Neuronal; Extracellular Matrix Proteins; Homeostasis; Humans; Inflammation; Nerve Tissue Proteins; Reelin Protein; Serine Endopeptidases; Signal Transduction

Influence of genotype on PCSK9-lipids association in cerebrospinal fluid and serum of patients in the Alzheimer's disease continuum. - Papotti, Bianca; Palumbo, Marcella; Adorni, Maria Pia; Elviri, Lisa; Chiari, Annalisa; Tondelli, Manuela; Bedin, Roberta; Baldelli, Enrica; Lancellotti, Giulia; Lupo, Maria Giovanna; Ferri, Nicola; Bertolotti, Marco; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alterations in factors involved in cholesterol homeostasis are critical in Alzheimer's disease (AD), but the stage of occurrence, their specific association, and a possible relationship with the genotype are not clarified. OBJECTIVE: We aimed to quantify and correlate specific lipid factors in patients with different degrees of cognitive decline, namely patients with AD and patients with mild cognitive impairment due to AD (MCI-AD), carriers or non-carriers of the genotype. METHODS: We evaluated Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9), cholesterol and the oxidative metabolites 24-, 25-, 27-hydroxycholesterol (HC) in the cerebrospinal fluid (CSF) and serum of AD (n = 28) and MCI-AD (n = 27) patients. RESULTS: CSF and serum PCSK9 and lipids were similar, except for higher serum PCSK9 and triglycerides in MCI-AD compared to AD. In CSF, AD carriers showed higher PCSK9 and 24-HC (+61.3%,  = 0.027 and +32.7%,  = 0.037), compared to non-carriers. There was a negative association between CSF PCSK9 and 27-HC in AD (r = -0.444,  = 0.049) and, exclusively among AD carriers, a negative association between CSF PCSK9 and 24-HC (r = -0.786,  = 0.028). A positive correlation was observed between CSF and serum PCSK9 in AD (r = 0.520,  = 0.004), driven by carriers (r = 0.544,  = 0.038), suggesting PCSK9 exchange between brain and periphery. A positive correlation was detected between serum and CSF 27-HC (r = 0.465,  = 0.039) in AD. None of these results were found in MCI-AD patients. CONCLUSIONS: PCSK9 and 24-HC might be specific markers of ApoE4-associated lipid alterations in AD, possibly contributing to clinical progression in the AD continuum.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cholesterol; Cognitive Dysfunction; Female; Genotype; Humans; Lipids; Male; Middle Aged; Proprotein Convertase 9

An Insertion Within SIRPβ1 Shows a Dual Effect Over Alzheimer's Disease Cognitive Decline Altering the Microglial Response. - García-Alberca, José María; de Rojas, Itziar; Sanchez-Mejias, Elisabeth; Garrido-Martín, Diego; Gonzalez-Palma, Laura; Jimenez, Sebastian; Pino-Angeles, Almudena; Cruz-Gamero, Jose Manuel; Mendoza, Silvia; Alarcón-Martín, Emilio; Muñoz-Castro, Clara; Real, Luis Miguel; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Microglial dysfunction plays a causative role in Alzheimer's disease (AD) pathogenesis. Here we focus on a germline insertion/deletion variant mapping SIRPβ1, a surface receptor that triggers amyloid-β(Aβ) phagocytosis via TYROBP. OBJECTIVE: To analyze the impact of this copy-number variant in SIRPβ1 expression and how it affects AD molecular etiology. METHODS: Copy-number variant proxy rs2209313 was evaluated in GERALD and GR@ACE longitudinal series. Hippocampal specimens of genotyped AD patients were also examined. SIRPβ1 isoform-specific phagocytosis assays were performed in HEK393T cells. RESULTS: The insertion alters the SIRPβ1 protein isoform landscape compromising its ability to bind oligomeric Aβ and its affinity for TYROBP. SIRPβ1 Dup/Dup patients with mild cognitive impairment show an increased cerebrospinal fluid t-Tau/Aβ ratio (p = 0.018) and a higher risk to develop AD (OR = 1.678, p = 0.018). MRIs showed that Dup/Dup patients exhibited a worse initial response to AD. At the moment of diagnosis, all patients showed equivalent Mini-Mental State Examination scores. However, AD patients with the duplication had less hippocampal degeneration (p < 0.001) and fewer white matter hyperintensities. In contrast, longitudinal studies indicate that patients bearing the duplication allele show a slower cognitive decline (p = 0.013). Transcriptional analysis also shows that the SIRPβ1 duplication allele correlates with higher TREM2 expression and an increased microglial activation. CONCLUSIONS: The SIRPβ1 internal duplication has opposite effects over MCI-to-Dementia conversion risk and AD progression, affecting microglial response to Aβ. Given the pharmacological approaches focused on the TREM2-TYROBP axis, we believe that SIRPβ1 structural variant might be considered as a potential modulator of this causative pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Humans; Microglia; Phagocytosis; Receptors, Cell Surface

Investigating the efficacy of ergothioneine to delay cognitive decline in mild cognitively impaired subjects: A pilot study. - Yau, Yu Fung; Cheah, Irwin K; Mahendran, Rathi; Tang, Richard My; Chua, Ru Yuan; Goh, Rachel E S; Feng, Lei; Li, Jialiang; Kua, Ee Heok; Chen, Christopher; Halliwell, Barry (J Alzheimers Dis, 2024)
BACKGROUND: Dementia, particularly Alzheimer's disease, is a major healthcare challenge in ageing societies. OBJECTIVE: This study aimed to investigate the efficacy and safety of a dietary compound, ergothioneine, in delaying cognitive decline in older individuals. METHODS: Nineteen subjects aged 60 or above with mild cognitive impairment were recruited for this double-blinded, randomized, and placebo-controlled study (ClinicalTrials.gov identifier: NCT03641404, registration date: 19/08/2018). Subjects received either ergothioneine (25 mg per capsule) or a placebo, taken 3 times a week for one year. The whole blood profile, markers of renal and liver functions, neurocognitive performance, plasma levels of ergothioneine and its metabolites, and plasma biomarkers related to neurodegeneration were measured across the study. RESULTS: Ergothioneine intake did not alter clinical safety markers (blood counts, kidney and liver function) throughout the study, further validating its safety for human consumption. Subjects receiving ergothioneine demonstrated improved performance in assessment of learning ability and stabilized plasma levels of neurofilament light chain, compared with the placebo group, which saw no improvement in cognitive assessments and a significant increase in neurofilament light chain levels. CONCLUSIONS: Prolonged intake of ergothioneine showed no toxicity in elderly people. Enhanced Rey Auditory Verbal Learning Test performance and stabilized neurofilament light chain levels suggest improvements in memory and learning abilities and a deceleration of neuronal damage, respectively. Our results add to existing data that ergothioneine is safe for extended consumption and may hold the potential to delay cognitive decline in elderly adults.

Long Non-Coding RNA Profile in Genetic Symptomatic and Presymptomatic Frontotemporal Dementia: A GENFI Study. - Serpente, Maria; Fenoglio, Chiara; Arcaro, Marina; Carandini, Tiziana; Sacchi, Luca; Pintus, Manuela; Rotondo, Emanuela; Borracci, Vittoria; Ghezzi, Laura; Bouzigues, Arabella; Russell, Lucy L; Foster, Phoebe H; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Long non-coding RNAs (lncRNAs) play crucial roles in gene regulation and are implicated in neurodegenerative diseases, including frontotemporal dementia (FTD). However, their expression patterns and potential as biomarkers in genetic FTD involving Chromosome 9 Open Reading Frame (C9ORF72), Microtubule Associated Protein Tau (MAPT), and Progranulin (GRN) genes are not well understood. OBJECTIVE: This study aimed to profile the expression levels of lncRNAs in peripheral blood mononuclear cells collected within the GENetic Frontotemporal dementia Initiative (GENFI). METHODS: Fifty-three lncRNAs were analyzed with the OpenArray Custom panel, in 131 patients with mutations in C9ORF72, MAPT, and GRN, including 68 symptomatic mutation carriers (SMC) and 63 presymptomatic mutation carriers (PMC), compared with 40 non-carrier controls (NC). RESULTS: Thirty-eight lncRNAs were detectable; the relative expression of NEAT1 and NORAD was significantly higher in C9ORF72 SMC as compared with NC. GAS5 expression was instead significantly lower in the GRN group versus NC. MAPT carriers showed no significant deregulations. No significant differences were observed in PMC. Disease duration did not correlate with lncRNA expression. CONCLUSIONS: NEAT1 and NORAD are upregulated in C9ORF72 SMC and GAS5 levels are downregulated in GRN SMC, underlining lncRNAs' relevance in FTD and their potential for biomarker development. Further validation and mechanistic studies are crucial for clinical implications.

Markers of amyloid-β deposition and burden of enlarged perivascular spaces in patients with cognitive impairment and small vessel disease. - Costa, Ana Sofia; Exalto, Lieza G; van der Flier, Wiesje M; Teunissen, Charlotte E; Barkhof, Frederik; Kuijf, Hugo J; Biessels, Geert Jan (J Alzheimers Dis, 2024)
MRI-visible enlarged perivascular spaces (EPVS) are common in patients with cognitive impairment and possibly linked to Alzheimer's disease (AD) and cerebral amyloid angiopathy (CAA). In a study of memory clinic patients (n = 450; mean age 66.5 ± 7.45, 45.8% female), we investigated CSF amyloid-β (Aβ) (AD biomarker) and strictly lobar microbleeds (CAA marker) in relation to centrum semiovale EPVS (CSO-EPVS). Age-controlled analyses showed that severe CSO-EPVS associated with Aβ status (odds ratio [OR] = 1.51, 95%CI = 1.02-2.24), but not strictly lobar microbleeds (OR = 1.39, 95%CI = 0.92-2.11), with no significant Aβ status and microbleeds interaction. This implies that in this setting, severe CSO-EPVS is not a specific indicator of CAA.

Memory consolidation, temporal and parietal atrophy, and metabolism in amyloid-β positive and negative mild cognitive impairment. - Keith, Cierra M; Haut, Marc W; Vieira Ligo Teixeira, Camila; Mehta, Rashi I; Phelps, Holly; Ward, Melanie; Miller, Mark; Navia, R Osvaldo; Coleman, Michelle M; Marano, Gary; Wang, Xiaofei; Pockl, Stephanie; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is classically characterized by alterations in memory consolidation. With the advent of diagnostic biomarkers, some patients clinically diagnosed with AD display biomarkers inconsistent with the diagnosis. OBJECTIVE: We aimed to explore differences in memory consolidation and neurodegeneration of the temporal and parietal lobes as a function of amyloid-β status in amnestic mild cognitive impairment (aMCI). METHODS: We examined differences in memory consolidation and neurodegeneration between patients diagnosed with amyloid-β positive aMCI (Aβ+ N = 78), amyloid-β negative aMCI (Aβ- N = 48), and healthy participants (HP; N = 41), within a well-characterized clinical cohort. RESULTS: Aβ+ exhibited more pronounced consolidation impairments compared to Aβ-, while Aβ- faced more consolidation challenges than HP. Both Aβ+ and Aβ- were similar in hippocampal volume and entorhinal thickness, but Aβ+ had thinner inferior parietal cortex than Aβ-. Using F-fluoro-deoxyglucose-positron emission tomography, metabolism in both temporal and parietal regions was lower in Aβ+ relative to Aβ-. CONCLUSIONS: These findings suggest pathologies other than AD likely contribute to memory consolidation difficulties in aMCI, and neurodegeneration of the parietal cortex in combination with hypometabolism may contribute to more pronounced consolidation problems in Aβ+.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Atrophy; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Memory Consolidation; Middle Aged; Neuropsychological Tests; Parietal Lobe; Positron-Emission Tomography; Temporal Lobe

Mendelian Randomization of Blood Metabolites Suggests Circulating Glutamine Protects Against Late-Onset Alzheimer's Disease. - Ramadan, Ferris A; Arani, Gayatri; Jafri, Ayan; Thompson, Tingting; Bland, Victoria L; Renquist, Benjamin; Raichlen, David A; Alexander, Gene E; Klimentidis, Yann C (J Alzheimers Dis, 2024)
BACKGROUND: Late-onset Alzheimer's disease (LOAD) represents a growing health burden. Previous studies suggest that blood metabolite levels influence risk of LOAD. OBJECTIVE: We used a genetics-based study design which may overcome limitations of other epidemiological studies to assess the influence of metabolite levels on LOAD risk. METHODS: We applied Mendelian randomization (MR) to evaluate bi-directional causal effects using summary statistics from the largest genome-wide association studies (GWAS) of 249 blood metabolites (n = 115,082) and GWAS of LOAD (ncase = 21,982, ncontrol = 41,944). RESULTS: MR analysis of metabolites as exposures revealed a negative association of genetically-predicted glutamine levels with LOAD (Odds Ratio (OR) = 0.83, 95% CI = 0.73, 0.92) that was consistent in multiple sensitivity analyses. We also identified a positive association of genetically-predicted free cholesterol levels in small LDL (OR = 1.79, 95% CI = 1.36, 2.22) on LOAD. Using genetically-predicted LOAD as the exposure, we identified associations with phospholipids to total lipids ratio in large LDL (OR = 0.96, 95% CI = 0.94, 0.98), but not with glutamine, suggesting that the relationship between glutamine and LOAD is unidirectional. CONCLUSIONS: Our findings support previous evidence that higher circulating levels of glutamine may be a target for protection against LOAD.

Pharmacodynamic and Clinical Effects of Ginkgo Biloba Extract EGb 761 and Its Phytochemical Components in Alzheimer's Disease. - Morató, Xavier; Tartari, Juan Pablo; Pytel, Vanesa; Boada, Merce (J Alzheimers Dis, 2024)
Extracts made from plants are complex mixtures of substances with varying compositions depending on the plant material and method of manufacture. This complexity makes it difficult for scientists and clinicians to interpret findings from pharmacological and clinical research. We performed a narrative review summarizing information on ginkgo biloba leaf extract, its composition, pharmacological data and clinical evidence supporting its administration for the treatment of Alzheimer's disease (AD). Medicinal products containing ginkgo biloba leaf extract which are manufactured in compliance with the requirements of the European Pharmacopoeia are approved as medicinal products for the treatment of dementia and related conditions by drug regulatory agencies in Europe, Asia and South America. As multicomponent mixtures, they may affect various targets in the pathogenesis of AD, the most common form of dementia. Pharmacodynamic studies demonstrate the effects of EGb 761 and individual constituents on various pathophysiological features of experimentally induced cognitive impairment and neurodegeneration that could contribute to its clinical efficacy. The safety and efficacy in the treatment of AD and cognitive decline has been studied in randomized, placebo-controlled clinical trials. Most of the studies that investigate the effects of ginkgo biloba extract (GbE) used the special extract EGb 761, which makes it the best-researched plant preparation worldwide. It is therefore the only herbal alternative to standard-of-care anti-dementia drugs. However, the mechanism of action has not been fully elucidated yet, and the clinical studies in AD show heterogeneity.
Keywords: Alzheimer Disease; Animals; Ginkgo biloba; Ginkgo Extract; Humans; Phytotherapy; Plant Extracts

Pharmacologic and Nutritional Interventions for Early Alzheimer's Disease: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials. - Zeng, Baoqi; Tang, Chunbian; Wang, Junjian; Yang, Qingqing; Ren, Qingcuo; Liu, Xiaozhi (J Alzheimers Dis, 2024)
BACKGROUND: Early intervention is essential for meaningful disease modification in Alzheimer's disease (AD). OBJECTIVE: We aimed to determine the efficacy and safety of pharmacologic and nutritional interventions for early AD. METHODS: PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov were searched from database inception until 1 September 2023. We included randomized controlled trials that evaluated the efficacy of interventions in early AD. Only interventions that demonstrated efficacy compared to placebo were included in the network meta-analysis (NMA). Then we performed frequentist fixed-effects NMA to rank the interventions. GRADE criteria were used to evaluate the level of evidence. RESULTS: Fifty-eight trials including a total of 33,864 participants and 48 interventions were eligible for inclusion. Among the 48 interventions analyzed, only 6 (12.5%) treatments- ranging from low to high certainty- showed significant improvement in cognitive decline compared to placebo. High certainty evidence indicated that donanemab (standardized mean difference [SMD] -0.239, 95% confidence interval [CI] -0.343 to -0.134) and lecanemab (SMD -0.194, 95% CI -0.279 to -0.108) moderately slowed the clinical progression in patients with amyloid pathology. Additionally, methylphenidate, donepezil, LipiDiDiet, and aducanumab with low certainty showed significant improvement in cognitive decline compared to placebo. However, there was no significant difference in serious adverse events as reported between the six interventions and placebo. CONCLUSIONS: Only 12.5% of interventions studied demonstrated efficacy in reducing cognitive impairment in early AD. Donanemab and lecanemab have the potential to moderately slow the clinical progression in patients with amyloid pathology. Further evidence is required for early intervention in AD.
Keywords: Alzheimer Disease; Humans; Network Meta-Analysis; Randomized Controlled Trials as Topic

Quantitative Metabolomic Analysis of the Rat Hippocampus: Effects of Age and of the Development of Alzheimer's Disease-Like Pathology. - Snytnikova, Olga; Telegina, Darya; Savina, Ekaterina; Tsentalovich, Yuri; Kolosova, Nataliya (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is the most common type of dementia in the elderly. Incomplete knowledge about the pathogenesis of this disease determines the absence of medications for the treatment of AD today. Animal models can provide the necessary knowledge to understand the mechanisms of biochemical processes occurring in the body in health and disease. OBJECTIVE: To identify the most promising metabolomic predictors and biomarkers reflecting metabolic disorders in the development of AD signs. METHODS: High resolution 1H NMR spectroscopy was used for quantitative metabolomic profiling of the hippocampus of OXYS rats, an animal model of sporadic AD, which demonstrates key characteristics of this disease. Animals were examined during several key periods: 20 days group corresponds to the "preclinical" period preceding the development of AD signs, during their manifestation (3 months), and active progression (18 months). Wistar rats of the same age were used as control. RESULTS: Ranges of variation and mean concentrations were established for 59 brain metabolites. The main metabolic patterns during aging, which are involved in energy metabolism pathways and metabolic shifts of neurotransmitters, have been established. Of particular note is the significant increase of scyllo-inositol and decrease of hypotaurine in the hippocampus of OXYS rats as compared to Wistars for all studied age groups. CONCLUSIONS: We suggest that the accumulation of scyllo-inositol and the reduction of hypotaurine in the brain, even at an early age, can be considered as predictors and potential biomarkers of the development of AD signs in OXYS rats and, probably, in humans.
Keywords: Aging; Alzheimer Disease; Animals; Disease Models, Animal; Hippocampus; Inositol; Magnetic Resonance Spectroscopy; Male; Metabolomics; Proton Magnetic Resonance Spectroscopy; Rats; Rats, Wistar

The RESIST Study: Examining Cognitive Change in Rheumatoid Arthritis Patients with Mild Cognitive Impairment Being Treated with a TNF-Inhibitor Compared to a Conventional Synthetic Disease-Modifying Anti-Rheumatic Drug. - Marr, Calum; McDowell, Bethany; Holmes, Clive; Edwards, Christopher J; Cardwell, Christopher; McHenry, Michelle; Meenagh, Gary; Teeling, Jessica L; McGuinness, Bernadette (J Alzheimers Dis, 2024)
BACKGROUND: Evidence suggests that TNF inhibitors (TNFi) used to treat rheumatoid arthritis (RA) may protect against Alzheimer's disease progression by reducing inflammation. OBJECTIVE: To investigate whether RA patients with mild cognitive impairment (MCI) being treated with a TNFi show slower cognitive decline than those being treated with a conventional synthetic disease-modifying anti-rheumatic drug (csDMARD). METHODS: 251 participants with RA and MCI taking either a csDMARD (N = 157) or a TNFi (N = 94) completed cognitive assessments at baseline and 6-month intervals for 18 months. It was hypothesized that those taking TNFis would show less decline on the primary outcome of Free and Cued Selective Reminding Test with Immediate Recall (FCSRT-IR) and the secondary outcome of Montreal Cognitive Assessment (MoCA). RESULTS: No significant changes in FCSRT-IR scores were observed in either treatment group. There was no significant difference in FCSRT-IR between treatment groups at 18 months after adjusting for baseline (mean difference = 0.5, 95% CI = -1.3, 2.3). There was also no difference in MoCA score (mean difference = 0.4, 95% CI = -0.4, 1.3). CONCLUSIONS: There was no cognitive decline in participants with MCI being treated with TNFis and csDMARDs, raising the possibility both classes of drug may be protective. Future studies should consider whether controlling inflammatory diseases using any approach is more important than a specific therapeutic intervention.
Keywords: Aged; Antirheumatic Agents; Arthritis, Rheumatoid; Cognitive Dysfunction; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Neuropsychological Tests; Tumor Necrosis Factor Inhibitors; Tumor Necrosis Factor-alpha

RNA Analysis of Circulating Leukocytes in Patients with Alzheimer's Disease. - Okinaka, Yuka; Shinagawa, Yoshiyuki; Claussen, Carsten; Gul, Sheraz; Matsui, Ikuko; Matsui, Yutaka; Taguchi, Akihiko (J Alzheimers Dis, 2024)
BACKGROUND: One of the key symptoms of Alzheimer's disease (AD) is the impairment of short-term memory. Hippocampal neurogenesis is essential for short-term memory and is known to decrease in patients with AD. Impaired short-term memory and impaired neurogenesis are observed in aged mice alongside changes in RNA expression of gap junction and metabolism-related genes in circulating leukocytes. Moreover, after penetrating the blood-brain barrier via the SDF1/CXCR4 axis, circulating leukocytes directly interact with hippocampal neuronal stem cells via gap junctions. OBJECTIVE: Evaluation of RNA expression profiles in circulating leukocytes in patients with AD. METHODS: Patients with AD (MMSE≧23, n = 10) and age-matched controls (MMSE≧28, n = 10) were enrolled into this study. RNA expression profiles of gap junction and metabolism-related genes in circulating leukocytes were compared between the groups (jRCT: 1050210166). RESULTS: The ratios of gap junction and metabolism-related genes were significantly different between patients with AD and age-matched controls. However, due to large inter-individual variations, there were no statistically significant differences in the level of single RNA expression between these groups. CONCLUSIONS: Our findings suggest a potential connection between the presence of circulating leukocytes and the process of hippocampal neurogenesis in individuals with AD. Analyzing RNA in circulating leukocytes holds promise as a means to offer novel insights into the pathology of AD, distinct from conventional markers.

Serial Cerebrospinal Fluid Sampling Reveals Trajectories of Potential Synaptic Biomarkers in Early Stages of Alzheimer's Disease. - Duits, Flora H; Nilsson, Johanna; Zetterberg, Henrik; Blennow, Kaj; van der Flier, Wiesje M; Teunissen, Charlotte E; Brinkmalm, Ann (J Alzheimers Dis, 2024)
BACKGROUND: Synaptic dysfunction is closely associated with cognitive function in Alzheimer's disease (AD), and is present already in an early stage of the disease. OBJECTIVE: Using serial cerebrospinal fluid (CSF) sampling, we aimed to investigate slopes of CSF synaptic proteins, and their relation with cognition along the AD continuum. METHODS: We included subjects with subjective cognitive decline (SCD) or mild cognitive impairment (MCI) (n = 50 amyloid-β+ [A +], n = 50 A-) and 50 patients with AD dementia from the Amsterdam dementia cohort, with CSF at two time points (median[IQR] 2.1[1.4-2.7] years). We analyzed 17 synaptic proteins and neurofilament light (NfL). Using linear mixed models we assessed trajectories of protein levels, and associations with cognitive decline (repeated Mini-Mental State Examination). We used Cox regression models to assess predictive value of protein levels for progression to AD dementia. RESULTS: At baseline most proteins showed increased levels in AD dementia compared to the other groups. In contrast NPTX2 levels were lower in AD dementia. Higher baseline levels of SNAP25, β-syn, and 14-3-3 proteins were associated with faster cognitive decline (St.B[SE] -0.27[0.12] to -0.61[0.12]). Longitudinal analyses showed that SYT1 and NPTX levels decreased over time in AD dementia (st.B[SE] -0.10[0.04] to -0.15[0.05]) and SCD/MCI-A+ (St.B[SE] -0.07[0.03] to -0.12[0.03]), but not in SCD/MCI-A- (pinteraction < 0.05). Increase over time in NfL levels was associated with faster cognitive decline in AD dementia (St.B[SE] -1.75[0.58]), but not in the other groups (pinteraction < 0.05). CONCLUSIONS: CSF synaptic proteins showed different slopes over time, suggesting complex synaptic dynamics. High levels of especially SNAP-25 may have value for prediction of cognitive decline in early AD stages, while increase in NfL over time correlates better with cognitive decline in later stages.

Small RNA Profiles of Brain Tissue-Derived Extracellular Vesicles in Alzheimer's Disease. - Huang, Yiyao; Driedonks, Tom A P; Cheng, Lesley; Turchinovich, Andrey; Pletniková, Olga; Redding-Ochoa, Javier; Troncoso, Juan C; Hill, Andrew F; Mahairaki, Vasiliki; Zheng, Lei; Witwer, Kenneth W (J Alzheimers Dis, 2024)
BACKGROUND: Extracellular vesicles (EVs) and non-coding RNAs (ncRNAs) are emerging contributors to Alzheimer's disease (AD) pathophysiology. Differential abundance of ncRNAs carried by EVs may provide valuable insights into underlying disease mechanisms. Brain tissue-derived EVs (bdEVs) are particularly relevant, as they may offer valuable insights about the tissue of origin. However, there is limited research on diverse ncRNA species in bdEVs in AD. OBJECTIVE: This study explored whether the non-coding RNA composition of EVs isolated from post-mortem brain tissue is related to AD pathogenesis. METHODS: bdEVs from age-matched late-stage AD patients (n = 23) and controls (n = 10) that had been separated and characterized in our previous study were used for RNA extraction, small RNA sequencing, and qPCR verification. RESULTS: Significant differences of non-coding RNAs between AD and controls were found, especially for miRNAs and tRNAs. AD pathology-related miRNA and tRNA differences of bdEVs partially matched expression differences in source brain tissues. AD pathology had a more prominent association than biological sex with bdEV miRNA and tRNA components in late-stage AD brains. CONCLUSIONS: Our study provides further evidence that EV non-coding RNAs from human brain tissue, including but not limited to miRNAs, may be altered and contribute to AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Extracellular Vesicles; Female; Humans; Male; MicroRNAs; RNA, Small Untranslated; RNA, Transfer; RNA, Untranslated

Small Vessel Disease Burden Predicts Incident Dementia and Poor Functional Outcome in Independent Outpatients. - Kitagawa, Kazuo; Toi, Sono; Hosoya, Megumi; Seki, Misa; Yamagishi, Sae; Hoshino, Takao; Yoshizawa, Hiroshi (J Alzheimers Dis, 2024)
BACKGROUND: Total small vessel disease (SVD) score is used to measure the burden of SVD. OBJECTIVE: This study aimed to clarify the predictive value of total SVD score for incident dementia and functional outcomes in independent outpatients with vascular risk factors. METHODS: We derived data from a Japanese cohort in which patients underwent magnetic resonance imaging and cognitive examinations. They were followed up until March 2023. The primary outcomes was dementia. Secondary outcome was functional outcomes. We measured a modified Rankin scale (mRS) score at the last visit and defined poor functional outcomes as mRS score ≥3. RESULTS: After excluding those with a mRS score ≥2, Mini-Mental State Examination score in Japanese version < 24, and missing T2* images, 692 patients were included. During a median follow-up period of 4.6 years, dementia occurred in 31 patients. In multivariate analysis, the score 4 group showed a significantly higher risk of incident dementia than the score 0-3 groups (adjusted hazard ratio, 6.25; 95% CI, 1.83-21.40, p = 0.003). The total SVD score was also independently related to poor functional outcome. CONCLUSIONS: The total SVD score of 4, and ≥1 could predict dementia and poor functional outcomes, respectively. Our results suggest intensive management of patients with SVD to prevent dementia and to maintain independent activities of daily living.

Social Activity and Cognitive Decline in Older Residents of Long-Term Care Facilities: A Cohort Study. - Angevaare, Milou J; Pieters, Jack A; Twisk, Jos W R; Van Hout, Hein P J (J Alzheimers Dis, 2024)
BACKGROUND: Cognitive decline is a major reason for dependence and resource use in long-term care. OBJECTIVE: We explored whether social activities may prevent cognitive decline of older residents of long-term care facilities. METHODS: In a routine care cohort, 3,603 residents of long-term care facilities were assessed on average 4.4 times using the interRAI-Long-Term-Care-Facilities instrument which includes frequency of participation in social activities of long standing interest over the last 30 days and the Cognitive Performance Scale. Linear mixed models repeated measures analyses were performed corrected for age, sex, physical activity, Activities of Daily Living, mood, and health indicators. RESULTS: Social activity was associated with cognitive preservation over time. This association was stronger in those with no or mild cognitive impairment at baseline, relative to those with moderate to severe impairment. Participation in specific social activities such as conversing and helping others showed a similar positive association. The relation between social activity and cognitive impairment appeared to be bi-directional. CONCLUSIONS: The protective effects of social activity offer a window of opportunity to preserve cognitive functioning in long-term care residents.

Space-Like Irradiation Exacerbated Cognitive Deficits and Amyloid Pathology in CRND8 Mouse Model of Alzheimer's Disease. - Wang, Wenzhang; Zhao, Fanpeng; Torres, Sandy; Harris, Peggy L R; Wang, Xinglong; Peng, Lihua; Siedlak, Sandra L; Zhu, Xiongwei (J Alzheimers Dis, 2024)
BACKGROUND: Space radiation was linked to neurological damage and behavioral deficits which raised concerns of increased degenerative risk on the brain and development of Alzheimer's disease following space travel. OBJECTIVE: In this study, we investigated the effects of irradiation by 56Fe and 28Si in CRND8 mice, an Alzheimer's disease mouse model. METHODS: Six-month-old CRND8 mice were exposed to whole body irradiation by 56Fe and 28Si at 0.5 Gy and 2 Gy doses. Behavior tests were administered 1-month to 3-months post-irradiation. Amyloid deposition and other pathological changes were analyzed 3-months and/or 6-months post-irradiatio. RESULTS: The Novel Object Recognition test showed some decline in 8-month-old mice compared to non-irradiated CRND8 mice. Male mice also showed a loss of freezing behavior in the fear conditioning contextual test following irradiation. Golgi staining revealed a loss of spines in hippocampal neurons after irradiation. Total amyloid immunohistochemistry showed a robust increase in 3-months post-irradiation 56Fe groups which became normalized to non-irradiated group by 6-months post-irradiation. However, 2 Gy 28Si caused a trend towards increased plaque load at 3-months post-irradiation which became significant at 6-months post irradiation only in male CRND8 mice. While 0.5 Gy Fe did not induce obvious changes in the total number of iba-1 positive microglia, more hippocampal microglia were found to express PCNA after 0.5 Gy Fe treatment, suggesting potential involvement of microglial dysfunction. CONCLUSIONS: Overall, our study provides new evidence of gender-specific and ion-dependent effects of space radiation on cognition and amyloid pathology in AD models.

Symptomatic Clusters Related to Amyloid Positivity in Cognitively Unimpaired Individuals. - Sannemann, Lena; Bartels, Claudia; Brosseron, Frederic; Buerger, Katharina; Fliessbach, Klaus; Freiesleben, Silka Dawn; Frommann, Ingo; Glanz, Wenzel; Heneka, Michael T; Janowitz, Daniel; Kilimann, Ingo; Kleineidam, Luca; et al. (J Alzheimers Dis, 2024)
BACKGROUND: The NIA-AA Research Framework on Alzheimer's disease (AD) proposes a transitional stage (stage 2) characterized by subtle cognitive decline, subjective cognitive decline (SCD) and mild neurobehavioral symptoms (NPS). OBJECTIVE: To identify participant clusters based on stage 2 features and assess their association with amyloid positivity in cognitively unimpaired individuals. METHODS: We included baseline data of N = 338 cognitively unimpaired participants from the DELCODE cohort with data on cerebrospinal fluid biomarkers for AD. Classification into the AD continuum (i.e., amyloid positivity, A+) was based on Aβ42/40 status. Neuropsychological test data were used to assess subtle objective cognitive dysfunction (OBJ), the subjective cognitive decline interview (SCD-I) was used to detect SCD, and the Neuropsychiatric Inventory Questionnaire (NPI-Q) was used to assess NPS. A two-step cluster analysis was carried out and differences in AD biomarkers between clusters were analyzed. RESULTS: We identified three distinct participant clusters based on presented symptoms. The highest rate of A+ participants (47.6% ) was found in a cluster characterized by both OBJ and SCD. A cluster of participants that presented with SCD and NPS (A+:26.6% ) and a cluster of participants with overall few symptoms (A+:19.7% ) showed amyloid positivity in a range that was not higher than the expected A+ rate for the age group. Across the full sample, participants with a combination of SCD and OBJ in the memory domain showed a lower Aβ42/ptau181 ratio compared to those with neither SCD nor OBJ. CONCLUSIONS: The cluster characterized by participants with OBJ and concomitant SCD was enriched for amyloid pathology.

A systematic review of lifestyle-based interventions for managing Alzheimer's disease: Insights from randomized controlled trials. - Martínez-López, Sara; Tabone, Mariangela; Clemente-Velasco, Sara; González-Soltero, Maria Del Rocío; Bailén, María; de Lucas, Beatriz; Bressa, Carlo; Domínguez-Balmaseda, Diego; Marín-Muñoz, Juan; Antúnez, Carmen; Gálvez, Beatriz G; Larrosa, Mar (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) presents a significant challenge in healthcare, prompting exploration into non-pharmacological interventions to complement traditional treatments. OBJECTIVE: This systematic review explores the efficacy of lifestyle-based interventions in managing AD. METHODS: A comprehensive literature search was conducted in PubMed, Web of Science, and Scopus between 2018 and 2023, selecting randomized controlled trials examining factors such as exercise, diet, stress, and cognitive training in AD patients. RESULTS: The review revealed physical exercise as the predominant non-pharmacological intervention, accompanied by dietary modifications, cognitive training, and therapies such as mindfulness and music. While exercise demonstrated improvements in quality of life, its cognitive benefits were limited. Modified diets, such as Atkins and ketogenic, displayed inconsistent effects on cognitive function but influenced other health-related parameters. Additionally, probiotic therapy and novel cognitive training technologies were explored. CONCLUSIONS: Despite some interventions showing promise in enhancing cognitive function and slowing disease progression, uncertainties remain regarding the dose-response relationship, underlying mechanisms, and potential synergistic effects. Moreover, consideration of genetic and sex-based disparities is warranted. This synthesis underscores the need for further research to elucidate the nuances of non-pharmacological interventions in managing AD effectively. PROSPERO REGISTRATION NUMBER: CRD42023432823.
Keywords: Alzheimer Disease; Exercise; Humans; Life Style; Quality of Life; Randomized Controlled Trials as Topic

Targeting Caspases 3/6 and Cathepsins L/B May Decrease Laminopathy-Induced Apoptosis in Alzheimer's Disease. - Rustamzadeh, Auob; Tafakhori, Abbas; Ariaei, Armin; Heydari, Mahdi; Shah-Abadi, Mehran Ebrahimi; Seif, Farhad (J Alzheimers Dis, 2024)
BACKGROUND: Laminopathy is a pathological manifestation observed in Alzheimer's disease (AD), leading to neuronal apoptosis. OBJECTIVE: Our objective was to assess inhibitors of enzymes involved in laminopathy. METHODS: The mRNA expression of the cathepsins L and B, caspases 3 and 6, lamins b1 and b2, granzymes A and B, and lamins A and C were extracted and analyzed from GSE5281 and GSE28146 datasets. A total of 145 ligands were selected for molecular docking. Subsequently, 10 ns and 100 ns atomistic molecular dynamics (MD) and Martini 3 were performed with NAMD for two selected ligands (PubChem id: 608841 and ChEMBL id: 550872). RESULTS: The mRNA expression level highlighted caspase 6 and lamin A/C upregulation in the hippocampus of the AD samples, in contrast to cathepsin B, lamin b2, and caspase 3. Moreover, there was a strong correlation between the expression level of cathepsin B, lamin A/C, and caspase 6 in the AD group. The MD results suggested molecule with ChEMBL id of 550872 had higher free binding energy, while in longer simulation the molecule with PubChem id of 608841 was suggested to be more stable in complex with the receptor. CONCLUSIONS: Our findings suggest that lamins A/C, cathepsins B/L, caspase 6, and lamin B2 are associated with laminopathy as potential factors contributing to apoptosis in AD. We propose that simultaneous inhibition of caspases 6 and cathepsins L may decrease the rate of apoptosis triggered by lamin degradation. Nevertheless, further studies are required to confirm these observations due to the lack of in vivo findings.
Keywords: Alzheimer Disease; Apoptosis; Caspase 3; Caspase 6; Cathepsin B; Cathepsin L; Hippocampus; Humans; Lamin Type A; Laminopathies; Male; Molecular Docking Simulation

There are dementia patients in Gaza too. - Irfan, Bilal; Abu Shammala, Abdallah; Alshaer, Nour; Nasser, Elias; Wajahath, Muaaz; Hamawy, Adam; Tahir, Mohammed; Khawaja, Haseeb; Khan, Osaama; Fikry, Karim; Kaleem, Arshad; Nasser, Mosab; et al. (J Alzheimers Dis, 2024)
This editorial highlights the devastating impact of the ongoing Israeli military assault in Gaza on dementia patients, whose fragile care systems have collapsed, leaving them vulnerable and without essential medical support. Through harrowing stories of displacement, medication shortages, and tragic deaths, the piece underscores the profound moral failure in protecting Gaza's most vulnerable, calling for urgent global action to address the humanitarian crisis and ensure dignity and healthcare for all affected individuals.
Keywords: Dementia; Humans; Middle East

Transcriptomic Profiling Reveals Neuroinflammation in the Corpus Callosum of a Transgenic Mouse Model of Alzheimer's Disease. - Takase, Hajime; Hamanaka, Gen; Hoshino, Tomonori; Ohtomo, Ryo; Guo, Shuzhen; Mandeville, Emiri T; Lo, Eng H; Arai, Ken (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a widespread neurodegenerative disorder characterized by progressive cognitive decline, affecting a significant portion of the aging population. While the cerebral cortex and hippocampus have been the primary focus of AD research, accumulating evidence suggests that white matter lesions in the brain, particularly in the corpus callosum, play an important role in the pathogenesis of the disease. OBJECTIVE: This study aims to investigate the gene expression changes in the corpus callosum of 5xFAD transgenic mice, a widely used AD mouse model. METHODS: We conducted behavioral tests for spatial learning and memory in 5xFAD transgenic mice and performed RNA sequencing analyses on the corpus callosum to examine transcriptomic changes. RESULTS: Our results show cognitive decline and demyelination in the corpus callosum of 5xFAD transgenic mice. Transcriptomic analysis reveals a predominance of upregulated genes in AD mice, particularly those associated with immune cells, including microglia. Conversely, downregulation of genes related to chaperone function and clock genes such as Per1, Per2, and Cry1 is also observed. CONCLUSIONS: This study suggests that activation of neuroinflammation, disruption of chaperone function, and circadian dysfunction are involved in the pathogenesis of white matter lesions in AD. The findings provide insights into potential therapeutic targets and highlight the importance of addressing white matter pathology and circadian dysfunction in AD treatment strategies.
Keywords: Alzheimer Disease; Animals; Corpus Callosum; Disease Models, Animal; Gene Expression Profiling; Mice; Mice, Transgenic; Neuroinflammatory Diseases

Unveiling New Strategies Facilitating the Implementation of Artificial Intelligence in Neuroimaging for the Early Detection of Alzheimer's Disease. - Etekochay, Maudlyn O; Amaravadhi, Amoolya Rao; González, Gabriel Villarrubia; Atanasov, Atanas G; Matin, Maima; Mofatteh, Mohammad; Steinbusch, Harry Wilhelm; Tesfaye, Tadele; Praticò, Domenico (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder with a global impact. The past few decades have witnessed significant strides in comprehending the underlying pathophysiological mechanisms and developing diagnostic methodologies for AD, such as neuroimaging approaches. Neuroimaging techniques, including positron emission tomography and magnetic resonance imaging, have revolutionized the field by providing valuable insights into the structural and functional alterations in the brains of individuals with AD. These imaging modalities enable the detection of early biomarkers such as amyloid-β plaques and tau protein tangles, facilitating early and precise diagnosis. Furthermore, the emerging technologies encompassing blood-based biomarkers and neurochemical profiling exhibit promising results in the identification of specific molecular signatures for AD. The integration of machine learning algorithms and artificial intelligence has enhanced the predictive capacity of these diagnostic tools when analyzing complex datasets. In this review article, we will highlight not only some of the most used diagnostic imaging approaches in neurodegeneration research but focus much more on new tools like artificial intelligence, emphasizing their application in the realm of AD. These advancements hold immense potential for early detection and intervention, thereby paving the way for personalized therapeutic strategies and ultimately augmenting the quality of life for individuals affected by AD.
Keywords: Alzheimer Disease; Artificial Intelligence; Biomarkers; Brain; Early Diagnosis; Humans; Neuroimaging; Positron-Emission Tomography

Accumulation of pTau231 at the Postsynaptic Density in Early Alzheimer's Disease. - Lilek, Jaclyn; Ajroud, Kaouther; Feldman, Alexander Z; Krishnamachari, Sesha; Ghourchian, Shadi; Gefen, Tamar; Spencer, Callen L; Kawles, Allegra; Mao, Qinwen; Tranovich, Jessica F; Jack, Clifford R; Mesulam, M-Marsel; et al. (J Alzheimers Dis, 2023)

Activation of TNF Receptor 2 Improves Synaptic Plasticity and Enhances Amyloid-β Clearance in an Alzheimer's Disease Mouse Model with Humanized TNF Receptor 2. - Ortí-Casañ, Natalia; Wajant, Harald; Kuiperij, H Bea; Hooijsma, Annelien; Tromp, Leon; Poortman, Isabelle L; Tadema, Norick; de Lange, Julia H E; Verbeek, Marcel M; De Deyn, Peter P; Naudé, Petrus J W; Eisel, Ulrich L M (J Alzheimers Dis, 2023)
BACKGROUND: Tumor necrosis factor-alpha (TNF-α) is a master cytokine involved in a variety of inflammatory and neurological diseases, including Alzheimer's disease (AD). Therapies that block TNF-α proved ineffective as therapeutic for neurodegenerative diseases, which might be explained by the opposing functions of the two receptors of TNF (TNFRs): while TNFR1 stimulation mediates inflammatory and apoptotic pathways, activation of TNFR2 is related to neuroprotection. Despite the success of targeting TNFR2 in a transgenic AD mouse model, research that better mimics the human context is lacking. OBJECTIVE: The aim of this study is to investigate whether stimulation of TNFR2 with a TNFR2 agonist is effective in activating human TNFR2 and attenuating AD neuropathology in the J20xhuTNFR2-k/i mouse model. METHODS: Transgenic amyloid-β (Aβ)-overexpressing mice containing a human extracellular TNFR2 domain (J20xhuTNFR2-k/i) were treated with a TNFR2 agonist (NewStar2). After treatment, different behavioral tests and immunohistochemical analysis were performed to assess different parameters, such as cognitive functions, plaque deposition, synaptic plasticity, or microglial phagocytosis. RESULTS: Treatment with NewStar2 in J20xhuTNFR2-k/i mice resulted in a drastic decrease in plaque load and beta-secretase 1 (BACE-1) compared to controls. Moreover, TNFR2 stimulation increased microglial phagocytic activity, leading to enhanced Aβ clearance. Finally, activation of TNFR2 rescued cognitive impairments and improved synaptic plasticity. CONCLUSION: Our findings demonstrate that activation of human TNFR2 ameliorates neuropathology and improves cognitive functions in an AD mouse model. Moreover, our study confirms that the J20xhuTNFR2-k/i mouse model is suitable for testing human TNFR2-specific compounds.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Humans; Mice; Mice, Transgenic; Neuronal Plasticity; Receptors, Tumor Necrosis Factor, Type II; Tumor Necrosis Factor-alpha

Advanced Alzheimer's Disease Patients Show Safe, Significant, and Persistent Benefit in 6-Month Bryostatin Trial. - Alkon, Daniel L; Sun, Miao-Kun; Tuchman, Alan J; Thompson, Richard E (J Alzheimers Dis, 2023)
BACKGROUND: In pre-clinical studies, Bryostatin, MW (molecular weight) 904, has demonstrated synaptogenic, anti-apoptotic, anti-amyloid, and anti-tau tangle efficacies. OBJECTIVE: To identify AD patients who show significant cognitive benefit versus placebo when treated in a trial with chronic Bryostatin dosing. METHODS: In this 6-month 122 AD patient Bryostatin trial, there were two cohorts: the Moderate Cohort (MMSE, Mini-Mental Status Exam: 15-18) and the Moderately Severe Cohort (MMSE 10-14) as pre-specified secondary endpoints. Patient randomization was stratified by baseline SIB to insure balance in baseline cognitive ability between treatment arms. RESULTS: With no safety events noted by the data safety and monitoring board, the Moderately Severe (MMSE 10-14) Bryostatin-treated patients were significantly improved above the placebo patients for Weeks #13 through Week #42. After two cycles of 7 x i.v. Bryostatin doses over a 26-week period, the 10-14 Cohort Severe Impairment Battery (SIB), measured every 2 weeks, showed significant benefit using a Mixed Model Repeated Measures model (MMRM, 2-tailed, p < 0.05) for Weeks #13 through #42, even 16 weeks after dosing completion by Week #26. Placebo 10-14 patients showed no benefit, declining to negative 12.8 points by Week #42. Trend analyses confirmed the MMRM data for this Cohort, with a significant downward slope (equivalent to Cognitive Decline) for the placebo group, p < 0.001, 2-tailed, but no significant decline for the Bryostatin-treated group (p = 0.409, NS), treatment versus placebo p < 0.007. The Moderate Cohort patients showed no significant benefit. CONCLUSIONS: The Bryostatin-treated MMSE 10-14 patients showed no significant cognitive decline throughout the 10-month trial, versus placebo patients' decline of -12.8 SIB points.
Keywords: Alzheimer Disease; Bryostatins; Cognition Disorders; Double-Blind Method; Humans; Treatment Outcome

Age-Related Association Between APOE ɛ4 and Cognitive Progression in de novo Parkinson's Disease. - Liu, Jia-Yao; Ma, Ling-Zhi; Wang, Jun; Cui, Xin-Jing; Sheng, Ze-Hu; Fu, Yan; Li, Meng; Ou, Ya-Nan; Yu, Jin-Tai; Tan, Lan; Lian, Yan (J Alzheimers Dis, 2023)
BACKGROUND: APOE ɛ4 genotype was correlated with exacerbation of pathology and higher risk of dementia in Parkinson's disease (PD). Meanwhile, the differential influence of APOE ɛ4 on cognition in young and old individuals interpreted as antagonistic pleiotropy. OBJECTIVE: To examine whether the effect of APOE ɛ4 on cognitive progression in de novo PD is age dependent. METHODS: In this study, 613 de novo PD patients were recruited from Parkinson's Progression Markers Initiative (PPMI). To examine the age-dependent relationship between APOE ɛ4 and cognitive changes, we added 3-way interaction of APOE ɛ4*baseline age*time to the linear mixed-effect (LME) models and evaluated the specific roles of APOE ɛ4 in the middle age group and elderly group separately. Cox regression was utilized to examine the progression of cognition in age-stratified PD participants. RESULTS: Age significantly modified relationship between APOE ɛ4 and cognitive changes in most cognitive domains (pinteraction <0.05). In the elderly group, APOE ɛ4 carriers showed steeper decline in global cognition (p = 0.001) as well as in most cognitive domains, and they had a greater risk of cognitive progression (adjusted HR 1.625, 95% CI 1.143-2.310, p = 0.007), compared with non-carriers. However, in the middle age group, no significant relationships between APOE ɛ4 and cognitive decline can be detected. CONCLUSION: Our results indicated that the APOE ɛ4 allele has an age-dependent effect on cognitive decline in PD patients. The underlying mechanisms need to be investigated in the future.
Keywords: Aged; Apolipoprotein E4; Cognition; Cognitive Dysfunction; Disease Progression; Genotype; Heterozygote; Humans; Parkinson Disease

Alzheimer's Disease and Neurosyphilis: Meaningful Commonalities and Differences of Clinical Phenotype and Pathophysiological Biomarkers. - Milano, Chiara; Hoxhaj, Domeniko; Del Chicca, Marta; Pascazio, Alessia; Paoli, Davide; Tommasini, Luca; Vergallo, Andrea; Pizzanelli, Chiara; Tognoni, Gloria; Nuti, Angelo; Ceravolo, Roberto; Siciliano, Gabriele; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Neurosyphilis-associated cognitive and behavioral impairment- historically coined as "general paralysis of the insane"- share clinical and neuroradiological features with the neurodegenerative disease spectrum, in particular Alzheimer's disease (AD). Anatomopathological similarities have been extensively documented, i.e., neuronal loss, fibrillary alterations, and local amyloid-β deposition. Consequently, accurate classification and timely differential diagnosis may be challenging. OBJECTIVE: To describe clinical, bio-humoral, brain MRI, FDG-PET, and amyloid-PET features in cases of neurosyphilis with an AD-like phenotypical presentation, as well as clinical outcome in terms of response to antibiotic therapy. METHODS: We selected the studies comparing patients with AD and with neurosyphilis associated cognitive impairment, to investigate candidate biomarkers classifying the two neurological diseases. RESULTS: The neuropsychological phenotype of general paralysis, characterized by episodic memory impairment and executive disfunction, substantially mimics clinical AD features. Neuroimaging often shows diffuse or medial temporal cortical atrophy, thus contributing to a high rate of misdiagnosis. Cerebrospinal fluid (CSF)-based analysis may provide supportive diagnostic value, since increased proteins or cells are often found in neurosyphilis, while published data on pathophysiological AD candidate biomarkers are controversial. Finally, psychometric testing using cross-domain cognitive tests, may highlight a wider range of compromised functions in neurosyphilis, involving language, attention, executive function, and spatial ability, which are atypical for AD. CONCLUSION: Neurosyphilis should be considered a potential etiological differential diagnosis of cognitive impairment whenever imaging, neuropsychological or CSF features are atypical for AD, in order to promptly start antibiotic therapy and delay or halt cognitive decline and disease progression.

Apathy as a Predictor of Conversion from Mild Cognitive Impairment to Alzheimer's Disease: A Texas Alzheimer's Research and Care Consortium (TARCC) Cohort-Based Analysis. - Salem, Haitham; Suchting, Robert; Gonzales, Mitzi M; Seshadri, Sudha; Teixeira, Antônio L (J Alzheimers Dis, 2023)
BACKGROUND: Apathy is among the neuropsychiatric symptoms frequently observed in people with cognitive impairment. It has been postulated to be a potential predictor of conversion from mild cognitive impairment (MCI) to Alzheimer's disease (AD). OBJECTIVE: To detect conversion rates from MCI to AD, and to determine the effect of apathy on the progression to AD in patients with MCI enrolled in the Texas Alzheimer's Research and Care Consortium (TARCC) cohort. METHODS: Apathy was determined by a positive response to the respective item in the Neuropsychiatric Inventory -Questionnaire (NPI-Q) completed by family members or caregivers. The final dataset included 2,897 observations from 1,092 individuals with MCI at the baseline. Kaplan-Meier survival curves were estimated to provide indices of the probability of conversion to AD over time across all individuals as well as between those with and without apathy. Cox proportional hazards regression measured the hazard associated with apathy and several other predictors of interest. RESULTS: Over a period of 8.21 years, 17.3% of individuals had conversion from MCI to AD (n = 190 of 1,092 total individuals) across observations. The median time-to-conversion across all participants was 6.41 years. Comparing individuals with apathy (n = 158) versus without apathy (n = 934), 36.1% and 14.2% had conversion to AD, respectively. The median time-to-conversion was 3.79 years for individuals with apathy and 6.83 years for individuals without apathy. Cox proportional hazards regression found significant effects of several predictors, including apathy, on time-to-conversion. Age and cognitive performance were found to moderate the relationship between apathy and time-to-conversion. CONCLUSIONS: Apathy is associated with progression from MCI to AD, suggesting that it might improve risk prediction and aid targeted intervention delivery.

Association of Age-Related Spontaneous Internal Jugular Vein Reflux with Cognitive Impairment and Incident Dementia. - Adachi, Utako; Toi, Sono; Hosoya, Megumi; Hoshino, Takao; Seki, Misa; Yoshizawa, Hiroshi; Tsutsumi, Yukiko; Maruyama, Kenji; Kitagawa, Kazuo (J Alzheimers Dis, 2023)
BACKGROUND: It remains unclear whether changes in the venous circulation contribute to cognitive decline. OBJECTIVE: This study aimed to clarify whether the spontaneous jugular vein reflux (JVR) is associated with cognitive impairment and incident dementia. METHODS: Patients with any evidence of cerebral vessel disease on magnetic resonance imaging (MRI) were consecutively enrolled between October 2015 to July 2019. We employed carotid duplex sonography to measure the internal jugular vein (IJV). The subjects were classified into two groups based on the degree of JVR on either side: none, mild (JVR(-) group) and moderate, severe (JVR (+) group) JVR. They underwent both the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment-Japanese (MoCA-J) global tests. Their cognitive status was prospectively assessed until March 2023. RESULTS: 302 patients with an MMSE score ≥24 underwent duplex sonography of the IJV. Among them, 91 had spontaneous JVR on either side. Both MMSE and MoCA-J were significantly lower in patients with JVR (+) group than in the JVR (-) group. After the adjustment for risk factors and MRI findings, intergroup differences in MoCA-J remained significant. Among the cognitive subdomains, median executive function and memory scores were significantly lower in the JVR (+) group than in the JVR (-) group. During the median 5.2-year follow-up, 11 patients with incident dementia were diagnosed. Patients with severe JVR were significantly more likely to be diagnosed with dementia (log-rank test, p = 0.031). CONCLUSIONS: Spontaneous IJV reflux especially severe JVR, was associated with global cognitive function, and potentially with incident dementia.

Association of Interleukin-6 and Interleukin-8 with Cognitive Decline in an Asian Memory Clinic Population. - Teoh, Nicole Shu Ning; Gyanwali, Bibek; Lai, Mitchell K P; Chai, Yuek Ling; Chong, Joyce R; Chong, Eddie Jun Yi; Chen, Christopher; Tan, Chuen Seng; Hilal, Saima (J Alzheimers Dis, 2023)
BACKGROUND: Neuroinflammation has been postulated to play an important role in cognitive impairment, cognitive decline, and dementia. Inflammatory biomarkers such as interleukin-6 (IL-6) and IL-8 are found to be associated with the neuro-inflammatory process and worse cognitive function. However, it is unknown whether these interleukins are associated with long-term cognitive function. OBJECTIVE: To investigate the association of baseline IL-6 and IL-8 with cognitive function at baseline as well as its association with cognitive decline over five-year follow-up. METHODS: 387 patients were recruited from an ongoing memory clinic-based study who underwent comprehensive physical, medical, neuropsychological and blood assessments together with brain MRI. IL-6 and IL-8 were measured using LUMINEX assays. The National Institute of Neurological Disorders and Stroke-Canadian Stroke Network neuropsychological battery was used to assess cognitive decline across multiple domains. RESULTS: Among the 387 (mean age = 72.9 years and 53.7% males) participants, 322 had at least two follow-up assessments and were included in the longitudinal analysis. Negative linear trend associations were found between tertiles of IL-8 with baseline global cognition (p-trend< 0.001), attention (p-trend = 0.005), executive function (p-trend< 0.001), and visuospatial function (p-trend = 0.002) domains. No association was found between baseline IL-8 and cognitive decline. IL-6 was not associated with both baseline and follow-up cognition. CONCLUSION: IL-8 was associated with worse cognition especially in attention, executive function, and visuospatial function, suggesting the role of neuroinflammation in cognitive impairment. Hence, blood inflammatory biomarkers may be useful indicators in identifying patients at risk of cognitive impairment and warrant consideration for inclusion in treatment trials.
Keywords: Aged; Biomarkers; Canada; Cognition; Cognitive Dysfunction; Female; Humans; Interleukin-6; Interleukin-8; Male; Neuroinflammatory Diseases; Neuropsychological Tests

Association of Sarcopenia and Its Defining Components with the Degree of Cognitive Impairment in a Memory Clinic Population. - Larsson, LE; Wang, Rui; Cederholm, Tommy; Wiggenraad, Fleur; Rydén, Marie; Hagman, Göran; Hellénius, Mai-Lis; Kivipelto, Miia; Thunborg, Charlotta (J Alzheimers Dis, 2023)
BACKGROUND: Sarcopenia and cognitive impairment are two leading causes of disabilities. OBJECTIVE: The objective was to examine the prevalence of sarcopenia and investigate the association between sarcopenia diagnostic components (muscle strength, muscle mass, and physical performance) and cognitive impairment in memory clinic patients. METHODS: 368 patients were included (age 59.0±7.25 years, women: 58.7%), displaying three clinical phenotypes of cognitive impairments, i.e., subjective cognitive impairment (SCI, 57%), mild cognitive impairment (MCI, 26%), and Alzheimer's disease (AD, 17%). Sarcopenia was defined according to diagnostic algorithm recommended by the European Working Group on Sarcopenia in Older People. Components of sarcopenia were grip strength, bioelectrical impedance analysis, and gait speed. They were further aggregated into a score (0-3 points) by counting the numbers of limited components. Multi-nominal logistic regression was applied. RESULTS: Probable sarcopenia (i.e., reduced grip strength) was observed in 9.6% of the patients, and 3.5% were diagnosed with sarcopenia. Patients with faster gait speed showed less likelihood of MCI (odds ratio [OR]: 0.24, 95% confidence interval [CI]: 0.06-0.90) and AD (OR: 0.12, 95% CI: 0.03-0.60). One or more limited sarcopenia components was associated with worse cognitive function. After adjusting for potential confounders, the association remained significant only for AD (OR 4.29, 95% CI 1.45-11.92). CONCLUSION: The results indicate a connection between the sarcopenia components and cognitive impairments. Limitations in the sarcopenia measures, especially slow walking speed, were related to poorer cognitive outcomes. More investigationsare required to further verify the causal relationship between sarcopenia and cognitive outcomes.

Associations Between Ambient Air Pollution and Cognitive Abilities from Midlife to Early Old Age: Modification by APOE Genotype. - Franz, Carol E; Gustavson, Daniel E; Elman, Jeremy A; Fennema-Notestine, Christine; Hagler, Donald J; Baraff, Aaron; Tu, Xin M; Wu, Tsung-Chin; De Anda, Jaden; Beck, Asad; Kaufman, Joel D; Whitsel, Nathan; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Fine particulate matter (PM2.5) and nitrogen dioxide (NO2) measures of ambient air pollution are associated with accelerated age-related cognitive impairment, and Alzheimer's disease and related dementias (ADRD). OBJECTIVE: We examined associations between air pollution, four cognitive factors, and the moderating role of apolipoprotein E (APOE) genotype in the understudied period of midlife. METHODS: Participants were ∼1,100 men in the Vietnam Era Twin Study of Aging. Baseline cognitive assessments were from 2003 to 2007. Measures included past (1993-1999) and recent (3 years prior to baseline assessment) PM2.5 and NO2 exposure, in-person assessment of episodic memory, executive function, verbal fluency, and processing speed, and APOE genotype. Average baseline age was 56 years with a 12-year follow-up. Analyses adjusted for health and lifestyle covariates. RESULTS: Performance in all cognitive domains declined from age 56 to 68. Higher PM2.5 exposures were associated with worse general verbal fluency. We found significant exposure-by-APOE genotype interactions for specific cognitive domains: PM2.5 with executive function and NO2 with episodic memory. Higher PM2.5 exposure was related to worse executive function in APOE ɛ4 carriers, but not in non-carriers. There were no associations with processing speed. CONCLUSION: These results indicate negative effects of ambient air pollution exposure on fluency alongside intriguing differential modifications of cognitive performance by APOE genotype. APOE ɛ4 carriers appeared more sensitive to environmental differences. The process by which air pollution and its interaction with genetic risk for ADRD affects risk for later life cognitive decline or progression to dementia may begin in midlife.

Associations Between Local Area Deprivation and Physical Activity Participation in People with Cognitive Impairment in the North East of England. - Mc Ardle, Ríona; Hamilton, Calum; Del Din, Silvia; Kingston, Andrew; Robinson, Louise; Galna, Brook; Thomas, Alan J; Rochester, Lynn (J Alzheimers Dis, 2023)
BACKGROUND: Promoting physical activity, such as habitual walking behaviors, in people with cognitive impairment may support their ability to remain independent with a good quality of life for longer. However, people with cognitive impairment participate in less physical activity compared to cognitively unimpaired older adults. The local area in which people live may significantly impact abilities to participate in physical activity. For example, people who live in more deprived areas may have less safe and walkable routes. OBJECTIVE: To examine this further, this study aimed to explore associations between local area deprivation and physical activity in people with cognitive impairment and cognitively unimpaired older adults (controls). METHODS: 87 participants with cognitive impairment (mild cognitive impairment or dementia) and 27 older adult controls from the North East of England were included in this analysis. Participants wore a tri-axial wearable accelerometer (AX3, Axivity) on their lower backs continuously for seven days. The primary physical activity outcome was daily step count. Individuals' neighborhoods were linked to UK government area deprivation statistics. Hierarchical Bayesian models assessed the association between local area deprivation and daily step count in people with cognitive impairment and controls. RESULTS: Key findings indicated that there was no association between local area deprivation and daily step count in people with cognitive impairment, but higher deprivation was associated with lower daily steps for controls. CONCLUSION: These findings suggest that cognitive impairment may be associated with lower participation in physical activity which supersedes the influence of local area deprivation observed in normal aging.

Can Traditional Board Games Prevent or Slow Down Cognitive Impairment? A Systematic Review and Meta-Analysis. - Pozzi, Federico Emanuele; Appollonio, Ildebrando; Ferrarese, Carlo; Tremolizzo, Lucio (J Alzheimers Dis, 2023)
BACKGROUND: Traditional board games can entail significant skills encompassing several cognitive functions across different domains. Therefore, they may potentially represent effective cognitive interventions in the aging population with or without Alzheimer's disease or other types of dementia. OBJECTIVE: We aimed at verifying the hypothesis that traditional board games can prevent or slow down cognitive decline, through a systematic review on traditional board games and dementia. METHODS: We searched five databases with tailored search strings. We included studies assessing the impact of board games on elderly subjects at risk of or suffering from cognitive impairment, or subjects with cognitive impairment irrespective of age. Studies where the effect of board games was not separated by cards or other games were excluded. A meta-analysis was performed for specific cognitive and non-cognitive outcomes. RESULTS: Board games improved mental function, as measured by Montreal Cognitive Assessment (p = 0.003) and Mini-Mental State Examination (p = 0.02). Ska and Go improved Trail Making Test -A, while Mahjong improved executive functions. There was no consistent effect across different games on Digit Span or Categorical Fluency. Chess improved quality of life measured with the WHO-QoL-OLD scale (p < 0.00001). Mahjong temporarily improved depressive symptoms. Go increased BDNF levels and left middle temporal gyrus and bilateral putamen metabolism. CONCLUSIONS: Traditional board games may slow global cognitive decline and improve the quality of life in elderly subjects. Different games have varying impacts on specific cognitive domains, possibly mediated by functional and biological factors.
Keywords: Aged; Alzheimer Disease; Cognition; Cognitive Dysfunction; Executive Function; Humans; Quality of Life

Circulating Omega-3 and Omega-6 Fatty Acids, Cognitive Decline, and Dementia in Older Adults. - de Oliveira Otto, Marcia C; Wu, Jason H Y; Thacker, Evan L; Lai, Heidi Tsz Mung; Lemaitre, Rozenn N; Padhye, Nikhil; Song, Xiaoling; King, Irena B; Lopez, Oscar; Siscovick, David S; Mozaffarian, Dariush (J Alzheimers Dis, 2023)
BACKGROUND: Comprising nearly 35% of brain lipids, polyunsaturated fatty acids (PUFA) are essential for optimal brain function. However, the role of PUFA on cognitive health outcomes later in life is largely unknown. OBJECTIVE: We investigated prospective associations of plasma phospholipid omega-3 (ALA [18 : 3], EPA [20 : 5], DPA [22 : 5], DHA [22 : 6]) and omega-6 (LA [18 : 2], AA [20 : 4]) PUFA with cognitive decline, risk of cognitive impairment and dementia among adults aged≥65 years in the Cardiovascular Health Study. METHODS: Circulating fatty acid concentrations were measured serially at baseline (1992/1993), 6 years, and 13 years later. Cognitive decline and impairment were assessed using the 100-point Modified Mini-Mental State Examination (3MSE) up to 7 times. Clinical dementia was identified using adjudicated neuropsychological tests, and ICD-9 codes. RESULTS: Among 3,564 older adults free of stroke and dementia at baseline, cognitive function declined annually by approximately -0.5 3MSE points; 507 participants developed cognitive impairment and 499 dementia over up to 23 years of follow-up. In multivariable models, higher circulating arachidonic acid (AA) concentrations were associated with slower cognitive decline and lower dementia risk, with associations growing stronger with greater length of follow-up (hazard ratio [HR,95% CI] of dementia per interquintile range, 0.74 [0.56-0.97] at 5 years, and 0.53 [0.37-0.77] at 15 years). Circulating docosapentaenoic (DPA) concentrations were associated with slower cognitive decline and lower risk of cognitive impairment (extreme-quintile HR, 0.72 [95% CI: 0.55, 0.95]). Findings were generally null or inconsistent for other omega-3 or omega-6 PUFA. CONCLUSION: Circulating AA and DPA, but not other PUFA, are associated with slower rate of cognitive decline and lower risk of dementia or cognitive impairment later in life.
Keywords: Aged; Arachidonic Acid; Cognitive Dysfunction; Dementia; Fatty Acids; Fatty Acids, Omega-3; Fatty Acids, Omega-6; Fatty Acids, Unsaturated; Humans

Coexistence of Amyotrophic Lateral Sclerosis and Alzheimer's Disease: Case Report and Review of the Literature. - Verde, Federico; Aiello, Edoardo Nicolò; Adobbati, Laura; Poletti, Barbara; Solca, Federica; Tiloca, Cinzia; Sangalli, Davide; Maranzano, Alessio; Muscio, Cristina; Ratti, Antonia; Zago, Stefano; Ticozzi, Nicola; et al. (J Alzheimers Dis, 2023)
We describe a case of amyotrophic lateral sclerosis (ALS) associated with Alzheimer's disease (AD) and review the literature about the coexistence of the two entities, highlighting the following: mean age at onset is 63.8 years, with slight female predominance; ALS tends to manifest after cognitive impairment and often begins in the bulbar region; average disease duration is 3 years; cognitive phenotype is mostly amnestic; the pattern of brain involvement is, in most cases, consistent with AD. Our case and the reviewed ones suggest that patients with ALS and dementia lacking unequivocal features of FTD should undergo additional examinations in order to recognize AD.
Keywords: Alzheimer Disease; Amyotrophic Lateral Sclerosis; Brain; Cognitive Dysfunction; Female; Frontotemporal Dementia; Humans; Male

Costs of Dementia in Low- And Middle-Income Countries: A Systematic Review. - Kenne Malaha, Angeladine; Thébaut, Clémence; Achille, Dayna; Preux, Pierre-Marie; Guerchet, Maëlenn (J Alzheimers Dis, 2023)
BACKGROUND: The proportion of people living with dementia in low- and middle-income countries (LMICs) is expected to reach 71% by 2050. Appraising the economic burden of the disease may contribute to strategic policy planning. OBJECTIVE: To review studies conducted on the costs of dementia in LMICs, describe their methodology and summarize available costs estimates. METHODS: Systematic review, including a search of health, economics, and social science bibliographic databases. No date or language restrictions were applied. All studies with a direct measure of the costs of dementia care were included. RESULTS: Of the 6,843 publications reviewed, 17 studies from 11 LMICs were included. Costs of dementia tended to increase with the severity of the disease. Medical costs were greater in the mild stage, while social and informal care costs were highest in the moderate and severe stages. Annual cost estimates per patient ranged from PPP$131.0 to PPP$31,188.8 for medical costs; from PPP$16.1 to PPP$10,581.7 for social care services and from PPP$140.0 to PPP$25,798 for informal care. Overall, dementia care can cost from PPP$479.0 to PPP$66,143.6 per year for a single patient. CONCLUSION: Few studies have been conducted on the costs of dementia in LMICs, and none so far in Africa. There seems to be a need to provide accurate data on the burden of disease in these countries to guide public health policies in the coming decades.
Keywords: Cost of Illness; Dementia; Developing Countries; Health Care Costs; Health Expenditures; Humans

Cross-Sectional Analysis of Periodontal Disease and Cognitive Impairment Conducted in a Memory Clinic: The Pearl Study. - Saji, Naoki; Ishihara, Yuichi; Murotani, Kenta; Uchiyama, Akira; Takeda, Akinori; Sakurai, Takashi; Matsushita, Kenji (J Alzheimers Dis, 2023)
BACKGROUND: Periodontal disease (PeD) is a risk factor of Alzheimer's disease and is associated with cognitive decline in older adults. However, the relationships between subitems of neuropsychological tests and PeD have not been fully clarified. OBJECTIVE: To evaluate associations between PeD and subitems of neuropsychological tests. METHODS: We performed a cross-sectional analysis of data of 183 participants (women: 50% , mean age: 79 years) from a clinical study. We enrolled patients who visited our memory clinic and assessed demographics, dementia-related risk factors, neuropsychological tests, brain magnetic resonance images, and a dental screening check. We evaluated the relationships between cognitive function and PeD using multivariable logistic regression analyses. RESULTS: Participants with dementia were less likely to make periodical visits to the dentist, had fewer teeth, had less frequent tooth brushing habits, and were more likely to have PeD. Impaired cognitive function was significantly associated with an increasing degree of PeD. In multivariable logistic regression analyses, impaired visuospatial function and attention were associated with twice the risk of moderate or severe PeD compared with individuals with preserved visuospatial function and attention (odds ratio: 2.11, 95% confidence interval: 1.04-4.29, p = 0.037). Impaired word recall and recognition and following commands were associated with increased risk of PeD (odds ratio: 2.80, 95% confidence interval: 1.41-5.32, p = 0.003). CONCLUSIONS: Cognitive decline, such as impaired visuospatial function, attention, word recall and recognition, and inability to follow commands were independently and strongly associated with PeD. These items can be assessed easily on a daily basis.

Different Trajectories of Apathy and Depression Among Subjective Cognitive Impairment Individuals with or without Conversion to Dementia: Results from the Memento Cohort in France. - Bogdan, Anamaria; Fabre, Roxane; Desmidt, Thomas; Golebiowski, Jérôme; Topin, Jérémie; Bethus, Ingrid; Hanon, Olivier; Boutoleau-Bretonnière, Claire; Wagemann, Nathalie; Annweiler, Cedric; Ousset, Pierre-Jean; Godefroy, Olivier; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Apathy and depression are two early behavioral symptoms in Alzheimer's disease (AD) and related disorders that often occur prior to the onset of cognitive decline and memory disturbances. Both have been associated with an increased risk of conversion to dementia, with a distinct neuropathology. OBJECTIVE: The assessment of the trajectories of apathy and depression and their independent impact on dementia conversion. METHODS: Apathy and Depression were measured using the Neuropsychiatric Inventory for caregiver (NPI) and clinician (NPI-C), among the nondemented individuals reporting subjective cognitive decline (SCD) at baseline. They were followed up over a 60-month period. Some converted to dementia, according to the methodology carried out by the French Memento Cohort. RESULTS: Among individuals with SCD (n = 2,323), the levels of apathy and depression were low and did not evolve significantly over the 60-month period, despite a trend in apathy increasing as of month 24. Regarding SCD individuals who converted to dementia within the 60-month period (n = 27), the prevalence of depression remained globally steady, while the levels of apathy increased over time. CONCLUSION: Apathy and depression have different trajectories among individuals with SCD and apathy alone is more likely-compared to depression-to be associated with conversion to dementia.

Effects of a Physical Activity Program that Incorporates Exercises Targeting Balance, Strength, and Proprioception on Cognitive Functions and Physical Performance in Old Adults with Mild Cognitive Impairment. - Boulares, Ayoub; Fabre, Claudine; Cherni, Ala; Jdidi, Hela; Gaied Chortane, Sabri; Trompetto, Carlo; Puce, Luca; Bragazzi, Nicola Luigi (J Alzheimers Dis, 2023)
BACKGROUND: Aging often leads to cognitive function decline, sensory structure deterioration, and musculoskeletal system weakening. This impacts postural control during static and dynamic activities like walking, increasing the fall risk among the elderly. Older adults with mild cognitive impairment (MCI) face an elevated fall risk and cognitive decline, magnifying the public health concern. OBJECTIVE: This study aimed to explore solutions by investigating the effects of a multi-component physical activity program on cognitive and motor functions in MCI patients. METHODS: Twenty-three participants were enrolled in the study and assigned into two groups: an intervention group (n = 13; age = 85.7±5.5 years) and a control group (n = 9; age = 85±6.7 years). The study spanned two months, with participants engaging in three 60-minute weekly physical exercise sessions. The intervention focused on improving proprioception, muscle strength, and balance. RESULTS: Results demonstrated significant enhancements in physical performance, fall risk reduction, and balance (p < 0.05). Various tests, including the timed up and go test, Unipedal Stance test, Tinetti test, Short Physical Performance Battery, and 6-minute walking test, indicated these improvements. Cognitive function was evaluated with the Mini-Mental State Examination, revealing non-significant progress (p > 0.05). Predictive models for outcomes were developed using linear regression analysis during the follow-up stage. CONCLUSIONS: This study underscores the effectiveness of a multi-component physical activity program encompassing balance, proprioception, and muscle-strengthening exercises as a non-pharmaceutical approach in improving balance skills and playing a key role in mitigating the risk of falls among old adults with MCI.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Exercise; Exercise Therapy; Humans; Physical Functional Performance; Postural Balance; Proprioception; Time and Motion Studies

Evaluation of Blood-Based Plasma Biomarkers as Potential Markers of Amyloid Burden in Preclinical Alzheimer's Disease. - Winston, Charisse N; Langford, Oliver; Levin, Natalie; Raman, Rema; Yarasheski, Kevin; West, Tim; Abdel-Latif, Sara; Donohue, Michael; Nakamura, Akinori; Toba, Kenji; Masters, Colin L; Doecke, James; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Participant eligibility for the A4 Study was determined by amyloid PET imaging. Given the disadvantages of amyloid PET imaging in accessibility and cost, blood-based biomarkers may serve as a sufficient biomarker and more cost-effective screening tool for patient enrollment into preclinical AD trials. OBJECTIVE: To determine if a blood-based screening test can adequately identify amyloid burden in participants screened into a preclinical AD trial. METHODS: In this cross-sectional study, 224 participants from the A4 Study received an amyloid PET scan (18Florbetapir) within 90 days of blood sample collection. Blood samples from all study participants were processed within 2 h after phlebotomy. Plasma amyloid measures were quantified by Shimazdu and C2 N Diagnostics using mass spectrometry-based platforms. A corresponding subset of blood samples (n = 100) was processed within 24 h after phlebotomy and analyzed by C2 N. RESULTS: Plasma Aβ42/Aβ40 demonstrated the highest association for Aβ accumulation in the brain with an AUC 0.76 (95%CI = 0.69, 0.82) at C2 N and 0.80 (95%CI = 0.75, 0.86) at Shimadzu. Blood samples processed to plasma within 2 h after phlebotomy provided a better prediction of amyloid PET status than blood samples processed within 24 h (AUC 0.80 versus 0.64; p < 0.001). Age, sex, and APOE ɛ4 carrier status did not the diagnostic performance of plasma Aβ42/Aβ40 to predict amyloid PET positivity in A4 Study participants. CONCLUSION: Plasma Aβ42/Aβ40 may serve as a potential biomarker for predicting elevated amyloid in the brain. Utilizing blood testing over PET imaging may improve screening efficiency into clinical trials.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Biomarkers; Cross-Sectional Studies; Humans; Peptide Fragments; Positron-Emission Tomography

Excessive Sedentary Time Is Associated with Cognitive Decline in Older Patients with Minor Ischemic Stroke. - Liang, Hongtao; Yin, Xiang; Chen, Tian; Zhang, Yan; Zhang, Qin; Lin, Jie; Yin, Huan; Tang, Jinghua; He, Yingyi; Xia, Ping; Zhu, Yongping; Li, Haihua; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Cognitive impairment is commonly seen after acute ischemic stroke (AIS). Sedentary behaviors increase the risk of dementia among community dwelling population. OBJECTIVE: This study aims to investigate the association of sedentary behaviors with poststroke cognitive impairment among older adults of minor AIS. METHODS: This cohort study recruited 594 older subjects with minor AIS from three hospitals in China during February 1, 2016, and December 31, 2018. Participants were followed up for two years and the sedentary time per day was self-reported at the endpoint of follow-up. Cognitive functions were assessed by Mini-Mental State Examination (MMSE). Participants were categorized into the high and low sedentary time group according to the median sedentary time of the participants. RESULTS: At two years of follow-up, the long sedentary time group had significantly lower MMSE scores than the short sedentary time group [median, (95% CI): 21 (18 to 25) versus 22 (18 to 25), p = 0.368]. The long sedentary time group had a higher speed of cognitive decline than the short sedentary time group. Excessive sedentary time was associated with a higher risk of longitudinal cognitive decline (OR: 2.267, 95% CI: 1.594 to 3.225), adjusting for age, sex, education, body mass index, APOE genotype, comorbidities, symptoms of depression, anxiety, and insomnia, baseline MMSE scores and National Institute of Health Stroke Scale scores, cognitive therapy, and TOAST ischemic stroke subtypes. CONCLUSIONS: This study identified a possible link between sedentary behaviors and longitudinal cognitive decline among older patients with minor AIS, suggesting that reducing sedentary time might be helpful for preventing poststroke dementia.

Exposure to World Trade Center Dust Exacerbates Cognitive Impairment and Evokes a Central and Peripheral Pro-Inflammatory Transcriptional Profile in an Animal Model of Alzheimer's Disease. - Iban-Arias, Ruth; Trageser, Kyle J; Yang, Eun-Jeong; Griggs, Elizabeth; Radu, Aurelian; Naughton, Sean; Al Rahim, Md; Tatsunori, Oguchi; Raval, Urdhva; Palmieri, Joshua; Huang, Zerlina; Chen, Lung-Chi; et al. (J Alzheimers Dis, 2023)
BACKGROUND: The terrorist attacks on September 11, 2001, on the World Trade Center (WTC) led to intense fires and a massive dense cloud of toxic gases and suspended pulverized debris. In the subsequent years, following the attack and cleanup efforts, a cluster of chronic health conditions emerged among First Responders (FR) who were at Ground Zero for prolonged periods and were repeatedly exposed to high levels of WTC particulate matter (WTCPM). Among those are neurological complications which may increase the risk for the development of Alzheimer's disease (AD) later in life. OBJECTIVE: We hypothesize that WTCPM dust exposure affects the immune cross-talking between the periphery and central nervous systems that may induce brain permeability ultimately promoting AD-type phenotype. METHODS: 5XFAD and wild-type mice were intranasally administered with WTCPM dust collected at Ground Zero within 72 h after the attacks. Y-maze assay and novel object recognition behavioral tests were performed for working memory deficits and learning and recognition memory, respectively. Transcriptomic analysis in the blood and hippocampus was performed and confirmed by RT qPCR. RESULTS: Mice exposed to WTCPM dust exhibited a significant impairment in spatial and recognition short and long-term memory. Furthermore, the transcriptomic analysis in the hippocampal formation and blood revealed significant changes in genes related to immune-inflammatory responses, and blood-brain barrier disruption. CONCLUSION: These studies suggest a putative peripheral-brain immune inflammatory cross-talking that may potentiate cognitive decline, identifying for the first time key steps which may be therapeutically targetable in future studies in WTC FR.
Keywords: Alzheimer Disease; Animals; Cognitive Dysfunction; Dust; Mice; Models, Animal; September 11 Terrorist Attacks

Impact of Hearing Aids on Progression of Cognitive Decline, Depression, and Quality of Life Among People with Cognitive Impairment and Dementia. - Atef, Roaa Zayed; Michalowsky, Bernhard; Raedke, Anika; Platen, Moritz; Mohr, Wiebke; Mühlichen, Franka; Thyrian, Jochen René; Hoffmann, Wolfgang (J Alzheimers Dis, 2023)
BACKGROUND: Hearing loss is common in people with dementia (PwD) and a modifiable risk factor for cognitive decline. Recent studies revealed that hearing loss could cause social isolation and depression, which is associated with health-related quality of life (HRQoL). However, there is a lack of knowledge about the impact of the utilization of hearing aids on these outcomes. OBJECTIVE: To assess whether hearing aids use might be positively associated with the progression of cognitive function, depression, and HRQoL among PwD. METHODS: We analyzed two-year follow-up data from 258 PwD (≥70 years, living at home). Cognitive decline was measured with Mini-Mental Status Examination (MMSE), depression using Geriatric Depression Scale (GDS), and HRQoL with Quality of Life in Alzheimer's Disease Scale (QoL-AD). The impact of hearing aid utilization on the progression of outcomes was assessed using multivariate regression models. RESULTS: 123 patients had hearing loss (47.7%), from which n = 54 (43.9%) used hearing aids. Patients with hearing loss were older and had a lower HRQoL than those without hearing loss. Use of hearing aids in patients with hearing loss was associated with a lower increase in depressive symptoms (b = -0.74, CI95 -1.48 --0.01, p = 0.047) over time as compared to those not using hearing aids. There was no effect on PwD's cognition, and the association with higher HRQoL was significant after one, but not consistently over two years. CONCLUSION: Early detection and intervention of presbycusis using hearing aids might improve mental health and HRQoL in dementia.
Keywords: Aged; Cognitive Dysfunction; Deafness; Dementia; Depression; Hearing Aids; Humans; Presbycusis; Quality of Life

The Impact of Routine Vaccinations on Alzheimer's Disease Risk in Persons 65 Years and Older: A Claims-Based Cohort Study using Propensity Score Matching. - Harris, Kristofer; Ling, Yaobin; Bukhbinder, Avram S; Chen, Luyao; Phelps, Kamal N; Cruz, Gabriela; Thomas, Jenna; Kim, Yejin; Jiang, Xiaoqian; Schulz, Paul E (J Alzheimers Dis, 2023)
BACKGROUND: Accumulating evidence suggests that adult vaccinations can reduce the risk of developing Alzheimer's disease (AD) and Alzheimer's disease related dementias. OBJECTIVE: To compare the risk for developing AD between adults with and without prior vaccination against tetanus and diphtheria, with or without pertussis (Tdap/Td); herpes zoster (HZ); or pneumococcus. METHODS: A retrospective cohort study was performed using Optum's de-identified Clinformatics® Data Mart Database. Included patients were free of dementia during a 2-year look-back period and were≥65 years old by the start of the 8-year follow-up period. We compared two similar cohorts identified using propensity score matching (PSM), one vaccinated and another unvaccinated, with Tdap/Td, HZ, or pneumococcal vaccines. We calculated the relative risk (RR) and absolute risk reduction (ARR) for developing AD. RESULTS: For the Tdap/Td vaccine, 7.2% (n = 8,370) vaccinated patients and 10.2% (n = 11,857) unvaccinated patients developed AD during follow-up; the RR was 0.70 (95% CI, 0.68-0.72) and ARR was 0.03 (95% CI, 0.02-0.03). For the HZ vaccine, 8.1% (n = 16,106) vaccinated patients and 10.7% (n = 21,273) unvaccinated patients developed AD during follow-up; the RR was 0.75 (95% CI, 0.73-0.76) and ARR was 0.02 (95% CI, 0.02-0.02). For the pneumococcal vaccine, 7.92% (n = 20,583) vaccinated patients and 10.9% (n = 28,558) unvaccinated patients developed AD during follow-up; the RR was 0.73 (95% CI, 0.71-0.74) and ARR was 0.02 (95% CI, 0.02-0.03). CONCLUSION: Several vaccinations, including Tdap/Td, HZ, and pneumococcal, are associated with a reduced risk for developing AD.

Impaired Early Insulin Response to Glucose Load Predicts Episodic Memory Decline: A 10-Year Population-Based Cohort Follow-Up of 45-74-Year-Old Men and Women. - Toppala, Sini; Ekblad, Laura L; Viitanen, Matti; Rinne, Juha O; Jula, Antti (J Alzheimers Dis, 2023)
BACKGROUND: Diabetes increases the risk for cognitive decline, but the mechanisms behind this association remain unknown. Impaired early insulin secretion in elderly men and insulin resistance, both of which are pathophysiological features of type 2 diabetes, have previously been linked to Alzheimer's disease. OBJECTIVE: To examine if the early insulin response to oral glucose load predicts cognitive performance after 10 years in men and women aged 45-74 years. METHODS: This study was based on a subpopulation of the Health 2000 Survey, a Finnish nationwide, population-based health examination study, and its follow-up, the Health 2011 Study. In total, 961 45-74-year-old individuals (mean age at baseline 55.6 years, 55.8% women) were examined. An oral glucose tolerance test was performed in 2001-2002, and early insulin response was defined as the ratio of the 30-min increment in insulin concentration to that of glucose concentration. Cognitive function was evaluated at baseline and follow-up with categorical verbal fluency, word-list learning, and word-list delayed recall. Statistical analyses were performed using multivariable linear models adjusted for age, sex, education, APOE&z.epsi;4 genotype, vascular risk factors including diabetes, and depressive symptoms. RESULTS: A lower early insulin response to glucose load predicted lower performance (β: 0.21, p = 0.03) and greater decline (β: 0.19, p = 0.03) in the word-list delayed recall test. Baseline early insulin response did not predict verbal fluency or word-list learning (all p-values≥0.13). CONCLUSION: Our results suggest that decreased early insulin secretion predicts episodic memory decline in middle-aged to elderly men and women.

Longitudinal White and Gray Matter Response to Precision Medicine-Guided Intervention for Alzheimer's Disease. - Chwa, Won Jong; Raji, Cyrus A; Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Jarrett, Michael; Bredesen, Dale E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a debilitating condition that is widely known to adversely affect gray matter (GM) and white matter (WM) tracts within the brain. Recently, precision medicine has shown promise in alleviating the clinical and gross morphological trajectories of patients with AD. However, regional morphological changes have not yet been adequately characterized. OBJECTIVE: Investigate regional morphological responses to a precision medicine-guided intervention with regards to white and gray matter in AD and mild cognitive impairment (MCI). METHODS: Clinical and neuroimaging data were compiled over a 9-month period from 25 individuals who were diagnosed with AD or MCI receiving individualized treatment plans. Structural T1-weighted MRI scans underwent segmentation and volumetric quantifications via Neuroreader. Longitudinal changes were calculated via annualized percent change of WM or GM ratios. RESULTS: Montreal Cognitive Assessment scores (p < 0.001) and various domains of the Computerized Neurocognitive Screening Vital Signs significantly improved from baseline to 9-month follow-up. There was regional variability in WM and GM atrophy or hypertrophy, but none of these observed changes were statistically significant after correction for multiple comparisons.
Keywords: Alzheimer Disease; Atrophy; Brain; Cognitive Dysfunction; Gray Matter; Humans; Magnetic Resonance Imaging; Precision Medicine; White Matter

Machine Learning Selection of Most Predictive Brain Proteins Suggests Role of Sugar Metabolism in Alzheimer's Disease. - Tandon, Raghav; Levey, Allan I; Lah, James J; Seyfried, Nicholas T; Mitchell, Cassie S (J Alzheimers Dis, 2023)
BACKGROUND: The complex and not yet fully understood etiology of Alzheimer's disease (AD) shows important proteopathic signs which are unlikely to be linked to a single protein. However, protein subsets from deep proteomic datasets can be useful in stratifying patient risk, identifying stage dependent disease markers, and suggesting possible disease mechanisms. OBJECTIVE: The objective was to identify protein subsets that best classify subjects into control, asymptomatic Alzheimer's disease (AsymAD), and AD. METHODS: Data comprised 6 cohorts; 620 subjects; 3,334 proteins. Brain tissue-derived predictive protein subsets for classifying AD, AsymAD, or control were identified and validated with label-free quantification and machine learning. RESULTS: A 29-protein subset accurately classified AD (AUC = 0.94). However, an 88-protein subset best predicted AsymAD (AUC = 0.85) or Control (AUC = 0.89) from AD (AUC = 0.96). AD versus Control: APP, DHX15, NRXN1, PBXIP1, RABEP1, STOM, and VGF. AD versus AsymAD: ALDH1A1, BDH2, C4A, FABP7, GABBR2, GNAI3, PBXIP1, and PKAR1B. AsymAD versus Control: APP, C4A, DMXL1, EXOC2, PITPNB, REBEP1, and VGF. Additional predictors: DNAJA3, PTBP2, SLC30A9, VAT1L, CROCC, PNP, SNCB, PRKAR1B, ENPP6, HAPLN2, PSMD4, and CMAS. CONCLUSION: Biomarkers were dynamically separable across disease stages. Predictive proteins were significantly enriched to sugar metabolism.

Medial Temporal Lobe Atrophy in Predementia Alzheimer's Disease: A Longitudinal Multi-Site Study Comparing Staging and A/T/N in a Clinical Research Cohort. - Jarholm, Jonas Alexander; Bjørnerud, Atle; Dalaker, Turi Olene; Akhavi, Mehdi Sadat; Kirsebom, Bjørn Eivind; Pålhaugen, Lene; Nordengen, Kaja; Grøntvedt, Gøril Rolfseng; Nakling, Arne; Kalheim, Lisa F; Almdahl, Ina S; Tecelao, Sandra; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Atrophy of the medial temporal lobe (MTL) is a biological characteristic of Alzheimer's disease (AD) and can be measured by segmentation of magnetic resonance images (MRI). OBJECTIVE: To assess the clinical utility of automated volumetry in a cognitively well-defined and biomarker-classified multi-center longitudinal predementia cohort. METHODS: We used Automatic Segmentation of Hippocampal Subfields (ASHS) to determine MTL morphometry from MRI. We harmonized scanner effects using the recently developed longitudinal ComBat. Subjects were classified according to the A/T/N system, and as normal controls (NC), subjective cognitive decline (SCD), or mild cognitive impairment (MCI). Positive or negative values of A, T, and N were determined by cerebrospinal fluid measurements of the Aβ42/40 ratio, phosphorylated and total tau. From 406 included subjects, longitudinal data was available for 206 subjects by stage, and 212 subjects by A/T/N. RESULTS: Compared to A-/T-/N- at baseline, the entorhinal cortex, anterior and posterior hippocampus were smaller in A+/T+orN+. Compared to NC A- at baseline, these subregions were also smaller in MCI A+. Longitudinally, SCD A+ and MCI A+, and A+/T-/N- and A+/T+orN+, had significantly greater atrophy compared to controls in both anterior and posterior hippocampus. In the entorhinal and parahippocampal cortices, longitudinal atrophy was observed only in MCI A+ compared to NC A-, and in A+/T-/N- and A+/T+orN+ compared to A-/T-/N-. CONCLUSION: We found MTL neurodegeneration largely consistent with existing models, suggesting that harmonized MRI volumetry may be used under conditions that are common in clinical multi-center cohorts.
Keywords: Alzheimer Disease; Atrophy; Cognitive Dysfunction; Entorhinal Cortex; Hippocampus; Humans; Magnetic Resonance Imaging; Temporal Lobe

Mediation Effect of Brain Volume on the Relationship Between Peripheral Inflammation and Cognitive Decline. - Zhuo, Bingting; Zheng, Dashan; Cai, Miao; Wang, Chongjian; Zhang, Shiyu; Zhang, Zilong; Tian, Fei; Wang, Xiaojie; Lin, Hualiang (J Alzheimers Dis, 2023)
BACKGROUND: Studies have reported the associations between inflammation, brain volume, and cognition separately. It is reasonable to assume peripheral inflammation may contribute to cognitive decline through brain volume atrophy. OBJECTIVE: To examine the associations between peripheral inflammation, brain volume, and cognition among adults, and to investigate whether brain volume atrophy mediates the inflammation-cognition relationshipMethods:We retrieved 20,381 participants with available data on peripheral inflammation, brain volume, and cognition from the UK Biobank cohort. Cognitive function was assessed by performance on cognitive tasks probing various cognitive domains. Brain volumes were measured by magnetic resonance imaging (MRI). Multivariable linear models were used to investigate the associations between three peripheral inflammatory indexes (C-reactive protein, systemic immune-inflammatory index, neutrophil-to-lymphocyte ratio), brain volume, and cognition. Mediation analyses were conducted to assess the potential mediating effect of brain volume atrophy. All results were corrected for multiple comparisons using the false-discovery rate (FDR). RESULTS: Peripheral inflammation was inversely associated with grey matter volume (GMV), white matter volume (WMV), and cognition after adjusting for potential covariates. For instance, CRP was associated with the GMV of left parahippocampal gyrus (β= -0.05, 95% confidence interval [CI]: -0.06 to -0.04, pFDR =1.07×10-16) and general cognitive factor (β= -0.03, 95% CI: -0. -0.04 to -0.01, pFDR = 0.001). Brain volume atrophy mediated the inflammation-cognitive decline relationship, accounting for 15-29% of the overall impact. CONCLUSION: In this cohort study, peripheral inflammation was associated with brain volume atrophy and cognitive decline. Brain atrophy may mediate the inflammation-cognitive decline relationship.
Keywords: Atrophy; Brain; Cognition; Cognitive Dysfunction; Cohort Studies; Encephalitis; Humans; Inflammation; Magnetic Resonance Imaging

Montreal Cognitive Assessment in Mild Cognitive Impairment: Relationship with Cerebrospinal Fluid Biomarkers and Conversion to Dementia. - Bernardes, Catarina; Lima, Marisa; Duro, Diana; Silva-Spínola, Anuschka; Durães, João; Tábuas-Pereira, Miguel; Baldeiras, Ines; Freitas, Sandra; Santana, Isabel (J Alzheimers Dis, 2023)
BACKGROUND: Mild cognitive impairment (MCI) is considered a prodromal state of dementia. Abnormal values of cerebrospinal fluid Alzheimer's disease biomarkers (CSF-AD-b) have been associated with a higher risk of conversion to dementia (due to Alzheimer's disease), but studies evaluating the ability of Montreal Cognitive Assessment (MoCA) in this task are lacking. OBJECTIVE: This study aims to investigate the relationship between MoCA and CSF-AD-b, as well as the ability of those tools to predict conversion to dementia. METHODS: Taking advantage of our MCI cohort with biological characterization on longitudinal follow-up (180 patients followed for 62.6 months during which 41.3% converted), we computed MoCA and MMSE z-scores, using Portuguese normative data. The performance in MoCA z-score was correlated with CSF-AD-b and the relative time to conversion and risk according to baseline characteristics were analyzed using Kaplan-Meier analysis and Cox regression models. RESULTS: MoCA z-scores were correlated with Aβ42 (p = 0.026), t-tau (p = 0.033), and p-tau (p = 0.01). Impaired MMSE (p < 0.001) and MoCA z-scores (p = 0.019), decreased Aβ42 (p < 0.001) and increased t-tau (p < 0.001) and p-tau (p < 0.001) were associated with shorter estimated time of conversion. Aβ42 (p < 0.001) and MMSE z-scores (p = 0.029) were independent predictors of conversion. For those with at least 9 years of education, MoCA z-score (p = 0.004) (but not MMSE) was an independent predictor of conversion as well as Aβ42. CONCLUSIONS: This study confirms the role of CSF-AD-b, namely Aβ42, in predicting conversion from MCI to dementia and suggests the utility of MoCA in predicting conversion in highly educated subjects, supporting its use in the evaluation of MCI patients.

Moral Emotions and Their Brain Structural Correlates Across Neurodegenerative Disorders. - Baez, Sandra; Trujillo-Llano, Catalina; de Souza, Leonardo Cruz; Lillo, Patricia; Forno, Gonzalo; Santamaría-García, Hernando; Okuma, Cecilia; Alegria, Patricio; Huepe, David; Ibáñez, Agustín; Decety, Jean; Slachevsky, Andrea (J Alzheimers Dis, 2023)
BACKGROUND: Although social cognition is compromised in patients with neurodegenerative disorders such as behavioral variant frontotemporal dementia (bvFTD) and Alzheimer's disease (AD), research on moral emotions and their neural correlates in these populations is scarce. No previous study has explored the utility of moral emotions, compared to and in combination with classical general cognitive state tools, to discriminate bvFTD from AD patients. OBJECTIVE: To examine self-conscious (guilt and embarrassment) and other-oriented (pity and indignation) moral emotions, their subjective experience, and their structural brain underpinnings in bvFTD (n = 31) and AD (n = 30) patients, compared to healthy controls (n = 37). We also explored the potential utility of moral emotions measures to discriminate bvFTD from AD. METHODS: We used a modified version of the Moral Sentiment Task measuring the participants' accuracy scores and their emotional subjective experiences. RESULTS: bvFTD patients exhibited greater impairments in self-conscious and other-oriented moral emotions as compared with AD patients and healthy controls. Moral emotions combined with general cognitive state tools emerged as useful measures to discriminate bvFTD from AD patients. In bvFTD patients, lower moral emotions scores were associated with lower gray matter volumes in caudate nucleus and inferior and middle temporal gyri. In AD, these scores were associated with lower gray matter volumes in superior and middle frontal gyri, middle temporal gyrus, inferior parietal lobule and supramarginal gyrus. CONCLUSION: These findings contribute to a better understanding of moral emotion deficits across neurodegenerative disorders, highlighting the potential benefits of integrating this domain into the clinical assessment.
Keywords: Alzheimer Disease; Brain; Emotions; Frontotemporal Dementia; Humans; Magnetic Resonance Imaging; Morals; Neuropsychological Tests

Multi-Site Cross-Site Inter-Rater and Test-Retest Reliability and Construct Validity of the MarkVCID White Matter Hyperintensity Growth and Regression Protocol. - Bahrani, Ahmed A; Abner, Erin L; DeCarli, Charles S; Barber, Justin M; Sutton, Abigail C; Maillard, Pauline; Sandoval, Francisco; Arfanakis, Konstantinos; Yang, Yung-Chuan; Evia, Arnold M; Schneider, Julie A; Habes, Mohamad; et al. (J Alzheimers Dis, 2023)
BACKGROUND: White matter hyperintensities (WMH) that occur in the setting of vascular cognitive impairment and dementia (VCID) may be dynamic increasing or decreasing volumes or stable over time. Quantifying such changes may prove useful as a biomarker for clinical trials designed to address vascular cognitive-impairment and dementia and Alzheimer's Disease. OBJECTIVE: Conducting multi-site cross-site inter-rater and test-retest reliability of the MarkVCID white matter hyperintensity growth and regression protocol. METHODS: The NINDS-supported MarkVCID Consortium evaluated a neuroimaging biomarker developed to track WMH change. Test-retest and cross-site inter-rater reliability of the protocol were assessed. Cognitive test scores were analyzed in relation to WMH changes to explore its construct validity. RESULTS: ICC values for test-retest reliability of WMH growth and regression were 0.969 and 0.937 respectively, while for cross-site inter-rater ICC values for WMH growth and regression were 0.995 and 0.990 respectively. Word list long-delay free-recall was negatively associated with WMH growth (p < 0.028) but was not associated with WMH regression. CONCLUSIONS: The present data demonstrate robust ICC validity of a WMH growth/regression protocol over a one-year period as measured by cross-site inter-rater and test-retest reliability. These data suggest that this approach may serve an important role in clinical trials of disease-modifying agents for VCID that may preferentially affect WMH growth, stability, or regression.

Pathological and Therapeutic Advances in Parkinson's Disease: Mitochondria in the Interplay. - Naren, Padmashri; Cholkar, Anjali; Kamble, Suchita; Khan, Sabiya Samim; Srivastava, Saurabh; Madan, Jitender; Mehra, Neelesh; Tiwari, Vinod; Singh, Shashi Bala; Khatri, Dharmendra Kumar (J Alzheimers Dis, 2023)
Parkinson's disease (PD) is the second most common neurodegenerative illness majorly affecting the population between the ages of 55 to 65 years. Progressive dopaminergic neuronal loss and the collective assemblage of misfolded alpha-synuclein in the substantia nigra, remain notable neuro-pathological hallmarks of the disease. Multitudes of mechanistic pathways have been proposed in attempts to unravel the pathogenesis of PD but still, it remains elusive. The convergence of PD pathology is found in organelle dysfunction where mitochondria remain a major contributor. Mitochondrial processes like bioenergetics, mitochondrial dynamics, and mitophagy are under strict regulation by the mitochondrial genome and nuclear genome. These processes aggravate neurodegenerative activities upon alteration through neuroinflammation, oxidative damage, apoptosis, and proteostatic stress. Therefore, the mitochondria have grabbed a central position in the patho-mechanistic exploration of neurodegenerative diseases like PD. The management of PD remains a challenge to physicians to date, due to the variable therapeutic response of patients and the limitation of conventional chemical agents which only offer symptomatic relief with minimal to no disease-modifying effect. This review describes the patho-mechanistic pathways involved in PD not only limited to protein dyshomeostasis and oxidative stress, but explicit attention has been drawn to exploring mechanisms like organelle dysfunction, primarily mitochondria and mitochondrial genome influence, while delineating the newer exploratory targets such as GBA1, GLP, LRRK2, and miRNAs and therapeutic agents targeting them.
Keywords: Aged; alpha-Synuclein; Humans; Mitochondria; Oxidative Stress; Parkinson Disease

Phonological and Semantic Fluency in Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Olmos-Villaseñor, Rocio; Sepulveda-Silva, Consuelo; Julio-Ramos, Teresa; Fuentes-Lopez, Eduardo; Toloza-Ramirez, David; Santibañez, Rodrigo A; Copland, David A; Mendez-Orellana, Carolina (J Alzheimers Dis, 2023)
BACKGROUND: Semantic and Phonological fluency (SF and PF) are routinely evaluated in patients with Alzheimer's disease (AD). There are disagreements in the literature regarding which fluency task is more affected while developing AD. Most studies focus on SF assessment, given its connection with the temporoparietal amnesic system. PF is less reported, it is related to working memory, which is also impaired in probable and diagnosed AD. Differentiating between performance on these tasks might be informative in early AD diagnosis, providing an accurate linguistic profile. OBJECTIVE: Compare SF and PF performance in healthy volunteers, volunteers with probable AD, and patients with AD diagnosis, considering the heterogeneity of age, gender, and educational level variables. METHODS: A total of 8 studies were included for meta-analysis, reaching a sample size of 1,270 individuals (568 patients diagnosed with AD, 340 with probable AD diagnosis, and 362 healthy volunteers). RESULTS: The three groups consistently performed better on SF than PF. When progressing to a diagnosis of AD, we observed a significant difference in SF and PF performance across our 3 groups of interest (p = 0.04). The age variable explained a proportion of this difference in task performance across the groups, and as age increases, both tasks equally worsen. CONCLUSION: The performance of SF and PF might play a differential role in early AD diagnosis. These tasks rely on partially different neural bases of language processing. They are thus worth exploring independently in diagnosing normal aging and its transition to pathological stages, including probable and diagnosed AD.
Keywords: Alzheimer Disease; Humans; Linguistics; Neuropsychological Tests; Semantics; Verbal Behavior

Plasma Amyloid-β Homeostasis Is Associated with Body Mass Index and Weight Loss in People with Overweight and Obesity. - Brook, Emily S; D'Alonzo, Zachary J; Lam, Virginie; Chan, Dick; Dhaliwal, Satvinder Singh; Watts, Geraldb F; Mamo, John C L; Takechi, Ryusuke (J Alzheimers Dis, 2023)
BACKGROUND: Obesity is linked to a higher incidence of Alzheimer's disease (AD). Studies show that plasma amyloid-β (Aβ) dyshomeostasis, particularly low 42/40 ratio indicates a heightened risk for developing AD. However, the relationship between body mass index (BMI) and circulating plasma Aβ has not been extensively studied. OBJECTIVE: We hypothesized that people with a high BMI have altered plasma Aβ homeostasis compared with people with a lower BMI. We also tested whether reducing BMI by calorie-restriction could normalize plasma concentrations of Aβ. METHODS: Plasma concentrations of Aβ 40, Aβ 42, and Aβ 42/40 ratio were measured in 106 participants with BMIs classified as lean, overweight, or obese. From this cohort, twelve participants with overweight or obese BMIs entered a 12-week calorie-restriction weight loss program. We then tested whether decreasing BMI affected plasma Aβ concentrations. RESULTS: Plasma Aβ 42/40 ratio was 17.54% lower in participants with an obese BMI compared to lean participants (p <  0.0001), and 11.76% lower compared to participants with an overweight BMI (p <  0.0001). The weight loss regimen decreased BMI by an average of 4.02% (p = 0.0005) and was associated with a 6.5% decrease in plasma Aβ 40 (p = 0.0425). However, weight loss showed negligible correlations with plasma Aβ 40, Aβ 42, and Aβ 42/40 ratio. CONCLUSION: Obesity is associated with aberrant plasma Aβ homeostasis which may be associated with an increased risk for AD. Weight loss appears to lower Aβ 40, but large-scale longitudinal studies in addition to molecular studies are required to elucidate the underlying mechanisms of how obesity and weight loss influence plasma Aβ homeostasis.

Plasma ApoE4 Levels Are Lower than ApoE2 and ApoE3 Levels, and Not Associated with Plasma Aβ 40/42 Ratio as a Biomarker of Amyloid-β Amyloidosis in Alzheimer's Disease. - Nakamura, Takumi; Kawarabayashi, Takeshi; Ueda, Tetsuya; Shimomura, Sachiko; Hoshino, Masaki; Itoh, Ken; Ihara, Kazushige; Nakaji, Shigeyuki; Takatama, Masamitsu; Ikeda, Yoshio; Shoji, Mikio (J Alzheimers Dis, 2023)
BACKGROUND: APOE4 is the strongest risk factor for Alzheimer's disease (AD). However, limited information is currently available on APOE4 and the pathological role of plasma apolipoprotein E (ApoE) 4 remains unclear. OBJECTIVE: The aims of the present study were to measure plasma levels of total ApoE (tE), ApoE2, ApoE3, and ApoE4 using mass spectrometry and elucidate the relationships between plasma ApoE and blood test items. METHODS: We herein examined plasma levels of tE, ApoE2, ApoE3, and ApoE4 in 498 subjects using liquid chromatograph-mass spectrometry (LC-MS/MS). RESULTS: Among 498 subjects, mean age was 60 years and 309 were female. tE levels were distributed as ApoE2/E3 = ApoE2/E4 >ApoE3/E3 = ApoE3/E4 >ApoE4/E4. In the heterozygous group, ApoE isoform levels were distributed as ApoE2 >ApoE3 >ApoE4. ApoE levels were not associated with aging, the plasma amyloid-β (Aβ) 40/42 ratio, or the clinical diagnosis of AD. Total cholesterol levels correlated with the level of each ApoE isoform. ApoE2 levels were associated with renal function, ApoE3 levels with low-density lipoprotein cholesterol and liver function, and ApoE4 levels with triglycerides, high-density lipoprotein cholesterol, body weight, erythropoiesis, and insulin metabolism. CONCLUSION: The present results suggest the potential of LC-MS/MS for the phenotyping and quantitation of plasma ApoE. Plasma ApoE levels are regulated in the order of ApoE2 >ApoE3 >ApoE4 and are associated with lipids and multiple metabolic pathways, but not directly with aging or AD biomarkers. The present results provide insights into the multiple pathways by which peripheral ApoE4 influences the progression of AD and atherosclerosis.

Plasma Glial Fibrillary Acidic Protein Is Associated with 18F-SMBT-1 PET: Two Putative Astrocyte Reactivity Biomarkers for Alzheimer's Disease. - Chatterjee, Pratishtha; Doré, Vincent; Pedrini, Steve; Krishnadas, Natasha; Thota, Rohith; Bourgeat, Pierrick; Ikonomovic, Milos D; Rainey-Smith, Stephanie R; Burnham, Samantha C; Fowler, Christopher; Taddei, Kevin; Mulligan, Rachel; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Astrocyte reactivity is an early event along the Alzheimer's disease (AD) continuum. Plasma glial fibrillary acidic protein (GFAP), posited to reflect astrocyte reactivity, is elevated across the AD continuum from preclinical to dementia stages. Monoamine oxidase-B (MAO-B) is also elevated in reactive astrocytes observed using 18F-SMBT-1 PET in AD. OBJECTIVE: The objective of this study was to evaluate the association between the abovementioned astrocyte reactivity biomarkers. METHODS: Plasma GFAP and Aβ were measured using the Simoa® platform in participants who underwent brain 18F-SMBT-1 and Aβ-PET imaging, comprising 54 healthy control (13 Aβ-PET+ and 41 Aβ-PET-), 11 mild cognitively impaired (3 Aβ-PET+ and 8 Aβ-PET-) and 6 probable AD (5 Aβ-PET+ and 1 Aβ-PET-) individuals. Linear regressions were used to assess associations of interest. RESULTS: Plasma GFAP was associated with 18F-SMBT-1 signal in brain regions prone to early Aβ deposition in AD, such as the supramarginal gyrus (SG), posterior cingulate (PC), lateral temporal (LT) and lateral occipital cortex (LO). After adjusting for age, sex, APOE ɛ4 genotype, and soluble Aβ (plasma Aβ42/40 ratio), plasma GFAP was associated with 18F-SMBT-1 signal in the SG, PC, LT, LO, and superior parietal cortex (SP). On adjusting for age, sex, APOE ɛ4 genotype and insoluble Aβ (Aβ-PET), plasma GFAP was associated with 18F-SMBT-1 signal in the SG. CONCLUSION: There is an association between plasma GFAP and regional 18F-SMBT-1 PET, and this association appears to be dependent on brain Aβ load.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Brain; Cognitive Dysfunction; Glial Fibrillary Acidic Protein; Humans; Positron-Emission Tomography; tau Proteins

Plasma Soluble ST2 Levels Are Higher in Neurodegenerative Disorders and Associated with Poorer Cognition. - Tan, Yi Jayne; Siow, Isabel; Saffari, Seyed Ehsan; Ting, Simon K S; Li, Zeng; Kandiah, Nagaendran; Tan, Louis C S; Tan, Eng King; Ng, Adeline S L (J Alzheimers Dis, 2023)
BACKGROUND: Suppressor of tumorgenicity 2 (ST2) is highly expressed in brain tissue and is a receptor for interleukin 33 (IL-33). ST2 exists in two forms, a transmembrane receptor (ST2L) and a soluble decoy receptor (sST2). IL-33 binds to ST2L, triggering downstream signaling pathways involved in amyloid plaque clearance. Conversely, sST2 binds competitively to IL-33, attenuating its neuroprotective effects. High sST2 levels have been reported in mild cognitive impairment (MCI) and Alzheimer's disease (AD), suggesting that the IL-33/ST2 signaling pathway may be implicated in neurodegenerative diseases. OBJECTIVE: To investigate plasma sST2 levels in controls and patients with MCI, AD, frontotemporal dementia (FTD), and Parkinson's disease (PD). METHODS: Plasma sST2 levels were measured using ELISA in 397 subjects (91 HC, 46 MCI, 38 AD, 28 FTD, and 194 PD). Cerebrospinal fluid (CSF) levels of sST2 were measured in 22 subjects. Relationship between sST2 and clinical outcomes were analyzed. RESULTS: Plasma sST2 levels were increased across all disease groups compared to controls, with highest levels seen in FTD followed by AD and PD. Dementia patients with higher sST2 had lower cross-sectional cognitive scores in Frontal Assessment Battery and Digit Span Backward. At baseline, PD-MCI patients had higher sST2, associated with worse attention. In the longitudinal PD cohort, higher sST2 significantly associated with decline in global cognition and visuospatial domains. Plasma sST2 levels correlated with CSF sST2 levels. CONCLUSION: Plasma sST2 is raised across neurodegenerative diseases and is associated with poorer cognition. Higher baseline sST2 is a potential biomarker of disease severity in neurodegeneration.
Keywords: Alzheimer Disease; Biomarkers; Cognition; Cross-Sectional Studies; Frontotemporal Dementia; Humans; Interleukin-1 Receptor-Like 1 Protein; Interleukin-33; Parkinson Disease

Post-Translational Chemical Modifications of Amyloid-β Peptides by 4-Hydroxy-2-Nonenal. - Kikuchi, Hiroyuki; Takahashi, Miki; Komatsu, Hiroaki; Axelsen, Paul H (J Alzheimers Dis, 2023)
BACKGROUND: The extraction and quantification of amyloid-β (Aβ) peptides in brain tissue commonly uses formic acid (FA) to disaggregate Aβ fibrils. However, it is not clear whether FA can disaggregate post-translationally modified Aβ peptides, or whether it induces artifact by covalent modification during disaggregation. Of particular interest are Aβ peptides that have been covalently modified by 4-hydroxy-2-nonenal (HNE), an oxidative lipid degradation product produced in the vicinity of amyloid plaques that dramatically accelerates the aggregation of Aβ peptides. OBJECTIVE: Test the ability of FA to disaggregate Aβ peptides modified by HNE and to induce covalent artifacts. METHODS: Quantitative liquid-chromatography-tandem-mass spectrometry of monomeric Aβ peptides and identify covalently modified forms. RESULTS: FA disaggregated ordinary Aβ fibrils but also induced the time-dependent formylation of at least 2 residue side chains in Aβ peptides, as well as oxidation of its methionine side chain. FA was unable to disaggregate Aβ peptides that had been covalently modified by HNE. CONCLUSION: The inability of FA to disaggregate Aβ peptides modified by HNE prevents FA-based approaches from quantifying a pool of HNE-modified Aβ peptides in brain tissue that may have pathological significance.

Precision Medicine Approach to Alzheimer's Disease: Rationale and Implications. - Bredesen, Dale E; Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Raji, Cyrus; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Chwa, Won Jong; Kurakin, Alexei; et al. (J Alzheimers Dis, 2023)
The neurodegenerative disease field has enjoyed extremely limited success in the development of effective therapeutics. One potential reason is the lack of disease models that yield accurate predictions and optimal therapeutic targets. Standard clinical trials have pre-determined a single treatment modality, which may be unrelated to the primary drivers of neurodegeneration. Recent proof-of-concept clinical trials using a precision medicine approach suggest a new model of Alzheimer's disease (AD) as a chronic innate encephalitis that creates a network insufficiency. Identifying and addressing the multiple potential contributors to cognitive decline for each patient may represent a more effective strategy. Here we review the rationale for a precision medicine approach in prevention and treatment of cognitive decline associated with AD. Results and implications from recent proof-of-concept clinical trials are presented. Randomized controlled trials, with much larger patient numbers, are likely to be significant to establishing precision medicine protocols as a standard of care for prevention and treatment of cognitive decline. Furthermore, combining this approach with the pharmaceutical approach offers the potential for enhanced outcomes. However, incorporating precision medicine approaches into everyday evaluation and care, as well as future clinical trials, would require fundamental changes in trial design, IRB considerations, funding considerations, laboratory evaluation, personalized treatment plans, treatment teams, and ultimately in reimbursement guidelines. Nonetheless, precision medicine approaches to AD, based on a novel model of AD pathophysiology, offer promise that has not been realized to date with monotherapeutic approaches.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Neurodegenerative Diseases; Precision Medicine

Soluble TREM2, Alzheimer's Disease Pathology, and Risk for Progression of Cerebral Small Vessel Disease: A Longitudinal Study. - Wu, Chao; Ma, Ya-Hui; Hu, Hao; Zhao, Bing; Tan, Lan (J Alzheimers Dis, 2023)
BackgroundUntil recently, studies on associations between neuroinflammation in vivo and cerebral small vessel disease (CSVD) are scarce. Cerebrospinal fluid (CSF) levels of soluble triggering receptor expressed on myeloid cells 2 (sTREM2), a candidate biomarker of microglial activation and neuroinflammation, were found elevated in Alzheimer's disease (AD), but they have not been fully explored in CSVD.ObjectiveTo determine whether CSF sTREM2 levels are associated with the increased risk of CSVD progression.MethodsA total of 426 individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database were included in this study. All participants underwent measurements of CSF sTREM2 and AD pathology (Aβ1-42, P-tau181P). The progression of CSVD burden and imaging markers, including cerebral microbleeds (CMBs), white matter hyperintensities and lacunes, were estimated based on neuroimaging changes. Logistic regression and moderation effect models were applied to explore associations of sTREM2 with CSVD progression and AD pathology.Results Higher CSF sTREM2 levels at baseline were associated with increased CSVD burden (OR = 1.28 [95% CI, 1.01-1.62]) and CMBs counts (OR = 1.32 [95% CI, 1.03-1.68]). Similarly, increased change rates of CSF sTREM2 might predict elevated CMBs counts (OR = 1.44 [95% CI, 1.05-1.98]). Participants with AD pathology (Aβ1-42 and P-tau181P) showed a stronger association between CSF sTREM2 and CSVD progression.ConclusionThis longitudinal study found a positive association between CSF sTREM2 and CSVD progression, suggesting that neuroinflammation might promote CSVD. Furthermore, neuroinflammation could be a shared pathogenesis of CSVD and AD at the early stage. Targeting neuroinflammation to intervene the progression of CSVD and AD warrants further investigation.
Keywords: Alzheimer Disease; Biomarkers; Cerebral Small Vessel Diseases; Humans; Longitudinal Studies; Membrane Glycoproteins; Myeloid Cells; Neuroinflammatory Diseases; Receptors, Immunologic

TDP-43 Pathology in the Setting of Intermediate and High Alzheimer's Disease Neuropathologic Changes: A Preliminary Evaluation Across Ethnoracial Groups. - Huie, Emily Z; Escudero, Anthony; Saito, Naomi; Harvey, Danielle; Nguyen, My-Le; Lucot, Katherine L; LaGrande, Jayne; Mungas, Dan; DeCarli, Charles; Lamar, Melissa; Schneider, Julie A; Kapasi, Alifiya; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Transactive Response DNA Binding Protein 43 kDa (TDP-43) pathology is frequently found in cases with Alzheimer's disease (AD). TDP-43 pathology is associated with hippocampal atrophy and greater AD severity denoted by cognition and clinical representation. Current TDP-43 pathology studies are predominantly based on non-Hispanic White cohorts. OBJECTIVE: We sought to evaluate the presence of TDP-43 pathology across ethnoracial groups utilizing the National Alzheimer's Coordinating Center; a database containing data from over 29 institutions across the United States. Cases (N = 1,135: Hispanics/Latinos = 29, African Americans/Black Americans = 51, Asians/Asian Americans = 10, American Indians/Alaskan Natives = 2, non-Hispanic White = 1,043) with intermediate/high AD having data on TDP-43 pathology in the amygdala, hippocampus, entorhinal cortex, and neocortex. METHODS: TDP-43 pathology frequency in each neuroanatomic region among ethnoracial groups were compared using generalized linear mixed effects models with center as a random effect adjusting for age at death, education, and gender. RESULTS: Although groups were imbalanced, there was no significant difference across ethnoracial groups based on TDP-43 pathology (p = 0.84). With respect to neuroanatomical regions evaluated, there were no significant differences across ethnoracial groups (p-values > 0.06). There were also no significant differences for age at death and gender ratios across ethnoracial groups based on TDP-43 pathology. Although not statistically significant, TDP-43 pathology was present less often in Hispanic/Latinos (34%) when compared to non-Hispanic Whites (46%). CONCLUSION: While this is a preliminary evaluation, it highlights the need for diverse cohorts and on TDP-43 pathology research across ethnoracial groups. This is the first study to our knowledge having a focus on the neuroanatomical distribution of TDP-43 deposits in Hispanic/Latino decedents with AD.

Timing of Alzheimer's Disease by Intellectual Disability Level in Down Syndrome. - Hartley, Sigan L; Fleming, Victoria; Schworer, Emily K; Peven, Jamie; Handen, Benjamin L; Krinsky-McHale, Sharon; Hom, Christy; Lee, Laisze; Tudorascu, Dana L; Laymon, Charles; Minhas, Davneet; Luo, Weiquan; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Trisomy 21 causes Down syndrome (DS) and is a recognized cause of early-onset Alzheimer's disease (AD). OBJECTIVE: The current study sought to determine if premorbid intellectual disability level (ID) was associated with variability in age-trajectories of AD biomarkers and cognitive impairments. General linear mixed models compared the age-trajectory of the AD biomarkers PET Aβ and tau and cognitive decline across premorbid ID levels (mild, moderate, and severe/profound), in models controlling trisomy type, APOE status, biological sex, and site. METHODS: Analyses involved adults with DS from the Alzheimer's Biomarkers Consortium-Down Syndrome. Participants completed measures of memory, mental status, and visuospatial ability. Premorbid ID level was based on IQ or mental age scores prior to dementia concerns. PET was acquired using [11C] PiB for Aβ, and [18F] AV-1451 for tau. RESULTS: Cognitive data was available for 361 participants with a mean age of 45.22 (SD = 9.92) and PET biomarker data was available for 154 participants. There was not a significant effect of premorbid ID level by age on cognitive outcomes. There was not a significant effect of premorbid ID by age on PET Aβ or on tau PET. There was not a significant difference in age at time of study visit of those with mild cognitive impairment-DS or dementia by premorbid ID level. CONCLUSION: Findings provide robust evidence of a similar time course in AD trajectory across premorbid ID levels, laying the groundwork for the inclusion of individuals with DS with a variety of IQ levels in clinical AD trials.

Two-Year Changes in Physical Activity and Concurrent Changes in Cognitive Function in a Cohort of Adults with Metabolic Syndrome. - Rognoni, Teresa; Fernández-Matarrubia, Marta; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Castañer, Olga; Martínez, J Alfredo; Alonso-Gómez, Ángel M; Gómez-Gracia, Enrique; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; et al. (J Alzheimers Dis, 2023)
BACKGROUND: It has been proposed that physical activity (PA) could prevent cognitive decline. OBJECTIVE: To evaluate the association between changes in PA and changes in cognitive function in a cohort of adults with metabolic syndrome. METHODS: Longitudinal observational study including 5,500 adults (mean age 65 years, SD = 5; women = 49.3%) with metabolic syndrome. Participants underwent physical activity measurements and cognitive evaluation at baseline and at two-years of follow-up. PA was quantified using the Minnesota questionnaire-shortened version. Cognitive function was evaluated using a battery of tests: Mini-Mental Test Examination, Clock Drawing Test, Trail Making Test A and B, Verbal Fluency Test, and Digit Span. The primary outcome was change in cognition at two-year follow-up, as measured through the Global Composite Score (GCS) of all neuropsychological tests. Multivariable-adjusted linear regression models were fitted with baseline PA and their changes as the main exposures and changes in cognitive function as the outcome. RESULTS: No significant association was found between PA levels (or their changes) and changes in cognitive function, as measured by the GCS. A greater increase in PA levels was associated with a more favorable two-year change in performance on the Trail Making Test A (Q4 versus Q1: b = -2.15, 95% CI -4.25 to -0.05; p-trend = 0.024). No significant association was found for other neuropsychological test. CONCLUSION: Our results do not support an association between increases in PA and the evolution of the global cognitive function at two-year follow-up, but they suggested a possible beneficial effect of PA on attentional function in older adults.

Understanding the Involvement of microRNAs in Mitochondrial Dysfunction and Their Role as Potential Biomarkers and Therapeutic Targets in Parkinson's Disease. - Tryphena, Kamatham Pushpa; Anuradha, Urati; Kumar, Rohith; Rajan, Shruti; Srivastava, Saurabh; Singh, Shashi Bala; Khatri, Dharmendra Kumar (J Alzheimers Dis, 2023)
Parkinson's disease (PD) is the second most common neurodegenerative disease, affecting the elderly worldwide and causing significant movement impairments. The goal of PD treatment is to restore dopamine levels in the striatum and regulate movement symptoms. The lack of specific biomarkers for early diagnosis, as well as medication aimed at addressing the pathogenic mechanisms to decelerate the progression of dopaminergic neurodegeneration, are key roadblocks in the management of PD. Various pathogenic processes have been identified to be involved in the progression of PD, with mitochondrial dysfunction being a major contributor to the disease's pathogenesis. The regulation of mitochondrial functions is influenced by a variety of factors, including epigenetics. microRNAs (miRNAs) are epigenetic modulators involved in the regulation of gene expression and regulate a variety of proteins that essential for proper mitochondrial functioning. They are found to be dysregulated in PD, as evidenced by biological samples from PD patients and in vitro and in vivo research. In this article, we attempt to provide an overview of several miRNAs linked to mitochondrial dysfunction and their potential as diagnostic biomarkers and therapeutic targets in PD.
Keywords: Aged; Biomarkers; Humans; MicroRNAs; Mitochondria; Neurodegenerative Diseases; Parkinson Disease

Urinary Amino Acid-Conjugated Acrolein and Taurine as New Biomarkers for Detection of Dementia. - Yoshida, Madoka; Uemura, Takeshi; Mizoi, Mutsumi; Waragai, Masaaki; Sakamoto, Akihiko; Terui, Yusuke; Kashiwagi, Keiko; Igarashi, Kazuei (J Alzheimers Dis, 2023)
BACKGROUND: Dementia, including Alzheimer's disease (AD), is one of the serious diseases at advanced age, and its early detection is important for maintaining quality of life (QOL). OBJECTIVE: In this study, we sought novel biomarkers for dementia in urine. METHODS: Samples of urine were collected from 57 control subjects without dementia, 62 mild cognitive impairment (MCI) patients, and 42 AD patients. Mini-Mental State Examination (MMSE) was evaluated when subjects were examined by medical doctors. Urinary amino acid (lysine)-conjugated acrolein (AC-Acro) was measured using N ɛ -(3-formyl-3, 4-dehydropiperidine) lysine (FDP-Lys) ELISA kit, and taurine content was measured using a taurine assay kit. Values were normalized by creatinine content which was measured with the colorimetric assay kit. RESULTS: We found that urinary amino acid (lysine)-conjugated acrolein (AC-Acro) and taurine negatively correlated with MMSE score and are significantly lower in dementia patients compared to the normal subjects. When AC-Acro and taurine were evaluated together with age using an artificial neural network model, median relative risk values for subjects with AD, subjects with mild cognitive impairment, and control subjects were 0.96, 0.53, and 0.06, respectively. CONCLUSION: Since urine is relatively easy to collect, our findings provide a novel biomarker for dementia without invasiveness.

Alzheimer's Disease Diagnostics Using miRNA Biomarkers and Machine Learning. - Xu, Amy; Kouznetsova, Valentina L; Tsigelny, Igor F (J Alzheimers Dis, 2022)
BACKGROUND: The current standard for Alzheimer's disease (AD) diagnosis is often imprecise, as with memory tests, and invasive or expensive, as with brain scans. However, the dysregulation patterns of miRNA in blood hold potential as useful biomarkers for the non-invasive diagnosis and even treatment of AD. OBJECTIVE: The goal of this research is to elucidate new miRNA biomarkers and create a machine-learning (ML) model for the diagnosis of AD. METHODS: We utilized pathways and target gene networks related to confirmed miRNA biomarkers in AD diagnosis and created multiple models to use for diagnostics based on the significant differences among miRNA expression between blood profiles (serum and plasma). RESULTS: The best performing serum-based ML model, trained on filtered disease-specific miRNA datasets, was able to identify miRNA biomarkers with 92.0% accuracy and the best performing plasma-based ML model, trained on filtered disease-specific miRNA datasets, was able to identify miRNA biomarkers with 90.9% accuracy. Through analysis of AD implicated miRNA, thousands of descriptors reliant on target gene and pathways were created which can then be used to identify novel biomarkers and strengthen disease diagnosis. CONCLUSION: Development of a ML model including miRNA and their genomic and pathway descriptors made it possible to achieve considerable accuracy for the prediction of AD.

Alzheimer's Disease with Epileptiform EEG Activity: Abnormal Cortical Sources of Resting State Delta Rhythms in Patients with Amnesic Mild Cognitive Impairment. - Babiloni, Claudio; Noce, Giuseppe; Di Bonaventura, Carlo; Lizio, Roberta; Eldellaa, Ali; Tucci, Federico; Salamone, Enrico M; Ferri, Raffaele; Soricelli, Andrea; Nobili, Flavio; Famá, Francesco; Arnaldi, Dario; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Patients with amnesic mild cognitive impairment due to Alzheimer's disease (ADMCI) typically show a "slowing" of cortical resting-state eyes-closed electroencephalographic (rsEEG) rhythms. Some of them also show subclinical, non-convulsive, and epileptiform EEG activity (EEA) with an unclear relationship with that "slowing." OBJECTIVE: Here we tested the hypothesis that the "slowing" of rsEEG rhythms is related to EEA in ADMCI patients. METHODS: Clinical and instrumental datasets in 62 ADMCI patients and 38 normal elderly (Nold) subjects were available in a national archive. No participant had received a clinical diagnosis of epilepsy. The eLORETA freeware estimated rsEEG cortical sources. The area under the receiver operating characteristic curve (AUROCC) indexed the accuracy of eLORETA solutions in the classification between ADMCI-EEA and ADMCI-noEEA individuals. RESULTS: EEA was observed in 15% (N = 8) of the ADMCI patients. The ADMCI-EEA group showed: 1) more abnormal Aβ 42 levels in the cerebrospinal fluid as compared to the ADMCI-noEEA group and 2) higher temporal and occipital delta ( CONCLUSION: It can be speculated that in ADMCI-EEA patients, AD-related amyloid neuropathology may be related to an over-excitation in neurophysiological low-frequency (delta) oscillatory mechanisms underpinning cortical arousal and quiet vigilance.

Anticholinergic Drug Burden and Neurocognitive Performance in the Study of Latinos-Investigation of Neurocognitive Aging. - Posis, Alexander Ivan B; Tarraf, Wassim; Gonzalez, Kevin A; Soria-Lopez, Jose A; Léger, Gabriel C; Stickel, Ariana M; Daviglus, Martha L; Lamar, Melissa; Zeng, Donglin; González, Hector M (J Alzheimers Dis, 2022)
BACKGROUND: Studies of cumulative anticholinergic drug burden on cognitive function and impairment are emerging, yet few for Hispanics/Latinos. OBJECTIVE: To examine associations between anticholinergic use and neurocognitive performance outcomes among diverse Hispanics/Latinos. METHODS: This prospective cohort study included diverse Hispanic/Latino participants, enrolled in the Study of Latinos-Investigation of Neurocognitive, from New York, Chicago, Miami, and San Diego (n = 6,249). Survey linear regression examined associations between anticholinergic use (measured during baseline [Visit 1] and average 7-year follow up [Visit 2]) with global cognition, episodic learning, memory, phonemic fluency, processing speed, executive functioning, and average 7-year change. RESULTS: Anticholinergic use was associated with lower cognitive global cognition (β= -0.21; 95% CI [-0.36; -0.05]), learning (β= -0.27; 95% CI [-0.47; -0.07]), memory (β= -0.22; 95% CI [-0.41; -0.03]), and executive functioning (β= -0.22; 95% CI [-0.40; -0.03]) scores, particularly among those who took anticholinergics at both visits. Anticholinergic use was associated with faster decline in global cognition, learning, and verbal fluency (β: -0.28 [95% CI: -0.55, -0.01]; β: -0.28 [95% CI: -0.55, -0.01]; β: -0.25, [95% CI -0.47, -0.04], respectively). Sex modified associations between anticholinergic use with global cognition, learning, and executive functioning (F3 = 3.59, F3 = 2.84, F3 = 3.88, respectively). CONCLUSION: Anticholinergic use was associated with lower neurocognitive performance, especially among those who used anticholinergics at both visits, among a study population of diverse Hispanics/Latinos. Findings will support evidence-based decisions regarding anticholinergic prescriptions and efforts to minimize cognitive impact.

Association of Brain Volume and Retinal Thickness in the Early Stages of Alzheimer's Disease. - Mathew, Sunu; WuDunn, Darrell; Mackay, Devin D; Vosmeier, Aaron; Tallman, Eileen F; Deardorff, Rachael; Harris, Alon; Farlow, Martin R; Brosch, Jared R; Gao, Sujuan; Apostolova, Liana G; Saykin, Andrew J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: The eye has been considered a 'window to the brain,' and several neurological diseases including neurodegenerative conditions like Alzheimer's disease (AD) also show changes in the retina. OBJECTIVE: To investigate retinal nerve fiber layer (RNFL) thickness and its association with brain volume via magnetic resonance imaging (MRI) in older adults with subjective or objective cognitive decline. METHODS: 75 participants underwent ophthalmological and neurological evaluation including optical coherence tomography and MRI (28 cognitively normal subjects, 26 with subjective cognitive decline, 17 patients diagnosed with mild cognitive impairment, and 4 with AD). Differences in demographics, thickness of RNFL, and brain volume were assessed using ANCOVA, while partial Pearson correlations, covaried for age and sex, were used to compare thickness of the peripapillary RNFL with brain volumes, with p < 0.05 considered statistically significant. RESULTS: Mean RNFL thickness was significantly correlated with brain volumes, including global volume (right eye r = 0.235 p = 0.046, left eye r = 0.244, p = 0.037), temporal lobe (right eye r = 0.242 p = 0.039, left eye r = 0.290, p = 0.013), hippocampal (right eye r = 0.320 p = 0.005, left eye r = 0.306, p = 0.008), amygdala (left eye r = 0.332, p = 0.004), and occipital lobe (right eye r = 0.264 p = 0.024) volumes. CONCLUSION: RNFL thickness in both eyes was positively associated with brain volumes in subjects with subjective and objective cognitive decline. The RNFL, however, did not correlate with the disease, but the small sample number makes it important to conduct larger studies. RNFL thickness may be a useful non-invasive and inexpensive tool for detection of brain neurodegeneration and may assist with diagnosis and monitoring of progression and treatment in AD.

Association of Carotid Intima Media Thickening with Future Brain Region Specific Amyloid-β Burden. - Baradaran, Hediyeh; Peloso, Gina M; Polak, Joseph F; Killiany, Ronald J; Ghosh, Saptaparni; DeCarli, Charles S; Thibault, Emma G; Sperling, Reisa A; Johnson, Keith A; Beiser, Alexa; Romero, Jose R; Seshadri, Sudha (J Alzheimers Dis, 2022)
BACKGROUND: Carotid atherosclerosis is associated with cognitive impairment and dementia, though there is limited evidence of a direct link between carotid disease and amyloid-β (Aβ) burden. OBJECTIVE: We studied the association of baseline and progressive carotid intima media thickness (CIMT) with Aβ on 11C-Pittsburgh Compound B (PiB) to determine if those with carotid atherosclerosis would have higher Aβ burden. METHODS: We studied 47 participants from the Framingham Offspring cohort with carotid ultrasounds measuring CIMT at their 6th clinic examination (aged 49.5±5.7 years) and an average of 9.6 years later, and PiB imaging measuring Aβ on average 22.1 years post baseline. We used multivariate linear regression analyses to relate baseline, follow-up, mean, and progression of internal carotid artery (ICA) and common carotid artery (CCA) CIMT to Aβ in brain regions associated with Alzheimer's disease (AD) and related dementias (ADRD), adjusting for age, sex, and other vascular risk factors. RESULTS: Participants with higher mean ICA IMT had more Aβ in the precuneus (beta±standard error [β±SE]: 0.466±0.171 mm, p = 0.01) and the frontal, lateral, and retrosplenial regions (β±SE: 0.392±0.164 mm, p = 0.022) after adjusting for age, sex, vascular risk factors, and medication use. We did not find an association between any CCA IMT measures and Aβ or progression of ICA or CCA IMT and Aβ. CONCLUSION: Carotid atherosclerosis, as measured by ICA IMT, is associated with increased Aβ burden later in life. These findings support a link between vascular disease and AD/ADRD pathophysiology.

Association of Cholinergic Basal Forebrain Volume and Functional Connectivity with Markers of Inflammatory Response in the Alzheimer's Disease Spectrum. - Teipel, Stefan J; Dyrba, Martin; Ballarini, Tommaso; Brosseron, Frederic; Bruno, Davide; Buerger, Katharina; Cosma, Nicoleta-Carmen; Dechent, Peter; Dobisch, Laura; Düzel, Emrah; Ewers, Michael; Fliessbach, Klaus; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Inflammation has been described as a key pathogenic event in Alzheimer's disease (AD), downstream of amyloid and tau pathology. Preclinical and clinical data suggest that the cholinergic basal forebrain may moderate inflammatory response to different pathologies. OBJECTIVE: To study the association of cholinergic basal forebrain volume and functional connectivity with measures of neuroinflammation in people from the AD spectrum. METHODS: We studied 261 cases from the DELCODE cohort, including people with subjective cognitive decline, mild cognitive impairment, AD dementia, first degree relatives, and healthy controls. Using Bayesian ANCOVA, we tested associations of MRI indices of cholinergic basal forebrain volume and functional connectivity with cerebrospinal fluid (CSF) levels of sTREM2 as a marker of microglia activation, and serum levels of complement C3. Using Bayesian elastic net regression, we determined associations between basal forebrain measures and a large inflammation marker panel from CSF and serum. RESULTS: We found anecdotal to moderate evidence in favor of the absence of an effect of basal forebrain volume and functional connectivity on CSF sTREM2 and serum C3 levels both in Aβ42/ptau-positive and negative cases. Bayesian elastic net regression identified several CSF and serum markers of inflammation that were associated with basal forebrain volume and functional connectivity. The effect sizes were moderate to small. CONCLUSION: Our data-driven analyses generate the hypothesis that cholinergic basal forebrain may be involved in the neuroinflammation response to Aβ42 and phospho-tau pathology in people from the AD spectrum. This hypothesis needs to be tested in independent samples.
Keywords: Aged; Alzheimer Disease; Basal Forebrain; Biomarkers; Cholinergic Agents; Cognitive Dysfunction; Cohort Studies; Female; Humans; Inflammation; Magnetic Resonance Imaging; Male

Associations Between Brainstem Volume and Alzheimer's Disease Pathology in Middle-Aged Individuals of the Framingham Heart Study. - Jacobs, Heidi I L; O'Donnell, Adrienne; Satizabal, Claudia L; Lois, Cristina; Kojis, Daniel; Hanseeuw, Bernard J; Thibault, Emma; Sanchez, Justin S; Buckley, Rachel F; Yang, Qiong; DeCarli, Charles; Killiany, Ron; et al. (J Alzheimers Dis, 2022)
The brainstem is among the first regions to accumulate Alzheimer's disease (AD)-related hyperphosphorylated tau pathology during aging. We aimed to examine associations between brainstem volume and neocortical amyloid-β or tau pathology in 271 middle-aged clinically normal individuals of the Framingham Heart Study who underwent MRI and PET imaging. Lower volume of the medulla, pons, or midbrain was associated with greater neocortical amyloid burden. No associations were detected between brainstem volumes and tau deposition. Our results support the hypothesis that lower brainstem volumes are associated with initial AD-related processes and may signal preclinical AD pathology.

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

Blood Pressure and Later-Life Cognition in Hispanic and White Adults (BP-COG): A Pooled Cohort Analysis of ARIC, CARDIA, CHS, FOS, MESA, and NOMAS. - Levine, Deborah A; Gross, Alden L; Briceño, Emily M; Tilton, Nicholas; Whitney, Rachael; Han, Dehua; Giordani, Bruno J; Sussman, Jeremy B; Hayward, Rodney A; Burke, James F; Elkind, Mitchell S V; Moran, Andrew E; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Ethnic differences in cognitive decline have been reported. Whether they can be explained by differences in systolic blood pressure (SBP) is uncertain. OBJECTIVE: Determine whether cumulative mean SBP levels explain differences in cognitive decline between Hispanic and White individuals. METHODS: Pooled cohort study of individual participant data from six cohorts (1971-2017). The present study reports results on SBP and cognition among Hispanic and White individuals. Outcomes were changes in global cognition (GC) (primary), executive function (EF) (secondary), and memory standardized as t-scores (mean [SD], 50 [10]); a 1-point difference represents a 0.1 SD difference in cognition. Median follow-up was 7.7 (Q1-Q3, 5.2-20.1) years. RESULTS: We included 24,570 participants free of stroke and dementia: 2,475 Hispanic individuals (median age, cumulative mean SBP at first cognitive assessment, 67 years, 132.5 mmHg; 40.8% men) and 22,095 White individuals (60 years,134 mmHg; 47.3% men). Hispanic individuals had slower declines in GC, EF, and memory than White individuals when all six cohorts were examined. Two cohorts recruited Hispanic individuals by design. In a sensitivity analysis, Hispanic individuals in these cohorts had faster decline in GC, similar decline in EF, and slower decline in memory than White individuals. Higher time-varying cumulative mean SBP was associated with faster declines in GC, EF, and memory in all analyses. After adjusting for time-varying cumulative mean SBP, differences in cognitive slopes between Hispanic and White individuals did not change. CONCLUSION: We found no evidence that cumulative mean SBP differences explained differences in cognitive decline between Hispanic and White individuals.

Brain Tissue-Derived Extracellular Vesicles in Alzheimer's Disease Display Altered Key Protein Levels Including Cell Type-Specific Markers. - Huang, Yiyao; Driedonks, Tom A P; Cheng, Lesley; Rajapaksha, Harinda; Routenberg, David A; Nagaraj, Rajini; Redding, Javier; Arab, Tanina; Powell, Bonita H; Pletniková, Olga; Troncoso, Juan C; Zheng, Lei; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Brain tissue-derived extracellular vesicles (bdEVs) play neurodegenerative and protective roles, including in Alzheimer's disease (AD). Extracellular vesicles (EVs) may also leave the brain to betray the state of the CNS in the periphery. Only a few studies have profiled the proteome of bdEVs and source brain tissue. Additionally, studies focusing on bdEV cell type-specific surface markers are rare. OBJECTIVE: We aimed to reveal the pathological mechanisms inside the brain by profiling the tissue and bdEV proteomes in AD patients. In addition, to indicate targets for capturing and molecular profiling of bdEVs in the periphery, CNS cell-specific markers were profiled on the intact bdEV surface. METHODS: bdEVs were separated and followed by EV counting and sizing. Brain tissue and bdEVs from age-matched AD patients and controls were then proteomically profiled. Total tau (t-tau), phosphorylated tau (p-tau), and antioxidant peroxiredoxins (PRDX) 1 and 6 were measured by immunoassay in an independent bdEV separation. Neuron, microglia, astrocyte, and endothelia markers were detected on intact EVs by multiplexed ELISA. RESULTS: Overall, concentration of recovered bdEVs was not affected by AD. Proteome differences between AD and control were more pronounced for bdEVs than for brain tissue. Levels of t-tau, p-tau, PRDX1, and PRDX6 were significantly elevated in AD bdEVs compared with controls. Release of certain cell-specific bdEV markers was increased in AD. CONCLUSION: Several bdEV proteins are involved in AD mechanisms and may be used for disease monitoring. The identified CNS cell markers may be useful tools for peripheral bdEV capture.

Cancer and Vascular Comorbidity Effects on Dementia Risk and Neuropathology in the Oldest-Old. - Lachner, Christian; Day, Gregory S; Camsari, Gamze Balci; Kouri, Naomi; Ertekin-Taner, Nilufer; Boeve, Bradley F; Labuzan, Sydney A; Lucas, John A; Thompson, E Aubrey; Siddiqui, Habeeba; Crook, Julia E; Cabrera-Rodriguez, Janisse N; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Dementia, vascular disease, and cancer increase with age, enabling complex comorbid interactions. Understanding vascular and cancer contributions to dementia risk and neuropathology in oldest-old may improve risk modification and outcomes. OBJECTIVE: Investigate vascular and cancer contributions to dementia and neuropathology in oldest-old. METHODS: Longitudinal clinicopathologic study of prospectively followed Mayo Clinic participants dying≥95 years-old who underwent autopsy. Participants were stratified by dementia status and compared according to demographics, vascular risk factors, cancer, and neuropathology. RESULTS: Participants (n = 161; 83% female; 99% non-Hispanic whites)≥95 years (95-106 years-old) with/without dementia did not differ based on demographics. APOE ɛ2 frequency was higher in no dementia (20/72 [28%]) versus dementia (11/88 [12%]; p = 0.03), but APOE ɛ4 frequency did not differ. Coronary artery disease was more frequent in no dementia (31/72 [43%]) versus dementia (23/89 [26%]; p = 0.03) associated with 56% lower dementia odds (odds ratio [OR] = 0.44 [confidence interval (CI) = 0.19-0.98]; p = 0.04) and fewer neuritic/diffuse plaques. Diabetes had an 8-fold increase in dementia odds (OR = 8.42 [CI = 1.39-163]; p = 0.02). Diabetes associated with higher cerebrovascular disease (Dickson score; p = 0.05). Cancer associated with 63% lower dementia odds (OR = 0.37 [CI = 0.17-0.78]; p <  0.01) and lower Braak stage (p = 0.01). CONCLUSION: Cancer exposure in the oldest-old was associated with lower odds of dementia and tangle pathology, whereas history of coronary artery disease was associated with lower odds of dementia and amyloid-β plaque pathology. History of diabetes mellitus was associated with increased odds of dementia and cerebrovascular disease pathology. Cancer-related mechanisms and vascular risk factor reduction strategies may alter dementia risk and neuropathology in oldest-old.

Characterization of Mild Cognitive Impairment and Dementia among Community-Dwelling Mexican Americans and Non-Hispanic Whites. - O'Bryant, Sid E; Petersen, Melissa; Hall, James; Johnson, Leigh A; Barber, Robert; Phillips, Nicole; Braskie, Meredith N; Yaffe, Kristine; Rissman, Robert; Toga, Arthur (J Alzheimers Dis, 2022)
BACKGROUND: Despite tremendous advancements in the field, our understanding of mild cognitive impairment (MCI) and Alzheimer's disease (AD) among Mexican Americans remains limited. OBJECTIVE: The aim of this study was to characterize MCI and dementia among Mexican Americans and non-Hispanic whites. METHODS: Baseline data were analyzed from n = 1,705 (n = 890 Mexican American; n = 815 non-Hispanic white) participants enrolled in the Health and Aging Brain Study-Health Disparities (HABS-HD). RESULTS: Among Mexican Americans, age (OR = 1.07), depression (OR = 1.09), and MRI-based neurodegeneration (OR = 0.01) were associated with dementia, but none of these factors were associated with MCI. Among non-Hispanic whites, male gender (OR = 0.33), neighborhood deprivation (OR = 1.34), depression (OR = 1.09), and MRI-based neurodegeneration (OR = 0.03) were associated with MCI, while depression (OR = 1.09) and APOEɛ4 genotype (OR = 4.38) were associated with dementia. CONCLUSION: Findings from this study revealed that the demographic, clinical, sociocultural and biomarker characteristics of MCI and dementia are different among Mexican Americans as compared to non-Hispanic whites.

Chronic Renin-Angiotensin System Activation Induced Neuroinflammation: Common Mechanisms Underlying Hypertension and Dementia? - Tran, Shirley; Kuruppu, Sanjaya; Rajapakse, Niwanthi W (J Alzheimers Dis, 2022)
Hypertension is a major risk factor for the pathogenesis of vascular dementia and Alzheimer's disease. Chronic activation of the renin-angiotensin system (RAS) contributes substantially to neuroinflammation. We propose that neuroinflammation arising from chronic RAS activation can initiate and potentiate the onset of hypertension and related dementia. Neuroinflammation induced by chronic activation of the RAS plays a key role in the pathogenesis of dementia. Increased levels of pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and transforming growth factor (TGF)-β have been reported in brain tissue of vascular dementia patients and animal models of vascular dementia induced by either angiotensin II infusion or transverse aortic coarctation. It is proposed that neuronal cell death and synaptic dysfunction induced by neuroinflammation lead to cognitive impairment in dementia. The neuroprotective RAS pathway, regulated by angiotensin-converting enzyme 2 (ACE2) which converts angiotensin II into angiotensin-(1-7), can attenuate hypertension and dementia. Furthermore, the use of anti-hypertensive medications in preventing dementia or cognitive decline in hypertensive patients and animal models of dementia have mostly been beneficial. Current evidence suggests a strong link between RAS induced neuroinflammation and the onset of hypertension and dementia, which warrants further investigation. Strategies to counteract an overactive RAS and enhance the neuroprotective arm of the RAS may help prevent or improve cognitive impairment associated with hypertension.
Keywords: Angiotensin I; Angiotensin II; Animals; Antihypertensive Agents; Brain; Cytokines; Dementia, Vascular; Humans; Hypertension; Inflammation; Peptide Fragments; Renin-Angiotensin System

Cognitive Function Associated with Gut Microbial Abundance in Sucrose and S-Adenosyl-L-Methionine (SAMe) Metabolic Pathways. - Jeong, Sohyun; Huang, Li-Kai; Tsai, Ming-Ju; Liao, Yi-Tyng; Lin, Yow-Sien; Hu, Chaur-Jong; Hsu, Yi-Hsiang (J Alzheimers Dis, 2022)
BACKGROUND: Differential abundance of gut microbiota has found to be associated with Alzheimer's disease (AD). However, the relative abundance of gut microbiota between dementia and mild cognitive impairment (MCI) in AD is not well studied. OBJECTIVE: We attempted to identify differentially enriched gut microbes and their metabolic pathways in AD patients with dementia comparing to AD patients with MCI. METHODS: Fecal samples were collected at Shuang Ho Hospital, Taipei Medical University, Taiwan and analyzed by whole metagenomic sequencing technique. For normal controls without AD (NC), 16S rRNA sequencing was obtained from the Taiwan Microbiome Database. A total of 48 AD (38 dementia and 10 MCI defined by cognitive function scores) and 50 NC were included. Microbiome alpha and beta diversities were estimated. Differentially enriched microbes were identified with HAllA, MaAsLin, DESeq2, and LEfSe statistical modeling approaches. RESULTS: We found significantly increased abundance of Firmicutes but decreased abundance of Bacteroidetes at phylum level in AD compared to NC. In AD patients, cognitive function scores were negatively associated with abundance of Blautia hydrogenotrophica (Firmicutes), Anaerotruncus colihominis (Firmicutes), and Gordonibacter pamelaeae (Actinobacteria). In addition, microbial abundance in the sucrose and S-Adenosyl-L-methionine (SAMe) metabolic pathways was more enriched in AD with MCI than AD with dementia and significantly associated with higher cognitive function scores. CONCLUSION: Gut microbe community diversity was similar in AD patients regardless of MCI or dementia status. However, differential analyses probed in lower-level taxa and metabolic pathways suggested that specific gut microbes in Firmicutes and Actinobacteria might involve in cognitive decline.
Keywords: Alzheimer Disease; Cognition; Cognitive Dysfunction; Gastrointestinal Microbiome; Humans; Metabolic Networks and Pathways; RNA, Ribosomal, 16S; S-Adenosylmethionine; Sucrose

Cognitive, Functional, and Emotional Changes During the COVID-19 Pandemic in Greek Patients with Neurocognitive Disorders. - Tsiakiri, Anna; Vlotinou, Pinelopi; Terzoudi, Aikaterini; Heliopoulos, Ioannis; Vadikolias, Konstantinos (J Alzheimers Dis, 2022)
BACKGROUND: Prolonged periods of social deprivation, such as COVID-19-related lockdowns, are associated with deleterious effects on cognitive functions. OBJECTIVE: The aim of this study was to gauge the effect of prolonged social isolation on the cognitive function of older adults with neurocognitive disorders. METHODS: We recruited 125 older adults with minor or major neurocognitive disorders divided into two groups. The control group was tested at the first period of the study (October 2018-May 2019), whereas the experimental group was evaluated at the second chronological period of the study (October 2020-May 2021) during the second wave of COVID-19. Neuropsychological tests were performed at baseline and six months after baseline. RESULTS: In the control group, significant changes in the scores from the Montreal Cognitive Assessment (MoCA; p = 0.049) and the Functional Rating Scale for Symptoms of Dementia (FRSSD; p = 0.005) were found between baseline and follow-up assessments, whereas no changes were identified in Mini-Mental State Examination (MMSE; p = 0.229) and Geriatric Depression Scale (GDS; p = 0.619) scores. In the experimental group, the scores from all neuropsychological tests (MoCA, MMSE, GDS, and FRSSD; p < 0.001 for all) were significantly different at follow-up when compared with those at baseline measurements. Moreover, significant deterioration of specific functions assessed in MMSE and FRSSD was detected, especially in the experimental group. CONCLUSION: This study highlights cognitive functions directly affected by social deprivation of individuals with neurocognitive disorders. The findings can be used in the rehabilitation from confinement and its negative consequences.
Keywords: Aged; Cognition; Cognitive Dysfunction; Communicable Disease Control; COVID-19; Greece; Humans; Neurocognitive Disorders; Neuropsychological Tests; Pandemics

Comparative Analysis of Alzheimer's Disease Cerebrospinal Fluid Biomarkers Measurement by Multiplex SOMAscan Platform and Immunoassay-Based Approach. - Timsina, Jigyasha; Gomez-Fonseca, Duber; Wang, Lihua; Do, Anh; Western, Dan; Álvarez, Ignacio; Aguilar, Miquel; Pastor, Pau; Henson, Rachel L; Herries, Elizabeth; Xiong, Chengjie; Schindler, Suzanne E; et al. (J Alzheimers Dis, 2022)
BACKGROUND: The SOMAscan assay has an advantage over immunoassay-based methods because it measures a large number of proteins in a cost-effective manner. However, the performance of this technology compared to the routinely used immunoassay techniques needs to be evaluated. OBJECTIVE: We performed comparative analyses of SOMAscan and immunoassay-based protein measurements for five cerebrospinal fluid (CSF) proteins associated with Alzheimer's disease (AD) and neurodegeneration: NfL, Neurogranin, sTREM2, VILIP-1, and SNAP-25. METHODS: We compared biomarkers measured in ADNI (N = 689), Knight-ADRC (N = 870), DIAN (N = 115), and Barcelona-1 (N = 92) cohorts. Raw protein values were transformed using z-score in order to combine measures from the different studies. sTREM2 and VILIP-1 had more than one analyte in SOMAscan; all available analytes were evaluated. Pearson's correlation coefficients between SOMAscan and immunoassays were calculated. Receiver operating characteristic curve and area under the curve were used to compare prediction accuracy of these biomarkers between the two platforms. RESULTS: Neurogranin, VILIP-1, and NfL showed high correlation between SOMAscan and immunoassay measures (r >  0.9). sTREM2 had a fair correlation (r >  0.6), whereas SNAP-25 showed weak correlation (r = 0.06). Measures in both platforms provided similar predicted performance for all biomarkers except SNAP-25 and one of the sTREM2 analytes. sTREM2 showed higher AUC for SOMAscan based measures. CONCLUSION: Our data indicate that SOMAscan performs as well as immunoassay approaches for NfL, Neurogranin, VILIP-1, and sTREM2. Our study shows promise for using SOMAscan as an alternative to traditional immunoassay-based measures. Follow-up investigation will be required for SNAP-25 and additional established biomarkers.

Comparison of Steady-State Pharmacokinetics of Donepezil Transdermal Delivery System with Oral Donepezil. - Tariot, Pierre N; Braeckman, Rene; Oh, Charles (J Alzheimers Dis, 2022)
BACKGROUND: Donepezil is approved for treatment of dementia of the Alzheimer type and is currently available only in tablet forms in the United States. OBJECTIVE: To compare steady-state pharmacokinetics of once-weekly 10-mg/d and 5-mg/d Corplex™ donepezil transdermal delivery systems (TDS) with once-daily 10-mg oral donepezil. METHODS: Open-label, randomized, crossover study (NCT04617782) enrolled healthy participants aged 18-55 years. All participants received 5-mg/d donepezil TDS during the 5-week Period 1, followed by 10-mg/d TDS or 10-mg/d oral donepezil in the 5-week Period 2; treatments were switched in Period 3. Bioequivalence was assessed at steady state on Week 5. RESULTS: All 60 enrolled participants received 5-mg/d TDS, 55 received 10-mg/d TDS, and 56 received oral donepezil. Adjusted geometric mean ratio (% [90% CI]) for maximum plasma concentration and area under the plasma concentration versus time curve (0-168 h) were 88.7 (81.7-96.2) and 108.6 (100.5-117.4) for 10-mg/d and 86.1 (79.8-92.9) and 105.3 (97.6-113.6) for dose-normalized 5-mg/d TDS and were generally within the 80% -125% range for establishing bioequivalence with oral donepezil. Skin adhesion was similar for both TDSs (>80% of patches remaining ≥75% adhered throughout the wear period). Overall incidence of adverse events (AEs) was similar across treatments. Compared with 10-mg/d TDS, oral donepezil was associated with higher incidence of gastrointestinal and nervous system AEs (14.5% versus 53.6% and 14.5% versus 30.4%, respectively). CONCLUSION: Donepezil TDSs are bioequivalent to oral donepezil at steady state and have a safety profile that supports their use in treating dementia of the Alzheimer type.
Keywords: Adolescent; Adult; Alzheimer Disease; Cross-Over Studies; Donepezil; Humans; Middle Aged; Young Adult

The Correlation of Tau Levels with Blood Monocyte Count in Patients with Alzheimer's Disease. - Sun, Hao-Lun; Zhou, Fa-Ying; Chen, Dong-Wan; Tan, Cheng-Rong; Zeng, Gui-Hua; Liu, Yu-Hui; Wang, Jun; Bu, Xian-Le; Wang, Yan-Jiang; Li, Hui-Yun; Jin, Wang-Sheng (J Alzheimers Dis, 2022)
BACKGROUND: Recent studies have shown that monocytes can phagocytize the tau protein, which may ameliorate tau-type pathology in Alzheimer's disease (AD). However, there are few clinical studies on the relationship between monocytes and tau-type pathology in AD patients. OBJECTIVE: We aimed to explore changes in peripheral monocytes and their association with tau protein in AD patients. METHODS: A total of 127 clinically diagnosed AD patients and 100 age- and sex-matched cognitively normal controls were recruited for analysis of the correlation of plasma tau levels with the blood monocyte count. Cerebrospinal fluid (CSF) samples from 46 AD patients and 88 controls were further collected to analyze the correlation of CSF tau and amyloid-β (Aβ) levels with the blood monocyte count. 105 clinically diagnosed mild cognitive impairment (MCI) patients and 149 age- and sex-matched cognitively normal controls were recruited from another cohort for verification. RESULTS: Compared to normal controls, AD patients showed a significant reduction in the blood monocyte count. In addition, the monocyte count of AD patients was negatively correlated with CSF t-tau and p-tau levels but not with plasma tau levels. In normal people, monocyte count lack correlation with tau levels both in plasma and CSF. Monocyte count were not correlated with CSF Aβ levels in either group but were negatively correlated with CSF tau/Aβ42 levels in the AD group. We had further verified the correlations of monocyte count with CSF tau levels in another cohort. CONCLUSION: This study suggests that monocytes may play an important role in the clearance of tau protein in the brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Cohort Studies; Female; Humans; Male; Monocytes; tau Proteins

Diabetic Retinopathy Predicts Risk of Alzheimer's Disease: A Danish Registry-Based Nationwide Cohort Study. - Pedersen, Frederik Nørregaard; Stokholm, Lonny; Pouwer, Frans; Hass Rubin, Katrine; Peto, Tunde; Frydkjær-Olsen, Ulrik; Thykjær, Anne Suhr; Andersen, Nis; Andresen, Jens; Bek, Toke; La Cour, Morten; Heegaard, Steffen; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Retinal neurodegeneration is evident in early diabetic retinopathy (DR) which may be associated with other neurodegenerative diseases like Alzheimer's disease (AD). OBJECTIVE: To investigate diabetes and DR as a risk marker of present and incident AD. METHODS: A register-based cohort study was performed. We included 134,327 persons with diabetes above 60 years of age, who had attended DR screening, and 651,936 age- and gender-matched persons without diabetes. RESULTS: At baseline, the prevalence of AD was 0.7% and 1.3% among patients with and without diabetes, respectively. In a multivariable regression model, patients with diabetes were less likely to have AD at baseline (adjusted OR 0.63, 95% CI 0.59-0.68). During follow-up, incident AD was registered for 1473 (0.35%) and 6,899 (0.34%) persons with and without diabetes, respectively. Compared to persons without diabetes, persons with diabetes and no DR had a lower risk to develop AD (adjusted HR 0.87, 95% CI 0.81-0.93), while persons with diabetes and DR had higher risk of AD (adjusted HR 1.24, 95% CI 1.08-1.43). When persons with diabetes and no DR were used as references, a higher risk of incident AD was observed in persons with DR (adjusted HR 1.34, 95% CI 1.18-1.53). CONCLUSION: Individuals with diabetes without DR were less likely to develop AD compared to persons without diabetes. However, individuals with DR had a 34% higher risk of incident AD, which raise the question whether screening for cognitive impairment should be done among individuals with DR.
Keywords: Alzheimer Disease; Cohort Studies; Denmark; Diabetes Mellitus; Diabetic Retinopathy; Humans; Registries; Risk Factors

DNA Damage Increases Secreted Aβ40 and Aβ42 in Neuronal Progenitor Cells: Relevance to Alzheimer's Disease. - Welty, Starr; Thathiah, Amantha; Levine, Arthur Samuel (J Alzheimers Dis, 2022)
BACKGROUND: Recent studies suggest a strong association between neuronal DNA damage, elevated levels of amyloid-β (Aβ), and regions of the brain that degenerate in Alzheimer's disease (AD). OBJECTIVE: To investigate the nature of this association, we tested the hypothesis that extensive DNA damage leads to an increase in Aβ40 and Aβ42 generation. METHODS: We utilized an immortalized human neuronal progenitor cell line (NPCs), ReN VM GA2. NPCs or 20 day differentiated neurons were treated with hydrogen peroxide or etoposide and allowed to recover for designated times. Sandwich ELISA was used to assess secreted Aβ40 and Aβ42. Western blotting, immunostaining, and neutral comet assay were used to evaluate the DNA damage response and processes indicative of AD pathology. RESULTS: We determined that global hydrogen peroxide damage results in increased cellular Aβ40 and Aβ42 secretion 24 h after treatment in ReN GA2 NPCs. Similarly, DNA double strand break (DSB)-specific etoposide damage leads to increased Aβ40 and Aβ42 secretion 2 h and 4 h after treatment in ReN GA2 NPCs. In contrast, etoposide damage does not increase Aβ40 and Aβ42 secretion in post-mitotic ReN GA2 neurons. CONCLUSION: These findings provide evidence that in our model, DNA damage is associated with an increase in Aβ secretion in neuronal progenitors, which may contribute to the early stages of neuronal pathology in AD.

Effect of Probiotic Bifidobacterium breve in Improving Cognitive Function and Preventing Brain Atrophy in Older Patients with Suspected Mild Cognitive Impairment: Results of a 24-Week Randomized, Double-Blind, Placebo-Controlled Trial. - Asaoka, Daisuke; Xiao, Jinzhong; Takeda, Tsutomu; Yanagisawa, Naotake; Yamazaki, Takahiro; Matsubara, Yoichiro; Sugiyama, Hideki; Endo, Noemi; Higa, Motoyuki; Kasanuki, Koji; Ichimiya, Yosuke; Koido, Shigeo; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Probiotics have been reported to ameliorate cognitive impairment. OBJECTIVE: We investigated the effect of the probiotic strain Bifidobacterium breve MCC1274 (A1) in enhancing cognition and preventing brain atrophy of older patients with mild cognitive impairment (MCI). METHODS: In this RCT, 130 patients aged from 65 to 88 years old with suspected MCI received once daily either probiotic (B. breve MCC1274, 2×1010 CFU) or placebo for 24 weeks. Cognitive functions were assessed by ADAS-Jcog and MMSE tests. Participants underwent MRI to determine brain atrophy changes using Voxel-based Specific Regional Analysis System for Alzheimer's disease (VSRAD). Fecal samples were collected for the analysis of gut microbiota composition. RESULTS: Analysis was performed on 115 participants as the full analysis set (probiotic 55, placebo 60). ADAS-Jcog subscale "orientation" was significantly improved compared to placebo at 24 weeks. MMSE subscales "orientation in time" and "writing" were significantly improved compared to placebo in the lower baseline MMSE (< 25) subgroup at 24 weeks. VSRAD scores worsened in the placebo group; probiotic supplementation tended to suppress the progression, in particular among those subjects with progressed brain atrophy (VOI Z-score ≥1.0). There were no marked changes in the overall composition of the gut microbiota by the probiotic supplementation. CONCLUSION: Improvement of cognitive function was observed on some subscales scores only likely due to the lower sensitiveness of these tests for MCI subjects. Probiotics consumption for 24 weeks suppressed brain atrophy progression, suggesting that B. breve MCC1274 helps prevent cognitive impairment of MCI subjects.
Keywords: Aged; Aged, 80 and over; Atrophy; Bifidobacterium breve; Brain; Cognition; Cognitive Dysfunction; Double-Blind Method; Humans; Probiotics

The Effectiveness of GRADIOR: A Neuropsychological Rehabilitation Program for People with Mild Cognitive Impairment and Mild Dementia. Results of a Randomized Controlled Trial After 4 and 12 Months of Treatment. - Diaz Baquero, Angie A; Franco-Martín, Manuel A; Parra Vidales, Esther; Toribio-Guzmán, José Miguel; Bueno-Aguado, Yolanda; Martínez Abad, Fernando; Perea Bartolomé, María V; Asl, Aysan Mahmoudi; van der Roest, Henriëtte G (J Alzheimers Dis, 2022)
BACKGROUND: Computer-based cognitive training programs have been developed with promising results on the maintenance/improvement of cognitive performance in people with dementia. OBJECTIVE: The objective was to evaluate the effectiveness of the cognitive rehabilitation program "GRADIOR" in people with mild cognitive impairment and mild dementia. METHOD: This study was a single-blind multicenter randomized clinical trial. Participants were recruited from hospitals/day centers. The experimental group (EG) and control group (CG) received computer-based cognitive training (CCT) and routine daily care, respectively. Outcome measures at T0: baseline, T1: at 4 months, T2: at 12 months were compared within and between-groups. RESULTS: Significant differences or important effect sizes were detected at the intragroup and intergroup level for most variables, observing a trend of improvement and/or maintenance at 4 months by Visual Reasoning of Cambridge Cognitive Examination (CAMCOG), Digit and Arithmetic of WAIS-III, Semantic Verbal Fluency, Mini-Mental State Exam (MMSE), Trail Making Test (TMT)-A-Mistakes and at 12 months by Visual Reasoning of CAMCOG, Digit Symbol of WAIS-III, TMT-B-mistakes, Visual Memory of Rivermead Behavioural Memory Test, Lexical Verbal Fluency-P, Yesavage's Geriatric Depression Scale (GDS), TMT-A-time scales whose objective was to evaluate some executive functions and/or the memory. The CG presented a worsening trend for most of the measures towards 12 months. There was also a significant interaction between "time and group" for MMSE (F = 8.971; p = 0.03; η 2 = 0.019) and the GDS (F = 3.414; p = 0.04; η 2 = 0.041), as well as small effect sizes for TMT-A-time (F = 1.641; p = 0.21; η 2 = 0.021) and TMT-A-mistakes (F = 0.908; p = 0.41; η 2 = 0.019). CONCLUSION: CCT with GRADIOR has been proved to benefit cognitive functions (ISRCTN:15742788).

Functional Neurophysiological Biomarkers of Early-Stage Alzheimer's Disease: A Perspective of Network Hyperexcitability in Disease Progression. - Tok, Sean; Ahnaou, Abdallah; Drinkenburg, Wilhelmus (J Alzheimers Dis, 2022)
Network hyperexcitability (NH) has recently been suggested as a potential neurophysiological indicator of Alzheimer's disease (AD), as new, more accurate biomarkers of AD are sought. NH has generated interest as a potential indicator of certain stages in the disease trajectory and even as a disease mechanism by which network dysfunction could be modulated. NH has been demonstrated in several animal models of AD pathology and multiple lines of evidence point to the existence of NH in patients with AD, strongly supporting the physiological and clinical relevance of this readout. Several hypotheses have been put forward to explain the prevalence of NH in animal models through neurophysiological, biochemical, and imaging techniques. However, some of these hypotheses have been built on animal models with limitations and caveats that may have derived NH through other mechanisms or mechanisms without translational validity to sporadic AD patients, potentially leading to an erroneous conclusion of the underlying cause of NH occurring in patients with AD. In this review, we discuss the substantiation for NH in animal models of AD pathology and in human patients, as well as some of the hypotheses considering recently developed animal models that challenge existing hypotheses and mechanisms of NH. In addition, we provide a preclinical perspective on how the development of animal models incorporating AD-specific NH could provide physiologically relevant translational experimental data that may potentially aid the discovery and development of novel therapies for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Biomarkers; Disease Progression; Humans; Nervous System Physiological Phenomena; Neurophysiology; tau Proteins

Improved Prediction of Amyloid-β and Tau Burden Using Hippocampal Surface Multivariate Morphometry Statistics and Sparse Coding. - Wu, Jianfeng; Su, Yi; Zhu, Wenhui; Jalili Mallak, Negar; Lepore, Natasha; Reiman, Eric M; Caselli, Richard J; Thompson, Paul M; Chen, Kewei; Wang, Yalin (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) plaques and tau protein tangles in the brain are the defining 'A' and 'T' hallmarks of Alzheimer's disease (AD), and together with structural atrophy detectable on brain magnetic resonance imaging (MRI) scans as one of the neurodegenerative ('N') biomarkers comprise the "ATN framework" of AD. Current methods to detect Aβ/tau pathology include cerebrospinal fluid (invasive), positron emission tomography (PET; costly and not widely available), and blood-based biomarkers (promising but mainly still in development). OBJECTIVE: To develop a non-invasive and widely available structural MRI-based framework to quantitatively predict the amyloid and tau measurements. METHODS: With MRI-based hippocampal multivariate morphometry statistics (MMS) features, we apply our Patch Analysis-based Surface Correntropy-induced Sparse coding and max-pooling (PASCS-MP) method combined with the ridge regression model to individual amyloid/tau measure prediction. RESULTS: We evaluate our framework on amyloid PET/MRI and tau PET/MRI datasets from the Alzheimer's Disease Neuroimaging Initiative. Each subject has one pair consisting of a PET image and MRI scan, collected at about the same time. Experimental results suggest that amyloid/tau measurements predicted with our PASCP-MP representations are closer to the real values than the measures derived from other approaches, such as hippocampal surface area, volume, and shape morphometry features based on spherical harmonics. CONCLUSION: The MMS-based PASCP-MP is an efficient tool that can bridge hippocampal atrophy with amyloid and tau pathology and thus help assess disease burden, progression, and treatment effects.

Informal Caregivers' Attitude Toward Dementia: The Impact of Dementia Knowledge, Confidence in Dementia Care, and the Behavioral and Psychological Symptoms of the Person with Dementia. A Cross-Sectional Study. - Teichmann, Birgit; Gkioka, Mara; Kruse, Andreas; Tsolaki, Magda (J Alzheimers Dis, 2022)
BACKGROUND: Dementia is rapidly increasing worldwide due to demographic aging. More than two-thirds of patients are cared by family members. The quality of care depends on the caregivers' attitude toward dementia influencing patient care decisions. OBJECTIVE: The aim of this study is to examine the factors that influence the caregivers' attitude and whether there is an association between participation in a psycho-educational program and attitude. METHODS: We performed a cross-sectional study using a structured closed-ended questionnaire to retrieve socio-demographic information from caregivers and the persons with dementia (N = 86). The study included validated scales such as the Dementia Attitude Scale, the Dementia Knowledge Assessment Tool 2, the Positive Aspects of Caregiving, the Zarit Burden Interview, the Confidence in Dementia Scale, and Spielberger's State-Trait Anxiety Inventory, as well as a neuropsychological battery to assess the condition of people with dementia. RESULTS: Our final model explains 55.6% of the total variance and shows a significant correlation of five factors with attitude toward dementia: confidence, behavioral and psychological symptoms of dementia, anxiety as a trait, positive aspects of caregiving, and dementia knowledge. The caregivers who participated in a psycho-educational program showed a significantly more positive attitude toward dementia, better dementia knowledge, higher confidence in dementia care, and lower anxiety as a state. CONCLUSION: The strong correlation of attitude and knowledge, as well as confidence in dementia care, supports the tripartite model of attitude, which hypothesizes the interrelation of affect, cognition, and behavior.
Keywords: Attitude; Caregivers; Cross-Sectional Studies; Dementia; Humans; Surveys and Questionnaires

Insulin-Like Growth Factor, Inflammation, and MRI Markers of Alzheimer's Disease in Predominantly Middle-Aged Adults. - Wittfeld, Katharina; Raman, Mekala R; Conner, Sarah C; Aslam, Asra; Teumer, Alexander; Nauck, Matthias; Hosten, Norbert; Habes, Mohamad; DeCarli, Charles; Vasan, Ramachandran S; Beiser, Alexa S; Himali, Jayandra J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Insulin-like growth factor 1 (IGF-1) signaling has been implicated in Alzheimer's disease pathogenesis, and further evidence suggests inflammation can be a moderator of this association. However, most research to date has been conducted on older adults. OBJECTIVE: To investigate the association of serum IGF-1 and IGF binding protein 3 (IGFBP-3) concentrations with MRI markers of Alzheimer's disease in predominantly middle-aged adults, and further assess moderation by chronic inflammation. METHODS: We included participants from the Framingham Heart Study (n = 1,852, mean age 46±8, 46% men) and the Study of Health in Pomerania (n = 674, mean age 50±13, 42% men) with available serum IGF-1, IFGBP-3, as well as brain MRI. IGF-1 and IFGBP-3 were related to MRI outcomes (i.e., total brain, cortical gray matter, white matter, white matter hyperintensities (WMH), and hippocampal volumes) using multivariable regression models adjusting for potential confounders. Subgroup analyses by C-reactive protein (CRP) concentrations were also performed. Cohort-specific summary statistics were meta-analyzed using random-effects models and corrected for multiple comparisons. RESULTS: Meta-analysis results revealed that higher IGF-1 concentrations were associated with lower WMH (estimate [β] [95% CI], -0.05 [-0.09, -0.02], p = 0.006) and larger hippocampal volumes (0.07 [0.02, 0.12], p = 0.01), independent of vascular risk factors. These associations occurred predominantly in individuals with CRP concentrations < 75th percentile. We did not observe associations between IGFBP-3 and MRI outcomes. CONCLUSION: Our findings suggest that IGF-1-related signaling may be implicated in brain health as early as midlife.

Interaction Between Diet and Microbiota in the Pathophysiology of Alzheimer's Disease: Focus on Polyphenols and Dietary Fibers. - Ticinesi, Andrea; Mancabelli, Leonardo; Carnevali, Luca; Nouvenne, Antonio; Meschi, Tiziana; Del Rio, Daniele; Ventura, Marco; Sgoifo, Andrea; Angelino, Donato (J Alzheimers Dis, 2022)
Animal studies increasingly indicate that the gut microbiota composition and function can be involved in the pathophysiology and progression of Alzheimer's disease (AD) at multiple levels. However, few studies have investigated this putative gut-brain axis in human beings, and none of them considered diet as a determinant of intestinal microbiota composition. Epidemiological studies highlight that a high intake of fruit and vegetables, such as that typical of the Mediterranean diet, can modulate AD progression. Thus, nutritional interventions are being increasingly studied as a possible non-pharmacological strategy to slow down the progression of AD. In particular, polyphenols and fibers represent the nutritional compounds with the higher potential of counterbalancing the pathophysiological mechanisms of dementia due to their antioxidant, anti-inflammatory, and anti-apoptotic properties. These actions are mediated by the gut microbiota, that can transform polyphenols and fibers into biologically active compounds including, among others, phenyl-γ-valerolactones, urolithins, butyrate, and other short-chain fatty acids. In this review, the complex mechanisms linking nutrition, gut microbiota composition, and pathophysiology of cognitive decline in AD are discussed, with a particular focus on the role of polyphenols and fibers. The gaps between pre-clinical and clinical studies are particularly emphasized, as well as the urgent need for studies comprehensively evaluating the link between nutrition, microbiome, and clinical aspects of AD.
Keywords: Alzheimer Disease; Animals; Diet; Diet, Mediterranean; Dietary Fiber; Humans; Microbiota; Polyphenols

Investigating Causal Relations Between Circulating Metabolites and Alzheimer's Disease: A Mendelian Randomization Study. - Huang, Shu-Yi; Yang, Yu-Xiang; Zhang, Ya-Ru; Kuo, Kevin; Li, Hong-Qi; Shen, Xue-Ning; Chen, Shi-Dong; Chen, Ke-Liang; Dong, Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: Metabolomics is a promising approach that can be used to understand pathophysiological pathways of Alzheimer's disease (AD). However, the causal relationships between metabolism and AD are poorly understood. OBJECTIVE: We aimed to investigate the causal association between circulating metabolites and risk of AD through two-sample Mendelian randomization (MR) approach. METHODS: Genetic associations with 123 circulating metabolic traits were utilized as exposures. Summary statistics data from International Genomics of Alzheimer's Project was used in primary analysis, including 21,982 AD cases and 41,944 controls. Validation was performed using family history of AD data from UK Biobank (27,696 cases of maternal AD, 14,338 cases of paternal AD, and 272,244 controls). We utilized inverse-variance weighted method as primary method. RESULTS: We found significantly increased risks of developing AD per standard deviation increase in the levels of circulating ApoB (odd ratio[OR] = 3.18; 95% confidence interval[CI]: 1.52-6.66, p = 0.0022), glycoprotein acetyls (OR = 1.21; 95% CI: 1.05-1.39, p = 0.0093), total cholesterol (OR = 2.73; 95% CI: 1.41-5.30, p = 0.0030), and low-density lipoprotein (LDL) cholesterol (OR = 2.34; 95% CI: 1.53-3.57, p = 0.0001). Whereas glutamine (OR = 0.81; 95% CI: 0.71-0.92, p = 0.0011) were significantly associated with lower risk of AD. We also detected causal effects of several different composition of LDL fractions on increased AD risk, which has been verified in validation. However, we found no association between circulating high-density lipoprotein cholesterol and AD. CONCLUSION: Our findings suggest causal effects of circulating glycoprotein acetyls, ApoB, LDL cholesterol, and serum total cholesterol on higher risk of AD, whereas glutamine showed the protective effect.
Keywords: Alzheimer Disease; Apolipoproteins B; Cholesterol; Genome-Wide Association Study; Glutamine; Humans; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Risk Factors

It's Groundhog Day! What Can the History of Science Say About the Crisis in Alzheimer's Disease Research? - Jacobs, Noortje; Theunissen, Bert (J Alzheimers Dis, 2022)
For years now, Alzheimer's disease (AD) research has been stuck in a Groundhog-Day scenario: an endless time loop with no breakthrough in sight. Disagreement about the validity of the field's dominant approach, based on the Amyloid Cascade Hypothesis, has led to a seemingly unresolvable trench war between proponents and critics. Our paper evaluates the recent scientific literature on AD from a historical and philosophical perspective. We show that AD research is a classic example of the boundary work at play in a field in crisis: both parties deploy historical and philosophical references to illustrate what counts as good and bad science, as proper scientific method and appropriate scientific conduct. We also show that boundary work has proved unable to point a way out of the deadlock and argue that the science system's tools for establishing scientific quality, such as peer review and the grant system, are unlikely to resolve the crisis. Rather, they consolidate the dominant model's position even more. In conclusion, we suggest that some kind of reverse boundary-work is needed that reopens the discussion on the nature of AD, an issue that has never been settled scientifically. Drawing on historical and philosophical work, we make clear that the definition of AD as a biomedical disease for which a cure can be found has consequences, not only for funding opportunities, but also for patients and their lives. A reconsideration of the desirability of these consequences may lead to different choices with respect to research priorities and patient care.
Keywords: Alzheimer Disease; Amyloid; Humans

Lipid Rafts Act as a Common Platform for Amyloid-β Oligomer-Induced Alzheimer's Disease Pathology. - Kawarabayashi, Takeshi; Nakamura, Takumi; Sato, Kaoru; Seino, Yusuke; Ichii, Sadanobu; Nakahata, Naoko; Takatama, Masamitsu; Westaway, David; George-Hyslop, Peter St; Shoji, Mikio (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) oligomers induce the overproduction of phosphorylated tau and neurodegeneration. These cascades gradually cause cognitive impairment in Alzheimer's disease (AD). While each pathological event in AD has been studied in detail separately, the spatial and temporal relationships between pathological events in AD remain unclear. OBJECTIVE: We demonstrated that lipid rafts function as a common platform for the pathological cascades of AD. METHODS: Cellular and synaptosomal lipid rafts were prepared from the brains of Aβ amyloid model mice (Tg2576 mice) and double transgenic mice (Tg2576 x TgTauP301L mice) and longitudinally analyzed. RESULTS: Aβ dimers, the cellular prion protein (PrPc), and Aβ dimer/PrPc complexes were detected in the lipid rafts. The levels of Fyn, the phosphorylated NR2B subunit of the N-methyl-D-aspartate receptor, glycogen synthase kinase 3β, total tau, phosphorylated tau, and tau oligomers increased with Aβ dimer accumulation in both the cellular and synaptosomal lipid rafts. Increases in the levels of these molecules were first seen at 6 months of age and corresponded with the early stages of Aβ accumulation in the amyloid model mice. CONCLUSION: Lipid rafts act as a common platform for the progression of AD pathology. The findings of this study suggest a novel therapeutic approach to AD, involving the modification of lipid raft components and the inhibition of their roles in the sequential pathological events of AD.

Low-Dose Radiation Therapy Reduces Amyloid Load in Young 3xTg-AD Mice. - Ceyzériat, Kelly; Tournier, Benjamin B; Millet, Philippe; Dipasquale, Giovanna; Koutsouvelis, Nikolaos; Frisoni, Giovanni B; Garibotto, Valentina; Zilli, Thomas (J Alzheimers Dis, 2022)
BACKGROUND: Low-dose radiation therapy (LD-RT) has been shown to decrease amyloidosis or inflammation in systemic diseases and has recently been proposed as possible treatment of Alzheimer's disease (AD). A positive effect of LD-RT on tauopathy, the other marker of AD, has also been suggested. These effects have been shown in preclinical studies, but their mechanisms are still not well understood. OBJECTIVE: This study aimed to evaluate if anti-amyloid and anti-inflammatory effects of LD-RT can be observed at an early stage of the disease. Its impact on tauopathy and behavioral alterations was also investigated. METHODS: The whole brain of 12-month-old 3xTg-AD mice was irradiated with 10 Gy in 5 daily fractions of 2 Gy. Mice underwent behavioral tests before and 8 weeks post treatment. Amyloid load, tauopathy, and neuroinflammation were measured using histology and/or ELISA. RESULTS: Compared with wild-type animals, 3xTg-AD mice showed a moderate amyloid and tau pathology restricted to the hippocampus, a glial reactivity restricted to the proximity of amyloid plaques. LD-RT significantly reduced Aβ 42 aggregated forms (-71%) in the hippocampus and tended to reduce other forms in the hippocampus and frontal cortex but did not affect tauopathy or cognitive performance. A trend for neuroinflammation markers reduction was also observed. CONCLUSION: When applied at an early stage, LD-RT reduced amyloid load and possibly neuroinflammation markers, with no impact on tauopathy. The long-term persistence of these beneficial effects of LD-RT should be evaluated in future studies.

Non-Alcoholic Fatty Liver Disease, Liver Fibrosis, and Regional Amyloid-β and Tau Pathology in Middle-Aged Adults: The Framingham Study. - Weinstein, Galit; O'Donnell, Adrienne; Davis-Plourde, Kendra; Zelber-Sagi, Shira; Ghosh, Saptaparni; DeCarli, Charles S; Thibault, Emma G; Sperling, Reisa A; Johnson, Keith A; Beiser, Alexa S; Seshadri, Sudha (J Alzheimers Dis, 2022)
BACKGROUND: Liver steatosis and fibrosis are emerging as risk factors for multiple extrahepatic health conditions; however, their relationship with Alzheimer's disease pathology is unclear. OBJECTIVE: To examine whether non-alcoholic fatty liver disease (NAFLD) and FIB-4, a non-invasive index of advanced fibrosis, are associated with brain amyloid-β (Aβ) and tau pathology. METHODS: The study sample included Framingham Study participants from the Offspring and Third generation cohorts who attended exams 9 (2011-2014) and 2 (2008-2011), respectively. Participants underwent 11C-Pittsburgh Compound-B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging and abdomen computed tomography, or had information on all components of the FIB-4 index. Linear regression models were used to assess the relationship of NAFLD and FIB-4 with regional tau and Aβ, adjusting for potential confounders and multiple comparisons. RESULTS: Of the subsample with NAFLD information (N = 169; mean age 52±9 y; 57% males), 57 (34%) had NAFLD. Of the subsample with information on liver fibrosis (N = 177; mean age 50±10 y; 51% males), 34 (19%) had advanced fibrosis (FIB-4 >  1.3). Prevalent NAFLD was not associated with Aβ or tau PET. However, FIB-4 index was significantly associated with increased rhinal tau (β= 1.03±0.33, p = 0.002). Among individuals with prevalent NAFLD, FIB-4 was related to inferior temporal, parahippocampal gyrus, entorhinal and rhinal tau (β= 2.01±0.47, p <  0.001; β= 1.60±0.53, p = 0.007, and β= 1.59±0.47, p = 0.003 and β= 1.60±0.42, p = 0.001, respectively) and to Aβ deposition overall and in the inferior temporal and parahippocampal regions (β= 1.93±0.47, p <  0.001; β= 1.59±0.38, p <  0.001, and β= 1.52±0.54, p = 0.008, respectively). CONCLUSION: This study suggests a possible association between liver fibrosis and early Alzheimer's disease pathology, independently of cardio-metabolic risk factors.

Peptidylarginine Deiminase and Alzheimer's Disease. - Wang, Lai; Chen, Hongyang; Tang, Jing; Guo, Zhengwei; Wang, Yanming (J Alzheimers Dis, 2022)
Peptidylarginine deiminases (PADs) are indispensable enzymes for post-translational modification of proteins, which can convert Arg residues on the surface of proteins to citrulline residues. The PAD family has five isozymes, PAD1, 2, 3, 4, and 6, which have been found in multiple tissues and organs. PAD2 and PAD4 were detected in cerebral cortex and hippocampus from human and rodent brain. In the central nervous system, abnormal expression and activation of PADs are involved in the pathological changes and pathogenesis of Alzheimer's disease (AD). This article reviews the classification, distribution, and function of PADs, with an emphasis on the relationship between the abnormal activation of PADs and AD pathogenesis, diagnosis, and the therapeutic potential of PADs as drug targets for AD.
Keywords: Alzheimer Disease; Animals; Cerebral Cortex; Citrulline; Hippocampus; Humans; Isoenzymes; Protein Processing, Post-Translational; Protein-Arginine Deiminases

Plasma Amyloid and in vivo Brain Amyloid in Late Middle-Aged Hispanics. - Rippon, Brady; Palta, Priya; Tahmi, Mouna; Sherwood, Greysi; Soto, Luisa; Cespedes, Sandino; Mesen, Yanette; He, Hengda; Laing, Krystal; Moreno, Herman; Teresi, Jeanne; Razlighi, Qolamreza; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Determining amyloid positivity is possible with cerebrospinal fluid and brain imaging of amyloid, but these methods are invasive and expensive. OBJECTIVE: To relate plasma amyloid-β (Aβ), measured using Single-molecule array (Simoatrademark) assays, to in vivo brain Aβ, measured using positron emission tomography (PET), examine the accuracy of plasma Aβ to predict brain Aβ positivity, and the relation of APOE ɛ4 with plasma Aβ. METHODS: We performed a cross-sectional analysis in a cohort of 345 late middle-aged Hispanic men and women (age 64 years, 72% women). Our primary plasma variable was Aβ 42/Aβ 40 ratio measured with Simoa. Brain Aβ burden was measured as global SUVR with 18F-Florbetaben PET examined continuously and categorically. RESULTS: Plasma Aβ 42/Aβ 40 ratio was inversely associated with global Aβ SUVR (β= -0.13, 95% Confidence Interval (CI): -0.23, -0.03; p = 0.013) and Aβ positivity (Odds Ratio: 0.59, 95% CI: 0.38, 0.91; p = 0.016), independent of demographics and APOE ɛ4. ROC curves (AUC = 0.73, 95% CI: 0.64, 0.82; p <  0.0001) showed that the optimal threshold for plasma Aβ 42/Aβ 40 ratio in relation to brain Aβ positivity was 0.060 with a sensitivity of 82.4% and specificity of 62.8% . APOE ɛ4 carriers had lower Aβ 42/Aβ 40 ratio and a higher Aβ positivity determined with the Aβ 42/Aβ 40 ratio threshold of 0.060. CONCLUSION: Plasma Aβ 42/Aβ 40 ratio assayed using Simoa is weakly correlated with in vivo brain amyloid and has limited accuracy in screening for amyloid positivity and for studying risk factors of brain amyloid burden when in vivo imaging is not feasible.

Plasma Myeloperoxidase as a Potential Biomarker of Patient Response to Anti-Dementia Treatment in Alzheimer's Disease. - Wright, Joy R; Deen, Quazi Fahm E; Stevenson, Anna; Telford-Cooke, Leolie; Parker, Craig; Martin-Ruiz, Carmen; Steinert, Joern R; Kalaria, Raj N; Mukaetova-Ladinska, Elizabeta B (J Alzheimers Dis, 2022)
BACKGROUND: Myeloperoxidase (MPO), a neutrophil-derived pro-inflammatory protein, co-localizes with amyloid-β (Aβ) plaques in Alzheimer's disease (AD). Anti-dementia treatment may facilitate efflux of Aβ and associated plaque proteins from the brain to the peripheral circulation, therefore providing potential biomarkers for the monitoring of donor response to drug treatment. OBJECTIVE: We investigated the diagnostic utility of MPO as a biomarker of AD, and how anti-dementia treatment alters plasma MPO concentration. METHODS: Thirty-two AD patients were recruited, and plasma collected pre-drug administration (baseline), and 1- and 6-months post-treatment. All patients received cholinesterase inhibitors (ChEIs). At baseline and 6 months, patients underwent neuropsychological assessment. Forty-nine elderly healthy individuals with normal cognitive status served as controls. Plasma MPO concentration was measured by ELISA. RESULTS: AD drug naïve patients had similar plasma MPO concentration to their control counterparts (p >  0.05). Baseline MPO levels positively correlated with Neuropsychiatric Inventory score (r = 0.5080; p = 0.011) and carer distress (r = 0.5022; p = 0.012). Following 1-month ChEI treatment, 84.4% of AD patients exhibited increased plasma MPO levels (p <  0.001), which decreased at 6 months (p <  0.001). MPO concentration at 1 month was greatest in AD patients whose memory deteriorated during the study period (p = 0.028), and for AD patients with deterioration in Cornell assessment score (p = 0.044). CONCLUSION: Whereas baseline MPO levels did not differentiate between healthy and AD populations, baseline MPO positively correlated with initial Neuropsychiatric Inventory evaluation. Post-treatment, transient MPO upregulation in ChEI-treated patients may reflect worse therapeutic outcome. Further studies are required to assess the potential of plasma MPO as an AD therapeutic biomarker.

Post-Stroke Cognitive Impairment: Epidemiology, Risk Factors, and Management. - Huang, Yu-Yuan; Chen, Shi-Dong; Leng, Xin-Yi; Kuo, Kevin; Wang, Zuo-Teng; Cui, Mei; Tan, Lan; Wang, Kai; Dong, Qiang; Yu, Jin-Tai (J Alzheimers Dis, 2022)
Stroke, characterized as a neurological deficit of cerebrovascular cause, is very common in older adults. Increasing evidence suggests stroke contributes to the risk and severity of cognitive impairment. People with cognitive impairment following stroke often face with quality-of-life issues and require ongoing support, which have a profound effect on caregivers and society. The high morbidity of post-stroke cognitive impairment (PSCI) demands effective management strategies, in which preventive strategies are more appealing, especially those targeting towards modifiable risk factors. In this review article, we attempt to summarize existing evidence and knowledge gaps on PSCI: elaborating on the heterogeneity in current definitions, reporting the inconsistent findings in PSCI prevalence in the literature, exploring established or less established predictors, outlining prevention and treatment strategies potentially effective or currently being tested, and proposing promising directions for future research.
Keywords: Aged; Cognitive Dysfunction; Humans; Prevalence; Risk Factors; Stroke

Precision Medicine Approach to Alzheimer's Disease: Successful Pilot Project. - Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Raji, Cyrus; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Chwa, Won Jong; Jarrett, Michael; Bredesen, Dale E (J Alzheimers Dis, 2022)
BACKGROUND: Effective therapeutics for Alzheimer's disease are needed. However, previous clinical trials have pre-determined a single treatment modality, such as a drug candidate or therapeutic procedure, which may be unrelated to the primary drivers of the neurodegenerative process. Therefore, increasing data set size to include the potential contributors to cognitive decline for each patient, and addressing the identified potential contributors, may represent a more effective strategy. OBJECTIVE: To determine whether a precision medicine approach to Alzheimer's disease and mild cognitive impairment is effective enough in a proof-of-concept trial to warrant a larger, randomized, controlled clinical trial. METHODS: Twenty-five patients with dementia or mild cognitive impairment, with Montreal Cognitive Assessment (MoCA) scores of 19 or higher, were evaluated for markers of inflammation, chronic infection, dysbiosis, insulin resistance, protein glycation, vascular disease, nocturnal hypoxemia, hormone insufficiency or dysregulation, nutrient deficiency, toxin or toxicant exposure, and other biochemical parameters associated with cognitive decline. Brain magnetic resonance imaging with volumetrics was performed at baseline and study conclusion. Patients were treated for nine months with a personalized, precision medicine protocol, and cognition was assessed at t = 0, 3, 6, and 9 months. RESULTS: All outcome measures revealed improvement: statistically significant improvement in MoCA scores, CNS Vital Signs Neurocognitive Index, and Alzheimer's Questionnaire Change score were documented. No serious adverse events were recorded. MRI volumetrics also improved. CONCLUSION: Based on the cognitive improvements observed in this study, a larger, randomized, controlled trial of the precision medicine therapeutic approach described herein is warranted.

Pre-Diagnostic Symptoms of Young-Onset Dementia in the General Practice up to Five Years Before Diagnosis. - Hendriks, Stevie; Peetoom, Kirsten; Tange, Huibert; van Bokhoven, Marloes A; van der Flier, Wiesje M; Bakker, Christian; Papma, Janne M; Koopmans, Raymond; Verhey, Frans; Köhler, Sebastian; de Vugt, Marjolein (J Alzheimers Dis, 2022)
BACKGROUND: Young-onset dementia (YOD) has many underlying etiologies, leading to a large heterogeneity in first symptoms. This makes it difficult for general practitioners (GPs) to recognize YOD. OBJECTIVE: Identify early symptoms that are more common in the pre-diagnostic phase of YOD. METHODS: We performed a case-control study nested in a primary-care registry on 89 cases and 162 matched controls, where we compared symptoms of people with YOD up to 5 years before diagnosis to their matched control group without YOD. The variables included in this study were International Classification of Primary Care codes and symptoms extracted from written GP notes and categorized in groups. We used Generalized Equation Estimation to analyze symptom's time-trajectories and logistic regression and ROC-curves to analyze differences in number of symptom categories reported. RESULTS: Cognitive symptoms were more common in people with YOD 5 years before diagnosis, affective symptoms 4 years before diagnosis, social symptoms 3 years, behavioral symptoms 2 years, and daily functioning disturbances 1 year before diagnosis. The ROC-curve suggested that reporting two or more symptom categories at the GP gave the best trade-off between sensitivity (85%) and specificity (77% ), for the highest percentage of correctly diagnosed persons. CONCLUSION: This study showed people with YOD present differently than people without YOD. However, it may still be difficult for GPs to use these symptom categories to distinguish people with YOD, since the symptoms also occur in people with other diseases. A combination of reported symptom categories increases the probability of an underlying cause of YOD.

Probiotic Bifidobacterium breve Prevents Memory Impairment Through the Reduction of Both Amyloid-β Production and Microglia Activation in APP Knock-In Mouse. - Abdelhamid, Mona; Zhou, Chunyu; Ohno, Kazuya; Kuhara, Tetsuya; Taslima, Ferdous; Abdullah, Mohammad; Jung, Cha-Gyun; Michikawa, Makoto (J Alzheimers Dis, 2022)
BACKGROUND: Probiotic supplementation reestablishes microbiome diversity and improves brain function in Alzheimer's disease (AD); their molecular mechanisms, however, have not yet been fully illustrated. OBJECTIVE: We investigated the effects of orally supplemented Bifidobacterium breve MCC1274 on cognitive function and AD-like pathologies in AppNL-G-F mice. METHODS: Three-month-old AppNL-G-F mice were orally supplemented with B. breve MCC1274 for four months. The short-term memory function was evaluated using a novel object recognition test. Amyloid plaques, amyloid-β (Aβ) levels, Aβ fibril, amyloid-β protein precursor and its processing enzymes, its metabolic products, glial activity, and cell proliferation in the subgranular zone of the dentate gyrus were evaluated by immunohistochemistry, Aβ ELISA, western blotting, and immunofluorescence staining. The mRNA expression levels of pro- and anti-inflammatory cytokines were determined by qRT-PCR analysis. RESULTS: We found that the oral B. breve MCC1 274 supplementation prevented memory impairment in AppNL-G-F mice and decreased hippocampal Aβ levels through the enhancement of the a-disintegrin and metalloproteinase 10 (ADAM10) level. Moreover, administration of the probiotic activated the ERK/HIF-1α signaling pathway responsible for increasing the ADAM10 level and also attenuated microglial activation, which in turn led to reduction in the mRNA expression levels of pro-inflammatory cytokines in the brain. In addition, B. breve MCC1274 supplementation increased the level of synaptic proteins in the hippocampus. CONCLUSION: Our findings support the possibility that oral B. breve MCC1274 supplementation might be used as a potential preventive therapy for AD progression.
Keywords: Amyloid beta-Peptides; Animals; Bifidobacterium breve; Brain; Disease Models, Animal; Hippocampus; Memory Disorders; Mice; Mice, Transgenic; Microglia; Probiotics

Proteomic Profiles of Neurodegeneration Among Mexican Americans and Non-Hispanic Whites in the HABS-HD Study. - O'Bryant, Sid E; Zhang, Fan; Petersen, Melissa; Hall, James R; Johnson, Leigh A; Yaffe, Kristine; Braskie, Meredith; Vig, Rocky; Toga, Arthur W; Rissman, Robert A (J Alzheimers Dis, 2022)
BACKGROUND: Hispanics are expected to experience the largest increase in Alzheimer's disease (AD) and AD related dementias over the next several decades. However, few studies have examined biomarkers of AD among Mexican Americans, the largest segment of the U.S. Hispanic population. OBJECTIVE: We sought to examine proteomic profiles of an MRI-based marker of neurodegeneration from the AT(N) framework among a multi-ethnic, community-dwelling cohort. METHODS: Community-dwelling Mexican Americans and non-Hispanic white adults and elders were recruited. All participants underwent comprehensive assessments including an interview, functional exam, clinical labs, informant interview, neuropsychological testing, and 3T MRI of the brain. A neurodegeneration MRI meta-ROI biomarker for the AT(N) framework was calculated. RESULTS: Data was examined from n = 1,291 participants. Proteomic profiles were highly accurate for detecting neurodegeneration (i.e., N+) among both Mexican Americans (AUC = 1.0) and non-Hispanic whites (AUC = 0.98). The proteomic profile of N + was different between ethnic groups. Further analyses revealed that the proteomic profiles of N + varied by diagnostic status (control, MCI, dementia) and ethnicity (Mexican American versus non-Hispanic whites) though diagnostic accuracy was high for all classifications. CONCLUSION: A proteomic profile of neurodegeneration has tremendous value and point towards novel diagnostic and intervention opportunities. The current findings demonstrate that the underlying biological factors associated with neurodegeneration are different between Mexican Americans versus non-Hispanic whites as well as at different levels of disease progression.

The Relationship Between Prior Cancer Diagnosis and All-Cause Dementia Progression Among US Adults. - Fowler, Mackenzie E; Wright, Nicole C; Triebel, Kristen; Rocque, Gabrielle B; Irvin, Ryan; Kennedy, Richard E (J Alzheimers Dis, 2022)
BACKGROUND: Cancer-related cognitive impairment (CRCI), a frequent effect of cancer and its treatments, shares common cognitive symptoms with dementia syndromes. Cross-sectional studies demonstrate an inverse relationship between cancer and dementia. However, the longitudinal relationship between dementia decline and cancer has not been investigated. OBJECTIVE: To evaluate the association between cancer and longitudinal progression of dementia. METHODS: We extracted electronic health record data from July 2003 to February 2020 from a single academic medical center. We identified dementia and cancer history prior to dementia using ICD-9/10 codes. We measured cognitive decline with the Alabama Brief Cognitive Screener (ABCs). We used adjusted linear mixed models to estimate baseline cognition and rate of progression by cancer history, including differences by race. RESULTS: The study included 3,809 participants with dementia, of which 672 (17.6%) had cancer history. Those with cancer history had higher baseline cognition (β: 0.62, 95% CI: -0.02-1.25), but similar rate of decline. Non-Hispanic Blacks had lower cognitive scores at baseline and throughout follow-up regardless of cancer status compared to non-Hispanic Whites and other races/ethnicities with and without cancer history. CONCLUSION: In this longitudinal retrospective study, participants with cancer history demonstrate better cognition at dementia diagnosis and no difference in cognitive decline than those without cancer history. Smoking and comorbidities attenuate this association and results indicate non-Hispanic Blacks have worse cognitive outcomes in dementia regardless of cancer history than other race/ethnicity groups. Further exploration of the role of smoking, comorbidities, and race/ethnicity on cancer and dementia-related cognitive decline is needed.

Relationship Between Weight-Change Patterns and Cognitive Function: A Retrospective Study. - Gong, Hong-Jian; Tang, Xingyao; Chai, Yin-He; Qiao, Yu-Shun; Xu, Hui; Patel, Ikramulhaq; Zhang, Jin-Yan; Simó, Rafael; Zhou, Jian-Bo (J Alzheimers Dis, 2022)
BACKGROUND: Obesity has been linked to cognitive impairment. However, how changes in body mass index (BMI) over the life course influence cognitive function remains unclear. OBJECTIVE: The influence of distinct weight-change patterns from young adulthood to midlife and late adulthood on cognitive function in older adults was explored. METHODS: A total of 5,809 individuals aged≥60 years were included and categorized into four groups on the basis of BMI change patterns. Cognitive function was assessed using four cognition tests in the baseline survey. The relationship between the weight-change patterns and cognition was evaluated using regression models. RESULTS: In comparison with participants who remained at non-obese, those moving from the non-obese to obese weight-change pattern from young (25 years of age) to middle adulthood showed lower Digit Symbol Substitution Test (DSST) scores (β= -1.28; 95% confidence interval [CI]: -2.24 to -0.32). A non-obese to obese change pattern from age 25 years of age to 10 years before baseline was associated with a higher risk of DSST impairment (odds ratio = 1.40; 95% CI: 1.09 to 1.79). In comparison with participants whose heaviest weight was recorded after 60 years of age, those with the heaviest weight between 18 and 40 years of age had lower DSST scores (β= -1.46; 95% CI: -2.77 to -1.52). CONCLUSION: Our results suggest that the transition from the non-obese to obese category in early adulthood and appearance of the heaviest weight between 18 and 40 years of age are associated with lower cognitive function in later life.

Relationships Between the Deposition of Amyloid-β and Tau Protein and Glymphatic System Activity in Alzheimer's Disease: Diffusion Tensor Image Study. - Ota, Miho; Sato, Noriko; Nakaya, Moto; Shigemoto, Yoko; Kimura, Yukio; Chiba, Emiko; Yokoi, Yuma; Tsukamoto, Tadashi; Matsuda, Hiroshi (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) and tau protein accumulation in the brain is thought to be one of the causes of Alzheimer's disease (AD). Recent study found that the glymphatic system was waste drainage system in the brain and promoting the elimination of Aβ and tau protein. OBJECTIVE: Objective: We evaluated the relationships between the glymphatic system activity and Aβ and tau protein deposition. METHODS: Subjects were 21 patients with AD and 36 healthy subjects who underwent diffusion tensor imaging (DTI) scan and the positron emission tomography using with the Aβ tracer: 11C-PiB and the tau/inflammatory tracer: 18F-THK5351. We computed diffusion tensor image analysis along the perivascular space (DTI-ALPS) index as the proxy of glymphatic system activity and estimated the relationships between the DTI-ALPS index and Aβ and tau protein/inflammatory deposition. RESULTS: We found significant negative correlations between DTI-ALPS index and the standard uptake value ratio (SUVR) of 11C-PiB in the bilateral temporal and left parietal cortices and left posterior cingulate gyrus in all subjects. Further, we detected significant negative correlations between DTI-ALPS index and the SUVR of 18F-THK5351 in the bilateral temporal cortices and right parietal cortex in all participants, too. CONCLUSION: Our data suggested that DTI-ALPS index was a good biomarker for the evaluation of Aβ and tau deposition and neuroinflammation, and this marker might be effective to estimate the glymphatic system activity.

Risk of Dementia in Cancer Survivors: A Meta-Analysis of Population-Based Cohort Studies. - Zhang, Dan-Dan; Ou, Ya-Nan; Fu, Yan; Wang, Zhi-Bo; Huang, Liang-Yu; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: A negative association between cancer and Alzheimer's disease (AD) was revealed. OBJECTIVE: We aimed to further explore the dementia risk among cancer survivors and then among cancer survivors who received cancer treatment in subsequent subgroup analyses. METHODS: Databases of PubMed, Embase, and Cochrane Library were systematically searched from inception to April 1, 2021, following PRISMA and MOOSE guidelines. Relative risks (RR) of dementia were pooled by a random-effects model stratifying the data by potential confounding factors to explore the heterogeneity. This study is registered with PROSPERO, number CRD42021250654. RESULTS: A total of 36 studies were included in this meta-analysis, of which 16 studies were about the risk of dementia in cancer survivors, and 20 studies were about the risk of dementia in survivors who accepted cancer treatment. The pooled RR reached 0.89 ([95% CI = 0.82-0.97], I2 = 97.9%) for dementia and 0.89 ([0.83-0.95], I2 = 92.6%) for AD in cancer survivors compared with non-cancer controls. Notably, both dementia risk and AD risk significantly decreased in survivors of colon, leukemia, small intestine, and thyroid cancers (RR ranged from 0.64 to 0.92). Furthermore, prostate cancer patients treated with androgen deprivation therapy exhibited a significantly increased risk of dementia (RR:1.18 [1.09-1.27], I2 = 89.5%) and AD (RR:1.17 [1.08-1.25], I2 = 81.3%), with evidence of between-study heterogeneity. CONCLUSION: Currently, available evidence suggests that the risk of dementia among cancer survivors is decreased. However, large-scale prospective cohort studies are warranted to further prove the association.

Safety and Efficacy of Monoclonal Antibodies for Alzheimer's Disease: A Systematic Review and Meta-Analysis of Published and Unpublished Clinical Trials. - Lacorte, Eleonora; Ancidoni, Antonio; Zaccaria, Valerio; Remoli, Giulia; Tariciotti, Leonardo; Bellomo, Guido; Sciancalepore, Francesco; Corbo, Massimo; Lombardo, Flavia L; Bacigalupo, Ilaria; Canevelli, Marco; Piscopo, Paola; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Monoclonal antibodies (mAbs) are currently among the most investigated targets for potential disease-modifying therapies in Alzheimer's disease (AD). OBJECTIVE: Our objectives were to identify all registered trials investigating mAbs in MCI due to AD or AD at any stage, retrieve available published and unpublished data from all registered trials, and analyze data on safety and efficacy outcomes. METHODS: A systematic search of all registered trials on ClinicalTrials.gov and EUCT was performed. Available results were searched on both platforms and on PubMed, ISI Web of Knowledge, and The Cochrane Library. RESULTS: Overall, 101 studies were identified on 27 mAbs. Results were available for 50 trials investigating 12 mAbs. For 18 trials, data were available from both published and unpublished sources, for 21 trials only from published sources, and for 11 trials only from unpublished sources. Meta-analyses of amyloid-related imaging abnormalities (ARIA) events showed overall risk ratios of 10.65 for ARIA-E and of 1.75 for ARIA-H. The meta-analysis of PET-SUVR showed an overall significant effect of mAbs in reducing amyloid (SMD -0.88), but when considering clinical efficacy, data on CDR-SB showed that treated patients had a statistically significant but clinically non-relevant lower worsening (MD -0.15). CONCLUSION: Our results suggest that the risk-benefit profile of mAbs remains unclear. Research should focus on clarifying the effect of amyloid on cognitive decline, providing data on treatment response rate, and accounting for minimal clinically important difference. Research on mAbs should also investigate the possible long-term impact of ARIA events, including potential factors predicting their onset.
Keywords: Alzheimer Disease; Amyloid; Amyloidogenic Proteins; Amyloidosis; Antibodies, Monoclonal; Cognitive Dysfunction; Humans

Subjective Cognitive Decline: Is a Resilient Personality Protective Against Progression to Objective Cognitive Impairment? Findings from Two Community-Based Cohort Studies. - Aschwanden, Damaris; Sutin, Angelina R; Ledermann, Thomas; Luchetti, Martina; Stephan, Yannick; Sesker, Amanda A; Zhu, Xianghe; Terracciano, Antonio (J Alzheimers Dis, 2022)
BACKGROUND: Subjective cognitive decline (SCD) is related to personality functioning and risk of subsequent objective cognitive impairment. OBJECTIVE: The aim of this study was to examine whether lower neuroticism and higher conscientiousness-resilient personality traits-protect against conversion from SCD to objective cognitive impairment in two longitudinal community-based cohorts. METHODS: Data from the Health and Retirement Study (N = 1,741, Mean age = 68.64 years, Follow-up mean = 7.34 years) and the National Health and Aging Trends Survey (N = 258, Mean age = 79.34 years, Follow-up mean = 4.31 years) were analyzed using Cox regression analysis, controlling for sociodemographic covariates, symptoms of anxiety and depression, and apolipoprotein ɛ4. RESULTS: The pooled results showed that lower neuroticism and higher conscientiousness were associated with decreased risk of conversion from SCD to objective cognitive impairment. CONCLUSION: Among individuals with SCD, those with a resilient personality may have more cognitive and psychological reserve to maintain cognitive functioning and delay conversion to objective cognitive impairment. The findings further contribute to a better understanding of personality along the cognitive continuum: The observed effect sizes were smaller than those reported in cognitively normal individuals but larger than in individuals with mild cognitive impairment. Personality could provide useful information to identify individuals with SCD who may develop objective cognitive impairment-namely those who hold a vulnerable personality (higher neuroticism, lower conscientiousness).

Traumatic Brain Injury and Risk of Alzheimer's Disease and Related Dementias in the Population. - Mielke, Michelle M; Ransom, Jeanine E; Mandrekar, Jay; Turcano, Pierpaolo; Savica, Rodolfo; Brown, Allen W (J Alzheimers Dis, 2022)
BACKGROUND: Epidemiological studies examining associations between traumatic brain injury (TBI) and Alzheimer's disease and related dementias (ADRD) have yielded conflicting results, which may be due methodological differences. OBJECTIVE: To examine the relationship between the presence and severity of TBI and risk of ADRD using a population-based cohort with medical record abstraction for confirmation of TBI and ADRD. METHODS: All TBI events among Olmsted County, Minnesota residents aged >  40 years from 1985-1999 were confirmed by manual review and classified by severity. Each TBI case was randomly matched to two age-, sex-, and non-head injury population-based referents without TBI. For TBI events with non-head trauma, the Trauma Mortality Prediction Model was applied to assign an overall measure of non-head injury severity and corresponding referents were matched on this variable. Medical records were manually abstracted to confirm ADRD diagnosis. Cox proportional hazards models examined the relationship between TBI and severity with risk of ADRD. RESULTS: A total of 1,418 residents had a confirmed TBI (865 Possible, 450 Probable, and 103 Definite) and were matched to 2,836 referents. When combining all TBI severities, the risk of any ADRD was significantly higher for those with a confirmed TBI compared to referents (HR = 1.32, 95% CI: 1.11, 1.58). Stratifying by TBI severity, Probable (HR = 1.42, 95% CI: 1.05, 1.92) and Possible (HR = 1.29, 95% CI: 1.02-1.62) TBI was associated with an increased risk of ADRD, but not Definite TBI (HR = 1.22, 95% CI: 0.68, 2.18). CONCLUSION: Our analyses support including TBI as a potential risk factor for developing ADRD.

α-Lipoic Acid Has the Potential to Normalize Copper Metabolism, Which Is Dysregulated in Alzheimer's Disease. - Metsla, Kristel; Kirss, Sigrid; Laks, Katrina; Sildnik, Gertrud; Palgi, Mari; Palumaa, Teele; Tõugu, Vello; Palumaa, Peep (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease (AD) is an age-dependent progressive neurodegenerative disorder and the most common cause of dementia. The treatment and prevention of AD present immense yet unmet needs. One of the hallmarks of AD is the formation of extracellular amyloid plaques in the brain, composed of amyloid-β (Aβ) peptides. Besides major amyloid-targeting approach there is the necessity to focus also on alternative therapeutic strategies. One factor contributing to the development of AD is dysregulated copper metabolism, reflected in the intracellular copper deficit and excess of extracellular copper. OBJECTIVE: In the current study, we follow the widely accepted hypothesis that the normalization of copper metabolism leads to the prevention or slowing of the disease and search for new copper-regulating ligands. METHODS: We used cell culture, ICP MS, and Drosophila melanogaster models of AD. RESULTS: We demonstrate that the natural intracellular copper chelator, α-lipoic acid (LA) translocates copper from extracellular to intracellular space in an SH-SY5Y-based neuronal cell model and is thus suitable to alleviate the intracellular copper deficit characteristic of AD neurons. Furthermore, we show that supplementation with LA protects the Drosophila melanogaster models of AD from developing AD phenotype by improving locomotor activity of fruit fly with overexpression of human Aβ with Iowa mutation in the fly brain. In addition, LA slightly weakens copper-induced smooth eye phenotype when amyloid-β protein precursor (AβPP) and beta-site AβPP cleaving enzyme 1 (BACE1) are overexpressed in eye photoreceptor cells. CONCLUSION: Collectively, these results provide evidence that LA has the potential to normalize copper metabolism in AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Brain; Cell Line; Copper; Disease Models, Animal; Drosophila melanogaster; Humans; Neurons; Thioctic Acid

40 Hz Light Flicker Promotes Learning and Memory via Long Term Depression in Wild-Type Mice. - Tian, Tian; Qin, Xin; Wang, Yali; Shi, Yan; Yang, Xin (J Alzheimers Dis, 2021)
BACKGROUND: 40 Hz light flicker is a well-known non-invasive treatment that is thought to be effective in treating Alzheimer's disease. However, the effects of 40 Hz visual stimulation on neural networks, synaptic plasticity, and learning and memory in wild-type animals remain unclear. OBJECTIVE: We aimed to explore the impact of 40 Hz visual stimulation on synaptic plasticity, place cell, and learning and memory in wild-type mice. METHODS: c-Fos+ cell distribution and in vivo electrophysiology was used to explore the effects of 40 Hz chronic visual stimulation on neural networks and neuroplasticity in wild-type mice. The character of c-Fos+ distribution in the brain and the changes of corticosterone levels in the blood were used to investigate the state of animal. Place cell analysis and novel location test were utilized to examine the effects of 40 Hz chronic visual stimulation on learning and memory in wild-type mice. RESULTS: We found that 40 Hz light flicker significantly affected many brain regions that are related to stress. Also, 40 Hz induced gamma enrichment within 15 min after light flickers and impaired the expression of long-term potentiation (LTP), while facilitated the expression of long-term depression (LTD) in the hippocampal CA1. Furthermore, 40 Hz light flicker enhanced the expression of corticosterone, rendered well-formed place cells unstable and improved animal's learning and memory in novel local recognition test, which could be blocked by pre-treatment with the LTD specific blocker Glu2A-3Y. CONCLUSION: These finding suggested that 40 Hz chronic light flicker contains stress effects, promoting learning and memory in wild-type mice via LTD.

Accelerometer-Measured, Habitual Physical Activity and Circulating Brain-Derived Neurotrophic Factor: A Cross-Sectional Study. - Spartano, Nicole L; Himali, Jayandra J; Trinquart, Ludovic; Yang, Qiong; Weinstein, Galit; Satizabal, Claudia L; Dukes, Kimberly A; Beiser, Alexa S; Murabito, Joanne M; Vasan, Ramachandran S; Seshadri, Sudha (J Alzheimers Dis, 2021)
BACKGROUND: One of the mechanisms suggested to link physical activity (PA) to favorable brain health is through stimulation of neural growth factors such as brain-derived neurotrophic factor (BDNF). Acute bouts of PA stimulate circulating BDNF levels. OBJECTIVE: In this investigation, we assessed whether habitual, accelerometer-measured PA levels were related to circulating BDNF levels in a middle-aged cohort. METHODS: In the Framingham Heart Study Third Generation cohort, 1,769 participants provided reliable accelerometry data and were not missing BDNF measurement and platelet counts. In a cross-sectional analysis, using multivariable regression, we related PA measures to serum BDNF levels, adjusting for age, sex, smoking status, platelet count, depression status, and accelerometer wear time. RESULTS: Our study participants (mean age 47±9 years, 50.8% women) spent an average of 22.3 mins/day moderate-to-vigorous (MV)PA. Most PA variables (steps, MVPA, light activity, and sedentary time) were not related to BDNF levels (p > 0.05). We observed a non-linear trend, where 15-50 mins/week vigorous activity was associated with lower BDNF compared to those with 0 min vigorous activity (β= -0.049±0.024, p = 0.05), but with no significant associations at lower or higher vigorous activity levels. In smokers, MVPA was also associated with lower BDNF levels (β= -0.216±0.079, p = 0.01). CONCLUSION: Our study reveals that circulating BDNF is not chronically elevated in individuals with higher levels of habitual PA in middle-aged adults from the community and may even be chronically suppressed with higher PA in subgroups, including current smokers. These results do not contradict previous studies demonstrating that circulating BDNF rises acutely after PA.

Acute Exercise and Cognitive Function in Alzheimer's Disease. - Ben Ayed, Ines; Castor-Guyonvarch, Naomie; Amimour, Souad; Naija, Salma; Aouichaoui, Chirine; Ben Omor, Sana; Tabka, Zouhair; El Massioui, Farid (J Alzheimers Dis, 2021)
BACKGROUND: Many studies have shown the impact of acute aerobic exercises (AAE) on cognition in healthy adults or at a pre-dementia stage. Few studies, however, have explored the positive effects of AAE in moderate Alzheimer's disease (ADM) patients. OBJECTIVE: Evaluating the effect of AAE on cognitive functions in ADM patients. METHODS: Overall, 79 (age: 69.62±0.99) ADM patients were recruited. Participants were divided into three groups according to the task: aerobic exercises done alone or combined with cognitive games presented on a screen, and a control group who performed a reading task. The aerobic exercise protocol consisted of a 20-min cycling exercise of moderate intensity, corresponding to 60%of the individual target maximal heart rate recorded in a 6-minute walking test. The participants' cognition was monitored before and after the intervention using the Tower of Hanoi, Digit Span, and Stroop tasks. RESULTS: After the exercise, the participants' attention in both the physical and combined groups improved for the Stroop, the forward and backward Digit Span tasks, as well as the time taken to solve the Tower of Hanoi, although no significant differences were found in the number of moves taken in the latter. By contrast, the control group did not show any significant improvement for most of the cognitive tasks after the reading session. CONCLUSION: Current evidence suggests that AAE may help to improve cognitive functions in ADM patients. This improvement is enhanced when the exercise is combined with cognitive games. Safe and progressive types of exercises should be promoted among ADM patients.

APOE4 Copy Number-Dependent Proteomic Changes in the Cerebrospinal Fluid. - Berger, Miles; Cooter, Mary; Roesler, Alexander S; Chung, Stacey; Park, John; Modliszewski, Jennifer L; VanDusen, Keith W; Thompson, J Will; Moseley, Arthur; Devinney, Michael J; Smani, Shayan; Hall, Ashley; et al. (J Alzheimers Dis, 2021)
BACKGROUND: APOE4 has been hypothesized to increase Alzheimer's disease risk by increasing neuroinflammation, though the specific neuroinflammatory pathways involved are unclear. OBJECTIVE: Characterize cerebrospinal fluid (CSF) proteomic changes related to APOE4 copy number. METHODS: We analyzed targeted proteomic data from ADNI CSF samples using a linear regression model adjusting for age, sex, and APOE4 copy number, and additional linear models also adjusting for AD clinical status or for CSF Aβ, tau, or p-tau levels. False discovery rate was used to correct for multiple comparisons correction. RESULTS: Increasing APOE4 copy number was associated with a significant decrease in a CRP peptide level across all five models (q < 0.05 for each), and with significant increases in ALDOA, CH3L1 (YKL-40), and FABPH peptide levels (q < 0.05 for each) except when controlling for AD clinical status or neurodegeneration biomarkers (i.e., CSF tau or p-tau). In all models except the one controlling for CSF Aβ levels, though not statistically significant, there was a consistent inverse direction of association between APOE4 copy number and the levels of all 24 peptides from all 8 different complement proteins measured. The odds of this happening by chance for 24 unrelated peptides would be less than 1 in 16 million. CONCLUSION: Increasing APOE4 copy number was associated with decreased CSF CRP levels across all models, and increased CSF ALDOA, CH3L1, and FABH levels when controlling for CSF Aβ levels. Increased APOE4 copy number may also be associated with decreased CSF complement pathway protein levels, a hypothesis for investigation in future studies.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Chitinase-3-Like Protein 1; DNA Copy Number Variations; Female; Fructose-Bisphosphate Aldolase; Humans; Male; Proteomics; Receptors, Immunologic

Association Between Elevated Depressive Symptoms and Cognitive Function Moderated by APOE4 Status: Framingham Offspring Study. - Piers, Ryan J; Liu, Yulin; Ang, Ting F A; Tao, Qiushan; Au, Rhoda; Qiu, Wei Qiao (J Alzheimers Dis, 2021)
BACKGROUND: Depression and Apolipoprotein E4 (APOE4) are associated with decreased cognitive function and differences in brain structure. OBJECTIVE: This study investigated whether APOE4 status moderates the association between elevated depressive symptoms, cognitive function, and brain structure. METHODS: Stroke- and dementia-free participants (n = 1,968) underwent neuropsychological evaluation, brain MRI, and depression screening. Linear and logistic regression was used to examine all associations. Secondary analyses were performed using interaction terms to assess effect modification by APOE4 status. RESULTS: Elevated depressive symptoms were associated with lower cognitive performance in several domains. In stratified analyses, elevated depressive symptoms were associated with poorer visual short- and long-term memory performance for APOE4 + participants. Elevated depressive symptoms were not associated with any brain structure in this study sample. CONCLUSION: Elevated depressive symptoms impact cognitive function in non-demented individuals. Having the APOE4 allele may exacerbate the deleterious effects of elevated depressive symptoms on visual memory performance. Screening for elevated depressive symptoms in both research studies and clinical practice may be warranted to avoid false positive identification of neurodegeneration, particularly among those who are APOE4 + .

Association of Malnutrition with Functional and Cognitive Trajectories in People Living with Dementia: A Five-Year Follow-Up Study. - Borda, Miguel Germán; Ayala Copete, Ana María; Tovar-Rios, Diego Alejandro; Jaramillo-Jimenez, Alberto; Giil, Lasse Melvær; Soennesyn, Hogne; Gómez-Arteaga, Camilo; Venegas-Sanabria, Luis Carlos; Kristiansen, Ida; Chavarro-Carvajal, Diego Andrés; Caicedo, Sandra; Cano-Gutierrez, Carlos Alberto; et al. (J Alzheimers Dis, 2021)
BACKGROUND: In dementia, functional status depends on multiple factors in addition to cognition. Nutritional status is a potentially modifiable factor related to homeostasis and proper functioning of body systems and may contribute to cognitive and functional decline. OBJECTIVE: This paper aims to analyze the association of malnutrition with the course of cognitive and functional decline in people living with dementia. METHODS: This is an analysis of a longitudinal cohort study, the Dementia Study of Western Norway. Data of 202 patients diagnosed with mild dementia were analyzed; Alzheimer's disease (AD) (n = 103), Lewy body dementia (LBD) (n = 74), and other dementias (OD) (n = 25). Cognition was assessed with the Mini-Mental State Examination and functional decline through the activities of daily living included in the Rapid Disability Rating Scale. The Global Leadership Initiative on Malnutrition Index was used to determine nutritional status. Associations of nutritional status with cognitive and functional decline were evaluated through adjusted linear mixed models. RESULTS: At baseline, the prevalence of general malnutrition was 28.7%; 17.32% were classified as moderate malnutrition and 11.38% as severe malnutrition (there were no significant differences between AD and LBD). Malnutrition at diagnosis and over follow-up was a significant predictor of functional-decline, but not of cognitive decline. CONCLUSION: According to our results malnutrition was associated with faster functional loss but, not cognitive decline in older adults with dementia. A more comprehensive dementia approach including nutritional assessments could improve prognosis.

Association of Midlife Depressive Symptoms with Regional Amyloid-β and Tau in the Framingham Heart Study. - Gonzales, Mitzi M; Samra, Jasmeet; O'Donnell, Adrienne; Mackin, R Scott; Salinas, Joel; Jacob, Mini; Satizabal, Claudia L; Aparicio, Hugo J; Thibault, Emma G; Sanchez, Justin S; Finney, Rebecca; Rubinstein, Zoe B; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Depressive symptoms predict increased risk for dementia decades before the emergence of cognitive symptoms. Studies in older adults provide preliminary evidence for an association between depressive symptoms and amyloid-β (Aβ) and tau accumulation. It is unknown if similar alterations are observed in midlife when preventive strategies may be most effective. OBJECTIVE: The study aim was to evaluate the association between depressive symptoms and cerebral Aβ and tau in a predominately middle-aged cohort with examination of the apolipoprotein (APOE) ɛ4 allele as a moderator. METHODS: Participants included 201 adults (mean age 53±8 years) who underwent 11C-Pittsburgh Compound B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging. Depressive symptoms were evaluated with the Center for Epidemiological Studies Depression Scale (CES-D) at the time of PET imaging, as well as eight years prior. Associations between depressive symptoms at both timepoints, as well as depression (CES-D≥16), with regional Aβ and tau PET retention were evaluated with linear regression adjusting for age and sex. Interactions with the APOE ɛ4 allele were explored. RESULTS: Depressive symptoms and depression were not associated with PET outcomes in the overall sample. However, among APOE ɛ4 allele carriers, there was a significant cross-sectional association between depressive symptoms and increased tau PET uptake in the entorhinal cortex (β= 0.446, SE = 0.155, p = 0.006) and amygdala (β= 0.350, SE = 0.133, p = 0.012). CONCLUSION: Although longitudinal studies are necessary, the results suggest that APOE ɛ4 carriers with depressive symptoms may present with higher susceptibility to early tau accumulation in regions integral to affective regulation and memory consolidation.

Association of White Matter Hyperintensity Progression with Cognitive Decline in Patients with Amnestic Mild Cognitive Impairment. - Hirao, Kentaro; Yamashita, Fumio; Tsugawa, Akito; Haime, Rieko; Fukasawa, Raita; Sato, Tomohiko; Kanetaka, Hidekazu; Umahara, Takahiko; Sakurai, Hirofumi; Hanyu, Haruo; Shimizu, Soichiro (J Alzheimers Dis, 2021)
BACKGROUND: White matter hyperintensities (WMH) on MRI have been reported to increase the risk of conversion from mild cognitive impairment (MCI) to Alzheimer's disease (AD). However, effects of the progression of WMH on the cognition of patients with MCI remains unclear to date. OBJECTIVE: To investigate the association between WMH progression and cognitive decline in amnestic MCI patients. METHODS: Thirty-eight subjects with amnestic MCI were analyzed prospectively every year for 2 years. Fourteen MCI subjects dropped out on the final visit, and therefore 24 subjects with MCI were analyzed for the entire duration. The volumes of periventricular hyperintensities (PVH) and deep WMH (DWMH) were measured on T2 FLAIR using the 3D-slicer. The associations between PVH/DWMH progression and cognitive decline were investigated. RESULTS: An increase in DWMH volume significantly correlated with changes in Mini-Mental State Examination and category verbal fluency scores, whereas an increase in PVH volume did not correlate with changes in any item. CONCLUSION: DWMH progression was closely associated with a decline in frontal lobe function and semantic memory, suggesting that WMH progression might affect some AD pathophysiologies in amnestic MCI patients.

Automatic Subtyping of Individuals with Primary Progressive Aphasia. - Themistocleous, Charalambos; Ficek, Bronte; Webster, Kimberly; den Ouden, Dirk-Bart; Hillis, Argye E; Tsapkini, Kyrana (J Alzheimers Dis, 2021)
BACKGROUND: The classification of patients with primary progressive aphasia (PPA) into variants is time-consuming, costly, and requires combined expertise by clinical neurologists, neuropsychologists, speech pathologists, and radiologists. OBJECTIVE: The aim of the present study is to determine whether acoustic and linguistic variables provide accurate classification of PPA patients into one of three variants: nonfluent PPA, semantic PPA, and logopenic PPA. METHODS: In this paper, we present a machine learning model based on deep neural networks (DNN) for the subtyping of patients with PPA into three main variants, using combined acoustic and linguistic information elicited automatically via acoustic and linguistic analysis. The performance of the DNN was compared to the classification accuracy of Random Forests, Support Vector Machines, and Decision Trees, as well as to expert clinicians' classifications. RESULTS: The DNN model outperformed the other machine learning models as well as expert clinicians' classifications with 80% classification accuracy. Importantly, 90% of patients with nfvPPA and 95% of patients with lvPPA was identified correctly, providing reliable subtyping of these patients into their corresponding PPA variants. CONCLUSION: We show that the combined speech and language markers from connected speech productions can inform variant subtyping in patients with PPA. The end-to-end automated machine learning approach we present can enable clinicians and researchers to provide an easy, quick, and inexpensive classification of patients with PPA.
Keywords: Acoustics; Aged; Aphasia, Primary Progressive; Decision Trees; Female; Humans; Linguistics; Machine Learning; Male; Models, Theoretical; Neural Networks, Computer; Primary Progressive Nonfluent Aphasia; Reproducibility of Results; Support Vector Machine

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome Scale (BPSD-DS II): Optimization and Further Validation. - Dekker, Alain D; Ulgiati, Aurora M; Groen, Henk; Boxelaar, Vincent A; Sacco, Silvia; Falquero, Ségolène; Carfi, Angelo; di Paola, Antonella; Benejam, Bessy; Valldeneu, Silvia; Fopma, Roelie; Oosterik, Marjo; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with Down syndrome (DS) are at high risk to develop Alzheimer's disease dementia (AD). Behavioral and psychological symptoms of dementia (BPSD) are common and may also serve as early signals for dementia. However, comprehensive evaluation scales for BPSD, adapted to DS, are lacking. Therefore, we previously developed the BPSD-DS scale to identify behavioral changes between the last six months and pre-existing life-long characteristic behavior. OBJECTIVE: To optimize and further study the scale (discriminative ability and reliability) in a large representative DS study population. METHODS: Optimization was based on item irrelevance and clinical experiences obtained in the initial study. Using the shortened and refined BPSD-DS II, informant interviews were conducted to evaluate 524 individuals with DS grouped according to dementia status: no dementia (DS, N = 292), questionable dementia (DS + Q, N = 119), and clinically diagnosed dementia (DS + AD, N = 113). RESULTS: Comparing item change scores between groups revealed prominent changes in frequency and severity for anxious, sleep-related, irritable, restless/stereotypic, apathetic, depressive, and eating/drinking behavior. For most items, the proportion of individuals displaying an increased frequency was highest in DS + AD, intermediate in DS + Q, and lowest in DS. For various items within sections about anxious, sleep-related, irritable, apathetic, and depressive behaviors, the proportion of individuals showing an increased frequency was already substantial in DS + Q, suggesting that these changes may serve as early signals of AD in DS. Reliability data were promising. CONCLUSION: The optimized scale yields largely similar results as obtained with the initial version. Systematically evaluating BPSD in DS may increase understanding of changes among caregivers and (timely) adaptation of care/treatment.
Keywords: Adult; Aged; Anxiety; Dementia; Down Syndrome; Female; Humans; Irritable Mood; Male; Middle Aged; Reproducibility of Results; Symptom Assessment

Body Mass Index and Mild Cognitive Impairment Among Middle-Aged and Older Adults from Low- and Middle-Income Countries. - Smith, Lee; Shin, Jae Il; Oh, Hans; Carmichael, Christina; Jacob, Louis; Stefanac, Sinisa; Lindsay, Rosie K; Soysal, Pinar; Veronese, Nicola; Tully, Mark A; Butler, Laurie; Barnett, Yvonne; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The effect of weight modification on future dementia risk is currently a subject of debate and may be modified by age. OBJECTIVE: The aim of the present study was to investigate the association between body mass index (BMI) status with mild cognitive impairment (MCI) (a preclinical stage of dementia) in middle-aged and older adults residing in six low- and middle-income countries using nationally representative data. METHODS: Cross-sectional data from the Study on Global Ageing and Adult Health (SAGE) were analyzed. MCI was defined using the National Institute on Aging-Alzheimer's Association criteria. BMI (kg/m2) was based on measured weight and height and categorized as: underweight (<18.5), normal (18.5-24.9), overweight (25.0-29.9), and obese (≥30.0). Multivariable logistic regression analysis and meta-analysis were conducted to assess associations. RESULTS: Data on 32,715 individuals aged ≥50 years with preservation in functional abilities were analyzed [mean (SD) age 62.1 (15.6) years; 51.7% females]. Among those aged 50-64 years, compared to normal weight, underweight (OR = 1.44; 95% CI = 1.14-1.81), overweight (OR = 1.17; 95% CI = 1.002-1.37), and obesity (OR = 1.46; 95% CI = 1.09-1.94) were all significantly associated with higher odds for MCI. In those aged ≥65 years, underweight (OR = 0.71; 95% CI = 0.54-0.95) and overweight (OR = 0.72; 95% CI = 0.55-0.94) were associated with significantly lower odds for MCI, while obesity was not significantly associated with MCI. CONCLUSION: The results of the study suggest that the association between BMI and MCI is likely moderated by age. Future longitudinal studies are required to confirm or refute the present findings before recommendations for policy and practice can be made.

Central Obesity, Cardiometabolic Risk, and Cognitive Change in the Study of Latinos: Investigation of Neurocognitive Aging. - Stickel, Ariana M; Tarraf, Wassim; Gonzalez, Kevin A; Isasi, Carmen R; Kaplan, Robert; Gallo, Linda C; Zeng, Donglin; Cai, Jianwen; Pirzada, Amber; Daviglus, Martha L; Goodman, Zachary T; Schneiderman, Neil; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The relationships between obesity and cognitive decline in aging are mixed and understudied among Hispanics/Latinos. OBJECTIVE: To understand associations between central obesity, cognitive aging, and the role of concomitant cardiometabolic abnormalities among Hispanics/Latinos. METHODS: Participants included 6,377 diverse Hispanics/Latinos enrolled in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) and SOL-Investigation for Neurocognitive Aging (SOL-INCA). Participants were 45 years and older at the first cognitive testing session (Visit 1). Cognitive outcomes (z-score units) included global composite and domain specific (learning, memory, executive functioning, processing speed) measures at a second visit (SOL-INCA, on average, 7 years later), and 7-year change. We used survey linear regression to examine associations between central obesity (waist circumference≥88 cm and≥102 cm for women and men, respectively) and cognition. We also tested whether the relationships between obesity and cognition differed by cardiometabolic status (indication of/treatment for 2 + of the following: high triglycerides, hypertension, hyperglycemia, low high-density lipoprotein cholesterol). RESULTS: Central obesity was largely unassociated with cognitive outcomes, adjusting for covariates. However, among individuals with central obesity, cardiometabolic abnormality was linked to poorer cognitive function at SOL-INCA (ΔGlobalCognition =-0.165, p < 0.001) and to more pronounced cognitive declines over the average 7 years (ΔGlobalCognition = -0.109, p < 0.05); this was consistent across cognitive domains. CONCLUSION: Central obesity alone was not associated with cognitive function. However, presence of both central obesity and cardiometabolic abnormalities was robustly predictive of cognition and 7-year cognitive declines, suggesting that in combination these factors may alter the cognitive trajectories of middle-aged and older Hispanics/Latinos.

Cerebrospinal Fluid Proteome Changes in Older Non-Cardiac Surgical Patients with Postoperative Cognitive Dysfunction. - VanDusen, Keith W; Li, Yi-Ju; Cai, Victor; Hall, Ashley; Hiles, Sarah; Thompson, J Will; Moseley, M Arthur; Cooter, Mary; Acker, Leah; Levy, Jerrold H; Ghadimi, Kamrouz; Quiñones, Quintin J; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Postoperative cognitive dysfunction (POCD), a syndrome of cognitive deficits occurring 1-12 months after surgery primarily in older patients, is associated with poor postoperative outcomes. POCD is hypothesized to result from neuroinflammation; however, the pathways involved remain unclear. Unbiased proteomic analyses have been used to identify neuroinflammatory pathways in multiple neurologic diseases and syndromes but have not yet been applied to POCD. OBJECTIVE: To utilize unbiased mass spectrometry-based proteomics to identify potential neuroinflammatory pathways underlying POCD. METHODS: Unbiased LC-MS/MS proteomics was performed on immunodepleted cerebrospinal fluid (CSF) samples obtained before, 24 hours after, and 6 weeks after major non-cardiac surgery in older adults who did (n = 8) or did not develop POCD (n = 6). Linear mixed models were used to select peptides and proteins with intensity differences for pathway analysis. RESULTS: Mass spectrometry quantified 8,258 peptides from 1,222 proteins in > 50%of patient samples at all three time points. Twelve peptides from 11 proteins showed differences in expression over time between patients with versus withoutPOCD (q < 0.05), including proteins previously implicated in neurodegenerative disease pathophysiology. Additionally, 283 peptides from 182 proteins were identified with trend-level differences (q < 0.25) in expression over time between these groups. Among these, pathway analysis revealed that 50 were from 17 proteins mapping to complement and coagulation pathways (q = 2.44*10-13). CONCLUSION: These data demonstrate the feasibility of performing unbiased mass spectrometry on perioperative CSF samples to identify pathways associated with POCD. Additionally, they provide hypothesis-generating evidence for CSF complement and coagulation pathway changes in patients with POCD.

Cognition at Each Stage of Lewy Body Disease with Co-occurring Alzheimer's Disease Pathology. - Ryman, Sephira G; Yutsis, Maya; Tian, Lu; Henderson, Victor W; Montine, Thomas J; Salmon, David P; Galasko, Douglas; Poston, Kathleen L (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease neuropathologic change (ADNC) may contribute to dementia in patients with Lewy body disease (LBD) pathology. OBJECTIVE: To examine how co-occurring ADNC impacts domain specific cognitive impairments at each pathologic stage (brainstem, limbic, cerebral cortical) of LBD. METHODS: 2,433 participants with antemortem longitudinal neuropsychological assessment and postmortem neuropathological assessment from the National Alzheimer's Coordinating Center's Uniform Data Set were characterized based on the evaluation of ADNC and LBD. Longitudinal mixed-models were used to derive measures of cumulative cognitive deficit for each cognitive domain at each pathologic stage of LBD (brainstem, limbic, and cerebral cortical). RESULTS: 111 participants with a pathologic diagnosis of LBD, 741 participants with combined LBD and ADNC, 1,357 participants with ADNC only, and 224 with no pathology (healthy controls) were included in the analyses. In the executive/visuospatial domain, combined LBD and ADNC showed worse deficits than LBD only when Lewy bodies were confined to the brainstem, but no difference when Lewy bodies extended to the limbic or cerebral cortical regions. The cerebral cortical LBD only group exhibited greater executive/visuospatial deficits than the ADNC only group. By contrast, the ADNC only group and the combined pathology group both demonstrated significantly greater cumulative memory deficits relative to Lewy body disease only, regardless of stage. CONCLUSION: The impact of co-occurring ADNC on antemortem cumulative cognitive deficits varies not only by domain but also on the pathological stage of Lewy bodies. Our findings stress the cognitive impact of different patterns of neuropathological progression in Lewy body diseases.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognitive Dysfunction; Female; Humans; Lewy Body Disease; Male

Cognitive Effects of the BET Protein Inhibitor Apabetalone: A Prespecified Montreal Cognitive Assessment Analysis Nested in the BETonMACE Randomized Controlled Trial. - Cummings, Jeffrey; Schwartz, Gregory G; Nicholls, Stephen J; Khan, Aziz; Halliday, Chris; Toth, Peter P; Sweeney, Michael; Johansson, Jan O; Wong, Norman C W; Kulikowski, Ewelina; Kalantar-Zadeh, Kamyar; Lebioda, Kenneth; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Epigenetic changes may contribute importantly to cognitive decline in late life including Alzheimer's disease (AD) and vascular dementia (VaD). Bromodomain and extra-terminal (BET) proteins are epigenetic "readers" that may distort normal gene expression and contribute to chronic disorders. OBJECTIVE: To assess the effects of apabetalone, a small molecule BET protein inhibitor, on cognitive performance of patients 70 years or older participating in a randomized trial of patients at high risk for major cardiovascular events (MACE). METHODS: The Montreal Cognitive Assessment (MoCA) was performed on all patients 70 years or older at the time of randomization. 464 participants were randomized to apabetalone or placebo in the cognition sub-study. In a prespecified analysis, participants were assigned to one of three groups: MoCA score≥26 (normal performance), MoCA score 25-22 (mild cognitive impairment), and MoCA score≤21 (dementia). Exposure to apabetalone was equivalent in the treatment groups in each MoCA-defined group. RESULTS: Apabetalone was associated with an increased total MoCA score in participants with baseline MoCA score of≤21 (p = 0.02). There was no significant difference in change from baseline in the treatment groups with higher MoCA scores. In the cognition study, more patients randomized to apabetalone discontinued study drug for adverse effects (11.3% versus 7.9%). CONCLUSION: In this randomized controlled study, apabetalone was associated with improved cognition as measured by MoCA scores in those with baseline scores of 21 or less. BET protein inhibitors warrant further investigation for late life cognitive disorders.
Keywords: Aged; Cardiovascular Diseases; Cognitive Dysfunction; Epigenesis, Genetic; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Quinazolinones

A Cost-Consequence Analysis of Different Screening Procedures in Alzheimer's Disease: Results from the MOPEAD Project. - Wimo, Anders; Belger, Mark; Bon, Jaka; Jessen, Frank; Dumas, Annette; Kramberger, Milica G; Jamilis, Laura; Johansson, Gunilla; Rodrigo Salas, Adrián; Rodríguez Gómez, Octavio; Sannemann, Lena; Stoekenbroek, Malou; et al. (J Alzheimers Dis, 2021)
BACKGROUND: For care planning and support, under-detection and late diagnosis of Alzheimer's disease (AD) is a great challenge. Models of Patient-Engagement for Alzheimer's Disease (MOPEAD) is an EU-funded project aiming at testing different strategies to improve this situation. OBJECTIVE: To make a cost-consequence analysis of MOPEAD. METHODS: Four screening strategies were tested in five countries (Germany, the Netherlands, Slovenia, Spain, and Sweden): 1) a web-approach; 2) Open-House initiative; 3) in primary care; and 4) by diabetes specialists. Persons-at-risk of AD in all strategies were offered referral to a hospital-based specialist. The primary health-economic outcome was the cost per true-positive case (TP) of AD from the screened population. RESULTS: Of 2,847 screened persons, 1,121 screened positive (39%), 402 were evaluated at memory clinics (14%), and 236 got an AD diagnosis (8%). The cost per TP of those screened was 3,115€ with the web-approach, 2,722€ with the Open-House, 1,530€ in primary care, and 1,190€ by diabetes specialists. Sensitivity analyses that more likely reflect the real-world situation confirmed the results. The number-needed-to-screen was 30 with the web-approach, 8 with the Open-House and primary care, and 6 with the diabetes specialists.There were country differences in terms of screening rates, referrals to memory clinics, staff-types involved, and costs per TP. CONCLUSION: In primary care and by the diabetes specialist, the costs per TP/screened population were lowest, but the capacity of such settings to identify cases with AD-risk must be discussed. Hence new diagnostic strategies such as web-solutions and Open-House initiatives may be valuable after modifications.

Current and Future Prevalence Estimates of Mild Cognitive Impairment, Dementia, and Its Subtypes in a Population-Based Sample of People 70 Years and Older in Norway: The HUNT Study. - GjØra, Linda; Strand, Bjørn Heine; Bergh, Sverre; Borza, Tom; Brækhus, Anne; Engedal, Knut; Johannessen, Aud; Kvello-Alme, Marte; Krokstad, Steinar; Livingston, Gill; Matthews, Fiona E; Myrstad, Christian; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Having accurate, up-to-date information on the epidemiology of mild cognitive impairment (MCI) and dementia is imperative. OBJECTIVE: To determine the prevalence of MCI and dementia in Norway using data from a large population-based study. METHODS: All people 70 + years of age, n = 19,403, in the fourth wave of the Trøndelag Health Study (HUNT4) were invited to participate in the study HUNT4 70 + . Trained health personnel assessed participants using cognitive tests at a field station, at homes, or at their nursing home. Interviewers also completed a structured carer questionnaire in regard to participants suspected of having dementia. Clinical experts made diagnoses according to DSM-5 criteria. We calculated prevalence weighing the data to ensure population representativeness. RESULTS: A total of 9,930 (51.2%) of the possible 19,403 people participated, and 9,663 of these had sufficient information for analysis. Standardized prevalence of dementia and MCI was 14.6% (95% confidence interval (CI) 13.9-15.4) and 35.3% (95% CI 34.3-36.4), respectively. Dementia was more prevalent in women and MCI more prevalent in men. The most prevalent dementia subtype was Alzheimer's disease (57%). By adding data collected from a study of persons < 70 years in the same region, we estimate that there are 101,118 persons with dementia in Norway in 2020, and this is projected to increase to 236,789 and 380,134 in 2050 and 2100, respectively. CONCLUSION: We found a higher prevalence of dementia and MCI than most previous studies. The present prevalence and future projections are vital for preparing for future challenges to the healthcare system and the entire society.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Forecasting; Humans; Male; Mental Status and Dementia Tests; Neuropsychological Tests; Norway; Prevalence; Sex Factors; Surveys and Questionnaires

Dementia and COVID-19, a Bidirectional Liaison: Risk Factors, Biomarkers, and Optimal Health Care. - Toniolo, Sofia; Scarioni, Marta; Di Lorenzo, Francesco; Hort, Jakub; Georges, Jean; Tomic, Svetlana; Nobili, Flavio; Frederiksen, Kristian Steen (J Alzheimers Dis, 2021)
Cognitive impairment following SARS-CoV-2 infection is being increasingly recognized as an acute and possibly also long-term sequela of the disease. Direct viral entry as well as systemic mechanisms such as cytokine storm are thought to contribute to neuroinflammation in these patients. Biomarkers of COVID-19-induced cognitive impairment are currently lacking, but there is some limited evidence that SARS-CoV-2 could preferentially target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET. Possible confounders include cognitive impairment due to hypoxia and mechanical ventilation and post-traumatic stress disorder. Conversely, patients already suffering from dementia, as well as their caregivers, have been greatly impacted by the disruption of their care caused by COVID-19. Patients with dementia have experienced worsening of cognitive, behavioral, and psychological symptoms, and the rate of COVID-19-related deaths is disproportionately high among cognitively impaired people. Multiple factors, such as difficulties in remembering and executing safeguarding procedures, age, comorbidities, residing in care homes, and poorer access to hospital standard of care play a role in the increased morbidity and mortality. Non-pharmacological interventions and new technologies have shown a potential for the management of patients with dementia, and for the support of their caregivers.
Keywords: Alzheimer Disease; Biomarkers; Brain; Cognitive Dysfunction; Comorbidity; COVID-19; Humans; Neuroimaging; Neuroimmunomodulation; Patient Care; SARS-CoV-2

Depression and Dementia: The Role of Cortisol and Vascular Brain Lesions. AGES-Reykjavik Study. - Gerritsen, Lotte; Twait, Emma L; Jonsson, Palmi V; Gudnason, Vilmundur; Launer, Lenore J; Geerlings, Mirjam I (J Alzheimers Dis, 2021)
BACKGROUND: Late-life depression (LLD) is related to an increased risk of developing dementia; however, the biological mechanisms explaining this relationship remain unclear. OBJECTIVE: To determine whether the relationship between LLD and dementia can be best explained by the glucocorticoid cascade or vascular hypothesis. METHODS: Data are from 4,354 persons (mean age 76±5 years) without dementia at baseline from the AGES-Reykjavik Study. LLD was assessed with the MINI diagnostic interview (current and remitted major depressive disorder [MDD]) and the Geriatric Depression Scale-15. Morning and evening salivary cortisol were collected (glucocorticoid cascade hypothesis). White matter hyperintensities (WMH; vascular hypothesis) volume was assessed using 1.5T brain MRI. Using Cox proportional hazard models, we estimated the associations of LLD, cortisol levels, and WMH volume with incident all-cause dementia, AD, and non-AD dementia. RESULTS: During 8.8±3.2 years of follow-up, 843 persons developed dementia, including 397 with AD. Current MDD was associated with an increased risk of developing all-cause dementia (HR = 2.17; 95% CI 1.66-2.67), with risks similar for AD and non-AD, while remitted MDD was not (HR = 1.02; 95% CI 0.55-1.49). Depressive symptoms were also associated with increased risk of dementia, in particular non-AD dementias. Higher levels of evening cortisol increased risk of dementia, but this was independent of MDD. WMH partially explained the relation between current MDD and dementia risk but remained increased (HR = 1.71; 95% CI 1.34-2.08). CONCLUSION: The current study highlights the importance of LLD in developing dementia. However, neither the glucocorticoid cascade nor the vascular hypotheses fully explained the relation between depression and dementia.

Different Inflammatory Signatures in Alzheimer's Disease and Frontotemporal Dementia Cerebrospinal Fluid. - Boström, Gustaf; Freyhult, Eva; Virhammar, Johan; Alcolea, Daniel; Tumani, Hayrettin; Otto, Markus; Brundin, Rose-Marie; Kilander, Lena; Löwenmark, Malin; Giedraitis, Vilmantas; Lleo, Alberto; von Arnim, Christine A F; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Neuroinflammatory processes are common in neurodegenerative diseases such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), but current knowledge is limited as to whether cerebrospinal fluid (CSF) levels of neuroinflammatory proteins are altered in these diseases. OBJECTIVE: To identify and characterize neuroinflammatory signatures in CSF from patients with AD, mild cognitive impairment (MCI), and FTD. METHODS: We used proximity extension assay and ANOVA to measure and compare levels of 92 inflammatory proteins in CSF from 42 patients with AD, 29 with MCI due to AD (MCI/AD), 22 with stable MCI, 42 with FTD, and 49 control subjects, correcting for age, gender, collection unit, and multiple testing. RESULTS: Levels of matrix metalloproteinase-10 (MMP-10) were increased in AD, MCI/AD, and FTD compared with controls (AD: fold change [FC] = 1.32, 95% confidence interval [CI] 1.14-1.53, q = 0.018; MCI/AD: FC = 1.53, 95% CI 1.20-1.94, q = 0.045; and FTD: FC = 1.42, 95% CI 1.10-1.83, q = 0.020). MMP-10 and eleven additional proteins were increased in MCI/AD, compared with MCI (q < 0.05). In FTD, 36 proteins were decreased, while none was decreased in AD or MCI/AD, compared with controls (q < 0.05). CONCLUSION: In this cross-sectional multi-center study, we found distinct patterns of CSF inflammatory marker levels in FTD and in both early and established AD, suggesting differing neuroinflammatory processes in the two disorders.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Frontotemporal Dementia; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; tau Proteins

Economic Burden of Alzheimer's Disease Dementia in Japan. - Ikeda, Shunya; Mimura, Masaru; Ikeda, Manabu; Wada-Isoe, Kenji; Azuma, Mie; Inoue, Sachie; Tomita, Kiyoyuki (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease dementia (ADD) is the leading cause of long-term care in Japan. OBJECTIVE: This study estimates the annual healthcare and long-term care costs in fiscal year 2018 for adults over 65 years of age with ADD in Japan and the informal care costs and productivity loss for their families. METHODS: Healthcare and long-term care costs for ADD were estimated according to the disease severity classified by the clinical dementia rating (CDR) score, using reports from a literature review. For the costs of time spent on caregiving activities, productivity loss for ADD family caregivers aged 20-69 and informal care costs for all ADD family caregivers were estimated. RESULTS: The total healthcare cost of ADD was JPY 1,073 billion, of which 86% (JPY 923 billion) was attributed to healthcare costs other than ADD drug costs (JPY 151 billion). The healthcare costs other than ADD drug costs by severity were less than JPY 200 billion for CDR 0.5, CDR 1, and CDR 2, respectively, but increased to JPY 447 billion (48%) for CDR 3. The public long-term care costs were estimated to be JPY 4,783 billion, which increased according to the severity. Total productivity loss for ADD family caregivers aged 20-69 was JPY 1,547 billion and the informal care cost for all ADD family caregivers was JPY 6,772 billion. CONCLUSION: ADD costs have a significant impact on public-funded healthcare, long-term care systems, and families in Japan. To minimize the economic burden of ADD, prolonging healthy life expectancy is the key factor to address.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Female; Health Care Costs; Humans; Japan; Long-Term Care; Male

Effects of High Definition-Transcranial Direct Current Stimulation on Local GABA and Glutamate Levels Among Older Adults with and without Mild Cognitive Impairment: An Exploratory Study. - Lengu, Ketrin; Ryan, Shannon; Peltier, Scott J; Tyszkowski, Troy; Kairys, Anson; Giordani, Bruno; Hampstead, Benjamin M (J Alzheimers Dis, 2021)
BACKGROUND: Prior research, primarily with young adults, suggests transcranial direct current stimulation (tDCS) effects are driven by the primary excitatory and/or inhibitory neurotransmitters, glutamate, and gamma-aminobutyric acid (GABA), respectively. OBJECTIVE: We examined the neurometabolic mechanisms of tDCS in older adults with and without mild cognitive impairment (MCI). METHODS: We used data from a double-blind, cross-over, randomized controlled trial (NCT01958437) in 32 older adults to evaluate high definition (HD)-tDCS-induced changes in glutamate and GABA via magnetic resonance spectroscopy (MRS). Participants underwent MRS following two counterbalanced HD-tDCS sessions (one active, one sham) that targeted the right superior parietal cortex (center anode at P2) and delivered 2mA for 20 minutes. RESULTS: Relative to sham, and when co-varying for MRS voxel overlap and right superior parietal volume, active HD-tDCS significantly increased GABA and decreased the ratio of glutamate to GABA. No changes were observed in a left prefrontal control MRS voxel. Although we did not find a significant correlation between strength of delivered current (measured via MRI-based computational modeling) and neurometabolite change, there was a robust positive relationship between the volume of right superior parietal cortex and neurometabolite change. CONCLUSION: Our preliminary findings of increased GABA and reduced glutamate/GABA ratio raise the possibility that (HD-)tDCS effects differ by age. Moreover, age- and disease-related regional brain volume loss may be especially important to consider when planning future studies. Replication would emphasize the importance of developing population-specific tDCS parameters that consider structural and physiologic changes associated with "normal" and pathological aging.

Effects of Peroral Omega-3 Fatty Acid Supplementation on Cerebrospinal Fluid Biomarkers in Patients with Alzheimer's Disease: A Randomized Controlled Trial-The OmegAD Study. - Tofiq, Avin; Zetterberg, Henrik; Blennow, Kaj; Basun, Hans; Cederholm, Tommy; Eriksdotter, Maria; Faxen-Irving, Gerd; Hjorth, Erik; Jernerén, Fredrik; Schultzberg, Marianne; Wahlund, Lars-Olof; Palmblad, Jan; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Studies have suggested a connection between a decrease in the levels of polyunsaturated fatty acids (PUFAs) and Alzheimer's disease (AD). We aimed to assess the effect of supplementation with omega-3 fatty acids (n-3 FAs) on biomarkers analyzed in the cerebrospinal fluid (CSF) of patients diagnosed with AD. OBJECTIVE: To investigate the effects of daily supplementation with 2.3 g of PUFAs in AD patients on the biomarkers in CSF described below. We also explored the possible correlation between these biomarkers and the performance in the cognitive test Mini-Mental State Examination (MMSE). METHODS: Thirty-three patients diagnosed with AD were randomized to either treatment with a daily intake of 2.3 g of n-3 FAs (n  =  18) or placebo (n  =  15). CSF samples were collected at baseline and after six months of treatment, and the following biomarkers were analyzed: Aβ 38, Aβ 40, Aβ 42, t-tau, p-tau, neurofilament light (NfL), chitinase-3-like protein 1 (YKL-40), acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), soluble IL-1 receptor type II (sIL-1RII), and IL-6. RESULTS: There were no significant differences between the groups concerning the level of the different biomarkers in the CSF at baseline. Within the treatment group, there was a small but significant increase in both YKL-40 (p = 0.04) and NfL (p = 0.03), while the other CSF biomarkers remained stable. CONCLUSION: Supplementation with n-3 FAs had a statistically significant effect on NfL and YKL-40, resulting in an increase of both biomarkers, indicating a possible increase of inflammatory response and axonal damage. This increase in biomarkers did not correlate with MMSE score.

Egocentric and Allocentric Spatial Memory in Mild Cognitive Impairment with Real-World and Virtual Navigation Tasks: A Systematic Review. - Tuena, Cosimo; Mancuso, Valentina; Stramba-Badiale, Chiara; Pedroli, Elisa; Stramba-Badiale, Marco; Riva, Giuseppe; Repetto, Claudia (J Alzheimers Dis, 2021)
BACKGROUND: Spatial navigation is the ability to estimate one's position on the basis of environmental and self-motion cues. Spatial memory is the cognitive substrate underlying navigation and relies on two different reference frames: egocentric and allocentric. These spatial frames are prone to decline with aging and impairment is even more pronounced in Alzheimer's disease (AD) or in mild cognitive impairment (MCI). OBJECTIVE: To conduct a systematic review of experimental studies investigating which MCI population and tasks are used to evaluate spatial memory and how allocentric and egocentric deficits are impaired in MCI after navigation. METHODS: PRISMA and PICO guidelines were applied to carry out the systematic search. Down and Black checklist was used to assess methodological quality. RESULTS: Our results showed that amnestic MCI and AD pathology are the most investigated typologies; both egocentric and allocentric memory are impaired in MCI individuals, and MCI due to AD biomarkers has specific encoding and retrieval impairments; secondly, spatial navigation is principally investigated with the hidden goal task (virtual and real-world version), and among studies involving virtual reality, the privileged setting consists of non-immersive technology; thirdly, despite subtle differences, real-world and virtual versions showed good overlap for the assessment of MCI spatial memory. CONCLUSION: Considering that MCI is a subclinical entity with potential risk for conversion to dementia, investigating spatial memory deficits with navigation tasks might be crucial to make accurate diagnosis and rehabilitation.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Spatial Memory; Spatial Navigation

Entorhinal Perfusion Predicts Future Memory Decline, Neurodegeneration, and White Matter Hyperintensity Progression in Older Adults. - Bangen, Katherine J; Thomas, Kelsey R; Sanchez, Danielle L; Edmonds, Emily C; Weigand, Alexandra J; Delano-Wood, Lisa; Bondi, Mark W (J Alzheimers Dis, 2021)
BACKGROUND: Altered cerebral blood flow (CBF) has been linked to increased risk for Alzheimer's disease (AD). However, whether altered CBF contributes to AD risk by accelerating cognitive decline remains unclear. It also remains unclear whether reductions in CBF accelerate neurodegeneration and development of small vessel cerebrovascular disease. OBJECTIVE: To examine associations between CBF and trajectories of memory performance, regional brain atrophy, and global white matter hyperintensity (WMH) volume. METHOD: 147 Alzheimer's Disease Neuroimaging Initiative participants free of dementia underwent arterial spin labeling (ASL) magnetic resonance imaging (MRI) to measure CBF and serial neuropsychological and structural MRI examinations. Linear mixed effects models examined 5-year rate of change in memory and 4-year rate of change in regional brain atrophy and global WMH volumes as a function of baseline regional CBF. Entorhinal and hippocampal CBF were examined in separate models. RESULTS: Adjusting for demographic characteristics, pulse pressure, apolipoprotein E ɛ4 positivity, cerebrospinal fluid p-tau/Aβ ratio, and neuronal metabolism (i.e., fluorodeoxyglucose standardized uptake value ratio), lower baseline entorhinal CBF predicted faster rates of decline in memory as well as faster entorhinal thinning and WMH progression. Hippocampal CBF did not predict cognitive or brain structure trajectories. CONCLUSION: Findings highlight the importance of early cerebrovascular dysfunction in AD risk and suggest that entorhinal CBF as measured by noninvasive ASL MRI is a useful biomarker predictive of future cognitive decline and of risk of both.

Is the Frontal Lobe the Primary Target of SARS-CoV-2? - Toniolo, Sofia; Di Lorenzo, Francesco; Scarioni, Marta; Frederiksen, Kristian Steen; Nobili, Flavio (J Alzheimers Dis, 2021)
Acute delirium and other neuropsychiatric symptoms have frequently been reported in COVID-19 patients and are variably referred to as acute encephalopathy, COVID-19 encephalopathy, SARS-CoV-2 encephalitis, or steroid-responsive encephalitis. COVID-19 specific biomarkers of cognitive impairment are currently lacking, but there is some evidence that SARS-CoV-2 could preferentially and directly target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET imaging. We suggest that an inflammatory parainfectious process targeting preferentially the frontal lobes (and/or frontal networks) could be the underlying cause of these shared clinical, neurophysiological, and imaging findings in COVID-19 patients. We explore the biological mechanisms and the clinical biomarkers that might underlie such disruption of frontal circuits and highlight the need of standardized diagnostic procedures to be applied when investigating patients with these clinical findings. We also suggest the use of a unique label, to increase comparability across studies.
Keywords: Acute Febrile Encephalopathy; Biomarkers; COVID-19; Delirium; Electroencephalography; Frontal Lobe; Humans; Magnetic Resonance Imaging; Nerve Net; SARS-CoV-2; Virulence

The Impact of a Global Pandemic on People Living with Dementia and Their Care Partners: Analysis of 417 Lived Experience Reports. - Tam, Mallorie T; Dosso, Jill A; Robillard, Julie M (J Alzheimers Dis, 2021)
BACKGROUND: The COVID-19 pandemic is impacting the physical and emotional health of older adults living with dementia and their care partners. OBJECTIVE: Using a patient-centered approach, we explored the experiences and needs of people living with dementia and their care partners during the COVID-19 pandemic as part of an ongoing evaluation of dementia support services in British Columbia, Canada. METHODS: A survey instrument was developed around the priorities identified in the context of the COVID-19 and Dementia Task Force convened by the Alzheimer Society of Canada. RESULTS: A total of 417 surveys were analyzed. Overall, respondents were able to access information that was helpful for maintaining their own health and managing a period of social distancing. Care partners reported a number of serious concerns, including the inability to visit the person that they care for in long-term or palliative care. Participants also reported that the pandemic increased their levels of stress overall and that they felt lonelier and more isolated than they did before the pandemic. The use of technology was reported as a way to connect socially with their loved ones, with the majority of participants connecting with others at least twice per week. CONCLUSION: Looking at the complex effects of a global pandemic through the experiences of people living with dementia and their care partners is vital to inform healthcare priorities to restore their quality of life and health and better prepare for the future.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; British Columbia; Caregivers; COVID-19; Disabled Persons; Female; Humans; Loneliness; Male; Needs Assessment; Psychosocial Support Systems; Social Isolation; Social Support; Stress, Psychological; Surveys and Questionnaires

Impact of Social Isolation on People with Dementia and Their Family Caregivers. - Azevedo, Lílian Viana Dos Santos; Calandri, Ismael Luis; Slachevsky, Andrea; Graviotto, Héctor Gastón; Vieira, Maria Carolina Santos; Andrade, Caíssa Bezerra de; Rossetti, Adriana Peredo; Generoso, Alana Barroso; Carmona, Karoline Carvalho; Pinto, Ludmilla Aparecida Cardoso; Sorbara, Marcos; Pinto, Alejandra; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with dementia and their family caregivers may face a great burden through social isolation due to the COVID-19 pandemic, which can be manifested as various behavioral and clinical symptoms. OBJECTIVE: To investigate the impacts of social isolation due to the COVID-19 pandemic on individuals with dementia and their family caregivers. METHODS: Two semi-structured questionnaires were applied via telephone to family caregivers of people diagnosed with dementia in three cities in Argentina, Brazil, and Chile, in order to assess clinical and behavioral changes in people with dementia and in their caregivers. RESULTS: In general, 321 interviews were conducted. A significant decline in memory function has been reported among 53.0%of people with dementia. In addition, 31.2%of individuals with dementia felt sadder and 37.4%had increased anxiety symptoms. These symptoms of anxiety were greater in individuals with mild to moderate dementia, while symptoms of agitation were greater in individuals with severe dementia. Moreover, compulsive-obsessive behavior, hallucinations, increased forgetfulness, altered appetite, and increased difficulty in activities of daily living were reported more frequently among individuals with moderate to severe dementia. Caregivers reported feeling more tired and overwhelmed during this period and these symptoms were also influenced by the severity of dementia. CONCLUSION: Social isolation during the COVID-19 pandemic triggered a series of negative behavioral repercussions, both for people with dementia and for their family caregivers in these three South American countries.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Argentina; Brazil; Caregivers; Chile; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Pandemics; Physical Distancing; Social Isolation; Surveys and Questionnaires

Improving the Diagnosis of the Frontal Variant of Alzheimer's Disease with the DAPHNE Scale. - Lehingue, Elsa; Gueniat, Julien; Jourdaa, Sandra; Hardouin, Jean BenoÎt; Pallardy, Amandine; Courtemanche, Hélène; Rocher, Laetitia; Etcharry-Bouyx, Frédérique; Auriacombe, Sophie; Mollion, Hélène; Formaglio, Maıté; Rouaud, Olivier; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The frontal variant of Alzheimer's disease (fAD) is poorly understood and poorly defined. The diagnosis remains challenging. The main differential diagnosis is the behavioral variant of frontotemporal degeneration (bvFTD). For fAD, there is some dissociation between the clinical frontal presentation and imaging and neuropathological studies, which do not always find a specific involvement of the frontal lobes. DAPHNE is a behavioral scale, which demonstrated excellent performance to distinguish between bvFTD and AD. OBJECTIVE: The aim of the present study was to assess the reliability of this new tool to improve the clinical diagnosis of fAD. METHODS: Twenty fAD patients and their caregivers were prospectively included and were compared with 36 bvFTD and 22 AD patients. RESULTS: The three main behavioral disorders in the fAD patients were apathy, loss of empathy, and disinhibition. Three disorders were discriminant because they were less frequent and less severe in the fAD patients than in the bvFTD patients, namely hyperorality, neglect, and perseverations. This specific pattern of behavioral disorders was corroborated by SPECT or 18FDG PET-CT scan that showed that patients with fAD could have a medial frontal hypoperfusion, whereas in bvFTD patients the orbitofrontal cortex was the main involved region, with more diffuse hypoperfusion. CONCLUSION: We demonstrated that DAPHNE had good sensitivity and good specificity to discriminate between the three groups and in particular between fAD and bvFTD patients. DAPHNE is a quick tool that could help clinicians in memory clinics not only to differentiate bvFTD from typical AD but also from fAD.
Keywords: Aged; Alzheimer Disease; Cohort Studies; Diagnosis, Differential; Female; Frontal Lobe; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests

In Vivo Amyloid, Neurodegeneration, and Verbal Learning in Late Middle-Aged Hispanics. - Tahmi, Mouna; Rippon, Brady; Palta, Priya; Sherwood, Greysi; Hernandez, Gabriela; Soto, Luisa; Ceballos, Fernando; Pardo, Michelle; Laing, Krystal; Igwe, Kay; He, Hengda; Teresi, Jeanne A; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The National Institute on Aging (NIA)/Alzheimer's Association (AA) 2018 framework conceptualizes Alzheimer's disease (AD) biologically. Evidence of brain amyloid by biomarkers defines AD pathologic change and the Alzheimer's continuum. The presence of tau or neurodegeneration in the absence of amyloid defines non-AD pathologic change. OBJECTIVE: To examine the relation of in vivo amyloid and neurodegeneration with verbal learning, one of the cognitive abilities affected early in AD, in late middle age. METHODS: This was a cross-sectional study of amyloid and neurodegeneration biomarkers in a community-based cohort of 350 late-middle aged Hispanics without dementia (mean age: 64.15±3.34; 72.0%women). Amyloid (A) was measured as global standardized uptake value ratio (SUVR) with 18F-Florbetaben positron emission tomography (PET). Neurodegeneration (N) was ascertained as cortical thickness (CT) in AD signature areas using brain magnetic resonance imaging. We examined A/N continuously, categorically, by A/N profiles, and profile categories. The amyloid threshold for positivity was defined using the K means method. The CT threshold was defined as 2 standard deviations below the mean CT. Verbal learning was ascertained using total recall and delayed recall in the Buschke Selective Reminding test (SRT). RESULTS: Higher cortical thickness was associated with higher performance in SRT delayed recall. Amyloid SUVR was not related to SRT performance. The low CT category was associated with lower performance in SRT delayed recall, while Amyloid categories were not related to any SRT score. The non-AD pathologic change group (A-N+) performed worse in SRT delayed recall compared to the Normal A/N profile group (A-N-). CONCLUSION: In late middle-aged Hispanics without dementia, non-AD pathologic change, but not the Alzheimer's continuum, was related to verbal learning.

Incremental Healthcare Utilization and Cost Burden of Comorbid Insomnia in Alzheimer's Disease Patients. - Qureshi, Zaina P; Thiel, Ellen; Nelson, James; Khandker, Rezaul (J Alzheimers Dis, 2021)
BACKGROUND: Insomnia is associated with worsened clinical outcomes among Alzheimer's disease dementia (AD) patients, increased caregiver burden, and healthcare utilization. OBJECTIVE: This study aimed to characterize the incremental healthcare burden of insomnia in AD using real-world data. METHODS: A retrospective observational study was conducted on AD patients selected from the IBM® MarketScan Commercial and Medicare Supplemental Databases. AD patients with claims-based evidence of insomnia were direct matched to a non-insomnia cohort based on demographic factors. Healthcare utilization and associated costs were assessed for a 12-month follow-up period. RESULTS: A total of 3,500 insomnia AD patients and 9,884 non-insomnia AD patients were analyzed. The insomnia cohort had a higher comorbidity burden at baseline (mean score on Charlson Comorbidity Index 2.5 versus 2.2, p < 0.001) and higher proportions of patients with baseline diagnoses for other conditions including depression: 40%, insomnia cohort versus 25%, non-insomnia (p < 0.001). AD patients with insomnia were more likely to have a claim for inpatient hospitalizations (39.8%versus 32.3%), emergency room services (56.4%versus 48.0%), and skilled-nursing services (42.6%versus 31.9%) (all p < 0.05). Mean total annual healthcare costs during the 12-month follow-up period were significantly higher among AD patients with insomnia as compared to those without. (Mean costs: $37,356 versus $27,990, p < 0.001). CONCLUSION: AD patients with comorbid insomnia are more likely to use higher-cost healthcare services such as inpatient hospitalization, and skilled nursing, and have higher total healthcare costs. This real-world analysis provides evidence that AD disease management should consider proper treatment of comorbid insomnia due to the incremental burden and cost implications.
Keywords: Aged, 80 and over; Alzheimer Disease; Comorbidity; Databases, Factual; Female; Health Care Costs; Humans; Male; Medicare; Patient Acceptance of Health Care; Retrospective Studies; Sleep Initiation and Maintenance Disorders; United States

Internal Jugular Vein Velocity and Spontaneous Echo Contrast Correlate with Alzheimer's Disease and Cognitive Function. - Matsuzono, Kosuke; Suzuki, Masayuki; Miura, Kumiko; Ozawa, Tadashi; Mashiko, Takafumi; Koide, Reiji; Tanaka, Ryota; Fujimoto, Shigeru (J Alzheimers Dis, 2021)
BACKGROUND: Many issues persist in the today's Alzheimer's disease (AD) screening and the breakthrough method is desired. OBJECTIVE: We aim to validate the association between venous reflux and AD, and to develop a new method for AD screening. METHODS: We examined spontaneous echo contrast, area, diameter, retrograde velocity, and anterograde velocity of the bilateral cervical internal jugular vein (IJV) using carotid ultrasonography. RESULTS: A total of 112 patients participated in this study, with 26 diagnosed as AD. The proportion of both or either IJV spontaneous echo contrast (+) occupied 25 of total 26 AD patients, which showed 96.2%of sensitivity and 98.5%negative predictive value. The IJV velocities also showed significant correlation with AD diagnosis, although the IJV area or diameter did not. CONCLUSION: Our results indicate that the validation of the spontaneous echo contrast or velocities of the IJV are convenient AD diagnosis screening methods and that the venous reflux disturbance correlates with AD development.

An Introduction to Ultrasensitive Assays for Plasma Tau Detection. - Ding, Xu-Long; Tuo, Qing-Zhang; Lei, Peng (J Alzheimers Dis, 2021)
The detection of plasma tau and its phosphorylation is technically challenging due to the relatively low sensitivity. However, in Alzheimer's disease and other tauopathies, it is hypothesized that tau in the biofluid may serve as a biomarker. In recent years, several ultrasensitive assays have been developed, which can successfully detect tau and its phosphorylation in various biofluids, and collectively demonstrated the prognostic and diagnostic value of plasma tau/phosphorylated tau. Here we have summarized the principle of four ultrasensitive assays newly developed suitable for plasma tau detection, namely single-molecule array, immunomagnetic reduction assay, enhanced immunoassay using multi-arrayed fiber optics, and meso scale discovery assay, with their advantages and applications. We have also compared these assays with traditional enzyme-linked-immunosorbent serologic assay, hoping to facilitate future tau-based biomarker discovery for Alzheimer's disease and other neurodegenerative diseases.
Keywords: Alzheimer Disease; Biological Assay; Biomarkers; Enzyme-Linked Immunosorbent Assay; Humans; Phosphorylation; tau Proteins

Life Course Air Pollution Exposure and Cognitive Decline: Modelled Historical Air Pollution Data and the Lothian Birth Cohort 1936. - Russ, Tom C; Cherrie, Mark P C; Dibben, Chris; Tomlinson, Sam; Reis, Stefan; Dragosits, Ulrike; Vieno, Massimo; Beck, Rachel; Carnell, Ed; Shortt, Niamh K; Muniz-Terrera, Graciela; Redmond, Paul; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Air pollution has been consistently linked with dementia and cognitive decline. However, it is unclear whether risk is accumulated through long-term exposure or whether there are sensitive/critical periods. A key barrier to clarifying this relationship is the dearth of historical air pollution data. OBJECTIVE: To demonstrate the feasibility of modelling historical air pollution data and using them in epidemiologicalmodels. METHODS: Using the EMEP4UK atmospheric chemistry transport model, we modelled historical fine particulate matter (PM2.5) concentrations for the years 1935, 1950, 1970, 1980, and 1990 and combined these with contemporary modelled data from 2001 to estimate life course exposure in 572 participants in the Lothian Birth Cohort 1936 with lifetime residential history recorded. Linear regression and latent growth models were constructed using cognitive ability (IQ) measured by the Moray House Test at the ages of 11, 70, 76, and 79 years to explore the effects of historical air pollution exposure. Covariates included sex, IQ at age 11 years, social class, and smoking. RESULTS: Higher air pollution modelled for 1935 (when participants would have been in utero) was associated with worse change in IQ from age 11-70 years (β = -0.006, SE = 0.002, p = 0.03) but not cognitive trajectories from age 70-79 years (p > 0.05). There was no support for other critical/sensitive periods of exposure or an accumulation of risk (all p > 0.05). CONCLUSION: The life course paradigm is essential in understanding cognitive decline and this is the first study to examine life course air pollution exposure in relation to cognitive health.
Keywords: Adolescent; Adult; Aged; Air Pollution; Child; Cognitive Dysfunction; Environmental Exposure; Female; History, 20th Century; Humans; Linear Models; Male; Middle Aged; Particulate Matter; Scotland; Young Adult

Loneliness, Not Social Support, Is Associated with Cognitive Decline and Dementia Across Two Longitudinal Population-Based Cohorts. - Freak-Poli, Rosanne; Wagemaker, Nina; Wang, Rui; Lysen, Thom S; Ikram, M Arfan; Vernooij, Meike W; Dintica, Christina S; Vernooij-Dassen, Myrra; Melis, Rene J M; Laukka, Erica J; Fratiglioni, Laura; Xu, Weili; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Poor social health is likely associated with cognitive decline and risk of dementia; however, studies show inconsistent results. Additionally, few studies separate social health components or control for mental health. OBJECTIVE: To investigate whether loneliness and social support are independently associated with cognitive decline and risk of dementia, and whether depressive symptoms confound the association. METHODS: We included 4,514 participants from the population-based Rotterdam Study (RS; aged 71±7SD years) followed up to 14 years (median 10.8, interquartile range 7.4-11.6), and 2,112 participants from the Swedish National Study on Aging and Care in Kungsholmen (SNAC-K; aged 72±10SD years) followed up to 10 years (mean 5.9±1.6SD). At baseline, participants were free of major depression and scored on the Mini-Mental State Examination (MMSE) ≥26 for RS and ≥25 for SNAC-K. We investigated loneliness, perceived social support, and structural social support (specifically marital status and number of children). In both cohorts, dementia was diagnosed and cognitive function was repeatedly assessed with MMSE and a global cognitive factor (g-factor). RESULTS: Loneliness was prospectively associated with a decline in the MMSE in both cohorts. Consistently, persons who were lonely had an increased risk of developing dementia (RS: HR 1.34, 95%CI 1.08-1.67; SNAC-K: HR 2.16, 95%CI 1.12-4.17). Adjustment for depressive symptoms and exclusion of the first 5 years of follow-up did not alter results. Neither perceived or structural social support was associated with cognitive decline or dementia risk. CONCLUSION: Loneliness, not social support, predicted cognitive decline and incident dementia independently of depressive symptoms.

Longitudinal Trajectories in Cortical Thickness and Volume Atrophy: Superior Cognitive Performance Does Not Protect Against Brain Atrophy in Older Adults. - Gardener, Samantha L; Weinborn, Michael; Sohrabi, Hamid R; Doecke, James D; Bourgeat, Pierrick; Rainey-Smith, Stephanie R; Shen, Kai-Kai; Fripp, Jurgen; Taddei, Kevin; Maruff, Paul; Salvado, Olivier; Savage, Greg; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Previous research has identified a small subgroup of older adults that maintain a high level of cognitive functioning well into advanced age. Investigation of those with superior cognitive performance (SCP) for their age is important, as age-related decline has previously been thought to be inevitable. OBJECTIVE: Preservation of cortical thickness and volume was evaluated in 76 older adults with SCP and 100 typical older adults (TOAs) assessed up to five times over six years. METHODS: Regions of interest (ROIs) found to have been associated with super-aging status (a construct similar to SCP status) in previous literature were investigated, followed by a discovery phase analyses of additional regions. SCPs were aged 70 + at baseline, scoring at/above normative memory (CVLT-II) levels for demographically similar individuals aged 30-44 years old, and in the unimpaired range for all other cognitive domains over the course of the study. RESULTS: In linear mixed models, following adjustment for multiple comparisons, there were no significant differences between rates of thinning or volume atrophy between SCPs and TOAs in previously identified ROIs, or the discovery phase analyses. With only amyloid-β negative individuals in the analyses, again there were no significant differences between SCPs and TOAs. CONCLUSION: The increased methodological rigor in classifying groups, together with the influence of cognitive reserve, are discussed as potential factors accounting for our findings as compared to the extant literature on those with superior cognitive performance for their age.

Lung Function Impairment and the Risk of Incident Dementia: The Rotterdam Study. - Xiao, Tian; Wijnant, Sara R A; Licher, Silvan; Terzikhan, Natalie; Lahousse, Lies; Ikram, M Kamran; Brusselle, Guy G; Ikram, M Arfan (J Alzheimers Dis, 2021)
BACKGROUND: The etiology of dementia may partly be underpinned by impaired lung function via systemic inflammation and hypoxia. OBJECTIVE: To prospectively examine the association between chronic obstructive pulmonary disease (COPD) and subclinical impairments in lung function and the risk of dementia. METHODS: In the Rotterdam Study, we assessed the risk of incident dementia in participants with Preserved Ratio Impaired Spirometry (PRISm; FEV1/FVC≥0.7, FEV1 < 80% predicted) and in participants with COPD (FEV1/FVC < 0.7) compared to those with normal spirometry (controls; FEV1/FVC≥0.7, FEV1≥80% predicted). Hazard ratios (HRs) with 95% confidence intervals (CI) for dementia were adjusted for age, sex, education attainment, smoking status, systolic blood pressure, body mass index, triglycerides, comorbidities and Apolipoprotein E (APOE) genotype. RESULTS: Of 4,765 participants, 110 (2.3%) developed dementia after 3.3 years. Compared to controls, participants with PRISm, but not COPD, had an increased risk for all-type dementia (adjusted HRPRISm 2.70; 95% CI, 1.53-4.75; adjusted HRCOPD 1.03; 95% CI, 0.61-1.74). These findings were primarily driven by men and smokers. Similarly, participants with FVC% predicted values in the lowest quartile compared to those in the highest quartile were at increased risk of all-type dementia (adjusted HR 2.28; 95% CI, 1.31-3.98), as well as Alzheimer's disease (AD; adjusted HR 2.13; 95% CI, 1.13-4.02). CONCLUSION: Participants with PRISm or a low FVC% predicted lung function were at increased risk of dementia, compared to those with normal spirometry or a higher FVC% predicted, respectively. Further research is needed to elucidate whether this association is causal and how PRISm might contribute to dementia pathogenesis.

Mitochondrial Membrane Potential Influences Amyloid-β Protein Precursor Localization and Amyloid-β Secretion. - Wilkins, Heather M; Troutwine, Benjamin R; Menta, Blaise W; Manley, Sharon J; Strope, Taylor A; Lysaker, Colton R; Swerdlow, Russell H (J Alzheimers Dis, 2021)
BACKGROUND: Amyloid-β (Aβ), which derives from the amyloid-β protein precursor (AβPP), forms plaques and serves as a fluid biomarker in Alzheimer's disease (AD). How Aβ forms from AβPP is known, but questions relating to AβPP and Aβ biology remain unanswered. AD patients show mitochondrial dysfunction, and an Aβ/AβPP mitochondria relationship exists. OBJECTIVE: We considered how mitochondrial biology may impact AβPP and Aβ biology. METHODS: SH-SY5Y cells were transfected AβPP constructs. After treatment with FCCP (uncoupler), Oligomycin (ATP synthase inhibitor), or starvation Aβ levels were measured. β-secretase (BACE1) expression was measured. Mitochondrial localized full-length AβPP was also measured. All parameters listed were measured in ρ0 cells on an SH-SY5Y background. iPSC derived neurons were also used to verify key results. RESULTS: We showed that mitochondrial depolarization routes AβPP to, while hyperpolarization routes AβPP away from, the organelle. Mitochondrial AβPP and cell Aβ secretion inversely correlate, as cells with more mitochondrial AβPP secrete less Aβ, and cells with less mitochondrial AβPP secrete more Aβ. An inverse relationship between secreted/extracellular Aβ and intracellular Aβ was observed. CONCLUSION: Our findings indicate mitochondrial function alters AβPP localization and suggest enhanced mitochondrial activity promote Aβ secretion while depressed mitochondrial activity minimize Aβ secretion. Our data complement other studies that indicate a mitochondrial, AβPP, and Aβ nexus, and could help explain why cerebrospinal fluid Aβ is lower in those with AD. Our data further suggest Aβ secretion could serve as a biomarker of cell or tissue mitochondrial function.

Neurotrophic Treatment Initiated During Early Postnatal Development Prevents the Alzheimer-Like Behavior and Synaptic Dysfunction. - Wei, Wei; Liu, Yinghua; Dai, Chunling; Baazaoui, Narjes; Tung, Yunn-Chyn; Liu, Fei; Iqbal, Khalid (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by impairments in synaptic plasticity and cognitive performance. Cognitive dysfunction and loss of neuronal plasticity are known to begin decades before the clinical diagnosis of the disease. The important influence of congenital genetic mutations on the early development of AD provides a novel opportunity to initiate treatment during early development to prevent the Alzheimer-like behavior and synaptic dysfunction. OBJECTIVE: To explore strategies for early intervention to prevent Alzheimer's disease. METHODS: In the present study, we investigated the effect of treatment during early development with a ciliary neurotrophic factor (CNTF) derived peptidergic compound, P021 (Ac-DGGLAG-NH2) on cognitive function and synaptic plasticity in 3xTg-AD transgenic mouse model of AD. 3xTg-AD and genetic background-matched wild type female mice were treated from birth to postnatal day 120 with P021 in diet or as a control with vehicle diet, and cognitive function and molecular markers of neuroplasticity were evaluated. RESULTS: P021 treatment during early development prevented cognitive impairment and increased expressions of pCREB and BDNF that activated downstream various signaling cascades such as PLC/PKC, MEK/ERK and PI3K/Akt, and ameliorated synaptic protein deficit in 4-month-old 3xTg-AD mice. CONCLUSION: These findings indicate that treatment with the neurotrophic peptide mimetic such as P021 during early development can be an effective therapeutic strategy to rescue synaptic deficit and cognitive impairment in familial AD and related tauopathies.

One-Year Aerobic Exercise Reduced Carotid Arterial Stiffness and Increased Cerebral Blood Flow in Amnestic Mild Cognitive Impairment. - Tomoto, Tsubasa; Liu, Jie; Tseng, Benjamin Y; Pasha, Evan P; Cardim, Danilo; Tarumi, Takashi; Hynan, Linda S; Munro Cullum, C; Zhang, Rong (J Alzheimers Dis, 2021)
BACKGROUND: Central arterial stiffness and brain hypoperfusion are emerging risk factors of Alzheimer's disease (AD). Aerobic exercise training (AET) may improve central arterial stiffness and brain perfusion. OBJECTIVE: To investigate the effects of AET on central arterial stiffness and cerebral blood flow (CBF) in patients with amnestic mild cognitive impairment (MCI), a prodromal stage of AD. METHODS: This is a proof-of-concept, randomized controlled trial that assigned 70 amnestic MCI patients into a 12-month program of moderate-to-vigorous AET or stretching-and-toning (SAT) intervention. Carotid β-stiffness index and CBF were measured by color-coded duplex ultrasonography and applanation tonometry. Total CBF was measured as the sum of CBF from both the internal carotid and vertebral arteries, and divided by total brain tissue mass assessed with MRI to obtain normalized CBF (nCBF). Episodic memory and executive function were assessed using standard neuropsychological tests (CVLT-II and D-KEFS). Changes in cardiorespiratory fitness were measured by peak oxygen uptake (VO2peak). RESULTS: Total 48 patients (29 in SAT and 19 in AET) were completed one-year training. AET improved VO2peak, decreased carotid β-stiffness index and CBF pulsatility, and increased nCBF. Changes in VO2peak were associated positively with changes in nCBF (r = 0.388, p = 0.034) and negatively with carotid β-stiffness index (r = -0.418, p = 0.007) and CBF pulsatility (r = -0.400, p = 0.014). Decreases in carotid β-stiffness were associated with increases in cerebral perfusion (r = -0.494, p = 0.003). AET effects on cognitive performance were minimal compared with SAT. CONCLUSION: AET reduced central arterial stiffness and increased CBF which may precede its effects on neurocognitive function in patients with MCI.
Keywords: Aged; Brain; Cardiorespiratory Fitness; Carotid Arteries; Cerebrovascular Circulation; Cognitive Dysfunction; Exercise; Humans; Magnetic Resonance Imaging; Neuropsychological Tests; Vascular Stiffness

Periodontal Disease and Risk of Dementia in Medicare Patients with Hepatitis C Virus. - Malone, Joseph; Jung, Jeah; Tran, Linh; Zhao, Chen (J Alzheimers Dis, 2021)
BACKGROUND: Periodontal disease and hepatitis C virus (HCV) represent chronic infectious states that are common in elderly adults. Both conditions have independently been associated with an increased risk for dementia. Chronic infections are thought to lead to neurodegenerative changes in the central nervous system possibly by promoting a proinflammatory state. This is consistent with growing literature on the etiological role of infections in dementia. Few studies have previously evaluated the association of periodontal disease with dementia in HCV patients. OBJECTIVE: To examine whether periodontal disease increases the risk of developing Alzheimer's disease and related dementias (ADRD) among HCV patients in Medicare claims data. METHODS: We used Medicare claims data for HCV patients to assess the incidence rate of ADRD with and without exposure to periodontal disease between 2014 and 2017. Cox multivariate regression was used to estimate the association between periodontal disease and development of ADRD, controlling for age, gender, race, ZIP-level income and education, and medical comorbidities. RESULTS: Of 439,760 HCV patients, the incidence rate of ADRD was higher in patients with periodontal diseases compared to those without (10.84% versus 9.26%, p <  0.001), and those with periodontal disease developed ADRD earlier compared to those without periodontal disease (13.99 versus 21.60 months, p <  0.001). The hazard of developing ADRD was 1.35 times higher in those with periodontal disease (95% CI, 1.30 to 1.40, p <  0.001) after adjusting for all covariates, including age. CONCLUSION: Periodontal disease increased the risk of developing ADRD among HCV patients in a national Medicare claims dataset.

Physical Activity and Trajectory of Cognitive Change in Older Persons: Mayo Clinic Study of Aging. - Krell-Roesch, Janina; Syrjanen, Jeremy A; Bezold, Jelena; Trautwein, Sandra; Barisch-Fritz, Bettina; Boes, Klaus; Woll, Alexander; Forzani, Erica; Kremers, Walter K; Machulda, Mary M; Mielke, Michelle M; Knopman, David S; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Little is known about the association between physical activity (PA) and cognitive trajectories in older adults. OBJECTIVE: To examine the association between PA and change in memory, language, attention, visuospatial skills, and global cognition, and a potential impact of sex or Apolipoprotein E (APOE) ɛ4 status. METHODS: Longitudinal study derived from the population-based Mayo Clinic Study of Aging, including 2,060 cognitively unimpaired males and females aged ≥70 years. Engagement in midlife (ages 50-65) and late-life (last year) PA was assessed using a questionnaire. Neuropsychological testing was done every 15 months (mean follow-up 5.8 years). We ran linear mixed-effect models to examine whether mid- or late-life PA at three intensities (mild, moderate, vigorous) was associated with cognitive z-scores. RESULTS: Light intensity midlife PA was associated with less decline in memory function compared to the no-PA reference group (time x light PA; estimate [standard error] 0.047 [0.016], p = 0.004). Vigorous late-life PA was associated with less decline in language (0.033 [0.015], p = 0.030), attention (0.032 [0.017], p = 0.050), and global cognition (0.039 [0.016], p = 0.012). Females who were physically inactive in midlife experienced more pronounced cognitive decline than females physically active in midlife and males regardless of PA (p-values for time interaction terms with midlife PA levels and sex were all p <  0.05 for global cognition). APOE ɛ4 carriership did not moderate the association between PA and cognition. CONCLUSION: Engaging in PA, particularly of vigorous intensity in late-life, was associated with less pronounced decline in global and domain-specific cognition. This association may differ by sex.

Plasma Total-Tau and Neurofilament Light Chain as Diagnostic Biomarkers of Alzheimer's Disease Dementia and Mild Cognitive Impairment in Adults with Down Syndrome. - Petersen, Melissa E; Rafii, Michael S; Zhang, Fan; Hall, James; Julovich, David; Ances, Beau M; Schupf, Nicole; Krinsky-McHale, Sharon J; Mapstone, Mark; Silverman, Wayne; Lott, Ira; Klunk, William; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The need for diagnostic biomarkers of cognitive decline is particularly important among aging adults with Down syndrome (DS). Growing empirical support has identified the utility of plasma derived biomarkers among neurotypical adults with mild cognitive impairment (MCI) and Alzheimer's disease (AD); however, the application of such biomarkers has been limited among the DS population. OBJECTIVE: This study aimed to investigate the cross-sectional diagnostic performance of plasma neurofilament light chain (Nf-L) and total-tau, individually and in combination among a cohort of DS adults. METHODS: Plasma samples were analyzed from n = 305 (n = 225 cognitively stable (CS); n = 44 MCI-DS; n = 36 DS-AD) participants enrolled in the Alzheimer's Biomarker Consortium -Down Syndrome. RESULTS: In distinguishing DS-AD participants from CS, Nf-L alone produced an AUC of 90%, total-tau alone reached 74%, and combined reached an AUC of 86%. When age and gender were included, AUC increased to 93%. Higher values of Nf-L, total-tau, and age were all shown to be associated with increased risk for DS-AD. When distinguishing MCI-DS participants from CS, Nf-L alone produced an AUC of 65%, while total-tau alone reached 56%. A combined model with Nf-L, total-tau, age, and gender produced an AUC of 87%. Both higher values in age and total-tau were found to increase risk for MCI-DS; Nf-L levels were not associated with increased risk for MCI-DS. CONCLUSION: Advanced assay techniques make total-tau and particularly Nf-L useful biomarkers of both AD pathology and clinical status in DS and have the potential to serve as outcome measures in clinical trials for future disease-modifying drugs.

Porphyromonas gingivalis (W83) Infection Induces Alzheimer's Disease-Like Pathophysiology in Obese and Diabetic Mice. - Bahar, Bojlul; Kanagasingam, Shalini; Tambuwala, Murtaza M; Aljabali, Alaa A A; Dillon, Stephanie A; Doaei, Saeid; Welbury, Richard; Chukkapalli, Sasanka S; Singhrao, Sim K (J Alzheimers Dis, 2021)
BACKGROUND: Periodontal disease(s) and metabolic illnesses negatively impact the quality of life and, eventually mental health. OBJECTIVE: This study investigated the effect of Porphyromonas gingivalis (W83) oral infection on the development of Alzheimer's disease (AD) pathophysiology in a wild-type obese, diabetic (db/db) mouse model. METHODS: The db/db mice were either orally infected with P. gingivalis and Fusobacterium nucleatum or sham infected for 16 weeks. The presence of amyloid-β (Aβ) and neurofibrillary tangles (NFTs) were assessed using a silver impregnation technique and subsequently by immunohistochemistry for tau and neuroinflammation. The mRNA abundance of a panel of 184 genes was performed using quantitative real-time PCR, and the differentially expressed genes were analyzed by Ingenuity Pathway Analysis. RESULTS: While no Aβ plaques and NFTs were evident by silver impregnation, immunohistochemistry (glial cell markers) of the P. gingivalis-infected mice tissue sections exhibited neuroinflammation in the form of reactive microglia and astrocytes. Anti-tau immunopositivity, in addition to cells, was prominent in thickened axons of hippocampal CA neurons. The mRNA abundance of crucial genes in the insulin signaling pathway (INSR, IGF1, IRS, IDE, PIK3R, SGK1, GYS, GSK3B, AKT1) were upregulated, potentially exacerbating insulin resistance in the brain by P. gingivalis oral infection. Increased mRNA abundance of several kinases, membrane receptors, transcription factors, and pro-inflammatory mediators indicated hyperactivation of intracellular cascades with potential for tau phosphorylation and Aβ release in the same infection group. CONCLUSION: P. gingivalis W83 infection of db/db mice provides a disease co-morbidity model with the potential to reproduce AD pathophysiology with induced periodontal disease.

Possible Role of Activin in the Adiponectin Paradox-Induced Progress of Alzheimer's Disease. - Hashimoto, Makoto; Ho, Gilbert; Sugama, Shuei; Takenouchi, Takato; Waragai, Masaaki; Sugino, Hiromu; Inoue, Satoshi; Masliah, Eliezer (J Alzheimers Dis, 2021)
Accumulating evidence suggests that the adiponectin (APN) paradox might be involved in promoting aging-associated chronic diseases such as Alzheimer's disease (AD). In human brain, APN regulation of the evolvability of amyloidogenic proteins (APs), including amyloid-β (Aβ) and tau, in developmental/reproductive stages, might be paradoxically manifest as APN stimulation of AD through antagonistic pleiotropy in aging. The unique mechanisms underlying APN activity remain unclear, a better understanding of which might provide clues for AD therapy. In this paper, we discuss the possible relevance of activin, a member of transforming growth factor β (TGFβ) superfamily of peptides, to antagonistic pleiotropy effects of APN. Notably, activin, a multiple regulator of cell proliferation and differentiation, as well as an endocrine modulator in reproduction and an organizer in early development, might promote aging-associated disorders, such as inflammation and cancer. Indeed, serum activin, but not serum TGFβ increases during aging. Also, activin/TGFβ signal through type II and type I receptors, both of which are transmembrane serine/threonine kinases, and the serine/threonine phosphorylation of APs, including Aβ 42 serine 8 and αS serine 129, may confer pathological significance in neurodegenerative diseases. Moreover, activin expression is induced by APN in monocytes and hepatocytes, suggesting that activin might be situated downstream of the APN paradox. Finally, a meta-analysis of genome-wide association studies demonstrated that two SNPs relevant to the activin/TGFβ receptor signaling pathways conferred risk for major aging-associated disease. Collectively, activin might be involved in the APN paradox of AD and could be a significant therapeutic target.

Quantifying and Examining Reserve in Symptomatic Former National Football League Players. - Foley, Éimear M; Tripodis, Yorghos; Yhang, Eukyung; Koerte, Inga K; Martin, Brett M; Palmisano, Joseph; Makris, Nikos; Schultz, Vivian; Lepage, Chris; Muehlmann, Marc; Wróbel, Paweł P; Guenette, Jeffrey P; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Repetitive head impacts (RHI) from contact sports have been associated with cognitive and neuropsychiatric disorders. However, not all individuals exposed to RHI develop such disorders. This may be explained by the reserve hypothesis. It remains unclear if the reserve hypothesis accounts for the heterogenous symptom presentation in RHI-exposed individuals. Moreover, optimal measurement of reserve in this population is unclear and likely unique from non-athlete populations. OBJECTIVE: We examined the association between metrics of reserve and cognitive and neuropsychiatric functioning in 89 symptomatic former National Football League players. METHODS: Individual-level proxies (e.g., education) defined reserve. We additionally quantified reserve as remaining residual variance in 1) episodic memory and 2) executive functioning performance, after accounting for demographics and brain pathology. Associations between reserve metrics and cognitive and neuropsychiatric functioning were examined. RESULTS: Higher reading ability was associated with better attention/information processing (β=0.25; 95% CI, 0.05-0.46), episodic memory (β=0.27; 95% CI, 0.06-0.48), semantic and phonemic fluency (β=0.24; 95% CI, 0.02-0.46; β=0.38; 95% CI, 0.17-0.59), and behavioral regulation (β=-0.26; 95% CI, -0.48, -0.03) performance. There were no effects for other individual-level proxies. Residual episodic memory variance was associated with better attention/information processing (β=0.45; 95% CI, 0.25, 0.65), executive functioning (β=0.36; 95% CI, 0.15, 0.57), and semantic fluency (β=0.38; 95% CI, 0.17, 0.59) performance. Residual executive functioning variance was associated with better attention/information processing (β=0.44; 95% CI, 0.24, 0.64) and episodic memory (β=0.37; 95% CI, 0.16, 0.58) performance. CONCLUSION: Traditional reserve proxies (e.g., years of education, occupational attainment) have limitations and may be unsuitable for use in elite athlete samples. Alternative approaches of reserve quantification may prove more suitable for this population.

Relation of a Socioeconomic Index with Cognitive Function and Neuroimaging in Hypertensive Individuals. - Paradela, Regina Silva; Ferreira, Naomi Vidal; Nucci, Mariana Penteado; Cabella, Brenno; Martino, Luiza Menoni; Torres, Laura Aló; Costa, Danielle Irigoyen da; Consolim-Colombo, Fernanda Marciano; Suemoto, Claudia Kimie; Irigoyen, Maria Claudia (J Alzheimers Dis, 2021)
BACKGROUND: Socioeconomic factors are important contributors to brain health. However, data from developing countries (where social inequalities are the most prominent) are still scarce, particularly about hypertensive individuals. OBJECTIVE: To evaluate the relationship between socioeconomic index, cognitive function, and cortical brain volume, as well as determine whether white matter hyperintensities are mediators of the association of the socioeconomic index with cognitive function in hypertensive individuals. METHODS: We assessed 92 hypertensive participants (mean age = 58±8.6 years, 65.2%female). Cognitive evaluation and neuroimaging were performed and clinical and sociodemographic data were collected using questionnaires. A socioeconomic index was created using education, income, occupation (manual or non-manual work), and race. The associations of the socioeconomic index with cognitive performance and brain volume were investigated using linear regression models adjusted for age, sex, time of hypertension since diagnosis, and comorbidities. A causal mediation analysis was also conducted. RESULTS: Better socioeconomic status was associated with better visuospatial ability, executive function, and global cognition. We found associations between a better socioeconomic index and a higher parietal lobe volume. White matter hyperintensities were also not mediators in the relationship between the socioeconomic index and cognitive performance. CONCLUSION: Socioeconomic disadvantages are associated with worse cognitive performance and brain volume in individuals with hypertension.

The Retinal Vessel Density Can Reflect Cognitive Function in Patients with Alzheimer's Disease: Evidence from Optical Coherence Tomography Angiography. - Yan, Yibing; Wu, Xingqi; Wang, Xiaojing; Geng, Zhi; Wang, Lu; Xiao, Guixian; Wu, Yue; Zhou, Shanshan; Liao, Rongfeng; Wei, Ling; Tian, Yanghua; Wang, Kai (J Alzheimers Dis, 2021)
BACKGROUND: There is increasing evidence that Alzheimer's disease (AD) patients may present decreased cerebral blood perfusion before pathological brain changes. Using the retina as a window to the brain, we can study disorders of the central nervous system through the eyes. OBJECTIVE: This study aimed to investigate differences in retinal structure and vessel density (VD) between patients with mild AD and healthy controls (HCs). Furthermore, we explored the relationship between retinal VD and cognitive function. METHODS: We enrolled 37 patients with AD and 29 age-matched HCs who underwent standard ophthalmic optical coherence tomography angiography (OCTA) for evaluation of the retinal layer thickness and VD parameters. Cognitive function was evaluated using a battery of neuropsychological assessments. Finally, the correlations among retinal layer thickness, VD parameters, and cognitive function were evaluated. RESULTS: The retinal fiber layer thickness and retinal VD of patients with AD were significantly reduced compared with HCs. The retinal VD was significantly correlated with overall cognition, memory, executive, and visual-spatial perception functions. However, there was no significant between-group difference in the macular thickness. CONCLUSION: Our findings indicate a positive correlation between retinal VD and some, but not all, cognitive function domains. Most importantly, we demonstrated the role of OCTA in detecting early capillary changes, which could be a noninvasive biomarker for early AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognition; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Retinal Vessels; Tomography, Optical Coherence

The Right Temporal Variant of Frontotemporal Dementia Is Not Genetically Sporadic: A Case Series. - Ulugut Erkoyun, Hulya; van der Lee, Sven J; Nijmeijer, Bas; van Spaendonk, Rosalina; Nelissen, Anne; Scarioni, Marta; Dijkstra, Anke; Samancı, Bedia; Gürvit, Hakan; Yıldırım, Zerrin; Tepgeç, Fatih; Bilgic, Basar; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Right temporal variant frontotemporal dementia (rtvFTD) has been generally considered as a right sided variant of semantic variant primary progressive aphasia (svPPA), which is a genetically sporadic disorder. Recently, we have shown that rtvFTD has a unique clinical syndrome compared to svPPA and behavioral variant frontotemporal dementia. OBJECTIVE: We challenge the assumption that rtvFTD is a sporadic, non-familial variant of FTD by identifying potential autosomal dominant inheritance and related genes in rtvFTD. METHODS: We collected all subjects with a diagnosis of FTD or primary progressive aphasia who had undergone genetic screening (n = 284) and subsequently who had a genetic variant (n = 48) with a diagnosis of rtvFTD (n = 6) in 2 specialized memory clinics. RESULTS: Genetic variants in FTD related genes were found in 33% of genetically screened rtvFTD cases; including MAPT (n = 4), GRN (n = 1), and TARDBP (n = 1) genes, whereas only one svPPA case had a genetic variant in our combined cohorts. Additionally, 4 out of 6 rtvFTD subjects had a strong family history for dementia. CONCLUSION: Our results demonstrate that rtvFTD, unlike svPPA, is not a pure sporadic, but a heterogeneous potential genetic variant of FTD, and screening for genetic causes for FTD should be performed in patients with rtvFTD.
Keywords: Aphasia, Primary Progressive; DNA-Binding Proteins; Female; Frontotemporal Dementia; Functional Laterality; Genetic Testing; Genetic Variation; Gyrus Cinguli; Humans; Male; Middle Aged; Progranulins; tau Proteins

Serum Uric Acid May Aggravate Alzheimer's Disease Risk by Affecting Amyloidosis in Cognitively Intact Older Adults: The CABLE Study. - Li, Lin-Lin; Ma, Ya-Hui; Bi, Yan-Lin; Sun, Fu-Rong; Hu, Hao; Hou, Xiao-He; Xu, Wei; Shen, Xue-Ning; Dong, Qiang; Tan, Lan; Yang, Jiu-Long; Yu, Jin-Tai (J Alzheimers Dis, 2021)
BACKGROUND: Serum uric acid (SUA) affects the reaction of oxidative stress and free radicals in the neurodegenerative processes. However, whether SUA impacts Alzheimer's disease (AD) pathology remains unclear. OBJECTIVE: We aimed to explore whether high SUA levels can aggravate the neurobiological changes of AD in preclinical AD. METHODS: We analyzed cognitively intact participants (n = 839, age 62.16 years) who received SUA and cerebrospinal fluid (CSF) biomarkers (amyloid-β [Aβ], total tau [t-Tau], and phosphorylated tau [p-Tau]) measurements from the Chinese Alzheimer's Biomarker and LifestylE (CABLE) database using multivariable-adjusted linear models. RESULTS: Levels of SUA in the preclinical AD elevated compared with the healthy controls (p = 0.007) and subjects with amyloid pathology had higher concentration of SUA than controls (p = 0.017). Roughly, equivalent levels of SUA displayed among cognitively intact individuals with or without tau pathology and neurodegeneration. CSF Aβ1 - 42 (p = 0.019) and Aβ1 - 42/Aβ1 - 40 (p = 0.027) were decreased and CSF p-Tau/Aβ1 - 42 (p = 0.009) and t-Tau/Aβ1 - 42 (p = 0.043) were increased with the highest (>  75th percentile) SUA when compared to lowest SUA, implying a high burden of cerebral amyloidosis in individuals with high SUA. Sensitivity analyses using the usual threshold to define hyperuricemia and precluding drug effects yielded robust associations. Nevertheless, the quadratic model did not show any U-shaped relationships between them. CONCLUSION: SUA may aggravate brain amyloid deposition in preclinical AD, which corroborated the detrimental role of SUA.

Site-Specific Cerebrospinal Fluid Tau Hyperphosphorylation in Response to Alzheimer's Disease Brain Pathology: Not All Tau Phospho-Sites are Hyperphosphorylated. - Barthélemy, Nicolas R; Toth, Balazs; Manser, Paul T; Sanabria-Bohórquez, Sandra; Teng, Edmond; Keeley, Michael; Bateman, Randall J; Weimer, Robby M; Wildsmith, Kristin R (J Alzheimers Dis, 2021)
BACKGROUND: Understanding patterns of association between CSF phosphorylated tau (p-tau) species and clinical disease severity will aid Alzheimer's disease (AD) diagnosis and treatment. OBJECTIVE: To evaluate changes in tau phosphorylation ratios to brain imaging (amyloid PET, [18F]GTP1 PET, and MRI) and cognition across clinical stages of AD in two different cohorts. METHODS: A mass spectrometry (MS)-based method was used to evaluate the relationship between p-tau/tau phosphorylation ratios on 11 sites in CSF and AD pathology measured by tau PET ([18F]GTP1) and amyloid PET ([18F]florbetapir or [18F]florbetaben). Cohort A included cognitively normal-amyloid negative (n = 6) and positive (n = 5) individuals, and amyloid positive prodromal (n = 13), mild (n = 12), and moderate AD patients (n = 10); and Cohort B included amyloid positive prodromal (n = 24) and mild (n = 40) AD patients. RESULTS: In this cross-sectional analysis, we identified clusters of phosphosites with different profiles of phosphorylation ratios across stages of disease. Eight of 11 investigated sites were hyperphosphorylated and associated with the SUVR measures from [18F]GTP1 and amyloid PET. Novel sites 111, 153, and 208 may be relevant biomarkers for AD diagnosis to complement tau hyperphosphorylation measures on previously established sites 181, 205, 217, and 231. Hypophosphorylation was detected on residues 175, 199, and 202, and was inversely associated with [18F]GTP1 and amyloid PET. CONCLUSION: Hyperphosphorylated and hypophosphorylated forms of tau are associated with AD pathologies, and due to their different site-specific profiles, they may be used in combination to assist with staging of disease.

A Super-Resolved View of the Alzheimer's Disease-Related Amyloidogenic Pathway in Hippocampal Neurons. - Yu, Yang; Gao, Yang; Winblad, Bengt; Tjernberg, Lars O; Schedin-Weiss, Sophia (J Alzheimers Dis, 2021)
BACKGROUND: Processing of the amyloid-β protein precursor (AβPP) is neurophysiologically important due to the resulting fragments that regulate synapse biology, as well as potentially harmful due to generation of the 42 amino acid long amyloid β-peptide (Aβ42), which is a key player in Alzheimer's disease. OBJECTIVE: Our aim was to clarify the subcellular locations of the fragments involved in the amyloidogenic pathway in primary neurons with a focus on Aβ42 and its immediate substrate AβPP C-terminal fragment (APP-CTF). To overcome the difficulties of resolving these compartments due to their small size, we used super-resolution microscopy. METHODS: Mouse primary hippocampal neurons were immunolabelled and imaged by stimulated emission depletion (STED) microscopy, including three-dimensional three-channel imaging, and quantitative image analyses. RESULTS: The first (β-secretase) and second (γ-secretase) cleavages of AβPP were localized to functionally and distally distinct compartments. The β-secretase cleavage was observed in early endosomes in soma, where we were able to show that the liberated N- and C-terminal fragments were sorted into distinct vesicles budding from the early endosomes. Lack of colocalization of Aβ42 and APP-CTF in soma suggested that γ-secretase cleavage occurs in neurites. Indeed, APP-CTF was, in line with Aβ42 in our previous study, enriched in the presynapse but absent from the postsynapse. In contrast, full-length AβPP was not detected in either the pre- or the postsynaptic side of the synapse. Furthermore, we observed that endogenously produced and endocytosed Aβ42 were localized in different compartments. CONCLUSION: These findings provide critical super-resolved insight into amyloidogenic AβPP processing in primary neurons.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Amyloidogenic Proteins; Animals; Cells, Cultured; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Microscopy; Neurons; Peptide Fragments; Protein Transport

Taking the A Train? Limited Consistency of Aβ42 and the Aβ42/40 Ratio in the AT(N) Classification. - Gouilly, Dominique; Tisserand, Camille; Nogueira, Leonor; Saint-Lary, Laura; Rousseau, Vanessa; Benaiteau, Marie; Rafiq, Marie; Carlier, Jasmine; Milongo-Rigal, Emilie; Pagès, Jean-Christophe; Pariente, Jérémie (J Alzheimers Dis, 2021)
The consistency of cerebrospinal fluid amyloid-β (Aβ)42/40 ratio and Aβ 42 has not been assessed in the AT(N) classification system. We analyzed the classification changes of the dichotomized amyloid status (A+/A-) in 363 patients tested for Alzheimer's disease biomarkers after Aβ 42 was superseded by the Aβ 42/40 ratio. The consistency of Aβ 42 and the Aβ 42/40 ratio was very low. Notably, the proportions of "false" A+T-patients were considerable (74-91%) and corresponded mostly to patients not clinically diagnosed with Alzheimer's disease. Our results suggest that the interchangeability of Aβ 42/40 ratio and Aβ 42 is limited for classifying patients in clinical setting using the AT(N) scheme.

TAR DNA-Binding Protein 43 Is Associated with Rate of Memory and Functional and Global Cognitive Decline in the Decade Prior to Death. - Buciuc, Marina; Tosakulwong, Nirubol; Machulda, Mary M; Whitwell, Jennifer L; Weigand, Stephen D; Murray, Melissa E; Ross Reichard, R; Parisi, Joseph E; Dickson, Dennis W; Boeve, Bradley F; Knopman, David S; Petersen, Ronald C; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Transactive response DNA-binding protein of 43 kDa (TDP-43) is associated with memory impairment and overall cognitive decline. It is unclear how TDP-43 contributes to the rate of clinical decline. OBJECTIVE: To determine whether cross-sectional and longitudinal cognitive and functional decline are associated with anatomical distribution of TDP-43 in the brain. METHODS: Longitudinal clinical-neuropathologic autopsy cohort study of 385 initially cognitively normal/mildly impaired older adults prospectively followed until death. We investigated how TDP-43, amyloid-β (Aβ), tau neurofibrillary tangles (NFT), Lewy body disease (LBD), age, sex, and genetics are associated with clinical scores and rates of their longitudinal decline. RESULTS: Of 385 participants, 260 (68%) had no TDP-43, 32 (8%) TDP-43 limited to amygdala, and 93 (24%) TDP-43 in the hippocampus and beyond. Higher TDP-43 and Braak NFT stages independently were associated with faster decline in global cognition, functional performance measured by Clinical Dementia Rating scale, and naming and episodic memory, whereas older age was associated with slower rate of cognitive, psychiatric, and functional decline. Cross-sectionally the following associations were found: higher TDP-43 and Braak NFT - worse performance; higher Aβ burden - worse global cognition, more behavioral changes, the latter also with higher LBD; older age - worse naming, lower frequency of behavioral changes; female sex - more impaired naming and better preserved episodic memory. There were no genetic associations. CONCLUSION: The association of TDP-43 distribution with decline in cognitive and functional performance suggests that TDP-43 is playing a role in the clinical progression to dementia. Further characterization of clinical features associated with TDP-43 can facilitate establishment of antemortem diagnosis.

Time Trends of Cerebrospinal Fluid Biomarkers of Neurodegeneration in Idiopathic Normal Pressure Hydrocephalus. - Lukkarinen, Heikki; Tesseur, Ina; Pemberton, Darrel; van der Ark, Peter; Timmers, Maarten; Slemmon, Randy; Janssens, Luc; Streffer, Johannes; Van Nueten, Luc; Bottelbergs, Astrid; Rauramaa, Tuomas; Koivisto, Anne M; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Longitudinal changes in cerebrospinal fluid (CSF) biomarkers are seldom studied. Furthermore, data on biomarker gradient between lumbar (L-) and ventricular (V-) compartments seems to be discordant. OBJECTIVE: To examine alteration of CSF biomarkers reflecting Alzheimer's disease (AD)-related amyloid-β (Aβ) aggregation, tau pathology, neurodegeneration, and early synaptic degeneration by CSF shunt surgery in idiopathic normal pressure hydrocephalus (iNPH) in relation to AD-related changes in brain biopsy. In addition, biomarker levels in L- and V-CSF were compared. METHODS: L-CSF was collected prior to shunt placement and, together with V-CSF, 3-73 months after surgery. Thereafter, additional CSF sampling took place at 3, 6, and 18 months after the baseline sample from 26 iNPH patients with confirmed Aβ plaques in frontal cortical brain biopsy and 13 iNPH patients without Aβ pathology. CSF Amyloid-β42 (Aβ42), total tau (T-tau), phosphorylated tau (P-tau181), neurofilament light (NFL), and neurogranin (NRGN) were analyzed with customized ELISAs. RESULTS: All biomarkers but Aβ42 increased notably by 140-810% in L-CSF after CSF diversion and then stabilized. Aβ42 instead showed divergent longitudinal decrease between Aβ-positive and -negative patients in L-CSF, and thereafter increase in Aβ-negative iNPH patients in both L- and V-CSF. All five biomarkers correlated highly between V-CSF and L-CSF (Aβ42 R = 0.87, T-tau R = 0.83, P-tau R = 0.92, NFL R = 0.94, NRGN R = 0.9; all p <  0.0001) but were systematically lower in V-CSF (Aβ42 14 %, T-tau 22%, P-tau 20%, NFL 32%, NRGN 19%). With APOE genotype-grouping, only Aβ42 showed higher concentration in non-carriers of allele ɛ4. CONCLUSION: Longitudinal follow up shows that after an initial post-surgery increase, T-tau, P-tau, and NRGN are stable in iNPH patients regardless of brain biopsy Aβ pathology, while NFL normalized toward its pre-shunt levels. Aβ42 as biomarker seems to be the least affected by the surgical procedure or shunt and may be the best predictor of AD risk in iNPH patients. All biomarker concentrations were lower in V- than L-CSF yet showing strong correlations.

Urban Air Pollution Nanoparticles from Los Angeles: Recently Decreased Neurotoxicity. - Zhang, Hongqiao; D'Agostino, Carla; Forman, Henry Jay; Cacciottolo, Mafalda; Thorwald, Max; Mack, William J; Liu, Qinghai; Shkirkova, Kristina; Lamorie-Foote, Krista; Sioutas, Constantinos; Pirhadi, Milad; Mack, Wendy Jean; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Air pollution is widely associated with accelerated cognitive decline at later ages and risk of Alzheimer's disease (AD). Correspondingly, rodent models demonstrate the neurotoxicity of ambient air pollution and its components. Our studies with nano-sized particulate matter (nPM) from urban Los Angeles collected since 2009 have shown pro-amyloidogenic and pro-inflammatory responses. However, recent batches of nPM have diminished induction of the glutamate receptor GluA1 subunit, Iba1, TNFα, Aβ42 peptide, and white matter damage. The same methods, materials, and mouse genotypes were used throughout. OBJECTIVE: Expand the nPM batch comparisons and evaluate archived brain samples to identify the earliest change in nPM potency. METHODS: Batches of nPM were analyzed by in vitro cell assays for NF-κB and Nrf2 induction for comparison with in vivo responses of mouse brain regions from mice exposed to these batches, analyzed by PCR and western blot. RESULTS: Five older nPM batches (2009-2017) and four recent nPM batches (2018, 2019) for NF-κB and Nrf2 induction showed declines in nPM potency after 2017 that paralleled declines of in vivo activity from independent exposures in different years. CONCLUSION: Transcription-based in vitro assays of nPM corresponded to the loss of in vivo potency for inflammatory and oxidative responses. These recent decreases of nPM neurotoxicity give a rationale for evaluating possible benefits to the risk of dementia and stroke in Los Angeles populations.

An Active Lifestyle Is Associated with Better Cognitive Function Over Time in APOE ɛ4 Non-Carriers. - Fernández-Matarrubia, Marta; Goni, Leticia; Rognoni, Teresa; Razquin, Cristina; Fernández-Lázaro, César Ignacio; Bes-Rastrollo, Maira; Martínez-González, Miguel Ángel; Toledo, Estefanía (J Alzheimers Dis, 2020)
BACKGROUND: Available evidence on the association of physical activity (PA) or sedentary behavior with cognitive decline is inconclusive. OBJECTIVE: To assess the association between an active lifestyle score and leisure-time physical activity (LTPA) and changes in cognitive function in the Seguimiento Universidad de Navarra (SUN) prospective cohort. METHODS: Cognitive function was evaluated in a subsample of 806 participants of the SUN cohort study using the validated Telephone Interview for Cognitive Status-modified (STICS-m) questionnaire at baseline and after 6 years. LTPA was evaluated with a previously validated 17-item self-administered questionnaire and with information on sedentary lifestyles. We also calculated a multidimensional 8-item PA score. Multivariable linear regression analysis evaluated the association between PA and changes in cognitive function and its interaction by APOE genotype. RESULTS: Mean age of participants was 66 (SD 5.3) years and 69.7% were male. When stratifying by APOE variants, no significant associations between the active lifestyle score or LTPA and changes in cognitive performance over time were found among APOE ɛ4 carriers. However, we observed that a higher adherence to an active lifestyle (high versus low PA score β= 0.76 95% CI 0.15,1.36; p trend = 0.011) and a high LTPA (Q4 versus Q1 β= 0.63; 95% CI -0.01,1.26; p trend = 0.030) were associated with more favorable changes in cognitive function over time among APOE ɛ4 non-carriers with statistically significant interactions in both cases (p for interaction = 0.042 for PA score, and p = 0.039 for LTPA). CONCLUSION: The results of the present study suggest that an active lifestyle is associated with a better status of cognitive function over time only among APOE ɛ4 non-carriers.

Adiponectin Paradox as a Therapeutic Target in Alzheimer's Disease. - Waragai, Masaaki; Ho, Gilbert; Takamatsu, Yoshiki; Wada, Ryoko; Sugama, Shuei; Takenouchi, Takato; Masliah, Eliezer; Hashimoto, Makoto (J Alzheimers Dis, 2020)
Despite the apparent neurotoxicity of amyloid-β (Aβ), recent clinical trials of Aβ immunotherapy have not shown any clinical benefit in Alzheimer's disease (AD). Given this, clarification of the next generation therapeutic strategy in AD is warranted. Hypothetically, adiponectin might be involved in promoting amyloidogenic evolvability in reproduction, which may result in the adiponectin paradox through antagonistic pleiotropy mechanism in aging, leading to AD. Accordingly, preventing the adiponectin paradox by suppressing adiponectin signaling might prove therapeutic in AD.

Age of Migration and Cognitive Function Among Older Latinos in the United States. - Garcia, Marc A; Ortiz, Kasim; Arévalo, Sandra P; Diminich, Erica D; Briceño, Emily; Vega, Irving E; Tarraf, Wassim (J Alzheimers Dis, 2020)
BACKGROUND: Age of migration has been shown to have a robust association with Latino immigrant health outcomes; however, the relationship between timing of migration and cognition is less understood. OBJECTIVE: To examine associations between race/ethnicity, nativity, age of migration, and cognitive aging among US-born (USB) non-Latino Whites (NLW) and USB and foreign-born Latinos 50 years and older. METHODS: We used longitudinal biennial data from the Health and Retirement Study (HRS; 2006-2014) to fit generalized linear and linear latent growth curve models for: 1) global cognition (Modified Telephone Interview for Cognitive Status; TICS-M); 2) memory and attention subdomains of TICS-M; and 3) cognitive dysfunction. We also tested for sex modifications. RESULTS: In age and sex adjusted models, all Latino subgroups, independent of nativity and age of migration, had lower global and domain-specific cognitive scores and higher propensity of cognitive impairment classification compared to USB-NLWs. Differences between USB Latinos, but not other Latino subgroups, and USB-NLWs remained after full covariate adjustment. Latinas, independent of nativity or age of migration, had poorer cognitive scores relative to NLW females. Differences between all Latinos and USB-NLWs were principally expressed at baseline. Racial/ethnic, nativity, and age of migration grouping was not associated with slope (nor explained variance) of cognitive decline. CONCLUSION: Older US-born Latinos, regardless of sex exhibit poorer cognitive function than older USB-NLWs and foreign-born Latinos. Social determinants that differentially affect cognitive function, particularly those that compensate for education and sex differences among US-born Latinos and foreign-born Latinos, require further exploration.

Age-Specific Retinal and Cerebral Immunodetection of Amyloid-β Plaques and Oligomers in a Rodent Model of Alzheimer's Disease. - Habiba, Umma; Merlin, Sam; Lim, Jeremiah K H; Wong, Vickie H Y; Nguyen, Christine T O; Morley, John W; Bui, Bang V; Tayebi, Mourad (J Alzheimers Dis, 2020)
BACKGROUND: Amyloid-β soluble oligomers (Aβo) are believed to be the cause of the pathophysiology underlying Alzheimer's disease (AD) and are normally detected some two decades before clinical onset of the disease. Retinal pathology associated with AD pathogenesis has previously been reported, including ganglion cell loss, accumulation of Aβ deposits in the retina, and reduction of nerve fiber layer thickness as well as abnormalities of the microvasculature. OBJECTIVE: This study's aim is to better understand the relationship between brain and retinal Aβo deposition and in particular to quantify levels of the toxic Aβo as a function of age in the retina of a rodent model of AD. METHODS: Retinas and brain tissue from 5×FAD mice were stained with Congo red, Thioflavin-T (Th-T), and Aβ plaque-specific and Aβo-specific antibodies. RESULTS: We show that retinas displayed an age-dependent increase of Th-T-specific amyloid fibrils. Staining with anti-Aβ antibody confirmed the presence of the Aβ plaques in all 5×FAD retinas tested. In contrast, staining with anti-Aβo antibody showed an age-dependent decrease of retinal Aβo. Of note, Aβo was observed mainly in the retinal nuclear layers. Finally, we confirmed the localization of Aβo to neurons, typically accumulating in late endosomes, indicating possible impairment of the endocytic pathway. CONCLUSION: Our results demonstrate the presence of intraneuronal Aβo in the retina and its accumulation inversely correlated with retinal Aβ plaque deposition, indicating an age-related conversion in this animal model. These results support the development of an early AD diagnostic test targeting Aβo in the eye.

Aggregates of RNA Binding Proteins and ER Chaperones Linked to Exosomes in Granulovacuolar Degeneration of the Alzheimer's Disease Brain. - Yamoah, Alfred; Tripathi, Priyanka; Sechi, Antonio; Köhler, Christoph; Guo, Haihong; Chandrasekar, Akila; Nolte, Kay Wilhelm; Wruck, Christoph Jan; Katona, Istvan; Anink, Jasper; Troost, Dirk; Aronica, Eleonora; et al. (J Alzheimers Dis, 2020)
Granulovacuolar degeneration (GVD) occurs in Alzheimer's disease (AD) brain due to compromised autophagy. Endoplasmic reticulum (ER) function and RNA binding protein (RBP) homeostasis regulate autophagy. We observed that the ER chaperones GRP78/BiP, Sigma receptor 1 (SigR1), and VAPB were elevated in many AD patients' subicular neurons. However, those neurons which were affected by GVD showed lower chaperone levels, and there was only minor co-localization of chaperones with GVD bodies (GVBs), suggesting that neurons lacking sufficient chaperone-mediated proteostasis enter the GVD pathway. Consistent with this notion, granular, incipient pTau aggregates in human AD and pR5 tau transgenic mouse neurons were regularly co-localized with increased chaperone immunoreactivity, whereas neurons with mature neurofibrillary tangles lacked both the chaperone buildup and significant GVD. On the other hand, APP/PS1 (APPswe/PSEN1dE9) transgenic mouse hippocampal neurons that are devoid of pTau accumulation displayed only few GVBs-like vesicles, which were still accompanied by prominent chaperone buildup. Identifying a potential trigger for GVD, we found cytoplasmic accumulations of RBPs including Matrin 3 and FUS as well as stress granules in GVBs of AD patient and pR5 mouse neurons. Interestingly, we observed that GVBs containing aggregated pTau and pTDP-43 were consistently co-localized with the exosomal marker Flotillin 1 in both AD and pR5 mice. In contrast, intraneuronal 82E1-immunoreactive amyloid-β in human AD and APP/PS1 mice only rarely co-localized with Flotillin 1-positive exosomal vesicles. We conclude that altered chaperone-mediated ER protein homeostasis and impaired autophagy manifesting in GVD are linked to both pTau and RBP accumulation and that some GVBs might be targeted to exocytosis.

Is Alzheimer's Disease a Liver Disease of the Brain? - Bassendine, Margaret F; Taylor-Robinson, Simon D; Fertleman, Michael; Khan, Michael; Neely, Dermot (J Alzheimers Dis, 2020)
Clinical specialization is not only a force for progress, but it has also led to the fragmentation of medical knowledge. The focus of research in the field of Alzheimer's disease (AD) is neurobiology, while hepatologists focus on liver diseases and lipid specialists on atherosclerosis. This article on AD focuses on the role of the liver and lipid homeostasis in the development of AD. Amyloid-β (Aβ) deposits accumulate as plaques in the brain of an AD patient long before cognitive decline is evident. Aβ generation is a normal physiological process; the steady-state level of Aβ in the brain is determined by balance between Aβ production and its clearance. We present evidence suggesting that the liver is the origin of brain Aβ deposits and that it is involved in peripheral clearance of circulating Aβ in the blood. Hence the liver could be targeted to decrease Aβ production or increase peripheral clearance.

Analysis of Taste Sensitivities in App Knock-In Mouse Model of Alzheimer's Disease. - Narukawa, Masataka; Takahashi, Suzuka; Saito, Takashi; Saido, Takaomi C; Misaka, Takumi (J Alzheimers Dis, 2020)
BACKGROUND: Some studies have reported a decline in taste sensitivities in patients with Alzheimer's disease. However, the detail remains unknown. OBJECTIVE: We investigated the effect of cognitive impairment on taste sensitivity using an App knock-in mouse model of Alzheimer's disease. METHODS: Behavioral assays, a brief access test, and a 48 h two-bottle preference test, to assess taste sensitivities were started from 12 months of age in mice that were confirmed to have impaired cognition. RESULTS: In the assays, there was no significant difference in taste sensitivities between wild type and App knock-in mice. Additionally, no apparent difference was observed in the expression of taste markers in their taste bud cells. CONCLUSION: We concluded that cognitive impairment might not greatly affect taste sensitivity.

Animal Models of Alzheimer's Disease Should Be Controlled for Roseolovirus. - Denner, Joachim; Tanzi, Rudolph; Jacobson, Steve (J Alzheimers Dis, 2020)
Animal models to study Alzheimer's disease (AD) pathogenesis are under development. Since herpesviruses have been postulated to be capable of triggering the pathogenic process, AD animal models (mouse, pig, and non-human primates) should be controlled for the presence of these viruses. Only virus-free models allow studying the genetic factors and the effect of adding viruses. Roseoloviruses such as human herpesvirus 6 and the related viruses in the animals are the main topic of this commentary.

Association of Peripheral Insulin Resistance and Other Markers of Type 2 Diabetes Mellitus with Brain Amyloid Deposition in Healthy Individuals at Risk of Dementia. - Pekkala, Timo; Hall, Anette; Mangialasche, Francesca; Kemppainen, Nina; Mecocci, Patrizia; Ngandu, Tiia; Rinne, Juha O; Soininen, Hilkka; Tuomilehto, Jaakko; Kivipelto, Miia; Solomon, Alina (J Alzheimers Dis, 2020)
We explored the association of type 2 diabetes related blood markers with brain amyloid accumulation on PiB-PET scans in 41 participants from the FINGER PET sub-study. We built logistic regression models for brain amyloid status with12 plasma markers of glucose and lipid metabolism, controlled for diabetes and APOEɛ4 carrier status. Lower levels of insulin, insulin resistance index (HOMA-IR), C-peptide, and plasminogen activator (PAI-1) were associated with amyloid positive status, although the results were not significant after adjusting for multiple testing. None of the models found evidence for associations between amyloid status and fasting glucose or HbA1c.

Awareness of the COVID-19 Outbreak and Resultant Depressive Tendencies in Patients with Severe Alzheimer's Disease. - Tsugawa, Akito; Sakurai, Shu; Inagawa, Yuta; Hirose, Daisuke; Kaneko, Yoshitsugu; Ogawa, Yusuke; Serisawa, Shuntaro; Takenoshita, Naoto; Sakurai, Hirofumi; Kanetaka, Hidekazu; Hirao, Kentaro; Shimizu, Soichiro (J Alzheimers Dis, 2020)
The ongoing coronavirus disease 2019 (COVID-19) pandemic has substantially affected patients with dementia and their caregivers. However, we found not all Alzheimer's disease (AD) patients were afraid of COVID-19 infection. Therefore, we investigated the association between rate of awareness of COVID-19 and depressive tendency in AD. 126 consecutive outpatients with AD were enrolled in this study from May 25, on the day when the declaration of emergency was lifted in Japan, through June 30, 2020. In addition to routine psychological tests, the participants were asked the following two questions: "Do you know COVID-19?" and "Why are you wearing a face mask?". Moderate to severe AD patients were found to have a low COVID-19 recognition rate and did not fully understand why they were wearing face masks. In addition, because they did not understand the seriousness of the COVID-19 outbreak, their Geriatric Depression Scale scores were also substantially lower. These results may appear to simply indicate that people with severe dementia are unaware of current events. However, these results provide insights into how to care for patients with dementia and how to allocate the time and support of our limited staff during the COVID-19 outbreak.
Keywords: Aged; Alzheimer Disease; Awareness; Betacoronavirus; Caregivers; Communicable Disease Control; Coronavirus Infections; COVID-19; Female; Humans; Japan; Male; Mental Competency; Pandemics; Patient Care; Pneumonia, Viral; Psychosocial Support Systems; SARS-CoV-2; Severity of Illness Index

Costs and Resource Use Associated with Community-Dwelling Patients with Alzheimer's Disease in Japan: Baseline Results from the Prospective Observational GERAS-J Study. - Nakanishi, Miharu; Igarashi, Ataru; Ueda, Kaname; Brnabic, Alan J M; Treuer, Tamas; Sato, Masayo; Kahle-Wrobleski, Kristin; Meguro, Kenichi; Yamada, Masahito; Mimura, Masaru; Arai, Heii (J Alzheimers Dis, 2020)
BACKGROUND: As the Japanese population ages, caring for people with Alzheimer's disease (AD) dementia is becoming a major socioeconomic issue. OBJECTIVE: To determine the contribution of patient and caregiver costs to total societal costs associated with AD dementia. METHODS: Baseline data was used from the longitudinal, observational GERAS-J study. Using the Mini-Mental State Examination (MMSE) score, patients routinely visiting memory clinics were stratified into three groups based on AD severity. Health care resource utilizationwas recorded using the Resource Utilization in Dementia questionnaire. Total monthly societal costs were estimated using Japan-specific unit costs of services and products (patient direct health care use, patient social care use, and informal caregiving time). Uncertainty around mean costs was estimated using bootstrapping methods. RESULTS: Overall, 553 community-dwelling patients withADdementia (28.3% mild[MMSE21-26], 37.8% moderate[MMSE 15-20], and 34.0% moderately severe/severe [MMSE < 14]) and their caregivers were enrolled. Patient characteristics were: mean age 80.3 years, 72.7% female, and 13.6% living alone. Caregiver characteristics were: mean age 62.1 years, 70.7% female, 78.8% living with patient, 49.0% child of patient, and 39.2% sole caregiver. Total monthly societal costs of AD dementia (Japanese yen) were: 158,454 (mild), 211,301 (moderate), and 294,224 (moderately severe/severe). Informal caregiving costs comprised over 50% of total costs. CONCLUSION: Baseline results of GERAS-J showed that total monthly societal costs associated with AD dementia increased with AD severity. Caregiver-related costs were the largest cost component. Interventions are needed to decrease informal costs and decrease caregiver burden.

COVID-19: Review of a 21st Century Pandemic from Etiology to Neuro-psychiatric Implications. - Yamamoto, Vicky; Bolanos, Joe F; Fiallos, John; Strand, Susanne E; Morris, Kevin; Shahrokhinia, Sanam; Cushing, Tim R; Hopp, Lawrence; Tiwari, Ambooj; Hariri, Robert; Sokolov, Rick; Wheeler, Christopher; et al. (J Alzheimers Dis, 2020)
COVID-19 is a severe infectious disease that has claimed >150,000 lives and infected millions in the United States thus far, especially the elderly population. Emerging evidence has shown the virus to cause hemorrhagic and immunologic responses, which impact all organs, including lungs, kidneys, and the brain, as well as extremities. SARS-CoV-2 also affects patients', families', and society's mental health at large. There is growing evidence of re-infection in some patients. The goal of this paper is to provide a comprehensive review of SARS-CoV-2-induced disease, its mechanism of infection, diagnostics, therapeutics, and treatment strategies, while also focusing on less attended aspects by previous studies, including nutritional support, psychological, and rehabilitation of the pandemic and its management. We performed a systematic review of >1,000 articles and included 425 references from online databases, including, PubMed, Google Scholar, and California Baptist University's library. COVID-19 patients go through acute respiratory distress syndrome, cytokine storm, acute hypercoagulable state, and autonomic dysfunction, which must be managed by a multidisciplinary team including nursing, nutrition, and rehabilitation. The elderly population and those who are suffering from Alzheimer's disease and dementia related illnesses seem to be at the higher risk. There are 28 vaccines under development, and new treatment strategies/protocols are being investigated. The future management for COVID-19 should include B-cell and T-cell immunotherapy in combination with emerging prophylaxis. The mental health and illness aspect of COVID-19 are among the most important side effects of this pandemic which requires a national plan for prevention, diagnosis and treatment.
Keywords: Coronavirus Infections; COVID-19; Humans; Immunotherapy; Mental Health; Nutritional Support; Pandemics; Pneumonia, Viral

Day-to-Day Home Blood Pressure Variability is Associated with Cerebral Small Vessel Disease Burden in a Memory Clinic Population. - de Heus, Rianne A A; Reumers, Stacha F I; van der Have, Alba; Tumelaire, Maxime; Tully, Phillip J; Claassen, Jurgen A H R (J Alzheimers Dis, 2020)
BACKGROUND: High visit-to-visit blood pressure variability (BPV) has been associated with cognitive decline and cerebral small vessel disease (cSVD), in particular cerebrovascular lesions. Whether day-to-day BPV also relates to cSVD has not been investigated. OBJECTIVE: To investigate the cross-sectional association between day-to-day BPV and total cSVD MRI burden in older memory clinic patients. METHODS: We included outpatients referred to our memory clinic, who underwent cerebral MRI as part of their diagnostic assessment. We determined the validated total cSVD score (ranging from 0-4) by combining four markers of cSVD that were visually rated. Home blood pressure (BP) measurements were performed for one week, twice a day, according to international guidelines. BPV was defined as the within-subject coefficient of variation (CV; standard deviation/mean BP*100). We used multivariable ordinal logistic regression analyses adjusted for age, sex, smoking, diabetes, antihypertensive medication, history of cardiovascular disease, and mean BP. RESULTS: For 82 patients (aged 71.2±7.9 years), mean home BP was 140/79±15/9 mmHg. Dementia and mild cognitive impairment were diagnosed in 46% and 34%, respectively. 78% had one or more markers of cSVD. Systolic CV was associated with cSVD burden (adjusted odds ratio per point increase in CV = 1.29, 95% confidence interval = 1.04-1.60, p = 0.022). There were no differences in diastolic CV and mean BP between the cSVD groups. When we differentiated between morning and evening BP, only evening BPV remained significantly associated with total cSVD burden. CONCLUSION: Day-to-day systolic BPV is associated with cSVD burden in memory clinic patients. Future research should indicate whether lowering BPV should be included in BP management in older people with memory complaints.

Dementia Care in the Time of COVID-19 Pandemic. - Tousi, Babak (J Alzheimers Dis, 2020)
Patients with dementia are particularly vulnerable during the COVID-19 pandemic. The initial response to COVID-19 promoted behavioral changes in both society and healthcare, while a long-term solution is sought by prioritizing societal values. In addition, there has been disruption to clinical care and clinical research. This pandemic might have significantly changed the care for our patients with dementia toward increased acceptance of telemedicine by the patients and providers, and its utilization in both clinical care and research.
Keywords: Betacoronavirus; Coronavirus Infections; Dementia; Health Services Accessibility; Humans; Pandemics; Pneumonia, Viral; Telemedicine

Dementia Care in Times of COVID-19: Experience at Fundació ACE in Barcelona, Spain. - Benaque, Alba; Gurruchaga, Miren Jone; Abdelnour, Carla; Hernandez, Isabel; Cañabate, Pilar; Alegret, Montserrat; Rodríguez, Isabel; Rosende-Roca, Maitee; Tartari, Juan Pablo; Esteban, Ester; López, Rogelio; Gil, Silvia; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Fundació ACE is a non-profit organization providing care based on a holistic model to persons with cognitive disorders and their families for 25 years in Barcelona, Spain. Delivering care to this vulnerable population amidst the COVID-19 pandemic has represented a major challenge to our institution. OBJECTIVE: To share our experience in adapting our model of care to the new situation to ensure continuity of care. METHODS: We detail the sequence of events and the actions taken within Fundació ACE to swiftly adapt our face-to-face model of care to one based on telemedicine consultations. We characterize individuals under follow-up by the Memory Unit from 2017 to 2019 and compare the number of weekly visits in 2020 performed before and after the lockdown was imposed. RESULTS: The total number of individuals being actively followed by Fundació ACE Memory Unit grew from 6,928 in 2017 to 8,147 in 2019. Among those newly diagnosed in 2019, most patients had mild cognitive impairment or mild dementia (42% and 25%, respectively). Weekly visits dropped by 60% following the suspension of face-to-face activity. However, by April 24 we were able to perform 78% of the visits we averaged in the weeks before confinement began. DISCUSSION: We have shown that Fundació ACE model of care has been able to successfully adapt to a health and social critical situation as COVID-19 pandemic. Overall, we were able to guarantee the continuity of care while preserving the safety of patients, families, and professionals. We also seized the opportunity to improve our model of care.
Keywords: Aged; Aged, 80 and over; Betacoronavirus; Coronavirus Infections; COVID-19; Dementia; Female; Follow-Up Studies; Holistic Health; Humans; Male; Pandemics; Patient-Centered Care; Pneumonia, Viral; SARS-CoV-2; Spain; Telemedicine

Detection of Mild Cognitive Impairment in an At-Risk Group of Older Adults: Can a Novel Self-Administered Serious Game-Based Screening Test Improve Diagnostic Accuracy? - Zygouris, Stelios; Iliadou, Paraskevi; Lazarou, Eftychia; Giakoumis, Dimitrios; Votis, Konstantinos; Alexiadis, Anastasios; Triantafyllidis, Andreas; Segkouli, Sofia; Tzovaras, Dimitrios; Tsiatsos, Thrasyvoulos; Papagianopoulos, Sotirios; Tsolaki, Magda (J Alzheimers Dis, 2020)
BACKGROUND: Literature supports the use of serious games and virtual environments to assess cognitive functions and detect cognitive decline. This promising assessment method, however, has not yet been translated into self-administered screening instruments for pre-clinical dementia. OBJECTIVE: The aim of this study is to assess the performance of a novel self-administered serious game-based test, namely the Virtual Supermarket Test (VST), in detecting mild cognitive impairment (MCI) in a sample of older adults with subjective memory complaints (SMC), in comparison with two well-established screening instruments, the Montreal Cognitive Assessment (MoCA) and the Mini-Mental State Examination (MMSE). METHODS: Two groups, one of healthy older adults with SMC (N = 48) and one of MCI patients (N = 47) were recruited from day centers for cognitive disorders and administered the VST, the MoCA, the MMSE, and an extended pencil and paper neuropsychological test battery. RESULTS: The VST displayed a correct classification rate (CCR) of 81.91% when differentiating between MCI patients and older adults with SMC, while the MoCA displayed of CCR of 72.04% and the MMSE displayed a CCR of 64.89%. CONCLUSION: The three instruments assessed in this study displayed significantly different performances in differentiating between healthy older adults with SMC and MCI patients. The VST displayed a good CCR, while the MoCA displayed an average CCR and the MMSE displayed a poor CCR. The VST appears to be a robust tool for detecting MCI in a population of older adults with SMC.

Development and Validation of a High Sensitivity Assay for Measuring p217 + tau in Cerebrospinal Fluid. - Triana-Baltzer, Gallen; Van Kolen, Kristof; Theunis, Clara; Moughadam, Setareh; Slemmon, Randy; Mercken, Marc; Galpern, Wendy; Sun, Hong; Kolb, Hartmuth (J Alzheimers Dis, 2020)
BACKGROUND: Early and accurate detection and staging is critical to managing Alzheimer's disease (AD) and supporting clinical trials. Cerebrospinal fluid (CSF) biomarkers for amyloid-β peptides, tau species, and various neurodegenerative and inflammatory analytes are leading the way in this regard, yet there is room for improved sensitivity and specificity. In particular tau is known to be present in many different fragments, conformations, and post-translationally modified forms. While the exact tau species that might best reflect AD pathology is unknown, a growing body of evidence suggests that forms with high levels of phosphorylation in the mid-region may be especially enriched in AD. OBJECTIVE: Develop an assay for measuring p217tau in CSF. METHODS: Here we describe the development and validation of a novel sELISA for measuring CSF tau species containing phosphorylation at threonines 212 & 217, aka p217 + tau, using the PT3 antibody. RESULTS: While the analyte is present at extremely low levels the assay is sufficiently sensitive and specific to quantitate p217 + tau with excellent precision, accuracy, and dilution linearity, allowing good differentiation between diagnostic subgroups. The p217 + tau measurements appear to track AD pathology better than the commonly used p181tau epitope, suggesting superior diagnostic and staging performance. Finally, the assay can also be configured to differentiate antibody-bound versus antibody-free tau, and therefore can be used to measure target engagement by p217 + tau-targeting immunotherapeutics. CONCLUSION: The assay for measuring p217 + tau described here is highly sensitive, accurate, precise, dilution linear, and shows good potential for identifying and staging AD.

Dickkopf-1 Overexpression in vitro Nominates Candidate Blood Biomarkers Relating to Alzheimer's Disease Pathology. - Shi, Liu; Winchester, Laura M; Liu, Benjamine Y; Killick, Richard; Ribe, Elena M; Westwood, Sarah; Baird, Alison L; Buckley, Noel J; Hong, Shengjun; Dobricic, Valerija; Kilpert, Fabian; Franke, Andre; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies suggest that Dickkopf-1 (DKK1), an inhibitor of Wnt signaling, plays a role in amyloid-induced toxicity and hence Alzheimer's disease (AD). However, the effect of DKK1 expression on protein expression, and whether such proteins are altered in disease, is unknown. OBJECTIVE: We aim to test whether DKK1 induced protein signature obtained in vitro were associated with markers of AD pathology as used in the amyloid/tau/neurodegeneration (ATN) framework as well as with clinical outcomes. METHODS: We first overexpressed DKK1 in HEK293A cells and quantified 1,128 proteins in cell lysates using aptamer capture arrays (SomaScan) to obtain a protein signature induced by DKK1. We then used the same assay to measure the DKK1-signature proteins in human plasma in two large cohorts, EMIF (n = 785) and ANM (n = 677). RESULTS: We identified a 100-protein signature induced by DKK1 in vitro. Subsets of proteins, along with age and apolipoprotein E ɛ4 genotype distinguished amyloid pathology (A + T-N-, A+T+N-, A+T-N+, and A+T+N+) from no AD pathology (A-T-N-) with an area under the curve of 0.72, 0.81, 0.88, and 0.85, respectively. Furthermore, we found that some signature proteins (e.g., Complement C3 and albumin) were associated with cognitive score and AD diagnosis in both cohorts. CONCLUSIONS: Our results add further evidence for a role of DKK regulation of Wnt signaling in AD and suggest that DKK1 induced signature proteins obtained in vitro could reflect theATNframework as well as predict disease severity and progression in vivo.

Environmental Nanoparticles, SARS-CoV-2 Brain Involvement, and Potential Acceleration of Alzheimer's and Parkinson's Diseases in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Torres-Jardón, Ricardo; Franco-Lira, Maricela; Kulesza, Randy; González-Maciel, Angelica; Reynoso-Robles, Rafael; Brito-Aguilar, Rafael; García-Arreola, Berenice; Revueltas-Ficachi, Paula; Barrera-Velázquez, Juana Adriana; García-Alonso, Griselda; García-Rojas, Edgar; et al. (J Alzheimers Dis, 2020)
Alzheimer's and Parkinson's diseases (AD, PD) have a pediatric and young adult onset in Metropolitan Mexico City (MMC). The SARS-CoV-2 neurotropic RNA virus is triggering neurological complications and deep concern regarding acceleration of neuroinflammatory and neurodegenerative processes already in progress. This review, based on our MMC experience, will discuss two major issues: 1) why residents chronically exposed to air pollution are likely to be more susceptible to SARS-CoV-2 systemic and brain effects and 2) why young people with AD and PD already in progress will accelerate neurodegenerative processes. Secondary mental consequences of social distancing and isolation, fear, financial insecurity, violence, poor health support, and lack of understanding of the complex crisis are expected in MMC residents infected or free of SARS-CoV-2. MMC residents with pre-SARS-CoV-2 accumulation of misfolded proteins diagnostic of AD and PD and metal-rich, magnetic nanoparticles damaging key neural organelles are an ideal host for neurotropic SARS-CoV-2 RNA virus invading the body through the same portals damaged by nanoparticles: nasal olfactory epithelium, the gastrointestinal tract, and the alveolar-capillary portal. We urgently need MMC multicenter retrospective-prospective neurological and psychiatric population follow-up and intervention strategies in place in case of acceleration of neurodegenerative processes, increased risk of suicide, and mental disease worsening. Identification of vulnerable populations and continuous effort to lower air pollution ought to be critical steps.
Keywords: Adult; Air Pollution; Alzheimer Disease; Brain Diseases; Coronavirus Infections; COVID-19; Disease Progression; Environmental Pollutants; Humans; Middle Aged; Nanoparticles; Pandemics; Parkinson Disease; Pneumonia, Viral; Suicide; Urban Population

Epilepsy in Neurodegenerative Dementias: A Clinical, Epidemiological, and EEG Study. - Arnaldi, Dario; Donniaquio, Andrea; Mattioli, Pietro; Massa, Federico; Grazzini, Matteo; Meli, Riccardo; Filippi, Laura; Grisanti, Stefano; Famá, Francesco; Terzaghi, Michele; Girtler, Nicola; Brugnolo, Andrea; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Seizures are common in patients with dementia but precise epidemiologic data of epilepsy in neurodegenerative dementia is lacking. OBJECTIVE: The first aim of the study was to investigate prevalence and clinical characteristics of epilepsy in a large cohort of patients with neurodegenerative dementias. Subsequently, we explored clinical, neuropsychological, and quantitative electroencephalogram (qEEG) data of Alzheimer's disease (AD) patients with epilepsy (AD-EPI) as compared to AD patients without epilepsy (AD-CTR). METHODS: We retrospectively evaluated consecutive patients with a diagnosis of a neurodegenerative dementia and a clinically diagnosed epilepsy that required antiepileptic drugs (AED). All patients underwent baseline comprehensive neuropsychological assessment. A follow-up of at least one year was requested to confirm the dementia diagnosis. In AD patients, qEEG power band analysis was performed. AD-CTR and AD-EPI patients were matched for age, Mini-Mental State Examination score, and gender. RESULTS: Thirty-eight out of 2,054 neurodegenerative dementia patients had epilepsy requiring AED. The prevalence of epilepsy was 1.82% for AD, 1.28% for the behavioral variant of frontotemporal dementia (bvFTD), 2.47% for dementia with Lewy bodies (DLB), and 12% for primary progressive aphasia. Epilepsy were more drug-responsive in AD than in non-AD dementias. Finally, no significant differences were found in neuropsychological and qEEG data between AD-EPI and AD-CTR patients. CONCLUSION: In our cohort, AD, FTD, and DLB dementias have similar prevalence of epilepsy, even if AD patients were more responsive to AED. Moreover, AD-EPI patients did not have significant clinical, neuropsychological qEEG differences compared with AD-CTR patients.

Estrogens Inhibit Amyloid-β-Mediated Paired Helical Filament-Like Conformation of Tau Through Antioxidant Activity and miRNA 218 Regulation in hTau Mice. - Guglielmotto, Michela; Manassero, Giusi; Vasciaveo, Valeria; Venezia, Marika; Tabaton, Massimo; Tamagno, Elena (J Alzheimers Dis, 2020)
BACKGROUND: The risk of developing Alzheimer's disease as well as its progression and severity are known to be different in men and women, and cognitive decline is greater in women than in men at the same stage of disease and could be correlated at least in part on estradiol levels. OBJECTIVE: In our work we found that biological sex influences the effect of amyloid-β42 (Aβ42) monomers on pathological tau conformational change. METHODS: In this study we used transgenic mice expressing the wild-type human tau (hTau) which were subjected to intraventricular (ICV) injections of Aβ peptides in nanomolar concentration. RESULTS: We found that Aβ42 produces pathological conformational changes and hyperphosphorylation of tau protein in male or ovariectomized female mice but not in control females. The treatment of ovariectomized females with estradiol replacement protects against the pathological conformation of tau and seems to be mediated by antioxidant activity as well as the ability to modulate the expression of miRNA 218 linked to tau phosphorylation. CONCLUSION: Our study indicates that factors as age, reproductive stage, hormone levels, and the interplay with other risk factors should be considered in women, in order to identify the best appropriate therapeutic approach in prevention of cognitive impairment.

Fascicle- and Glucose-Specific Deterioration in White Matter Energy Supply in Alzheimer's Disease. - Roy, Maggie; Rheault, François; Croteau, Etienne; Castellano, Christian-Alexandre; Fortier, Mélanie; St-Pierre, Valérie; Houde, Jean-Christophe; Turcotte, Éric E; Bocti, Christian; Fülöp, Tamás; Cunnane, Stephen C; Descoteaux, Maxime (J Alzheimers Dis, 2020)
BACKGROUND: White matter energy supply to oligodendrocytes and the axonal compartment is crucial for normal axonal function. Although gray matter glucose hypometabolism is extensively reported in Alzheimer's disease (AD), glucose and ketones, the brain's two main fuels, are rarely quantified in white matter in AD. OBJECTIVE: Using adual-tracer PET method combined with a fascicle-specific diffusion MRI approach, robust to white matter hyper intensities and crossing fibers, we aimed to quantify both glucose and ketone metabolismin specific white matter fascicles associated with mild cognitive impairment (MCI; n = 51) and AD (n = 13) compared to cognitively healthy age-matched controls (Controls; n = 14). METHODS: Eight white matter fascicles of the limbic lobe and corpus callosum were extracted and analyzed into fascicle profiles of five sections. Glucose (18F-fluorodeoxyglucose) and ketone (11C-acetoacetate) uptake rates, corrected for partial volume effect, were calculated along each fascicle. RESULTS: The only fascicle with significantly lower glucose uptake in AD compared to Controls was the left posterior cingulate segment of the cingulum (-22%; p = 0.016). Non-significantly lower glucose uptake in this fascicle was also observed in MCI. In contrast to glucose, ketone uptake was either unchanged or higher in sections of the fornix and parahippocampal segment of the cingulum in AD. CONCLUSION: To our knowledge, this is the first report of brain fuel uptake calculated along white matter fascicles in humans. Energetic deterioration in white matter in AD appears to be specific to glucose and occurs first in the posterior cingulum.

Functional Integrity of Synapses in the Central Nervous System of Cognitively Intact Individuals with High Alzheimer's Disease Neuropathology is Associated with Absence of Synaptic Tau Oligomers. - Singh, Ayush; Allen, Dyron; Fracassi, Anna; Tumurbaatar, Batbayar; Natarajan, Chandramouli; Scaduto, Pietro; Woltjer, Randy; Kayed, Rakez; Limon, Agenor; Krishnan, Balaji; Taglialatela, Giulio (J Alzheimers Dis, 2020)
BACKGROUND: Certain individuals, here referred to as Non-Demented with Alzheimer Neuropathology (NDAN), do not show overt neurodegeneration (N - ) and remain cognitively intact despite the presence of plaques (A+) and tangles (T+) that would normally be consistent with fully symptomatic Alzheimer's disease (AD). OBJECTIVE: The existence of NDAN (A + T +N - ) subjects suggests that the human brain utilizes intrinsic mechanisms that can naturally evade cognitive decline normally associated with the symptomatic stages of AD (A + T +N +). Deciphering the underlying mechanisms would prove relevant to develop complementing therapeutics to prevent progression of AD-related cognitive decline. METHODS: Previously, we have reported that NDAN present with preserved neurogenesis and synaptic integrity paralleled by absence of amyloid oligomers at synapses. Using postmortem brain samples from age-matched control subjects, demented AD patients and NDAN individuals, we performed immunofluorescence, western blots, micro transplantation of synaptic membranes in Xenopus oocytes followed by twin electrode voltage clamp electrophysiology and fluorescence assisted single synaptosome-long term potentiation studies. RESULTS: We report decreased tau oligomers at synapses in the brains of NDAN subjects. Furthermore, using novel approaches we report, for the first time, that such absence of tau oligomers at synapses is associated with synaptic functional integrity in NDAN subjects as compared to demented AD patients. CONCLUSION: Overall, these results give further credence to tau oligomers as primary actors of synaptic destruction underscoring cognitive demise in AD and support their targeting as a viable therapeutic strategy for AD and related tauopathies.

Gait Disturbances are Associated with Increased Cognitive Impairment and Cerebrospinal Fluid Tau Levels in a Memory Clinic Cohort. - Muurling, Marijn; Rhodius-Meester, Hanneke F M; Pärkkä, Juha; van Gils, Mark; Frederiksen, Kristian S; Bruun, Marie; Hasselbalch, Steen G; Soininen, Hilkka; Herukka, Sanna-Kaisa; Hallikainen, Merja; Teunissen, Charlotte E; Visser, Pieter Jelle; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Gait analysis with accelerometers is a relatively inexpensive and easy to use method to potentially support clinical diagnoses of Alzheimer's disease and other dementias. It is not clear, however, which gait features are most informative and how these measures relate to Alzheimer's disease pathology. OBJECTIVE: In this study, we tested if calculated features of gait 1) differ between cognitively normal subjects (CN), mild cognitive impairment (MCI) patients, and dementia patients, 2) are correlated with cerebrospinal fluid (CSF) biomarkers related to Alzheimer's disease, and 3) predict cognitive decline. METHODS: Gait was measured using tri-axial accelerometers attached to the fifth lumbar vertebra (L5) in 58 CN, 58 MCI, and 26 dementia participants, while performing a walk and dual task. Ten gait features were calculated from the vertical L5 accelerations, following principal component analysis clustered in four domains, namely pace, rhythm, time variability, and length variability. Cognitive decline over time was measured using MMSE, and CSF biomarkers were available in a sub-group. RESULTS: Linear mixed models showed that dementia patients had lower pace scores than MCI patients and CN subjects (p < 0.05). In addition, we found associations between the rhythm domain and CSF-tau, especially in the dual task. Gait was not associated with CSF Aβ42 levels and cognitive decline over time as measured with the MMSE. CONCLUSION: These findings suggest that gait-particularly measures related to pace and rhythm-are altered in dementia and have a direct link with measures of neurodegeneration.

Generation of Transgenic Cynomolgus Monkeys Overexpressing the Gene for Amyloid-β Precursor Protein. - Seita, Yasunari; Morimura, Toshifumi; Watanabe, Naoki; Iwatani, Chizuru; Tsuchiya, Hideaki; Nakamura, Shinichiro; Suzuki, Toshiharu; Yanagisawa, Daijiro; Tsukiyama, Tomoyuki; Nakaya, Masataka; Okamura, Eiichi; Muto, Masanaga; et al. (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) is the most common cause of dementia and understanding its pathogenesis should lead to improved therapeutic and diagnostic methods. Although several groups have developed transgenic mouse models overexpressing the human amyloid-β precursor protein (APP) gene with AD mutations, with and without presenilin mutations, as well as APP gene knock-in mouse models, these animals display amyloid pathology but do not show neurofibrillary tangles or neuronal loss. This presumably is due to differences between the etiology of the aged-related human disease and the mouse models. Here we report the generation of two transgenic cynomolgus monkeys overexpressing the human gene for APP with Swedish, Artic, and Iberian mutations, and demonstrated expression of gene tagged green fluorescent protein marker in the placenta, amnion, hair follicles, and peripheral blood. We believe that these nonhuman primate models will be very useful to study the pathogenesis of dementia and AD. However, generated Tg monkeys still have some limitations. We employed the CAG promoter, which will promote gene expression in a non-tissue specific manner. Moreover, we used transgenic models but not knock-in models. Thus, the inserted transgene destroys endogenous gene(s) and may affect the phenotype(s). Nevertheless, it will be of great interest to determine whether these Tg monkeys will develop tauopathy and neurodegeneration similar to human AD.

The GSM BPN-15606 as a Potential Candidate for Preventative Therapy in Alzheimer's Disease. - Prikhodko, Olga; Rynearson, Kevin D; Sekhon, Travis; Mante, Mike M; Nguyen, Phuong D; Rissman, Robert A; Tanzi, Rudolph E; Wagner, Steven L (J Alzheimers Dis, 2020)
BACKGROUND: In the amyloid hypothesis of Alzheimer's disease (AD), the dysregulation of amyloid-β protein (Aβ) production and clearance leads to amyloid deposits, tau tangles, neuronal loss, and cognitive dysfunction. Thus far, therapies targeting the enzymes responsible for Aβ production have been found ineffective or having significant side effects. OBJECTIVE: To test whether a γ-secretase modulator, BPN-15606, is an effective disease-modifying or preventative treatment in the PSAPP mouse model of AD. METHODS: We treated pre-plaque (3-month-old) and post-plaque (6-month-old) PSAPP AD transgenic mice for 3 months and examined behavioral, biochemical, and pathological end points. RESULTS: BPN-15606 attenuated cognitive impairment and reduced amyloid plaque load, microgliosis, and astrogliosis associated with the AD phenotype of PSAPP mice when administered to pre-plaque (3-month-old) but was ineffective when administered to post-plaque (6-month-old) mice. No treatment-related toxicity was observed. CONCLUSION: BPN-15606 appears efficacious when administered prior to significant pathology.

Metabolic Profiles Help Discriminate Mild Cognitive Impairment from Dementia Stage in Alzheimer's Disease. - Jääskeläinen, Olli; Hall, Anette; Tiainen, Mika; van Gils, Mark; Lötjönen, Jyrki; Kangas, Antti J; Helisalmi, Seppo; Pikkarainen, Maria; Hallikainen, Merja; Koivisto, Anne; Hartikainen, Päivi; Hiltunen, Mikko; et al. (J Alzheimers Dis, 2020)
Accurate differentiation between neurodegenerative diseases is developing quickly and has reached an effective level in disease recognition. However, there has been less focus on effectively distinguishing the prodromal state from later dementia stages due to a lack of suitable biomarkers. We utilized the Disease State Index (DSI) machine learning classifier to see how well quantified metabolomics data compares to clinically used cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD). The metabolic profiles were quantified for 498 serum and CSF samples using proton nuclear magnetic resonance spectroscopy. The patient cohorts in this study were dementia (with a clinical AD diagnosis) (N = 359), mild cognitive impairment (MCI) (N = 96), and control patients with subjective memory complaints (N = 43). DSI classification was conducted for MCI (N = 51) and dementia (N = 214) patients with low CSF amyloid-β levels indicating AD pathology and controls without such amyloid pathology (N = 36). We saw that the conventional CSF markers of AD were better at classifying controls from both dementia and MCI patients. However, quantified metabolic subclasses were more effective in classifying MCI from dementia. Our results show the consistent effectiveness of traditional CSF biomarkers in AD diagnostics. However, these markers are relatively ineffective in differentiating between MCI and the dementia stage, where the quantified metabolomics data provided significant benefit.

A New Serum Biomarker Set to Detect Mild Cognitive Impairment and Alzheimer's Disease by Peptidome Technology. - Abe, Koji; Shang, Jingwei; Shi, Xiaowen; Yamashita, Toru; Hishikawa, Nozomi; Takemoto, Mami; Morihara, Ryuta; Nakano, Yumiko; Ohta, Yasuyuki; Deguchi, Kentaro; Ikeda, Masaki; Ikeda, Yoshio; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Because dementia is an emerging problem in the world, biochemical markers of cerebrospinal fluid (CSF) and radio-isotopic analyses are helpful for diagnosing Alzheimer's disease (AD). Although blood sample is more feasible and plausible than CSF or radiological biomarkers for screening potential AD, measurements of serum amyloid- β (Aβ), plasma tau, and serum antibodies for Aβ1 - 42 are not yet well established. OBJECTIVE: We aimed to identify a new serum biomarker to detect mild cognitive impairment (MCI) and AD in comparison to cognitively healthy control by a new peptidome technology. METHODS: With only 1.5μl of serum, we examined a new target plate "BLOTCHIP®" plus a matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS) to discriminate control (n = 100), MCI (n = 60), and AD (n = 99). In some subjects, cognitive Mini-Mental State Examination (MMSE) were compared to positron emission tomography (PET) with Pittsburgh compound B (PiB) and the serum probability of dementia (SPD). The mother proteins of candidate serum peptides were examined in autopsied AD brains. RESULTS: Apart from Aβ or tau, the present study discovered a new diagnostic 4-peptides-set biomarker for discriminating control, MCI, and AD with 87% of sensitivity and 65% of specificity between control and AD (***p < 0.001). MMSE score was well correlated to brain Aβ deposition and to SPD of AD. The mother proteins of the four peptides were upregulated for coagulation, complement, and plasticity (three proteins), and was downregulated for anti-inflammation (one protein) in AD brains. CONCLUSION: The present serum biomarker set provides a new, rapid, non-invasive, highly quantitative and low-cost clinical application for dementia screening, and also suggests an alternative pathomechanism of AD for neuroinflammation and neurovascular unit damage.

Older Patients with Alzheimer's Disease-Related Cortical Atrophy Who Develop Post-Operative Delirium May Be at Increased Risk of Long-Term Cognitive Decline After Surgery. - Racine, Annie M; Touroutoglou, Alexandra; Abrantes, Tatiana; Wong, Bonnie; Fong, Tamara G; Cavallari, Michele; Travison, Thomas G; Gou, Yun; Marcantonio, Edward R; Alsop, David C; Jones, Richard N; Inouye, Sharon K; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Older surgical patients with Alzheimer's disease (AD) dementia and delirium are at increased risk for accelerated long-term cognitive decline. OBJECTIVE: Investigate associations between a probabilistic marker of preclinical AD, delirium, and long-term cognitive decline. METHODS: The Successful Aging after Elective Surgery cohort includes older adults (≥70 years) without dementia who underwent elective surgery. 140 patients underwent preoperative magnetic resonance imaging and had≥6 months cognitive follow-up. Cortical thickness was measured in 'AD-Signature' regions. Delirium was evaluated each postoperative day by the Confusion Assessment Method. Cognitive performance was assessed using a detailed neuropsychological battery at baseline; months 1, 2, and 6; and every 6 months thereafter until 36 months. Using either a General Cognitive Performance composite (GCP) or individual test scores as outcomes, we performed linear mixed effects models to examine main effects of AD-signature atrophy and the interaction of AD-signature atrophy and delirium on slopes of cognitive change from post-operative months 2-36. RESULTS: Reduced baseline AD-signature cortical thickness was associated with greater 36-month cognitive decline in GCP (standardized beta coefficient, β = -0.030, 95% confidence interval [-0.060, -0.001]). Patients who developed delirium who also had thinner AD signature cortex showed greater decline on a verbal learning test (β = -0.100 [-0.192, -0.007]). CONCLUSION: Patients with the greatest baseline AD-related cortical atrophy who develop delirium after elective surgery appear to experience the greatest long-term cognitive decline. Thus, atrophy suggestive of preclinical AD and the development of delirium may be high-risk indicators for long-term cognitive decline following surgery.

Optimizing Use of Neuroimaging Tools in Evaluation of Prodromal Alzheimer's Disease and Related Disorders. - Raji, Cyrus A; Torosyan, Nare; Silverman, Daniel H S (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) is the most common neurodegenerative disease and is characterized by preclinical, pre-dementia, and dementia phases. Progression of the disease leads to cognitive decline and is associated with loss of functional independence, personality changes, and behavioral disturbances. Current guidelines for AD diagnosis include the use of neuroimaging tools as biomarkers for identifying and monitoring pathological changes. Various imaging modalities, namely magnetic resonance imaging (MRI), fluorodeoxyglucose-positron emission tomography (FDG-PET) and PET with amyloid-beta tracers are available to facilitate early accurate diagnoses. Enhancing diagnosis in the early stages of the disease can allow for timely interventions that can delay progression of the disease. This paper will discuss the characteristic findings associated with each of the imaging tools for patients with AD, with a focus on FDG-PET due to its established accuracy in assisting with the differential diagnosis of dementia and discussion of other methods including MRI. Diagnostically-relevant features to aid clinicians in making a differential diagnosis will also be pointed out and multimodal imaging will be reviewed. We also discuss the role of quantification software in interpretation of brain imaging. Lastly, to guide evaluation of patients presenting with cognitive deficits, an algorithm for optimal integration of these imaging tools will be shared. Molecular imaging modalities used in dementia evaluations hold promise toward identifying AD-related pathology before symptoms are fully in evidence. The work describes state of the art functional and molecular imaging methods for AD. It will also overview a clinically applicable quantitative method for reproducible assessments of such scans in the early identification of AD.

Partial Inhibition of Mitochondrial Complex I Reduces Tau Pathology and Improves Energy Homeostasis and Synaptic Function in 3xTg-AD Mice. - Stojakovic, Andrea; Chang, Su-Youne; Nesbitt, Jarred; Pichurin, Nicholas P; Ostroot, Mark A; Aikawa, Tomonori; Kanekiyo, Takahisa; Trushina, Eugenia (J Alzheimers Dis, 2020)
BACKGROUND: Accumulation of hyperphosphorylated tau (pTau) protein is associated with synaptic dysfunction in Alzheimer's disease (AD). We previously demonstrated that neuroprotection in familial mouse models of AD could be achieved by targeting mitochondria complex I (MCI) and activating the adaptive stress response. Efficacy of this strategy on pTau-related pathology remained unknown. OBJECTIVE: To investigate the effect of specific MCI inhibitor tricyclic pyrone compound CP2 on levels of human pTau, memory function, long term potentiation (LTP), and energy homeostasis in 18-month-old 3xTg-AD mice and explore the potential mechanisms. METHODS: CP2 was administered to male and female 3xTg-AD mice from 3.5-18 months of age. Cognitive function was assessed using the Morris water maze. Glucose metabolism was measured in periphery using a glucose tolerance test and in the brain using fluorodeoxyglucose F18 positron-emission tomography (FDG-PET). LTP was evaluated using electrophysiology in the hippocampus. The expression of key proteins associated with neuroprotective mechanisms were assessed by western blotting. RESULTS: Chronic CP2 treatment restored synaptic activity in female 3xTg-AD mice; cognitive function, levels of synaptic proteins, glucose metabolism, and energy homeostasis were improved in male and female 3xTg-AD mice. Significant reduction of human pTau in the brain was associated with increased activity of protein phosphatase of type 2A (PP2A), and reduced activity of cyclin-dependent kinase 5 (CDK5) and glycogen synthase kinase 3β (GSK3β). CONCLUSION: CP2 treatment protected against synaptic dysfunction and memory impairment in symptomatic 3xTg-AD mice, and reduced levels of human pTau, indicating that targeting mitochondria with small molecule specific MCI inhibitors represents a promising strategy for treating AD.

Perceived Stress is Associated with Alzheimer's Disease Cerebrospinal Fluid Biomarkers in African Americans with Mild Cognitive Impairment. - Trammell, Antoine R; McDaniel, Darius J; Obideen, Malik; Okafor, Maureen; Thomas, Tiffany L; Goldstein, Felicia C; Shaw, Leslie M; Hajjar, Ihab M (J Alzheimers Dis, 2020)
BACKGROUND: African Americans (AA) have a higher Alzheimer's disease (AD) prevalence and report more perceived stress than White Americans. The biological basis of the stress-AD link is unclear. This study investigates the connection between stress and AD biomarkers in a biracial cohort. OBJECTIVE: Establish biomarker evidence for the observed association between stress and AD, especially in AA. METHODS: A cross-sectional study (n = 364, 41.8% AA) administering cognitive tests and the perceived stress scale (PSS) questionnaire. A subset (n = 309) provided cerebrospinal fluid for measurement of Aβ42, Tau, Ptau, Tau/Aβ42 (TAR), and Ptau/Aβ42 (PTAR). Multivariate linear regression, including factors that confound racial differences in AD, was performed. RESULTS: Higher PSS scores were associated with higher Ptau (β= 0.43, p = 0.01) and PTAR (β= 0.005, p = 0.03) in AA with impaired cognition (mild cognitive impairment). CONCLUSION: Higher PSS scores were associated with Tau-related AD biomarker indices in AA/MCI, suggesting a potential biological connection for stress with AD and its racial disparity.

Plasma High Density Lipoprotein Small Subclass is Reduced in Alzheimer's Disease Patients and Correlates with Cognitive Performance. - Pedrini, Steve; Hone, Eugene; Gupta, Veer B; James, Ian; Teimouri, Elham; Bush, Ashley I; Rowe, Christopher C; Villemagne, Victor L; Ames, David; Masters, Colin L; Rainey-Smith, Stephanie; Verdile, Giuseppe; et al. (J Alzheimers Dis, 2020)
BACKGROUND: The link between cholesterol and Alzheimer's disease (AD) has received much attention, as evidence suggests high levels of cholesterol might be an AD risk factor. The carriage of cholesterol and lipids through the body is mediated via lipoproteins, some of which, particularly apolipoprotein E (ApoE), are intimately linked with AD. In humans, high density lipoprotein (HDL) is regarded as a "good" lipid complex due to its ability to enable clearance of excess cholesterol via 'cholesterol reverse transport', although its activities in the pathogenesis of AD are poorly understood. There are several subclasses of HDL; these range from the newly formed small HDL, to much larger HDL. OBJECTIVE: We examined the major subclasses of HDL in healthy controls, mild cognitively impaired, and AD patients who were not taking statins to determine whether there were HDL profile differences between the groups, and whether HDL subclass levels correlated with plasma amyloid-β (Aβ) levels or brain Aβ deposition. METHODS: Samples from AIBL cohort were used in this study. HDL subclass levels were assessed by Lipoprint while Aβ1-42 levels were assessed by ELISA. Brain Aβ deposition was assessed by PET scan. Statistical analysis was performed using parametric and non-parametric tests. RESULTS: We found that small HDL subclass is reduced in AD patients and it correlates with cognitive performance while plasma Aβ concentrations do not correlate with lipid profile or HDL subfraction levels. CONCLUSION: Our data indicate that AD patients exhibit altered plasma HDL profile and that HDL subclasses correlate with cognitive performances.

The Prevalence of Dementia: A Systematic Review and Meta-Analysis. - Cao, Qing; Tan, Chen-Chen; Xu, Wei; Hu, Hao; Cao, Xi-Peng; Dong, Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2020)
Dementia is a severe neurodegenerative disorder and it can be categorized into several subtypes by different pathogenic causes. We sought to comprehensively analyzed the prevalence of dementia from perspectives of geographic region (Asia, Africa, South America, and Europe/North America), age, and gender. We searched PubMed and EMBASE for relevant articles on dementia published from January 1985 to August 2019. In these studies, analyses were stratified by geographic region, age, and gender. Meta-regression was conducted to identify if there were significant differences between groups. We included forty-seven studies. Among the individuals aged 50 and over in the community, the pooled prevalence for all-cause dementia, Alzheimer's disease, and vascular dementia were 697 (CI95%: 546-864) per 10,000 persons, 324 (CI95%: 228-460) per 10,000 persons, and 116 (CI95%: 86-157) per 10,000 persons, respectively. In our study, the prevalence of all-type dementia in individuals aged 100 years and older (6,592 per 10,000 cases) is 244 times higher than in those aged 50-59 (27 per 10,000 cases). The number of people living with dementia approximately doubles every five years. The prevalence was greater in women than in men (788 cases versus 561 cases per 10,000 persons) in overall analysis. In individuals aged 60 to 69 years, AD prevalence in females was 1.9 times greater than that in males (108 cases versus 56 cases per 10,000 persons), while the prevalence of VaD was 1.8 times greater in males than in females (56 cases versus 32 cases per 10,000 persons). Prevalence rate was higher in Europe and North America than in Asia, Africa, and South America.

Resilience of Alzheimer's Disease to COVID-19. - Li, Jingwen; Long, Xi; Huang, Heqing; Tang, Jine; Zhu, Chunli; Hu, Shaoping; Wu, Jing; Li, Jinghong; Lin, Zhicheng; Xiong, Nian (J Alzheimers Dis, 2020)
BACKGROUND: Facing the novel coronavirus disease 2019 (COVID-19), most vulnerable individuals are seniors, especially those with comorbidities. More attention needs to been paid to the COVID-19 patients with Alzheimer's disease (AD), which is the top age-related neurodegenerative disease. OBJECTIVE: Since it is unclear whether AD patients are prone to COVID-19 infection and progression to severe stages, we report for the first time a retrospective analysis of the clinical characteristics of AD patients with COVID-19 pneumonia. METHODS: We conducted a retrospective cohort study of the clinical data of 19 AD patients with COVID-19 pneumonia, compared with 23 non-AD COVID-19 patients admitted at the same time to our hospital. Demographic, clinical, laboratory, radiological, and treatment data were collected and analyzed. RESULTS: Between AD patients and non-AD patients with COVID-19 pneumonia, the pneumonia severity was not significantly different. AD patients had a higher clustering onset than non-AD patients. The median duration from symptom onset to hospitalization were shorter in AD patients than non-AD patients, indicating the former were sent to the hospital by their family or from nursing home earlier than the later. The median duration from hospitalization to discharge seemed shorter in AD patients than non-AD patients. Dementia patients seemed less likely to report fatigue. It is noticed that more AD patients might have pericardial effusion than the non-AD patients. CONCLUSION: AD patients with COVID-19 were in milder conditions with a better prognosis than non-AD patients. AD patients who had adequate access to healthcare showed resilience to COVID-19 with shorter hospital stays.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cluster Analysis; Cohort Studies; Coronavirus Infections; COVID-19; Disease Progression; Fatigue; Female; Humans; Length of Stay; Male; Middle Aged; Pandemics; Patient Discharge; Pleural Effusion; Pneumonia; Pneumonia, Viral; Prognosis; Resilience, Psychological

Revised Framingham Stroke Risk Profile: Association with Cognitive Status and MRI-Derived Volumetric Measures. - Pelcher, Isabelle; Puzo, Christian; Tripodis, Yorghos; Aparicio, Hugo J; Steinberg, Eric G; Phelps, Alyssa; Martin, Brett; Palmisano, Joseph N; Vassey, Elizabeth; Lindbergh, Cutter; McKee, Ann C; Stein, Thor D; et al. (J Alzheimers Dis, 2020)
BACKGROUND: The Framingham Stroke Risk Profile (FSRP) was created in 1991 to estimate 10-year risk of stroke. It was revised in 2017 (rFSRP) to reflect the modern data on vascular risk factors and stroke risk. OBJECTIVE: This study examined the association between the rFSRP and cognitive and brain aging outcomes among participants from the National Alzheimer's Coordinating Center (NACC) Uniform Data Set (UDS). METHODS: Cross-sectional rFSRP was computed at baseline for 19,309 participants (mean age = 72.84, SD = 8.48) from the NACC-UDS [9,697 (50.2%) normal cognition, 4,705 (24.4%) MCI, 4,907 (25.4%) dementia]. Multivariable linear, logistic, or ordinal regressions examined the association between the rFSRP and diagnostic status, neuropsychological test performance, CDR® Sum of Boxes, as well as total brain volume (TBV), hippocampal volume (HCV), and log-transformed white matter hyperintensities (WMH) for an MRI subset (n = 1,196). Models controlled for age, sex, education, racial identity, APOEɛ4 status, and estimated intracranial volume for MRI models. RESULTS: The mean rFSRP probability was 10.42% (min = 0.50%, max = 95.71%). Higher rFSRP scores corresponded to greater CDR Sum of Boxes (β= 0.02, p = 0.028) and worse performance on: Trail Making Test A (β= 0.05, p <  0.001) and B (β= 0.057, p <  0.001), and Digit Symbol (β= -0.058, p <  0.001). Higher rFSRP scores were associated with increased odds for a greater volume of log-transformed WMH (OR = 1.02 per quartile, p = 0.015). No associations were observed for diagnosis, episodic memory or language test scores, HCV, or TBV. CONCLUSION: These results support the rFSRP as a useful metric to facilitate clinical research on the associations between cerebrovascular disease and cognitive and brain aging.

Serum Hepcidin Levels in Cognitively Normal Older Adults with High Neocortical Amyloid-β Load. - Chatterjee, Pratishtha; Mohammadi, Maryam; Goozee, Kathryn; Shah, Tejal M; Sohrabi, Hamid R; Dias, Cintia B; Shen, Kaikai; Asih, Prita R; Dave, Preeti; Pedrini, Steve; Ashton, Nicholas J; Hye, Abdul; et al. (J Alzheimers Dis, 2020)
BACKGROUND/OBJECTIVE: Hepcidin, an iron-regulating hormone, suppresses the release of iron by binding to the iron exporter protein, ferroportin, resulting in intracellular iron accumulation. Given that iron dyshomeostasis has been observed in Alzheimer's disease (AD) together with elevated serum hepcidin levels, the current study examined whether elevated serum hepcidin levels are an early event in AD pathogenesis by measuring the hormone in cognitively normal older adults at risk of AD, based on high neocortical amyloid-β load (NAL). METHODS: Serum hepcidin levels in cognitively normal participants (n = 100) aged between 65-90 years were measured using ELISA. To evaluate NAL, all participants underwent 18F-florbetaben positron emission tomography. A standard uptake value ratio (SUVR) RESULTS: Serum hepcidin was significantly higher in participants with high NAL compared to those with low NAL before and after adjusting for covariates: age, gender, and APOEɛ4 carriage (p < 0.05). A receiver operating characteristic curve based on a logistic regression of the same covariates, the base model, distinguished high from low NAL (area under the curve, AUC = 0.766), but was outperformed when serum hepcidin was added to the base model (AUC = 0.794) and further improved with plasma Aβ42/40 ratio (AUC = 0.829). CONCLUSION: The present findings indicate that serum hepcidin is increased in individuals at risk for AD and contribute to the body of evidence supporting iron dyshomeostasis as an early event of AD. Further, hepcidin may add value to a panel of markers that contribute toward identifying individuals at risk of AD; however, further validation studies are required.

Structural Brain Magnetic Resonance Imaging to Rule Out Comorbid Pathology in the Assessment of Alzheimer's Disease Dementia: Findings from the Ontario Neurodegenerative Disease Research Initiative (ONDRI) Study and Clinical Trials Over the Past 10 Years. - Kapoor, Arunima; Bartha, Robert; Black, Sandra E; Borrie, Michael; Freedman, Morris; Gao, Fuqiang; Herrmann, Nathan; Mandzia, Jennifer; Ozzoude, Miracle; Ramirez, Joel; Scott, Christopher J M; Symons, Sean; et al. (J Alzheimers Dis, 2020)
BACKGROUND/OBJECTIVE: Structural brain magnetic resonance imaging (MRI) is not mandatory in Alzheimer's disease (AD) research or clinical guidelines. We aimed to explore the use of structural brain MRI in AD/mild cognitive impairment (MCI) trials over the past 10 years and determine the frequency with which inclusion of standardized structural MRI acquisitions detects comorbid vascular and non-vascular pathologies. METHODS: We systematically searched ClinicalTrials.gov for AD clinical trials to determine their neuroimaging criteria and then used data from an AD/MCI cohort who underwent standardized MRI protocols, to determine type and incidence of clinically relevant comorbid pathologies. RESULTS: Of 210 AD clinical trials, 105 (50%) included structural brain imaging in their eligibility criteria. Only 58 (27.6%) required MRI. 16,479 of 53,755 (30.7%) AD participants were in trials requiring MRI. In the observational AD/MCI cohort, 141 patients met clinical criteria; 22 (15.6%) had relevant MRI findings, of which 15 (10.6%) were exclusionary for the study. DISCUSSION: In AD clinical trials over the last 10 years, over two-thirds of participants could have been enrolled without brain MRI and half without even a brain CT. In a study sample, relevant comorbid pathology was found in 15% of participants, despite careful screening. Standardized structural MRI should be incorporated into NIA-AA diagnostic guidelines (when available) and research frameworks routinely to reduce diagnostic heterogeneity.

Synaptic Vesicle Protein 2B Negatively Regulates the Amyloidogenic Processing of AβPP as a Novel Interaction Partner of BACE1. - Miyamoto, Masakazu; Kuzuya, Akira; Noda, Yasuha; Ueda, Sakiho; Asada-Utsugi, Megumi; Ito, Shinji; Fukusumi, Yoshiyasu; Kawachi, Hiroshi; Takahashi, Ryosuke; Kinoshita, Ayae (J Alzheimers Dis, 2020)
BACKGROUND: Given that amyloid-β (Aβ) peptide is produced and released at synapses, synaptic Aβ is one of the promising therapeutic targets to prevent synaptic dysfunction in Alzheimer's disease (AD). Although Aβ production begins with the cleavage of the amyloid-β protein precursor (AβPP) by β-site AβPP cleaving enzyme 1 (BACE1), the mechanism on how BACE1 is involved in AβPP processing at synapses remains unclear. OBJECTIVE: This study aimed to identify novel BACE1 interacting proteins regulating Aβ production at the synapse. METHODS: BACE1 interacting proteins were pulled down using a mass spectrometry-based proteomics of wild-type (WT) rat brain synaptoneurosome lysates utilizing anti-BACE1 antibody. Then, a novel BACE1 interactor was identified and characterized using experimental systems that utilized transfected cells and knockout (KO) mice. RESULTS: Synaptic vesicle protein 2B (SV2B) was identified as a novel presynaptic interaction partner of BACE1. In HEK293 cells, co-overexpression of SV2B with BACE1 significantly reduced the sAβPPβ and Aβ levels released in the media; thus, SV2B overexpression negatively affected the AβPP cleavage by BACE1. Compared with those of WT mice, the hippocampal lysates of SV2B knockout mice had significantly elevated Aβ levels, whereas the β-secretase activity and the AβPP and BACE1 protein levels remained unchanged. Finally, a fractionation assay revealed that BACE1 was mislocalized in SV2B KO mice; hence, SV2B may be involved in BACE1 trafficking downregulating the amyloidogenic pathway of AβPP. CONCLUSION: SV2B has a novel role of negatively regulating the amyloidogenic processing of AβPP at the presynapses.

Ultra-High Field MRI in Alzheimer's Disease: Effective Transverse Relaxation Rate and Quantitative Susceptibility Mapping of Human Brain In Vivo and Ex Vivo Compared to Histology. - Tuzzi, Elisa; Balla, David Z; Loureiro, Joana R A; Neumann, Manuela; Laske, Christoph; Pohmann, Rolf; Preische, Oliver; Scheffler, Klaus; Hagberg, Gisela E (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) is the most common cause of dementia worldwide. So far, diagnosis of AD is only unequivocally defined through postmortem histology. Amyloid plaques are a classical hallmark of AD and amyloid load is currently quantified by Positron Emission tomography (PET) in vivo. Ultra-high field magnetic resonance imaging (UHF-MRI) can potentially provide a non-invasive biomarker for AD by allowing imaging of pathological processes at a very-high spatial resolution. The first aim of this work was to reproduce the characteristic cortical pattern previously observed in vivo in AD patients using weighted-imaging at 7T. We extended these findings using quantitative susceptibility mapping (QSM) and quantification of the effective transverse relaxation rate (R2*) at 9.4T. The second aim was to investigate the origin of the contrast patterns observed in vivo in the cortex of AD patients at 9.4T by comparing quantitative UHF-MRI (9.4T and 14.1T) of postmortem samples with histology. We observed a distinctive cortical pattern in vivo in patients compared to healthy controls (HC), and these findings were confirmed ex vivo. Specifically, we found a close link between the signal changes detected by QSM in the AD sample at 14.1T and the distribution pattern of amyloid plaques in the histological sections of the same specimen. Our findings showed that QSM and R2* maps can distinguish AD from HC at UHF by detecting cortical alterations directly related to amyloid plaques in AD patients. Furthermore, we provided a method to quantify amyloid plaque load in AD patients at UHF non-invasively.

Validation of Plasma Proteomic Biomarkers Relating to Brain Amyloid Burden in the EMIF-Alzheimer's Disease Multimodal Biomarker Discovery Cohort. - Westwood, Sarah; Baird, Alison L; Anand, Sneha N; Nevado-Holgado, Alejo J; Kormilitzin, Andrey; Shi, Liu; Hye, Abdul; Ashton, Nicholas J; Morgan, Angharad R; Bos, Isabelle; Vos, Stephanie J B; Baker, Susan; et al. (J Alzheimers Dis, 2020)
We have previously investigated, discovered, and replicated plasma protein biomarkers for use to triage potential trials participants for PET or cerebrospinal fluid measures of Alzheimer's disease (AD) pathology. This study sought to undertake validation of these candidate plasma biomarkers in a large, multi-center sample collection. Targeted plasma analyses of 34 proteins with prior evidence for prediction of in vivo pathology were conducted in up to 1,000 samples from cognitively healthy elderly individuals, people with mild cognitive impairment, and in patients with AD-type dementia, selected from the EMIF-AD catalogue. Proteins were measured using Luminex xMAP, ELISA, and Meso Scale Discovery assays. Seven proteins replicated in their ability to predict in vivo amyloid pathology. These proteins form a biomarker panel that, along with age, could significantly discriminate between individuals with high and low amyloid pathology with an area under the curve of 0.74. The performance of this biomarker panel remained consistent when tested in apolipoprotein E ɛ4 non-carrier individuals only. This blood-based panel is biologically relevant, measurable using practical immunocapture arrays, and could significantly reduce the cost incurred to clinical trials through screen failure.

Waist Circumference and Domain-Specific Cognitive Function Among Non-Demented Japanese Older Adults Stratified by Sex: Results from the Takashima Cognition Study. - Waki, Takashi; Tanaka-Mizuno, Sachiko; Takashima, Naoyuki; Takechi, Hajime; Hayakawa, Takehito; Miura, Katsuyuki; Ueshima, Hirotsugu; Kita, Yoshikuni; Dodge, Hiroko H (J Alzheimers Dis, 2020)
BACKGROUND: While being obese in mid-life is associated with an increased risk of dementia and cognitive decline in late-life, being obese in late-life is shown to be associated with a lower risk of these outcomes in some studies. This phenomenon is known as the "obesity paradox", but the underlying reasons and potential sex difference have not been well understood. OBJECTIVE: To investigate the association between cognition and waist circumference (WC), an alternative measure of body fat which can be measured easier than body mass index (BMI), among older adults in each generation of late-life for men and women separately. METHODS: Three hundred thirty-five participants were used in the current study who were identified by random sampling of residents aged 65-74, 75-84, and 85 + years in Takashima County, Shiga Prefecture, Japan during 2005-2006. Associations between WC and domain-specific cognitive functions measured by 12 neuropsychological tests were examined using multivariable linear regression models with covariates: age, education, and hypertension. RESULTS: Larger WC was associated with better attention/working memory among 65-74-year old women and with better learning/acquisition among 65-74-year-old men, while larger WC was associated with worse learning/acquisition, memory, attention/working memory, and language/fluency among 75-84-year old men. CONCLUSION: We found age and sex differences in the association between WC and domain-specific cognitive functions. Among older old men (age 75-84) larger WC had negative effects on various domains including memory, attention, language, and executive functions, while we did not find any negative effects of larger WC on cognition among women in any age groups.

Amyloidogenic Nanoplaques in Blood Serum of Patients with Alzheimer's Disease Revealed by Time-Resolved Thioflavin T Fluorescence Intensity Fluctuation Analysis. - Tiiman, Ann; Jelic, Vesna; Jarvet, Jüri; Järemo, Petter; Bogdanovic, Nenad; Rigler, Rudolf; Terenius, Lars; Gräslund, Astrid; Vukojević, Vladana (J Alzheimers Dis, 2019)
BACKGROUND: Biomarkers are central to current research on molecular mechanisms underlying Alzheimer's disease (AD). Their further development is of paramount importance for understanding pathophysiological processes that eventually lead to disease onset. Biomarkers are also crucial for early disease detection, before clinical manifestation, and for development of new disease modifying therapies. OBJECTIVE: The overall aim of this work is to develop a minimally invasive method for fast, ultra-sensitive and cost-effective detection of structurally modified peptide/protein self-assemblies in the peripheral blood and in other biological fluids. Specifically, we focus here on using this method to detect structured amyloidogenic oligomeric aggregates in the blood serum of apparently healthy individuals and patients in early AD stage, and measure their concentration and size. METHODS: Time-resolved detection of Thioflavin T (ThT) fluorescence intensity fluctuations in a sub-femtoliter observation volume element was used to identify in blood serum ThT-active structured amyloidogenic oligomeric aggregates, hereafter called nanoplaques, and measure with single-particle sensitivity their concentration and size. RESULTS: The concentration and size of structured amyloidogenic nanoplaques are significantly higher in the blood serum of individuals diagnosed with AD than in control subjects. CONCLUSION: A new method with the ultimate, single-particle sensitivity was successfully developed. The proposed approach neither relies on the use of immune-based probes, nor on the use of radiotracers, signal-amplification or protein separation techniques, and provides a minimally invasive test for fast and cost-effective early determination of structurally modified peptides/proteins in the peripheral blood, as shown here, but also in other biological fluids.

Antiepileptic Drug Use Is Associated with an Increased Risk of Pneumonia Among Community-Dwelling Persons with Alzheimer's Disease-Matched Cohort Study. - Taipale, Heidi; Lampela, Pasi; Koponen, Marjaana; Tanskanen, Antti; Tiihonen, Jari; Hartikainen, Sirpa; Tolppanen, Anna-Maija (J Alzheimers Dis, 2019)
BACKGROUND: Antiepileptic drugs (AEDs) have sedative properties which may lead to an increased risk of pneumonia. OBJECTIVES: To investigate whether incident AED use is associated with an increased risk of pneumonia among community-dwelling persons with Alzheimer's disease (AD). In addition, we determined the risk according to duration of AED use and specific AEDs. METHODS: Persons with AD were identified from the MEDALZ dataset which includes all community-dwelling persons who received a clinically verified diagnosis of AD during 2005-2011 in Finland (N=70,718). New AED users were identified with one-year washout period. A matched cohort (1 : 1, N=5,769, matching criteria age, gender, and time since AD diagnoses) of nonusers was formed. Data from nationwide registers included dispensed medications which were modelled with PRE2DUP method, hospitalizations, and causes of death. The association between AED use and hospital admission or death due to pneumonia was analyzed with Cox proportional hazard models. RESULTS: AED use was associated with an increased risk of pneumonia (adjusted HR 1.92, 95% CI 1.63-2.26; incidence rate per 100 person-years 12.58, 95% CI 12.49-12.66 during AED use and 6.41, 95% CI 6.37-6.45 during nonuse). The highest risk was observed during the first month of use (aHR 3.59, 95% CI 2.29-5.61) and the risk remained elevated until two years of use. Of specific drug substances, phenytoin, carbamazepine, valproic acid, and pregabalin were associated with an increased risk. CONCLUSION: Antiepileptic drug use may increase the risk of pneumonia which is concerning as persons with AD have elevated risk of pneumonia.

APOE Effect on Amyloid-β PET Spatial Distribution, Deposition Rate, and Cut-Points. - Toledo, Jon B; Habes, Mohamad; Sotiras, Aristeidis; Bjerke, Maria; Fan, Yong; Weiner, Michael W; Shaw, Leslie M; Davatzikos, Christos; Trojanowski, John Q (J Alzheimers Dis, 2019)
There are conflicting results regarding how APOE genotype, the strongest genetic risk factor for Alzheimer's disease (AD), influences spatial and longitudinal amyloid-β (Aβ) deposition and its impact on the selection of biomarker cut-points. In our study, we sought to determine the impact of APOE genotype on cross-sectional and longitudinal florbetapir positron emission tomography (PET) amyloid measures and its impact in classification of patients and interpretation of clinical cohort results. We included 1,019 and 1,072 Alzheimer's Disease Neuroimaging Initiative participants with cerebrospinal fluid Aβ1 - 42 and florbetapir PET values, respectively. 623 of these subjects had a second florbetapir PET scans two years after the baseline visit. We evaluated the effect of APOE genotype on Aβ distribution pattern, pathological biomarker cut-points, cross-sectional clinical associations with Aβ load, and longitudinal Aβ deposition rate measured using florbetapir PET scans. 1) APOEɛ4 genotype influences brain amyloid deposition pattern; 2) APOEɛ4 genotype does not modify Aβ biomarker cut-points estimated using unsupervised mixture modeling methods if white matter and brainstem references are used (but not when cerebellum is used as a reference); 3) findings of large differences in Aβ biomarker value differences based on APOE genotype are due to increased probability of having AD neuropathology and are most significant in mild cognitive impairment subjects; and 4) APOE genotype and age (but not gender) were associated with increased Aβ deposition rate. APOEɛ4 carrier status affects rate and location of brain Aβ deposition but does not affect choice of biomarker cut-points if adequate references are selected for florbetapir PET processing.

Association of Cognitive Function with Amyloid-β and Tau Proteins in the Vitreous Humor. - Wright, Lauren M; Stein, Thor D; Jun, Gyungah; Chung, Jaeyoon; McConnell, Kate; Fiorello, Marissa; Siegel, Nicole; Ness, Steven; Xia, Weiming; Turner, Kelley L; Subramanian, Manju L (J Alzheimers Dis, 2019)
BACKGROUND: The eye may serve as source for diagnostic testing for early detection of Alzheimer's disease (AD). Examination of amyloid-β (Aβ) and tau protein content in human vitreous and its correlation to neuro-cognition may improve ocular-based AD detection methods. OBJECTIVE: To evaluate levels of Aβ and tau protein in human vitreous humor and investigate the clinical predictive role of these proteins as early diagnostic markers of AD. METHODS: A prospective, single-center, multi-surgeon cohort study. Vitreous humor samples from 80 eyes were measured quantitatively for Aβ40-42, pTau, and tTau. Linear regression was used to test associations between AD biomarker levels, Mini-Mental State Exam (MMSE), and serum apolipoprotein E (APOE) allele status, with adjustment for age, sex, and education level of patients. RESULTS: Lower MMSE scores were significantly associated with lower levels of vitreous Aβ40 (p = 0.015), Aβ42 (p = 0.0066), and tTau (p = 0.0085), and these biomarkers were not associated with any pre-existing eye conditions. Presence of the ɛ4 allele and the ɛ2 allele approached significance with reduced Aβ40 level (p = 0.053) and increased p-Tau level (p = 0.056), respectively. CONCLUSION: Patients with poor cognitive function have significantly lower vitreous humor levels of AD-related biomarkers Aβ40, Aβ42, and tTau. These biomarkers do not correlate with underlying eye conditions, suggesting their specificity in association with cognitive change. This is the first study to our knowledge to correlate cognition with AD-related proteins in the vitreous humor. Results suggest ocular proteins may have a role for early dementia detection in individuals at risk for AD.

Cerebral Microbleeds Are Associated with Cerebral Hypoperfusion in Patients with Alzheimer's Disease. - Hatada, Yutaka; Hashimoto, Mamoru; Shiraishi, Shinya; Ishikawa, Tomohisa; Fukuhara, Ryuji; Yuki, Seiji; Tanaka, Hibiki; Miyagawa, Yusuke; Kitajima, Mika; Uetani, Hiroyuki; Tsunoda, Naoko; Koyama, Asuka; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Although cerebral microbleeds (CMBs) are commonly observed in patients with Alzheimer's disease (AD), their clinical relevance for AD remains unclear. OBJECTIVE: We investigated the significance of CMBs in AD by examining the relationship between CMBs and cerebral blood flow (CBF) in patients with AD. METHODS: Thirty-four patients (aged 77.9±7.6 years; 17 men) with probable AD and multiple (≥8) CMBs were selected from 394 consecutive patients. For each lobe of the brain, the correlation between the number of CMBs observed on susceptibility-weighted images and the decrease in CBF observed on single-photon emission computed tomography was assessed. RESULTS: The number of microbleeds was significantly correlated with the severity of decrease in the occipital lobe (Spearman's r = 0.531, p <  0.001) and temporal lobe (r = 0.437, p <  0.001) but not in the frontal lobe (r = 0.201, p = 0.101) and parietal lobe (r = 0.178, p = 0.146). These results were unchanged in the partial correlational analysis after controlling the effect of other small vessel disease such as lacunars and white matter hyperintensities. CONCLUSION: Multiple CMBs are associated with cerebral hypoperfusion in AD. The effects of CMBs on CBF differed according to brain location, possibly reflecting different distributions of the underlying cerebral amyloid angiopathy and AD-related histopathology, such as neurofibrillary tangles.

The Clinical Phenotype of Vascular Cognitive Impairment in Patients with Type 2 Diabetes Mellitus. - Groeneveld, Onno N; Moneti, Costanza; Heinen, Rutger; de Bresser, Jeroen; Kuijf, Hugo J; Exalto, Lieza G; Boomsma, Jooske M F; Kappelle, L Jaap; Barkhof, Frederik; Prins, Niels D; Scheltens, Philip; van der Flier, Wiesje M; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Type 2 diabetes mellitus (T2DM) increases the risk of vascular cognitive impairment (VCI). It is unknown which type of vascular lesions and co-morbid etiologies, in particular Alzheimer's disease pathology, are associated with T2DM in patients with VCI, and how this relates to cognition and prognosis. OBJECTIVE: To compare brain MRI and cerebrospinal fluid (CSF) markers, cognition, and prognosis in patients with possible VCI with and without T2DM. METHODS: We included 851 memory clinic patients with vascular brain injury on MRI (i.e., possible VCI) from a prospective cohort study (T2DM: n = 147, 68.4±7.9 years, 63% men; no T2DM: n = 704, 67.6±8.5 years, 52% men). At baseline, we assessed between-group differences in brain MRI abnormalities, CSF markers of Alzheimer's disease, and cognitive profile. After two years follow-up, we compared occurrence of cognitive decline, stroke, and death. RESULTS: The distribution of clinical diagnoses did not differ between patients with and without T2DM. T2DM patients had more pronounced brain atrophy (total and white matter volume), and more lacunar infarcts, whereas microbleeds were less common (all p <  0.05). CSF amyloid-β levels were similar between the groups. T2DM patients performed worse on working memory (effect size: - 0.17, p = 0.03) than those without, whereas performance on other domains was similar. During follow-up, risk of further cognitive decline was not increased in T2DM.∥Conclusion: In patients with possible VCI, presence of T2DM is related to more pronounced brain atrophy and a higher burden of lacunar infarcts, but T2DM does not have a major impact on cognitive profile or prognosis.∥.

Clinico-Neuropathological Findings in the Oldest Old from the Georgia Centenarian Study. - Tanprasertsuk, Jirayu; Johnson, Elizabeth J; Johnson, Mary Ann; Poon, Leonard W; Nelson, Peter T; Davey, Adam; Martin, Peter; Barbey, Aron K; Barger, Kathryn; Wang, Xiang-Dong; Scott, Tammy M (J Alzheimers Dis, 2019)
BACKGROUND: Centenarian studies are important sources for understanding of factors that contribute to longevity and healthy aging. Clinico-neuropathological finding is a key in identifying pathology and factors contributing to age-related cognitive decline and dementia in the oldest old. OBJECTIVE: To characterize the cross-sectional relationship between neuropathologies and measures of premortem cognitive performance in centenarians. METHODS: Data were acquired from 49 centenarians (≥98 years) from the Georgia Centenarian Study. Cognitive assessment from the time point closest to mortality was used ( RESULTS: Wide ranges of AD-type neuropathological changes were observed in both non-demented and demented subjects. Neocortical NFT and Braak staging were related to clinical dementia rating. Neocortical NFT and NP, Braak and NIARI staging, cerebral and ventricular atrophy, HS, CAA, and TDP-43 proteinopathy were differentially associated with poor performance in multiple cognitive domains and activities of daily living. CONCLUSION: AD-type pathology was associated with severe dementia and poor cognition but was not the only variable that explained cognitive impairment, indicating the complexity and heterogeneity of pathophysiology of dementia in the oldest old.

Developing Effective Alzheimer's Disease Therapies: Clinical Experience and Future Directions. - Elmaleh, David R; Farlow, Martin R; Conti, Peter S; Tompkins, Ronald G; Kundakovic, Ljiljana; Tanzi, Rudolph E (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) clinical trials, focused on disease modifying drugs and conducted in patients with mild to moderate AD, as well as prodromal (early) AD, have failed to reach efficacy endpoints in improving cognitive function in most cases to date or have been terminated due to adverse events. Drugs that have reached clinical stage were reviewed using web resources (such as clinicaltrials.gov, alzforum.org, company press releases, and peer reviewed literature) to identify late stage (Phase II and Phase III) efficacy clinical trials and summarize reasons for their failure. For each drug, only the latest clinical trials and ongoing trials that aimed at improving cognitive function were included in the analysis. Here we highlight the potential reasons that have hindered clinical success, including clinical trial design and choice of outcome measures, heterogeneity of patient populations, difficulties in diagnosing and staging the disease, drug design, mechanism of action, and toxicity related to the long-term use. We review and suggest approaches for AD clinical trial design aimed at improving our ability to identify novel therapies for this devastating disease.

Distinctive Neurochemistry in Alzheimer's Disease via 7 T In Vivo Magnetic Resonance Spectroscopy. - Marjańska, Małgorzata; McCarten, J Riley; Hodges, James S; Hemmy, Laura S; Terpstra, Melissa (J Alzheimers Dis, 2019)
This study's objective was to increase understanding of biological mechanisms underlying clinical Alzheimer's disease (AD) by noninvasively measuring an expanded neurochemical profile and exploring how well this advanced technology distinguishes AD from cognitively normal controls. We measured concentrations of 14 neurochemicals using ultra-high field (7 T) ultra-short echo time (8 ms) magnetic resonance spectroscopy (MRS) in 16 participants with mild to moderate clinical AD and 33 age- and gender-matched control participants. MRS was localized to the posterior cingulate cortex (PCC), a region known to be impacted by AD, and the occipital cortex (OCC), a control region. Participants with AD were recruited from dementia specialty clinics. Concentration of the antioxidant ascorbate was higher (p < 0.0007) in both brain regions. Concentrations of the glial marker myo-inositol and the choline-containing compounds involved in membrane turnover were higher (p≤0.0004) in PCC of participants with AD. Ascorbate and myo-inositol concentrations were strongly associated, especially in the PCC. Random forests, using the 14 neurochemicals in the two regions, distinguished participants with AD from controls: same-sample sensitivity and specificity were 88% and 97%, respectively, though out-of-sample-values would be lower. Ultra-high field ultra-short echo time MRS identified the co-occurrence of elevated ascorbate and myo-inositol in the PCC as markers that distinguish participants with mild to moderate AD from controls. While elevated myo-inositol may be a surrogate marker of neuroinflammation, the unexpected elevation of the antioxidant ascorbate may reflect infiltration of ascorbate-rich leukocytes.

Early-Stage Alzheimer's Disease Is Associated with Simultaneous Systemic and Central Nervous System Dysregulation of Insulin-Linked Metabolic Pathways. - de la Monte, Suzanne M; Tong, Ming; Daiello, Lori A; Ott, Brian R (J Alzheimers Dis, 2019)
BACKGROUND: Brain insulin resistance is a well-recognized abnormality in Alzheimer's disease (AD) and the likely mediator of impaired glucose utilization that emerges early and progresses with disease severity. Moreover, the rates of mild cognitive impairment (MCI) or AD are significantly greater in people with diabetes mellitus or obesity. OBJECTIVE: This study was designed to determine whether systemic and central nervous system (CNS) insulin resistant disease states emerge together and thus may be integrally related. METHODS: Insulin-related molecules were measured in paired human serum and cerebrospinal fluid (CSF) samples from 19 with MCI or early AD, and 21 controls using a multiplex ELISA platform. RESULTS: In MCI/AD, both the CSF and serum samples had significantly altered mean levels of C-peptide (both elevated), Visfatin, incretins, PAI-1, ghrelin, and leptin, whereas only CSF showed a significant reduction in insulin and only serum had increased glucagon levels. Although the overall CSF and serum responses reflected insulin resistance together with insulin deficiency, the specific alterations measured in CSF and serum were different. CONCLUSION: In MCI and early-stage AD, CNS and systemic insulin-related metabolic dysfunctions, including insulin resistance, occur simultaneously, suggesting that they are integrally related and possibly mediated similar pathogenic factors.

Evaluation of Medicare Claims Data as a Tool to Identify Dementia. - Lee, Eunjung; Gatz, Margaret; Tseng, Chiuchen; Schneider, Lon S; Pawluczyk, Sonia; Wu, Anna H; Deapen, Dennis (J Alzheimers Dis, 2019)
BACKGROUND: Medicare claims record linkage has been used to identify diagnosed dementia cases in order to estimate dementia prevalence and cost of care. Claims records in the 1990 s and early 2000 s have been found to provide 85% - ∼90% sensitivity and specificity. OBJECTIVE: Considering that dementia awareness has improved over time, we sought to examine sensitivity and specificity of more recent Medicare claims records against a standard criterion, clinical diagnosis of dementia. METHODS: For a sample of patients evaluated at the University of Southern California Alzheimer Disease Research Center (ADRC), we performed database linkage with Medicare claims files for a six-year period, 2007-2012. We used clinical diagnosis at the ADRC as the criterion diagnosis in order to calculate sensitivity and specificity. RESULTS: Medicare claims correctly identified 85% of dementia patients and 77% of individuals with normal cognition. About half of patients clinically diagnosed with mild cognitive impairment had dementia diagnoses in Medicare claims. Misclassified dementia patients (i.e., missed diagnosis by Medicare claims) had more favorable Mini-Mental State Examination and Clinical Dementia Rating scores and were less likely to present behavioral symptoms than correctly-classified dementia patients. CONCLUSIONS: Database linkage to Medicare claims records is an efficient and reasonably accurate tool to identify dementia cases in a population-based cohort. However, possibilities of obtaining biased results due to misclassification of dementia status need to be carefully considered to use Medicare claims diagnosis for etiologic research studies. Additional confirmation of dementia diagnosis may also be considered. A larger study is warranted to confirm our findings.

Exercise Training in Amnestic Mild Cognitive Impairment: A One-Year Randomized Controlled Trial. - Tarumi, Takashi; Rossetti, Heidi; Thomas, Binu P; Harris, Thomas; Tseng, Benjamin Y; Turner, Marcel; Wang, Ciwen; German, Zohre; Martin-Cook, Kristin; Stowe, Ann M; Womack, Kyle B; Mathews, Dana; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The current evidence is inconclusive to support the benefits of aerobic exercise training (AET) for preventing neurocognitive decline in patients with amnestic mild cognitive impairment (aMCI). OBJECTIVE: To examine the effect of a progressive, moderate-to-high intensity AET program on memory and executive function, brain volume, and cortical amyloid-β (Aβ) plaque deposition in aMCI patients. METHODS: This is a proof-of-concept trial that randomized 70 aMCI patients to 12 months of AET or stretching and toning (SAT, active control) interventions. Primary neuropsychological outcomes were assessed by using the California Verbal Learning Test-second edition (CVLT-II) and the Delis-Kaplan Executive Function System (D-KEFS). Secondary outcomes were the global and hippocampal brain volumes and the mean cortical and precuneus Aβ deposition. RESULTS: Baseline cognitive scores were similar between the groups. Memory and executive function performance improved over time but did not differ between the AET and SAT groups. Brain volume decreased and precuneus Aβ plaque deposition increased over time but did not differ between the groups. Cardiorespiratory fitness was significantly improved in the AET compared with SAT group. In amyloid positive patients, AET was associated with reduced hippocampal atrophy when compared with the SAT group. CONCLUSION: The AET and SAT groups both showed evidence of slightly improved neuropsychological scores in previously sedentary aMCI patients. However, these interventions did not prevent brain atrophy or increases in cortical Aβ deposition over 12 months. In amyloid positive patients, AET reduced hippocampal atrophy when compared with the SAT group.

A Fragment of S38AA is a Novel Plasma Biomarker of Alzheimer's Disease. - Hashimoto, Masakazu; Yamazaki, Akira; Ohno, Atsushi; Kimura, Toru; Winblad, Bengt; Tjernberg, Lars O (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) is a progressive neurodegenerative disease without a cure. The pathological process starts decades before clinical onset, and thus clinical trials of drugs aimed at treating AD should start at a presymptomatic stage. Therefore, it is critical to diagnose AD at an early stage. Tau, phosphorylated tau, and amyloid-β peptide (Aβ) in cerebrospinal fluid (CSF), and positron emission tomography (PET) imaging of Aβ or tau accumulation are supportive biomarkers for AD diagnosis, but there is no reliable presymptomatic diagnostic marker. Since CSF sampling is invasive, and PET imaging is expensive and available only at specialized centers, a reliable blood biomarker has long been sought for. Here we describe a novel extramembrane fragment from solute carrier family 38 member 10 (SLC38A10, S38AA) that we found to be decreased in pyramidal neurons in AD cases by proteomics and immunohistochemical analysis. We detected a S38AA fragment in CSF and found the levels to correlate with severity of AD and APOE genotype. Importantly, the plasma levels of the fragment also showed a significant correlation with Mini-Mental State Examination scores in AD. Moreover, plasma from other neurodegenerative disease was analyzed and the fragment was found to be increased specifically in AD. Interestingly, the fragment is detected in mouse, rat, and monkey, and increases in amyloid precursor protein transgenic mice as the AD-like pathology progresses. We propose that the S38AA fragment in plasma could be a novel quantitative diagnostic marker for AD and potentially a marker of disease progression in AD.

Gut Microbiota Alteration and Its Time Course in a Tauopathy Mouse Model. - Sun, Bin-Lu; Li, Wei-Wei; Wang, Jun; Xu, Ya-Li; Sun, Hao-Lun; Tian, Ding-Yuan; Wang, Yan-Jiang; Yao, Xiu-Qing (J Alzheimers Dis, 2019)
Emerging evidence suggests that gut microbiota dysbiosis plays a role in neurodegenerative disorders. However, whether the composition and diversity of the gut microbiota are altered in tauopathies remains largely unknown. This study was aimed to examine the diversity and composition of the gut microbiota in tauopathies, as well as the correlation with pathological changes in the brain. We collected fecal samples from 32 P301L tau transgenic mice and 32 age- and gender-matched littermate mice at different ages. The 16S ribosomal RNA sequencing technique was used to analyze the microbiota composition in feces. Brain tau pathology levels were measured by immunohistochemistry. The diversity and composition of the gut microbiota significantly changed with aging. At the phylum level, the relative abundance of Bacteroidetes was increased, while Firmicutes were decreased in P301L mice compared with that in Wt mice after 3 months of age. In addition, Actinobacteria was decreased in P301L mice at 3 and 6 months of age, meanwhile Tenericutes was decreased in P301L mice at 10 months of age. Moreover, several specific macrobiota were highly associated with the levels of paired helical filament-tau or pT231-tau protein in the brain. Our findings suggest that gut microbiota changed with aging, as well as in the tauopathy mice model. Modulation of the gut microbiota may be a potential strategy for treatment of tauopathy.

Higher Body Mass Index Is Associated with Lower Cortical Amyloid-β Burden in Cognitively Normal Individuals in Late-Life. - Thirunavu, Vineeth; McCullough, Austin; Su, Yi; Flores, Shaney; Dincer, Aylin; Morris, John C; Cruchaga, Carlos; Benzinger, Tammie L S; Gordon, Brian A (J Alzheimers Dis, 2019)
BACKGROUND: Both low and high body mass index (BMI) have been associated with an increased risk of dementia, including that caused by Alzheimer's disease (AD). Specifically, high middle-age BMI or a low late-age BMI has been considered a predictor for the development of AD dementia. Less studied is the relationship between BMI and AD pathology. OBJECTIVE: We explored the association between BMI and cortical amyloid-β (Aβ) burden in cognitively normal participants that were either in mid-life (45-60 years) or late-life (>60). METHODS: We analyzed cross-sectional baseline data from the Knight Alzheimer Disease Research Center (ADRC) at Washington University. Aβ pathology was measured in 373 individuals with Aβ PET imaging and was quantified using Centiloid units. We split the cohort into mid- and late-life groups for analyses (n = 96 and n = 277, respectively). We ran general linear regression models to predict Aβ levels from BMI while controlling for age, sex, years of education, and APOE4 status. Analyses were also conducted to test the interaction between BMI and APOE4 genotype and between BMI and sex. RESULTS: Higher BMI was associated with lower cortical Aβ burden in late-life (β= -0.81, p = 0.0066), but no relationship was found in mid-life (β= 0.04, p > 0.5). The BMI×APOE4+ and BMI×male interaction terms were not significant in the mid-life (β= 0.28, p = 0.41; β= 0.64, p = 0.13) or the late-life (β= 0.17, p > 0.5; β= 0.50, p = 0.43) groups. CONCLUSION: Higher late-life BMI is associated with lower cortical Aβ burden in cognitively normal individuals.

Identifying Unmet Needs of Family Dementia Caregivers: Results of the Baseline Assessment of a Cluster-Randomized Controlled Intervention Trial. - Zwingmann, Ina; Michalowsky, Bernhard; Esser, Alexander; Kaczynski, Anika; Monsees, Jessica; Keller, Armin; Hertel, Johannes; Wucherer, Diana; Thyrian, Jochen René; Eichler, Tilly; Kilimann, Ingo; Teipel, Stefan; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Caregivers providing informal care for people with dementia (PwD) often report unmet needs, burden, and health impairments. Optimal support for family dementia caregivers will likely benefit from better understanding and assessment of the prevalence and types of caregivers' unmet needs and associated socio-demographic and clinical characteristics. OBJECTIVE: The present study investigates 1) the number and types of caregivers' unmet needs, 2) socio-demographic and clinical characteristics of both PwD and caregivers, and 3) caregivers' burden and health-related outcomes that are related to caregivers' unmet needs. METHODS: The present analyses are based on cross-sectional data of n = 226 dyads of caregivers and their community-dwelling PwD participating in a comprehensive standardized, computer-based caregivers' needs assessment within a general practitioner (GP)-based, cluster-randomized intervention trial. RESULTS: A total of n = 505 unmet needs were identified for n = 171 caregivers from the intervention group at baseline. Only 24.3% caregivers reported no unmet need (n = 55), whereas 75.7% caregivers had at least one unmet need (n = 171). Caregivers had on average 2.19 unmet needs (mean = 2.19, SD = 2.15). Specifically, 53.1% of caregivers had one up to three unmet needs (n = 120), 18.6% (n = 42) had three up to six unmet needs, and 4.0% (n = 9) had more than six unmet needs. DISCUSSION: Our results underline the importance of a comprehensive needs assessment for family dementia caregivers to develop and implement concepts that can provide family dementia caregivers with optimal support.

Inferring the Molecular Mechanisms of Noncoding Alzheimer's Disease-Associated Genetic Variants. - Amlie-Wolf, Alexandre; Tang, Mitchell; Way, Jessica; Dombroski, Beth; Jiang, Ming; Vrettos, Nicholas; Chou, Yi-Fan; Zhao, Yi; Kuzma, Amanda; Mlynarski, Elisabeth E; Leung, Yuk Yee; Brown, Christopher D; et al. (J Alzheimers Dis, 2019)
Most of the loci identified by genome-wide association studies (GWAS) for late-onset Alzheimer's disease (LOAD) are in strong linkage disequilibrium (LD) with nearby variants all of which could be the actual functional variants, often in non-protein-coding regions and implicating underlying gene regulatory mechanisms. We set out to characterize the causal variants, regulatory mechanisms, tissue contexts, and target genes underlying these associations. We applied our INFERNO algorithm to the top 19 non-APOE loci from the IGAP GWAS study. INFERNO annotated all LD-expanded variants at each locus with tissue-specific regulatory activity. Bayesian co-localization analysis of summary statistics and eQTL data was performed to identify tissue-specific target genes. INFERNO identified enhancer dysregulation in all 19 tag regions analyzed, significant enrichments of enhancer overlaps in the immune-related blood category, and co-localized eQTL signals overlapping enhancers from the matching tissue class in ten regions (ABCA7, BIN1, CASS4, CD2AP, CD33, CELF1, CLU, EPHA1, FERMT2, ZCWPW1). In several cases, we identified dysregulation of long noncoding RNA (lncRNA) transcripts and applied the lncRNA target identification algorithm from INFERNO to characterize their downstream biological effects. We also validated the allele-specific effects of several variants on enhancer function using luciferase expression assays. By integrating functional genomics with GWAS signals, our analysis yielded insights into the regulatory mechanisms, tissue contexts, genes, and biological processes affected by noncoding genetic variation associated with LOAD risk.

Influx of Tau and Amyloid-β Proteins into the Blood During Hemodialysis as a Therapeutic Extracorporeal Blood Amyloid-β Removal System for Alzheimer's Disease. - Kitaguchi, Nobuya; Tatebe, Harutsugu; Sakai, Kazuyoshi; Kawaguchi, Kazunori; Matsunaga, Shinji; Kitajima, Tomoko; Tomizawa, Hiroshi; Kato, Masao; Sugiyama, Satoshi; Suzuki, Nobuo; Mizuno, Masao; Takechi, Hajime; et al. (J Alzheimers Dis, 2019)
The accumulation of amyloid-β protein (Aβ) and tau in the brain is a major pathological change related to Alzheimer's disease. We have continued to develop Extracorporeal Blood Aβ Removal Systems (E-BARS) as a method for enhancing Aβ clearance from the brain. Our previous report revealed that dialyzers effectively remove blood Aβ and evoke large Aβ influxes into the blood, resulting in a decrease in brain Aβ accumulation after initiating hemodialysis, and that patients who underwent hemodialysis had lower brain Aβ accumulation than those who did not. Here, plasma total tau concentrations from 30 patients undergoing hemodialysis were measured using an ultrasensitive immunoassay and compared to those from 11 age-matched controls. Plasma total tau concentrations were higher in patients with renal failure regardless of whether they underwent hemodialysis, suggesting the involvement of the kidneys in tau degradation and excretion. Hemodialyzers effectively removed blood Aβ but not extracorporeal blood tau. The influx of tau into the blood was observed at around the 1 h period during hemodialysis sessions. However, the influx amount of tau was far smaller than that of Aβ. Furthermore, histopathological analysis revealed similar, not significantly less, cerebral cortex phosphorylated tau accumulation between the 17 patients who underwent hemodialysis and the 16 age-matched subjects who did not, although both groups showed sparse accumulation. These findings suggest that hemodialysis may induce both tau and Aβ migration into the blood. However, as a therapeutic strategy for Alzheimer's disease, it may only be effective for removing Aβ from the brain.

Midlife Insulin Resistance as a Predictor for Late-Life Cognitive Function and Cerebrovascular Lesions. - Toppala, Sini; Ekblad, Laura L; Lötjönen, Jyrki; Helin, Semi; Hurme, Saija; Johansson, Jarkko; Jula, Antti; Karrasch, Mira; Koikkalainen, Juha; Laine, Hanna; Parkkola, Riitta; Viitanen, Matti; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Type 2 diabetes (T2DM) increases the risk for Alzheimer's disease (AD) but not for AD neuropathology. The association between T2DM and AD is assumed to be mediated through vascular mechanisms. However, insulin resistance (IR), the hallmark of T2DM, has been shown to associate with AD neuropathology and cognitive decline. OBJECTIVE: To evaluate if midlife IR predicts late-life cognitive performance and cerebrovascular lesions (white matter hyperintensities and total vascular burden), and whether cerebrovascular lesions and brain amyloid load are associated with cognitive functioning. METHODS: This exposure-to-control follow-up study examined 60 volunteers without dementia (mean age 70.9 years) with neurocognitive testing, brain 3T-MRI and amyloid-PET imaging. The volunteers were recruited from the Finnish Health 2000 survey (n = 6062) to attend follow-up examinations in 2014-2016 according to their insulin sensitivity in 2000 and their APOE genotype. The exposure group (n = 30) had IR in 2000 and the 30 controls had normal insulin sensitivity. There were 15 APOEɛ4 carriers per group. Statistical analyses were performed with multivariable linear models. RESULTS: At follow-up the IR+group performed worse on executive functions (p = 0.02) and processing speed (p = 0.007) than the IR- group. The groups did not differ in cerebrovascular lesions. No associations were found between cerebrovascular lesions and neurocognitive test scores. Brain amyloid deposition associated with slower processing speed. CONCLUSION: Midlife IR predicted poorer executive functions and slower processing speed, but not cerebrovascular lesions. Brain amyloid deposition was associated with slower processing speed. The association between midlife IR and late-life cognition might not be mediated through cerebrovascular lesions measured here.

Mild Cognitive Impairment and Dementia Involving Multiple Cognitive Domains in Mexican Urbanites. - Calderón-Garcidueñas, Lilian; Mukherjee, Partha S; Kulesza, Randy J; Torres-Jardón, Ricardo; Hernández-Luna, Jacqueline; Ávila-Cervantes, Rodrigo; Macías-Escobedo, Edgar; González-González, Oscar; González-Maciel, Angelica; García-Hernández, Kevin; Hernández-Castillo, Ariatna; Villarreal-Ríos, Rodolfo (J Alzheimers Dis, 2019)
Exposures to fine particulate matter PM2.5 and ozone O3 are associated with Alzheimer's disease (AD) risk. Mexico City residents have lifetime exposures to PM2.5 and O3 above annual USEPA standards and their brains contain high redox, combustion, and friction-derived magnetite nanoparticles. AD pathological changes with subcortical pre-tangle stages in infancy and cortical tau pre-tangles, NFT Stages I-II, and amyloid phases 1-2 are identified by the 2nd decade. Given their AD continuum, a reliable identification of cognitive impairment is of utmost importance. The Montreal Cognitive Assessment (MoCA) was administered to 517 urbanites, age 21.60±5.88 years, with 13.69±1.28 formal education years, in Mexican PM2.5 polluted cities. MoCA score was 23.92±2.82, and 24.7% and 30.3% scored ≤24 and ≤22, respectively (MCI≤24, AD≤22). Cognitive deficits progressively targeted Visuospatial, Executive, Language, and Memory domains, body mass index (BMI) impacting total scores negatively (p = 0.0008), aging driving down Executive, Visuospatial, and Language index scores (p <  0.0001, 0.0037, and 0.0045), and males performing better in Executive tasks. Average age for AD MoCA scores was 22.38±7.7 years. Residency in polluted cities is associated with progression of multi-domain cognitive impairment affecting 55% of Mexican seemingly healthy youth. Normal BMI ought to be a neuroprotection goal. MoCA provides guidance for further mandatory neuropsychological testing in young populations. Identifying and lowering key neurotoxicants impacting neural risk trajectories in the developing brain and monitoring cognitive performance would greatly facilitate multidisciplinary early diagnosis and prevention of AD in high risk young populations. Cognitive deficits hinder development of those representing the force moving the country in future years.

Porphyromonas gingivalis Infection Induces Amyloid-β Accumulation in Monocytes/Macrophages. - Nie, Ran; Wu, Zhou; Ni, Junjun; Zeng, Fan; Yu, Weixian; Zhang, Yufeng; Kadowaki, Tomoko; Kashiwazaki, Haruhiko; Teeling, Jessica L; Zhou, Yanmin (J Alzheimers Dis, 2019)
Abnormal accumulation of amyloid-β (Aβ) in the brain is the most significant pathological hallmark of Alzheimer's disease (AD). We have found that chronic systemic exposure to lipopolysaccharide of Porphyromonas gingivalis (P. gingivalis) induces the accumulation of Aβ in the brain of middle-aged mice. On the other hand, recent research has shown that circulating Aβ is transferred into the brain; however, the involvement of chronic systemic P. gingivalis infection in the peripheral Aβ metabolism is unknown. We hypothesized that chronic P. gingivalis infection expands Aβ pools in peripheral inflammatory tissues and thereby contributes to the accumulation of Aβ in the brain of patients with periodontitis. We showed that the increased expression of IL-1β, AβPP770, CatB, Aβ1-42, and Aβ3-42 was mainly co-localized with macrophages in the liver of P. gingivalis infected mice. Blocking CatB and NF-κB significantly inhibited the P. gingivalis-induced expression of IL-1β, AβPP770, Aβ1-42, and Aβ3-42 in RAW264.7 cells. Aβ3-42, but not Aβ1-42, induced the significant death of macrophages, and the reduction of phagocytic abilities induced by Aβ3-42 tended to be higher than that induced by Aβ1-42. Additionally, the expression of AβPP770, CatB, Aβ1-42, and Aβ3-42 was determined in the macrophages of gingival tissues from periodontitis patients. These findings indicate that chronic systemic P. gingivalis infection induces the Aβ accumulation in inflammatory monocytes/macrophages via the activation of CatB/NF-κB signaling, thus suggesting monocytes/macrophages serve as a circulating pool of Aβ in patients with periodontitis. Taken together, CatB may be a novel therapeutic target for preventing the periodontitis-related AD initiation and pathological progression.

Present Algorithms and Future Treatments for Alzheimer's Disease. - Grossberg, George T; Tong, Gary; Burke, Anna D; Tariot, Pierre N (J Alzheimers Dis, 2019)
An estimated 47 million people live with Alzheimer's disease (AD) and other forms of dementia worldwide. Although no disease-modifying treatments are currently available for AD, earlier diagnosis and proper management of the disease could have considerable impact on patient and caregiver quality of life and functioning. Drugs currently approved for AD treat the cognitive, behavioral, and functional symptoms of the disease and consist of three cholinesterase inhibitors (ChEIs) and the N-methyl-D-aspartate receptor antagonist memantine. Treatment of patients with mild to moderate AD is generally initiated with a ChEI. Patients who show progression of symptoms while on ChEI monotherapy may be switched to another ChEI and/or memantine can be added to the treatment regimen. In recent years, putative disease-modifying therapies have emerged that aim to slow the progression of AD instead of only addressing its symptoms. However, many therapies have failed in clinical trials in patients with established AD, suggesting that, once developed, disease-modifying agents may need to be deployed earlier in the course of illness. The goal of this narrative literature review is to discuss present treatment algorithms and potential future therapies in AD.

Quantification of Tau Protein Lysine Methylation in Aging and Alzheimer's Disease. - Huseby, Carol J; Hoffman, Claire N; Cooper, Grace L; Cocuron, Jean-Christophe; Alonso, Ana P; Thomas, Stefani N; Yang, Austin J; Kuret, Jeff (J Alzheimers Dis, 2019)
Tau is a microtubule-associated protein that normally interacts in monomeric form with the neuronal cytoskeleton. In Alzheimer's disease, however, it aggregates to form the structural component of neurofibrillary lesions. The transformation is controlled in part by age- and disease-associated post-translational modifications. Recently we reported that tau isolated from cognitively normal human brain was methylated on lysine residues, and that high-stoichiometry methylation depressed tau aggregation propensity in vitro. However, whether methylation stoichiometry reached levels needed to influence aggregation propensity in human brain was unknown. Here we address this problem using liquid chromatography-tandem mass spectrometry approaches and human-derived tau samples. Results revealed that lysine methylation was present in soluble tau isolated from cognitively normal elderly cases at multiple sites that only partially overlapped with the distributions reported for cognitively normal middle aged and AD cohorts, and that the quality of methylation shifted from predominantly dimethyl-lysine to monomethyl-lysine with aging and disease. However, bulk mol methylation/mol tau stoichiometries never exceeded 1 mol methyl group/mol tau protein. We conclude that lysine methylation is a physiological post-translational modification of tau protein that changes qualitatively with aging and disease, and that pharmacological elevation of tau methylation may provide a means for protecting against pathological tau aggregation.

A Randomized, Double-Blind, Placebo-Controlled, Phase II Study Assessing Safety, Tolerability, and Efficacy of Bryostatin in the Treatment of Moderately Severe to Severe Alzheimer's Disease. - Farlow, Martin R; Thompson, Richard E; Wei, Lee-Jen; Tuchman, Alan J; Grenier, Elaine; Crockford, David; Wilke, Susanne; Benison, Jeffrey; Alkon, Daniel L (J Alzheimers Dis, 2019)
BACKGROUND: Bryostatin-activated PKC epsilon pre-clinically induces synaptogenesis, anti-apoptosis, anti-amyloid-β oligomers, and anti-hyperphosphorylated tau. OBJECTIVES: To investigate bryostatin safety, tolerability, and efficacy to improve cognition in advanced Alzheimer's disease (AD) patients. METHODS: A double-blind, randomized, placebo-controlled Phase II, 12-week trial of i.v. bryostatin for 150 advanced AD patients (55-85) with MMSE-2 of 4-15, randomized 1:1:1 into 20 μg and 40 μg bryostatin, and placebo arms. The Full Analysis Set (FAS) and the Completer Analysis Set (CAS) were pre-specified alternative assessments (1-sided, p < 0.1 for primary efficacy, and 2-sided, p < 0.05 for pre-specified and post hoc exploratory analyses). RESULTS: The safety profile was similar for 20 μg treatment and placebo patients. The 40 μg patients showed safety and drop-out issues, but no efficacy. Primary improvement of Severe Impairment Battery (SIB) scores at 13 weeks was not significant (p = 0.134) in the FAS, although in the CAS, the SIB comparison favored 20 μg bryostatin compared to placebo patients (p < 0.07). Secondary analyses at weeks 5 and 15 (i.e., 30 days post-final dosing) also favored 20 μg bryostatin compared to placebo patients. A pre-specified ANCOVA for baseline memantine blocking bryostatin and positive post-hoc trend analyses were statistically significant (2-sided, p < 0.05). CONCLUSION: Although the primary endpoint was not significant in the FAS, primary and secondary analyses in the CAS, and pre-specified and post-hoc exploratory analyses did favor bryostatin 20 μg compared to the placebo cohort. These promising Phase II results support further trials of 20 μg bryostatin- without memantine- to treat AD.

Remembering Robert D. Terry at a Time of Change in the World of Alzheimer's Disease. - Terry, Nickolas; Masliah, Alberto; Overk, Cassia; Masliah, Eliezer (J Alzheimers Dis, 2019)

Risk Factors for and Clinical Relevance of Incident and Progression of Cerebral Small Vessel Disease Markers in an Asian Memory Clinic Population. - Gyanwali, Bibek; Shaik, Muhammad Amin; Tan, Boon Yeow; Venketasubramanian, Narayanaswamy; Chen, Christopher; Hilal, Saima (J Alzheimers Dis, 2019)
BACKGROUND: Cerebral small vessel disease (SVD) is one of the major contributors to cognitive impairment and dementia. However, data on the incidence and progression of SVD in an Asian population are lacking. OBJECTIVE: The present study aims to investigate the incidence, progression, associated risk factors, and clinical relevance of SVD in a memory clinic setting. METHODS: A prospective case-control study, where 346 patients underwent repeated brain MRI with a mean interval of 24.5 months, accessing white matter hyperintensities (WMH), lacunes and cerebral microbleeds (CMBs). Severity of cognitive impairment was assessed using Clinical Dementia Rating scale and change in clinical diagnosis. Data on demographics, vascular risk factors, and clinical history were collected at baseline. RESULTS: The prevalence of significant WMH (Fazekas ≥2) was 56.6% at baseline which progressed to 59.0% at follow-up. Overall prevalence of CMBs increased from 42.2% to 47.4% (9% new cases) and lacunes increased from 31.8% to 33.2% (2.1% new cases). Hypertension was associated with WMH progression (OR: 1.78, 95% CI: 1.01, 2.99) and increasing age was associated with incident CMBs (OR: 1.04, 95% CI: 1.01, 1.08). Moreover, the use of lipid-lowering medications decreased the incidence of lacunes (OR: 0.15, 95% CI: 0.04, 0.61). The major risk factor for incident SVD was baseline SVD lesion load. WMH progression was associated with increased severity of cognitive impairment (OR: 1.95, 95% CI: 1.16, 3.23). CONCLUSION: Vascular risk factors and baseline severity of SVD lesion load were associated with progression of SVD. Furthermore, WMH progression was linked with increased severity of cognitive impairment. Future studies should be aimed to slow cognitive deterioration by preventing SVD related brain damage by targeting vascular risk factors.

Self and Informant Memory Reports in FINGER: Associations with Two-Year Cognitive Change. - Vaskivuo, Laura; Hokkanen, Laura; Hänninen, Tuomo; Antikainen, Riitta; Bäckman, Lars; Laatikainen, Tiina; Paajanen, Teemu; Stigsdotter-Neely, Anna; Strandberg, Timo; Tuomilehto, Jaakko; Soininen, Hilkka; Kivipelto, Miia; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Subjective memory complaints (SMCs) may be the first sign of cognitive decline in aging. OBJECTIVE: To examine whether SMCs reported by oneself and informant predict cognitive change over 2 years among at-risk elderly people, and to determine the relationship of different types of SMCs (prospective and retrospective memory complaints) and change in cognitive function. METHODS: This investigation is part of the FINGER project, which is a multicenter randomized controlled trial aiming at preventing cognitive decline in cognitively healthy older adults with increased risk of dementia. A subsample of 303 control-group participants (aged 60-80 years) and their informants (n = 261) rated the frequency of SMCs, using the Prospective and Retrospective Memory Questionnaire (PRMQ). Cognitive performance was measured at baseline and at 1- and 2-year follow-up visits using a neuropsychological test battery. RESULTS: Participants who reported more SMCs improved less in global cognition, executive function, and memory during the subsequent 2 years in the fully-adjusted analyses. Self-reported retrospective memory problems predicted less improvement in all cognitive domains, whereas prospective memory problems did not. Informant-reported memory problems were not linked to subsequent change in cognition. CONCLUSION: Our results indicate that self-reported SMCs, measured with PRMQ, predict future cognitive change in several cognitive domains. By contrast, reports by informants were not linked to changes in cognition. Among cognitively healthy at-risk elderly individuals, the persons themselves observe more easily problems relevant for their future cognitive trajectories than their informants.

Small Molecule Amyloid-β Protein Precursor Processing Modulators Lower Amyloid-β Peptide Levels via cKit Signaling. - Chen, Ci-Di; Zeldich, Ella; Khodr, Christina; Camara, Kaddy; Tung, Tze Yu; Lauder, Emma C; Mullen, Patrick; Polanco, Taryn J; Liu, Yen-Yu; Zeldich, Dean; Xia, Weiming; Van Nostrand, William E; et al. (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) is characterized by the accumulation of neurotoxic amyloid-β (Aβ) peptides consisting of 39-43 amino acids, proteolytically derived fragments of the amyloid-β protein precursor (AβPP), and the accumulation of the hyperphosphorylated microtubule-associated protein tau. Inhibiting Aβ production may reduce neurodegeneration and cognitive dysfunction associated with AD. We have previously used an AβPP-firefly luciferase enzyme complementation assay to conduct a high throughput screen of a compound library for inhibitors of AβPP dimerization, and identified a compound that reduces Aβ levels. In the present study, we have identified an analog, compound Y10, which also reduced Aβ. Initial kinase profiling assays identified the receptor tyrosine kinase cKit as a putative Y10 target. To elucidate the precise mechanism involved, AβPP phosphorylation was examined by IP-western blotting. We found that Y10 inhibits cKit phosphorylation and increases AβPP phosphorylation mainly on tyrosine residue Y743, according to AβPP751 numbering. A known cKit inhibitor and siRNA specific to cKit were also found to increase AβPP phosphorylation and lower Aβ levels. We also investigated a cKit downstream signaling molecule, the Shp2 phosphatase, and found that known Shp2 inhibitors and siRNA specific to Shp2 also increase AβPP phosphorylation, suggesting that the cKit signaling pathway is also involved in AβPP phosphorylation and Aβ production. We further found that inhibitors of both cKit and Shp2 enhance AβPP surface localization. Thus, regulation of AβPP phosphorylation by small molecules should be considered as a novel therapeutic intervention for AD.

Stem Cell-Derived Neurons as Cellular Models of Sporadic Alzheimer's Disease. - Foveau, Bénédicte; Correia, Ana Sofia; Hébert, Sébastien S; Rainone, Sara; Potvin, Olivier; Kergoat, Marie-Jeanne; Belleville, Sylvie; Duchesne, Simon; LeBlanc, Andréa C (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) occurs as either an autosomal dominant inherited disease or sporadically. While familial mutant genes can be expressed in cells or in animal models to assess dysregulated functions, sporadic AD cannot be replicated in models given our lack of understanding of causality. Furthermore, the study of sporadic forms of AD is difficult given the inaccessibility of brain tissues in living individuals and the manifestation of symptoms years after the onset of disease. Here, the objective was to assess if induced pluripotent stem cell-derived neurons from well-ascertained sporadic AD individuals could represent potential cellular models to determine the underlying molecular mechanisms of disease. We used cryopreserved peripheral blood mononuclear cells from three well-ascertained sporadic AD and three non-cognitively impaired (NCI) individuals of the CIMA-Q cohort to obtain iPSC-derived neurons. Microtubule associated protein 2 was decreased in AD neurons, whereas expression of AD-associated amyloid precursor protein, tau, and amyloid-β peptide was similar in AD and NCI individuals. RNA sequencing identified several upregulated and downregulated mRNAs in AD relative to NCI neurons. Of these, complement Factor H (CFH), signal regulatory protein beta1 (SIRPB1), and insulin like growth factor binding protein 5 (IGFBP5) were previously associated with AD. In addition, several transcription factors not previously associated with AD, but involved in neuronal proliferation and differentiation were differentially expressed. The results identify novel avenues for the study of the underlying causes of sporadic AD and support the establishment of additional lines to identify mechanisms of disease in sporadic AD individuals.

Treatment Combinations for Alzheimer's Disease: Current and Future Pharmacotherapy Options. - Cummings, Jeffrey L; Tong, Gary; Ballard, Clive (J Alzheimers Dis, 2019)
Although Alzheimer's disease (AD) is the world's leading cause of dementia and the population of patients with AD continues to grow, no new therapies have been approved in more than a decade. Many clinical trials of single-agent therapies have failed to affect disease progression or symptoms compared with placebo. The complex pathophysiology of AD may necessitate combination treatments rather than monotherapy. The goal of this narrative literature review is to describe types of combination therapy, review the current clinical evidence for combination therapy regimens (both symptomatic and disease-modifying) in the treatment of AD, describe innovative clinical trial study designs that may be effective in testing combination therapy, and discuss the regulatory and drug development landscape for combination therapy. Successful combination therapies in other complex disorders, such as human immunodeficiency virus, may provide useful examples of a potential path forward for AD treatment.

Two Year Outcomes, Cognitive and Behavioral Markers of Decline in Healthy, Cognitively Normal Older Persons with Global Deterioration Scale Stage 2 (Subjective Cognitive Decline with Impairment). - Reisberg, Barry; Torossian, Carol; Shulman, Melanie B; Monteiro, Isabel; Boksay, Istvan; Golomb, James; Guillo Benarous, Francoise; Ulysse, Anaztasia; Oo, Thet; Vedvyas, Alok; Rao, Julia A; Marsh, Karyn; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Little is known with respect to behavioral markers of subjective cognitive decline (SCD), a condition initially described in association with Global Deterioration Scale (GDS) stage 2. OBJECTIVE: Two-year interval behavioral markers were investigated herein. METHODS: Subjects from a published 7-year outcome study of GDS stage 2 subjects were selected. This study had demonstrated a hazard ratio of 4.5 for progression of GDS stage 2, in comparison with GDS stage 1 (no subjective or objective cognitive decline) subjects, after controlling for demographic and temporal variables. Because GDS 2 subjects have previously demonstrated impairment in comparison with healthy persons free of complaints, we herein suggest the terminology "SCD(I)" for these persons. 98 SCD(I) persons, 63 women and 35 men, mean baseline age, 67.12±8.75 years, with a mean educational background of 15.55±2.60 years, and mean baseline MMSE scores of 28.9±1.24 were followed for 2.13±0.30 years. RESULTS: Observed annual decline on the GDS was 6.701% per annum, very close to a 1986 published estimate. At follow up, the MMSE, and 7 of 8 psychometric tests did not decline significantly. Of 21 Hamilton Depression Scale items, 2 improved and the remainder were unchanged. Anxieties declined from multiple perspectives. The Brief Cognitive Rating Scale (BCRS) declined significantly (p < 0.001), with component declines in Remote memory (p < 0.01), and Functioning/self-care (p = 0.01). CONCLUSION: SCD(I) persons decline at an annual rate of approximately 6.7% /year from several recent studies. The BCRS assessments and the Digit Symbol Substitution Test can be sensitive measures for future studies of progression mitigation.

Ultrasensitive Detection of Plasma Amyloid-β as a Biomarker for Cognitively Normal Elderly Individuals at Risk of Alzheimer's Disease. - Chatterjee, Pratishtha; Elmi, Mitra; Goozee, Kathryn; Shah, Tejal; Sohrabi, Hamid R; Dias, Cintia B; Pedrini, Steve; Shen, Kaikai; Asih, Prita R; Dave, Preeti; Taddei, Kevin; Vanderstichele, Hugo; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Aberrant amyloid-β (Aβ) deposition in the brain occurs two decades prior to the manifestation of Alzheimer's disease (AD) clinical symptoms and therefore brain Aβ load measured using PET serves as a gold standard biomarker for the early diagnosis of AD. However, the uneconomical nature of PET makes blood markers, that reflect brain Aβ deposition, attractive candidates for investigation as surrogate markers. OBJECTIVE: Investigation of plasma Aβ as a surrogate marker for brain Aβ deposition in cognitively normal elderly individuals. METHODS: Plasma Aβ40 and Aβ42 concentrations were measured using the ultrasensitive Single Molecule Array (Simoa) assay in 95 cognitively normal elderly individuals, who have all undergone PET to assess brain Aβ deposition. Based on the standard uptake value ratios (SUVR) obtained from PET imaging, using the tracer 18F-Florbetaben, plasma Aβ was compared between 32 participants assessed to have low brain Aβ load (Aβ-, SUVR <1.35) and 63 assessed to have high brain Aβ load (Aβ+, SUVR ≥1.35). RESULTS: Plasma Aβ42/Aβ40 ratios were lower in the Aβ+ group compared to the Aβ-group. Plasma Aβ40 and Aβ42 levels were not significantly different between Aβ-and Aβ+ groups, although a trend of higher plasma Aβ40 was observed in the Aβ+ group. Additionally, plasma Aβ42/Aβ40 ratios along with the known AD risk factors, age and APOEɛ4 status, resulted in Aβ+ participants being distinguished from Aβ-participants based on an area under the receiver operating characteristic curve shown to be 78%. CONCLUSION: Plasma Aβ ratios in this study are a potential biomarker for brain Aβ deposition and therefore, for preclinical AD. However, this method to measure plasma Aβ needs further development to increase the accuracy of this promising AD blood biomarker.

Upregulation of Thioredoxin-Interacting Protein in Brain of Amyloid-β Protein Precursor/Presenilin 1 Transgenic Mice and Amyloid-β Treated Neuronal Cells. - Wang, Yiran; Wang, Ying; Bharti, Veni; Zhou, Hong; Hoi, Vanessa; Tan, Hua; Wu, Zijian; Nagakannan, Pandian; Eftekharpour, Eftekhar; Wang, Jun-Feng (J Alzheimers Dis, 2019)
Oxidative stress has been hypothesized to play a role in the pathophysiology of Alzheimer's disease (AD). Previously, we found that total nitrosylated protein levels were increased in the brain of amyloid-β protein precursor (AβPP) and presenilin 1 (PS1) double transgenic mice, an animal model for AD, suggesting that cysteine oxidative protein modification may contribute to this disease. Thioredoxin (Trx) is a major oxidoreductase that can reverse cysteine oxidative modifications such as sulfenylation and nitrosylation, and inhibit oxidative stress. Thioredoxin-interacting protein (Txnip) is an endogenous Trx inhibitor. To understand the involvement of Trx and Txnip in AD development, we investigated Trx and Txnip in the brain of AβPP/PS1 mice. Using immunoblotting analysis, we found that although Trx protein levels were not changed, Txnip protein levels were significantly increased in hippocampus and frontal cortex of 9- and 12-month-old AβPP/PS1 mice when compared to wild-type mice. Txnip protein levels were also increased by amyloid-β treatment in primary cultured mouse cerebral cortical neurons and HT22 mouse hippocampal cells. Using biotin switch and dimedone conjugation methods, we found that amyloid-β treatment increased protein nitrosylation and sulfenylation in HT22 cells. We also found that downregulation of Txnip, using CRISPR/Cas9 method in HT22 cells, attenuated amyloid-β-induced protein nitrosylation and sulfenylation. Our findings suggest that amyloid-β may increase Txnip levels, subsequently inhibiting Trx reducing capability and enhancing protein cysteine oxidative modification. Our findings also indicate that Txnip may be a potential target for the treatment of AD.

Vital Exhaustion and Incidence of Dementia: Results from the Copenhagen City Heart Study. - Islamoska, Sabrina; Ishtiak-Ahmed, Kazi; Hansen, Åse Marie; Grynderup, Matias Brødsgaard; Mortensen, Erik Lykke; Garde, Anne Helene; Gyntelberg, Finn; Prescott, Eva Irene Bossano; Török, Eszter; Waldemar, Gunhild; Nabe-Nielsen, Kirsten (J Alzheimers Dis, 2019)
BACKGROUND: Psychological distress is potentially linked to the risk of dementia through neurologic and cardiovascular mechanisms. Vital exhaustion (VE) is a mental state of psychological distress, which could be a risk factor for dementia. OBJECTIVE: To investigate whether VE is a risk factor for dementia in later life. METHODS: We used data from 6,807 participants attending the third survey of the Copenhagen City Heart Study in 1991-1994. VE was assessed by 17 symptoms (score: 0-17) from the Maastricht Questionnaire. Information on dementia was obtained from national registers. Risk time for dementia was counted from five years after VE assessment for participants > 55 years at the time of VE assessment. For younger participants, risk time for dementia was counted from the year they turned 60 years and onwards. Participants were followed until 2016. We used Poisson regression to calculate incidence rate ratios (IRR) and their 95% confidence intervals (CI). RESULTS: During an average follow-up of 10 years, 872 participants were registered with dementia. We found a dose-response relation between the number of VE symptoms and the incidence of dementia. For every additional VE symptom, the dementia incidence increased by 2% (IRR = 1.024; 95% CI: 1.004-1.043). Adjustment for socio-demographic and health-related factors did not change the results substantially. Neither did stratification by age, sex, educational level, and marital status. CONCLUSION: We found evidence that VE is a risk factor for dementia. Our sensitivity analyses supported that this association was not only due to VE being a potential prodromal sign of dementia.

Why Is Amyloid-β PET Requested After Performing Cerebrospinal Fluid Biomarkers? - Reimand, Juhan; Groot, Colin; Teunissen, Charlotte E; Windhorst, Albert D; Boellaard, Ronald; Barkhof, Frederik; Nazarenko, Sergei; van der Flier, Wiesje M; van Berckel, Bart N M; Scheltens, Philip; Ossenkoppele, Rik; Bouwman, Femke (J Alzheimers Dis, 2019)
BACKGROUND: Amyloid-β PET and cerebrospinal fluid (CSF) Aβ42 are considered interchangeable for clinical diagnosis of Alzheimer's disease. OBJECTIVE: To explore the clinical reasoning for requesting additional amyloid-β PET after performing CSF biomarkers. METHODS: We retrospectively identified 72 memory clinic patients who underwent amyloid-β PET after CSF biomarkers analysis for clinical diagnostic evaluation between 2011 and 2019. We performed patient chart reviews to identify factors which led to additional amyloid-β PET. Additionally, we assessed accordance with appropriate-use-criteria (AUC) for amyloid-β PET. RESULTS: Mean patient age was 62.0 (SD = 8.1) and mean Mini-Mental State Exam score was 23.6 (SD = 3.8). CSF analysis conflicting with the clinical diagnosis was the most frequent reason for requesting an amyloid-β PET scan (n = 53, 74%), followed by incongruent MRI (n = 16, 22%), unusual clinical presentation (n = 11, 15%) and young age (n = 8, 11%). An amyloid-β PET scan was rarely (n = 5, 7%) requested in patients with a CSF Aβ+/tau+ status. Fifteen (47%) patients with a post-PET diagnosis of AD had a predominantly non-amnestic presentation. In n = 11 (15%) cases, the reason that the clinician requested amyloid-β was not covered by AUC. This happened most often (n = 7) when previous CSF analysis did not support current clinical diagnosis, which led to requesting amyloid-β PET. CONCLUSION: In this single-center study, the main reason for requesting an amyloid-β PET scan after performing CSF biomarkers was the occurrence of a mismatch between the primary clinical diagnosis and CSF Aβ/tau results.

The 20-Year Voyage Aboard the Journal of Alzheimer's Disease: Docking at 'Type 3 Diabetes', Environmental/Exposure Factors, Pathogenic Mechanisms, and Potential Treatments. - de la Monte, Suzanne M; Tong, Ming; Wands, Jack R (J Alzheimers Dis, 2018)
The Journal of Alzheimer's Disease (JAD), founded in 1998, played a pivotal role in broadening the field of research on Alzheimer's disease (AD) by publishing a diverse range of clinical, pathological, molecular, biochemical, epidemiological, experimental, and review articles from its birth. This article recounts my own journey as an author who contributed articles to JAD over the 20 years of the journal's existence. In retrospect, it seems remarkable that a considerable body of work that originated from our group marks a trail that began with studies of vascular, stress, and mitochondrial factors in AD pathogenesis, exploded into the concept of 'Type 3 Diabetes', and continued with the characterization of how environmental, exposure, and lifestyle factors promote neurodegeneration and which therapeutic strategies could reverse the neurodegeneration cascade.

Aberrant Cortical Event-Related Potentials During Associative Learning in Rat Models for Presymptomatic Stages of Alzheimer's Disease. - Nouriziabari, Bardia; Sarkar, Susmita; Tanninen, Stephanie E; Dayton, Robert D; Klein, Ronald L; Takehara-Nishiuchi, Kaori (J Alzheimers Dis, 2018)
Trace eyeblink conditioning is a hippocampus-dependent associative learning paradigm which is impaired in patients with Alzheimer's disease (AD) and animal AD models. Learning in this paradigm accompanies changes in oscillatory activity in forebrain regions, some of which are loci of pathogenic changes in prodromal AD stages. These observations motivated us to examine how cortical event-related potentials (ERPs) during this paradigm are affected by two features of the asymptomatic, AD-related brain abnormality, entorhinal tau accumulation and mild cholinergic deficit. Adult rats received viral overexpression of P301L mutant human tau in the entorhinal cortex, low-dose scopolamine treatment, or both. Electroencephalograms were recorded with epidural electrodes on the surface of the frontal, parietal, and temporal cortices during differential and reversal trace eyeblink conditioning. All rats developed conditioned responses to one of two stimuli (auditory or visual) paired with mild eyelid shock (CS+), but not to the other stimulus presented alone (CS-). They were also able to adjust the response when the stimulus contingency was reversed. With learning, the amplitude of several ERP components in the frontal and temporal cortices came to differentiate the CS+ from CS-. Scopolamine affected the learning-related change in temporal P2 and other learning-unrelated components in three regions. Entorhinal tau overexpression primary affected the amplitude of temporal visual ERPs and learning-unrelated frontal and temporal auditory ERP components. The double manipulation only affected two components of temporal auditory ERPs. Thus, cortical ERPs during differential associative learning are sensitive to asymptomatic brain abnormality associated with AD.

Abnormalities of Resting State Cortical EEG Rhythms in Subjects with Mild Cognitive Impairment Due to Alzheimer's and Lewy Body Diseases. - Babiloni, Claudio; Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Catania, Valentina; Nobili, Flavio; Arnaldi, Dario; Famá, Francesco; et al. (J Alzheimers Dis, 2018)
The present study tested the hypothesis that cortical sources of resting state eyes-closed electroencephalographic (rsEEG) rhythms reveal different abnormalities in cortical neural synchronization in groups of patients with mild cognitive impairment due to Alzheimer's disease (ADMCI) and dementia with Lewy bodies (DLBMCI) as compared to cognitively normal elderly (Nold) subjects. Clinical and rsEEG data in 30 ADMCI, 23 DLBMCI, and 30 Nold subjects were available in an international archive. Age, gender, and education were carefully matched in the three groups. The Mini-Mental State Evaluation (MMSE) score was matched between the ADMCI and DLBMCI groups. Individual alpha frequency peak (IAF) was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were also considered. eLORETA estimated the rsEEG cortical sources. Receiver operating characteristic curve (ROCC) classified these sources across individuals. Compared to Nold, IAF showed marked slowing in DLBMCI and moderate in ADMCI. Furthermore, the posterior alpha 2 and alpha 3 source activities were more abnormal in the ADMCI than the DLBMCI group, while widespread delta source activities were more abnormal in the DLBMCI than the ADMCI group. The posterior delta and alpha sources correlated with the MMSE score and correctly classified the Nold and MCI individuals (area under the ROCC >0.85). In conclusion, the ADMCI and DLBMCI patients showed different features of cortical neural synchronization at delta and alpha frequencies underpinning brain arousal and vigilance in the quiet wakefulness. Future prospective cross-validation studies will have to test the clinical validity of these rsEEG markers.

The Added Value of Diffusion-Weighted MRI-Derived Structural Connectome in Evaluating Mild Cognitive Impairment: A Multi-Cohort Validation1. - Wang, Qi; Guo, Lei; Thompson, Paul M; Jack, Clifford R; Dodge, Hiroko; Zhan, Liang; Zhou, Jiayu (J Alzheimers Dis, 2018)
T1-weighted MRI has been extensively used to extract imaging biomarkers and build classification models for differentiating Alzheimer's disease (AD) patients from healthy controls, but only recently have brain connectome networks derived from diffusion-weighted MRI been used to model AD progression and various stages of disease such as mild cognitive impairment (MCI). MCI, as a possible prodromal stage of AD, has gained intense interest recently, since it may be used to assess risk factors for AD. Little work has been done to combine information from both white matter and gray matter, and it is unknown how much classification power the diffusion-weighted MRI-derived structural connectome could provide beyond information available from T1-weighted MRI. In this paper, we focused on investigating whether diffusion-weighted MRI-derived structural connectome can improve differentiating healthy controls subjects from those with MCI. Specifically, we proposed a novel feature-ranking method to build classification models using the most highly ranked feature variables to classify MCI with healthy controls. We verified our method on two independent cohorts including the second stage of Alzheimer's Disease Neuroimaging Initiative (ADNI2) database and the National Alzheimer's Coordinating Center (NACC) database. Our results indicated that 1) diffusion-weighted MRI-derived structural connectome can complement T1-weighted MRI in the classification task; 2) the feature-rank method is effective because of the identified consistent T1-weighted MRI and network feature variables on ADNI2 and NACC. Furthermore, by comparing the top-ranked feature variables from ADNI2, NACC, and combined dataset, we concluded that cross-validation using independent cohorts is necessary and highly recommended.

Age-Dependent Changes in the Sarkosyl-Insoluble Proteome of APPSWE/PS1ΔE9 Transgenic Mice Implicate Dysfunctional Mitochondria in the Pathogenesis of Alzheimer's Disease. - Thygesen, Camilla; Metaxas, Athanasios; Larsen, Martin R; Finsen, Bente (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD), the most common cause of dementia, is characterized by the intra- and extracellular aggregation and accumulation of proteins. The major molecular hallmark is the aggregation of amyloid-β (Aβ) and hyperphosphorylated tau proteins into plaques and tangles, respectively. Evidence points to the pre-fibrillary states of protein aggregates harboring the greatest neurotoxicity. OBJECTIVE: This study was designed to identify and quantify pre-fibrillary protein species enriched by their insolubility in the detergent sarkosyl in the APPSWE/PS1ΔE9 (APP/PS1) transgenic mouse model of AD. Sarkosyl insoluble fractions were isolated from the brains of APP/PS1 and littermate wild type (Wt) mice to identify pre-fibrillary protein species associated with AD. METHODS: Pre-fibrillary protein species were isolated from the brains of 3- and 24-month-old APP/PS1 and littermate Wt mice using sarkosyl extraction and subjected to quantitative proteomics analysis by the use of isobaric tags for relative and absolute quantitation (iTRAQ). RESULTS: The sarkosyl-insoluble pre-fibrillary proteome showed differential age- and genotype-induced effects. In addition to Aβ and tau, old APP/PS1 mice showed significant enrichment in proteins in the sarkosyl fraction involved in oxidative phosphorylation and mitochondrial function. CONCLUSION: The results of this study implicate dysfunctional mitochondria as playing a key role of Aβ- and potentially tau-induced pathological events in the APP/PS1 transgenic mouse model of AD.

Age-Dependent Changes to Sphingolipid Balance in the Human Hippocampus are Gender-Specific and May Sensitize to Neurodegeneration. - Couttas, Timothy A; Kain, Nupur; Tran, Collin; Chatterton, Zac; Kwok, John B; Don, Anthony S (J Alzheimers Dis, 2018)
The greatest risk factor for developing Alzheimer's disease (AD) is aging. The major genetic risk factor for AD is the ɛ4 allele of the APOE gene, encoding the brain's major lipid transport protein, apolipoprotein E (ApoE). The research community is yet to decipher why the ApoE4 variant pre-disposes to AD, and how aging causes the disease. Studies have shown deregulated levels of sphingolipids, including decreased levels of the neuroprotective signaling lipid sphingosine 1-phosphate (S1P), and increased ceramide content, in brain tissue and serum of people with pre-clinical or very early AD. In this study we investigated whether sphingolipid levels are affected as a function of age or APOE genotype, in the hippocampus of neurologically normal subjects over the age of 65. Lipids were quantified in 80 postmortem tissue samples using liquid chromatography tandem mass spectrometry (LC-MS/MS). Sphingolipid levels were not significantly affected by the presence of one ɛ4 or ɛ2 allele. However, ceramide, sphingomyelin, and sulfatide content was very significantly correlated with age in the hippocampus of males. On the other hand, S1P, normalized to its non-phosphorylated precursor sphingosine, was inversely correlated with age in females. Our results therefore establish gender-specific differences in sphingolipid metabolism in the aging human brain. Ceramide is a pro-apoptotic lipid, and heavily implicated as a driver of insulin resistance in metabolic tissues. S1P is a neuroprotective lipid that supports glutamatergic neurotransmission. Increasing ceramide and decreasing S1P levels may contribute significantly to a pro-neurodegenerative phenotype in the aging brain.

Age-Dependent Decrease of Mitochondrial Complex II Activity in a Familial Mouse Model for Alzheimer's Disease. - Emmerzaal, Tim L; Rodenburg, Richard J; Tanila, Heikki; Verweij, Vivienne; Kiliaan, Amanda J; Kozicz, Tamas (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a severe neurodegenerative disorder for which the exact etiology is largely unknown. An increasingly recognized and investigated notion is the pathogenic role of mitochondrial dysfunction in AD. We assessed mitochondrial oxidative-phosphorylation (OXPHOS) enzyme activities in the APPswe/PS1ΔE9 mouse model from 4.5 to 14 months of age. We show an age-dependent decrease in mitochondrial complex-II activity starting at 9 months in APP/PS1 mice. Other enzymes of the OXPHOS do not show any alterations. Since amyloid-β (Aβ) plaques are already present from 4 months of age, mitochondrial dysfunction likely occurs downstream of Aβ pathology in this mouse model.

Aging-Related Calcium Dysregulation in Rat Entorhinal Neurons Homologous with the Human Entorhinal Neurons in which Alzheimer's Disease Neurofibrillary Tangles First Appear. - Gant, John C; Kadish, Inga; Chen, Kuey-Chu; Thibault, Olivier; Blalock, Eric M; Porter, Nada M; Landfield, Philip W (J Alzheimers Dis, 2018)
Aging is the leading risk factor for idiopathic Alzheimer's disease (AD), indicating that normal aging processes promote AD and likely are present in the neurons in which AD pathogenesis originates. In AD, neurofibrillary tangles (NFTs) appear first in entorhinal cortex, implying that aging processes in entorhinal neurons promote NFT pathogenesis. Using electrophysiology and immunohistochemistry, we find pronounced aging-related Ca2 + dysregulation in rat entorhinal neurons homologous with the human neurons in which NFTs originate. Considering that humans recapitulate many aspects of animal brain aging, these results support the hypothesis that aging-related Ca2 + dysregulation occurs in human entorhinal neurons and promotes NFT pathogenesis.

Albuminuria and Microalbuminuria as Predictors of Cognitive Performance in a General Population: An 11-Year Follow-Up Study. - Ekblad, Laura L; Toppala, Sini; Johansson, Jouni K; Koskinen, Seppo; Sundvall, Jouko; Rinne, Juha O; Puukka, Pauli; Viitanen, Matti; Jula, Antti (J Alzheimers Dis, 2018)
Microalbuminuria, defined as urine albumin-to-creatinine ratio (UACR)>3.0 mg/mmol and ≤ 30 mg/mmol, is an early marker of endothelial damage of the renal glomeruli. Recent research suggests an association among microalbuminuria, albuminuria (UACR > 3.0 mg/mmol), and cognitive impairment. Previous studies on microalbuminuria, albuminuria, and cognition in the middle-aged have not provided repeated cognitive testing at different time-points. We hypothesized that albuminuria (micro- plus macroalbuminuria) and microalbuminuria would predict cognitive decline independently of previously reported risk factors for cognitive decline, including cardiovascular risk factors. In addition, we hypothesized that UACR levels even below the cut-off for microalbuminuria might be associated with cognitive functioning. These hypotheses were tested in the Finnish nationwide, population-based Health 2000 Survey (n = 5,921, mean age 52.6, 55.0% women), and its follow-up, Health 2011 (n = 3,687, mean age at baseline 49.3, 55.6% women). Linear regression analysis was used to determine the associations between measures of albuminuria and cognitive performance. Cognitive functions were assessed with verbal fluency, word-list learning, word-list delayed recall (at baseline and at follow-up), and with simple and visual choice reaction time tests (at baseline only). Here, we show that micro- plus macroalbuminuria associated with poorer word-list learning and a slower reaction time at baseline, with poorer word-list learning at follow-up, and with a steeper decline in word-list learning during 11 years after multivariate adjustments. Also, higher continuous UACR consistently associated with poorer verbal fluency at levels below microalbuminuria. These results suggest that UACR might have value in evaluating the risk for cognitive decline.
Keywords: Adult; Aged; Albuminuria; Cognition; Cognitive Dysfunction; Creatinine; Cross-Sectional Studies; Female; Finland; Follow-Up Studies; Humans; Kidney; Linear Models; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Risk Factors

Alterations in Acrolein Metabolism Contribute to Alzheimer's Disease. - Tsou, Han-Hsing; Hsu, Wen-Chin; Fuh, Jong-Ling; Chen, Shih-Pin; Liu, Tsung-Yun; Wang, Hsiang-Tsui (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a detrimental neurodegenerative disease, and early diagnosis appears to be the key to successful treatment. Acrolein, a byproduct of lipid peroxidation, has been shown to contribute to the pathological process of AD. This study recruited 118 elderly subjects consisting of 58 non-demented control subjects and 62 AD patients. We analyzed the acrolein-related metabolites in the plasma, cerebrospinal fluid (CSF), and urine of all subjects. We found that the levels of acrolein-conjugated protein (Acr-PC) in the plasma (p = 0.00012) and CSF (p = 0.00161) of AD patients were significantly higher than those of control subjects, whereas the levels of a urinary acrolein metabolite, 3-hydroxypropyl mercapturic acid (3-HPMA), were markedly decreased (p = 0.00882) in AD patients. These data suggest that deregulated acrolein metabolism may be correlated with neuronal damage in AD patients, which might provide further insights into the disease progression and early diagnosis of AD.
Keywords: Acetylcysteine; Acrolein; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Creatinine; Disease Progression; Early Diagnosis; Female; Humans; Male; Middle Aged

Alzheimer-Like Pattern of Hypometabolism Emerges with Elevated Amyloid-β Burden in Down Syndrome. - Lao, Patrick J; Handen, Ben L; Betthauser, Tobey J; Mihaila, Iulia; Hartley, Sigan L; Cohen, Annie D; Tudorascu, Dana L; Bulova, Peter D; Lopresti, Brian J; Tumuluru, Rameshwari V; Murali, Dhanabalan; Mathis, Chester A; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The Down syndrome (DS) population is genetically predisposed to amyloid-β protein precursor overproduction and Alzheimer's disease (AD). OBJECTIVE: The temporal ordering and spatial association between amyloid-β, glucose metabolism, and gray matter (GM) volume in the DS population can provide insight into those associations in the more common sporadic AD. METHODS: Twenty-four adults (13 male, 11 female; 39±7 years) with DS underwent [11C]PiB, [18F]FDG, and volumetric MRI scans. Voxel-wise associations between PiB SUVR, FDG SUVR, and GM volume were investigated, with and without individual adjustments for variables of interest. RESULTS: Positive associations of PiB and age were widespread throughout the neocortex and striatum. Negative associations of FDG and age (frontal, parietal, and temporal cortex) and of GM volume and age (frontal and insular cortex) were observed. PiB and FDG were negatively associated in parietal cortex, after adjustment for GM volume. CONCLUSIONS: In adults with DS, early amyloid-β accumulation in the striatum is divergent from sporadic AD; however, despite the early striatal amyloid-β, glucose hypometabolism was confined to the typical AD-associated regions, which occurs similarly in autosomal dominant AD. Importantly, the glucose hypometabolism was not explained solely by increased partial volume effect due to GM volume reductions.
Keywords: Adult; Alzheimer Disease; Amyloid beta-Peptides; Down Syndrome; Female; Fluorodeoxyglucose F18; Gray Matter; Humans; Linear Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; United States

Alzheimer's Disease: A Journey from Amyloid Peptides and Oxidative Stress, to Biomarker Technologies and Disease Prevention Strategies-Gains from AIBL and DIAN Cohort Studies. - Martins, Ralph N; Villemagne, Victor; Sohrabi, Hamid R; Chatterjee, Pratishtha; Shah, Tejal M; Verdile, Giuseppe; Fraser, Paul; Taddei, Kevin; Gupta, Veer B; Rainey-Smith, Stephanie R; Hone, Eugene; Pedrini, Steve; et al. (J Alzheimers Dis, 2018)
Worldwide there are over 46 million people living with dementia, and this number is expected to double every 20 years reaching about 131 million by 2050. The cost to the community and government health systems, as well as the stress on families and carers is incalculable. Over three decades of research into this disease have been undertaken by several research groups in Australia, including work by our original research group in Western Australia which was involved in the discovery and sequencing of the amyloid-β peptide (also known as Aβ or A4 peptide) extracted from cerebral amyloid plaques. This review discusses the journey from the discovery of the Aβ peptide in Alzheimer's disease (AD) brain to the establishment of pre-clinical AD using PET amyloid tracers, a method now serving as the gold standard for developing peripheral diagnostic approaches in the blood and the eye. The latter developments for early diagnosis have been largely achieved through the establishment of the Australian Imaging Biomarker and Lifestyle research group that has followed 1,100 Australians for 11 years. AIBL has also been instrumental in providing insight into the role of the major genetic risk factor apolipoprotein E ɛ4, as well as better understanding the role of lifestyle factors particularly diet, physical activity and sleep to cognitive decline and the accumulation of cerebral Aβ.

Alzheimer's Disease in Systemic Sclerosis Patients: A Nationwide Population-Based Cohort Study. - Watad, Abdulla; Bragazzi, Nicola L; Tiosano, Shmuel; Yavne, Yarden; Comaneshter, Doron; Cohen, Arnon D; Amital, Howard (J Alzheimers Dis, 2018)
BACKGROUND: Neurological features are often overlooked in systemic sclerosis (SSc) patients and little is known about the link between dementia and SSc. OBJECTIVES: We sought to investigate whether an association exists between Alzheimer's disease (AD) and SSc, as well as assess the impact of a dual diagnosis on mortality rates, by performing an extensive data analysis on a large subject sample. METHODS: We utilized the medical database of the Clalit-Health-Services in a case-control study. Patients with SSc were compared with age- and sex-matched controls with regard to the prevalence of AD and its impact on their mortality. RESULTS: Our study included 2,431 SSc patients and 12,377 age- and sex-matched controls. The mean age of the study population was 63.32±18.06 years and the female to male ratio was 4.5:1. 134 (5.5%) cases had AD as a co-morbidity in comparison with 749 (5.9%) of the controls. The mortality rate was 12.5% among controls and 26.2% among SSc cases. On the Cox multivariate survival analysis, diagnosis of SSc and AD demonstrated significant HRs (2.35 (95% CI 2.05-2.69, p < 0.0001) and 2.19 (95% CI 1.94-2.48, p < 0.0001), respectively). SSc patients with AD had a relative risk of death of 2.35 (95% CI: 1.44-3.83) in comparison with SSc patients without AD. CONCLUSION: AD is a predictor of death in SSc and therefore preemptive screening may be warranted. Further studies are needed to evaluate whether improvements in the medical regimen for SSc may lead to a reduction in AD development and possibly to increased survival as well.

Alzheimer's Disease rs11767557 Variant Regulates EPHA1 Gene Expression Specifically in Human Whole Blood. - Liu, Guiyou; Zhang, Yan; Wang, Longcai; Xu, Jianyong; Chen, Xiaoyun; Bao, Yunjuan; Hu, Yang; Jin, Shuilin; Tian, Rui; Bai, Weiyang; Zhou, Wenyang; Wang, Tao; et al. (J Alzheimers Dis, 2018)
Large-scale genome-wide association studies have reported EPHA1 rs11767557 variant to be associated with Alzheimer's disease (AD) risk in the European population. However, it is still unclear how this variant functionally contributes to the underlying disease pathogenesis. The rs11767557 variant is located approximately 3 kb upstream of EPHA1 gene. We think that rs11767557 may modify the expression of nearby genes such as EPHA1 and further cause AD risk. Until now, the potential association between rs11767557 and the expression of nearby genes has not been reported in previous studies. Here, we evaluate the potential expression association between rs11767557 and EPHA1 using multiple large-scale eQTLs datasets in human brain tissues and the whole blood. The results show that rs11767557 variant could significantly regulate EPHA1 gene expression specifically in human whole blood. These findings may further provide important supplementary information about the regulating mechanisms of rs11767557 variant in AD risk.
Keywords: Alzheimer Disease; Case-Control Studies; China; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Receptor, EphA1; Risk Assessment

Anticholinergic Burden and Risk of Stroke and Death in People with Different Types of Dementia. - Tan, Edwin C K; Eriksdotter, Maria; Garcia-Ptacek, Sara; Fastbom, Johan; Johnell, Kristina (J Alzheimers Dis, 2018)
BACKGROUND: Anticholinergic burden is associated with poorer cognitive and functional outcomes in people with dementia. However, the impact of anticholinergics on significant adverse outcomes such as stroke has not been studied previously. OBJECTIVE: To investigate the association between total anticholinergic cognitive burden (ACB) and risk of stroke and death in people with different dementia subtypes. METHODS: This was a cohort study of 39,107 people with dementia and no prior history of stroke registered in the Swedish Dementia Registry (SveDem) from 2008-2014. Data were extracted from the Swedish Prescribed Drug Register, the Swedish National Patient Register, and the Swedish Total Population Register. Competing risk regression models were used to compute hazard ratios (HRs) and 95% confidence intervals (CIs) for the association between time-varying ACB score and risk of stroke and all-cause mortality. RESULTS: During a mean follow-up period of 2.31 (standard deviation 1.66) years, 11,224 (28.7%) individuals had a stroke or died. Compared with non-users of anticholinergic medications, ACB score of 1 (HR 1.09, 95% CI 1.04-1.14) and ACB score of ≥2 (HR 1.20, 95% CI 1.14-1.26) increased the risk of developing the composite outcome of stroke and death. When stratifying by dementia disorder, the association remained significant in Alzheimer's disease, mixed dementia, and vascular dementia. CONCLUSIONS: The use of anticholinergic medicines may be associated with an increased risk of stroke and death in people with dementia. A dose-response relationship was observed. Careful consideration should be made when prescribing medications with anticholinergic properties to people with dementia.

Anti-Tau Monoclonal Antibodies Derived from Soluble and Filamentous Tau Show Diverse Functional Properties in vitro and in vivo. - Vandermeeren, Marc; Borgers, Marianne; Van Kolen, Kristof; Theunis, Clara; Vasconcelos, Bruno; Bottelbergs, Astrid; Wintmolders, Cindy; Daneels, Guy; Willems, Roland; Dockx, Koen; Delbroek, Lore; Marreiro, André; et al. (J Alzheimers Dis, 2018)
The tau spreading hypothesis provides rationale for passive immunization with an anti-tau monoclonal antibody to block seeding by extracellular tau aggregates as a disease-modifying strategy for the treatment of Alzheimer's disease (AD) and potentially other tauopathies. As the biochemical and biophysical properties of the tau species responsible for the spatio-temporal sequences of seeding events are poorly defined, it is not yet clear which epitope is preferred for obtaining optimal therapeutic efficacy. Our internal tau antibody collection has been generated by immunizations with different tau species: aggregated- and non-aggregated tau and human postmortem AD brain-derived tau fibrils. In this communication, we describe and characterize a set of these anti-tau antibodies for their biochemical and biophysical properties, including binding, tissue staining by immunohistochemistry, and epitope. The antibodies bound to different domains of the tau protein and some were demonstrated to be isoform-selective (PT18 and hTau56) or phospho-selective (PT84). Evaluation of the antibodies in cellular- and in vivo seeding assays revealed clear differences in maximal efficacy. Limited proteolysis experiments support the hypothesis that some epitopes are more exposed than others in the tau seeds. Moreover, antibody efficacy seems to depend on the structural properties of fibrils purified from tau Tg mice- and postmortem human AD brain.

The Association Between Frontotemporal Lobar Degeneration and Bullous Pemphigoid. - Katisko, Kasper; Kokkonen, Nina; Krüger, Johanna; Hartikainen, Päivi; Koivisto, Anne M; Helisalmi, Seppo; Korhonen, Ville E; Kokki, Merja; Tuusa, Jussi; Herukka, Sanna-Kaisa; Solje, Eino; Haapasalo, Annakaisa; et al. (J Alzheimers Dis, 2018)
Recent studies have shown an epidemiological and immunological association between bullous pemphigoid (BP) and several neurological or psychiatric diseases. Here, our aim was for the first time to specify whether an association exists between BP and frontotemporal lobar degeneration (FTLD). Medical histories of FTLD patients (N = 196) were screened for clinical comorbidity, and BP180 and BP230 autoantibodies were analyzed in the sera of FTLD patients (N = 70, including 24 C9orf72 repeat expansion carriers) by BP180-NC16A-ELISA and BP230-ELISA. One FTLD patient (C9orf72 repeat expansion carrier) had a comorbid diagnosis of BP. Increased levels of serum BP180 autoantibodies (cutoff value >9 U/ml) were detected more often in FTLD patients (10.0%) than in controls (4.9%). Moreover, elevated levels of both BP180 and BP230 autoantibodies were found more often in C9orf72 repeat expansion-carrying FTLD than non-carrying patients or controls. However, none of these differences reached a statistical significance likely due to our limited cohort size. In conclusion, our findings suggest that subset of FTLD patients especially with the C9orf72 repeat expansion may have an immunological association with BP.

Association between Plasma Levels of PAI-1, tPA/PAI-1 Molar Ratio, and Mild Cognitive Impairment in Chinese Patients with Type 2 Diabetes Mellitus. - Wang, Jiaqi; Yuan, Yang; Cai, Rongrong; Huang, Rong; Tian, Sai; Lin, Hongyan; Guo, Dan; Wang, Shaohua (J Alzheimers Dis, 2018)
BACKGROUND: Plasminogen activator inhibitor 1 (PAI-1) and tissue plasminogen activator (tPA) are involved in the complications of type 2 diabetes mellitus (T2DM) and early pathology of Alzheimer's disease. OBJECTIVE: This study aimed to investigate the association between plasma PAI-1, tPA/PAI-1 molar ratio, and mild cognitive impairment (MCI) in Chinese T2DM patients. METHODS: A total of 162 Chinese T2DM patients were recruited and divided into two groups according to the Montreal Cognitive Assessment score. Demographic data were collected, plasma PAI-1 and tPA levels were measured through enzyme-linked immunosorbent assay, tPA/PAI-1 molar ratio was calculated, and neuropsychological test results were examined. The association between PAI-1, tPA/PAI-1 molar ratio, and cognition was analyzed. RESULTS: There were 66 diabetic MCI patients and 96 healthy cognition participants (controls). T2DM patients with MCI displayed significantly increased plasma PAI-1 levels (p = 0.016) and decreased tPA/PAI-1 molar ratio (p = 0.021) compared with the controls. High PAI-1 levels and low tPA/PAI-1 molar ratio were associated with MCI in T2DM patients, e.g., plasma level of PAI-1 were negatively correlated (r = -0.343, p = 0.007) with logic memory in T2DM patients with MCI. Linear regression analysis further revealed that PAI-1 concentration was an independent factor of diabetic MCI (p = 0.001). CONCLUSIONS: High PAI-1 levels and low tPA/PAI-1 molar ratio were significantly correlated with T2DM-associated cognitive impairment, especially memory function, in Chinese patients.

Association between α-Klotho and Deep White Matter Lesions in the Brain: A Pilot Case Control Study Using Brain MRI. - Kuriyama, Nagato; Ozaki, Etsuko; Mizuno, Toshiki; Ihara, Masafumi; Mizuno, Shigeto; Koyama, Teruhide; Matsui, Daisuke; Watanabe, Isao; Akazawa, Kentaro; Takeda, Kazuo; Takada, Akihiro; Inaba, Masaaki; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The anti-aging protein, α-Klotho, may be involved in cognitive decline and has potential as a surrogate marker that reflects dementia. However, the role of α-Klotho in the brain has not been sufficiently investigated. OBJECTIVE: Here, we investigated the association between α-Klotho and cognitive decline that is associated with cerebral deep white matter lesions (DWMLs). METHODS: Two hundred-eighty participants (187 males and 93 females, mean age: 70.8 years old) were evaluated for DWMLs, and the Fazekas scale (Grade) was assessed following brain magnetic resonance imaging. A questionnaire concerning lifestyle and neuropsychological tests was administered, and their associations with the blood α-Klotho level were retrospectively investigated. RESULTS: The α-Klotho level was 685.1 pg/mL in Grade 0 (68 subjects), 634.1 in G1 (134), 596.0 in G2 (62), and 571.6 in G3 (16), showing that the level significantly decreased with advanced grades. Significant correlations were noted between the α-Klotho level and higher brain function tests including the Mini-Mental State Examination and word fluency tests (p < 0.05). When a 90th percentile value of the level in the G0 group (400 pg/mL) or lower was defined as a low α-Klotho level, the odds ratio of the high-grade G3 group was 2.9 (95% confidence interval: 1.4-7.8) (after correction for age, sex, hypertension, and chronic kidney disease), which was significant. CONCLUSION: A reduced blood α-Klotho level was correlated with grading of cerebral DWMLs and was accompanied by cognitive decline as an independent risk factor. The α-Klotho level may serve as a useful clinical index of vascular cognitive impairment.
Keywords: Aged; Aged, 80 and over; Apolipoprotein E4; Brain; C-Reactive Protein; Case-Control Studies; Cognition Disorders; Female; Glucuronidase; Humans; Image Processing, Computer-Assisted; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Pilot Projects; Severity of Illness Index

Association of Cerebrospinal Fluid (CSF) Insulin with Cognitive Performance and CSF Biomarkers of Alzheimer's Disease. - Geijselaers, Stefan L C; Aalten, Pauline; Ramakers, Inez H G B; De Deyn, Peter Paul; Heijboer, Annemieke C; Koek, Huiberdina L; OldeRikkert, Marcel G M; Papma, Janne M; Reesink, Fransje E; Smits, Lieke L; Stehouwer, Coen D A; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Abnormal insulin signaling in the brain has been linked to Alzheimer's disease (AD). OBJECTIVE: To evaluate whether cerebrospinal fluid (CSF) insulin levels are associated with cognitive performance and CSF amyloid-β and Tau. Additionally, we explore whether any such association differs by sex or APOE ɛ4 genotype. METHODS: From 258 individuals participating in the Parelsnoer Institute Neurodegenerative Diseases, a nationwide multicenter memory clinic population, we selected 138 individuals (mean age 66±9 years, 65.2% male) diagnosed with subjective cognitive impairment (n = 45), amnestic mild cognitive impairment (n = 44), or AD (n = 49), who completed a neuropsychological assessment, including tests of global cognition and memory performance, and who underwent lumbar puncture. We measured CSF levels of insulin, amyloid-β1-42, total (t-)Tau, and phosphorylated (p-)Tau. RESULTS: CSF insulin levels did not differ between the diagnostic groups (p = 0.136). Across the whole study population, CSF insulin was unrelated to cognitive performance and CSF biomarkers of AD, after adjustment for age, sex, body mass index, diabetes status, and clinic site (all p≥0.131). Importantly, however, we observed effect modification by sex and APOE ɛ4 genotype. Specifically, among women, higher insulin levels in the CSF were associated with worse global cognition (standardized regression coefficient -0.483; p = 0.008) and higher p-Tau levels (0.353; p = 0.040). Among non-carriers of the APOE ɛ4 allele, higher CSF insulin was associated with higher t-Tau (0.287; p = 0.008) and p-Tau (0.246; p = 0.029). CONCLUSION: Our findings provide further evidence for a relationship between brain insulin signaling and AD pathology. It also highlights the need to consider sex and APOE ɛ4 genotype when assessing the role of insulin.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Cognition Disorders; Female; Humans; Insulin; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Signal Transduction; tau Proteins

Association of Plasma Neurofilament Light Chain with Neocortical Amyloid-β Load and Cognitive Performance in Cognitively Normal Elderly Participants. - Chatterjee, Pratishtha; Goozee, Kathryn; Sohrabi, Hamid R; Shen, Kaikai; Shah, Tejal; Asih, Prita R; Dave, Preeti; ManYan, Candice; Taddei, Kevin; Chung, Roger; Zetterberg, Henrik; Blennow, Kaj; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The disruption of neurofilament, an axonal cytoskeletal protein, in neurodegenerative conditions may result in neuronal damage and its release into the cerebrospinal fluid and blood. In Alzheimer's disease (AD), neurofilament light chain (NFL), a neurofilament subunit, is elevated in the cerebrospinal fluid and blood. OBJECTIVE: Investigate the association of plasma NFL with preclinical-AD features, such as high neocortical amyloid-β load (NAL) and subjective memory complaints, and cognitive performance in cognitively normal older adults. METHODS: Plasma NFL concentrations were measured employing the single molecule array platform in participants from the Kerr Anglican Retirement Village Initiative in Ageing Health cohort, aged 65- 90 years. Participants underwent a battery of neuropsychological testing to evaluate cognitive performance and were categorized as low NAL (NAL-, n = 65) and high NAL (NAL+, n = 35) assessed via PET, and further stratified into subjective memory complainers (SMC; nNAL- = 51, nNAL+ = 25) and non-SMC (nNAL- = 14, nNAL+ = 10) based on the Memory Assessment Clinic- Questionnaire. RESULTS: Plasma NFL inversely correlated with cognitive performance. No significant difference in NFL was observed between NAL+ and NAL- participants; however, within APOEɛ4 non-carriers, higher NAL was observed in individuals with NFL concentrations within quartiles 3 and 4 (versus quartile 1). Additionally, within the NAL+ participants, SMC had a trend of higher NFL compared to non-SMC. CONCLUSION: Plasma NFL is inversely associated with cognitive performance in elderly individuals. While plasma NFL may not reflect NAL in individuals with normal global cognition, the current observations indicate that onset of axonal injury, reflected by increased plasma NFL, within the preclinical phase of AD may contribute to the pathogenesis of AD.

Association of the New Variant Tyr424Asp at TBK1 Gene with Amyotrophic Lateral Sclerosis and Cognitive Decline. - Piaceri, Irene; Bessi, Valentina; Matà, Sabrina; Polito, Cristina; Tedde, Andrea; Berti, Valentina; Bagnoli, Silvia; Braccia, Arianna; Del Mastio, Monica; Pignone, Alberto Moggi; Pupi, Alberto; Sorbi, Sandro; et al. (J Alzheimers Dis, 2018)
A new risk gene associated with amyotrophic lateral sclerosis (ALS) has recently been identified: the Tank-binding kinase 1 (TBK1) gene. Up to now, 90 TBK1 variants have been described in ALS patients with or without frontotemporal dementia (FTD), thus making TBK1 the third or fourth most frequent genetic cause of ALS and FTD. A point mutation analysis in a cohort of 69 Italian ALS patients was performed in order to analyze the frequency of TBK1 mutations and the correlation with clinical phenotypes. The analysis identified the novel variant p.Tyr424Asp in a patient with a rapid progression of the disease. Our data supports the implication of TBK1 in ALS pathogenesis in Italy.
Keywords: Aged; Amyotrophic Lateral Sclerosis; Aspartic Acid; C9orf72 Protein; Cognitive Dysfunction; DNA Mutational Analysis; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Italy; Male; Mental Status and Dementia Tests; Middle Aged; Mutation; Neuropsychological Tests; Positron-Emission Tomography; Protein-Serine-Threonine Kinases; Tyrosine

Associations of Dietary Protein and Fiber Intake with Brain and Blood Amyloid-β. - Fernando, W M A D Binosha; Rainey-Smith, Stephanie R; Gardener, Samantha L; Villemagne, Victor L; Burnham, Samantha C; Macaulay, S Lance; Brown, Belinda M; Gupta, Veer Bala; Sohrabi, Hamid R; Weinborn, Michael; Taddei, Kevin; Laws, Simon M; et al. (J Alzheimers Dis, 2018)
Accumulating evidence suggests a diet high in protein and fiber may confer some protection against Alzheimer's disease (AD). However, no human studies to-date have assessed the relationship between protein and fiber intake, and plasma and brain amyloid-β (Aβ). Consequently, this cross-sectional study, investigated the association of self-reported dietary intakes of protein and fiber, with plasma and brain Aβ burden (n = 541, and n = 162 respectively), in a well-characterized cohort of cognitively normal older adults, drawn from the larger Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging. We observed 12.59 and 8.43 higher odds of 'high' brain Aβ burden (PiB PET SUVR≥1.5) if protein intake fell in the lowest and middle tertile, respectively, compared to the highest tertile (p = 0.008; p = 0.013). Thus, in this cohort, the more protein consumed, the less likelihood of 'high' Aβ burden in the brain. No other significant associations were observed. The results of this study highlight the potentially protective impact of high dietary protein intake on brain Aβ burden in older adults, before objective memory decline is apparent. While longitudinal validation is required, these findings may assist in the development of dietary approaches aimed at preventing or delaying AD onset.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Australia; Biomarkers; Brain; Cognition; Cohort Studies; Cross-Sectional Studies; Dietary Fiber; Dietary Proteins; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

Aβ42/Aβ40 and Aβ42/Aβ38 Ratios Are Associated with Measures of Gait Variability and Activities of Daily Living in Mild Alzheimer's Disease: A Pilot Study. - Koychev, Ivan; Galna, Brook; Zetterberg, Henrik; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil H; Rowe, James B; Thomas, Alan; Howard, Robert; Malhotra, Paresh; Ritchie, Craig; Lovestone, Simon; et al. (J Alzheimers Dis, 2018)
Gait disturbances are some of the earliest changes in dementia and their monitoring presents an opportunity for early diagnosis. The exact relationship between gait and well-established biomarkers of Alzheimer's disease (AD) remains to be clarified. In this study we compared gait-related measures with cerebrospinal fluid (CSF) markers of AD pathology. We recruited seventeen participants with mild AD in a multi-site study and performed gait assessment as well as lumbar punctures to obtain CSF. CSF Aβ42/Aβ40 and Aβ42/Aβ38 correlated positively with measures of variability (step time and step length) in the clinic-based assessments. This was driven by a negative relationship between gait variability and Aβ40 and Aβ38 but not Aβ42.The amyloid ratios and gait variability measures were also associated with more severe functional impairment. We interpret these data as an indication that increasing amyloid production (i.e., increasing Aβ40 and Aβ38) is associated with diminishing cognitive-motor control of gait. These preliminary results suggest that the two amyloid ratios may be a marker of the earliest disturbances in the interplay between cognitive and motor control which characterize dementia.

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome (BPSD-DS) Scale: Comprehensive Assessment of Psychopathology in Down Syndrome. - Dekker, Alain D; Sacco, Silvia; Carfi, Angelo; Benejam, Bessy; Vermeiren, Yannick; Beugelsdijk, Gonny; Schippers, Mieke; Hassefras, Lyanne; Eleveld, José; Grefelman, Sharina; Fopma, Roelie; Bomer-Veenboer, Monique; et al. (J Alzheimers Dis, 2018)
People with Down syndrome (DS) are prone to develop Alzheimer's disease (AD). Behavioral and psychological symptoms of dementia (BPSD) are core features, but have not been comprehensively evaluated in DS. In a European multidisciplinary study, the novel Behavioral and Psychological Symptoms of Dementia in Down Syndrome (BPSD-DS) scale was developed to identify frequency and severity of behavioral changes taking account of life-long characteristic behavior. 83 behavioral items in 12 clinically defined sections were evaluated. The central aim was to identify items that change in relation to the dementia status, and thus may differentiate between diagnostic groups. Structured interviews were conducted with informants of persons with DS without dementia (DS, n = 149), with questionable dementia (DS+Q, n = 65), and with diagnosed dementia (DS+AD, n = 67). First exploratory data suggest promising interrater, test-retest, and internal consistency reliability measures. Concerning item relevance, group comparisons revealed pronounced increases in frequency and severity in items of anxiety, sleep disturbances, agitation & stereotypical behavior, aggression, apathy, depressive symptoms, and eating/drinking behavior. The proportion of individuals presenting an increase was highest in DS+AD, intermediate in DS+Q, and lowest in DS. Interestingly, among DS+Q individuals, a substantial proportion already presented increased anxiety, sleep disturbances, apathy, and depressive symptoms, suggesting that these changes occur early in the course of AD. Future efforts should optimize the scale based on current results and clinical experiences, and further study applicability, reliability, and validity. Future application of the scale in daily care may aid caregivers to understand changes, and contribute to timely interventions and adaptation of caregiving.

Beneficial Effects of Sideritis scardica and Cichorium spinosum against Amyloidogenic Pathway and Tau Misprocessing in Alzheimer's Disease Neuronal Cell Culture Models. - Chalatsa, Ioanna; Arvanitis, Demetrios A; Mikropoulou, Eleni V; Giagini, Athina; Papadopoulou-Daifoti, Zeta; Aligiannis, Nektarios; Halabalaki, Maria; Tsarbopoulos, Anthony; Skaltsounis, Leandros A; Sanoudou, Despina (J Alzheimers Dis, 2018)
BACKGROUND: Natural products are a significantly underutilized source of potential treatments against human disease. Alzheimer's disease (AD) is a prime example of conditions that could be amenable to such treatments as suggested by recent findings. OBJECTIVE: Aiming to identify novel potentially therapeutic approaches against AD, we assessed the effects of Cichorium spinosum and Sideritis scardica extracts, both distinct components of the Mediterranean diet. METHODS/RESULTS: After the detailed characterization of the extracts' composition using LC-HRMS methods, they were evaluated on two AD neuronal cell culture models, namely the AβPP overexpressing SH-SY5Y-AβPP and the hyperphosphorylated tau expressing PC12-htau. Initially their effect on cell viability of SH-SY5Y and PC12 cells was examined, and subsequently their downstream effects on AβPP and tau processing pathways were investigated in the SH-SY5Y-AβPP and PC12-htau cells. We found that the S. scardica and C. spinosum extracts have similar effects on tau, as they both significantly decrease total tau, the activation of the GSK3β, ERK1 and/or ERK2 kinases of tau, as well as tau hyperphosphorylation. Furthermore, both extracts appear to promote AβPP processing through the alpha, non-amyloidogenic pathway, albeit through partly different mechanisms. CONCLUSIONS: These findings suggest that C. spinosum and S. scardica could have a notable potential in the prevention and/or treatment of AD, and merit further investigations at the in vivo level.

Biallelic Loss of Function of SORL1 in an Early Onset Alzheimer's Disease Patient. - Le Guennec, Kilan; Tubeuf, Hélène; Hannequin, Didier; Wallon, David; Quenez, Olivier; Rousseau, Stéphane; Richard, Anne-Claire; Deleuze, Jean-François; Boland, Anne; Frebourg, Thierry; Gaildrat, Pascaline; Campion, Dominique; et al. (J Alzheimers Dis, 2018)
Heterozygous SORL1 protein truncating variants (PTV) are a strong risk factor for early-onset Alzheimer's disease (EOAD). In case control studies performed at the genome-wide level, PTV definition is usually straightforward. Regarding splice site variants, only those affecting canonical sites are typically included. Some other variants, not annotated as PTV, could, however, affect splicing and hence result in a loss of SORL1 function. We took advantage of the whole exome sequencing data from the 9/484 patients with a previously reported SORL1 PTV in the French EOAD series and searched for a second variant which may affect splicing and eventually result in more than 50% loss of function overall. We found that one patient, known to carry a variant predicted to disrupt the canonical 5' splice site of exon 8, also carried a second novel intronic variant predicted to affect SORL1 splicing of exon 29. Segregation analysis showed that the second variant was located in trans from the known PTV. We performed ex vivo minigene splicing assays and showed that both variants led to the generation of transcripts containing a premature stop codon. This is therefore the first evidence of a human carrying biallelic SORL1 PTV. This patient had a family history of dementia in both maternal and paternal lineages with later ages of onset than the proband himself. However, his 55 years age at onset was in the same ranges as previously published SORL1 heterozygous PTV carriers. This suggests that biallelic loss of SORL1 function is an extremely rare event that was not associated with a dramatically earlier age at onset than heterozygous SORL1 loss-of-function variant carriers, in this single patient.
Keywords: Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Risk Factors

Bi-directional Association of Cerebrospinal Fluid Immune Markers with Stage of Alzheimer's Disease Pathogenesis. - Meyer, Pierre-François; Savard, Mélissa; Poirier, Judes; Labonte, Anne; Rosa-Neto, Pedro; Weitz, Tara M; Town, Terrence; Breitner, John (J Alzheimers Dis, 2018)
Immune mechanisms may be important in the pathogenesis of Alzheimer's disease (AD). Yet, studies comparing cerebrospinal fluid (CSF) and plasma immune marker levels of healthy and demented individuals have yielded conflicting results. We analyzed CSF from 101 members of the parental history-positive PREVENT-AD cohort of healthy aging adults, and 237 participants without dementia from the initial cohort of the Alzheimer's Disease Neuroimaging Initiative (ADNI-1). Following recent practice, we used the biomarkers total-tau and amyloid-β1-42 to allocate participants from each study into four stages of AD pathogenesis: Stage 0 (no abnormality), Stage 1 (reduced amyloid-β1-42), Stage 2 (reduced amyloid-β1-42 and increased total-tau), or "Suspected Non-Alzheimer Pathology" (elevated total-tau only). Investigating the PREVENT-AD participants' CSF assay results for 19 immune/inflammatory markers, we found six that showed a distinct bi-directional relationship with pathogenetic stage. Relative to Stage 0, these were diminished at Stage 1 but strongly increased at Stage 2. Among the ADNI participants (90 healthy controls and 147 with mild cognitive impairment), we found that 23 of 83 available CSF markers also showed this distinct pattern. These results support recent observations that immune activation may become apparent only after the onset of both amyloid and tau pathologies. Unexpectedly, they also suggest that immune marker activity may diminish along with earliest appearance of amyloid-β plaque pathology. These findings may explain discordant results from past studies, and suggest the importance of characterizing the extent of AD pathology when comparing clinical groups.

Bioactive Food Abates Metabolic and Synaptic Alterations by Modulation of Gut Microbiota in a Mouse Model of Alzheimer's Disease. - Syeda, Tauqeerunnisa; Sanchez-Tapia, Mónica; Pinedo-Vargas, Laura; Granados, Omar; Cuervo-Zanatta, Daniel; Rojas-Santiago, Eleazar; Díaz-Cintra, Sof A; Torres, Nimbe; Perez-Cruz, Claudia (J Alzheimers Dis, 2018)
Recent investigations have demonstrated an important role of gut microbiota (GM) in the pathogenesis of Alzheimer's disease (AD). GM modulates a host's health and disease by production of several substances, including lipopolysaccharides (LPS) and short-chain fatty acids (SCFAs), among others. Diet can modify the composition and diversity of GM, and ingestion of a healthy diet has been suggested to lower the risk to develop AD. We have previously shown that bioactive food (BF) ingestion can abate neuroinflammation and oxidative stress and improve cognition in obese rats, effects associated with GM composition. Therefore, BF can impact the gut-brain axis and improved behavior. In this study, we aim to explore if inclusion of BF in the diet may impact central pathological markers of AD by modulation of the GM. Triple transgenic 3xTg-AD (TG) female mice were fed a combination of dried nopal, soy, chia oil, and turmeric for 7 months. We found that BF ingestion improved cognition and reduced Aβ aggregates and tau hyperphosphorylation. In addition, BF decreased MDA levels, astrocyte and microglial activation, PSD-95, synaptophysin, GluR1 and ARC protein levels in TG mice. Furthermore, TG mice fed BF showed increased levels of pGSK-3β. GM analysis revealed that pro-inflammatory bacteria were more abundant in TG mice compared to wild-type, while BF ingestion was able to restore the GM's composition, LPS, and propionate levels to control values. Therefore, the neuroprotective effects of BF may be mediated, in part, by modulation of GM and the release of neurotoxic substances that alter brain function.

Bone-Marrow-Derived Microglia-Like Cells Ameliorate Brain Amyloid Pathology and Cognitive Impairment in a Mouse Model of Alzheimer's Disease. - Kawanishi, Shohei; Takata, Kazuyuki; Itezono, Shouma; Nagayama, Hiroko; Konoya, Sayaka; Chisaki, Yugo; Toda, Yuki; Nakata, Susumu; Yano, Yoshitaka; Kitamura, Yoshihisa; Ashihara, Eishi (J Alzheimers Dis, 2018)
Microglia, the primary immune cells in the brain, sense pathogens and tissue damage, stimulate cytokine production, and phagocytosis to maintain homeostasis. Accumulation of amyloid-β peptides (Aβ) in the brain triggers the onset of Alzheimer's disease (AD). Accordingly, promotion of Aβ clearance represents a promising strategy for AD therapy. We previously demonstrated that primary-cultured rat microglia phagocytose Aβ, and that transplantation of these cells ameliorates the Aβ burden in brains of Aβ-injected rats. In this study, we demonstrate that stimulation with colony-stimulating factor-1 efficiently differentiates mouse bone marrow cells into bone marrow-derived microglia-like (BMDML) cells that express markers for microglia, including the recently identified transmembrane protein 119. BMDML cells effectively phagocytose Aβ in vitro, with effects comparable to primary-cultured mouse microglia and greater than peritoneal macrophages. RT-qPCR analysis for cytokine mRNA levels revealed that BMDML cells polarize to a relatively anti-inflammatory state under non-stimulated and inflammatory conditions but exert a pro-inflammatory reaction after lipopolysaccharide treatment. Moreover, BMDML cells hippocampally injected into a mouse model of AD are morphologically similar to the ramified and amoeboid types of residential microglia. Comparisons with simulations assuming a uniform distribution of cells suggest that BMDML cells migrate directionally toward Aβ plaques. We also detected Aβ phagocytosis by BMDML cells, concomitant with a reduction in the number and area of Aβ plaques. Finally, we observed amelioration of cognitive impairment in a mouse model of AD after hippocampal injection of BMDML cells. Our results suggest that BMDML cells have potential as a cell-based disease-modifying therapy against AD.

Brimapitide Reduced Neuronal Stress Markers and Cognitive Deficits in 5XFAD Transgenic Mice. - Gourmaud, Sarah; Thomas, Priscilla; Thomasseau, Sylvie; Tible, Marion; Abadie, Claire; Paquet, Claire; Hugon, Jacques (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by accumulations of amyloid-β (Aβ42) and hyperphosphorylated tau proteins, associated with neuroinflammation, synaptic loss, and neuronal death. Several studies indicate that c-Jun N-terminal kinase (JNK) is implicated in the pathological features of AD. We have investigated in 5XFAD mice, the therapeutic effects of Brimapitide, a JNK-specific inhibitory peptide previously tested with higher concentrations in another AD model (TgCRND8). Three-month-old 5XFAD and wild-type littermate mice were treated by intravenous injections of low doses (10 mg/kg) of Brimapitide every 3 weeks, for 3 or 6 months (n = 6-9 per group). Cognitive deficits and brain lesions were assessed using Y-maze, fear-conditioning test, and histological and biochemical methods. Chronic treatment of Brimapitide for 3 months resulted in a reduction of Aβ plaque burden in the cortex of 5XFAD treated mice. After 6 months of treatment, cognitive deficits were reduced but also a significant reduction of cell death markers and the pro-inflammatory IL-1β cytokine in treated mice were detected. The Aβ plaque burden was not anymore modified by the 6 months of treatment. In addition to modulating cognition and amyloid plaque accumulation, depending on the treatment duration, Brimapitide seems experimentally to reduce neuronal stress in 5XFAD mice.

Can a Novel High-Density EEG Approach Disentangle the Differences of Visual Event Related Potential (N170), Elicited by Negative Facial Stimuli, in People with Subjective Cognitive Impairment? - Lazarou, Ioulietta; Adam, Katerina; Georgiadis, Kostas; Tsolaki, Anthoula; Nikolopoulos, Spiros; Yiannis Kompatsiaris, Ioannis; Tsolaki, Magda (J Alzheimers Dis, 2018)
BACKGROUND: Studies on subjective cognitive impairment (SCI) and neural activation report controversial results. OBJECTIVE: To evaluate the ability to disentangle the differences of visual N170 ERP, generated by facial stimuli (Anger & Fear) as well as the cognitive deterioration of SCI, mild cognitive impairment (MCI), and Alzheimer's disease (AD) compared to healthy controls (HC). METHOD: 57 people took part in this study. Images corresponding to facial stimuli of "Anger" and "Fear" were presented to 12 HC, 14 SCI, 17 MCI and 14 AD participants. EEG data were recorded by using a HD-EEG HydroCel with 256 channels. RESULTS: Results showed that the amplitude of N170 can contribute in distinguishing the SCI group, since statistically significant differences were observed with the HC (p < 0.05) and the MCI group from HC (p < 0.001), as well as AD from HC (p = 0.05) during the processing of facial stimuli. Noticeable differences were also observed in the topographic distribution of the N170 amplitude, while localization analysis by using sLORETA images confirmed the activation of superior, middle-temporal, and frontal lobe brain regions. Finally, in the case of "Fear", SCI and HC demonstrated increased activation in the orbital and inferior frontal gyrus, respectively, MCI in the inferior temporal gyrus, and AD in the lingual gyrus. CONCLUSION: These preliminary findings suggest that the amplitude of N170 elicited after negative facial stimuli could be modulated by the decline related to pathological cognitive aging and can contribute in distinguishing HC from SCI, MCI, and AD.

Cannabinoid Receptor 2-Deficiency Ameliorates Disease Symptoms in a Mouse Model with Alzheimer's Disease-Like Pathology. - Schmöle, Anne-Caroline; Lundt, Ramona; Toporowski, Gregor; Hansen, Jan N; Beins, Eva; Halle, Annett; Zimmer, Andreas (J Alzheimers Dis, 2018)
It is widely accepted that the endocannabinoid system (ECS) is a modulator of neuroinflammation associated with neurodegenerative disorders, including Alzheimer's disease (AD). Thus, expression of the cannabinoid receptor 2 (CB2) is induced in plaque-associated microglia and astrocytes in brain tissues from AD patients and in genetic mouse models expressing pathogenic variants of the amyloid precursor protein (APP). However, the exact mechanism of CB2 signaling in this mouse model remains elusive, because the genetic deletion of CB2 and the pharmacological activation of CB2 both reduced neuroinflammation. Here, we demonstrate that CB2 deletion also improved cognitive and learning deficits in APP/PS1*CB2-/- mice. This was accompanied by reduced neuronal loss and decreased plaque levels and coincided with increased expression of Aβ degrading enzymes. Interestingly, plaque-associated microglia in APP/PS1*CB2-/- mice showed a less activated morphology, while plaques were smaller and more condensed than in APP/PS1 mice. Taken together, these results indicate a beneficial effect of CB2-deficiency in APP transgenic mice. CB2 appears to be part of a protective system that may be detrimental when engaged continuously.

Cardiorespiratory Fitness and White Matter Neuronal Fiber Integrity in Mild Cognitive Impairment. - Ding, Kan; Tarumi, Takashi; Zhu, David C; Tseng, Benjamin Y; Thomas, Binu P; Turner, Marcel; Repshas, Justin; Kerwin, Diana R; Womack, Kyle B; Lu, Hanzhang; Cullum, C Munro; Zhang, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Mounting evidence showed the self-reported levels of physical activity are positively associated with white matter (WM) integrity and cognitive performance in normal adults and patients with mild cognitive impairment (MCI). However, the objective measure of cardiorespiratory fitness (CRF) was not used in these studies. OBJECTIVE: To determine the associations of CRF measured by maximal oxygen uptake (VO2max) with WM fiber integrity and neurocognitive performance in older adults with MCI. METHODS: Eighty-one participants (age = 65±7 years, 43 women), including 26 cognitively normal older adults and 55 amnestic MCI patients, underwent VO2max test to measure CRF, diffusion tensor imaging (DTI) to assess WM fiber integrity, and neurocognitive assessment focused on memory and executive function. DTI data were analyzed by the tract-based spatial statistics and region-of-interest approach. RESULTS: Cognitively normal older adults and MCI patients were not different in global WM fiber integrity and VO2max. VO2max was associated positively with DTI metrics of fractional anisotropy in ∼54% WM fiber tracts, and negatively with mean and radial diffusivities in ∼46% and ∼56% of the WM fiber tracts. The associations of VO2max with DTI metrics remained statistically significant after adjustment of age, sex, body mass index, WM lesion burden, and MCI status. The DTI metrics obtained from the area that correlated to VO2max were associated with executive function performance in MCI patients. CONCLUSIONS: Higher levels of CRF are associated with better WM fiber integrity, which in turn is correlated with better executive function performance in MCI patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anisotropy; Cardiorespiratory Fitness; Case-Control Studies; Cognition; Cognitive Dysfunction; Diffusion Tensor Imaging; Executive Function; Female; Humans; Linear Models; Male; Memory; Middle Aged; Nerve Fibers, Myelinated; Neuropsychological Tests; Texas; White Matter

Cerebral Amyloid Angiopathy and Cerebral Amyloid Angiopathy-Related Inflammation: Comparison of Hemorrhagic and DWI MRI Features. - Renard, Dimitri; Tatu, Lavinia; Collombier, Laurent; Wacongne, Anne; Ayrignac, Xavier; Charif, Mahmoud; Boukriche, Yassine; Chiper, Laura; Fourcade, Genevieve; Azakri, Souhayla; Gaillard, Nicolas; Mercier, Erick; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral amyloid angiopathy (CAA) can be associated with primary vasculitis of small/medium-sized leptomeningeal and cortical arteries, called CAA-related inflammation (CAA-ri). OBJECTIVE: To compare hemorrhagic and diffusion-weighted imaging (DWI) MRI features in CAA and CAA-ri. METHODS: We prospectively scored in a consecutive CAA and CAA-ri cohort: presence/number of chronic intracerebral hemorrhage (ICH), cerebral microbleeds (CMB), and cortical superficial siderosis (CSS) on initial T2*-weighted imaging, and DWI lesions on both initial and follow-up imaging. In a subgroup, ApoE, CSF, and 18F-florbetaben-positron emission tomography (FBB-PET) were also analyzed. RESULTS: In CAA-ri, CMB presence was more frequent (100% versus 40%, p < 0.001) and CMB numbers higher (mean 137 versus 8, p < 0.001). No difference was observed for chronic ICH or CSS. DWI lesions were more frequent in acute compared to chronic CAA-ri (p = 0.025), whereas no such difference was observed between acute and chronic CAA (p = 0.18). Both ApoE4 (genotyping available in 22 CAA-ri and 48 CAA patients) carriers and homozygosity were more frequent in CAA-ri (48% versus 19% [p = 0.014] and 32% versus 2% [p < 0.001] respectively). CSF biomarker analyses (performed in 20 CAA-ri and 45 CAA patients) showed lower Aβ42 levels in CAA-ri compared to CAA (median 312 versus 422 pg/mL, p = 0.0032). FBB-PET (performed in 11 CAA-ri and 20 CAA patients) showed higher standardized uptake value ratios in CAA-ri compared with CAA, only significant when the pons was used as reference (p = 0.037). CONCLUSION: Compared to CAA, CAA-ri was associated with higher CMB numbers, more frequent ApoE4 carriers and homozygotes, lower CSF Aβ42 levels, and more severe amyloid load on FBB-PET.

Cerebral White Matter Lesions have Low Impact on Cognitive Function in a Large Elderly Memory Clinic Population. - Claus, Jules J; Coenen, Mirthe; Staekenborg, Salka S; Schuur, Jacqueline; Tielkes, Caroline E M; Koster, Pieter; Scheltens, Philip (J Alzheimers Dis, 2018)
BACKGROUND: Evidence suggests that cerebral white matter lesions (WML) play a role in cognitive decline. OBJECTIVE: To assess the impact of cerebral WML on cognitive function relative to absence or presence of medial temporal atrophy (MTA) in a large single-center memory clinic population. METHODS: Patients included had subjective cognitive impairment (SCI, n = 333), mild cognitive impairment (MCI, n = 492) and Alzheimer's disease (AD, n = 832). The relationships between visually rated WML (Fazekas scale, 0-3) on brain Computed Tomography and CAMCOG memory and non-memory function were investigated with regression analysis adjusted for age, gender and education in combined patient groups. We assessed possible interaction versus addition effects of these relationships with visually rated MTA (Scheltens scale). RESULTS: The highly statistical significant relationship between WML and memory function was no longer significant when MTA was taken into account. However, the strong significant relationship between WML and non-memory function remained significant after adjustment for MTA, but the explained variance attributed to WML was only 1.3%. There was no interaction between WML and MTA on CAMCOG test scores. In addition, shown by a 2×2 factorial model by presence versus absence of WML and MTA, WML affected non-memory function only in the presence of MTA. CONCLUSION: Our data suggest that presence of WML is associated with lower non-memory cognitive function but this effect is conditional on the presence of pre-existing MTA. The very small explained variance suggests little impact of WML to the clinical profile of a memory clinic patient.

Cerebrospinal Fluid Levels of Angiotensin-Converting Enzyme Are Associated with Amyloid-β42 Burden in Alzheimer's Disease. - Rocha, Natalia P; Toledo, Andre; Corgosinho, Laiane T S; de Souza, Leonardo C; Guimarães, Henrique C; Resende, Elisa P F; Braz, Nayara F T; Gomes, Karina B; Simoes E Silva, Ana C; Caramelli, Paulo; Teixeira, Antônio L (J Alzheimers Dis, 2018)
This study was designed to determine whether the levels of renin-angiotensin system (RAS) components are associated with Alzheimer's disease (AD) pathology. Cerebrospinal fluid levels of Angiotensin (Ang) II, Ang-(1-7), angiotensin-converting enzyme (ACE), ACE2, Amyloid-β (Aβ)40, Aβ42, total tau (hTau), and phospho-tau (pTau) were measured in 18 patients with AD and 10 controls. Patients with AD presented decreased levels of ACE when compared with controls. We found a significant positive correlation between ACE and Aβ42 levels among patients. Our results strengthen the hypothesis that ACE is associated with Aβ pathology in AD.

Cerebrospinal Fluid, MRI, and Florbetaben-PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Collombier, Laurent; Demattei, Christophe; Wacongne, Anne; Charif, Mahmoud; Ayrignac, Xavier; Azakri, Souhayla; Gaillard, Nicolas; Boudousq, Vincent; Lehmann, Sylvain; Menjot de Champfleur, Nicolas; Thouvenot, Eric (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is associated with a cerebrospinal fluid (CSF) biomarker profile similar to that observed in CAA. Few CAA-ri patients have been studied by fibrillar amyloid-β (Aβ) imaging (using 11C-Pittsburgh compound B and 18F-florbetapir, but not 18F-florbetaben). OBJECTIVE: To describe CSF biomarkers, magnetic resonance imaging (MRI), and 18F-florbetaben (FBB)-positron emission tomography (PET) changes in CAA-ri patients. METHODS: CSF levels of total tau, phosphorylated tau, Aβ1-42, and Aβ1-40, MRI (cerebral microbleeds count on susceptibility-weighted imaging and semi-quantitative analysis of fluid-attenuation inversion recovery white matter hyperintensities), and FBB-PET (using both cerebellar cortex and pons to calculate standardized uptake value ratios) were analyzed in nine consecutive CAA-ri patients. RESULTS: A median number of 769 cerebral microbleeds/patient were counted on MRI. When using the pons as reference region, amyloid load on FBB-PET was very strongly correlated to CSF Aβ1-40 levels (rho = -0.83, p = 0.008) and moderately correlated to cerebral microbleed numbers in the occipital lobes (rho = 0.59, p = 0.001), while comparisons with other CSF biomarkers were not statistically significant (total tau, rho = -0.63, p = 0.076; phosphorylated tau, rho = -0.68, p = 0.05; Aβ1-42, rho = -0.59, p = 0.09). All correlations were weaker, and not statistically significant, when using the cerebellum as reference region. A non-significant correlation (rho = -0.50, p = 0.18) was observed between CSF Aβ1-40 levels and cerebral microbleed numbers. CONCLUSION: In CAA-ri, CSF Aβ1-40 levels correlated well with amyloid load assessed by FBB-PET when the pons was used as reference, and to a lesser degree with cerebral microbleeds count on MRI. This confirms earlier data on CSF Aβ1-40 as an in vivo marker for CAA and CAA-ri.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Aniline Compounds; Biomarkers; Brain; Cerebral Amyloid Angiopathy; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Positron-Emission Tomography; Prospective Studies; Stilbenes; tau Proteins; Vasculitis, Central Nervous System

Change of Amyloid-β 1-42 Toxic Conformer Ratio After Cerebrospinal Fluid Diversion Predicts Long-Term Cognitive Outcome in Patients with Idiopathic Normal Pressure Hydrocephalus. - Akiba, Chihiro; Nakajima, Madoka; Miyajima, Masakazu; Ogino, Ikuko; Motoi, Yumiko; Kawamura, Kaito; Adachi, Satoshi; Kondo, Akihide; Sugano, Hidenori; Tokuda, Takahiko; Irie, Kazuhiro; Arai, Hajime (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) pathology in idiopathic normal pressure hydrocephalus (iNPH) contributes to poor shunt responses. Amyloid-β 1- 42 (Aβ42) toxic conformer was recently identified with features of rapid oligomerization, strong neurotoxicity and synaptotoxicity. OBJECTIVE: This observational study points to Aβ42 toxic conformer as a biomarker for AD pathology and for poor postoperative prognosis in patients with iNPH. METHODS: The first cohort consisted of patients with AD (n = 17) and iNPH (n = 17), and cognitively normal individuals (CN, n = 12). The second cohort, consisted of 51 patients with iNPH, was divided into two groups according to phosphorylated Tau (pTau) level (low- and high-pTau groups); the low-pTau group was further subdivided according to one-year postoperative change in Aβ42 toxic conformer ratio (%) [Aβ42 toxic conformer/Aβ42×100] (decreased- and increased-conformer subgroups). Enzyme-linked immunosorbent assay was used to measure pTau, Aβ42, and Aβ42 toxic conformer in cerebrospinal fluid. Outcomes were evaluated using neuropsychological tests one- and two-years postoperatively. RESULTS: In the first cohort, Aβ42 toxic conformer ratio in the iNPH group (10.8%) was significantly higher than that in the CN group (6.3%) and significantly lower than that in the AD group (17.2%). In the second cohort, the high-pTau group showed cognitive decline two-years postoperatively compared to baseline. However, the low-pTau group showed favorable outcomes one-year postoperatively; furthermore, the increased-conformer subgroup showed cognitive decline two-years postoperatively while the decreased-conformer subgroup maintained the improvement. CONCLUSIONS: Change in Aβ42 toxic conformer ratio predicts long-term cognitive outcome in iNPH, even in the low-pTau group.

Characterization of Music and Photograph Evoked Autobiographical Memories in People with Alzheimer's Disease. - Baird, Amee; Brancatisano, Olivia; Gelding, Rebecca; Thompson, William Forde (J Alzheimers Dis, 2018)
BACKGROUND: Music evoked autobiographical memories (MEAMs) have been documented in people with Alzheimer's disease (AD), but it is unclear whether music is more effective than other familiar stimuli at evoking memories. OBJECTIVE: To explore the frequency and specificity of memories in response to famous songs compared with photographs of famous events (photograph evoked autobiographical memories, PEAMs), and whether stimuli from the period of the reminiscence bump (10-30 years of age) were more likely to elicit memories. METHODS: 10 participants with AD and 10 aged-matched healthy elderly people reported memories following exposure to 2 songs (longest time at number one in Australian music charts) and 2 photographs (of prominent famous events) from each decade from 1930 to 2010. RESULTS: PEAMs were more frequent than MEAMs in healthy elderly (p < 0.05), but no such differences were observed among people with AD. There was no difference in the frequency of MEAMs between groups, but people with AD showed a significant decline in the frequency of PEAMs. In both groups, MEAMs were typically less specific than PEAMs and comprised semantic knowledge or repeated/extended events. Stimuli from when participants were aged 10-30 years triggered more frequent memories compared with stimuli from later decades, but this was only statistically significant for MEAMs. CONCLUSION: Our findings indicate a preserved mnemonic effect of music relative to pictures in this patient population, corroborating suggestions that MEAMs represent an island of preservation during the progression of AD.

Circulating, Cell-Free Micro-RNA Profiles Reflect Discordant Development of Dementia in Monozygotic Twins. - Mengel-From, Jonas; Rønne, Mette E; Carlsen, Anting L; Skogstrand, Kristin; Larsen, Lisbeth A; Tan, Qihua; Christiansen, Lene; Christensen, Kaare; Heegaard, Niels H H (J Alzheimers Dis, 2018)
We aim to examine if circulating micro-RNA and cytokine levels associate with dementia diagnosis and cognitive scores. To test our hypothesis, we use plasma donated from 48 monozygotic twin pairs in 1997 and 46 micro-RNAs and 10 cytokines were quantified using microfluidic RT-qPCR and multiplex solid-phase immunoassays, respectively. Micro-RNA and cytokine profiling were examined for associations with dementia diagnoses in a longitudinal registry study or with cognitive scores at baseline. Thirty-six micro-RNAs and all cytokines were detected consistently. Micro-RNA profiles associate with diagnoses and cognitive scores at statistically significant levels while cytokine only showed trends pointing at chronic inflammation in twins having or developing dementia. The most notable findings were decreased miR-106a and miR-210, and increased miR-106b expression in twins with a dementia diagnosis. This pioneering evaluation of micro-RNA and cytokine and dementia diagnosis suggests micro-RNA targets in vasculogenesis, lipoprotein transport, and amyloid precursor protein genes.

Circulating miR-127-3p as a Potential Biomarker for Differential Diagnosis in Frontotemporal Dementia. - Piscopo, Paola; Grasso, Margherita; Puopolo, Maria; D'Acunto, Emanuela; Talarico, Giuseppina; Crestini, Alessio; Gasparini, Marina; Campopiano, Rosa; Gambardella, Stefano; Castellano, Anna Elisa; Bruno, Giuseppe; Denti, Michela A; et al. (J Alzheimers Dis, 2018)
Given the heterogeneous nature of frontotemporal dementia (FTD), sensitive biomarkers are greatly needed for the accurate diagnosis of this neurodegenerative disorder. Circulating miRNAs have been reported as promising biomarkers for neurodegenerative disorders and processes affecting the central nervous system, especially in aging. The objective of the study was to evaluate if some circulating miRNAs linked with apoptosis (miR-29b-3p, miR-34a-5p, miR-16-5p, miR-17-5p, miR-107, miR-19b-3p, let-7b-5p, miR-26b-5p, and 127-3p) were able to distinguish between FTD patients and healthy controls. For this study, we enrolled 127 subjects, including 54 patients with FTD, 20 patients with Alzheimer's disease (AD), and 53 healthy controls. The qRT-PCR analysis showed a downregulation of miR-127-3p in FTD compared to controls, while the levels of other miRNAs remained unchanged. Then, miR-127-3p expression was also analyzed in AD patients, finding a different expression between two patient groups. A receiver operating characteristic curve was then created for miR-127-3p to discriminate FTD versus AD (AUC: 0.8986), and versus healthy controls (AUC: 0.8057). In conclusion, miR-127-3p could help to diagnose FTD and to distinguish it from AD.

Circulating Progenitor Cells Correlate with Memory, Posterior Cortical Thickness, and Hippocampal Perfusion. - Nation, Daniel A; Tan, Alick; Dutt, Shubir; McIntosh, Elissa C; Yew, Belinda; Ho, Jean K; Blanken, Anna E; Jang, Jung Yun; Rodgers, Kathleen E; Gaubert, Aimée (J Alzheimers Dis, 2018)
BACKGROUND: Bone marrow-derived progenitor cells survey the vasculature and home to sites of tissue injury where they can promote repair and regeneration. It has been hypothesized that these cells may play a protective role neurodegenerative and vascular cognitive impairment. OBJECTIVE: To evaluate progenitor cell levels in older adults with and without mild cognitive impairment (MCI), and to relate circulating levels to memory, brain volume, white matter lesion volume, and cerebral perfusion. METHOD: Thirty-two older adults, free of stroke and cardiovascular disease, were recruited from the community and evaluated for diagnosis of MCI versus cognitively normal (CN). Participants underwent brain MRI and blood samples were taken to quantify progenitor reserve using flow cytometry (CD34+, CD34+CD133+, and CD34+CD133+CD309+ cells). RESULTS: Participants with MCI (n = 10) exhibited depletion of all CPC markers relative to those who were CN (n = 22), after controlling for age, sex, and education. Post-hoc age, sex, and education matched comparisons (n = 10 MCI, n = 10 CN) also revealed the same pattern of results. Depletion of CD34+ cells correlated with memory performance, left posterior cortical thickness, and bilateral hippocampal perfusion. Participants exhibited low levels of vascular risk and white matter lesion burden that did not correlate with progenitor levels. CONCLUSIONS: Circulating progenitor cells are associated with cognitive impairment, memory, cortical atrophy, and hippocampal perfusion. We hypothesize that progenitor depletion contributes to, or is triggered by, cognitive decline and cortical atrophy. Further study of progenitor cell depletion in older adults may benefit efforts to prevent or delay dementia.
Keywords: Aged; Aged, 80 and over; Antigens, CD; Apolipoproteins E; Cerebral Cortex; Cognitive Dysfunction; Female; Flow Cytometry; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perfusion; Stem Cells; White Matter

Clinical Experience with Cerebrospinal Fluid Aβ42, Total and Phosphorylated Tau in the Evaluation of 1,016 Individuals for Suspected Dementia. - Tariciotti, Leonardo; Casadei, Matthew; Honig, Lawrence S; Teich, Andrew F; McKhann Ii, Guy M; Tosto, Giuseppe; Mayeux, Richard (J Alzheimers Dis, 2018)
BACKGROUND: Elevated total tau (tTau), 181-phosphorylated phosphorylated tau (pTau), and low amyloid-β42 (Aβ42) in cerebrospinal fluid (CSF) represent a diagnostic biomarker for Alzheimer's disease (AD). OBJECTIVE: The goal was to determine the overall accuracy of CSF Aβ42, tTau, pTau, and the Aβ42/total tau index (ATI) in a non-research, clinical setting for the diagnosis of AD. METHODS: From medical records in 1,016 patients that had CSF studies for dementia over a 12-year period (2005 to 2017), we calculated the sensitivity and specificity of CSF Aβ42, tTau, and pTau and the ATI in relation to the final clinical diagnosis. RESULTS: Compared with non-demented patients and patients with other dementias or mild cognitive impairment (MCI), the sensitivity and specificity of the recommended ATI and pTau cut-offs (ATI < 1.0 and pTau >61 pg/ml) for the diagnosis of AD were 0.88 and 0.72, respectively. Similar results were obtained comparing AD with non-demented patients only (0.88, 0.82) and AD with other types of dementia (0.81, 0.77). A subgroup of patients with presumed normal pressure hydrocephalus (n = 154) were biopsied at the time of shunt placement. Using the pathological manifestations of AD as the standard, the sensitivity was 0.83 while the specificity was 0.72. CONCLUSIONS: In a non-research setting, CSF biomarkers for AD showed a high sensitivity in accordance with previous studies, but modest specificity differentiating AD from other types of dementia or MCI. This study of unselected patients provides a valid and realistic assessment of the diagnostic accuracy of these CSF biomarkers in clinical practice.

Clinic-Based Validation of Cerebrospinal Fluid Biomarkers with Florbetapir PET for Diagnosis of Dementia. - Álvarez, Ignacio; Aguilar, Miquel; González, Jose Manuel; Ysamat, Montse; Lorenzo-Bosquet, Carles; Alonso, Alvaro; Tartari, Juan Pablo; Romero, Silvia; Diez-Fairen, Monica; Carcel, Maria; Pujalte, Francisco; Pastor, Pau (J Alzheimers Dis, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) biomarker studies have shown variable accuracy for diagnosis of Alzheimer's disease (AD); therefore, internal validation is recommended. OBJECTIVE: To investigate the correlation between CSF biomarkers and cerebral 18-Florbetapir positron emission tomography (Amyloid-PET) and calculate their sensitivity and specificity to obtain the optimal clinical cut-off points to diagnose the etiology of cognitive impairment. METHODS: We performed Amyloid-PET scans and CSF biomarker levels analyses in 68 subjects (50 with mild cognitive impairment, 11 with AD dementia, and 7 with non-AD dementia). Visual examination of Amyloid-PET scans was performed. CSF analyses were performed using standard sandwich ELISA. RESULTS: Amyloid-PET was positive in 36 subjects, negative in 26, and inconclusive in 6. Optimal clinical cut-off points for CSF markers were the following: amyloid-β 1-42 (Aβ42) = 629 pg/ml, total tau (t-tau) = 532 pg/ml, phosphorylated tau (p-tau) = 88 pg/ml, and t-tau/Aβ42 ratio = 0.58. T-tau/Aβ42 ratio showed the best sensitivity and specificity (92 and 84%, respectively). T-tau and p-tau CSF levels (r2 = 0.867) followed by the t-tau and t-tau/Aβ42 CSF ratio (r2 = 0.666) showed the strongest inter-marker correlation. Interestingly, subjects with inconclusive Amyloid-PET showed intermediate values for all CSF markers between negative and positive Amyloid-PET groups. CONCLUSIONS: CSF t-tau/Aβ42 ratio appears to be the most accurate AD CSF marker. The presence of intermediate values for CSF markers among the subjects with inconclusive Amyloid-PET suggests the presence of other dementias associated with AD pathology or intermediate phenotypes.
Keywords: Aged; Amyloid beta-Peptides; Analysis of Variance; Aniline Compounds; Apolipoproteins E; Biomarkers; Cognition Disorders; Dementia; Ethylene Glycols; Female; Humans; Male; Middle Aged; Peptide Fragments; Positron-Emission Tomography; tau Proteins

A Clinicopathological Investigation of White Matter Hyperintensities and Alzheimer's Disease Neuropathology. - Alosco, Michael L; Sugarman, Michael A; Besser, Lilah M; Tripodis, Yorghos; Martin, Brett; Palmisano, Joseph N; Kowall, Neil W; Au, Rhoda; Mez, Jesse; DeCarli, Charles; Stein, Thor D; McKee, Ann C; et al. (J Alzheimers Dis, 2018)
BACKGROUND: White matter hyperintensities (WMH) on magnetic resonance imaging (MRI) have been postulated to be a core feature of Alzheimer's disease. Clinicopathological studies are needed to elucidate and confirm this possibility. OBJECTIVE: This study examined: 1) the association between antemortem WMH and autopsy-confirmed Alzheimer's disease neuropathology (ADNP), 2) the relationship between WMH and dementia in participants with ADNP, and 3) the relationships among cerebrovascular disease, WMH, and ADNP. METHODS: The sample included 82 participants from the National Alzheimer's Coordinating Center's Data Sets who had quantitated volume of WMH from antemortem FLAIR MRI and available neuropathological data. The Clinical Dementia Rating (CDR) scale (from MRI visit) operationalized dementia status. ADNP+ was defined by moderate to frequent neuritic plaques and Braak stage III-VI at autopsy. Cerebrovascular disease neuropathology included infarcts or lacunes, microinfarcts, arteriolosclerosis, atherosclerosis, and cerebral amyloid angiopathy. RESULTS: 60/82 participants were ADNP+. Greater volume of WMH predicted increased odds for ADNP (p = 0.037). In ADNP+ participants, greater WMH corresponded with increased odds for dementia (CDR≥1; p = 0.038). WMH predicted cerebral amyloid angiopathy, microinfarcts, infarcts, and lacunes (ps < 0.04). ADNP+ participants were more likely to have moderate-severe arteriolosclerosis and cerebral amyloid angiopathy compared to ADNP-participants (ps < 0.04). CONCLUSIONS: This study found a direct association between total volume of WMH and increased odds for having ADNP. In patients with Alzheimer's disease, FLAIR MRI WMH may be able to provide key insight into disease severity and progression. The association between WMH and ADNP may be explained by underlying cerebrovascular disease.

Co-Expression of Glia Maturation Factor and Apolipoprotein E4 in Alzheimer's Disease Brain. - Thangavel, Ramasamy; Bhagavan, Sachin M; Ramaswamy, Swathi Beladakere; Surpur, Spurthi; Govindarajan, Raghav; Kempuraj, Duraisamy; Zaheer, Smita; Raikwar, Sudhanshu; Ahmed, Mohammad E; Selvakumar, Govindhasamy Pushpavathi; Iyer, Shankar S; Zaheer, Asgar (J Alzheimers Dis, 2018)
Apolipoprotein E4 (ApoE4) is a major genetic risk factor for Alzheimer's disease (AD). The E4 allele of ApoE plays a crucial role in the inflammatory and neurodegenerative processes associated with AD. This is evident from the multiple effects of the ApoE isoforms in amyloid-β (Aβ) aggregation. Glia maturation factor (GMF) is a brain-specific neuroinflammatory protein that we have previously demonstrated to be significantly upregulated in various regions of AD brains compared to non-AD control brains and that it induces neurodegeneration. We have previously reported that GMF is predominantly expressed in the reactive astrocytes surrounding amyloid plaques (APs) in AD brain. In the present study, using immunohistochemical and dual immunofluorescence staining, we show the expression and colocalization of GMF and ApoE4 in AD brains. Our results show that ApoE4 is present within the APs of AD brain. Further, we found that GMF and ApoE4 were strongly expressed and co-associated in APs and in the reactive astrocytes surrounding APs in AD. An increased expression of GMF in APs and neurofibrillary tangles in the AD brain, and the co-localization of GMF and ApoE4 in APs suggest that GMF and ApoE4 together should be contributing to the neuropathological changes associated with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Case-Control Studies; Fluorescent Antibody Technique; Glia Maturation Factor; Humans; Neurofibrillary Tangles; Plaque, Amyloid

Cognitive Function in Individuals with Normal Weight Obesity: Results from the Third National Health and Nutrition Examination Survey (NHANES III). - Malandrino, Noemi; Capristo, Esmeralda; Taveira, Tracey H; Mingrone, Geltrude; Wu, Wen-Chih (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: Normal weight obesity (NWO) is associated with increased risk of metabolic syndrome, cardiovascular- and all-cause mortality. However, no data have been reported on the relationship between adiposity and cognitive performance in NWO. We therefore studied the association between cognitive function and body fat percentage (BF%) in NWO, using a representative sample of the United States population. METHODS: A cross-sectional study was performed using the nationwide 1988 to 1994 data set from the Third National Health and Nutrition Examination Survey. Cognitive function was measured by three validated cognitive tests: simple reaction time test (SRTT), symbol digit substitution test (SDST), and serial digit learning test (SDLT). The association between BF% and cognitive performance was evaluated in 2,039 adults aged 20-59 years and with a body mass index ranging from 18.5 to 24.9 kg/m2. Linear regression modeling was used to adjust for potential confounders. RESULTS: Increased BF% was significantly associated with poorer performance on SDLT in the entire study sample (coefficient [95% CI]: 0.15 [0.01, 0.29]) and with poorer performance on SDST in the age group 20-29 years (coefficient [95% CI]: 0.30 [0.10, 0.49]). Increased BF% did not significantly predict poorer performance on SRTT. CONCLUSION: Higher BF% is significantly associated with poorer cognitive function in a nationally representative sample of US adults with NWO. The identification of possible complications associated with increased adipose tissue underlines the need to measure body fat content in NWO individuals, whose metabolic and cognitive dysfunction could go undetected for years due to their young age and normal body weight.

Common Variant in PLD3 Influencing Cerebrospinal Fluid Total Tau Levels and Hippocampal Volumes in Mild Cognitive Impairment Patients from the ADNI Cohort. - Tan, Meng-Shan; Wang, Ping; Ma, Fang-Chen; Li, Jie-Qiong; Tan, Chen-Chen; Yu, Jin-Tai; Tan, Lan (J Alzheimers Dis, 2018)
Recent studies found the variants in Alzheimer's disease (AD) risk gene PLD3 were associated with cognitive function, but its detailed mechanism before typical AD onset was unknown. Our current study examined the impact of PLD3 common variant rs11667768 on cerebrospinal fluid (CSF) total-tau and phosphorylated-tau levels and structural MRI from the ADNI database. We found rs11667768 was significantly associated with CSF total-tau levels and hippocampal volumes at baseline and six-year follow-up in the total non-demented elderly group and the mild cognitive impairment subgroup, indicating a potential role of PLD3 common variants in influencing cognitive function through changing CSF total-tau levels and hippocampal volumes.

Comparison of Different Hypotheses Regarding the Spread of Alzheimer's Disease Using Markov Random Fields and Multimodal Imaging. - Dyrba, Martin; Grothe, Michel J; Mohammadi, Abdolreza; Binder, Harald; Kirste, Thomas; Teipel, Stefan J (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by a cascade of pathological processes that can be assessed in vivo using different neuroimaging methods. Recent research suggests a systematic sequence of pathogenic events on a global biomarker level, but little is known about the associations and dependencies of distinct lesion patterns on a regional level. Markov random fields are a probabilistic graphical modeling approach that represent the interaction between individual random variables by an undirected graph. We propose the novel application of this approach to study the interregional associations and dependencies between multimodal imaging markers of AD pathology and to compare different hypotheses regarding the spread of the disease. We retrieved multimodal imaging data from 577 subjects enrolled in the Alzheimer's Disease Neuroimaging Initiative. Mean amyloid load (AV45-PET), glucose metabolism (FDG-PET), and gray matter volume (MRI) were calculated for the six principle nodes of the default mode network- a functional network of brain regions that appears to be preferentially targeted by AD. Multimodal Markov random field models were developed for three different hypotheses regarding the spread of the disease: the "intraregional evolution model", the "trans-neuronal spread" hypothesis, and the "wear-and-tear" hypothesis. The model likelihood to reflect the given data was evaluated using tenfold cross-validation with 1,000 repetitions. The most likely graph structure contained the posterior cingulate cortex as main hub region with edges to various other regions, in accordance with the "wear-and-tear" hypothesis of disease vulnerability. Probabilistic graphical models facilitate the analysis of interactions between several variables in a network model and therefore afford great potential to complement traditional multiple regression analyses in multimodal neuroimaging research.

Comprehensive Characterization of the Pyroglutamate Amyloid-β Induced Motor Neurodegenerative Phenotype of TBA2.1 Mice. - Dunkelmann, Tina; Schemmert, Sarah; Honold, Dominik; Teichmann, Kerstin; Butzküven, Elke; Demuth, Hans-Ulrich; Shah, Nadim Joni; Langen, Karl-Josef; Kutzsche, Janine; Willbold, Dieter; Willuweit, Antje (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common neurodegenerative disorder and is being intensively investigated using a broad variety of animal models. Many of these models express mutant versions of human amyloid-β protein precursor (AβPP) that are associated with amyloid-β protein (Aβ)-induced early onset familial AD. Most of these models, however, do not develop bold neurodegenerative pathology and the respective phenotypes. Nevertheless, this may well be essential for their suitability to identify therapeutically active compounds that have the potential for a curative or at least disease-modifying therapy in humans. In this study, the new transgenic mouse model TBA2.1 was explored in detail to increase knowledge about the neurodegenerative process induced by the presence of pyroglutamate modified human Aβ3-42 (pEAβ3-42). Analysis of the sensorimotor phenotype, motor coordination, Aβ pathology, neurodegeneration, and gliosis revealed formation and progression of severe pathology and phenotypes including massive neuronal loss in homozygous TBA2.1 mice within a few months. In contrast, the start of a slight phenotype was observed only after 21 months in heterozygous mice. These data highlight the role of pEAβ3-42 in the disease development and progression of AD. Based on the findings of this study, homozygous TBA2.1 mice can be utilized to gain deeper understanding in the underlying mechanisms of pEAβ3-42 and might be suitable as an animal model for treatment studies targeting toxic Aβ species, complementary to the well described transgenic AβPP mouse models.

Is Computerized Working Memory Training Effective in Healthy Older Adults? Evidence from a Multi-Site, Randomized Controlled Trial. - Simon, Sharon S; Tusch, Erich S; Feng, Nicole C; Håkansson, Krister; Mohammed, Abdul H; Daffner, Kirk R (J Alzheimers Dis, 2018)
BACKGROUND: Developing effective interventions to attenuate age-related cognitive decline and prevent or delay the onset of dementia are major public health goals. Computerized cognitive training (CCT) has been marketed increasingly to older adults, but its efficacy remains unclear. Working memory (WM), a key determinant of higher order cognitive abilities, is susceptible to age-related decline and a relevant target for CCT in elders. OBJECTIVE: To evaluate the efficacy of CCT focused on WM compared to an active control condition in healthy older adults. METHODS: Eighty-two cognitively normal adults from two sites (USA and Sweden) were randomly assigned to Cogmed Adaptive or Non-Adaptive (active control) CCT groups. Training was performed in participants' homes, five days per week over five weeks. Changes in the performance of the Cogmed trained tasks, and in five neuropsychological tests (Trail Making Test Part A and Part B, Digit Symbol, Controlled Oral Word Association Test and Semantic Fluency) were used as outcome measures. RESULTS: The groups were comparable at baseline. The Adaptive group showed robust gains in the trained tasks, and there was a time-by-group interaction for the Digit Symbol test, with significant improvement only after Adaptive training. In addition, the magnitude of the intervention effect was similar at both sites. CONCLUSION: Home-based CCT Adaptive WM training appears more effective than Non-Adaptive training in older adults from different cultural backgrounds. We present evidence of improvement in trained tasks and on a demanding untrained task dependent upon WM and processing speed. The benefits over the active control group suggest that the Adaptive CCT gains were linked to providing a continuously challenging level of WM difficulty.

Concordance Between Cerebrospinal Fluid Biomarkers with Alzheimer's Disease Pathology Between Three Independent Assay Platforms. - Doecke, James D; Rembach, Alan; Villemagne, Victor L; Varghese, Shiji; Rainey-Smith, Stephanie; Sarros, Shannon; Evered, Lisbeth A; Fowler, Christopher J; Pertile, Kelly K; Rumble, Rebecca L; Trounson, Brett; Taddei, Kevin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: To enhance the accuracy of clinical diagnosis for Alzheimer's disease (AD), pre-mortem biomarkers have become increasingly important for diagnosis and for participant recruitment in disease-specific treatment trials. Cerebrospinal fluid (CSF) biomarkers provide a low-cost alternative to positron emission tomography (PET) imaging for in vivo quantification of different AD pathological hallmarks in the brains of affected subjects; however, consensus around the best platform, most informative biomarker and correlations across different methodologies are controversial. OBJECTIVE: Assessing levels of Aβ-amyloid and tau species determined using three different versions of immunoassays, the current study explored the ability of CSF biomarkers to predict PET Aβ-amyloid (32 Aβ-amyloid-and 45 Aβ-amyloid+), as well as concordance between CSF biomarker levels and PET Aβ-amyloid imaging. METHODS: Prediction and concordance analyses were performed using a sub-cohort of 77 individuals (48 healthy controls, 15 with mild cognitive impairment, and 14 with AD) from the Australian Imaging Biomarker and Lifestyle study of aging. RESULTS: Across all three platforms, the T-tau/Aβ42 ratio biomarker had modestly higher correlation with SUVR/BeCKeT (ρ= 0.69-0.8) as compared with Aβ42 alone (ρ= 0.66-0.75). Differences in CSF biomarker levels between the PET Aβ-amyloid-and Aβ-amyloid+ groups were strongest for the Aβ42/Aβ40 and T-tau/Aβ42 ratios (p < 0.0001); however, comparison of predictive models for PET Aβ-amyloid showed no difference between Aβ42 alone and the T-tau/Aβ42 ratio. CONCLUSION: This study confirms strong concordance between CSF biomarkers and PET Aβ-amyloid status is independent of immunoassay platform, supporting their utility as biomarkers in clinical practice for the diagnosis of AD and for participant enrichment in clinical trials.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Female; Humans; Male; Mental Status Schedule; Peptide Fragments; Positron-Emission Tomography; ROC Curve; tau Proteins

A Decade of Blood Biomarkers for Alzheimer's Disease Research: An Evolving Field, Improving Study Designs, and the Challenge of Replication. - Shi, Liu; Baird, Alison L; Westwood, Sarah; Hye, Abdul; Dobson, Richard; Thambisetty, Madhav; Lovestone, Simon (J Alzheimers Dis, 2018)
Blood-based biomarkers represent a less invasive and potentially cheaper approach for aiding Alzheimer's disease (AD) detection compared with cerebrospinal fluid and some neuroimaging biomarkers. Acknowledging that many in the field have made great progress, here we review some of the work that our group has pursued to identify and validate blood-based proteomic biomarkers through both case control and AD pathology endophenotype-based approaches. Our focus is primarily to identify a minimally invasive and hopefully cost-effective blood-based biomarker to reduce screen failure in clinical trials where participants have prodromal or even pre-clinical disease. We summarize some of the key findings and approaches taken in these biomarker studies, while addressing the main challenges, including that of limited replication in the field, and discuss opportunities for biomarker development.

Deep Brain Stimulation Targeting the Fornix for Mild Alzheimer Dementia (the ADvance Trial): A Two Year Follow-up Including Results of Delayed Activation. - Leoutsakos, Jeannie-Marie S; Yan, Haijuan; Anderson, William S; Asaad, Wael F; Baltuch, Gordon; Burke, Anna; Chakravarty, M Mallar; Drake, Kristen E; Foote, Kelly D; Fosdick, Lisa; Giacobbe, Peter; Mari, Zoltan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Given recent challenges in developing new treatments for Alzheimer dementia (AD), it is vital to explore alternate treatment targets, such as neuromodulation for circuit dysfunction. We previously reported an exploratory Phase IIb double-blind trial of deep brain stimulation targeting the fornix (DBS-f) in mild AD (the ADvance trial). We reported safety but no clinical benefits of DBS-f versus the delayed-on (sham) treatment in 42 participants after one year. However, secondary post hoc analyses of the one-year data suggested a possible DBS-f benefit for participants≥65 years. OBJECTIVE: To examine the long-term safety and clinical effects of sustained and delayed-on DBS-f treatment of mild AD after two years. METHODS: 42 participants underwent implantation of DBS-f electrodes, with half randomized to active DBS-f stimulation (early on) for two years and half to delayed-on (sham) stimulation after 1 year to provide 1 year of active DBS-f stimulation (delayed on). We evaluated safety and clinical outcomes over the two years of the trial. RESULTS: DBS-f had a favorable safety profile with similar rates of adverse events across both trial phases (years 1 and 2) and between treatment arms. There were no differences between treatment arms on any primary clinical outcomes. However, post-hoc age group analyses suggested a possible benefit among older (>65) participants. CONCLUSION: DBS-f was safe. Additional study of mechanisms of action and methods for titrating stimulation parameters will be needed to determine if DBS has potential as an AD treatment. Future efficacy studies should focus on patients over age 65.

Deficits in Regional Cerebral Blood Flow on Brain SPECT Predict Treatment Resistant Depression. - Amen, Daniel G; Taylor, Derek V; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2018)
BACKGROUND: Depression remains an important risk factor for Alzheimer's disease, yet few neuroimaging biomarkers are available to identify treatment response in depression. OBJECTIVE: To analyze and compare functional perfusion neuroimaging in persons with treatment resistant depression (TRD) compared to those experiencing full remission. METHODS: A total of 951 subjects from a community psychiatry cohort were scanned with perfusion single photon emission computed tomography (SPECT) of the brain in both resting and task related settings. Of these, 78% experienced either full remission (n = 506) or partial remission (n = 237) and 11% were minimally responsive (n = 103) or non-responsive (11%. n = 106). Severity of depression symptoms were used to define these groups with changes in the Beck Depression Inventory prior to and following treatment. Voxel-based analyses of brain SPECT images from full remission compared to the worsening group was conducted with the statistical parametric mapping software, version 8 (SPM 8). Multiple comparisons were accounted for with a false discovery rate (p < 0.001). RESULTS: Persons with depression that worsened following treatment had reduced cerebral perfusion compared to full remission in the multiple regions including the bilateral frontal lobes, right hippocampus, left precuneus, and cerebellar vermis. Such differences were observed on both resting and concentration SPECT scans. CONCLUSION: Our findings identify imaging-based biomarkers in persons with depression related to treatment response. These findings have implications in understanding both depression to prognosis and its role as a risk factor for dementia.

Delirium Severity Post-Surgery and its Relationship with Long-Term Cognitive Decline in a Cohort of Patients without Dementia. - Vasunilashorn, Sarinnapha M; Fong, Tamara G; Albuquerque, Asha; Marcantonio, Edward R; Schmitt, Eva M; Tommet, Douglas; Gou, Yun; Travison, Thomas G; Jones, Richard N; Inouye, Sharon K (J Alzheimers Dis, 2018)
BACKGROUND: Delirium has been associated with more rapid cognitive decline. However, it is unknown whether increased delirium severity is associated with a higher rate of long-term cognitive decline. OBJECTIVE: To evaluate delirium severity and the presence and rate of cognitive decline over 36 months following surgery. METHODS: We examined patients from the Successful Aging after Elective Surgery Study, who were age ≥70 years undergoing major elective surgery (N = 560). Delirium severity was determined by the peak Confusion Assessment Method-Severity (CAM-S) score for each patient's hospitalization and grouped based on the sample distribution: scores of 0-2, 3-7, and 8-19. A neuropsychological composite, General Cognitive Performance (GCP), and proxy-reported Informant Questionnaire for Cognitive Decline (IQCODE) were used to examine cognitive outcomes following surgery at 0, 1, and 2 months, and then every 6 months for up to 3 years. RESULTS: No significant cognitive decline was observed for patients with peak CAM-S scores 0-2 (-0.17 GCP units/year, 95% confidence interval [CI] -0.35, 0.01). GCP scores decreased significantly in the group with peak CAM-S scores 3-7 (-0.30 GCP units/year, 95% CI -0.51, -0.09), and decreased almost three times faster in the highest delirium severity group (peak CAM-S scores 8-19; -0.82 GCP units/year, 95% CI -1.28, -0.37). A similar association was found for delirium severity and the proportion of patients who developed IQCODE impairment over time. CONCLUSION: Patients with the highest delirium severity experienced the greatest rate of cognitive decline, which exceeds the rate previously observed for patients with dementia, on serial neuropsychological testing administered over 3 years, with a dose-response relationship between delirium severity and long-term cognitive decline.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Delirium; Elective Surgical Procedures; Female; Humans; Male; Neuropsychological Tests; Postoperative Complications; Severity of Illness Index

Dementia Care Competence Among Care Professionals and Reduced Challenging Behavior of Home-Dwelling Persons with Dementia: A Pre- and Post-Intervention Data Analysis. - Nakanishi, Miharu; Hirooka, Kayo; Imai, Yasuaki; Inoue, Shintaro; Yukari, Yukio; Katayama, Chie; Miyamoto, Yuki; Shindo, Yumi; Ueno, Hideki; Toya, Junichiro; Takano, Yosuke; Nishida, Atsushi (J Alzheimers Dis, 2018)
BACKGROUND: We developed a psychosocial dementia care program to help care managers and professional caregivers manage challenging behavior in home-dwelling persons with dementia in Japan. The program consists of a web-based tool for ongoing monitoring and assessment for challenging behavior, and multi-agency discussion meetings. Results of a cluster-randomized controlled trial indicate a reduction in challenging behavior through this program. OBJECTIVES: The present study aimed to identify a key component of the developed program that is associated with a reduction in challenging behavior. METHODS: We used consecutive data of the intervention and examined the association between challenging behavior in home-dwelling persons with dementia, professionals' competence, and the frequency of revision of action plans. Challenging behavior was assessed using the total score of the Neuropsychiatric Inventory. A baseline and follow-up questionnaire was completed by care professionals using a Japanese version of the Sense of Competence in Dementia Care Staff scale. RESULTS: A total of 86 care professionals completed a 6-month intervention with 219 persons with dementia. The 86 care professionals significantly improved in their dementia care competence. Challenging behavior was significantly reduced among the 219 persons with dementia at follow-up regardless of the level of professionals' competence or the frequency of revision of action plans. Less pain was significantly related to the lower levels of challenging behavior. CONCLUSION: The ongoing multi-agency discussion meetings, with a focus on challenging behavior, may have been the key component in the psychosocial dementia care program. Pain management should be emphasized in action plans for challenging behavior.

Depression and Alzheimer's Disease Biomarkers Predict Driving Decline. - Babulal, Ganesh M; Chen, Suzie; Williams, Monique M; Trani, Jean-Francois; Bakhshi, Parul; Chao, Grace L; Stout, Sarah H; Fagan, Anne M; Benzinger, Tammie L S; Holtzman, David M; Morris, John C; Roe, Catherine M (J Alzheimers Dis, 2018)
BACKGROUND: Symptomatic Alzheimer's disease (AD) and depression independently increase crash risk. Additionally, depression is both a risk factor for and a consequence of AD. OBJECTIVE: To examine whether a depression diagnosis, antidepressant use, and preclinical AD are associated with driving decline among cognitively normal older adults. METHODS: Cognitively normal participants, age ≥65, were enrolled. Cox proportional hazards models evaluated whether a depression diagnosis, depressive symptoms (Geriatric Depression Scale), antidepressant use, cerebrospinal fluid (amyloid-β42 [Aβ42], tau, phosphorylated tau181 [ptau181]), and amyloid imaging biomarkers (Pittsburgh Compound B and Florbetapir) were associated with time to receiving a rating of marginal/fail on a road test. Age was adjusted for in all models. RESULTS: Data were available from 131 participants with age ranging from 65.4 to 88.2 years and mean follow up of 2.4 years (SD = 1.0). A depression diagnosis was associated with a faster time to receiving a marginal/fail rating on a road test and antidepressant use (p = 0.024, HR = 2.62). Depression diagnosis and CSF and amyloid PET imaging biomarkers were associated with driving performance on the road test (p≤0.05, HR = 2.51-3.15). In the CSF ptau181 model, depression diagnosis (p = 0.031, HR = 2.51) and antidepressant use (p = 0.037, HR = 2.50) were statistically significant predictors. There were no interaction effects between depression diagnosis, antidepressant use, and biomarker groups. Depressive symptomology was not a statistically significant predictor of driving performance. CONCLUSIONS: While, as previously shown, preclinical AD alone predicts a faster time to receiving a marginal/fail rating, these results suggest that also having a diagnosis of depression accelerates the onset of driving problems in cognitively normal older adults.

Development of a High-Sensitivity Method for the Measurement of Human Nasal Aβ42, Tau, and Phosphorylated Tau. - Liu, Ziyi; Kameshima, Naoko; Nanjo, Toshifumi; Shiino, Akihiko; Kato, Tomoko; Shimizu, Shino; Shimizu, Takeshi; Tanaka, Sachiko; Miura, Katsuyuki; Tooyama, Ikuo (J Alzheimers Dis, 2018)
Cost-effective and feasible methods for early diagnosis of Alzheimer's disease (AD) are needed. We present two methods to measure AD-related biomarkers simultaneously from one nasal smear for the purpose of diagnosing AD. Japanese men and women aged 63-85 years old were recruited in 2015-2016 for this case-control study. A total of 25 AD cases and 25 controls (22 men and 28 women) participated in this research. Nasal smears were collected from the common nasal meatus, inferior concha, middle nasal meatus, and olfactory cleft, and the proteins in the samples were analyzed by two methods, which we named PGD (Pre-treatment with guanidine- n-Dodecyl-beta-D-maltoside solution) method 1 (PGD-I) and 2 (PGD-II). The PGD-I method measured total tau and amyloid-β (Aβ)42, but no differences in median levels of total tau and Aβ42 between AD cases and controls were found in any of the nasal locations. The PGD-II method measured Aβ42, total tau, and phosphorylated tau, but levels of Aβ40 in all nasal locations of both groups were near zero. Median levels of phosphorylated tau to total tau (p-tau/t-tau) ratios in the middle nasal meatus and in the olfactory cleft were significantly higher in AD cases than in controls, and could significantly predict AD. To assess diagnostic reliability, areas under the ROC curve were 0.74 (95% CL = 0.52-0.95, p = 0.030) for the middle nasal meatus and 0.72 (95% CL = 0.52-0.92, p = 0.029) for the olfactory cleft. Thus, PGD-I and PGD-II can detect AD-related biomarkers in nasal smears and PGD-II may be a useful tool for diagnosing AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Female; Humans; Male; Middle Aged; Nasal Mucosa; Peptide Fragments; Phosphorylation; Reproducibility of Results; ROC Curve; tau Proteins

Diagnosis of Mild Cognitive Impairment Due to Alzheimer's Disease with Transcranial Magnetic Stimulation. - Padovani, Alessandro; Benussi, Alberto; Cantoni, Valentina; Dell'Era, Valentina; Cotelli, Maria Sofia; Caratozzolo, Salvatore; Turrone, Rosanna; Rozzini, Luca; Alberici, Antonella; Altomare, Daniele; Depari, Alessandro; Flammini, Alessandra; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Considering the increasing evidence that disease-modifying treatments for Alzheimer's disease (AD) must be administered early in the disease course, the development of diagnostic tools capable of accurately identifying AD at early disease stages has become a crucial target. In this view, transcranial magnetic stimulation (TMS) has become an effective tool to discriminate between different forms of neurodegenerative dementia. OBJECTIVE: To determine whether a TMS multi-paradigm approach can be used to correctly identify mild cognitive impairment (MCI) due to AD (AD MCI). METHODS: A sample of 69 subjects with MCI were included and classified as AD MCI or MCI unlikely due to AD (non-AD MCI) based on 1) extensive neurological and neuropsychological evaluation, 2) MRI imaging, and 3) cerebrospinal fluid analysis or/and amyloid PET imaging. A paired-pulse TMS multi-paradigm approach assessing short interval intracortical inhibition-facilitation (SICI-ICF), dependent on GABAergic and glutamatergic intracortical circuits, respectively, and short latency afferent inhibition (SAI), dependent on cholinergic circuits, was performed. RESULTS: We observed a significant impairment of SAI and unimpaired SICI and ICF in AD MCI as compared to non-AD MCI. According to ROC curve analysis, the SICI-ICF / SAI index differentiated AD MCI from non-AD MCI with a specificity of 87.9% and a sensitivity of 94.4%. CONCLUSIONS: The assessment of intracortical connectivity with TMS could aid in the characterization of MCI subtypes, correctly identifying AD pathophysiology. TMS can be proposed as an adjunctive, non-invasive, inexpensive, and time-saving screening tool in MCI differential diagnosis.

Diagnostic Value of Diffusion Tensor Imaging and Positron Emission Tomography in Early Stages of Frontotemporal Dementia. - Krämer, Julia; Lueg, Gero; Schiffler, Patrick; Vrachimis, Alexis; Weckesser, Matthias; Wenning, Christian; Pawlowski, Matthias; Johnen, Andreas; Teuber, Anja; Wersching, Heike; Meuth, Sven G; Duning, Thomas (J Alzheimers Dis, 2018)
BACKGROUND: Due to suboptimal sensitivity and specificity of structural and molecular neuroimaging tools, the diagnosis of behavioral variant frontotemporal dementia (bvFTD) remains challenging. OBJECTIVE: Investigation of the sensitivity of diffusion tensor imaging (DTI) and fluorodeoxyglucose positron emission tomography (FDG-PET) to detect cerebral alterations in early stages of bvFTD despite inconspicuous conventional MRI. METHODS: Thirty patients with early stages of bvFTD underwent a detailed neuropsychological examination, cerebral 3T MRI with DTI analysis, and FDG-PET. After 12 months of follow-up, all patients finally fulfilled the diagnosis of bvFTD. Individual FDG-PET data analyses showed that 20 patients exhibited a "typical" pattern for bvFTD with bifrontal and/or temporal hypometabolism (bvFTD/PET+), and that 10 patients showed a "non-typical"/normal pattern (bvFTD/PET-). DTI data were compared with 42 healthy controls in an individual and voxel-based group analysis. To examine the clinical relevance of the findings, associations between pathologically altered voxels of DTI or FDG-PET results and behavioral symptoms were estimated by linear regression analyses. RESULTS: DTI voxel-based group analyses revealed microstructural degeneration in bifrontal and bitemporal areas in bvFTD/PET+ and bvFTD/PET- groups. However, when comparing the sensitivity of individual DTI data analysis with FDG-PET, DTI appeared to be less sensitive. Neuropsychological symptoms were considerably related to neurodegeneration within frontotemporal areas identified by DTI and FDG-PET. CONCLUSION: DTI seems to be an interesting tool for detection of functionally relevant neurodegenerative alterations in early stages of bvFTD, even in bvFTD/PET- patients. However, at a single subject level, it seems to be less sensitive than FDG-PET. Thus, improvement of individual DTI analysis is necessary.

Differences in Synaptic Dysfunction Between rTg4510 and APP/PS1 Mouse Models of Alzheimer's Disease. - Gelman, Simon; Palma, Jonathan; Tombaugh, Geoffrey; Ghavami, Afshin (J Alzheimers Dis, 2018)
Genetically modified mice have provided insights into the progression and pathology of Alzheimer's disease (AD). Here, we have examined two mouse models of AD: the rTg4510 mouse, which overexpresses mutant human Tau gene, and the APP/PS1 mouse, which overexpresses mutant human genes for amyloid precursor protein and presenilin 1. Both models exhibit deficits in hippocampal function, but comparative analyses of these deficits are sparse. We used extracellular field potential recordings in hippocampal slices to study basal synaptic transmission (BST), paired-pulse facilitation (PPF), and long-term potentiation (LTP) at the Schaffer collateral-CA1 pyramidal cell synapses in both models. We found that 6-7, but not 2-3-month-old rTg4510 mice exhibited reduced pre-synaptic activation (fiber volley (FV) amplitude, ∼50%) and field excitatory post-synaptic potential (fEPSP) slope (∼40%) compared to wild-type controls. In contrast to previous reports, BST, when controlled for FV amplitude, was not altered in rTg4510. APP/PS1 mice (2-3 mo and 8-10 mo) had unchanged FV amplitude compared to wild-type controls, while fEPSP slope was reduced by ∼34% in older mice, indicating a deficit in BST. PPF was unchanged in 8-10-month-old APP/PS1 mice, but was reduced in 6-7-month-old rTg4510 mice. LTP was reduced only in older rTg4510 and APP/PS1 mice. Our data suggest that BST deficits appear earlier in APP/PS1 than in rTg4510, which exhibited no BST deficits at the ages tested. However, FV and synaptic plasticity deficits developed earlier in rTg4510. These findings highlight fundamental differences in the progression of synaptic pathology in two genetically distinct models of AD.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Biophysics; Disease Models, Animal; Electric Stimulation; Excitatory Postsynaptic Potentials; Hippocampus; Humans; Mice; Mice, Transgenic; Mutation; Presenilin-1; Synapses; Synaptic Transmission; tau Proteins

Different Abnormalities of Cortical Neural Synchronization Mechanisms in Patients with Mild Cognitive Impairment due to Alzheimer's and Chronic Kidney Diseases: An EEG Study. - Lizio, Roberta; Babiloni, Claudio; Del Percio, Claudio; Losurdo, Antonia; Vernò, Lucia; De Tommaso, Marina; Montemurno, Anna; Dalfino, Giuseppe; Cirillo, Pietro; Soricelli, Andrea; Ferri, Raffaele; Noce, Giuseppe; et al. (J Alzheimers Dis, 2018)
This study tested whether resting state alpha rhythms (8-13 Hz) may characterize mild cognitive impairment due to Alzheimer's disease (ADMCI) compared with MCI due to chronic kidney disease (CKDMCI). Clinical and resting state eyes-closed electroencephalographic (rsEEG) rhythms from 40 ADMCI, 29 CKDMCI, and 45 cognitively normal elderly (Nold) subjects were available in a national archive. Age, gender, and education were matched in the three groups, and Mini-Mental State Evaluation (MMSE) score was paired in the ADMCI and CKDMCI groups. Delta (<4 Hz), theta (4-8 Hz), alpha 1 (8-10.5 Hz), alpha 2 (10.5-13 Hz), beta 1 (13-20 Hz), beta 2 (20-30 Hz), and gamma (30-40 Hz) cortical sources were estimated by eLORETA freeware and classified across individuals by area under the receiver operating characteristic curve (AUROCC). Compared with Nold group, posterior alpha 1 source activities were more reduced in ADMCI than CKDMCI group. In contrast, widespread delta source activities were greater in CKDMCI than ADMCI group. These source activities correlated with the MMSE score and correctly classified between Nold and all MCI individuals (AUROCC = 0.8-0.85) and between ADMCI and CKDMCI subjects (AUROCC = 0.75). These results suggest that early AD affects cortical neural synchronization at alpha frequencies underpinning brain arousal and low vigilance in the quiet wakefulness. In contrast, CKD may principally affect cortical neural synchronization at the delta frequencies. Future prospective cross-validation studies will have to test these candidate rsEEG markers for clinical applications and drug discovery.

Differential Effect of APOE ɛ4 Status and Elevated Pulse Pressure on Functional Decline in Cognitively Normal Older Adults. - Werhane, Madeleine L; Thomas, Kelsey R; Edmonds, Emily C; Bangen, Katherine J; Tran, My; Clark, Alexandra L; Nation, Daniel A; Gilbert, Paul E; Bondi, Mark W; Delano-Wood, Lisa (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: The APOE ɛ4 allele and increased vascular risk have both been independently linked to cognitive impairment and dementia. Since few studies have characterized how these risk factors affect everyday functioning, we investigated the relationship between APOE ɛ4 genotype and elevated pulse pressure (PP) on functional change in cognitively normal participants from the Alzheimer's Disease Neuroimaging Initiative (ADNI). METHODS: 738 normally aging participants underwent APOE genotyping, and baseline PP was calculated from blood pressure indices. The Functional Activities Questionnaire (FAQ) was completed by participants' informant at baseline and 6, 12, 24, 36, and 48-month follow-up visits. Multiple linear regression and multilevel modeling were used to examine the effects of PP and APOE ɛ4 genotype on cross-sectional and longitudinal FAQ scores, respectively. RESULTS: Adjusting for demographic and clinical covariates, results showed that both APOE ɛ4 status and elevated PP predicted greater functional difficulty trajectories across four years of follow-up. Interestingly, however, elevated PP was associated with greater functional decline over time in ɛ4 non-carriers versus carriers. CONCLUSION: Results show that, although APOE ɛ4 status is the prominent predictor of functional difficulty for ɛ4 carriers, an effect of arterial stiffening on functional difficulty was observed in non-carriers. Future studies are needed in order to clarify the etiology of the association between PP and different brain aging processes, and further explore its utility as a marker of dementia risk. The present study underscores the importance of targeting modifiable risk factors such as elevated PP to prevent or slow functional decline and pathological brain aging.

Distinct Neuroanatomical Correlates of Neuropsychiatric Symptoms in the Three Main Forms of Genetic Frontotemporal Dementia in the GENFI Cohort. - Sellami, Leila; Bocchetta, Martina; Masellis, Mario; Cash, David M; Dick, Katrina M; van Swieten, John; Borroni, Barbara; Galimberti, Daniela; Tartaglia, Maria Carmela; Rowe, James B; Graff, Caroline; Tagliavini, Fabrizio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The overlap between frontotemporal dementia (FTD) and primary psychiatric disorders has been brought to light by reports of prominent neuropsychiatric symptoms (NPS) in FTD-related genetic mutations, particularly among C9orf72 and GRN carriers. It has been recently demonstrated that early neuroanatomical changes in genetic FTD may be different across the major disease-causing mutations. OBJECTIVE: We aimed to identify whether NPS could be driven by distinct structural correlates. METHODS: One hundred and sixty-seven mutation carriers (75 GRN, 60 C9orf72, and 32 MAPT) were included from the Genetic FTD Initiative (GENFI) study, a large international cohort of genetic FTD. Neuropsychiatric symptoms including delusions, hallucinations (visual, auditory, and tactile), depression, and anxiety were investigated using a structured interview. Voxel-based morphometry was performed to identify neuroanatomical correlates of NPS. RESULTS: Psychotic symptoms correlated mainly with grey matter (GM) atrophy in the anterior insula, left thalamus, cerebellum, and cortical regions including frontal, parietal, and occipital lobes in GRN mutations carriers. GM atrophy in posterior structures of the default-mode network was associated with anxiety in the GRN group. Delusions in C9orf72 expansion carriers were mainly associated with left frontal cortical atrophy. Cerebellar atrophy was found to be correlated only with anxiety in C9orf72 carriers. NPS in the MAPT group were mainly associated with volume loss in the temporal lobe. CONCLUSION: Neuroanatomical correlates of NPS appear to be distinct across the main forms of genetic FTD. Overall, our findings support overlapping brain structural changes between FTD and primary psychiatric disorders.

Distinct White Matter Changes Associated with Cerebrospinal Fluid Amyloid-β1-42 and Hypertension. - Al-Janabi, Omar M; Brown, Christopher A; Bahrani, Ahmed A; Abner, Erin L; Barber, Justin M; Gold, Brian T; Goldstein, Larry B; Murphy, Ronan R; Nelson, Peter T; Johnson, Nathan F; Shaw, Leslie M; Smith, Charles D; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) pathology and hypertension (HTN) are risk factors for development of white matter (WM) alterations and might be independently associated with these alterations in older adults. OBJECTIVE: To evaluate the independent and synergistic effects of HTN and AD pathology on WM alterations. METHODS: Clinical measures of cerebrovascular disease risk were collected from 62 participants in University of Kentucky Alzheimer's Disease Center studies who also had cerebrospinal fluid (CSF) sampling and MRI brain scans. CSF Aβ1-42 levels were measured as a marker of AD, and fluid-attenuated inversion recovery imaging and diffusion tensor imaging were obtained to assess WM macro- and microstructural properties. Linear regression analyses were used to assess the relationships among WM alterations, cerebrovascular disease risk, and AD pathology. Voxelwise analyses were performed to examine spatial patterns of WM alteration associated with each pathology. RESULTS: HTN and CSF Aβ1-42 levels were each associated with white matter hyperintensities (WMH). Also, CSF Aβ1-42 levels were associated with alterations in normal appearing white matter fractional anisotropy (NAWM-FA), whereas HTN was marginally associated with alterations in NAWM-FA. Linear regression analyses demonstrated significant main effects of HTN and CSF Aβ1-42 on WMH volume, but no significant HTN×CSF Aβ1-42 interaction. Furthermore, voxelwise analyses showed unique patterns of WM alteration associated with hypertension and CSF Aβ1-42. CONCLUSION: Associations of HTN and lower CSF Aβ1-42 with WM alteration were statistically and spatially distinct, suggesting independent rather than synergistic effects. Considering such spatial distributions may improve diagnostic accuracy to address each underlying pathology.

Distribution of Cerebrospinal Fluid Biomarker Profiles in Patients Explored for Cognitive Disorders. - Paquet, Claire; Bouaziz-Amar, Elodie; Cognat, Emmanuel; Volpe-Gillot, Lisette; Haddad, Victor; Mahieux, Florence; Dekimeche, Siham; Defontaines, Benedicte; Chabriat, Hugues; Belin, Catherine; Texeira, Antonio; Goutagny, Stephane; et al. (J Alzheimers Dis, 2018)
BACKGROUND: CSF Alzheimer's disease (AD) biomarkers allow classifying individuals based on their levels of amyloid and neurodegeneration pathologies. OBJECTIVE: To investigate the distribution of AD biomarker profiles from patients suffering from cognitive disorders. METHODS: We analyzed 3001 patients with cognitive disorders and referred by 18 French memory clinics located in and around Paris. Patients were classified as normal, amyloidosis (A+/N-), amyloidosis and neurodegeneration (A+/N+) or suspected non-AD pathophysiology (SNAP), according to their CSF levels of biomarkers. Analysis were performed for the overall population and stratified by gender, age quintiles, and Mini-Mental State Examination (MMSE) score quintiles. Results were compared to previous findings in cohorts of healthy elderly adults. RESULTS: 37% of the sample were classified as A+/N+, 22% were classified A+/N-, and 15% as SNAP. The A+/N+ profile was associated with female gender, advanced age, and lower MMSE score, while the A+/N-profile was observed more frequently in men and the distribution was stable across age and MMSE. The SNAP profile showed no association with gender or age, was less frequent in patients with lower MMSE, and had a lower repartition than the one previously reported in asymptomatic populations. CONCLUSIONS: While A+/N+ patients had the clinical characteristics typically observed in AD, A+/N-patients had a different epidemiological pattern (higher frequency in men, no association with advanced age or lower MMSE). The SNAP profile was less frequent than previously reported in the general elderly population, suggesting that this profile is not a frequent cause of memory impairment in this population.

DJ-1 Suppresses Cytoplasmic TDP-43 Aggregation in Oxidative Stress-Induced Cell Injury. - Lei, Yang; Zhang, Zhi-Feng; Lei, Rui-Xue; Wang, Shu; Zhuang, Yang; Liu, An-Chun; Wu, Yan; Chen, Juan; Tang, Jun-Chun; Pan, Meng-Xian; Liu, Rui; Liao, Wei-Jing; et al. (J Alzheimers Dis, 2018)
DJ-1 (also called PARK7) is a multifunctional redox-sensitive protein that is protective against oxidative stress-induced cell death. TAR DNA-binding protein 43 (TDP-43) is a major protein component of pathological inclusions in amyotrophic lateral sclerosis and frontotemporal dementia. Reducing aberrant aggregation of TDP-43 is a potential approach to prevent cell death. To investigate whether DJ-1 might inhibit TDP-43 aggregation to exert a protective effect in oxidative stress-induced injury, we tested the protein level and subcellular localization of TDP-43 and DJ-1 in SH-SY5Y cells transfected with wild-type DJ-1, DJ-1 mutant (L166P) cDNA, or DJ-1 siRNA. We show that oxidative stress induced by paraquat leads to the formation of cytosolic TDP-43 aggregation in SH-SY5Y cells. DJ-1 overexpression decreases paraquat-induced cytoplasmic accumulation of TDP-43 in SH-SY5Y cells and protects against paraquat-induced cell death. Transfection of DJ-1 L166P mutant or DJ-1 siRNA leads to increased cytosolic aggregation of TDP-43 in paraquat-treated SH-SY5Y cells and promotes cell death. These data suggest that DJ-1 may protect against oxidative stress-induced cell death through the suppression of cytoplasmic TDP-43 aggregation.

Do Cardiometabolic Risk Factors Influence Amyloid, Tau, and Neuronal Function in APOE4 Carriers and Non-Carriers in Alzheimer's Disease Trajectory? - Femminella, Grazia Daniela; Taylor-Davies, Genevieve; Scott, James; Edison, Paul (J Alzheimers Dis, 2018)
Cardiovascular risk could be calculated using Qrisk2. It is suggested that cardiovascular risk factors influence the progression of Alzheimer's disease (AD). However, studies have not specifically evaluated the influence of cardiovascular risk using Qrisk2 on neuropathological progression and AD biomarkers. The aim of the study was to evaluate the influence of cardiovascular risk factors using Qrisk2 on CSF amyloid-β (Aβ) and tau, 18F-AV45-PET, 18F-FDG-PET, MRI, and cognitive measures in APOE4 negative cognitively normal and mild cognitive impairment (MCI) subjects. 614 cognitively normal, early, and late MCI subjects were selected from the ADNI cohort with a 2-year follow-up. CSF Aβ and tau, 18F-AV45-PET, 18F-FDG-PET, MRI, and cognitive measures along with modified Qrisk2 were evaluated. APOE4 non-carrier, high cardiovascular risk sub-group of early and late MCI and cognitively normal subjects, demonstrated worse biomarker and cognitive profile at baseline and during follow up compared to low cardiovascular risk group. Additionally, similar pattern was also observed in APOE4 carriers. We demonstrated that Qrisk2 and APOE4 were independent predictors of biomarker and clinical progression in AD trajectory. High cardiovascular risk is associated with biomarker changes in APOE4 non-carriers in prodromal AD, which may suggest that treatment of cardiovascular risk is an effective prevention strategy even in APOE4 negative subjects and may influence disease progression independent of amyloid pathology. Demonstration of accelerated neuropathological changes in both APOE4 carriers and non-carriers suggest that focusing on modifiable cardiovascular risk factors is an effective preventative strategy while we eagerly waiting for new treatments.

The Down-Expression of ACE and IDE Exacerbates Exogenous Amyloid-β Neurotoxicity in CB2R-/- Mice. - Wang, Lin; Shi, Fang-Xiao; Xu, Wei-Qi; Cao, Yun; Li, Na; Li, Man; Wang, Qun; Wang, Jian-Zhi; Tian, Qing; Yu, Li-Kai; Zhou, Xin-Wen (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by neuritic plaques and neurofibrillary tangles. It is reported that enzymatic degradation of amyloid-β (Aβ) plays a pivotal role in Aβ accumulation and type-2 cannabinoid receptor (CB2R) participates in Aβ processing in the brain; however, the underlying mechanisms remain unclear. We determined that Aβ degradation-related proteins are significantly different between CB2R-/- mice and wild-type (WT) mice via proteomic analysis. Moreover, the data demonstrated that the angiotensin converting enzyme (ACE) and insulin-degrading enzyme (IDE) levels are substantially attenuated, and the Aβ level is significantly enhanced in CB2R-/--Aβ1 - 42 mice compared with that of WT-Aβ1 - 42 mice. Furthermore, Aβ-mediated synaptic dysfunction, the loss of memory associated proteins, and the suppression of glutamatergic transmission are more severe in CB2R-/--Aβ1 - 42 mice than that in WT-Aβ1 - 42 mice. CB2R activation could decrease Aβ1 - 40 and Aβ1 - 42 levels and enhance ACE and IDE levels with its selective agonist JWH133; however, AM630 (CB2R antagonist) abrogates all changes induced by JWH133 in N2a cells with AβPP overexpression. Taken together, our study demonstrated that the deletion of CB2R reduces exogenous Aβ degradation and aggravates the toxicity of Aβ via the reduction of ACE and IDE, which suggests that CB2R is involved in the onset of AD and a potential therapeutic target for AD.

Dual Time-Point [18F]Florbetaben PET Delivers Dual Biomarker Information in Mild Cognitive Impairment and Alzheimer's Disease. - Florek, Lisa; Tiepolt, Solveig; Schroeter, Matthias L; Berrouschot, Jörg; Saur, Dorothee; Hesse, Swen; Jochimsen, Thies; Luthardt, Julia; Sattler, Bernhard; Patt, Marianne; Hoffmann, Karl-Titus; Villringer, Arno; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Current research diagnostic criteria for Alzheimer's disease (AD) and mild cognitive impairment (MCI) due to AD include biomarkers to supplement clinical testing. Recently, we demonstrated that dual time-point [18F]FBB PET is able to deliver both blood flow and amyloid-β (Aβ) load surrogates. OBJECTIVE: The aim of this study was to investigate whether these surrogates can be utilized as AD biomarkers. METHODS: 112 subjects (41 with MCI, 50 with probable/possible AD, 21 with other dementias) underwent dual time-point [18F]FBB PET. Data were visually and relative quantitatively (Herholz scores for the early and composite SUVRs for the late PET data) analyzed. RESULTS: In the early images AD-typical patterns were present in 42% /27% /33% of probable/possible AD/MCI/other dementia cases. In late [18F]FBB PET, 42% /29% /38% of probable/possible AD/ MCI/other dementia cases were Aβ-positive. 17% of the MCIs were categorized as "MCI due to AD-high likelihood", 44% of the probable ADs as "probable AD with high evidence of AD pathophysiological process" and 28% of the possible ADs as "possible AD with evidence of AD pathophysiological process". 27% of all subjects showed a positive diagnostic and progression biomarker. Herholz scores were lower (0.85±0.05 versus 0.88±0.04, p = 0.015) for probable/possible AD versus MCI. Composite late phase SUVRs were significantly higher (1.65±0.23 versus 1.15±0.17, p < 0.005) in Aβ-positive versus Aβ-negative patients. Herholz and MMSE scores were positively correlated (R = 0.30 p = 0.006). CONCLUSION: Dual time-point [18F]FBB PET provides dual biomarker information which enables to categorize MCI and AD dementia patients according to established diagnostic criteria. Thus, dual time-point [18F]FBB PET has great potential to supplement diagnostic dementia workups.

Early and Selective Activation and Subsequent Alterations to the Unfolded Protein Response in Down Syndrome Mouse Models. - Lanzillotta, Chiara; Tramutola, Antonella; Meier, Shelby; Schmitt, Frederick; Barone, Eugenio; Perluigi, Marzia; Di Domenico, Fabio; Abisambra, Jose F (J Alzheimers Dis, 2018)
Down syndrome (DS) is the most common chromosomal disorder and the leading genetic cause of intellectual disability in humans, which results from the triplication of chromosome 21. DS individuals have an increased risk of developing Alzheimer's disease (AD)-like pathology and dementia by the age of 40 due to the triplication of several genes involved in the formation of amyloid plaques and tau tangles. Further, DS and AD are characterized by the aberrant accumulation of unfolded/misfolded proteins resulting from over-burdened protein quality control systems. The accumulation of misfolded proteins in the endoplasmic reticulum (ER) triggers a cellular stress response called the unfolded protein response (UPR). Long-term activation of the UPR mediates neuronal dysfunction in AD. We hypothesized that the UPR is impacted in a mouse model of DS. To test this, we performed gene and protein expression analysis of ER stress markers in the Ts65Dn mouse model of DS at 3, 9, and 18 months. We identified activation of the PERK pathway in Ts65Dn DS mice at 3 months of age compared to euploid controls. We also determined that the early and overt UPR activation decreased with age, the UPR signal was significantly reduced by 18 months. Our data suggest that UPR activation in DS mouse models occurs early before consistent brain neurodegeneration and might be an essential contributor to dys-proteostasis.

Early Stage Alterations in CA1 Extracellular Region Proteins Indicate Dysregulation of IL6 and Iron Homeostasis in the 5XFAD Alzheimer's Disease Mouse Model. - Gurel, Busra; Cansev, Mehmet; Sevinc, Cansu; Kelestemur, Seda; Ocalan, Busra; Cakir, Aysen; Aydin, Sami; Kahveci, Nevzat; Ozansoy, Mehmet; Taskapilioglu, Ozlem; Ulus, Ismail Hakki; Başar, Merve Karayel; et al. (J Alzheimers Dis, 2018)
In recent years, an increasing number of research papers revealed that the compositional and volumetric alterations in the extracellular matrix are the consequences of aging and may be related to Alzheimer's disease (AD). In this study, we aimed to demonstrate the alterations in hippocampal extracellular fluid proteins in vivo using the 5XFAD mouse model. Samples were obtained from hippocampi of 5XFAD mice (n = 6) and their non-transgenic littermates by intracerebral push-pull perfusion technique at 3 months of age, representing the pre-pathological stage of the AD. Proteins in the hippocampal perfusates were analyzed by Ultra Performance Liquid Chromatography-Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry (UPLC-ESI-qTOF-MS/MS). 178 proteins were identified and 19 proteins of them were found to be statistically significantly altered (p≤0.05, fold change ≥40%, unique peptide count ≥3) in the hippocampal CA1 extracellular fluid of the 5XFAD mouse model. Ingenuity pathway analysis of the protein expression results identified IL6 as an upstream regulator. The upregulation of IL6 was validated by immunohistochemical staining of the hippocampus and cortex of the 5XFAD mice prior to Aβ plaque formation. Furthermore, the iron level in the hippocampus was measured by inductively coupled plasma-mass spectrometry as IL6 is mentioned in several studies to take part in iron homeostasis and inflammation and found to be increased in 5XFAD mice hippocampus. Alterations in extracellular matrix proteins in addition to increasing amount of hippocampal IL6 and iron in the early stages of AD may reveal inflammation-mediated iron dyshomeostasis in the early stages of neurodegeneration.
Keywords: Alzheimer Disease; Animals; CA1 Region, Hippocampal; Chromatography, Liquid; Disease Models, Animal; Female; Homeostasis; Interleukin-6; Iron; Mice; Mice, Transgenic; Proteomics; Tandem Mass Spectrometry

Effect of Education on Alzheimer's Disease-Related Neuroimaging Biomarkers in Healthy Controls, and Participants with Mild Cognitive Impairment and Alzheimer's Disease: A Cross-Sectional Study. - Wada, Masataka; Noda, Yoshihiro; Shinagawa, Shunichiro; Chung, Jun Ku; Sawada, Kyosuke; Ogyu, Kamiyu; Tarumi, Ryosuke; Tsugawa, Sakiko; Miyazaki, Takahiro; Yamagata, Bun; Graff-Guerrero, Ariel; Mimura, Masaru; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cognitive reserve is the acquired capacity reflecting a functional brain adaptability/flexibility in the context of aging. Educational attainment is thought to be among the most important factors that contribute to cognitive reserve. OBJECTIVE: The aim of this study is to investigate the relationships among duration of education and Alzheimer's disease (AD) related neuroimaging biomarkers such as amyloid-β deposition, glucose metabolism, and brain volumes in each stage of AD. METHODS: We reanalyzed a part of the datasets of the Alzheimer's Disease Neuroimaging Initiative. Participants were between 55 and 90 years of age and diagnosed as one of the following: healthy controls (HC), mild cognitive impairment (MCI), or AD. Multiple regression analyses were conducted to examine the relationships among duration of education and amyloid-β deposition (n = 825), brain metabolism (n = 1,304), and brain volumes (n = 1,606) among three groups using data for 18F-Florbetapir (AV-45) imaging, fludeoxyglucose (FDG) positron emission tomography, and T1-weighted magnetic resonance imaging. RESULTS: Duration of education had no correlations with amyloid-β deposition or brain metabolism in any groups. However, duration of education was positively associated with the total brain volume only in participants with MCI. CONCLUSIONS: Our findings suggest that education may exert a protective effect on total brain volume in the MCI stage but not in HC or AD. Thus, education may play an important role in preventing the onset of dementia through brain reserve in MCI.

Endocytosis and Transcytosis of Amyloid-β Peptides by Astrocytes: A Possible Mechanism for Amyloid-β Clearance in Alzheimer's Disease. - Domínguez-Prieto, Marta; Velasco, Ana; Tabernero, Arantxa; Medina, José M (J Alzheimers Dis, 2018)
Amyloid-β (Aβ) peptides, Aβ40, Aβ42, and recently Aβ25 - 35, have been directly implicated in the pathogenesis of Alzheimer's disease (AD). We have previously shown that all three peptides decrease neuronal viability, but Aβ40 also promotes synaptic disassembling. In this work, we have studied the effects of these peptides on astrocytes in primary culture and found that the three Aβ peptides were internalized by astrocytes and significantly decreased astrocyte viability, while increasing ROS production. Aβ peptide internalization is temperature-dependent, a fact that supports the idea that Aβ peptides are actively endocytosed by astrocytes. However, inhibiting caveolae formation by methyl-beta-cyclodextrin or by silencing caveolin-1 with RNA interference did not prevent Aβ endocytosis, which suggests that Aβ peptides do not use caveolae to enter astrocytes. Conversely, inhibition of clathrin-coated vesicle formation by chlorpromazine or by silencing clathrin with RNA interference significantly decreased Aβ internalization and partially reverted the decrease of astrocyte viability caused by the presence of Aβ. These results suggest that Aβ is endocytosed by clathrin-coated vesicles in astrocytes. Aβ-loaded astrocytes, when co-incubated with non-treated astrocytes in separate wells but with the same incubation medium, promoted cell death in non-treated astrocytes; a fact that was associated with the presence of Aβ inside previously unloaded astrocytes. This phenomenon was inhibited by the presence of chlorpromazine in the co-incubation medium. These results suggest that astrocyte may perform Aβ transcytosis, a process that could play a role in the clearance of Aβ peptides from the brain to cerebrospinal fluid.

Ethical Arguments Concerning the Use of Alzheimer's Disease Biomarkers in Individuals with No or Mild Cognitive Impairment: A Systematic Review and Framework for Discussion. - Smedinga, Marthe; Tromp, Krista; Schermer, Maartje H N; Richard, Edo (J Alzheimers Dis, 2018)
BACKGROUND: The shift to defining Alzheimer's disease (AD) as a biological continuum, which is characterized by the presence of biomarkers instead of clinical symptoms, has sparked a widespread debate. Insight into the given arguments and their underlying moral values is crucial to ensure well-considered and appropriate AD biomarker testing in the future. OBJECTIVE: To critically review the arguments in favor of or against AD biomarker testing in people with no or mild cognitive impairment and to explicate their underlying moral values. METHODS: Seven databases were systematically searched for publications mentioning arguments of interest. Arguments are identified using qualitative data-analysis and evaluated within an ethical framework. RESULTS: Our search yielded 3,657 articles of which 34 met the inclusion criteria. We discuss the clusters of arguments separate from their evaluation and the assessment of the debate as a whole. The right to know, which derives from the moral value of respect for autonomy, is a central argument in favor of biomarker testing. On the other hand, fear of the disease and lack of a disease-modifying treatment may result in a negative balance of good over inflicted harms, which argues against its use. CONCLUSION: Critical evaluation and weighing of the given arguments in a specific context, within an ethical framework, demonstrates the necessity to differentiate between what we hope or expect from research and where we currently stand. While AD biomarkers may have an indispensable value for research, the current advantage for clinical practice appears limited.

Evaluation of Matrix Metalloproteinase-2 (MMP-2) and -9 (MMP-9) and Their Tissue Inhibitors (TIMP-1 and TIMP-2) in Plasma from Patients with Neurodegenerative Dementia. - Tuna, Gamze; Yener, Görsev Gülmen; Oktay, Gülgün; İşlekel, Gül Hüray; Kİrkalİ, Fatoş Güldal (J Alzheimers Dis, 2018)
Matrix metalloproteinases (MMPs) are substantial regulators of learning and memory and might be involved in neurodegeneration. It is known that MMPs are involved in pathogenesis of Alzheimer's disease (AD) and are particularly involved in the amyloid-β processing pathway. However, information on circulating levels of these proteins and their tissue inhibitors (TIMPs) in AD and other neurodegenerative dementia (ND) diseases such as dementia with Lewy bodies (DLB) and frontotemporal dementia (FTD) is not clear. Therefore, this study was directed toward finding out how plasma levels of MMP-2, MMP-9, TIMP-1, and TIMP-2 vary in AD, DLB, and FTD; and investigating the correlation of the levels of MMPs and their inhibitors with clinical parameters of the patients. MMP-2, MMP-9, TIMP-1, and TIMP-2 levels were measured by enzyme linked immunosorbent assay (ELISA). Plasma MMP-2 levels were significantly lower in all the patient groups than in the age-matched healthy controls (HCs) (p < 0.05). MMP-9 levels were significantly lower in the FTD patients than in the HCs (p < 0.05). Also, TIMP-1 levels were lower in the AD and FTD patients than in the HCs (p < 0.05). TIMP-2 levels were similar in all the groups. These findings highlight the importance of circulating MMPs in ND and suggest that MMPs and their inhibitors might play a role in impaired amyloid-β peptide metabolism which is responsible for the genesis and progression of ND. Furthermore, measurement of MMP-2 and MMP-9 and their inhibitors may be of great importance for large scale basic research and clinical studies of ND.

Evolvability of Amyloidogenic Proteins in Human Brain. - Hashimoto, Makoto; Ho, Gilbert; Sugama, Shuei; Takamatsu, Yoshiki; Shimizu, Yuka; Takenouchi, Takato; Waragai, Masaaki; Masliah, Eliezer (J Alzheimers Dis, 2018)
Currently, the physiological roles of amyloidogenic proteins (APs) in human brain, such as amyloid-β and α-synuclein, are elusive. Given that many APs arose by gene duplication and have been resistant against the pressures of natural selection, APs may be associated with some functions that are advantageous for survival of offspring. Nonetheless, evolvability is the sole physiological quality of APs that has been characterized in microorganisms such as yeast. Since yeast and human brain may share similar strategies in coping with diverse range of critical environmental stresses, the objective of this paper was to discuss the potential role of evolvability of APs in aging-associated neurodegenerative disorders, including Alzheimer's disease and Parkinson's disease. Given the heterogeneity of APs in terms of structure and cytotoxicity, it is argued that APs might be involved in preconditioning against diverse stresses in human brain. It is further speculated that these stress-related APs, most likely protofibrillar forms, might be transmitted to offspring via the germline, conferring preconditioning against forthcoming stresses. Thus, APs might represent a vehicle for the inheritance of the acquired characteristics against environmental stresses. Curiously, such a characteristic of APs is reminiscent of Charles Darwin's 'gemmules', imagined molecules of heritability described in his pangenesis theory. We propose that evolvability might be a physiological function of APs during the reproductive stage and neurodegenerative diseases could be a by-product effect manifested later in aging. Collectively, our evolvability hypothesis may play a complementary role in the pathophysiology of APs with the conventional amyloid cascade hypothesis.

Executive and Language Subjective Cognitive Decline Complaints Discriminate Preclinical Alzheimer's Disease from Normal Aging. - Valech, Natalia; Tort-Merino, Adrià; Coll-Padrós, Nina; Olives, Jaume; León, María; Rami, Lorena; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to specify the profile of subjective cognitive decline in preclinical Alzheimer's disease (preAD). OBJECTIVES: To explore specific items of the Subjective Cognitive Decline Questionnaire (SCD-Q) that discriminate preAD from normal aging. METHODS: 68 cognitively normal older adults were classified as controls (n = 52) or preAD (n = 16) according to amyloid-β (Aβ) levels. An exploratory factor analysis and item analysis of the SCD-Q were performed. Informant reports of the SCD-Q were used to corroborate the findings of self-reports. One-year neuropsychological follow-up was available. RESULTS: Four SCD-Q factors were extracted: EM-factor (episodic memory), A-factor (attention), O-factor (organization), and L-factor (language). PreAD reported a significantly higher decline in L-factor (F(1) = 6.49; p = 0.014) and A-factor (F(1) = 4.04; p = 0.049) compared to controls, and showed a higher frequency of perceived decline in SCD-Q items related with language and executive tasks (Sig-items.) Significant discriminative powers for Aβ-positivity were found for L-factor (AUC = 0.75; p = 0.003) and A-factor (AUC = 0.74; p = 0.004). Informants in the preAD group confirmed significantly higher scores in L-factor and Sig-items. A significant time×group interaction was found in the Semantic Fluency and Stroop tests, with the preAD group showing a decrease in performance at one-year. CONCLUSIONS: Our results suggest that SCD-Q items related with language and executive decline may help in prediction algorithms to detect preAD. Validation in an independent population is needed.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Executive Function; Factor Analysis, Statistical; Female; Humans; Language; Male; Middle Aged; Neuropsychological Tests; Self Report

Exercise Training on Locomotion in Patients with Alzheimer's Disease: A Feasibility Study. - Pedrinolla, Anna; Venturelli, Massimo; Fonte, Cristina; Munari, Daniele; Benetti, Maria Vittoria; Rudi, Doriana; Tamburin, Stefano; Muti, Ettore; Zanolla, Luisa; Smania, Nicola; Schena, Federico (J Alzheimers Dis, 2018)
BACKGROUND: Although current literature has shown that patients with Alzheimer's disease (AD) have worse locomotion compared with healthy counterparts, no studies have focused on the efficacy of exercise training in improving gait abnormalities including biomechanics and metabolic aspects, in this population. OBJECTIVE: To verify the effectiveness of exercise training (ET) on gait parameters (i.e., speed, step and stride length, single and double support, and energy cost of walking (Cw)) in patients with AD with respect to a standard cognitive treatment (CT). METHODS: In this study, we included a small portion of data belonging to a larger study (ClinicalTrials.gov number, NCT03034746). Patients with AD (Mini-Mental State Examination 22±5) were included in the study. Gait parameters and Cw were assessed at baseline and after 6 months (72 treatment sessions) of treatment. ET included 90 min of aerobic and strength training. CT included 90 min of cognitive stimuli. RESULTS: The 16 patients assigned to ET exhibited significant improvement of Cw (-0.9±0.1 J/kg·m-1), while differences in gait parameters were negligible. The effect on gait parameters were undetectable in the 18 patients assigned to CT (-0.2±0.5 J/kg·m-1). CONCLUSIONS: Data from this study showed that ET program seems effective in improving Cw in patients with AD. Interestingly, the positive effect of ET on Cw was not coupled with ameliorations of patient's gait parameters, suggesting that the gain of metabolic aspects of locomotion were the main factors responsible for this positive result.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomechanical Phenomena; Exercise Test; Exercise Therapy; Feasibility Studies; Female; Gait; Humans; Italy; Male; Single-Blind Method

Exploring the Role of Cognitive Factors in a New Instrument for Elders' Financial Capacity Assessment. - Giannouli, Vaitsa; Stamovlasis, Dimitrios; Tsolaki, Magda (J Alzheimers Dis, 2018)
BACKGROUND: The influence of cognitive factors on financial capacity across the dementia spectrum of cognitive aging, Alzheimer's disease (AD), and mild cognitive impairment (MCI) has been little investigated, while it has not been investigated at all in other types of dementia as well as in extended samples of elders in Greece. OBJECTIVE: The aim of this study is to investigate financial capacity, to develop a tool, test its psychometric properties, validate, and then test the tool in groups of healthy controls compared to elders with dementia, while examining other facets of their cognitive performance. METHODS: 719 elders from Greece including healthy participants and patients with different types of dementia were examined with Legal Capacity for Property Law Transactions Assessment Scale (LCPLTAS) and a battery of neuropsychological tests concerning various cognitive functions. RESULTS: Significantly different profiles in the scores and subscores of LCPLTAS for all the groups of dementia patients were found, with a general incapacity finding for all the dementia groups including the MCI patients. Logistic regression showed that Mini-Mental State Examination (MMSE), Geriatric Depression Scale, and Trail Making Part B predicted competence on LCPLTAS for the dementia patients. Persons with MCI and dementia had lower financial knowledge scores than those without cognitive impairment, with MMSE scores below 27 suggestive as an indication of financial incapacity. CONCLUSION: The LCPLTAS provides information for a strong positive correlation with MMSE, while the use both of MMSE and LCPLTAS as adequate measures of financial (in)capacity is discussed for the Greek legal procedures regarding elder guardianship cases.

Findings from the Swedish Study on Familial Alzheimer's Disease Including the APP Swedish Double Mutation. - Thordardottir, Steinunn; Graff, Caroline (J Alzheimers Dis, 2018)
This is a brief summary of the findings from the Swedish study on familial Alzheimer's disease (FAD). Similar to other FAD studies, it includes prospective assessments of cognitive function, tissue sampling, and technical analyses such as MRI and PET. This 24-year-old study involves 69 individuals with a 50% risk of inheriting a disease-causing mutation in presenilin 1 (PSEN1 H163Y or I143T), or amyloid precursor protein (the Swedish APP or the arctic APP mutation) who have made a total of 169 visits. Our results show the extraordinary power in this study design to unravel the earliest changes in preclinical AD. The Swedish FAD study will continue and future research will focus on disentangling the order of pathological change using longitudinal data as well as modeling the changes in patient derived cell systems.

Forgetting Rate on the Recency Portion of a Word List Differentiates Mild to Moderate Alzheimer's Disease from Other Forms of Dementi. - Turchetta, Chiara Stella; Perri, Roberta; Fadda, Lucia; Caruso, Giulia; De Simone, Maria Stefania; Caltagirone, Carlo; Carlesimo, Giovanni Augusto (J Alzheimers Dis, 2018)
Patients with Alzheimer's disease (AD) demonstrate a disproportionately larger forgetting rate in episodic memory tasks. Previous studies documented that, in comparison with healthy controls, the increased forgetting manifested by AD patients in word list recall tasks is confined to the recency portion of the list with normal forgetting rates on the primacy and mid-list portions. In this study we compared the primacy, mid-list, and recency ratios, obtained by dividing the immediate and delayed recall of words in position 1-4, 5-11, and 12-15 of a 15-word list, in different groups of demented patients, i.e., AD, frontal variant of frontotemporal dementia (fvFTD), Lewy body disease (LBD), subcortical ischemic vascular dementia (SIVD), and a group of normal controls (NC). The aim was to investigate whether the above reported forgetting pattern would differentiate AD performance from that of other dementia groups. Results of the statistical analysis showed that only the recency ratio differentiated AD from patients in the other dementia groups. Consistently, hierarchical logistic regression analyses demonstrated that the recency ratio discriminated between AD patients and individuals affected by other forms of dementia. In particular, the discrimination power was high in differentiating AD from fvFTD patients but was less accurate in differentiating AD from LBD and SIVD patients. We assume that the increased forgetting in AD patients is due to a deficit in memory consolidation mechanisms (specific to AD) that prevent the terminal items in a list from being transferred from a temporary short-term memory store to a stable long-term memory store.

Fragmentation of the Golgi Apparatus in Neuroblastoma Cells Is Associated with Tau-Induced Ring-Shaped Microtubule Bundles. - Rodríguez-Cruz, Fanny; Torres-Cruz, Francisco Miguel; Monroy-Ramírez, Hugo Christian; Escobar-Herrera, Jaime; Basurto-Islas, Gustavo; Avila, Jesús; Garcia-Sierra, Francisco (J Alzheimers Dis, 2018)
Abnormal fibrillary aggregation of tau protein is a pathological condition observed in Alzheimer's disease and other tauopathies; however, the presence and pathological significance of early non-fibrillary aggregates of tau remain under investigation. In cell and animal models expressing normal or modified tau, toxic effects altering the structure and function of several membranous organelles have also been reported in the absence of fibrillary structures; however, how these abnormalities are produced is an issue yet to be addressed. In order to obtain more insights into the mechanisms by which tau may disturb intracellular membranous elements, we transiently overexpressed human full-length tau and several truncated tau variants in cultured neuroblastoma cells. After 48 h of transfection, either full-length or truncated tau forms produced significant fragmentation of the Golgi apparatus (GA) with no changes in cell viability. Noteworthy is that in the majority of cells exhibiting dispersion of the GA, a ring-shaped array of cortical or perinuclear microtubule (Mt) bundles was also generated under the expression of either variant of tau. In contrast, Taxol treatment of non-transfected cells increased the amount of Mt bundles but not sufficiently to produce fragmentation of the GA. Tau-induced ring-shaped Mt bundles appeared to be well-organized and stable structures because they were resistant to Nocodazole post-treatment and displayed a high level of tubulin acetylation. These results further indicate that a mechanical force generated by tau-induced Mt-bundling may be responsible for Golgi fragmentation and that the repeated domain region of tau may be the main promoter of this effect.

Free Heme and Amyloid-β: A Fatal Liaison in Alzheimer's Disease. - Chiziane, Elisabeth; Telemann, Henriette; Krueger, Martin; Adler, Juliane; Arnhold, Jürgen; Alia, A; Flemmig, Jörg (J Alzheimers Dis, 2018)
While the etiology of Alzheimer's disease (AD) is still unknown, an increased formation of amyloid-β (Aβ) peptide and oxidative processes are major pathological mechanism of the disease. The interaction of Aβ with free heme leads to the formation of peroxidase-active Aβ-heme complexes. However, enzyme-kinetic data and systematic mutational studies are still missing. These aspects were addressed in this study to evaluate the role of Aβ-heme complexes in AD. The enzyme-kinetic measurements showed peroxidase-specific pH- and H2O2-dependencies. In addition, the enzymatic activity of Aβ-heme complexes constantly increased at higher peptide excess. Moreover, the role of the Aβ sequence for the named enzymatic activity was tested, depicting human-specific R5, Y10, and H13 as essential amino acids. Also by studying Y10 as an endogenous peroxidase substrate for Aβ-heme complexes, ratio-specific effects were observed, showing an optimal dityrosine formation at an about 40-fold peptide excess. As dityrosine formation promotes Aβ fibrillation while free heme disturbs protein aggregation, we also investigated the effect of Aβ-heme complex-derived peroxidase activity on the formation of Aβ fibrils. The fluorescence measurements showed a different fibrillation behavior at strong peroxidase activity, leading also to altered fibril morphologies. The latter was detected by electron microscopy. As illustrated by selected in vivo measurements on a mouse model of AD, the disease is also characterized by Aβ-derived microvessel destructions and hemolytic processes. Thus, thrombo-hemorrhagic events are discussed as a source for free heme in brain tissue. In summary, we suggest the formation and enzymatic activity of Aβ-heme complexes as pathological key features of AD.
Keywords: Alzheimer Disease; Amino Acid Sequence; Amyloid; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Heme; Humans; Hydrogen Peroxide; Mice; Mice, Transgenic; Oxidation-Reduction; Peptide Fragments; Peroxidases

A Free Radical-Generating System Regulates Amyloid Oligomers: Involvement of Cathepsin B. - Llorente, Patricia; Kristen, Henrike; Sastre, Isabel; Toledano-Zaragoza, Ana; Aldudo, Jesús; Recuero, María; Bullido, Maria J (J Alzheimers Dis, 2018)
Amyloid-β (Aβ), a major component of senile plaques, is generated via the proteolysis of amyloid-β protein precursor (AβPP). This cleavage also produces AβPP fragment-derived oligomers which can be highly neurotoxic. AβPP metabolism/processing is affected by many factors, one of which is oxidative stress (OS). Associated with aging, OS is an important risk factor for Alzheimer's disease. In addition, the protein degradation systems, especially those involving cathepsins, are impaired in aging brains. Moreover, cathepsin B (CTSB) is a cysteine protease with potentially specific roles in AβPP proteolysis (β-secretase activity) and Aβ clearance (Aβ degradative activity). The present work examines the effect of OS and the involvement of CTSB in amyloid oligomer formation. The xanthine/xanthine oxidase (X-XOD) free radical generating system induced the partial inhibition of CTSB activity, which was accompanied by an increase in large amyloid oligomers. These were located throughout the cytosol and in endo-lysosomal vesicles. Cells treated with the CTSB inhibitor CA-074Me also showed increased amyloid oligomer levels, whereas those subjected to OS in the presence of the inhibitor showed no such increase. However, CTSB inhibition clearly modulated the AβPP metabolism/processing induced by X-XOD, as revealed by the increase in intracellular AβPP and secreted α-secretase-cleaved soluble AβPP. The present results suggest that CTSB participates in the changes of amyloid oligomer induced by mild OS.

Frequency of Cardiovascular Genetic Risk Factors in a Calabrian Population and Their Effects on Dementia. - Maletta, Raffaele; Smirne, Nicoletta; Bernardi, Livia; Anfossi, Maria; Gallo, Maura; Conidi, Maria Elena; Colao, Rosanna; Puccio, Gianfranco; Curcio, Sabrina A M; Laganà, Valentina; Frangipane, Francesca; Cupidi, Chiara; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several genetic variants playing a key role in cholesterol levels, blood pressure, and vascular dysfunction influence the risk of Alzheimer's disease (AD) and vascular dementia (VaD). The many meta-analysis studies carried out on large numbers of samples in different populations have not provided clear results to date, because a trans-ethnic shift of risk genotypes in different populations is often observed. OBJECTIVES: To determine genotypes allele frequencies of the polymorphisms most frequently identified to be correlated with cardio-cerebrovascular disease and AD in a Southern Italy population and to investigate their possible association with dementia. METHODS: The genotype and allele frequencies of 13 cardio-cerebrovascular risk polymorphisms were assessed and their possible association with dementia was investigated in a case-control study, including 221 consecutive unrelated subjects diagnosed with dementia (120 subjects affected by AD, 55 by frontotemporal dementia, and 33 by vascular dementia) and 218 matched controls of Calabrian origin. RESULTS: Carriers of at least one APOEɛ4 allele resulted to be at higher risk of AD [OR(95% CI) = 2.721(1.477-5.011)] and VaD [OR(95% CI) = 6.205(2.356-16.342)] compared to non-carriers. Individuals with the IV genotype of the CETP polymorphism were more likely to have AD [OR(95% CI) = 2.427(1.364-4.319)] and VaD [OR(95% CI) = 3.649(1.455-9.152)] compared to subjects with the II-VV genotypes. CONCLUSION: CETP I405V polymorphism is likely a risk factor for AD and VaD in our cohort, independent of APOEɛ4 status. Unmodifiable genetic risk factors should be taken into account to promote a healthy lifestyle to prevent dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Case-Control Studies; Cholesterol Ester Transfer Proteins; Cohort Studies; Dementia, Vascular; Female; Frontotemporal Dementia; Gene Frequency; Humans; Italy; Male; Middle Aged; Polymorphism, Genetic; Risk Factors

Frontotemporal Dementia and Chorea Associated with a Compound Heterozygous TREM2 Mutation. - Redaelli, Veronica; Salsano, Ettore; Colleoni, Lara; Corbetta, Paola; Tringali, Giovanni; Del Sole, Angelo; Giaccone, Giorgio; Rossi, Giacomina (J Alzheimers Dis, 2018)
Frontotemporal dementia (FTD) is clinically characterized by behavioral changes, language impairment, and executive dysfunction. FTD usually belongs to the frontotemporal lobar degeneration (FTLD) disease group, and its familial forms are dominantly inherited and linked to a group of genes relevant to frontal and temporal brain pathology, such as MAPT, GRN, C9ORF72, TARDBP, CHMP2B, VCP, and FUS. However, FTD can also be associated with different clinical or pathological phenotypes caused by mutations in other genes, whose heredity can be dominant or recessive. In this work we report on a familial case of FTD characterized by behavioral changes and aphasia, very early onset and very long duration, choreic movements, and white matter lesions at magnetic resonance imaging. We performed a wide-range genetic analysis, using a next generation sequencing approach, to evaluate a number of genes involved in neurodegeneration. We found a previously unreported compound heterozygous mutation in TREM2, that is commonly associated with the recessively inherited Nasu-Hakola disease. We discuss the differential diagnosis to be taken into account in cases of FTD presenting with atypical features.

Gait in Mild Alzheimer's Disease: Feasibility of Multi-Center Measurement in the Clinic and Home with Body-Worn Sensors: A Pilot Study. - Mc Ardle, Ríona; Morris, Rosie; Hickey, Aodhán; Del Din, Silvia; Koychev, Ivan; Gunn, Roger N; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil; Sahakian, Barbara J; Rowe, James B; Thomas, Alan; et al. (J Alzheimers Dis, 2018)
Gait is emerging as a potential diagnostic tool for cognitive decline. The 'Deep and Frequent Phenotyping for Experimental Medicine in Dementia Study' (D&FP) is a multicenter feasibility study embedded in the United Kingdom Dementia Platform designed to determine participant acceptability and feasibility of extensive and repeated phenotyping to determine the optimal combination of biomarkers to detect disease progression and identify early risk of Alzheimer's disease (AD). Gait is included as a clinical biomarker. The tools to quantify gait in the clinic and home, and suitability for multi-center application have not been examined. Six centers from the National Institute for Health Research Translational Research Collaboration in Dementia initiative recruited 20 individuals with early onset AD. Participants wore a single wearable (tri-axial accelerometer) and completed both clinic-based and free-living gait assessment. A series of macro (behavioral) and micro (spatiotemporal) characteristics were derived from the resultant data using previously validated algorithms. Results indicate good participant acceptability, and potential for use of body-worn sensors in both the clinic and the home. Recommendations for future studies have been provided. Gait has been demonstrated to be a feasible and suitable measure, and future research should examine its suitability as a biomarker in AD.

Generation of a New Tau Knockout (tauΔex1) Line Using CRISPR/Cas9 Genome Editing in Mice. - Tan, Daniel C S; Yao, Sherilyn; Ittner, Arne; Bertz, Josefine; Ke, Yazi D; Ittner, Lars M; Delerue, Fabien (J Alzheimers Dis, 2018)
Alzheimer's disease and other dementias present with tau pathology. Several mouse lines with knockout of the tau-encoding Mapt gene have been reported, yet findings often differed between lines and sites. Here, we report a new tau knockout strain (tauΔex1), generated by CRISPR/Cas9-mediated genome editing of intron -1/exon 1 of Mapt in C57Bl/6J mice. TauΔex1 mice had no overt phenotype, but, in line with previous models, they showed a significantly reduced susceptibility to excitotoxic seizures, with normal memory formation in young mice. This new in vivo resource will be made freely available to the research community.

Genotyping of the Alzheimer's Disease Genome-Wide Association Study Index Single Nucleotide Polymorphisms in the Brains for Dementia Research Cohort. - Brookes, Keeley J; McConnell, George; Williams, Kirsty; Chaudhury, Sultan; Madhan, Gaganjit; Patel, Tulsi; Turley, Christopher; Guetta-Baranes, Tamar; Bras, Jose; Guerreiro, Rita; Hardy, John; Francis, Paul T; et al. (J Alzheimers Dis, 2018)
The Brains for Dementia Research project is a recently established longitudinal cohort which aims to provide brain tissue for research purposes from neuropathologically defined samples. Here we present the findings from our analysis on the 19 established GWAS index SNPs for Alzheimer's disease, in order to demonstrate if the BDR sample also displays association to these variants. A highly significant association of the APOEɛ4 allele was identified (p = 3.99×10-12). Association tests for the 19 GWAS SNPs found that although no SNPs survive multiple testing, nominal significant findings were detected and concordance with the Lambert et al. GWAS meta-analysis was observed.

Ginkgo biloba Extract EGb 761 and Its Specific Components Elicit Protective Protein Clearance Through the Autophagy-Lysosomal Pathway in Tau-Transgenic Mice and Cultured Neurons. - Qin, Yiren; Zhang, Yu; Tomic, Inge; Hao, Wenlin; Menger, Michael D; Liu, Chunfeng; Fassbender, Klaus; Liu, Yang (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disease pathologically characterized by extracellular amyloid-β (Aβ) deposits and intracellular neurofibrillary tangles (NFT) in many brain regions. NFT are primarily composed of hyperphosphorylated tau protein (p-Tau). Aβ and p-Tau are two major pathogenic molecules with tau acting downstream to Aβ to induce neuronal degeneration. In this study, we investigated whether Ginkgo biloba extract EGb 761 reduces cerebral p-Tau level and prevents AD pathogenesis. Human P301S tau mutant-transgenic mice were fed with EGb 761, added to the regular diet for 2 or 5 months. We observed that treatment with EGb 761 for 5 months significantly improved the cognitive function of mice, attenuated the loss of synaptophysin and recovered the phosphorylation of CREB in the mouse brain. Treatment with EGb 761 for 5 but not 2 months also decreased p-Tau protein amount and shifted microglial pro-inflammatory to anti-inflammatory activation in the brain. As potential therapeutic mechanisms, we demonstrated that treatment with EGb 761, especially the components of ginkgolide A, bilobalide, and flavonoids, but not with purified ginkgolide B or C, increased autophagic activity and degradation of p-Tau in lysosomes of neurons. Inhibiting ATG5 function or treating cells with Bafilomycin B1 abolished EGb 761-enhanced degradation of p-Tau in cultured neurons. Additionally, we observed that 5- instead of 2-month-treatment with EGb 761 inhibited the activity of p38-MAPK and GSK-3β. Therefore, long-term treatment with Ginkgo biloba extract EGb 761, a clinically available and well-tolerated herbal medication, ameliorates AD pathology through mechanisms against multiple AD pathogenic processes.

Glia Maturation Factor and Mast Cell-Dependent Expression of Inflammatory Mediators and Proteinase Activated Receptor-2 in Neuroinflammation. - Kempuraj, Duraisamy; Selvakumar, Govindhasamy Pushpavathi; Thangavel, Ramasamy; Ahmed, Mohammad Ejaz; Zaheer, Smita; Kumar, Keerthana Kuppamma; Yelam, Anudeep; Kaur, Harleen; Dubova, Iuliia; Raikwar, Sudhanshu P; Iyer, Shankar S; Zaheer, Asgar (J Alzheimers Dis, 2018)
Parkinson's disease (PD) is characterized by the presence of inflammation-mediated dopaminergic neurodegeneration in the substantia nigra. Inflammatory mediators from activated microglia, astrocytes, neurons, T-cells and mast cells mediate neuroinflammation and neurodegeneration. Administration of neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induces PD like motor deficits in rodents. 1-methyl-4-phenylpyridinium (MPP+), a toxic metabolite of MPTP activates glial cells, neurons and mast cells to release neuroinflammatory mediators. Glia maturation factor (GMF), mast cells and proteinase activated receptor-2 (PAR-2) are implicated in neuroinflammation. Alpha-synuclein which induces neurodegeneration increases PAR-2 expression in the brain. However, the exact mechanisms are not yet understood. In this study, we quantified inflammatory mediators in the brains of MPTP-administered wild type (Wt), GMF-knockout (GMF-KO), and mast cell knockout (MC-KO) mice. Additionally, we analyzed the effect of MPP+, GMF, and mast cell proteases on PAR-2 expression in astrocytes and neurons in vitro. Results show that the levels of interleukin-1beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and the chemokine (C-C motif) ligand 2 (CCL2) were lesser in the brains of GMF-KO mice and MC-KO mice when compared to Wt mice brain after MPTP administration. Incubation of astrocytes and neurons with MPP+, GMF, and mouse mast cell protease-6 (MMCP-6) and MMCP-7 increased the expression of PAR-2. Our studies show that the absence of mast cells and GMF reduce the expression of neuroinflammatory mediators in the brain. We conclude that GMF along with mast cell interactions with glial cells and neurons during neuroinflammation can be explored as a new therapeutic target for PD and other neuroinflammatory disorders.

Gut Microbiome is Altered in Patients with Alzheimer's Disease. - Zhuang, Zhen-Qian; Shen, Lin-Lin; Li, Wei-Wei; Fu, Xue; Zeng, Fan; Gui, Li; Lü, Yang; Cai, Min; Zhu, Chi; Tan, Yin-Ling; Zheng, Peng; Li, Hui-Yun; et al. (J Alzheimers Dis, 2018)
Previous studies suggest that gut microbiota is associated with neuropsychiatric disorders, such as Parkinson's disease, amyotrophic lateral sclerosis, and depression. However, whether the composition and diversity of gut microbiota is altered in patients with Alzheimer's disease (AD) remain largely unknown. In the present study, we collected fecal samples from 43 AD patients and 43 age- and gender-matched cognitively normal controls. 16S ribosomal RNA sequencing technique was used to analyze the microbiota composition in feces. The composition of gut microbiota was different between the two groups. Several bacteria taxa in AD patients were different from those in controls at taxonomic levels, such as Bacteroides, Actinobacteria, Ruminococcus, Lachnospiraceae, and Selenomonadales. Our findings suggest that gut microbiota is altered in AD patients and may be involved in the pathogenesis of AD.

The GWAS Risk Genes for Depression May Be Actively Involved in Alzheimer's Disease. - Ni, Hua; Xu, Min; Zhan, Gui-Lai; Fan, Yu; Zhou, Hejiang; Jiang, Hong-Yan; Lu, Wei-Hong; Tan, Liwen; Zhang, Deng-Feng; Yao, Yong-Gang; Zhang, Chen (J Alzheimers Dis, 2018)
Depression is one of the most frequent psychiatric symptoms observed in people during the development of Alzheimer's disease (AD). We hypothesized that genetic factors conferring risk of depression might affect AD development. In this study, we screened 31 genes, which were located in 19 risk loci for major depressive disorder (MDD) identified by two recent large genome-wide association studies (GWAS), in AD patients at the genomic and transcriptomic levels. Association analysis of common variants was performed by using summary statistics of the International Genomics of Alzheimer's Project (IGAP), and association analysis of rare variants was conducted by sequencing the entire coding region of the 31 MDD risk genes in 107 Han Chinese patients with early-onset and/or familial AD. We also quantified the mRNA expression alterations of these MDD risk genes in brain tissues of AD patients and AD mouse models, followed by protein-protein interaction network prediction to show their potential effects in AD pathways. We found that common and rare variants of L3MBTL2 were significantly associated with AD. mRNA expression levels of 18 MDD risk genes, in particular SORCS3 and OAT, were differentially expressed in AD brain tissues. 13 MDD risk genes were predicted to physically interact with core AD genes. The involvement of HACE1, NEGR1, and SLC6A15 in AD was supported by convergent lines of evidence. Taken together, our results showed that MDD risk genes might play an active role in AD pathology and supported the notion that depression might be the "common cold" of psychiatry.

High-Density Lipoprotein Subclasses and Mild Cognitive Impairment: Study of Outcome and aPolipoproteins in Dementia (STOP-Dementia)1. - Ohtani, Ryo; Nirengi, Shinsuke; Nakamura, Michikazu; Murase, Nagako; Sainouchi, Makoto; Kuwata, Yasuhiro; Takata, Masaki; Masuda, Yuuichi; Kotani, Kazuhiko; Sakane, Naoki (J Alzheimers Dis, 2018)
BACKGROUND: High-density lipoprotein (HDL) containing apolipoprotein A-I is associated with the pathogenesis of Alzheimer's disease (AD). HDL particle size is modified in the presence of pathological conditions, while the significance of the HDL particle size remains controversial. OBJECTIVE: The aim of this study was to investigate the HDL lipoprotein subclasses in mild cognitive impairment (MCI) and AD. METHODS: This cross-sectional study included 20 AD patients, 17 MCI patients, and 17 age-matched controls without cognitive impairment, selected from the database of the Study of Outcome and aPolipoproteins in Dementia (STOP-Dementia) registry. The diagnoses of AD and MCI were performed by expert neurologists according to the Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition criteria. Serum HDL subclasses were measured by electrophoretic separation of lipoproteins using the Lipoprint System. The neutrophil-lymphocyte ratio (NLR), a marker of inflammation, was calculated by dividing the neutrophil count by the lymphocyte count. RESULTS: Small-sized HDL particle levels in the MCI group were significantly higher than in the control group, although there was no difference in serum HDL-cholesterol levels between MCI and control groups. NLR in the MCI group was higher than in the control group, but this difference was non-significant (p = 0.09). There was no difference in HDL subclasses or NLR between the AD and control groups. CONCLUSION: These findings suggest that HDL subclasses might be associated with the development of MCI.

Hippocampal Sclerosis in the Oldest Old: A Finnish Population-Based Study. - Kero, Mia; Raunio, Anna; Polvikoski, Tuomo; Tienari, Pentti J; Paetau, Anders; Myllykangas, Liisa (J Alzheimers Dis, 2018)
BACKGROUND: There are only few population-based studies that have systemically investigated the prevalence of hippocampal sclerosis (HS) in the very old. The frequency of unilateral versus bilateral HS has been rarely studied. OBJECTIVE: We investigated the prevalence and laterality of HS and its association with other neurodegenerative and vascular pathologies in a population-based sample of very elderly. Furthermore, the concomitant presence of immunoreactivity for TDP-43, p62, and HPtau was studied. METHODS: The population-based Vantaa 85+ study includes all inhabitants of the city of Vantaa, who were >85 years in 1991 (n = 601). Neuropathological assessment was possible in 302 subjects. Severity of neuronal loss of CA sectors and subiculum was determined bilaterally by HE- staining. Immunohistochemistry performed using antibodies for TDP-43, p62, and HPtau. RESULTS: Neuronal loss and pathological changes in the hippocampus sector CA1 and subiculum were observed in 47 of the 302 individuals (16%), and 51% of these changes were bilateral. HS without comorbid neurodegenerative pathology was found in 1/47 subjects with HS (2%). Dementia (p < 0.001) and TDP-43 immunopositivity of the granular cell layer of the dentate fascia (p < 0.001) were strongly associated with HS. The CERAD score, immunopositivity for HPtau and p62 in the granular cell layer of the fascia dentate were also associated. CONCLUSION: HS is prevalent (16%) in the oldest old population, but HS without any comorbid neurodegenerative pathology is rare. The high frequency of unilateral HS (49%) implied that bilateral sampling of hippocampi should be routine practice in neuropathological examination.

Homocysteine and Cerebral Atrophy: The Epidemiology of Dementia in Singapore Study. - Tan, Bryce; Venketasubramanian, Narayanaswamy; Vrooman, Henri; Cheng, Ching-Yu; Wong, Tien Yin; Ikram, Mohammad Kamran; Chen, Christopher; Hilal, Saima (J Alzheimers Dis, 2018)
BACKGROUND: Plasma homocysteine levels are increasingly studied as a potential risk factor for dementia. Elevated homocysteine levels have been linked with gray and white matter volume reduction among individuals with mild cognitive impairment and Alzheimer's disease. However, the effects of homocysteine on brain changes in preclinical stages of dementia remain unexplored. OBJECTIVE: To examine the association of elevated homocysteine levels with markers of neurodegeneration, i.e., white and gray matter volume in an elderly population. METHODS: The study included 768 participants (mean age: 69.6±6.5 years, 51.3% women) from the Epidemiology of Dementia In Singapore study. Participants underwent a brain MRI scan and blood tests. Serum homocysteine was measured using competitive immunoassay. Cortical thickness and subcortical structural volume were quantified using FreeSurfer whereas white matter volume was quantified using a previous validated method. RESULTS: Higher homocysteine levels were significantly associated with decreased global white matter volume [mean difference (β) in volume (ml) per micromole per liter (μmol/l) increase in homocysteine levels: - 0.555, 95% Confidence Interval (CI): - 0.873; - 0.237], decreased parietal cortical thickness [β in thickness (μm) per μmol/l increase in homocysteine levels:- 1.429, 95% CI: - 2.781; - 0.077], and smaller volumes of the thalamus [β: - 0.017, 95% CI: - 0.026; - 0.008], brainstem [β: - 0.037, 95% CI: - 0.058; - 0.016], and accumbens [β: - 0.004, 95% CI: - 0.006; - 0.002]. CONCLUSION: Higher homocysteine levels were associated with cerebral atrophy. Further studies are required to assess whether lowering plasma homocysteine levels may prevent neurodegenerative changes or delay progression of clinical symptoms before the development of dementia.
Keywords: Aged; Atrophy; Biomarkers; Dementia; Female; Homocysteine; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Organ Size; Risk Factors; Singapore; White Matter

Honokiol Alleviates Cognitive Deficits of Alzheimer's Disease (PS1V97L) Transgenic Mice by Activating Mitochondrial SIRT3. - Li, Haitao; Jia, Jianping; Wang, Wei; Hou, Tingting; Tian, Yuanruhua; Wu, Qiaoqi; Xu, Lingzhi; Wei, Yiping; Wang, Xiu (J Alzheimers Dis, 2018)
Accumulating evidence has demonstrated that mitochondrial dysfunction is a prominent early event in the progression of Alzheimer's disease (AD). Whether protecting mitochondrial function can reduce amyloid-β oligomer (AβO)-induced neurotoxicity in PS1V97L transgenic mice remains unknown. In this study, we examined the possible protective effects of honokiol (HKL) on mitochondrial dysfunction induced by AβOs in neurons, and cognitive function in AD PS1V97Ltransgenic mice. We determined that HKL increased mitochondrial sirtuin 3 (SIRT3) expression levels and activity, which in turn markedly improved ATP production and weakened mitochondrial reactive oxygen species production. We demonstrated that the enhanced energy metabolism and attenuated oxidative stress of HKL restores AβO-mediated mitochondrial dysfunction in vitro and in vivo. Consequently, memory deficits in the PS1V97L transgenic mice were rescued by HKL in the early stages. These results suggest that HKL has therapeutic potential for delaying the onset of AD symptoms by alleviating mitochondrial impairment and increasing hyperactivation of SIRT3 in the pathogenesis of preclinical AD.

Hospitalization after Oral Antibiotic Initiation in Finnish Community Dwellers with and without Alzheimer's Disease: Retrospective Register-Based Cohort Study. - Järvinen, Heli; Taipale, Heidi; Koponen, Marjaana; Tanskanen, Antti; Tiihonen, Jari; Tolppanen, Anna-Maija; Hartikainen, Sirpa (J Alzheimers Dis, 2018)
BACKGROUND: Persons with Alzheimer's disease (AD) are frequently hospitalized from infection-related causes. There are no previous studies investigating hospitalization associated with antibiotic initiation in persons with AD. OBJECTIVE: To investigate the frequency and risk of hospitalization associated with oral antibiotic initiation among community dwellers with and without AD. METHODS: We performed a retrospective register-based study utilizing register-based Medication Use and Alzheimer's disease (MEDALZ) cohort. It includes all community dwellers diagnosed with AD during 2005-2011 in Finland and their matched comparison persons without AD. Antibiotic use was initiated by 34,785 persons with and 36,428 without AD. Drug use data were collected from Prescription Register and comorbidities from Special Reimbursement and Hospital Care Registers. Infection diagnoses were collected from the Hospital Care Register. Factors associated with hospitalization were estimated utilizing logistic regression models. RESULTS: Risk of hospitalization following antibiotic initiation was higher among antibiotic initiators with AD than without AD (adjusted odds ratio, aOR, 1.37, 95% Cl 1.28-1.46).Strongest association with hospitalization was found for oral glucocorticoid use, aOR 1.41 (1.25-1.59); epilepsy, aOR 1.33 (1.10-1.63); and active cancer, aOR 1.30 (1.14-1.49). Among initiators of cephalexin, pivmecillinam, amoxicillin/amoxicillin, and enzyme inhibitor and doxycycline, persons with AD were more frequently hospitalized than persons without AD. A quarter of hospitalized antibiotic initiators had infection diagnosis in their hospital care records. CONCLUSIONS: Persons with AD initiating an antibiotic had a higher risk for hospitalization than antibiotic initiators without AD. Further research is needed to determine whether infection-related hospitalization could be reduced.

How Does Utilization of Health Care Services Change in People with Dementia Served by Dementia Care Networks? Results of the Longitudinal, Observational DemNet-D-Study. - Thyrian, Jochen René; Michalowsky, Bernhard; Hertel, Johannes; Wübbeler, Markus; Gräske, Johannes; Holle, Bernhard; Schäfer-Walkmann, Susanne; Wolf-Ostermann, Karin; Hoffmann, Wolfgang (J Alzheimers Dis, 2018)
BACKGROUND: There is no common definition for the Dementia Care Network (DCN). They are heterogeneous and there is no general, longitudinal evidence for the effects of DCN. OBJECTIVE: We describe changes in utilization of health services by people served by dementia care networks in Germany and factors associated with those changes over time. METHODS: Primary data was assessed in 560 people with dementia (PwD) and their caregivers supported by DCN in Germany; sociodemographic and clinical variables, utilization of services; DCN were characterized according to governance. The design: observational study with face-to-face interviews at two time points over a period of one year. Data was assessed via semi-structured interviews at the participants' homes. RESULTS: Utilization of health services in this study is consistently higher than reported for the general population and does not significantly change over time. The strongest predictor of utilization of any service after one year was the use of this service at baseline (OR from 3.23 to 44.16). Higher activities of daily functioning increased the chances to utilize specialist physicians (OR = 1.32; 95% -CI: 1.08-1.63) or occupational therapy (OR = 1.24; 95% -CI: 1.02-1.50) significantly. Being a female decreased chances to utilize specialist physicians (OR = 0.57; 95% -CI: 0.37-0.87) and increased the chances to utilize no services (OR = 2.08; 95% -CI: 1.29-3.33). CONCLUSION: While health care acknowledges the importance and benefits of dementia care networks (i.e., in Germany, the results were considered in new German legislation (SGB XI)), further research is needed to define this kind of service delivery to facilitate comparison as well as promote evidence-based implementation.

Immunohistochemical Analysis of Activin Receptor-Like Kinase 1 (ACVRL1/ALK1) Expression in the Rat and Human Hippocampus: Decline in CA3 During Progression of Alzheimer's Disease. - Adams, Stephanie L; Benayoun, Laurent; Tilton, Kathy; Mellott, Tiffany J; Seshadri, Sudha; Blusztajn, Jan Krzysztof; Delalle, Ivana (J Alzheimers Dis, 2018)
The pathophysiology of Alzheimer's disease (AD) includes signaling defects mediated by the transforming growth factor β-bone morphogenetic protein-growth and differentiation factor (TGFβ-BMP-GDF) family of proteins. In animal models of AD, administration of BMP9/GDF2 improves memory and reduces amyloidosis. The best characterized type I receptor of BMP9 is ALK1. We characterized ALK1 expression in the hippocampus using immunohistochemistry. In the rat, ALK1 immunoreactivity was found in CA pyramidal neurons, most frequently and robustly in the CA2 and CA3 fields. In addition, there were sporadic ALK1-immunoreactive cells in the stratum oriens, mainly in CA1. The ALK1 expression pattern in human hippocampus was similar to that of rat. Pyramidal neurons within the CA2, CA3, and CA4 were strongly ALK1-immunoreactive in hippocampi of cognitively intact subjects with no neurofibrillary tangles. ALK1 signal was found in the axons of alveus and fimbria, and in the neuropil across CA fields. Relatively strongest ALK1 neuropil signal was observed in CA1 where pyramidal neurons were occasionally ALK1-immunoractive. As in the rat, horizontally oriented neurons in the stratum oriens of CA1 were both ALK1- and GAD67-immunoreactive. Analysis of ALK1 immunoreactivity across stages of AD pathology revealed that disease progression was characterized by overall reduction of the ALK1 signal in CA3 in advanced, but not early, stages of AD. These data suggest that the CA3 pyramidal neurons may remain responsive to the ALK1 ligands, e.g., BMP9, during initial stages of AD and that ALK1 may constitute a therapeutic target in early and moderate AD.

The Impact of Hospitalization on Readmission, Institutionalization, and Mortality of People with Dementia: A Systematic Review and Meta-Analysis. - Lehmann, Jana; Michalowsky, Bernhard; Kaczynski, Anika; Thyrian, Jochen René; Schenk, Nele Sophie; Esser, Alexander; Zwingmann, Ina; Hoffmann, Wolfgang (J Alzheimers Dis, 2018)
BACKGROUND: People with dementia (PwD) are at a high risk of hospitalization. Hospitals are often not adequately equipped for PwD and discharges often come unexpected. Therefore, PwD are at a risk of adverse outcomes. However, information about those outcomes is rare but crucial for the development of preventive strategies. OBJECTIVES: To conduct a quantitative systematic review and meta-analyses on the impact of a hospitalization on readmission, institutionalization, and mortality in PwD. To identify factors associated with these outcomes. METHODS: PubMed, CENTRAL, and ScienceDirect were searched for studies including terms for dementia, hospital, readmission, institutionalization, and mortality. Relevant were assessed by a quality criteria sheet. Results were summarized in a table. Meta-analysis was conducted with Review Manager 5.3. RESULTS: The search yielded 1,108 studies; 20 fulfilled the inclusion criteria and 10 studies were eligible for meta-analyses. The incidence and relative risk (RR) of mortality (RR 1.74 CI95 % 1.50, 2.05) and institutionalization (RR: 2.16 CI95 % 1.31, 3.56) of PwD was significantly higher when compared to people without dementia. Results according to readmission rate were inconsistent. Factors significantly associated with the examined adverse outcomes were severity of dementia, number of medications, and deficits in daily living activities. CONCLUSION: Hospitalization of PwD lead to adverse outcomes. An improvement in the identification of and care for PwD in the acute setting as well as in after care in the community setting, especially in the interface between both settings, is required to prevent adverse outcomes in hospitalized PwD.

The Impact of Music on the Self in Dementia. - Baird, Amee; Thompson, William Forde (J Alzheimers Dis, 2018)
In this review, we consider how the onset and progression of dementia can disrupt one's sense of self, and propose that music is an ideal tool for alleviating this distressing symptom. Various aspects of the self can be impaired in people with dementia, depending on how the self is defined. There are anecdotal reports that music can 'bring people back to themselves' in the face of dementia, but there have been scarce empirical investigations of this topic. Motivated by a consideration of the existing literature, we outline a novel theoretical framework that accounts for the relationship between music and the self in people with dementia. We propose that music has a number of 'design features' that make it uniquely equipped to engage multiple aspects of the self. We suggest that each design feature interacts with different aspects of the self to varying degrees, promoting overall wellbeing. We discuss how existing research on music and dementia fits within this framework, and describe two case studies in which music was an ideal stimulus for reaffirming their sense of self. Our framework may be useful for the diagnosis and treatment of impairments of self in people with dementia, and highlights how music, given its ability to engage all aspects of the self simultaneously, can result in an overall enhanced sense of self.
Keywords: Consciousness; Dementia; Humans; Music; Music Therapy; Personality

Impact of Total Knee Arthroplasty with General Anesthesia on Brain Networks: Cognitive Efficiency and Ventricular Volume Predict Functional Connectivity Decline in Older Adults. - Huang, Haiqing; Tanner, Jared; Parvataneni, Hari; Rice, Mark; Horgas, Ann; Ding, Mingzhou; Price, Catherine (J Alzheimers Dis, 2018)
Using resting state functional magnetic resonance imaging (RS-fMRI), we explored: 1) pre- to post-operative changes in functional connectivity in default mode, salience, and central executive networks after total knee arthroplasty (TKA) with general anesthesia, and 2) the contribution of cognitive/brain reserve metrics these resting state functional declines. Individuals age 60 and older electing unilateral total knee arthroplasty (TKA; n = 48) and non-surgery peers with osteoarthritis (n = 45) completed baseline cognitive testing and baseline and post-surgery (post-baseline, 48-h post-surgery) brain MRI. We acquired cognitive and brain estimates for premorbid (vocabulary, reading, education, intracranial volume) and current (working memory, processing speed, declarative memory, ventricular volume) reserve. Functional network analyses corrected for pain severity and pain medication. The surgery group declined in every functional network of interest (p < 0.001). Relative to non-surgery peers, 23% of surgery participants declined in at least one network and 15% of the total TKA sample declined across all networks. Larger preoperative ventricular volume and lower scores on preoperative metrics of processing speed and working memory predicted default mode network connectivity decline. Premorbid cognitive and premorbid brain reserve did not predict decline. Within 48 hours after surgery, at least one fourth of the older adult sample showed significant functional network decline. Metrics of current brain status (ventricular volume), working memory, and processing speed predicted the severity of default mode network connectivity decline. These findings demonstrate the relevance of preoperative cognition and brain integrity on acute postoperative functional network change.

In Vitro Potency and Preclinical Pharmacokinetic Comparison of All-D-Enantiomeric Peptides Developed for the Treatment of Alzheimer's Disease. - Schartmann, Elena; Schemmert, Sarah; Niemietz, Nicole; Honold, Dominik; Ziehm, Tamar; Tusche, Markus; Elfgen, Anne; Gering, Ian; Brener, Oleksandr; Shah, Nadim Joni; Langen, Karl-Josef; Kutzsche, Janine; et al. (J Alzheimers Dis, 2018)
Diffusible amyloid-β (Aβ) oligomers are currently presumed to be the most cytotoxic Aβ assembly and held responsible to trigger the pathogenesis of Alzheimer's disease (AD). Thus, Aβ oligomers are a prominent target in AD drug development. Previously, we reported on our solely D-enantiomeric peptide D3 and its derivatives as AD drug candidates. Here, we compare one of the most promising D3 derivatives, ANK6, with its tandem version (tANK6), and its head-to-tail cyclized isoform (cANK6r). In vitro tests investigating the D-peptides' potencies to inhibit Aβ aggregation, eliminate Aβ oligomers, and reduce Aβ-induced cytotoxicity revealed that all three D-peptides efficiently target Aβ. Subsequent preclinical pharmacokinetic studies of the three all-D-peptides in wildtype mice showed promising blood-brain barrier permeability with cANK6r yielding the highest levels in brain. The peptides' potencies to lower Aβ toxicity and their remarkable brain/plasma ratios make them promising AD drug candidates.

In vivo Depiction of α7 Nicotinic Receptor Loss for Cognitive Decline in Alzheimer's Disease. - Nakaizumi, Kyoko; Ouchi, Yasuomi; Terada, Tatsuhiro; Yoshikawa, Etsuji; Kakimoto, Akihiro; Isobe, Takashi; Bunai, Tomoyasu; Yokokura, Masamichi; Suzuki, Katsuaki; Magata, Yasuhiro (J Alzheimers Dis, 2018)
BACKGROUND: The α7 subtype of the nicotinic acetylcholine receptor (nAChR) is considered important in higher cognitive functions, and cholinergic loss underpins the pathophysiology of Alzheimer's disease (AD). However, the relationships between α7 nAChR function and clinical functions or amyloid-β (Aβ) deposition remain to be explored in the living AD brain. OBJECTIVE: We aimed to elucidate the relationship between α7 nAChR availability in the specific cholinergic region and cognitive decline in the Aβ-confirmed AD brain. METHODS: Twenty AD patients and ten age-matched healthy subjects were examined. The α7-nAChR availability and Aβ deposition were evaluated using positron emission tomography with an α7 nAChR radiotracer 11C-(R)-MeQAA and 11C-Pittsburg compound B (11C-PiB), respectively. Semi-quantified values of tracer binding were estimated with a simplified reference tissue method for BPND of 11C-(R)-MeQAA and a tissue ratio method for SUVR of 11C-PiB. These parameters and clinical scores were compared voxel-wise using a statistical parametric mapping method. RESULTS: The levels of 11C-(R)-MeQAA BPND in the temporal and prefrontal cholinergic projection regions were significantly lower in AD, and negative correlations were found between 11C-PiB SUVR and 11C-(R)-MeQAA BPND in the region of the nucleus basalis magnocellularis and medial prefrontal cortex. Levels of 11C-(R)-MeQAA BPND were significantly correlated with memory and frontal function scores in AD. CONCLUSION: The association between Aβ burden and α7-nAChR reduction in the basal forebrain cholinergic system was highlighted in relation to cognitive decline in AD. This suggests that Aβ-linked α7-nAChR reduction is clinico-pathophyisologically important for considering a good therapeutic target in AD.
Keywords: Adult; Aged; alpha7 Nicotinic Acetylcholine Receptor; Alzheimer Disease; Brain; Case-Control Studies; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Positron-Emission Tomography; Young Adult

In Vivo Visualization of Tau Accumulation, Microglial Activation, and Brain Atrophy in a Mouse Model of Tauopathy rTg4510. - Ishikawa, Ai; Tokunaga, Masaki; Maeda, Jun; Minamihisamatsu, Takeharu; Shimojo, Masafumi; Takuwa, Hiroyuki; Ono, Maiko; Ni, Ruiqing; Hirano, Shigeki; Kuwabara, Satoshi; Ji, Bin; Zhang, Ming-Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Tau imaging using PET is a promising tool for the diagnosis and evaluation of tau-related neurodegenerative disorders, but the relationship among PET-detectable tau, neuroinflammation, and neurodegeneration is not yet fully understood. OBJECTIVE: We aimed to elucidate sequential changes in tau accumulation, neuroinflammation, and brain atrophy by PET and MRI in a tauopathy mouse model. METHODS: rTg4510 transgenic (tg) mice expressing P301L mutated tau and non-tg mice were examined with brain MRI and PET imaging (analyzed numbers: tg = 17, non-tg = 13; age 2.5∼14 months). As PET probes, [11C]PBB3 (Pyridinyl-Butadienyl-Benzothiazole 3) and [11C]AC-5216 were used to visualize tau pathology and 18-kDa translocator protein (TSPO) neuroinflammation. Tau pathology and microglia activation were subsequently analyzed by histochemistry. RESULTS: PET studies revealed age-dependent increases in [11C]PBB3 and [11C]AC-5216 signals, which were correlated with age-dependent volume reduction in the forebrain on MRI. However, the increase in [11C]PBB3 signals reached a plateau at age 7 months, and therefore its significant correlation with [11C]AC-5216 disappeared after age 7 months. In contrast, [11C]AC-5216 showed a strong correlation with both age and volume reduction until age 14 months. Histochemical analyses confirmed the relevance of pathological tau accumulation and elevated TSPO immunoreactivity in putative microglia. CONCLUSION: Our results showed that tau accumulation is associated with neuroinflammation and brain atrophy in a tauopathy mouse model. The time-course of the [11C]PBB3- and TSPO-PET finding suggests that tau deposition triggers progressive neuroinflammation, and the sequential changes can be evaluated in vivo in mouse brains.
Keywords: Animals; Atrophy; Benzothiazoles; Brain; Disease Models, Animal; Female; Magnetic Resonance Imaging; Male; Mice; Mice, Transgenic; Microglia; Positron-Emission Tomography; Receptors, GABA; tau Proteins; Tauopathies

Incidence and Prevalence of Antiepileptic Medication Use in Community-Dwelling Persons with and without Alzheimer's Disease. - Sarycheva, Tatyana; Taipale, Heidi; Lavikainen, Piia; Tiihonen, Jari; Tanskanen, Antti; Hartikainen, Sirpa; Tolppanen, Anna-Maija (J Alzheimers Dis, 2018)
BACKGROUND: Although antiepileptic drugs (AEDs) have a potential for adverse drug reactions in older populations, little is known about their use in relation to Alzheimer's disease (AD) diagnosis. OBJECTIVES: In this study, we investigated the incidence and prevalence of AED use in relation to AD diagnosis. METHODS: The MEDALZ-study includes all Finnish persons who received clinically verified AD diagnoses (n = 70,718) during 2005-2011 and a matched comparison cohort without AD (n = 70,718). AD diagnoses were identified from the Special Reimbursement Register. We used the Prescription Register to identify dispensed AEDs. Incident AED users were identified with a one-year washout period 9-10 years before AD diagnosis, and incidence rates per 100 person-years were calculated for each six-month period from nine years before to five years after AD diagnosis. Prevalence was assessed as proportion using AEDs during each six-month time period for incident use. RESULTS: Persons with AD were more likely to use AEDs during the study period (4.3%) than persons without AD (3.2%). The incidence and prevalence of AED use was higher among persons with AD and increased around the time of AD diagnosis. Epilepsy diagnoses did not explain these differences. Persons with AD were more likely to use older AEDs. CONCLUSION: Our study highlights the need to balance effective symptom control with the possible risks of treatment.

Induction of Amyloid-β42 Production by Fipronil and Other Pyrazole Insecticides. - Cam, Morgane; Durieu, Emilie; Bodin, Marion; Manousopoulou, Antigoni; Koslowski, Svenja; Vasylieva, Natalia; Barnych, Bogdan; Hammock, Bruce D; Bohl, Bettina; Koch, Philipp; Omori, Chiori; Yamamoto, Kazuo; et al. (J Alzheimers Dis, 2018)
Generation of amyloid-β peptides (Aβs) by proteolytic cleavage of the amyloid-β protein precursor (AβPP), especially increased production of Aβ42/Aβ43 over Aβ40, and their aggregation as oligomers and plaques, represent a characteristic feature of Alzheimer's disease (AD). In familial AD (FAD), altered Aβ production originates from specific mutations of AβPP or presenilins 1/2 (PS1/PS2), the catalytic subunits of γ-secretase. In sporadic AD, the origin of altered production of Aβs remains unknown. We hypothesize that the 'human chemical exposome' contains products able to favor the production of Aβ42/Aβ43 over Aβ40 and shorter Aβs. To detect such products, we screened a library of 3500 + compounds in a cell-based assay for enhanced Aβ42/Aβ43 production. Nine pyrazole insecticides were found to induce a β- and γ-secretase-dependent, 3-10-fold increase in the production of extracellular Aβ42 in various cell lines and neurons differentiated from induced pluripotent stem cells derived from healthy and FAD patients. Immunoprecipitation/mass spectrometry analyses showed increased production of Aβs cleaved at positions 42/43, and reduced production of peptides cleaved at positions 38 and shorter. Strongly supporting a direct effect on γ-secretase activity, pyrazoles shifted the cleavage pattern of another γ-secretase substrate, alcadeinα, and shifted the cleavage of AβPP by highly purified γ-secretase toward Aβ42/Aβ43. Focusing on fipronil, we showed that some of its metabolites, in particular the persistent fipronil sulfone, also favor the production of Aβ42/Aβ43 in both cell-based and cell-free systems. Fipronil administered orally to mice and rats is known to be metabolized rapidly, mostly to fipronil sulfone, which stably accumulates in adipose tissue and brain. In conclusion, several widely used pyrazole insecticides enhance the production of toxic, aggregation prone Aβ42/Aβ43 peptides, suggesting the possible existence of environmental "Alzheimerogens" which may contribute to the initiation and propagation of the amyloidogenic process in sporadic AD.

Interrelationship between the Levels of C9orf72 and Amyloid-β Protein Precursor and Amyloid-β in Human Cells and Brain Samples. - Leskelä, Stina; Takalo, Mari; Marttinen, Mikael; Huber, Nadine; Paananen, Jussi; Mitra, Vikram; Rauramaa, Tuomas; Mäkinen, Petra; Leinonen, Ville; Soininen, Hilkka; Pike, Ian; Remes, Anne M; et al. (J Alzheimers Dis, 2018)
A subset of C9orf72 repeat expansion-carrying frontotemporal dementia patients display an Alzheimer-like decrease in cerebrospinal fluid amyloid-β (Aβ) biomarker levels. We report that downregulation of C9orf72 in non-neuronal human cells overexpressing amyloid-β protein precursor (AβPP) resulted in increased levels of secreted AβPP fragments and Aβ, while levels of AβPP or its C-terminal fragments (CTFs) remained unchanged. In neuronal cells, AβPP and C83 CTF levels were decreased upon C9orf72 knockdown, but those of secreted AβPP fragments or Aβ remained unchanged. C9orf72 protein levels significantly increased in human brain with advancing neurofibrillary pathology and positively correlated with brain Aβ42 levels. Our data suggest that altered C9orf72 levels may lead to cell-type specific alterations in AβPP processing, but warrant further studies to clarify the underlying mechanisms.

Intracranial Transplantation of Pancreatic Islets Attenuates Cognitive and Peripheral Metabolic Dysfunctions in a Rat Model of Sporadic Alzheimer's Disease. - Bloch, Konstantin; Gil-Ad, Irit; Vanichkin, Alexey; Hornfeld, Shay Henry; Taler, Michal; Dar, Shira; Azarov, Dmitry; Vardi, Pnina; Weizman, Abraham (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is often associated with brain insulin resistance and peripheral metabolic dysfunctions. Recently, we developed a model of sporadic AD associated with obesity-related peripheral metabolic abnormalities in Lewis rats using intracerebroventricular administration of streptozotocin (icv-STZ). OBJECTIVE: We aimed to assess the effect of intracranially grafted pancreatic islets on cognitive and peripheral metabolic dysfunctions in the icv-STZ Lewis rats. METHODS: AD-like dementia associated with obesity was induced in inbred Lewis rats using a single icv-STZ. Two months after icv-STZ, syngeneic islets (100 islets per recipient) were implanted in the cranial subarachnoid cavity of icv-STZ rats. Morris water maze and marble burying tests were used for studying cognitive and behavioral functions. Central and peripheral metabolic alterations were assessed by histological and biochemical assays. RESULTS: The icv-STZ induced increases in food intake, body weight, and blood levels of insulin and leptin without alteration of glucose homeostasis. Grafted islets reduced body weight gain, food consumption, peripheral insulin resistance, and hyperleptinemia. Biochemical and histological analysis of the brain revealed viable grafted islets expressing insulin and glucagon. The grafted islets did not affect expression of brain insulin receptors and peripheral glucose homeostasis. Two months after islet transplantation, cognitive and behavioral functioning in transplanted rats were significantly better than the sham-operated icv-STZ rats. No significant differences in the locomotor activity between transplanted and non-transplanted icv-STZ rats were found. CONCLUSIONS: Intracranial islet transplantation attenuates cognitive decline and peripheral metabolic dysfunctions providing a novel therapeutic approach for sporadic AD associated with peripheral metabolic dysfunctions.

Involvement of Activation of Asparaginyl Endopeptidase in Tau Hyperphosphorylation in Repetitive Mild Traumatic Brain Injury. - Hu, Wen; Tung, Yunn Chyn; Zhang, Yanchong; Liu, Fei; Iqbal, Khalid (J Alzheimers Dis, 2018)
Traumatic brain injury (TBI) is an established risk factor for the development of neurodegeneration and dementia late in life. Repetitive mild TBI (r-mTBI) is directly associated with chronic traumatic encephalopathy (CTE), a progressive neurodegenerative disorder characterized by focal perivascular to widespread Alzheimer-type neurofibrillary pathology of hyperphosphorylated tau. Studies in animal models have shown hyperphosphorylation of tau after TBI. However, the molecular mechanisms by which TBI leads to tau pathology are not understood. In this study, we employed western blots and immunohistochemistry to test, in triple-transgenic mouse model of Alzheimer's disease (3xTg-AD), the effect of r-mTBI on tau hyperphosphorylation and activation of asparaginyl endopeptidase (AEP), a cysteine proteinase which is known to be involved in tau hyperphosphorylation. We found that the level of active AEP was increased and correlated with the level of tau hyperphosphorylation following r-mTBI, and that fimbria showed increased immunoreactivity to phospho-tau. In addition, inhibitor 2 of protein phosphatase 2A (I2PP2A) was translocated from neuronal nucleus to the cytoplasm and colocalized with hyperphosphorylated tau. These data suggest the involvement of AEP-I2PP2A-PP2A-ptau pathway in tau pathology in TBI.

Ketogenic Medium Chain Triglycerides Increase Brain Energy Metabolism in Alzheimer's Disease. - Croteau, Etienne; Castellano, Christian-Alexandre; Richard, Marie Anne; Fortier, Mélanie; Nugent, Scott; Lepage, Martin; Duchesne, Simon; Whittingstall, Kevin; Turcotte, Éric E; Bocti, Christian; Fülöp, Tamás; Cunnane, Stephen C (J Alzheimers Dis, 2018)
BACKGROUND: In Alzheimer's disease (AD), it is unknown whether the brain can utilize additional ketones as fuel when they are derived from a medium chain triglyceride (MCT) supplement. OBJECTIVE: To assess whether brain ketone uptake in AD increases in response to MCT as it would in young healthy adults. METHODS: Mild-moderate AD patients sequentially consumed 30 g/d of two different MCT supplements, both for one month: a mixture of caprylic (55%) and capric acids (35%) (n = 11), followed by a wash-out and then tricaprylin (95%; n = 6). Brain ketone (11C-acetoacetate) and glucose (FDG) uptake were quantified by PET before and after each MCT intervention. RESULTS: Brain ketone consumption doubled on both types of MCT supplement. The slope of the relationship between plasma ketones and brain ketone uptake was the same as in healthy young adults. Both types of MCT increased total brain energy metabolism by increasing ketone supply without affecting brain glucose utilization. CONCLUSION: Ketones from MCT compensate for the brain glucose deficit in AD in direct proportion to the level of plasma ketones achieved.

Lipid Metabolism and Survival Across the Frontotemporal Dementia-Amyotrophic Lateral Sclerosis Spectrum: Relationships to Eating Behavior and Cognition. - Ahmed, Rebekah M; Highton-Williamson, Elizabeth; Caga, Jashelle; Thornton, Nicolette; Ramsey, Eleanor; Zoing, Margaret; Kim, Woojin Scott; Halliday, Glenda M; Piguet, Olivier; Hodges, John R; Farooqi, I Sadaf; Kiernan, Matthew C (J Alzheimers Dis, 2018)
BACKGROUND: Patients with frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) exhibit changes in eating behavior that could potentially affect lipid levels. OBJECTIVE: This study aimed to document changes in lipid metabolism across the ALS-FTD spectrum to identify potential relationships to eating behavior (including fat intake), cognitive change, body mass index (BMI), and effect on survival. METHODS: One hundred and twenty-eight participants were recruited: 37 ALS patients, 15 ALS patients with cognitive and behavioral change (ALS-Plus), 13 ALS-FTD, 31 behavioral variant FTD, and 32 healthy controls. Fasting total cholesterol, low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL) and triglyceride levels were measured and correlated to eating behavior (caloric, fat intake), cognitive change, and BMI; effect on survival was examined using cox regression analyses. RESULTS: There was a spectrum of lipid changes from ALS to FTD with increased triglyceride (p < 0.001), total cholesterol/HDL ratio (p < 0.001), and lower HDL levels (p = 0.001) in all patient groups compared to controls. While there was no increase in total cholesterol levels, a higher cholesterol level was found to correlate with 3.25 times improved survival (p = 0.008). Triglyceride and HDL cholesterol levels correlated to fat intake, BMI, and measures of cognition and disease duration. CONCLUSION: A spectrum of changes in lipid metabolism has been identified in ALS-FTD, with total cholesterol levels found to potentially impact on survival. These changes were mediated by changes in fat intake, and BMI, and may also be mediated by the neurodegenerative process, offering the potential to modify these factors to slow disease progression and improve survival.
Keywords: Adult; Aged; Amyotrophic Lateral Sclerosis; Australia; Body Mass Index; Case-Control Studies; Cholesterol; Cholesterol, HDL; Cognition; Energy Intake; Feeding Behavior; Female; Frontotemporal Dementia; Humans; Lipid Metabolism; Male; Middle Aged; Neuropsychological Tests; Survival Analysis

Longitudinal Neuroimaging Analysis in Mild-Moderate Alzheimer's Disease Patients Treated with Plasma Exchange with 5% Human Albumin. - Cuberas-Borrós, Gemma; Roca, Isabel; Boada, Merce; Tárraga, Lluís; Hernandez, Isabel; Buendia, Mar; Rubio, Lourdes; Torres, Gustavo; Bittini, Ángel; Guzmán-de-Villoria, Juan A; Pujadas, Francesc; Torres, Mireia; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Recently, modifications of Aβ1-42 levels in CSF and plasma associated with improvement in memory and language functions have been observed in patients with mild-moderate Alzheimer's disease (AD) treated with plasma exchange (PE) with albumin replacement. OBJECTIVE: To detect structural and functional brain changes in PE-treated AD patients as part of a Phase II clinical trial. METHODS: Patients received between 3 and 18 PE with albumin (Albutein® 5%, Grifols) or sham-PE (controls) for 21 weeks (divided in one intensive and two maintenance periods) followed by 6-month follow-up. Brain perfusion assessed by SPECT scans using an automated software (NeuroGam®) and brain structural changes assessed by MRI were performed at weeks 0 (baseline), 21, and 44 (with additional SPECT at weeks 9 and 33). Statistical parametric mapping (voxel-based analysis, SPM) and Z-scores calculations were applied to investigate changes to baseline. RESULTS: 42 patients were recruited (39 evaluable; 37 analyzed: 18 PE-treated; 19 controls). There was a trend toward decreasing hippocampi and total intracranial volume for both patient groups during the study (p < 0.05). After six months, PE-treated patients had less cerebral perfusion loss than controls in frontal, temporal, and parietal areas, and perfusion stabilization in Brodmann area BA38-R during the PE-treatment period (p < 0.05). SPM analysis showed stabilization or absence of progression of perfusion loss in PE-treated patients until week 21, not observed in controls. CONCLUSIONS: Mild-moderate AD patients showed decreased brain volume and impairment of brain perfusion as expected for the progression of the disease. PE-treatment with albumin replacement favored the stabilization of perfusion.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Plasma Exchange; Serum Albumin, Human; Time Factors; Tomography, Emission-Computed, Single-Photon; Treatment Outcome

A Longitudinal Study of Total and Phosphorylated α-Synuclein with Other Biomarkers in Cerebrospinal Fluid of Alzheimer's Disease and Mild Cognitive Impairment. - Wang, Hua; Stewart, Tessandra; Toledo, Jon B; Ginghina, Carmen; Tang, Lu; Atik, Anzari; Aro, Patrick; Shaw, Leslie M; Trojanowski, John Q; Galasko, Douglas R; Edland, Steven; Jensen, Poul H; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) features a dynamic sequence of amyloid deposition, neurodegeneration, and cognitive impairment. A significant fraction of AD brains also displays Lewy body pathology, suggesting that addition of classically Parkinson's disease-related proteins to the AD biomarker panel may be of value. To determine whether addition of cerebrospinal fluid (CSF) total α-synuclein and its form phosphorylated at S129 (pS129) to the AD biomarker panel [Amyloid-β1-42 (Aβ42), tau, and phosphorylated tau (p-tau181)] improves its performance, we examined CSF samples collected longitudinally up to 7 years as part of the Alzheimer's Disease Neuroimaging Initiative. From 87 AD, 177 mild cognitive impairment (MCI), and 104 age-matched healthy controls, 792 baseline and longitudinal CSF samples were tested for total α-synuclein, pS129, Aβ42, tau, and p-tau181. pS129, but not total α-synuclein, was weakly associated with diagnosis at baseline when t-tau/Aβ42 was included in the statistical model (β= 0.0026, p = 0.041, 95% CI [(0.0001)-(0.005)]). CSF α-synuclein predicted Alzheimer's Disease Assessment Scale-Cognitive (β= -0.59, p = 0.0015, 95% CI [(-0.96)-(-0.23)]), memory (β= 0.4, p = 0.00025, 95% CI [(0.16)-(0.59)]), and executive (0.62,<0.0001, 95% CI [(0.31)-(0.93)]) function composite scores, and progression from MCI to AD (β= 0.019, p = 0.0011, 95% CI [(0.002)-(0.20)]). pS129 was associated with executive function (β= -2.55, p = 0.0085, 95% CI [(-4.45)-(-0.66)]). Lower values in the mismatch between α-synuclein and p-tau181 predicted faster cognitive decline (β= 0.64, p = 0.0012, 95% CI [(0.48)-(0.84)]). Longitudinal biomarker changes did not differ between groups, and may not reflect AD progression. The α-synuclein-p-tau181-Mismatch could better predict longitudinal cognitive changes than classical AD markers alone, and its pathological correlates should be investigated further.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Executive Function; Female; Humans; Linear Models; Longitudinal Studies; Male; Memory Disorders; Multivariate Analysis; Neuropsychological Tests; Phosphorylation; tau Proteins

Low Accuracy of Brief Cognitive Tests in Tracking Longitudinal Cognitive Decline in an Asian Elderly Cohort. - Phua, April Ka Sin; Hiu, Shaun Kuan Wei; Goh, Win King; Ikram, Mohammad Kamran; Venketasubramanian, Narayanaswamy; Tan, Boon Yeow; Chen, Christopher Li-Hsian; Xu, Xin (J Alzheimers Dis, 2018)
BACKGROUND: Researchers have questioned the utility of brief cognitive tests such as the Mini-Mental Status Examination (MMSE) and the Montreal Cognitive Assessment (MoCA) in serial administration and suggested that brief cognitive tests may not accurately track changes in Global Cognition. OBJECTIVE: To examine the accuracy of longitudinal changes on brief cognitive tests in reflecting progression in Global Cognition measured using comprehensive neuropsychological assessments. METHODS: Two hundred and seven participants were assessed with the MMSE, MoCA, and a validated comprehensive neuropsychological battery. Global z-scores on the battery were derived and used to assess overall and significant (≥0.5 standard deviation) decline on Global Cognition. Different patterns of decline on MMSE/MoCA were classified. Accuracy was examined using receiver operating characteristic curve, and sensitivity, specificity, positive (PPV) and negative (NPV) predictive values were reported. RESULTS: The overall ability of MMSE/MoCA change scores to discriminate participants who did and did not decline on Global Cognition was fair-to-moderate (AUC [95% CI] = 0.71 [0.64-0.78] & 0.73 [0.66-0.80] for overall decline; 0.78 [0.70-0.85] & 0.80 [0.73-0.86] for significant decline, respectively). Changes in MMSE/MoCA had low accuracy in identifying significant Global Cognitive Decline (PPV = 0.41 & 0.46, respectively) but high accuracy in ruling out significant decline and identifying cognitively stable participants (NPV = 0.89 & 0.88, respectively). CONCLUSION: There is limited utility in brief cognitive tests for tracking cognitive decline. Instead, they should be used for identifying participants who remain cognitively stable on follow up. These results accentuate the importance of acknowledging the limitations of brief cognitive tests when assessing cognitive change.

Mechanism of Tau Hyperphosphorylation Involving Lysosomal Enzyme Asparagine Endopeptidase in a Mouse Model of Brain Ischemia. - Basurto-Islas, Gustavo; Gu, Jin-Hua; Tung, Yunn Chyn; Liu, Fei; Iqbal, Khalid (J Alzheimers Dis, 2018)
Dementias including Alzheimer's disease (AD) are multifactorial disorders that involve several different etiopathogenic mechanisms. Cerebral ischemia has been suspected in the altered regulation of protein kinases and phosphatases that leads to hyperphosphorylation of tau and further neurofibrillary pathology, a key hallmark of AD and related neurodegenerative diseases. However, the deregulation of these enzymes and their relationship with ischemia and AD remain unclear. Previously, we reported a mechanism by which the lysosomal enzyme asparagine endopeptidase (AEP) is associated with brain acidosis and AD. In this study, we subjected mice to middle cerebral artery occlusion and found that compared with wild type mice, the ischemia-induced brain injury and motor deficit in AEP-knockout mice are reduced, probably because ischemia activates AEP. AEP cleaves inhibitor 2 of protein phosphatase 2A (I2PP2A), which translocates from the neuronal nucleus to the cytoplasm and produces hyperphosphorylation of tau through inhibition of PP2A. These findings suggest a possible mechanism of tau pathology associated with ischemia.

Medical Comorbidity in Alzheimer's Disease: A Nested Case-Control Study. - Wang, Jen-Hung; Wu, Ya-Ju; Tee, Boon Lead; Lo, Raymond Y (J Alzheimers Dis, 2018)
BACKGROUND: Little is known about the distribution of medical comorbidities in Alzheimer's disease (AD). OBJECTIVE: We aimed to describe the comorbidity pattern of AD in a nested case-control study. METHODS: Incident AD cases were identified by International Classification of Diseases codes in a random sample of 2 million individuals in Taiwan National Health Insurance program during 2001-2011. We further restricted cases to those treated with AD drugs of approved reimbursement. We sampled a set of age- and sex-matched control subjects (2:1 ratio) and employed conditional logistic regression to estimate the associations between pre-specified 14 comorbidities and AD. The clusters of multiple chronic diseases were then identified by exploratory factor analysis. RESULTS: A total of 2,618 AD cases were identified during 2001-2011 with a mean age of 76.1 years and female preponderance (59%). The most common 5 comorbidities in AD were hypertension (55.1%), osteoarthritis (38.2%), depression (32.3%), diabetes mellitus (DM) (25.7%), and cerebrovascular disease (CVD) (22.7%). After adjusting for age and sex, DM, osteoporosis, depression, and CVD were significantly associated with AD. The number of comorbidity was 3-fold greater in the AD group. The cluster of hypertension, DM, and hyperlipidemia was the most common combination in old age, whereas the cluster osteoarthritis and osteoporosis was the only multimorbidity pattern significantly associated with AD. CONCLUSION: Multimorbidity is common in AD. Depression, CVD, osteoporosis, and DM are associated with incident AD, supporting that their co-existence is a typical feature of AD at old age. Comorbidity care should be integrated into current management for patients with AD.

Melatonin in Synaptic Impairments of Alzheimer's Disease. - Shi, Yan; Fang, Ying-Yan; Wei, Yu-Ping; Jiang, Qian; Zeng, Peng; Tang, Na; Lu, Youming; Tian, Qing (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) underlies dementia for millions of people worldwide with no effective treatment. The dementia of AD is thought stem from the impairments of the synapses because of their critical roles in cognition. Melatonin is a neurohormone mainly released by the pineal gland in a circadian manner and it regulates brain functions in various manners. It is reported that both the melatonin deficit and synaptic impairments are present in the very early stage of AD and strongly contribute to the progress of AD. In the mammalian brains, the effects of melatonin are mainly relayed by two of its receptors, melatonin receptor type 1a (MT1) and 1b (MT2). To have a clear idea on the roles of melatonin in synaptic impairments of AD, this review discussed the actions of melatonin and its receptors in the stabilization of synapses, modulation of long-term potentiation, as well as their contributions in the transmissions of glutamatergic, GABAergic and dopaminergic synapses, which are the three main types of synapses relevant to the synaptic strength. The synaptic protective roles of melatonin in AD treatment were also summarized. Regarding its protective roles against amyloid-β neurotoxicity, tau hyperphosphorylation, oxygenation, inflammation as well as synaptic dysfunctions, melatonin may be an ideal therapeutic agent against AD at early stage.

Meta-Analysis of the Association between Variants in ABCA7 and Alzheimer's Disease. - Ma, Fang-Chen; Wang, Hui-Fu; Cao, Xi-Peng; Tan, Chen-Chen; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2018)
The ATP-binding cassette transporter A7 (ABCA7) was identified as a known risk factor for Alzheimer's disease (AD). However, the relation between ABCA7 and AD was still inconsistent across these studies. Here, our meta-analysis aimed at confirming the association of ABCA7 with AD. Finally, 16 case-control studies (63747 versus 85833) were retrieved from PubMed and other databases. Three common loci were confirmed to increase the risk of AD (rs3764650: OR = 1.20, 95% CI = 1.16-1.24; rs3752246: OR = 1.13,95% CI = 1.08-1.19; rs4147929: OR = 1.17, 95% CI = 1.10-1.24), but the associations varied among the different races. Furthermore, ABCA7 loss-of-function (LOF) mutations conferred a higher risk for AD than did the above variants (LOF: OR = 1.78, 95%  = 1.43-2.22). In conclusion, ABCA7 genetic variants, especially the LOF mutations, were significantly associated with the risk of AD.

Metabolomics Analyses of Saliva Detect Novel Biomarkers of Alzheimer's Disease. - Huan, Tao; Tran, Tran; Zheng, Jiamin; Sapkota, Shraddha; MacDonald, Stuart W; Camicioli, Richard; Dixon, Roger A; Li, Liang (J Alzheimers Dis, 2018)
Using a non-invasive biofluid (saliva), we apply a powerful metabolomics workflow for unbiased biomarker discovery in Alzheimer's disease (AD). We profile and differentiate Cognitively Normal (CN), Mild Cognitive Impairment (MCI), and AD groups. The workflow involves differential chemical isotope labeling liquid chromatography mass spectrometry using dansylation derivatization for in-depth profiling of the amine/phenol submetabolome. The total sample (N = 109) was divided in to the Discovery Phase (DP) (n = 82; 35 CN, 25 MCI, 22 AD) and a provisional Validation Phase (VP) (n = 27; 10 CN, 10 MCI, 7 AD). In DP we detected 6,230 metabolites. Pairwise analyses confirmed biomarkers for AD versus CN (63), AD versus MCI (47), and MCI versus CN (2). We then determined the top discriminating biomarkers and diagnostic panels. A 3-metabolite panel distinguished AD from CN and MCI (DP and VP: Area Under the Curve [AUC] = 1.000). The MCI and CN groups were best discriminated with a 2-metabolite panel (DP: AUC = 0.779; VP: AUC = 0.889). In addition, using positively confirmed metabolites, we were able to distinguish AD from CN and MCI with good diagnostic performance (AUC > 0.8). Saliva is a promising biofluid for both unbiased and targeted AD biomarker discovery and mechanism detection. Given its wide availability and convenient accessibility, saliva is a biofluid that can promote diversification of global AD biomarker research.

Methylenetetrahydrofolate Reductase Deficiency Deregulates Regional Brain Amyloid-β Protein Precursor Expression and Phosphorylation Levels. - Hoffman, Alexander; Taleski, Goce; Qian, Helena; Wasek, Brandi; Arning, Erland; Bottiglieri, Teodoro; Sontag, Jean-Marie; Sontag, Estelle (J Alzheimers Dis, 2018)
Deregulation of the amyloid-β protein precursor (AβPP) plays a critical role in the neurodegenerative cascade of Alzheimer's disease (AD). Significantly, common functional polymorphisms in the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene are a risk factor for the development of late-onset AD. Reduced MTHFR activity is associated with alterations in folate and homocysteine metabolism. Here, we first show that in young MTHFR knockout mice, mild and severe MTHFR deficiency markedly increase cortical and hippocampal AβPP phosphorylation at the regulatory Thr668 site. However, the hippocampus is especially vulnerable to the effects of aging and mild MTHFR deficiency. Notably, the effects of severe MTHFR deficiency in young mice are recapitulated by prolonged dietary folate deficiency in old mice, which leads to regional brain accumulation of cystathionine due to impaired methylation of homocysteine. The incremental AβPP phosphorylation at Thr668 mediated by severe genetic-or diet-induced impairment of the folate cycle correlates with enhanced accumulation of demethylated protein phosphatase 2A (PP2A), and activation of glycogen synthase kinase-3β (GSK-3β). Lastly, we show that severe disturbances in folate metabolism can also affect AβPP expression levels in a brain region specific manner. Together our findings identify a novel link between genetic MTHFR deficiency, activation of GSK-3β, demethylation of PP2A, and enhanced phosphorylation of AβPP at Thr668, which is known to critically influence neuronal AβPP function and pathological amyloidogenic processing. Deregulation of AβPP provides a novel mechanism by which common human MTHFR polymorphisms may interact with dietary folate deficiency to alter neuronal homeostasis and increase the risk for sporadic AD.

Microglial Activation During Pathogenesis of Tauopathy in rTg4510 Mice: Implications for the Early Diagnosis of Tauopathy. - Sahara, Naruhiko; Maeda, Jun; Ishikawa, Ai; Tokunaga, Masaki; Suhara, Tetsuya; Higuchi, Makoto (J Alzheimers Dis, 2018)
Tauopathy is characterized by the fibrillar tau accumulation in neurons and glial cells. In order to advance our understanding of the causative mechanisms of tauopathy, neuroinflammation, which has been suggested to play important roles in disease progression, will require particular attention. Neuroinflammation is characterized predominantly by microglial activation. At present, it is still under debate whether microglial activation is a cause or a result of neurodegeneration. To search for a temporal relationship between neurodegeneration and neuroinflammation, our group demonstrated that in vivo imaging (e.g., tau-PET, TSPO-PET, and volumetric MRI) of tauopathy mice strongly supports the evidence of microglial activation along with both pathological tau accumulation and brain atrophy. Both in vivo imaging and histochemical analysis confirmed that microglial TSPO accumulation was the late event during the pathogenesis of tauopathy. On the other hand, it is known that purinergic receptor P2Y12 as a marker of homeostatic microglia cells was reduced at an early stage of disease progression. In this review, we will introduce a phenotypic change of microglia in a mouse model of tauopathy and propose novel approaches to the establishment of imaging biomarkers, thereby targeting the early diagnosis of tauopathy.

Mitochondrial Dysfunction as a Predictor and Driver of Alzheimer's Disease-Like Pathology in OXYS Rats. - Tyumentsev, Mikhail A; Stefanova, Natalia A; Muraleva, Natalia A; Rumyantseva, Yulia V; Kiseleva, Elena; Vavilin, Valentin A; Kolosova, Nataliya G (J Alzheimers Dis, 2018)
Growing evidence suggests that mitochondrial dysfunction is an early event in sporadic Alzheimer's disease (AD), but the impact of mitochondrial dysfunction on the transition from healthy aging to AD remains elusive. Here we estimated the influence of mitochondrial dysfunction on the initiation of AD signs in OXYS rats, which simulate key characteristics of sporadic AD. We assessed the mitochondrial ultrastructure of pyramidal neurons of the hippocampus at the age preceding the development (age 20 days), during manifestation (4-5 months), and at the well-pronounced stages (18-24 months) of the AD-like pathology in OXYS rats. Ultrastructural alterations were collated with the amounts of proteins mediating mitochondrial dynamics [mitofusins (MFN1 and MFN2) and dynamin-1-like protein (DRP1)]; with activity of respiratory chain complexes I, IV, and V in the hippocampal mitochondria; with reactive oxygen species (ROS) production; and with expression of uncoupling protein 2 (UCP2) regulating ROS production. Already at the preclinical stage, OXYS rats showed some characteristic changes in hippocampal mitochondria, which increased in size with the manifestation and progression of AD-like pathology, including decreased activity of respiratory complexes against the background of greater fusion and formation of larger mitochondria. Signs of AD developed simultaneously with increasing dysfunction of mitochondria, with a dramatic decrease in their number, and with increased fission but without upregulation of ROS production (observed only in 20-day-old OXYS rats). Summarizing the data from our present and previous studies, we conclude that mitochondrial dysfunction appears to mediate or possibly even initiate pathological molecular cascades of AD-like pathology in OXYS rats and can be considered a predictor of the early development of the late-onset form of AD in humans.

The Montreal Cognitive Assessment: Normative Data from a German-Speaking Cohort and Comparison with International Normative Samples. - Thomann, Alessandra E; Goettel, Nicolai; Monsch, Raphael J; Berres, Manfred; Jahn, Thomas; Steiner, Luzius A; Monsch, Andreas U (J Alzheimers Dis, 2018)
BACKGROUND: The Montreal Cognitive Assessment (MoCA) is used to evaluate multiple cognitive domains in elderly individuals. However, it is influenced by demographic characteristics that have yet to be adequately considered. OBJECTIVE: The aim of our study was to investigate the effects of age, education, and sex on the MoCA total score and to provide demographically adjusted normative values for a German-speaking population. METHODS: Subjects were recruited from a registry of healthy volunteers. Cognitive health was defined using the Mini-Mental State Examination (score ≥27/30 points) and the Consortium to Establish a Registry for Alzheimer's Disease-Neuropsychological Assessment Battery (total score ≥85.9 points). Participants were assessed with the German version of the MoCA. Normative values were developed based on regression analysis. Covariates were chosen using the Predicted Residual Sums of Squares approach. RESULTS: The final sample consisted of 283 participants (155 women, 128 men; mean (SD) age = 73.8 (5.2) years; education = 13.6 (2.9) years). Thirty-one percent of participants scored below the original cut-off (<26/30 points). The MoCA total score was best predicted by a regression model with age, education, and sex as covariates. Older age, lower education, and male sex were associated with a lower MoCA total score (p < 0.001). CONCLUSION: We developed a formula to provide demographically adjusted standard scores for the MoCA in a German-speaking population. A comparison with other MoCA normative studies revealed considerable differences with respect to selection of volunteers and methods used to establish normative data.

MRI-Based Screening of Preclinical Alzheimer's Disease for Prevention Clinical Trials. - Casamitjana, Adrià; Petrone, Paula; Tucholka, Alan; Falcon, Carles; Skouras, Stavros; Molinuevo, José Luis; Vilaplana, Verónica; Gispert, Juan Domingo (J Alzheimers Dis, 2018)
The identification of healthy individuals harboring amyloid pathology represents one important challenge for secondary prevention clinical trials in Alzheimer's disease (AD). Consequently, noninvasive and cost-efficient techniques to detect preclinical AD constitute an unmet need of critical importance. In this manuscript, we apply machine learning to structural MRI (T1 and DTI) of 96 cognitively normal subjects to identify amyloid-positive ones. Models were trained on public ADNI data and validated on an independent local cohort. Used for subject classification in a simulated clinical trial setting, the proposed method is able to save 60% of unnecessary CSF/PET tests and to reduce 47% of the cost of recruitment. This recruitment strategy capitalizes on available MR scans to reduce the overall amount of invasive PET/CSF tests in prevention trials, demonstrating a potential value as a tool for preclinical AD screening. This protocol could foster the development of secondary prevention strategies for AD.

Multicenter Resting State Functional Connectivity in Prodromal and Dementia Stages of Alzheimer's Disease. - Teipel, Stefan J; Metzger, Coraline D; Brosseron, Frederic; Buerger, Katharina; Brueggen, Katharina; Catak, Cihan; Diesing, Dominik; Dobisch, Laura; Fliebach, Klaus; Franke, Christiana; Heneka, Michael T; Kilimann, Ingo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alterations of intrinsic networks from resting state fMRI (rs-fMRI) have been suggested as functional biomarkers of Alzheimer's disease (AD). OBJECTIVE: To determine the diagnostic accuracy of multicenter rs-fMRI for prodromal and preclinical stages of AD. METHODS: We determined rs-fMRI functional connectivity based on Pearson's correlation coefficients and amplitude of low-frequency fluctuation in people with subjective cognitive decline, people with mild cognitive impairment, and people with AD dementia compared with healthy controls. We used data of 247 participants of the prospective DELCODE study, a longitudinal multicenter observational study, imposing a unified fMRI acquisition protocol across sites. We determined cross-validated discrimination accuracy based on penalized logistic regression to account for multicollinearity of predictors. RESULTS: Resting state functional connectivity reached significant cross-validated group discrimination only for the comparison of AD dementia cases with healthy controls, but not for the other diagnostic groups. AD dementia cases showed alterations in a large range of intrinsic resting state networks, including the default mode and salience networks, but also executive and language networks. When groups were stratified according to their CSF amyloid status that was available in a subset of cases, diagnostic accuracy was increased for amyloid positive mild cognitive impairment cases compared with amyloid negative controls, but still inferior to the accuracy of hippocampus volume. CONCLUSION: Even when following a strictly harmonized data acquisition protocol and rigorous scan quality control, widely used connectivity measures of multicenter rs-fMRI do not reach levels of diagnostic accuracy sufficient for a useful biomarker in prodromal stages of AD.

A Multi-Center Study on Human Brain Glutathione Conformation using Magnetic Resonance Spectroscopy. - Shukla, Deepika; Mandal, Pravat K; Ersland, Lars; Grüner, Eli Renate; Tripathi, Manjari; Raghunathan, Partha; Sharma, Ankita; Chaithya, G R; Punjabi, Khushboo; Splaine, Christopher (J Alzheimers Dis, 2018)
Molecular dynamics simulation and in vitro nuclear magnetic resonance (NMR) studies on glutathione (GSH) indicated existence of closed and extended conformations. The present work in a multi-center research setting reports in-depth analysis of GSH conformers in vivo using a common magnetic resonance spectroscopy (MRS) protocol and signal processing scheme. MEGA-PRESS pulse sequence was applied on healthy subjects using 3T Philips MRI scanner (India) and 3T GE MRI scanner (Norway) using the same experimental parameters (echo time, repetition time, and selective 180° refocusing ON-pulse at 4.40 ppm and 4.56 ppm). All MRS data were processed at one site National Brain Research Center (NBRC) using in-house MRS processing toolbox (KALPANA) for consistency. We have found that both the closed and extended GSH conformations are present in human brain and the relative proportion of individual conformer peak depends on the specific selection of refocusing ON-pulse position in MEGA-PRESS pulse sequence. It is important to emphasize that in vivo experiments with different refocusing and inversion pulse positions, echo time, and voxel size, clearly evidence the presence of both the GSH conformations. The GSH conformer peak positions for the closed GSH (Cys-Hβ) peak at ∼2.80 ppm and extended GSH (Cys-Hβ) peak at ∼2.95 ppm remain consistent irrespective of the selective refocusing OFF-pulse positions. This is the first in vivo study where both extended and closed GSH conformers are detected using the MEGA-PRESS sequence employing the parameters derived from the high resolution in vitro NMR studies on GSH.

Multi-Parametric Classification of Vascular Cognitive Impairment and Dementia: The Impact of Diverse Cerebrovascular Injury Biomarkers. - Lang, Brittany; Kindy, Mark S; Kozel, F Andrew; Schultz, Susan K; Taheri, Saeid (J Alzheimers Dis, 2018)
Vascular cognitive impairment and dementia (VCID) is a diagnostic term applied to cognitively impaired individuals with heterogeneous cerebrovascular conditions affecting large and/or small vessels. Individual biomarkers have been identified as instrumental in relating VCID to specific underlying pathologies to better characterize this syndrome. Emerging research to refine panels of biomarkers will increase classification sensitivity and specificity. Refined VCID clustering based on the severity and pathology of vascular injury will permit the development of optimal prevention and treatment strategies. Here, we review recently reported data concerning the diversity of VCID-related pathology and attempts for VCID clustering based on biomarkers obtained from different sets of measurements. We discuss three major sets of biomarkers: 1) neuroimaging biomarkers, 2) neuropsychological performance measures, and 3) biochemical markers in current VCID clustering. Finally, we highlight the effect of blood-brain barrier health on cerebrovascular disease trajectory.

Nailfold Capillary Morphology in Alzheimer's Disease Dementia. - Cousins, Clara C; Alosco, Michael L; Cousins, Henry C; Chua, Alicia; Steinberg, Eric G; Chapman, Kimberly R; Bing-Canar, Hanaan; Tripodis, Yorghos; Knepper, Paul A; Stern, Robert A; Pasquale, Louis R (J Alzheimers Dis, 2018)
BACKGROUND: Cerebrovascular disease (CVD) is highly comorbid with Alzheimer's disease (AD), yet its role is not entirely understood. Nailfold video capillaroscopy (NVC) is a noninvasive method of live imaging the capillaries near the fingernail's cuticle and may help to describe further vascular contributions to AD. OBJECTIVE: To examine finger nailfold capillary morphology using NVC in subjects with AD dementia, mild cognitive impairment (MCI), and normal cognition (NC). METHODS: We evaluated nailfold capillary hemorrhages, avascular zones ≥100 microns, and degree of tortuosity in 28 NC, 15 MCI, and 18 AD dementia subjects using NVC. Tortuosity was measured with a semi-quantitative rating scale. To assess the relation between nailfold capillary morphological features and diagnostic grouping, univariate and multivariable logistic regression models were fit to the data. RESULTS: 56% of subjects with AD dementia compared to 14% with NC and 13% with MCI displayed moderate to severe tortuosity. Greater severity of tortuosity was associated with 10.6-fold (95% confidence interval [CI]: 2.4, 46.2; p = 0.0018) and 7.4-fold (95% CI: 1.3, 41.3; p = 0.023) increased odds of AD dementia relative to NC and MCI, respectively, after adjusting for multiple covariates. CONCLUSION: Greater nailfold capillary tortuosity was found in participants with AD dementia compared to those with MCI or NC. These data provide preliminary evidence of a systemic microvasculopathy in AD that may be noninvasively and inexpensively evaluated through NVC.

A Natural Benzofuran from the Patagonic Aleurodiscus vitellinus Fungus has Potent Neuroprotective Properties on a Cellular Model of Amyloid-β Peptide Toxicity. - González-Ramírez, Mariela; Gavilán, Javiera; Silva-Grecchi, Tiare; Cajas-Madriaga, Daniel; Triviño, Sergio; Becerra, José; Saez-Orellana, Francisco; Pérez, Claudia; Fuentealba, Jorge (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by amyloid plaques that form due to an increase in amyloid-β peptide (Aβ) aggregation. One strategy in the search of new treatments for AD focuses on compounds that decrease Aβ accumulation. Compounds containing a benzofuran ring have been described to play an important role in decreasing Aβ-induced toxicity; however, only synthetic benzofurans have been tested thus far. The aim of the present study was to examine the in vitro neuroprotective properties of fomannoxin (Fx), a natural benzofuran isolated from cultures of the Andean-Patagonian fungi Aleurodiscus vitellinus, and evaluate its effect on Aβ peptide. We tested the effect of Fx at a wide concentration range (10-11-10-4 M) in PC-12 cells, and found the compound did not alter cellular viability. Fx also showed a concentration-dependent effect on the Aβ-induced toxicity in PC12 cells, showing viability above 100% at 10-6 M. We then measured the effect of Fx (10-7-10-5 M) on the frequency of cytosolic Ca2+ transients in rat hippocampal neurons at both acute and chronic (24 h) times. Acute incubation with Fx increased the frequency of cytosolic Ca2+ transients to values around 200%, whereas chronic incubation with Fx increased the frequency of Ca2+ transients. Finally, the Aβ-induced decrease in intracellular Ca2+ transients was prevented when Fx (10-6 M) was co-incubated with Aβ (5×10-6 M). The results suggest a potent neuroprotective effect of this naturally occurring benzofuran against Aβ peptide toxicity that could be mediated by an interference with it binding to plasma membrane, and lead Fx as new chemical entity to develop pharmacological tools against Aβ peptide neurotoxicity.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Basidiomycota; Benzofurans; Cell Survival; Hippocampus; Neurons; Neuroprotective Agents; PC12 Cells; Plaque, Amyloid; Rats

Neuro-Immuno-Gene- and Genome-Editing-Therapy for Alzheimer's Disease: Are We There Yet? - Raikwar, Sudhanshu P; Thangavel, Ramasamy; Dubova, Iuliia; Ahmed, Mohammad Ejaz; Selvakumar, Pushpavathi Govindhasamy; Kempuraj, Duraisamy; Zaheer, Smita; Iyer, Shankar; Zaheer, Asgar (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a highly complex neurodegenerative disorder and the current treatment strategies are largely ineffective thereby leading to irreversible and progressive cognitive decline in AD patients. AD continues to defy successful treatment despite significant advancements in the field of molecular medicine. Repeatedly, early promising preclinical and clinical results have catapulted into devastating setbacks leading to multi-billion dollar losses not only to the top pharmaceutical companies but also to the AD patients and their families. Thus, it is very timely to review the progress in the emerging fields of gene therapy and stem cell-based precision medicine. Here, we have made sincere efforts to feature the ongoing progress especially in the field of AD gene therapy and stem cell-based regenerative medicine. Further, we also provide highlights in elucidating the molecular mechanisms underlying AD pathogenesis and describe novel AD therapeutic targets and strategies for the new drug discovery. We hope that the quantum leap in the scientific advancements and improved funding will bolster novel concepts that will propel the momentum toward a trajectory leading to a robust AD patient-specific next generation precision medicine with improved cognitive function and excellent life quality.

Neuroprotective Effects of Ferruginol, Jatrophone, and Junicedric Acid Against Amyloid-β Injury in Hippocampal Neurons. - Zolezzi, Juan M; Lindsay, Carolina B; Serrano, Felipe G; Ureta, Roxana C; Theoduloz, Cristina; Schmeda-Hirschmann, Guillermo; Inestrosa, Nibaldo C (J Alzheimers Dis, 2018)
Soluble amyloid-β (Aβ) oligomers have been recognized as early neurotoxic intermediates with a key role in the synaptic dysfunction observed in Alzheimer's disease (AD). Aβ oligomers block hippocampal long-term potentiation (LTP) and impair rodent spatial memory. Additionally, the presence of Aβ oligomers is associated with imbalanced intracellular calcium levels and apoptosis in neurons. In this context, we evaluated the effects of three diterpenes (ferruginol, jatrophone, and junicedric acid) that are found in medicinal plants and have several forms of biological activity. The intracellular calcium levels in hippocampal neurons increased in the presence of ferruginol, jatrophone, and junicedric acid, a result that was consistent with the observed increase in CA1 synaptic transmission in mouse hippocampal slices. Additionally, assays using Aβ peptide demonstrated that diterpenes, particularly ferruginol, restore LTP and reduce apoptosis. Recovery of the Aβ oligomer-induced loss of the synaptic proteins PSD-95, synapsin, VGlut, and NMDA receptor subunit 2A was observed in mouse hippocampal slices treated with junicedric acid. This cascade of events may be associated with the regulation of kinases, e.g., protein kinase C (PKC) and calcium/calmodulin-dependent protein kinase II (CaMKII), in addition to the activation of the canonical Wnt signaling pathway and could thus provide protection against Aβ oligomers, which trigger synaptic dysfunction. Our results suggest a potential neuroprotective role for diterpenes against the Aβ oligomers-induced neurodegenerative alterations, which make them interesting molecules to be further studied in the context of AD.

Neuropsychiatric Symptoms and the Diagnostic Stability of Mild Cognitive Impairment. - Sugarman, Michael A; Alosco, Michael L; Tripodis, Yorghos; Steinberg, Eric G; Stern, Robert A (J Alzheimers Dis, 2018)
BACKGROUND: Mild cognitive impairment (MCI) is an intermediate diagnosis between normal cognition (NC) and dementia, including Alzheimer's disease (AD) dementia. However, MCI is heterogeneous; many individuals subsequently revert to NC while others remain stable at MCI for several years. Identifying factors associated with this diagnostic instability could assist in defining clinical populations and determining cognitive prognoses. OBJECTIVE: The current study examined whether neuropsychiatric symptoms could partially account for the temporal instability in cognitive diagnoses. METHOD: The sample included 6,763 participants from the National Alzheimer's Coordinating Center Uniform Data Set. All participants had NC at baseline, completed at least two follow-up visits (mean duration: 5.5 years), and had no recent neurological conditions. Generalized linear models estimated by generalized estimating equations examined associations between changes in cognitive diagnoses and symptoms on the Neuropsychiatric Inventory Questionnaire (NPI-Q) and Geriatric Depression Scale (GDS-15). RESULTS: 1,121 participants converted from NC to MCI; 324 reverted back to NC and 242 progressed to AD dementia. Higher symptoms on the GDS-15 and circumscribed symptom domains on the NPI-Q were associated with conversion from NC to MCI and a decreased likelihood of reversion from MCI to NC. Individuals with higher symptoms on NPI-Q Hyperactivity and Mood items were more likely to progress to AD dementia. DISCUSSION: The temporal instability of MCI can be partially explained by neuropsychiatric symptoms. Individuals with higher levels of specific symptoms are more likely to progress to AD dementia and less likely to revert to NC. Identification and treatment of these symptoms might support cognitive functioning in older adults.

A New Perspective in Utilizing MMP-9 as a Therapeutic Target for Alzheimer's Disease and Type 2 Diabetes Mellitus. - Kaminari, Archontia; Tsilibary, Effie C; Tzinia, Athina (J Alzheimers Dis, 2018)
Matrix metalloprotease 9 (MMP-9) is a 92 kDa type IV collagenase and a member of the family of endopeptidases. MMP-9 is involved in the degradation of extracellular matrix components, tissue remodeling, cellular receptor stripping, and processing of various signaling molecules. In the CNS, the effects of MMP-9 are quite complex, since it exerts beneficial effects including neurogenesis, angiogenesis, myelogenesis, axonal growth, and inhibition of apoptosis, or destructive effects including apoptosis, blood-brain barrier disorder, and demyelination. Likewise, in the periphery, physiological events, as the involvement of MMP-9 in angiogenesis, for instance in wound healing, can be turned into pathological, such as in tumor metastasis, depending on the state of the organism. Alzheimer's disease is a neurodegenerative disorder, characterized by amyloid accumulation and deposition in the brain. Amyloidogenesis, however, also occurs in diseases of the periphery, such as type II diabetes mellitus, where an analogous type of amyloid, is deposited in the pancreas. Interestingly, both diseases exhibit similar pathology and disease progression, with insulin resistance being a major common denominator. Hence, combinatorial strategies searching new or existing molecules to apply for therapeutic use for both diseases are gaining momentum. MMP-9 is extensively studied due to its association with a variety of physiological and pathological processes. Consequently, meticulous design could render MMP-9 into a potential therapeutic target for Alzheimer's disease and type 2 diabetes mellitus; two seemingly unrelated diseases.

NO-Dependent Akt Inactivation by S-Nitrosylation as a Possible Mechanism of STZ-Induced Neuronal Insulin Resistance. - Crunfli, Fernanda; Mazucanti, Caio Henrique; de Moraes, Ruan Carlos Macêdo; Costa, Andressa Pereira; Rodrigues, Alice Cristina; Scavone, Cristoforo; Torrão, Andréa da Silva (J Alzheimers Dis, 2018)
Sporadic Alzheimer's disease (sAD) is associated with energy metabolism deficiency and impairment of insulin receptor (IR) signaling in the brain. In this context, low doses of intracerebroventricular (icv) injection of streptozotocin (STZ) in rodents has been used as an experimental model of sAD which leads to an insulin-resistant brain state and neurodegeneration. However, the STZ effects on brain insulin signaling-related proteins it is not appropriately elucidated. The aim of this study was to evaluate the beginning and progression of alterations in the brain IR pathway of rats after 1, 3, 5, and 7 days of STZ injection and investigate intracellular signaling involved on STZ induced insulin resistance. We observed that STZ injection causes cognitive impairment in the animals, a temporal variation of the insulin signaling-related proteins and apoptosis cell death in the hippocampus. We also have shown that STZ causes insulin resistance and impairment on phosphoinositide 3-kinase (PI3K) activity in the Neuro-2a cells through protein kinase B (Akt) inactivation by S-nitrosylation, which could upregulate GSK3-β activity. STZ ability to cause an insulin-resistant neuron state involves NO production and ROS production which may play an important role in the mechanism linked to STZ-induced neurotoxicity. The icv injection of STZ model and STZ exposed Neuro-2a cells may be potential experimental models for assessing molecules related to the pathogenesis of sAD.

Non-Genetic Risk Factors for Degenerative and Vascular Young Onset Dementia: Results from the INSPIRED and KGOW Studies. - Cations, Monica; Draper, Brian; Low, Lee-Fay; Radford, Kylie; Trollor, Julian; Brodaty, Henry; Sachdev, Perminder; Gonski, Peter; Broe, Gerald Anthony; Withall, Adrienne (J Alzheimers Dis, 2018)
BACKGROUND: Several brain reserve, vascular risk, and other modifiable factors have been associated with late-onset dementia, but their association with young onset dementia (YOD) has not been adequately explored. OBJECTIVE: To examine the association of cognitive reserve enhancing factors, cardiovascular risk factors (including smoking), depression, alcohol use, and traumatic brain injury (TBI) with non-autosomal dominant degenerative and/or vascular YOD. METHODS: Data for this matched case-control study were taken from two larger studies conducted in NSW, Australia. One comprised all people with YOD within a geographical region, while the other exclusively included Aboriginal and Torres Strait Islander participants. Dementia diagnosis was confirmed by clinical consensus, and risk exposure was retrospectively self- and/or informant-reported. RESULTS: Participants were 96 people with YOD (58.4% with probable Alzheimer's disease) and 175 age-group, sex, and sample matched control participants. Poor educational attainment, low participation in cognitive leisure activity, stroke, transient ischemic attack, and self-reported very heavy alcohol use were related to the risk of primary degenerative and/or vascular YOD. The effect of hypertension and depression varied depending on when they occurred relative to dementia onset. Current smoking was significantly associated with risk in univariate analyses but did not retain significance in multivariate modelling. There was no association with hypercholesterolemia, diabetes, or TBI of any kind. Some compensation for low educational attainment was possible via a complex occupation later in life. CONCLUSION: Non-genetic factors have a role in YOD, though the relative importance of each factor may be different to late onset dementia. The timing and severity of exposure, as well as the potential for compensation with later protective exposures, are important considerations for potential prevention strategies.

Non-Phosphorylated Tau in Cerebrospinal Fluid is a Marker of Alzheimer's Disease Continuum in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Mukherjee, Partha S; Waniek, Katharina; Holzer, Max; Chao, Chih-Kai; Thompson, Charles; Ruiz-Ramos, Rubén; Calderón-Garcidueñas, Ana; Franco-Lira, Maricela; Reynoso-Robles, Rafael; González-Maciel, Angelica; Lachmann, Ingolf (J Alzheimers Dis, 2018)
Long-term exposure to fine particulate matter (PM2.5) and ozone (O3) above USEPA standards is associated with Alzheimer's disease (AD) risk. Metropolitan Mexico City (MMC) children exhibit subcortical pretangles in infancy and cortical tau pre-tangles, NFTs, and amyloid phases 1-2 by the 2nd decade. Given their AD continuum, we measured in 507 normal cerebrospinal fluid (CSF) samples (MMC 354, controls 153, 12.82±6.73 y), a high affinity monoclonal non-phosphorylated tau antibody (non-P-Tau), as a potential biomarker of AD and axonal damage. In 81 samples, we also measured total tau (T-Tau), tau phosphorylated at threonine 181 (P-Tau), amyloid-β1-42, BDNF, and vitamin D. We documented by electron microscopy myelinated axonal size and the pathology associated with combustion-derived nanoparticles (CDNPs) in anterior cingulate cortex white matter in 6 young residents (16.25±3.34 y). Non-P-Tau showed a strong increase with age significantly faster among MMC versus controls (p = 0.0055). Aβ1 - 42 and BDNF concentrations were lower in MMC children (p = 0.002 and 0.03, respectively). Anterior cingulate cortex showed a significant decrease (p = <0.0001) in the average axonal size and CDNPs were associated with organelle pathology. Significant age increases in non-P-Tau support tau changes early in a population with axonal pathology and evolving AD hallmarks in the first two decades of life. Non-P-Tau is an early biomarker of axonal damage and potentially valuable to monitor progressive longitudinal changes along with AD multianalyte classical CSF markers. Neuroprotection of young urbanites with PM2.5 and CDNPs exposures ought to be a public health priority to halt the development of AD in the first two decades of life.

Olfactory Function is Associated with Cognitive Performance: Results of the Heinz Nixdorf Recall Study. - Tebrügge, Sarah; Winkler, Angela; Gerards, Diana; Weimar, Christian; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Jokisch, Martha (J Alzheimers Dis, 2018)
BACKGROUND: There is strong evidence for an association of olfactory dysfunction and neurodegenerative diseases. Studies on the association of olfaction and cognition in the general population are rare. OBJECTIVE: To evaluate gender- and age-specific associations of olfactory function and cognitive performance in a well characterized population-based study sample. METHODS: At the third examination of the Heinz Nixdorf Recall study (n = 3,087), 2,640 participants (48% men; 68.2±7.2 years) underwent Sniffin' Sticks Screening Test measuring olfactory function on a scale of 0-12 points. Olfactory function was rated as anosmic, hyposmic, or normosmic (≤6, 7-10 or ≥11 points, respectively). All participants performed eight validated cognitive subtests. Age- (55-64 years, 65-74 years, 75-86 years) and gender-stratified multivariate analysis of covariance was used to evaluate group differences in cognitive performance. RESULTS: Women showed better olfactory function than men (p < 0.001). For middle-aged participants, olfactory groups differed in almost all cognitive subtests. The analyses revealed no gender effects, although associations were slightly greater for women than for men. Anosmics showed the worst cognitive performance and normosmics showed the best cognitive performance. In the young- and old-aged groups, a quantitative association was found for anosmics in all subtests and for normosmics and hyposmics in almost all subtests. CONCLUSION: This is the first study reporting on age-specific associations of olfactory function and cognitive performance in the general population. The association found in middle-aged participants (65-74 years) may serve as a marker to improve identification of persons at high risk for cognitive decline and dementia.

Palmitoylethanolamide Blunts Amyloid-β42-Induced Astrocyte Activation and Improves Neuronal Survival in Primary Mouse Cortical Astrocyte-Neuron Co-Cultures. - Beggiato, Sarah; Borelli, Andrea Celeste; Ferraro, Luca; Tanganelli, Sergio; Antonelli, Tiziana; Tomasini, Maria Cristina (J Alzheimers Dis, 2018)
BACKGROUND: Based on the pivotal role of astrocytes in brain homeostasis and the strong metabolic cooperation existing between neurons and astrocytes, it has been suggested that astrocytic dysfunctions might cause and/or contribute to neuroinflammation and neurodegenerative processes. Therapeutic approaches aimed at both neuroprotection and neuroinflammation reduction may prove particularly effective in slowing the progression of these diseases. The endogenous lipid mediator palmitoylethanolamide (PEA) displayed neuroprotective and anti(neuro)inflammatory properties, and demonstrated interesting potential as a novel treatment for Alzheimer's disease. OBJECTIVE AND METHODS: We firstly evaluated whether astrocytes could participate in regulating the Aβ42-induced neuronal damage, by using primary mouse astrocytes cell cultures and mixed astrocytes-neurons cultures. Furthermore, the possible protective effects of PEA against Aβ42-induced neuronal toxicity have also been investigated by evaluating neuronal viability, apoptosis, and morphometric parameters. RESULTS: The presence of astrocytes pre-exposed to Aβ42 (0.5μM; 24 h) induced a reduction of neuronal viability in primary mouse astrocytes-neurons co-cultures. Furthermore, under these experimental conditions, an increase in the number of neuronal apoptotic nuclei and a decrease in the number of MAP-2 positive neurons were observed. Finally, astrocytic Aβ42 pre-exposure induced an increase in the number of neurite aggregations/100μm as compared to control (i.e., untreated) astrocytes-neurons co-cultures. These effects were not observed in neurons cultured in the presence of astrocytes pre-exposed to PEA (0.1μM), applied 1 h before and maintained during Aβ42 treatment. CONCLUSION: Astrocytes contribute to Aβ42-induced neurotoxicity and PEA, by blunting Aβ42-induced astrocyte activation, improved neuronal survival in mouse astrocyte-neuron co-cultures.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Animals; Animals, Newborn; Anti-Inflammatory Agents, Non-Steroidal; Astrocytes; Cell Survival; Cells, Cultured; Cerebral Cortex; Coculture Techniques; Ethanolamines; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Neurons; Palmitic Acids; Peptide Fragments; Time Factors

Parietal Involvement in the Semantic Variant of Primary Progressive Aphasia with Alzheimer's Disease Cerebrospinal Fluid Profile. - Bera, Géraldine; Migliaccio, Raffaella; Michelin, Thibaut; Lamari, Foudil; Ferrieux, Sophie; Nogues, Marie; Bertin, Hugo; Habert, Marie Odile; Dubois, Bruno; Teichmann, Marc; Kas, Aurélie (J Alzheimers Dis, 2018)
Semantic variant of primary progressive aphasia (svPPA) is typically associated with non-Alzheimer's disease (AD) pathology. However, some anatomopathological studies have found AD lesions in those patients. We compared brain perfusion SPECT of 18 svPPA patients with cerebrospinal fluid (CSF) biomarkers indicative of non-AD pathology (svPPA-nonAD) and three svPPA patients with CSF biomarkers indicative of underlying AD (svPPA-AD). All svPPA patients had severe left temporopolar hypoperfusion. SvPPA-nonAD had additional anterior cingulate and mediofrontal hypoperfusion, whereas svPPA-AD had greater left parietal and posterior cingulate involvement. Parietal damage in svPPA constitutes a biomarker for underlying Alzheimer pathology thus refining the classification of this PPA variant.

Past to Future: What Animal Models Have Taught Us About Alzheimer's Disease. - Martini, Alessandra C; Forner, Stefania; Trujillo-Estrada, Laura; Baglietto-Vargas, David; LaFerla, Frank M (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) impairs memory and causes significant cognitive deficits. The disease course is prolonged, with a poor prognosis, and thus exacts an enormous economic and social burden. Over the past two decades, genetically engineered mouse models have proven indispensable for understanding AD pathogenesis, as well as for discovering new therapeutic targets. Here we highlight significant studies from our laboratory that have helped advance the AD field by elucidating key pathogenic processes operative in AD and exploring a variety of aspects of the disease which may yield novel therapeutic strategies for combatting this burdensome disease.

Patient Engagement: The Fundació ACE Framework for Improving Recruitment and Retention in Alzheimer's Disease Research. - Boada, Merce; Santos-Santos, Miguel A; Rodríguez-Gómez, Octavio; Alegret, Montserrat; Cañabate, Pilar; Lafuente, Asunción; Abdelnour, Carla; Buendia, Mar; de Dios, Maria José; Morera, Amèrica; Sanabria, Ángela; Campo, Laura; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) research is at a critical time. The global society is increasingly aware of the frightening rate of growth of the human and financial burden caused by this condition and of the urgent need to halt its progression. Consequently, the scientific community holds great responsibility to quickly put in place and optimize the machinery necessary for testing new treatments or interventions. In this context demand for participants for AD research is at an all-time high. In this review, we will focus on a methodological factor that is increasingly recognized as a key factor that shapes trial populations and affects validity of results in clinical trials: patient engagement, recruitment, and retention. We outline specific problems relevant to patient engagement in AD including recruiting enough participants, difficulties in participant retention, ensuring the recruited sample is representative of the general AD population, the burden of screening failures, and new challenges related to recruiting in preclinical disease. To address the urgent need for more research studying the applicability and cost-effectiveness of different recruitment strategies across different settings and nationalities, we describe the Models of Patient Engagement for Alzheimer's Disease (MOPEAD) project, a public-private partnership promoted by the Innovative Medicine Initiative (IMI), which will provide a large multinational quantitative analysis comparing different innovative recruitment models. We also discuss strategies that address each problem and draw on the experience of Fundació ACE to argue that focusing resources on comprehensive AD centers that offer coordinated clinical and social care and participate in basic and clinical research, is an effective and efficient way of implementing many of the discussed strategies.

Patients with Dementia in Primary Care: Who Is Referred to a Neurologist/Psychiatrist and What Patient-Oriented Factors Are Associated with the Visit? - Strohmaier, Urs; Keller, Felix; Kilimann, Ingo; Michalowsky, Bernhard; Wucherer, Diana; Zwingmann, Ina; Teipel, Stefan; Hoffmann, Wolfgang; Thyrian, Jochen René (J Alzheimers Dis, 2018)
BACKGROUND: The current guidelines imply that basic medical diagnostics for dementia should be provided by general practitioners in cooperation with other specialists such as neurologists and psychiatrists. OBJECTIVES: The aims of this paper were to 1) compare the dementia patients of general practice residents whose care is co-managed by neurology/psychiatry residents with those whose care is not; 2) identify the patient variables associated with the utilization of neurological and psychiatric specialists; and 3) describe the frequency of imaging used for dementia patients in primary care. METHODS: The analyses utilized data from 485 individuals who screened positive for dementia in primary care (PWD). Clinical variables and the utilization of specialists were assessed via medical records and face-to-face interviews. The factors associated with the utilization of specialists were assessed using multivariate linear regression and included age, sex, relationship status, cognitive impairment, depression, activities of daily living, and formal diagnosis of dementia. RESULTS: Our results show that 89 out of 485 study participants (18.4%) were referred to specialists 12 months prior to assessment. Of these 89 individuals, 14.6% (n = 13) did not receive imaging diagnostics, while 39.3% (n = 35) received brain imaging by CT scan and 46.1% (n = 41) by MRI. PWD referred to specialists differed from those not referred, in age, relationship status, and the presence of a formal diagnosis. Our multivariate analysis revealed that younger age (OR = 0.95; 95% -confidence interval 0.90-0.99; p = 0.04) and higher functional impairment (OR = 1.15; 95% -confidence interval 1.02-1.30; p = 0.02) were associated with a visit to a specialist. DISCUSSION: Only 1 out of every 4 to 5 individuals who have screened positive for dementia have visited a specialist in psychiatry or neurology. While in general, women utilized specialists less often than men, younger and more functionally impaired patients were more likely to be sent to a specialist by their treating general practitioner. Almost 90% of the patients sent to a specialist received cranial neuroimaging, suggesting high adherence to diagnostic guidelines in specialized care.

Personality Modulates the Efficacy of Art Intervention on Chronic Pain in a Population of Patients with Alzheimer's Disease. - Rouch, Isabelle; Pongan, Elodie; Leveque, Yohana; Tillmann, Barbara; Trombert, Béatrice; Getenet, Jean Claude; Auguste, Nicolas; Krolak-Salmon, Pierre; Laurent, Bernard; Dorey, Jean-Michel (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) mainly occurs in elderly individuals. Comorbidities and chronic pain are frequent in this population. Previous studies revealed that personality modulates both chronic pain (CP) andADoccurrence and evolution. Moreover, as pain treatments can induce side-effects, non-drugs treatments, such as art interventions, are interesting alternative therapies for decreasing CP in these patients. OBJECTIVE: Our aim was to assess the potential role of personality traits on art intervention efficacy for reducing CP in a population of patients with mild AD. METHODS: Design: multicenter randomized controlled trial. Fifty mild AD patients underwent a 12-week art intervention including singing and painting groups. Personality was assessed with the Big Five Inventory before the sessions. CP was measured with Numeric Rating Scale (NRS) [Usual pain (NRS-U) and most Intense pain (NRS-I)], Simple Visual Scale [Usual pain (SVS-U) and most Intense pain (SVS-I)] and Brief Pain Inventory (BPI) before and after the sessions. The influence of personality traits on CP evolution before and after art intervention was assessed with multiple linear regression models. RESULTS: A positive association was observed between neuroticism and the evolution of three CP measures including NRS-U (B = 0.34, p = 0.01), SVS-U (B = 0.20, p = 0.04), and BPI-U (B = 0.46, p = 0.02) evolution. No significant relationship was observed between neuroticism and NRS-I, SVS-I and BPI-R evolution. CONCLUSIONS: Our findings suggest that neuroticism can decrease the efficacy of group art intervention on pain in patients with mild AD. Individual therapies could be more appropriate for these patients. These results emphasize the interest of taking into account patients' personality before proposing them to participate to a group therapy.

Plasma Amyloid-β (Aβ42) Correlates with Cerebrospinal Fluid Aβ42 in Alzheimer's Disease. - Teunissen, Charlotte E; Chiu, Ming-Jang; Yang, Che-Chuan; Yang, Shieh-Yueh; Scheltens, Philip; Zetterberg, Henrik; Blennow, Kaj (J Alzheimers Dis, 2018)
The 42 amino acid form of amyloid-β (Aβ42) plays a key role in the pathogenesis of Alzheimer's disease (AD) and is a core biomarker for the diagnosis of AD. Numerous studies have shown that cerebrospinal fluid (CSF) Aβ42 concentrations are decreased in AD, when measured by enzyme-linked immunosorbent assay (ELISA) and other conventional immunoassays. While most studies report no change in plasma Aβ42, independent studies using the immunomagnetic reduction (IMR) technique report an increase in plasma Aβ42 levels in AD. To confirm the opposite changes of Aβ42 levels in CSF and plasma for AD, we assayed the levels of Aβ42 in plasma of subjects with known CSF Aβ42 levels. In total 43 controls and 63 AD patients were selected at two sites: the VU University Medical Center (n = 55) and Sahlgrenska University Hospital (n = 51). IMR and ELISA were applied to assay Aβ42 in plasma and CSF, respectively. We found a moderately negative correlation between plasma and CSF Aβ42 levels in AD patients (r = -0.352), and a weakly positive correlation in controls (r = 0.186). These findings further corroborate that there are opposite changes of Aβ42 levels in CSF and plasma in AD. The possible causes for the negative correlation are discussed by taken assay technologies, Aβ42 transport from brain to peripheral blood, and sample matrix into account.

Post Traumatic Stress Disorder Heralding the Onset of Semantic Frontotemporal Dementia. - Bonanni, Laura; Franciotti, Raffaella; Martinotti, Giovanni; Vellante, Federica; Flacco, Maria Elena; Di Giannantonio, Massimo; Thomas, Astrid; Onofrj, Marco (J Alzheimers Dis, 2018)
BACKGROUND: Post traumatic stress disorder (PTSD) is associated with cognitive decline. The dementia type following PTSD is unclear. OBJECTIVE: To assess whether PTSD is associated with a specific dementia. METHODS: Prospective study: 46 PTSD patients (DSM-IV-TR) were followed for 6-10 years with clinical, neuropsychological, imaging evaluations for possible development of dementia.Retrospective study:849 dementia patients followed during 1999-2014 (509 Alzheimer's disease, AD; 207 dementia with Lewy bodies, DLB; 90 vascular dementia, VaD; 43 frontotemporal dementia, FTD) and 287 patients with any neurological condition (including patients with/without dementia) were evaluated for the presence of PTSD in their history. RESULTS: Prospective study: 8 patients developed dementia; 1 AD, 1 DLB, 6 semantic FTD (13.0% of the PTSD population). Retrospective study: 38 patients (4.5%) had a history of PTSD; 3.5% of AD, 4.3% of DLB, 14.0% of FTD, 5.6% of VaD. The percentage was higher in FTD than in AD or DLB (χ2 = 10, p = 0.001, and χ2 = 6, p = 0.02). At difference with AD, DLB, or VaD, FTD incidence among dementia patients with PTSD history (38 patients) was higher than in the dementia population overall (16% versus 5%, χ2 = 8, p = 0.005). The impact of possible demographical/clinical confounders (age, gender, MMSE) was excluded by Poisson regression. PTSD prevalence in the comparative group without dementia matched the prevalence in the Italian general population (1.1%). PTSD prevalence in the demented comparative group matched the prevalence in our dementia retrospective cohort, 3.7%). DISCUSSION: PTSD was associated with the development of semantic FTD.

Postsynaptic Proteome of Non-Demented Individuals with Alzheimer's Disease Neuropathology. - Zolochevska, Olga; Bjorklund, Nicole; Woltjer, Randall; Wiktorowicz, John E; Taglialatela, Giulio (J Alzheimers Dis, 2018)
Some individuals, here referred to as Non-Demented with Alzheimer's Neuropathology (NDAN), retain their cognitive function despite the presence of amyloid plaques and tau tangles typical of symptomatic Alzheimer's disease (AD). In NDAN, unlike AD, toxic amyloid-β oligomers do not localize to the postsynaptic densities (PSDs). Synaptic resistance to amyloid-β in NDAN may thus enable these individuals to remain cognitively intact despite the AD-like pathology. The mechanism(s) responsible for this resistance remains unresolved and understanding such protective biological processes could reveal novel targets for the development of effective treatments for AD. The present study uses a proteomic approach to compare the hippocampal postsynaptic densities of NDAN, AD, and healthy age-matched persons to identify protein signatures characteristic for these groups. Subcellular fractionation followed by 2D gel electrophoresis and mass spectrometry were used to analyze the PSDs. We describe fifteen proteins which comprise the unique proteomic signature of NDAN PSDs, thus setting them apart from control subjects and AD patients.

Pramlintide: The Effects of a Single Drug Injection on Blood Phosphatidylcholine Profile for Alzheimer's Disease. - Tao, Qiushan; Zhu, Haihao; Chen, Xi; Stern, Robert A; Kowall, Neil; Au, Rhoda; Blusztajn, Jan Krzysztof; Qiu, Wei Qiao (J Alzheimers Dis, 2018)
Studies suggest that a single injection of pramlintide, an amylin analog, induces changes in Alzheimer's disease (AD) biomarkers in the blood of AD mouse models and AD patients. The aim of this study was to examine whether a pramlintide challenge combined with a phosphatidylcholine (PC) profile diagnoses of AD and mild cognitive impairment (MCI) better than PC alone. Non-diabetic subjects with cognitive status were administered a single subcutaneous injection of 60 mcg of pramlintide under fasting condition. A total of 71 PCs, amyloid-β peptide (Aβ), and total tau (t-tau) in plasma at different time points were measured and treated as individual variables. A single injection of pramlintide altered the levels of 7 PCs in the blood, while a pramlintide injection plus food modulated the levels of 10 PCs in the blood (p < 0.05). The levels of 2 PCs in MCI and 12 PCs in AD in the pramlintide challenge were significantly lower than the ones in controls. We found that while some PCs were associated with only Aβ levels, other PCs were associated with both Aβ and t-tau levels. A receiver operating characteristic analysis of the PCs was combined with the Aβ and t-tau data to produce an area under the curve predictive value of 0.9799 between MCI subjects and controls, 0.9794 between AD subjects and controls, and 0.9490 between AD and MCI subjects. A combination of AD biomarkers and a group of PCs post a pramlintide challenge may provide a valuable diagnostic and prognostic test for AD and MCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Female; Humans; Islet Amyloid Polypeptide; Logistic Models; Male; Middle Aged; Phosphatidylcholines; ROC Curve; tau Proteins

Predicting and Tracking Short Term Disease Progression in Amnestic Mild Cognitive Impairment Patients with Prodromal Alzheimer's Disease: Structural Brain Biomarkers. - Marizzoni, Moira; Ferrari, Clarissa; Jovicich, Jorge; Albani, Diego; Babiloni, Claudio; Cavaliere, Libera; Didic, Mira; Forloni, Gianluigi; Galluzzi, Samantha; Hoffmann, Karl-Titus; Molinuevo, José Luis; Nobili, Flavio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Early Alzheimer's disease (AD) detection using cerebrospinal fluid (CSF) biomarkers has been recommended as enrichment strategy for trials involving mild cognitive impairment (MCI) patients. OBJECTIVE: To model a prodromal AD trial for identifying MRI structural biomarkers to improve subject selection and to be used as surrogate outcomes of disease progression. METHODS: APOE ɛ4 specific CSF Aβ42/P-tau cut-offs were used to identify MCI with prodromal AD (Aβ42/P-tau positive) in the WP5-PharmaCog (E-ADNI) cohort. Linear mixed models were performed 1) with baseline structural biomarker, time, and biomarker×time interaction as factors to predict longitudinal changes in ADAS-cog13, 2) with Aβ42/P-tau status, time, and Aβ42/P-tau status×time interaction as factors to explain the longitudinal changes in MRI measures, and 3) to compute sample size estimation for a trial implemented with the selected biomarkers. RESULTS: Only baseline lateral ventricle volume was able to identify a subgroup of prodromal AD patients who declined faster (interaction, p = 0.003). Lateral ventricle volume and medial temporal lobe measures were the biomarkers most sensitive to disease progression (interaction, p≤0.042). Enrichment through ventricular volume reduced the sample size that a clinical trial would require from 13 to 76%, depending on structural outcome variable. The biomarker needing the lowest sample size was the hippocampal subfield GC-ML-DG (granule cells of molecular layer of the dentate gyrus) (n = 82 per arm to demonstrate a 20% atrophy reduction). CONCLUSION: MRI structural biomarkers can enrich prodromal AD with fast progressors and significantly decrease group size in clinical trials of disease modifying drugs.

Predicting Imminent Progression to Clinically Significant Memory Decline Using Volumetric MRI and FDG PET. - Stonnington, Cynthia M; Chen, Yinghua; Savage, Cary R; Lee, Wendy; Bauer Iii, Robert J; Sharieff, Sameen; Thiyyagura, Pradeep; Alexander, Gene E; Caselli, Richard J; Locke, Dona E C; Reiman, Eric M; Chen, Kewei (J Alzheimers Dis, 2018)
BACKGROUND: Brain imaging measurements can provide evidence of possible preclinical Alzheimer's disease (AD). Their ability to predict individual imminent clinical conversion remains unclear. OBJECTIVE: To investigate the ability of pre-specified volumetric magnetic resonance imaging (MRI) and fluorodeoxyglucose positron emission tomography (FDG-PET) measurements to predict which cognitively unimpaired older participants would subsequently progress to amnestic mild cognitive impairment (aMCI) within 2 years. METHODS: From an apolipoprotein E4 (APOE4) enriched prospective cohort study, 18 participants subsequently progressed to the clinical diagnosis of aMCI or probable AD dementia within 1.8±0.8 years (progressors); 20 participants matched for sex, age, education, and APOE allele dose remained cognitively unimpaired for at least 4 years (nonprogressors). A complementary control group not matched for APOE allele dose included 35 nonprogressors. Groups were compared on baseline FDG-PET and MRI measures known to be preferentially affected in the preclinical and clinical stages of AD and by voxel-wise differences in regional gray matter volume and glucose metabolism. Receiver Operating Characteristic, binary logistic regression, and leave-one-out procedures were used to predict clinical outcome for the a priori measures. RESULTS: Compared to non-progressors and regardless of APOE-matching, progressors had significantly reduced baseline MRI and PET measurements in brain regions preferentially affected by AD and reduced hippocampal volume was the strongest predictor of an individual's imminent progression to clinically significant memory decline (79% sensitivity/78% specificity among APOE-matched cohorts). CONCLUSION: Regional MRI and FDG-PET measurements may be useful in predicting imminent progression to clinically significant memory decline.

Predictors of Age of Diagnosis and Survival of Alzheimer's Disease in Down Syndrome. - Sinai, Amanda; Mokrysz, Claire; Bernal, Jane; Bohnen, Ingrid; Bonell, Simon; Courtenay, Ken; Dodd, Karen; Gazizova, Dina; Hassiotis, Angela; Hillier, Richard; McBrien, Judith; McCarthy, Jane; et al. (J Alzheimers Dis, 2018)
BACKGROUND: People with Down syndrome (DS) are an ultra-high risk population for Alzheimer's disease (AD). Understanding the factors associated with age of onset and survival in this population could highlight factors associated with modulation of the amyloid cascade. OBJECTIVE: This study aimed to establish the typical age at diagnosis and survival associated with AD in DS and the risk factors associated with these. METHODS: Data was obtained from the Aging with Down Syndrome and Intellectual Disabilities (ADSID) research database, consisting of data extracted from clinical records of patients seen by Community Intellectual Disability Services (CIDS) in England. Survival times when considering different risk factors were calculated. RESULTS: The mean age of diagnosis was 55.80 years, SD 6.29. Median survival time after diagnosis was 3.78 years, and median age at death was approximately 60 years. Survival time was associated with age of diagnosis, severity of intellectual disability, living status, anti-dementia medication status, and history of epilepsy. Age at diagnosis and treatment status remained predictive of survival time following adjustment. CONCLUSION: This study provides the best estimate of survival in dementia within the DS population to date, and is in keeping with previous estimates from smaller studies in the DS population. This study provides important estimates and insights into possible predictors of survival and age of diagnosis of AD in adults with DS, which will inform selection of participants for treatment trials in the future.
Keywords: Age of Onset; Alzheimer Disease; Down Syndrome; England; Female; Humans; Male; Middle Aged; Risk Factors; Survival Analysis

Predictors of Delirium Development in Older Medical Inpatients: Readily Identifiable Factors at Admission. - O'Regan, Niamh A; Fitzgerald, James; Adamis, Dimitrios; Molloy, David William; Meagher, David; Timmons, Suzanne (J Alzheimers Dis, 2018)
BACKGROUND: Identifying patients at high risk of delirium is crucial to facilitate prevention. Although dementia is the most consistent risk factor across populations, it remains under-diagnosed. Hence understanding other markers of delirium vulnerability on admission is important. OBJECTIVE: We aimed to identify predictors of incident delirium development in older medical inpatients that were readily identifiable at presentation to the emergency department. METHODS: Medical inpatients of ≥70 years were assessed on admission for delirium using the Revised Delirium Rating Scale (DRS-R98) and those with prevalent delirium were excluded. Consenting non-delirious patients were then assessed daily using the DRS-R98. Data pertaining to multiple baseline delirium risk factors were collected, including pre-morbid dementia. Multivariable logistic regression was used to examine which factors predicted the development of incident delirium. RESULTS: Of 555 patients approached, 184 (33.1%) had prevalent delirium. Following other exclusions, 191 were included in the study and 61 developed incident delirium. Predictors of incident delirium on multivariable analysis, controlling for confounders, were dementia (OR 2.54, 95% CI 1.01-6.43, p = 0.048); Barthel Index score (OR 1.15 for each unit decrease in score, 95% CI 1.06-1.25, p = 0.001), and Modified Cumulative Illness Rating Scale score (OR 1.13 for each unit increase in score, 95% CI 1.05-1.22, p = 0.001). CONCLUSION: Dementia is a well-known risk factor for delirium; however, it too is under-recognized and on admission can be missed. Conversely, the Barthel Index is a simple and widely used measure of functional ability that may prove useful in stratifying those at risk of in-hospital delirium on admission.

Preoperative Phosphorylated Tau Concentration in the Cerebrospinal Fluid Can Predict Cognitive Function Three Years after Shunt Surgery in Patients with Idiopathic Normal Pressure Hydrocephalus. - Nakajima, Madoka; Miyajima, Masakazu; Ogino, Ikuko; Akiba, Chihiro; Kawamura, Kaito; Kamohara, Chihiro; Fusegi, Keiko; Harada, Yoshinao; Hara, Takeshi; Sugano, Hidenori; Tange, Yuichi; Karagiozov, Kostadin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is commonly treated by cerebrospinal fluid (CSF) shunting. However, the long-term efficacy of shunt intervention in the presence of comorbid Alzheimer's disease (AD) pathology is debated. OBJECTIVE: To identify AD-associated CSF biomarkers predictive of shunting surgery outcomes in patients with iNPH. METHODS: Preoperative levels of total and phosphorylated Tau (p-Tau) were measured in 40 patients with iNPH divided into low (<30 pg/mL) and high (≥30 pg/mL) p-Tau groups and followed up for three years after lumboperitoneal shunting. The modified Rankin Scale (mRS), Mini-Mental State Examination (MMSE), Frontal Assessment Battery, and iNPH Grading Scale scores were compared between the age-adjusted low (n = 24; mean age 75.7 years [SD 5.3]) and high (n = 11; mean age 76.0 years [SD 5.6]) p-Tau groups. RESULTS: Cognitive function improved early in the low p-Tau group and was maintained thereafter (p = 0.005). In contrast, the high p-Tau group showed a gradual decline to baseline levels by the third postoperative year (p = 0.040). Although the p-Tau concentration did not correlate with the preoperative MMSE score, a negative correlation appeared and strengthened during follow-up (R2 = 0.352, p < 0.001). Furthermore, the low p-Tau group showed rapid and sustained mRS grade improvement, whereas mRS performance gradually declined in the high p-Tau group. CONCLUSIONS: Preoperative CSF p-Tau concentration predicted some aspects of cognitive function after shunt intervention in patients with iNPH. The therapeutic effects of shunt treatment were shorter-lasting in patients with coexisting AD pathology.

Preserved Structural Network Organization Mediates Pathology Spread in Alzheimer's Disease Spectrum Despite Loss of White Matter Tract Integrity. - Powell, Fon; Tosun, Duygu; Sadeghi, Roksana; Weiner, Michael; Raj, Ashish (J Alzheimers Dis, 2018)
Models of Alzheimer's disease (AD) hypothesize stereotyped progression via white matter (WM) fiber connections, most likely via trans-synaptic transmission of toxic proteins along neuronal pathways. An important question in the field is whether and how organization of fiber pathways is affected by disease. It remains unknown whether fibers act as conduits of degenerative pathologies, or if they also degenerate with the gray matter network. This work uses graph theoretic modeling in a longitudinal design to investigate the impact of WM network organization on AD pathology spread. We hypothesize if altered WM network organization mediates disease progression, then a previously published network diffusion model will yield higher prediction accuracy using subject-specific connectomes in place of a healthy template connectome. Neuroimaging data in 124 subjects from ADNI were assessed. Graph topology metrics show preserved network organization in patients compared to controls. Using a published diffusion model, we further probe the effect of network alterations on degeneration spread in AD. We show that choice of connectome does not significantly impact the model's predictive ability. These results suggest that, despite measurable changes in integrity of specific fiber tracts, WM network organization in AD is preserved. Further, there is no difference in the mediation of putative pathology spread between healthy and AD-impaired networks. This conclusion is somewhat at variance with previous results, which report global topological disturbances in AD. Our data indicates the combined effect of edge thresholding, binarization, and inclusion of subcortical regions to network graphs may be responsible for previously reported effects.

Prevalence and Determinants of Agonistic Autoantibodies Against α1-Adrenergic Receptors in Patients Screened Positive for Dementia: Results from the Population-Based DelpHi-Study. - Thyrian, Jochen René; Hertel, Johannes; Schulze, Lara N; Dörr, Marcus; Prüss, Harald; Hempel, Petra; Bimmler, Marion; Kunze, Rudolf; Grabe, Hans Jörgen; Teipel, Stefan; Hoffmann, Wolfgang (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to assess promising biomarkers for diagnosis and treatment response in real-life settings. Despite the important role of vascular risk factors, cardiovascular biomarkers have played a minor role in dementia research. Agonistic autoantibodies (agAAB) directed against G-protein-coupled receptors (GPCR) are discussed as modulators of pathology and clinical manifestation. OBJECTIVE: 1) Describe prevalence of agAAB directed against GPCR, especially agABB against α1-adrenergic receptors (α1-AR-agAAB) and agABB directed against β2-adrenergic receptors (β2-AR-agAAB) and 2) identify factors associated with agAAB in people with dementia during routine care. METHODS: Blood samples and data from 95 subjects who screened positive for dementia from a primary care cohort, analyzed using an enzyme-linked immunosorbent assay (ELISA) for detecting agAAB. Sociodemographic and clinical data were assessed, and medical records checked. RESULTS: In 40 (42%) samples, agAAB was detected, with n = 29 (31%) representing α1-AR-agAAB and n = 21 (22%) β2-AR-agAAB. There was no association between the presence of any antibody and a formal diagnosis of dementia. However, patients with coronary heart disease were more likely (OR = 4.23) to have α1-AR-agAAB than those without coronary heart disease. There were no associations between agAAB and age, sex, education, or cognitive impairment. DISCUSSION: For the first time, we show that autoantibodies have a significant prevalence in people with dementia in a routine care setting. Previous findings were restricted to highly selective samples. We replicated the association between α1-AR-agAAB in patients with coronary heart diseases but were not able to find other factors associated with the presence of agAAB.

The Price of Stress: High Bedtime Salivary Cortisol Levels Are Associated with Brain Atrophy and Cognitive Decline in Stroke Survivors. Results from the TABASCO Prospective Cohort Study. - Tene, Oren; Hallevi, Hen; Korczyn, Amos D; Shopin, Ludmila; Molad, Jeremy; Kirschbaum, Clemens; Bornstein, Natan M; Shenhar-Tsarfaty, Shani; Kliper, Efrat; Auriel, Eitan; Usher, Sali; Stalder, Tobias; et al. (J Alzheimers Dis, 2018)
BACKGROUND AND OBJECTIVE: Previous studies suggest that excessive cortisol levels after stroke are associated with cognitive dysfunction. However, limited data exist regarding associations between post-stroke cortisol levels, brain abnormalities, genetic factors, and cognitive outcome. We sought to study these issues in a longitudinal stroke survivors cohort. METHODS: Data from 182 cognitively intact ischemic stroke patients from the TABASCO study were available. Saliva cortisol levels (bedtime and post-awakening) and cognitive assessments were obtained on admission, and 6, 12, and 24 months thereafter. During hospitalization, patients underwent 3T MRI scans and APOE genotyping. RESULTS: Higher bedtime cortisol levels immediately post-stroke were associated with larger neurological deficits (p < 0.001), brain atrophy (p = 0.025), worse white matter integrity (p = 0.003), and worse cognitive results up to 24 months post-stroke. These findings remained significant when adjusted for age, gender, education, smoking, stroke severity, apolipoprotein E4 (ApoE4) status, and body mass index. ApoE4 negatively modified the relation between cortisol and memory. As a group, participants who presented with high admission bedtime cortisol levels continued to present relatively elevated bedtime levels across all examined time-points, and this group had inferior memory and executive functioning scores compared to the lower cortisol group 24 months post-stroke (p = 0.05, p = 0.035, respectively). Post-awakening cortisol levels were not associated with neuroimaging findings or cognitive scores. CONCLUSIONS: High bedtime salivary cortisol levels post-stroke may provide information about dysregulation of diurnal HPA-axis activity under acute challenge conditions, and predict worse cognitive outcome. ApoE4 genotype might modify this association. These findings call for specific stress management interventions in stroke survivors.

Prodromal Alzheimer's Disease Demonstrates Increased Errors at a Simple and Automated Anti-Saccade Task. - Holden, John G; Cosnard, Alexandre; Laurens, Brice; Asselineau, Julien; Biotti, Damien; Cubizolle, Stéphanie; Dupouy, Sandrine; Formaglio, Maıté; Koric, Lejla; Seassau, Magali; Tilikete, Caroline; Vighetto, Alain; et al. (J Alzheimers Dis, 2018)
Saccade alterations are potential early signs of Alzheimer's disease. However, uncertainty persists in how early and reliably automated saccade recording systems detect impairments. This multicenter pathophysiological case-control transversal study explored saccade execution in carefully diagnosed amnestic mild cognitive impairment patients fulfilling research criteria for prodromal Alzheimer's disease (n = 29), as compared to both aged-matched mild Alzheimer's disease patients (n = 23) and controls (n = 27). Auto-coded saccades from horizontal (gap) vertical (step) stimulus elicited pro-saccades, and anti-saccade (gap) tasks were compared across the 3 groups. Mild cognitive impairment patients committed significantly more anti-saccade errors compared to controls (46.9 versus 24.3%, p < 0.001). Conventional analyses of the auto-coded stimulus elicited saccades parameters did not distinguish the amnestic mild cognitive impairment from controls or the mild Alzheimer's disease group. However, an offline analysis of manually coded saccade latencies, using resampling statistics did reveal subtle differences among the groups. Analysis of the manually coded data revealed that the mild Alzheimer's disease group had a reliably larger self-corrected error-rate than in amnestic mild cognitive impairment and controls (p = 0.003). Analysis of the manually coded saccade latencies, using more sensitive lognormal bootstrap analysis revealed a continuum, from amnestic mild cognitive impairment to mild Alzheimer's disease, of an increased severity of impaired inhibition of stimulus elicited saccades and correct voluntary saccade initiation. Anti-saccade error rates and psychometric measures of executive and several other cognitive functions were moderately and negatively correlated. Overall, inhibitory impairments in stimulus elicited saccades, characteristic of Alzheimer's disease, may be detected early in presumed prodromal patients using a simple, automated anti-saccade task.

The Progressive Acalculia Presentation of Parietal Variant Alzheimer's Disease. - Mendez, Mario F; Moheb, Negar; Desarzant, Randy E; Teng, Edmond H (J Alzheimers Dis, 2018)
BACKGROUND: Many patients with early-onset Alzheimer's disease (EOAD; age of onset <65 years) have non-amnestic presentations involving language (logopenic primary progressive aphasia, lvPPA), visuospatial abilities (posterior cortical atrophy, PCA), and even asymmetric symptoms consistent with corticobasal syndrome (CBS). An inferior parietal lobule variant of EOAD commonly presents with progressive difficulty with calculations. METHODS: We reviewed 276 EOAD patients for presentations with predominant acalculia. These patients were diagnosed with clinically probable Alzheimer's disease (AD) verified by positron emission tomography (PET) or cerebrospinal fluid amyloid-β or tau biomarkers. RESULTS: We identified 18 (9M/9F) (6.5%) EOAD patients with progressive acalculia that did not meet most criteria for lvPPA, visual PCA, or CBS. Their ages of onset and presentation were 56.6 (5.0) and 59.4 (6.5), respectively. Their acalculia was consistent with a primary acalculia ("anarithmetia") not explained by language or visuospatial impairments. Many also had anomia (14/18), ideomotor apraxia (13/18), and the complete Gerstmann's syndrome (7/18). Visual analysis of their diverse magnetic resonance imaging disclosed biparietal atrophy, disproportionately worse on the left. CONCLUSIONS: Primary acalculia may be the most common manifestation of an inferior parietal presentation of EOAD affecting the left intraparietal sulcus. This parietal variant also commonly involves progressive anomia, ideomotor apraxia, and other elements of Gerstmann's syndrome. The early recognition of patients with this variant, which is distinguishable from lvPPA, visual PCA, or CBS, would be facilitated by its recognition as a unique subtype of EOAD.

Prominent Non-Memory Deficits in Alzheimer's Disease Are Associated with Faster Disease Progression. - Scheltens, Nienke M E; Tijms, Betty M; Heymans, Martijn W; Rabinovici, Gil D; Cohn-Sheehy, Brendan I; Miller, Bruce L; Kramer, Joel H; Wolfsgruber, Steffen; Wagner, Michael; Kornhuber, Johannes; Peters, Oliver; Scheltens, Philip; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is a heterogeneous disorder. OBJECTIVE: To investigate whether cognitive AD subtypes are associated with different rates of disease progression. METHODS: We included 1,066 probable AD patients from the Amsterdam Dementia Cohort (n = 290), Alzheimer's Disease Neuroimaging Initiative (n = 268), Dementia Competence Network (n = 226), and University of California, San Francisco (n = 282) with available follow-up data. Patients were previously clustered into two subtypes based on their neuropsychological test results: one with most prominent memory impairment (n = 663) and one with most prominent non-memory impairment (n = 403). We examined associations between cognitive subtype and disease progression, as measured with repeated Mini-Mental State Examination (MMSE) and Clinical Dementia Rating scale sum of boxes (CDR sob), using linear mixed models. Furthermore, we investigated mortality risk associated with subtypes using Cox proportional hazard analyses. RESULTS: Patients were 71±9 years old; 541 (51%) were female. At baseline, pooled non-memory patients had worse MMSE scores (23.1±0.1) and slightly worse CDR sob (4.4±0.1) than memory patients (MMSE 24.0±0.1; p < 0.001; CDR sob 4.1±0.1; p < 0.001). During follow-up, pooled non-memory patients showed steeper annual decline in MMSE (-2.8±0.1) and steeper annual increase in CDR sob (1.8±0.1) than memory patients (MMSE - 1.9±0.1; pinteraction<0.001; CDR sob 1.3±0.1; pinteraction<0.001). Furthermore, the non-memory subtype was associated with an increased risk of mortality compared with the memory subtype at trend level (HR = 1.36, CI = 1.00-1.85, p = 0.05). CONCLUSIONS: AD patients with most prominently non-memory impairment show faster disease progression and higher risk of mortality than patients with most prominently memory impairment.

Protective Effects of Indian Spice Curcumin Against Amyloid-β in Alzheimer's Disease. - Reddy, P Hemachandra; Manczak, Maria; Yin, XiangLing; Grady, Mary Catherine; Mitchell, Andrew; Tonk, Sahil; Kuruva, Chandra Sekhar; Bhatti, Jasvinder Singh; Kandimalla, Ramesh; Vijayan, Murali; Kumar, Subodh; Wang, Rui; et al. (J Alzheimers Dis, 2018)
The purpose of our article is to assess the current understanding of Indian spice, curcumin, against amyloid-β (Aβ)-induced toxicity in Alzheimer's disease (AD) pathogenesis. Natural products, such as ginger, curcumin, and gingko biloba have been used as diets and dietary supplements to treat human diseases, including cancer, cardiovascular, respiratory, infectious, diabetes, obesity, metabolic syndromes, and neurological disorders. Products derived from plants are known to have protective effects, including anti-inflammatory, antioxidant, anti-arthritis, pro-healing, and boosting memory cognitive functions. In the last decade, several groups have designed and synthesized curcumin and its derivatives and extensively tested using cell and mouse models of AD. Recent research on Aβ and curcumin has revealed that curcumin prevents Aβ aggregation and crosses the blood-brain barrier, reach brain cells, and protect neurons from various toxic insults of aging and Aβ in humans. Recent research has also reported that curcumin ameliorates cognitive decline and improves synaptic functions in mouse models of AD. Further, recent groups have initiated studies on elderly individuals and patients with AD and the outcome of these studies is currently being assessed. This article highlights the beneficial effects of curcumin on AD. This article also critically assesses the current limitations of curcumin's bioavailability and urgent need for new formulations to increase its brain levels to treat patients with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blood-Brain Barrier; Curcumin; Disease Models, Animal; Humans; Mice; Neuroprotective Agents; Randomized Controlled Trials as Topic; Spices

Psychological and Mnemonic Benefits of Nostalgia for People with Dementia. - Ismail, Sanda; Christopher, Gary; Dodd, Emily; Wildschut, Tim; Sedikides, Constantine; Ingram, Tom A; Jones, Roy W; Noonan, Krist A; Tingley, Danielle; Cheston, Richard (J Alzheimers Dis, 2018)
BACKGROUND: Studies with non-clinical populations show that nostalgia increases psychological resources, such as self-esteem and social connectedness. OBJECTIVES: Our objectives were to find out if the benefits of nostalgia in non-clinical populations generalize to people with dementia and if nostalgia facilitates recall of dementia-related information. METHODS: All three experiments recruited participants with mild or moderate levels of dementia. Experiment 1 tested whether nostalgia (compared to control) enhances psychological resources among 27 participants. Experiment 2 used music to induce nostalgia (compared to control) in 29 participants. Experiment 3 compared recall for self-referent dementia statements among 50 participants randomized to either a nostalgia or control condition. Findings across experiments were synthesized with integrative data analysis. RESULTS: Nostalgia (compared to control) significantly increased self-reported social connectedness, meaning in life, self-continuity, optimism, self-esteem, and positive (but not negative) affect (Experiments 1-3). Compared to controls, nostalgic participants also recalled significantly more self-referent dementia-related information (Experiment 3). CONCLUSION: This series of experiments extends social psychological research with non-clinical populations into dementia care, providing evidence that nostalgia significantly enhances psychological resources. The finding that nostalgia increased recall of self-referent statements about dementia suggests that this emotion lends participants the fortitude to face the threat posed by their illness. The finding has potentially important clinical implications both for the development of reminiscence therapy and for facilitating adjustment to a diagnosis of dementia.

Psychological Distress, Self-Beliefs, and Risk of Cognitive Impairment and Dementia. - Sutin, Angelina R; Stephan, Yannick; Terracciano, Antonio (J Alzheimers Dis, 2018)
Depressive symptoms and a history of mental disorders are associated with increased risk for dementia. Less is known about whether other aspects of psychological distress and negative self-beliefs also increase risk. The purpose of this research is to examine 1) whether eight aspects of psychological distress and self-beliefs (anxiety, negative affect, hostility, anger-in, anger-out, hopelessness, pessimism, perceived constraints) are associated with risk of incident dementia and cognitive impairment not dementia (CIND), 2) whether the associations are independent of depressive symptoms and history of a mental health diagnosis, and 3) whether the associations are also independent of behavioral, clinical, and genetic risk factors. A total of 9,913 participants (60% female) from the Health and Retirement Study completed the baseline measures, scored in the non-impaired range of cognition at baseline, and had cognitive status assessed across the 6-8-year follow-up. Baseline measures included eight aspects of psychological distress and self-beliefs, cognitive performance, depressive symptoms, and genetic, clinical, and behavioral risk factors. Participants who scored higher on anxiety, negative affect, hostility, pessimism, hopelessness, and perceived constraints were at a 20-30% increased risk of dementia and a 10-20% increased risk of CIND. The associations held controlling for baseline depressive symptoms, history of a mental health diagnosis, clinical and behavioral risk factors, and genetic risk. Anger-in and anger-out were unrelated to risk of either dementia or CIND. Independent of the core experience of depressed affect, other aspects of negative emotionality and self-beliefs increase risk of mild and severe cognitive impairment, which suggests additional targets of intervention.

Quantitative Genetics Validates Previous Genetic Variants and Identifies Novel Genetic Players Influencing Alzheimer's Disease Cerebrospinal Fluid Biomarkers. - Ramos de Matos, Mafalda; Ferreira, Catarina; Herukka, Sanna-Kaisa; Soininen, Hilkka; Janeiro, André; Santana, Isabel; Baldeiras, Ines; Almeida, Maria Rosário; Lleo, Alberto; Dols-Icardo, Oriol; Alcolea, Daniel; Benussi, Luisa; et al. (J Alzheimers Dis, 2018)
Cerebrospinal fluid (CSF) biomarkers have been extensively investigated in the Alzheimer's disease (AD) field, and are now being applied in clinical practice. CSF amyloid-beta (Aβ1-42), total tau (t-tau), and phosphorylated tau (p-tau) reflect disease pathology, and may be used as quantitative traits for genetic analyses, fostering the identification of new genetic factors and the proposal of novel biological pathways of the disease. In patients, the concentration of CSF Aβ1-42 is decreased due to the accumulation of Aβ1-42 in amyloid plaques in the brain, while t-tau and p-tau levels are increased, indicating the extent of neuronal damage. To better understand the biological mechanisms underlying the regulation of AD biomarkers, and its relation to AD, we examined the association between 36 selected single nucleotide polymorphisms (SNPs) and AD biomarkers Aβ1-42, t-tau, and p-tau in CSF in a cohort of 672 samples (571 AD patients and 101 controls) collected within 10 European consortium centers.Our results highlighted five genes, APOE, LOC100129500, PVRL2, SNAR-I, and TOMM40, previously described as main players in the regulation of CSF biomarkers levels, further reinforcing a role for these in AD pathogenesis. Three new AD susceptibility loci, INPP5D, CD2AP, and CASS4, showed specific association with CSF tau biomarkers. The identification of genes that specifically influence tau biomarkers point out to mechanisms, independent of amyloid processing, but in turn related to tau biology that may open new venues to be explored for AD treatment.

Quantitative PET and Histology of Brain Biopsy Reveal Lack of Selective Pittsburgh Compound-B Binding to Intracerebral Amyloidoma. - Groot, Colin; Tolboom, Nelleke; Ikonomovic, Milos D; Lammertsma, Adriaan A; Boon, Baayla D C; Barkhof, Frederik; Scheltens, Philip; Klunk, William E; Rozemuller, Annemieke J M; Ossenkoppele, Rik; van Berckel, Bart N M (J Alzheimers Dis, 2018)
This single case study examines selective Pittsburgh compound-B (PiB) binding to an intracerebral light-chain amyloidoma using a 90-minute dynamic [11C]PiB-PET scan and brain biopsy tissue. Parametric non-displaceable binding potential (BPND) images showed low specific binding in the amyloidoma (BPND = 0.23), while relative tracer delivery was adequate (R1 = 0.44). Histology of the tissue revealed strong coloring with Congo-red, thioflavin-S, and X-34, indicating presence of amyloid. However, immunological staining with 6F/3D revealed absence of amyloid-β and histofluorescence of 6-CN-PiB, a highly fluorescent derivative of PiB, was at background levels. Our results suggest that PiB does not detect the atypical amyloid pathology associated with an intracerebral light-chain amyloidoma. These findings are of interest to clinicians and researchers applying [11C]PiB-PET to detect atypical forms of amyloid pathology.

Quantitative Susceptibility Mapping of Amyloid-β Aggregates in Alzheimer's Disease with 7T MR. - Tiepolt, Solveig; Schäfer, Andreas; Rullmann, Michael; Roggenhofer, Elisabeth; Gertz, Hermann-Josef; Schroeter, Matthias L; Patt, Marianne; Bazin, Pierre-Louis; Jochimsen, Thies H; Turner, Robert; Sabri, Osama; Barthel, Henryk (J Alzheimers Dis, 2018)
BACKGROUND: PET imaging is an established technique to detect cerebral amyloid-β (Aβ) plaques in vivo. Some preclinical and postmortem data report an accumulation of redox-active iron near Aβ plaques. Quantitative susceptibility mapping (QSM) at high-field MRI enables iron deposits to be depicted with high spatial resolution. OBJECTIVE: Aim of this study was to examine whether iron and Aβ plaque accumulation is related and thus, whether 7T MRI might be an additive diagnostic tool to Aβ PET imaging. METHODS: Postmortem human Alzheimer's disease (AD) and healthy control (HC) frontal gray matter (GM) was imaged with 7T MRI which resulted in T1 maps and QSM. Aβ plaque load was determined by histopathology. In vivo, 10 Aβ PET-positive AD patients (74.1±6.0a) and 10 Aβ PET-negative HCs (67.1±4.4a) underwent 7T MR examination and QSM maps were analyzed. Severity of cognitive deficits was determined by MMSE. RESULTS: Postmortem, the susceptibility of Aβ plaque-containing GM were higher than those of Aβ plaque-free GM (0.011±0.002 versus - 0.008±0.003 ppm, p < 0.001). In vivo, only the bilateral globus pallidus showed significantly higher susceptibility in AD patients compared to HCs (right: 0.277±0.018 versus - 0.009±0.009 ppm; left: 0.293±0.014 versus - 0.007±0.012 ppm, p < 0.0001). The pallidal QSM values were negatively correlated with those of the MMSE (r = - 0.69, p = 0.001). CONCLUSION: The postmortem study revealed significant susceptibility differences between the Aβ plaque-containing and Aβ plaque-free GM, whereas in vivo only the QSM values of the globus pallidus differed significantly between AD and HC group. The pallidal QSM values correlated with the severity of cognitive deficits. These findings encourage efforts to optimize the 7T-QSM methodology.

Rab10 Phosphorylation is a Prominent Pathological Feature in Alzheimer's Disease. - Yan, Tingxiang; Wang, Luwen; Gao, Ju; Siedlak, Sandra L; Huntley, Mikayla L; Termsarasab, Pichet; Perry, George; Chen, Shu G; Wang, Xinglong (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the leading cause of dementia in the elderly, characterized by neurofibrillary tangles (NFTs), senile plaques (SPs), and a progressive loss of neuronal cells in selective brain regions. Rab10, a small Rab GTPase involved in vesicular trafficking, has recently been identified as a novel protein associated with AD. Interestingly, Rab10 is a key substrate of leucine-rich repeat kinase 2 (LRRK2), a serine/threonine protein kinase genetically associated with the second most common neurodegenerative disease Parkinson's disease. However, the phosphorylation state of Rab10 has not yet been investigated in AD. Here, using a specific antibody recognizing LRRK2-mediated Rab10 phosphorylation at the amino acid residue threonine 73 (pRab10-T73), we performed immunocytochemical analysis of pRab10-T73 in hippocampal tissues of patients with AD. pRab10-T73 was prominent in NFTs in neurons within the hippocampus in all cases of AD examined, whereas immunoreactivity was very faint in control cases. Other characteristic AD pathological structures including granulovacuolar degeneration, dystrophic neurites and neuropil threads also contained pRab10-T73. The pRab10-T73 immunoreactivity was diminished greatly following dephosphorylation with alkaline phosphatase. pRab10-T73 was further found to be highly co-localized with hyperphosphorylated tau (pTau) in AD, and demonstrated similar pathological patterns as pTau in Down syndrome and progressive supranuclear palsy. Although pRab10-T73 immunoreactivity could be noted in dystrophic neurites surrounding SPs, SPs were largely negative for pRab10-T73. These findings indicate that Rab10 phosphorylation could be responsible for aberrations in the vesicle trafficking observed in AD leading to neurodegeneration.

Rare Variants in PLD3 Increase Risk for Alzheimer's Disease in Han Chinese. - Tan, Meng-Shan; Zhu, Jun-Xia; Cao, Xi-Peng; Yu, Jin-Tai; Tan, Lan (J Alzheimers Dis, 2018)
Next-generation sequencing studies had reported that a rare coding variant p.V232M in PLD3 was associated with Alzheimer's disease (AD) and a two-fold increased AD risk in European cohorts. To test whether coding region variants of PLD3 were associated with AD in a large Han Chinese cohort, we performed sequencing to analyze all exons of PLD3, and demonstrated that rare variants p.I163M and c.1020-8G>A conferred considerable risk of late-onset AD (LOAD) in our cohort. Meanwhile, the previously reported p.V232M variant was identified in our AD group. These findings indicate that rare variants of PLD3 may play an important role in LOAD in northern Han Chinese.

Rationale and Design of the Mechanistic Potential of Antihypertensives in Preclinical Alzheimer's (HEART) Trial. - Wharton, Whitney; Goldstein, Felicia C; Tansey, Malú G; Brown, Alexandra L; Tharwani, Sonum D; Verble, Danielle D; Cintron, Amarallys; Kehoe, Patrick G (J Alzheimers Dis, 2018)
Research indicates that certain antihypertensive medications alter Alzheimer's disease (AD) biomarkers in Caucasians. The renin angiotensin system (RAS) regulates blood pressure (BP) in the body and the brain and may directly influence AD biomarkers, including amyloid-β (Aβ) neuropathology, cerebral blood flow (CBF), and inflammatory markers. This hypothesis is supported by studies, including ours, showing that antihypertensives targeting the RAS reduce the risk and slow the progression of AD in Caucasians. While mounting evidence supports a protective role of RAS medications in Caucasians, this mechanism has not been explored in African Americans. To assess the mechanism by which RAS medications modify the brain RAS, cerebrospinal fluid (CSF) Aβ, CBF, and inflammatory markers in African Americans, we are conducting an eight month, Phase Ib randomized, placebo controlled trial, enrolling 60 middle-aged (45-70 years), non-demented individuals, at risk for AD by virtue of a parental history. Participants include normotensive and treated hypertensives that have never been exposed to a RAS medication. Participants are randomized (1 : 1:1) by gender and BP medication use (yes/no) to one of three groups: placebo, or 20 mg, or 40 mg telmisartan (Micardis), to determine the dose required to penetrate the CNS. Our overarching hypothesis is that, compared to placebo, both doses of telmisartan will penetrate the CNS and produce salutary, dose dependent effects on the brain RAS as well as CSF Aβ, CBF, and CSF inflammatory markers in African Americans, over eight months. This manuscript describes the trial rationale and design.
Keywords: African Americans; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antihypertensive Agents; Biomarkers; Blood Pressure; Brain; Clinical Trials, Phase I as Topic; Female; Georgia; Humans; Linear Models; Male; Middle Aged; Randomized Controlled Trials as Topic; Renin-Angiotensin System; Telmisartan

The Rationale and Design of the Reducing Pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR) Trial. - Kehoe, Patrick G; Blair, Peter S; Howden, Beth; Thomas, David L; Malone, Ian B; Horwood, Jeremy; Clement, Clare; Selman, Lucy E; Baber, Hannah; Lane, Athene; Coulthard, Elizabeth; Passmore, Anthony Peter; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Anti-hypertensives that modify the renin angiotensin system may reduce Alzheimer's disease (AD) pathology and reduce the rate of disease progression. OBJECTIVE: To conduct a phase II, two arm, double-blind, placebo-controlled, randomized trial of losartan to test the efficacy of Reducing pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR). METHODS: Men and women aged at least 55 years with mild-to-moderate AD will be randomly allocated 100 mg encapsulated generic losartan or placebo once daily for 12 months after successful completion of a 2-week open-label phase and 2-week placebo washout to establish drug tolerability. 228 participants will provide at least 182 subjects with final assessments to provide 84% power to detect a 25% difference in atrophy rate (therapeutic benefit) change over 12 months at an alpha level of 0.05. We will use intention-to-treat analysis, estimating between-group differences in outcomes derived from appropriate (linear or logistic) multivariable regression models adjusting for minimization variables. RESULTS: The primary outcome will be rate of whole brain atrophy as a surrogate measure of disease progression. Secondary outcomes will include changes to 1) white matter hyperintensity volume and cerebral blood flow; 2) performance on a standard series of assessments of memory, cognitive function, activities of daily living, and quality of life. Major assessments (for all outcomes) and relevant safety monitoring of blood pressure and bloods will be at baseline and 12 months. Additional cognitive assessment will also be conducted at 6 months along with safety blood pressure and blood monitoring. Monitoring of blood pressure, bloods, and self-reported side effects will occur during the open-label phase and during the majority of the post-randomization dispensing visits. CONCLUSION: This study will identify whether losartan is efficacious in the treatment of AD and whether definitive Phase III trials are warranted.
Keywords: Activities of Daily Living; Alzheimer Disease; Antihypertensive Agents; Atrophy; Blood Pressure Monitors; Brain; Clinical Trials, Phase II as Topic; Disease Progression; Double-Blind Method; Female; Humans; Losartan; Magnetic Resonance Imaging; Male; Multivariate Analysis; Quality of Life; Randomized Controlled Trials as Topic; Regression Analysis; Renin-Angiotensin System

Reduced Cerebrovascular Reserve Capacity as a Biomarker of Microangiopathy in Alzheimer's Disease and Mild Cognitive Impairment. - Urbanova, Barbora Soukupova; Schwabova, Jaroslava Paulasova; Magerova, Hana; Jansky, Petr; Marková, Hana; Vyhnálek, Martin; Laczó, Jan; Hort, Jakub; Tomek, Ales (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral microangiopathy in Alzheimer's disease (AD) causes chronic hypoperfusion and probably accelerates neurodegenerative changes. OBJECTIVE: We hypothesize microvascular impairment could be present already in mild cognitive impairment (MCI) and can be revealed using transcranial color-coded sonography (TCCS) and the breath-holding maneuver. METHODS: Three groups of subjects (AD in the stage of dementia, MCI, and cognitively normal controls) with detailed neuropsychological testing and low cerebrovascular burden (no history of stroke, no intra- or extracranial artery stenoses, and no severe vascular lesions on brain MRI), underwent a TCCS assessment of peak systolic (PSV), mean flow (MFV), and end diastolic velocities (EDV) and resistance and pulsatility indices (RI, PI) in large intracranial vessels bilaterally. Cerebrovascular reserve capacity was assessed using the breath-holding index (BHI) in middle cerebral artery (MCA) bilaterally. The ultrasound parameters were compared between the groups, correlated with neuropsychological tests, and compared between amnestic and non-amnestic MCI subtypes. RESULTS: Fourteen AD (3 males, 67.9±11.1 years, MMSE 18.0±4.6), 24 MCI (13 males, 71.9±7.3 years, MMSE 28.0±1.6), and 24 risk factor-matched controls (14 males, 67.8±6.4 years, MMSE 29.1±1.2) were enrolled. Significant differences were found between AD and controls in MFV, EDV, RI, PI in right MCA after breath holding, in PSV, MFV, EDV in left MCA after breath holding, and in BHI on the left side. The left BHI correlated positively with verbal memory test. CONCLUSION: Results show decreased cerebrovascular reserve capacity in AD as a sign of impaired cerebral hemodynamic status without severe underlying atherosclerosis. This can be identified using TCCS and BHI.

Regional Distribution, Asymmetry, and Clinical Correlates of Tau Uptake on [18F]AV-1451 PET in Atypical Alzheimer's Disease. - Tetzloff, Katerina A; Graff-Radford, Jonathan; Martin, Peter R; Tosakulwong, Nirubol; Machulda, Mary M; Duffy, Joseph R; Clark, Heather M; Senjem, Matthew L; Schwarz, Christopher G; Spychalla, Anthony J; Drubach, Daniel A; Jack, Clifford R; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Despite common pathology, Alzheimer's disease (AD) can have multiple clinical presentations which pathological studies suggest result from differences in the regional distribution of tau pathology. Positron emission tomography (PET) ligands are now available that can detect tau proteins in vivo and hence can be used to investigate the biological mechanisms underlying atypical AD. OBJECTIVE: To assess regional patterns of tau uptake on PET imaging in two atypical AD variants, posterior cortical atrophy (PCA) and logopenic progressive aphasia (lvPPA). METHODS: Eighteen PCA and 19 lvPPA subjects that showed amyloid-β deposition on PET underwent tau-PET imaging with [18F]AV-1451. Group comparisons of tau uptake in PCA and lvPPA were performed using voxel-level and regional-level analyses. We also assessed the degree of lobar tau asymmetry and correlated regional tau uptake to age and performance on clinical evaluations. RESULTS: Both syndromes showed diffuse tau uptake throughout all cortical regions, although PCA showed greater uptake in occipital regions compared to lvPPA, and lvPPA showed greater uptake in left frontal and temporal regions compared to PCA. While lvPPA showed predominant left-asymmetric tau deposition, PCA was more bilateral. Younger subjects showed greater tau uptake bilaterally in frontal and parietal lobes than older subjects, and sentence repetition, Boston naming test, simultanagnosia, and visuoperceptual function showed specific regional tau correlates. CONCLUSION: Tau deposition is closely related to clinical presentation in atypical AD with age playing a role in determining the degree of cortical tau deposition.

Regional White Matter Hyperintensity Influences Grey Matter Atrophy in Mild Cognitive Impairment. - Vipin, Ashwati; Foo, Heidi Jing Ling; Lim, Joseph Kai Wei; Chander, Russell Jude; Yong, Ting Ting; Ng, Adeline Su Lyn; Hameed, Shahul; Ting, Simon Kang Seng; Zhou, Juan; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
The association between cerebrovascular disease pathology (measured by white matter hyperintensities, WMH) and brain atrophy in early Alzheimer's disease (AD) remain to be elucidated. Thus, we investigated how WMH influence neurodegeneration and cognition in prodromal and clinical AD. We examined 51 healthy controls, 35 subjects with mild cognitive impairment (MCI), and 30 AD patients. We tested how total and regional WMH is related to specific grey matter volume (GMV) reductions in MCI and AD compared to controls. Stepwise regression analysis was further performed to investigate the association of GMV and regional WMH volume with global cognition. We found that total WMH volume was highest in AD but showed the strongest association with lower GMV in MCI. Frontal and parietal WMH had the most extensive influence on GMV loss in MCI. Additionally, parietal lobe WMH volume (but not hippocampal atrophy) was significantly associated with global cognition in MCI while smaller hippocampal volume (but not WMH volume) was associated with lower global cognition in AD. Thus, although WMH volume was highest in AD subjects, it had a more pervasive influence on brain structure and cognitive impairment in MCI. Our study thus highlights the importance of early detection of cerebrovascular disease, as its intervention at the MCI stage might potentially slow down neurodegeneration.

Relationship of Area of Soft Drusen in Retina with Cerebral Amyloid-β Accumulation and Blood Amyloid-β Level in the Elderly. - Shoda, Chiho; Kitagawa, Yorihisa; Shimada, Hiroyuki; Yuzawa, Mitsuko; Tateno, Amane; Okubo, Yoshiro (J Alzheimers Dis, 2018)
BACKGROUND: Histopathological studies have confirmed that soft drusen contains amyloid-β (Aβ). OBJECTIVE: To examine the relationship between the area of soft drusen in the macular area and cerebral Aβ accumulation or plasma Aβ level in elderly persons without dementia. METHODS: Fourteen consecutive patients (18 eyes) aged ≥50 years with macular soft drusen were studied prospectively. From color fundus photographs, the area of soft drusen (pixel) within a 6,000 μm diameter with the macula as center was measured. Standard uptake value ratio (SUVR) was obtained from positron emission tomography using florbetapir, which indicates the ratio of cerebral cortical-to-cerebellar Aβ accumulation. Ratio of plasma Aβ1-42 to Aβ1-40 level was calculated. RESULTS: Mean age was 73.3±7.6 years. The soft drusen area was 4.32±2.42 mm2. The SUVR was 1.08±0.15. Plasma Aβ1-42/Aβ1-40 ratio was 0.17±0.08. When SUVR ≥1.10 was defined as positive and <1.10 as negative, the soft drusen area in SUVR-positive patients (6.19±1.14 mm2) was significantly (p = 0.0043) larger than that in SUVR-negative patients (3.13±2.27 mm2). Multivariate regression analysis showed that SUVR positivity correlated with soft drusen area (p = 0.0484) and with Voxel-based Specific Regional Analysis System for Alzheimer's Disease score (p = 0.0360). However, there was no correlation with gender (p = 0.1921), age (p = 0.2361), Alzheimer's Disease Assessment Scale score (p = 0.6310), Mini-Mental State Examination score (p = 0.4246), or plasma Aβ1-42/Aβ1-40 ratio (p = 0.8398). CONCLUSION: Among elderly persons without dementia, the area of soft drusen was larger in those with more extensive cerebral Aβ accumulation. The area of soft drusen may be a biomarker of cerebral Aβ accumulation.

A Retrospective Belgian Multi-Center MRI Biomarker Study in Alzheimer's Disease (REMEMBER). - Niemantsverdriet, Ellis; Ribbens, Annemie; Bastin, Christine; Benoit, Florence; Bergmans, Bruno; Bier, Jean-Christophe; Bladt, Roxanne; Claes, Lene; De Deyn, Peter Paul; Deryck, Olivier; Hanseeuw, Bernard; Ivanoiu, Adrian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Magnetic resonance imaging (MRI) acquisition/processing techniques assess brain volumes to explore neurodegeneration in Alzheimer's disease (AD). OBJECTIVE: We examined the clinical utility of MSmetrix and investigated if automated MRI volumes could discriminate between groups covering the AD continuum and could be used as a predictor for clinical progression. METHODS: The Belgian Dementia Council initiated a retrospective, multi-center study and analyzed whole brain (WB), grey matter (GM), white matter (WM), cerebrospinal fluid (CSF), cortical GM (CGM) volumes, and WM hyperintensities (WMH) using MSmetrix in the AD continuum. Baseline (n = 887) and follow-up (FU, n = 95) T1-weighted brain MRIs and time-linked neuropsychological data were available. RESULTS: The cohort consisted of cognitively healthy controls (HC, n = 93), subjective cognitive decline (n = 102), mild cognitive impairment (MCI, n = 379), and AD dementia (n = 313). Baseline WB and GM volumes could accurately discriminate between clinical diagnostic groups and were significantly decreased with increasing cognitive impairment. MCI patients had a significantly larger change in WB, GM, and CGM volumes based on two MRIs (n = 95) compared to HC (FU>24months, p = 0.020). Linear regression models showed that baseline atrophy of WB, GM, CGM, and increased CSF volumes predicted cognitive impairment. CONCLUSION: WB and GM volumes extracted by MSmetrix could be used to define the clinical spectrum of AD accurately and along with CGM, they are able to predict cognitive impairment based on (decline in) MMSE scores. Therefore, MSmetrix can support clinicians in their diagnostic decisions, is able to detect clinical disease progression, and is of help to stratify populations for clinical trials.

Revolution of Alzheimer Precision Neurology. Passageway of Systems Biology and Neurophysiology. - Hampel, Harald; Toschi, Nicola; Babiloni, Claudio; Baldacci, Filippo; Black, Keith L; Bokde, Arun L W; Bun, René S; Cacciola, Francesco; Cavedo, Enrica; Chiesa, Patrizia A; Colliot, Olivier; Coman, Cristina-Maria; et al. (J Alzheimers Dis, 2018)
The Precision Neurology development process implements systems theory with system biology and neurophysiology in a parallel, bidirectional research path: a combined hypothesis-driven investigation of systems dysfunction within distinct molecular, cellular, and large-scale neural network systems in both animal models as well as through tests for the usefulness of these candidate dynamic systems biomarkers in different diseases and subgroups at different stages of pathophysiological progression. This translational research path is paralleled by an "omics"-based, hypothesis-free, exploratory research pathway, which will collect multimodal data from progressing asymptomatic, preclinical, and clinical neurodegenerative disease (ND) populations, within the wide continuous biological and clinical spectrum of ND, applying high-throughput and high-content technologies combined with powerful computational and statistical modeling tools, aimed at identifying novel dysfunctional systems and predictive marker signatures associated with ND. The goals are to identify common biological denominators or differentiating classifiers across the continuum of ND during detectable stages of pathophysiological progression, characterize systems-based intermediate endophenotypes, validate multi-modal novel diagnostic systems biomarkers, and advance clinical intervention trial designs by utilizing systems-based intermediate endophenotypes and candidate surrogate markers. Achieving these goals is key to the ultimate development of early and effective individualized treatment of ND, such as Alzheimer's disease. The Alzheimer Precision Medicine Initiative (APMI) and cohort program (APMI-CP), as well as the Paris based core of the Sorbonne University Clinical Research Group "Alzheimer Precision Medicine" (GRC-APM) were recently launched to facilitate the passageway from conventional clinical diagnostic and drug development toward breakthrough innovation based on the investigation of the comprehensive biological nature of aging individuals. The APMI movement is gaining momentum to systematically apply both systems neurophysiology and systems biology in exploratory translational neuroscience research on ND.
Keywords: Alzheimer Disease; Animals; Brain; Humans; Neurology; Neurophysiology; Precision Medicine; Systems Biology; Translational Medical Research

Risk Factors Associated with Cortical Thickness and White Matter Hyperintensities in Dementia Free Okinawan Elderly. - Silbert, Lisa C; Lahna, David; Promjunyakul, Nutta-On; Boespflug, Erin; Ohya, Yusuke; Higashiuesato, Yasushi; Nishihira, Junko; Katsumata, Yuriko; Tokashiki, Takashi; Dodge, Hiroko H (J Alzheimers Dis, 2018)
BACKGROUND: Cortical gray matter (GM) and white matter (WM) deterioration are signals of neurodegeneration and increased dementia risk; however, their specific etiologies in dementia-free aging is unclear. OBJECTIVE: The objective of this study was to examine potentially modifiable risk factors of GM and WM degeneration in a well-characterized cohort of dementia-free elderly. METHODS: 96 Okinawan elderly participants (age 83.6) from the Keys to Optimal Cognitive Aging Project (KOCOA) underwent MRI and cognitive evaluation. Serum markers of inflammation (interleukin-6 (IL-6), high sensitivity C-reactive protein), cerebrovascular disease (systolic blood pressure (SBP) 140+, hemoglobin A1C (HgbA1C), total cholesterol), and essential minerals (copper (Cu), magnesium, and calcium) were examined in relation to mean cortical thickness (MCT) and white matter hyperintensities (WMH), adjusting for age and gender. Voxel-based morphometry (VBM) analyses identified relationships between regional GM density and the above markers. RESULTS: Decreased MCT was associated with SBP 140 + (p = 0.029) and increased serum IL-6 (p = 0.036), HgbA1C (p = 0.002), and Cu (p = 0.025). In VBM analyses, increased IL-6, HgbA1C, and Cu were associated with decreased GM density in temporal lobe regions. HgbA1C (p = 0.004) was associated with greater WMH volume. CONCLUSIONS: Peripheral markers of Cu, CVD risk, and inflammation are associated with MRI-markers of decreased brain health in dementia-free Okinawan elderly, with regional cortical thinning in areas involved in early accumulation of Alzheimer's disease pathology. Results identify potentially modifiable biomarkers as targets in the prevention of dementia in older individuals.

Risk Factors of Rapid Cognitive Decline in Alzheimer's Disease and Mild Cognitive Impairment: A Systematic Review and Meta-Analysis. - Song, Ya-Nan; Wang, Ping; Xu, Wei; Li, Jie-Qiong; Cao, Xi-Peng; Yu, Jin-Tai; Tan, Lan (J Alzheimers Dis, 2018)
BACKGROUND: The conclusions about risk factors for rapid cognitive decline (RCD) in Alzheimer's disease (AD) and mild cognitive impairment (MCI) remain contradictory. OBJECTIVE: To explore the factors predicting RCD in AD and MCI. METHODS: We searched the PubMed, EMBASE, and the Cochrane Library from inception to May 27, 2017 for studies investigating factors associated with faster cognitive progression in AD and MCI. Effect sizes were meta-analyzed using fixed-effects and random-effects models. RESULTS: Fifty-three studies with 14,330 patients (12,396 AD and 1,934 MCI) were included in the systematic review. The following factors were identified to increase the risk of RCD in AD: Apolipoprotein E4 (ApoE4) (SMD [95% CI]: 0.52 [0.06,0.98]), early age at onset (SMD [95% CI]: -0.42 [-0.71, -0.13]), high level of education (RR = 2.05, 95% CI = 1.26 to 3.33), early appearance of extrapyramidal signs (RR = 2.18; 95% CI = 1.30 to 3.67), and neuropsychiatric conditions including hallucination (RR = 2.01, 95% CI = 1.40 to 2.87), strolling (RR = 1.99, 95% CI = 1.38 to 2.86), agitation (RR = 1.66, 95% CI = 1.23 to 2.24), and psychosis (RR = 1.42, 95% CI = 1.07 to 1.89). Instead, advanced age (≥75 years) (RR = 0.96, 95% CI = 0.93 to 0.99), diabetes (RR = 0.57; 95% CI = 0.35 to 0.93), and multidrug therapy (RR = 0.61, 95% CI = 0.60 to 0.62) would lower the risk of RCD. Furthermore, systematic research also reviewed seven risk factors associated with RCD in MCI. CONCLUSION: ApoE4, early onset, early appearance of extrapyramidal signs, high education level, and neuropsychiatric conditions might increase the risk of RCD while older age, diabetes, and multidrug therapy were the protective factors for AD.

Risk of Alzheimer's Disease in Obstructive Sleep Apnea Syndrome: Amyloid-β and Tau Imaging. - Elias, Alby; Cummins, Tia; Tyrrell, Regan; Lamb, Fiona; Doré, Vincent; Williams, Robert; Rosenfeld, J V; Hopwood, Malcolm; Villemagne, Victor L; Rowe, Christopher C (J Alzheimers Dis, 2018)
BACKGROUND: An association between obstructive sleep apnea (OSA) and Alzheimer's disease has been suggested but little is known about amyloid-β and tau deposition in this syndrome. OBJECTIVE: To determine amyloid and tau burden and cognitive function in OSA in comparison with those without a diagnosis of OSA. METHODS: The status of OSA was determined by asking participants about history of polysomnographic diagnosis of OSA and the use of Continuous Positive Airway Pressure (CPAP). A comprehensive neuropsychological battery measured cognitive function. Positron emission tomography (PET) was used to measure standardized uptake value ratio (SUVR) of 18F-florbetaben and 18F-AV1451, to quantify amyloid and tau burden. RESULTS: 119 male Vietnam veterans completed assessment. Impairment in visual attention and processing speed and increased body mass index (BMI) were seen in subjects with OSA compared with those without a diagnosis OSA. The cortical uptake of 18F-florbetaben was higher in the OSA group than in the control group (SUVR: 1.35±0.21 versus 1.27±0.16, p = 0.04). There were more apolipoprotein E ɛ4 allele (APOE ɛ4) carriers in the OSA group than in the control group. In multilinear regression analysis, the significance of OSA in predicting 18F-florbetaben uptake remained independent of age and vascular risk factors but not when BMI or APOE ɛ4 was adjusted. The reported use of CPAP (n = 14) had no effect on cognitive or amyloid PET findings. There was no significant difference in 18F-AV1451 uptake between the two groups. CONCLUSIONS: Obstructive sleep apnea is associated with Alzheimer's disease pathology, but this relationship is moderated by APOE ɛ4 and BMI.

Risk of Conversion to Dementia in a Mild Behavioral Impairment Group Compared to a Psychiatric Group and to a Mild Cognitive Impairment Group. - Taragano, Fernando E; Allegri, Ricardo F; Heisecke, Silvina L; Martelli, María I; Feldman, Mónica L; Sánchez, Viviana; García, Virginia A; Tufro, Graciela; Castro, Diego M; Leguizamón, Patricio Perez; Guelar, Verónica; Ruotolo, Eva; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is insufficient available information on behavioral changes in the absence of cognitive impairment as factors increasing the risk of conversion to dementia. OBJECTIVE: To observe and analyze patients with mild behavioral impairment (MBI), mild cognitive impairment (MCI), and a psychiatry group (PG) to compare the risk of progression to dementia. METHODS: From 677 initially assessed ≥60-year-old patients, a series of 348 patients was studied for a five-year period until censoring or conversion to dementia: 96 with MBI, 87 with MCI, and 165 with general psychiatry disorders, including 4 subgroups: Anxiety, Depression, Psychosis and Others. All patients were assessed with clinical, psychiatric, neurological, neuropsychological, and neuroimaging studies. RESULTS: From 348 patients, 126 evolved to dementia (36.2%). Conversion was significantly higher in MBI (71.5%), followed by the MCI-MBI overlap (59.6%) and MCI (37.8%) groups, compared to PG (13.9%) (Log-rank p < 0.001). MCI patients mostly converted to Alzheimer's dementia, while MBI converted to frontotemporal dementia and Lewy body dementia. Patients in PG converted to Lewy body dementia and frontotemporal dementia. CONCLUSION: Conversion to dementia is significantly higher in patients with neuropsychiatric symptoms. The MBI concept generates a new milestone in the refining of diagnosis of neurodegenerative diseases and the possibility of creating neuropsychiatric profiles. Its earlier identification will allow new possibilities for therapeutic intervention.

Role of ASK1/p38 Cascade in a Mouse Model of Alzheimer's Disease and Brain Aging. - Hasegawa, Yu; Toyama, Kensuke; Uekawa, Ken; Ichijo, Hidenori; Kim-Mitsuyama, Shokei (J Alzheimers Dis, 2018)
To examine the role of ASK1 in Alzheimer's disease (AD), we generated 5XFAD mice deficient in ASK1 and investigated the characteristics of old 5XFAD and wild-type mice with ASK1 deficiency. ASK1 deficiency improved cognitive function in 24-month-old 5XFAD mice, which was associated with the reduction of phosphorylated p38. Thus, ASK1/p38 cascade seems to play some role in the pathogenesis of AD in mice. In 24-month-old wild-type mice, ASK1 deficiency increased cerebral vasoreactivity to acetazolamide and significantly reduced brain soluble Aβ, which were also associated with the reduction of phosphorylated p38. Thus, ASK1/p38 cascade may contribute to brain aging of wild-type mice. Collectively, our present results provided the evidence suggesting the involvement of ASK1/p38 cascade in AD and brain aging.
Keywords: Aging; Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Avoidance Learning; Disease Models, Animal; Gene Expression Regulation; MAP Kinase Kinase Kinase 5; MAP Kinase Signaling System; Mice; Mice, Inbred C57BL; Mice, Transgenic; Presenilin-1; Reaction Time

The Role of Verb Fluency in the Detection of Early Cognitive Impairment in Alzheimer's Disease. - Alegret, Montserrat; Peretó, Mar; Pérez, Alba; Valero, Sergi; Espinosa, Ana; Ortega, Gemma; Hernandez, Isabel; Mauleón, Ana; Rosende-Roca, Maitee; Vargas, Liliana; Rodríguez-Gómez, Octavio; Abdelnour, Carla; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Verb fluency (VF) is the less commonly used fluency test, despite several studies suggesting its potential as a neuropsychological assessment tool. OBJECTIVE: To investigate the presence of VF deficits in mild cognitive impairment (MCI) and mild Alzheimer's disease (AD) dementia; to assess the usefulness of VF in the detection of cognitively healthy (CH) people who will convert to MCI, and from MCI to dementia; and to establish the VF cut-offs useful in the cognitive assessment of Spanish population. METHODS: 568 CH, 885 MCI, and 367 mild AD dementia individuals were administered the VF test and a complete neuropsychological battery. Longitudinal analyses were performed in 231 CH and 667 MCI subjects to search for VF predictors of diagnosis conversion. RESULTS: A worsening on VF performance from CH, MCI to AD dementia groups was found. Lower performances on VF were significantly related to conversion from CH to MCI/MCI to dementia. When the effect of time to conversion was analyzed, a significant effect of VF was found on the faster conversion from CH to MCI, but not from MCI to dementia. Moreover, VF cut-off scores and sensitivity/specificity values were calculated for 6 conditions (3 age ranges by 2 educational levels). CONCLUSION: The VF test may be a useful tool for the differential diagnosis of cognitive failure in the elderly. Since VF deficits seem to take place in early stages of the disease, it is a suitable neuropsychological tool for the detection not only of CH people who will convert to MCI, but also from MCI to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Cross-Sectional Studies; Early Diagnosis; Executive Function; Female; Humans; Language Tests; Logistic Models; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Sensitivity and Specificity; Spain

S-[18F]THK-5117-PET and [11C]PIB-PET Imaging in Idiopathic Normal Pressure Hydrocephalus in Relation to Confirmed Amyloid-β Plaques and Tau in Brain Biopsies. - Leinonen, Ville; Rauramaa, Tuomas; Johansson, Jarkko; Bottelbergs, Astrid; Tesseur, Ina; van der Ark, Peter; Pemberton, Darrel; Koivisto, Anne M; Jääskeläinen, Juha E; Hiltunen, Mikko; Herukka, Sanna-Kaisa; Blennow, Kaj; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Detection of pathological tau aggregates could facilitate clinical diagnosis of Alzheimer's disease (AD) and monitor drug effects in clinical trials. S-[18F]THK-5117 could be a potential tracer to detect pathological tau deposits in brain. However, no previous study have correlated S-[18F]THK-5117 uptake in PET with brain biopsy verified tau pathology in vivo. OBJECTIVE: Here we aim to evaluate the association between cerebrospinal fluid (CSF) AD biomarkers, S-[18F]THK-5117, and [11C]PIB PET against tau and amyloid lesions in brain biopsy. METHODS: Fourteen patients with idiopathic normal pressure hydrocephalus (iNPH) with previous shunt surgery including right frontal cortical brain biopsy and CSF Aβ1 - 42, total tau, and P-tau181 measures, underwent brain MRI, [11C]PIB PET, and S-[18F]THK-5117 PET imaging. RESULTS: Seven patients had amyloid-β (Aβ, 4G8) plaques, two both Aβ and phosphorylated tau (Pτ, AT8) and one only Pτ in biopsy. As expected, increased brain biopsy Aβ was well associated with higher [11C]PIB uptake in PET. However, S-[18F]THK-5117 uptake did not show any statistically significant correlation with either brain biopsy Pτ or CSF P-tau181 or total tau. CONCLUSIONS: S-[18F]THK-5117 lacked clear association with neuropathologically verified tau pathology in brain biopsy probably, at least partially, due to off-target binding. Further studies with larger samples of patients with different tau tracers are urgently needed. The detection of simultaneous Aβ and tau pathology in iNPH is important since that may indicate poorer and especially shorter response for CSF shunt surgery compared with no pathology.

Sally-Anne Test in Patients with Alzheimer's Disease Dementia. - Takenoshita, Shintaro; Terada, Seishi; Yokota, Osamu; Kutoku, Yumiko; Wakutani, Yosuke; Nakashima, Makoto; Maki, Yohko; Hattori, Hideyuki; Yamada, Norihito (J Alzheimers Dis, 2018)
Social cognition has recently been recognized as one of the essential cognitive domains. Some reports suggested that patients with Alzheimer's disease dementia (ADD) presented significant theory of mind deficits even in the mild condition. However, most previous studies included only small numbers of patients with ADD. The present study administered the first-order false belief (Sally-Anne) test to 116 consecutive patients with ADD from the outpatient units of the Memory Clinic and compared the characteristics of the two groups with correct and incorrect answers on the test. Then various clinical characteristics were evaluated. Only 37.1% of patients with ADD correctly answered the Sally-Anne test with the right explanation. Comparison between the two groups of correct and incorrect answers revealed a significant association between the frontal assessment battery score and the result of the Sally-Anne test in the multiple logistic regression analyses. Thus, patients with ADD presented a significant deficit in social cognition even in the mild condition. Frontal dysfunction was thought to be related to the deficits in mild ADD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Disease Progression; Female; Humans; Logistic Models; Male; Neuropsychological Tests; Social Behavior Disorders; Theory of Mind

Secular Trends in Dementia Prevalence and Incidence Worldwide: A Systematic Review. - Stephan, Blossom C M; Birdi, Ratika; Tang, Eugene Yee Hing; Cosco, Theodore D; Donini, Lorenzo M; Licher, Silvan; Ikram, M Arfan; Siervo, Mario; Robinson, Louise (J Alzheimers Dis, 2018)
BACKGROUND: Time trends for dementia prevalence and incidence rates have been reported over the past seven decades in different countries and some have reported a decline. OBJECTIVE: To undertake a systematic review to critically appraise and provide an evidence-based summary of the magnitude and direction of the global changes in dementia prevalence and incidence across time. METHODS: Medline, EMBASE, and PsychINFO were searched for studies focused on secular trends in dementia prevalence and/or incidence until 18 December 2017. In total, 10,992 articles were identified and 43 retained. RESULTS: Overall, prevalence rates are largely increasing (evidence primarily from record-based surveys and cohort studies in Japan, Canada, and France) or have remained stable (evidence primarily from cohort studies in Sweden, Spain and China). A significant decline in prevalence has however been reported in more recent studies (i.e., from 2010 onwards) from Europe (e.g., UK and Sweden) and the USA. Incidence rates have generally remained stable or decreased in China, Canada, France, Germany, Denmark, Sweden, the Netherlands, UK, and USA. An increase has only been reported in five countries: Italy, Japan, Wales, Germany, and the Netherlands. Only one study reported findings (stability in incidence) from a low and middle-income country using data from Nigeria. CONCLUSIONS: The evidence on secular trends in the prevalence and incidence of dementia is mixed including contradictory findings using different (and in some cases the same) datasets in some countries (e.g., the USA, UK, and Sweden). This making it difficult to draw concrete conclusions. However, declining trends recently observed in some high-income Western countries in the most recent two decades including the UK, USA, and Sweden are encouraging. Updated dementia prevalence and incidence estimates will inform public health and financial planning as well as development of prevention strategies.

Self-Reported Physical Activity is Associated with Tau Burden Measured by Positron Emission Tomography. - Brown, Belinda M; Rainey-Smith, Stephanie R; Doré, Vincent; Peiffer, Jeremiah J; Burnham, Samantha C; Laws, Simon M; Taddei, Kevin; Ames, David; Masters, Colin L; Rowe, Christopher C; Martins, Ralph N; Villemagne, Victor L (J Alzheimers Dis, 2018)
Numerous animal studies have reported exercise reduces the accumulation of Alzheimer's disease pathology, including amyloid-β (Aβ) and tau. Furthermore, we previously reported a relationship between higher levels of physical activity (PA) and lower brain Aβ burden in a human population. The recent advent of tau positron emission tomography (PET) tracers enables us to extend our investigations into the evaluation of the relationship between PA and brain tau burden. Utilizing data from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study, we have examined the cross-sectional relationship between habitual PA and PET-quantified tau burden. Forty-three cognitively healthy older adults were categorized into low-moderate PA (LMPA; n = 16) or high PA (HPA; n = 27), based on self-reported PA levels. Tau PET imaging with the AV1451 tracer was conducted on all participants. The LMPA group had significantly higher neocortical tau burden (presented as a z-score; 1.22±1.98), compared to the HPA group (z-score: - 0.28±1.18). The difference between the LMPA and HPA groups was also evident when examining regional tau burden in the temporoparietal cortex and the prefrontal cortex. Our results suggest an association between self-reported PA level and brain tau burden. Future longitudinal and interventional studies utilizing larger samples sizes are vital to further investigate the nature of the relationship between tau and PA.

Shear-Induced Amyloid Formation in the Brain: III. The Roles of Shear Energy and Seeding in a Proposed Shear Model. - Trumbore, Conrad N (J Alzheimers Dis, 2018)
If cerebrospinal and interstitial fluids move through very narrow brain flow channels, these restrictive surroundings generate varying levels of fluid shear and different shear rates, and dissolved amyloid monomers absorb different shear energies. It is proposed that dissolved amyloid-β protein (Aβ) and other amyloid monomers undergo shear-induced conformational changes that ultimately lead to amyloid monomer aggregation even at very low brain flow and shear rates. Soluble Aβ oligomers taken from diseased brains initiate in vivo amyloid formation in non-diseased brains. The brain environment is apparently responsible for this result. A mechanism involving extensional shear is proposed for the formation of a seed Aβ monomer molecule that ultimately promotes templated conformational change of other Aβ molecules. Under non-quiescent, non-equilibrium conditions, gentle extensional shear within the brain parenchyma, and perhaps even during laboratory preparation of Aβ samples, may be sufficient to cause subtle conformational changes in these monomers. These result from brain processes that significantly lower the high activation energy predicted for the quiescent Aβ dimerization process. It is further suggested that changes in brain location and changes brought about by aging expose Aβ molecules to different shear rates, total shear, and types of shear, resulting in different conformational changes in these molecules. The consequences of such changes caused by variable shear energy are proposed to underlie formation of amyloid strains causing different amyloid diseases. Amyloid researchers are urged to undertake studies with amyloids, anti-amyloid drugs, and antibodies while all of these are under shear conditions similar to those in the brain.

Shear-Induced Amyloid Formation in the Brain: IV. Effects on Synapses Surrounding Senile Plaque and in Plaque-Free Regions. - Trumbore, Conrad N (J Alzheimers Dis, 2018)
Amyloid-β oligomers (AβO) have been proposed as neurotoxins in the synaptic dysfunction that precedes Alzheimer's disease symptoms. Human and animal model studies report that senile plaques contain a halo of AβO molecules surrounding these plaques. A far smaller number of oligomers are distributed widely in plaque-free regions. It has been suggested that oligomers migrate from halos to nearby synapses and are incorporated into both pre- and postsynaptic terminals. These two types of oligomers have two different toxicities when extracted and injected in animal models. This paper proposes a shear-energy based explanation for the data in these studies. Shear hypotheses in the preceding three papers in this series are applied to suggest how the hydrodynamics and resulting shear patterns explain the spatial distribution of both AβO types, the apparent synapse loss in the vicinity of plaque particles, and possible reasons for the differing toxicities. A shear-based mechanism is proposed for the preferential migration of locally shear-excited Aβ molecules into the synaptic cleft. It is proposed that high energy laminar shear generated by the forced diversion of interstitial fluid around the flow-impeding plaque particle is responsible for the formation of AβOs around the plaque. It is suggested that in plaque-free regions, a different type of AβO with different toxicity is generated by lower energy shear flow around synapses, depositing AβO within the synapse from either the neuron membrane surface or by prion-like seeding within the synaptic cleft by locally-sheared Aβ molecules near the synapse entry.

Social Dysfunction in Older Age and Relationships with Cognition, Depression, and Apathy: The GreatAGE Study. - Lozupone, Madia; Panza, Francesco; Piccininni, Marco; Copetti, Massimiliano; Sardone, Rodolfo; Imbimbo, Bruno P; Stella, Eleonora; D'Urso, Francesca; Barulli, Maria Rosaria; Battista, Petronilla; Grasso, Alessandra; Tortelli, Rosanna; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Most studies focused on only one measure of social dysfunction in older age, without proper validation and distinction across different dimensions including subjectivity, structural, and functional aspects. OBJECTIVE: We sought to validate the Social Dysfunction Rating Scale (SDRS) and its factorial structure, also determining the association of SDRS with cognitive functions, global psychopathology, and social deprivation. METHODS: The SDRS was administered to 484 Italian community-dwelling elderly, recruited in the GreatAGE study, a population-based study on aging conducted in Castellana Grotte, Bari, Southern Italy. We determined objective and subjective psychometric properties of SDRS against the gold standard evaluation of social dysfunction according to the Semi-structured Clinical Diagnostic Interview for DSM-IV-TR Axis I Disorders (SCID-I) criterion. RESULTS: The SDRS showed a moderate accuracy with an optimal cut-off of 26 maximized with higher sensitivity (0.74,95% CI:0.63-0.84) than specificity (0.57,95% CI:0.50-0.64). A five-factor structure was carried out and five dimensions of SDRS were identified (loneliness; social isolation; feeling of contribution/uselessness; lack of leisure activities; anxiety for the health). Education and global cognitive functions were inversely correlated to SDRS, while a direct association with global psychopathology, depression, and apathy was found. The prevalence of higher SDRS scores was major in subjects with current psychiatric disorders versus other subjects.∥Conclusion: The SDRS could be a valid instrument to capture both size and quality of social dysfunction, both in subjects with psychiatric disorders and in normal subjects. Several categories of social dysfunction differed only in the degree of health deprivation, not in social or material deprivation.

SPARCL1 Accelerates Symptom Onset in Alzheimer's Disease and Influences Brain Structure and Function During Aging. - Seddighi, Sahba; Varma, Vijay R; An, Yang; Varma, Sudhir; Beason-Held, Lori L; Tanaka, Toshiko; Kitner-Triolo, Melissa H; Kraut, Michael A; Davatzikos, Christos; Thambisetty, Madhav (J Alzheimers Dis, 2018)
We recently reported that alpha-2 macroglobulin (A2M) is a biomarker of neuronal injury in Alzheimer's disease (AD) and identified a network of nine genes co-expressed with A2M in the brain. This network includes the gene encoding SPARCL1, a protein implicated in synaptic maintenance. Here, we examine whether SPARCL1 is associated with longitudinal changes in brain structure and function in older individuals at risk for AD in the Baltimore Longitudinal Study of Aging. Using data from the Gene-Tissue Expression Project, we first identified two single nucleotide polymorphisms (SNPs), rs9998212 and rs7695558, associated with lower brain SPARCL1 gene expression. We then analyzed longitudinal trajectories of cognitive performance in 591 participants who remained cognitively normal (average follow-up interval: 11.8 years) and 129 subjects who eventually developed MCI or AD (average follow-up interval: 9.4 years). Cognitively normal minor allele carriers of rs7695558 who developed incident AD showed accelerated memory loss prior to disease onset. Next, we compared longitudinal changes in brain volumes (MRI; n = 120 participants; follow-up = 6.4 years; 826 scans) and resting-state cerebral blood flow (rCBF; 15O-water PET; n = 81 participants; follow-up = 7.7 years; 664 scans) in cognitively normal participants. Cognitively normal minor allele carriers of rs9998212 showed accelerated atrophy in several global, lobar, and regional brain volumes. Minor allele carriers of both SNPs showed longitudinal changes in rCBF in several brain regions, including those vulnerable to AD pathology. Our findings suggest that SPARCL1 accelerates AD pathogenesis and thus link neuroinflammation with widespread changes in brain structure and function during aging.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Brain; Calcium-Binding Proteins; Cerebrovascular Circulation; Cognition Disorders; Extracellular Matrix Proteins; Female; Humans; Independent Living; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Positron-Emission Tomography

Stereological Investigation of the Effects of Treadmill Running Exercise on the Hippocampal Neurons in Middle-Aged APP/PS1 Transgenic Mice. - Chao, Fenglei; Jiang, Lin; Zhang, Yi; Zhou, Chunni; Zhang, Lei; Tang, Jing; Liang, Xin; Qi, Yingqiang; Zhu, Yanqing; Ma, Jing; Tang, Yong (J Alzheimers Dis, 2018)
The risk of cognitive decline during Alzheimer's disease (AD) can be reduced if physical activity is maintained; however, the specific neural events underlying this beneficial effect are still uncertain. To quantitatively investigate the neural events underlying the effect of running exercise on middle-aged AD subjects, 12-month-old male APP/PS1 mice were randomly assigned to a control group or running group, and age-matched non-transgenic littermates were used as a wild-type group. AD running group mice were subjected to a treadmill running protocol (regular and moderate intensity) for four months. Spatial learning and memory abilities were assessed using the Morris water maze. Hippocampal amyloid plaques were observed using Thioflavin S staining and immunohistochemistry. Hippocampal volume, number of neurons, and number of newborn cells (BrdU+ cells) in the hippocampus were estimated using stereological techniques, and newborn neurons were observed using double-labelling immunofluorescence. Marked neuronal loss in both the CA1 field and dentate gyrus (DG) and deficits in both the neurogenesis and survival of new neurons in the DG of middle-aged APP/PS1 mice were observed. Running exercise could improve the spatial learning and memory abilities, reduce amyloid plaques in the hippocampi, delay neuronal loss, induce neurogenesis, and promote the survival of newborn neurons in the DG of middle-aged APP/PS1 mice. Exercise-induced protection of neurons and adult neurogenesis within the DG might be part of the important structural basis of the improved spatial learning and memory abilities observed in AD mice.

Stimulation of SIRT1 Attenuates the Level of Oxidative Stress in the Brains of APP/PS1 Double Transgenic Mice and in Primary Neurons Exposed to Oligomers of the Amyloid-β Peptide. - Dong, Yang-Ting; Cao, Kun; Tan, Long-Chun; Wang, Xiao-Ling; Qi, Xiao-Lan; Xiao, Yan; Guan, Zhi-Zhong (J Alzheimers Dis, 2018)
In the study, we examined whether the silent information regulator 1 (SIRT1) can attenuate oxidative stress in the brains of mice carrying the APP/PS1 double mutation and/or in primary neonatal rat neurons exposed to oligomers of amyloid-β peptide (AβOs). Starting at 4 or 8 months of age, the transgenic mice were treated with resveratrol (RSV, a stimulator of SIRT1) or suramin (an inhibitor) (each 20 mg/kg BW/day) for two months. The primary neurons were exposed to AβOs (0.5 μM) for 48 h and thereafter RSV (20 μM) or suramin (300 mg/ml) for 24 h. Cell viability was assessed by the CCK-8 assay; SIRT1 protein and mRNA determined by western blotting and real-time PCR, respectively; senile plaques examined immunohistochemically; ROS monitored by flow cytometry; and the contents of OH-, H2O2, O2·-, and MDA, and the activities of SOD and GSH-Px measured by standard biochemical procedures. In comparison to wild-type mice or untreated primary neurons, the expression of SIRT1 was significantly lower in the brains of APP/PS1 mice or neurons exposed to AβOs. In these same systems, increased numbers of senile plaques and a high level of oxidative stress were apparent. Interestingly, these two latter changes were attenuated by treatment with RSV, but enhanced by suramin. These findings indicate that SIRT1 may be neuroprotective.

Structural Connectivity Alterations Along the Alzheimer's Disease Continuum: Reproducibility Across Two Independent Samples and Correlation with Cerebrospinal Fluid Amyloid-β and Tau. - Tucholka, Alan; Grau-Rivera, Oriol; Falcon, Carles; Rami, Lorena; Sánchez-Valle, Raquel; Lladó, Albert; Gispert, Juan Domingo; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: Gray matter changes associated with the progression of Alzheimer's disease (AD) have been thoroughly studied. However, alterations in white matter tracts have received less attention, particularly during early or preclinical stages of the disease. OBJECTIVE: To identify the structural connectivity changes across the AD continuum. METHODS: We performed probabilistic tractography in a total of 183 subjects on two independent samples that include control (n = 68) and preclinical AD individuals (n = 28), patients diagnosed with mild cognitive impairment (MCI) due to AD (n = 44), and AD patients (n = 43). We compared the connectivity between groups, and with CSF Aβ42 and tau biomarkers. RESULTS: We observed disconnections in preclinical individuals, mainly located in the temporal lobe. This pattern of disconnection spread to the parietal and frontal lobes at the MCI stage and involved almost all the brain in AD. These findings were not driven by gray matter atrophy. DISCUSSION: Using tractography, we were able to identify white matter changes between subsequent disease stages and, notably, also in preclinical AD. Therefore, this method may be useful for detecting early and specific brain structural changes during preclinical AD stage.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Gray Matter; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Reproducibility of Results; Spain; tau Proteins; White Matter

A Study of a Supplement Containing Huperzine A and Curcumin in Dementia Patients and Individuals with Mild Cognitive Impairment. - Tabira, Takeshi; Kawamura, Nobutoshi (J Alzheimers Dis, 2018)
Extracts from Huperzia serrata (HS) function as a cholinesterase inhibitor and a glutamic acid receptor antagonist. We tested a supplement containing HS extracts, curcumin, and others in dementia patients and individuals with mild cognitive impairment (MCI) in an open label study. Most patients with Alzheimer's disease, dementia with Lewy bodies, and MCI individuals exhibited improvements in cognitive functions, as assessed by the Alzheimer's Disease Assessment Scale-cognitive subscale Japanese version. The scores were significantly improved at 6-12 weeks compared with baseline scores (p = 0.007) and at 22-28 weeks (p = 0.004). Thus, this supplement may be administered to dementia patients as well as MCI individuals.

Subjective Sleep Quality is not Associated with Incident Dementia: The Rotterdam Study. - Lysen, Thom S; Wolters, Frank J; Luik, Annemarie I; Ikram, M Kamran; Tiemeier, Henning; Ikram, M Arfan (J Alzheimers Dis, 2018)
BACKGROUND: Poor sleep is related to higher dementia risk, but this association is more equivocal for subjective sleep quality specifically. This study investigates the link between subjective sleep quality and dementia risk in the general population. OBJECTIVE: To study the role of subjective sleep quality in the risk of dementia in the general population. METHODS: In the prospective population-based Rotterdam Study, 4,835 persons (mean age 72 years, 58% women) underwent a home interview (2002- 2006) that included the validated Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality. Participants were followed until 2015 for incident dementia, through in-person screening and continuous monitoring of medical records. We used Cox regression models to associate sleep quality with dementia risk, adjusting for age, sex, education, smoking, employment, coffee consumption, alcohol consumption, activities of daily living, cardiovascular risk factors, anxiety, depressive symptoms, cognition, and snoring. RESULTS: During 41,385 person-years (8.5 years mean), 420 participants developed dementia, of whom 320 Alzheimer's disease (AD). Poorer subjective sleep quality was not associated with the risk of all-cause dementia (hazard ratio [HR] per SD increase in PSQI score: 0.91, 95% CI 0.82- 1.02) or AD (HR 0.92, 95% CI 0.81- 1.05). Similarly, individual components of the PSQI were also not associated with dementia. Several sensitivity analyses, i.e., excluding last years of the follow-up time duration or restricting to those with best MMSE scores at baseline, did not reveal subgroups with increased risks. CONCLUSION: In this study, we found no association of poor subjective sleep quality with higher risk of dementia.

Sulforaphane Inhibits the Generation of Amyloid-β Oligomer and Promotes Spatial Learning and Memory in Alzheimer's Disease (PS1V97L) Transgenic Mice. - Hou, Ting-Ting; Yang, He-Yun; Wang, Wei; Wu, Qiao-Qi; Tian, Yuan-Ruhua; Jia, Jian-Ping (J Alzheimers Dis, 2018)
Abnormal amyloid-β (Aβ) aggregates are a striking feature of Alzheimer's disease (AD), and Aβ oligomers have been proven to be crucial in the pathology of AD. Any intervention targeting the generation or aggregation of Aβ can be expected to be useful in AD treatment. Oxidative stress and inflammation are common pathological changes in AD that are involved in the generation and aggregation of Aβ. In the present study, 6-month-old PS1V97L transgenic (Tg) mice were treated with sulforaphane, an antioxidant, for 4 months, and this treatment significantly inhibited the generation and aggregation of Aβ. Sulforaphane also alleviated several downstream pathological changes that including tau hyperphosphorylation, oxidative stress, and neuroinflammation. Most importantly, the cognition of the sulforaphane-treated PS1V97L Tg mice remained normal compared to that of wild-type mice at 10 months of age, when dementia typically emerges in PS1V97L Tg mice. Pretreating cultured cortical neurons with sulforaphane also protected against neuronal injury caused by Aβ oligomers in vitro. These findings suggest that sulforaphane may be a potential compound that can inhibit Aβ oligomer production in AD.

Synthetic Fragment of Receptor for Advanced Glycation End Products Prevents Memory Loss and Protects Brain Neurons in Olfactory Bulbectomized Mice. - Volpina, Olga M; Samokhin, Alexandr N; Koroev, Dmitriy O; Nesterova, Inna V; Volkova, Tatyana D; Medvinskaya, Natalia I; Nekrasov, Pavel V; Tatarnikova, Olga G; Kamynina, Anna V; Balasanyants, Samson M; Voronina, Tamara A; Kulikov, Alexey M; et al. (J Alzheimers Dis, 2018)
Activation of receptor for advanced glycation end products (RAGE) plays an essential role in the development of Alzheimer's disease (AD). It is known that the soluble isoform of the receptor binds to ligands and prevents negative effects of the receptor activation. We proposed that peptide fragments from RAGE prevent negative effects of the receptor activation during AD neurodegeneration. We have synthesized peptide fragments from surface-exposed regions of RAGE. Peptides were intranasally administrated into olfactory bulbectomized (OBX) mice, which developed some characteristics similar to AD neurodegeneration. We have found that only insertion of fragment (60-76) prevents the memory of OBX mice. Immunization of OBX mice with peptides showed that again only (60-76) peptide protected the memory of animals. Both intranasal insertion and immunization decreased the amyloid-β (Aβ) level in the brain. Activity of shortened fragments of (60-76) peptide was tested and showed only the (60-70) peptide is responsible for manifestation of activity. Intranasal administration of (60-76) peptide shows most protective effect on morpho-functional characteristics of neurons in the cortex and hippocampal areas. Using Flu-(60-76) peptide, we revealed its penetration in the brain of OBX mice as well as colocalization of Flu-labeled peptide with Aβ in the brain regions in transgenic mice. Flu-(60-76) peptide complex with trimer of Aβ was detected by SDS-PAGE. These data indicate that Aβ can be one of the molecular target of (60-70) peptide. These findings provide a new peptide molecule for design of anti-AD drug and for investigation of RAGE activation ways in progression of AD neurodegeneration.
Keywords: Administration, Intranasal; Animals; Behavior, Animal; Brain; Disease Models, Animal; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Neurons; Olfactory Bulb; Peptide Fragments; Receptor for Advanced Glycation End Products

Tauopathies: Mechanisms and Therapeutic Strategies. - Tan, Chen-Chen; Zhang, Xiao-Yan; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2018)
Tauopathies are morphologically, biochemically, and clinically heterogeneous neurodegenerative diseases defined by the accumulation of abnormal tau proteins in the brain. There is no effective method to prevent and reverse the tauopathies, but this gloomy picture has been changed by recent research advances. Evidences from genetic studies, experimental animal models, and molecular and cell biology have shed light on the main mechanisms of the diseases. The development of radiology and biochemistry, especially the development of PET imaging, will provide important biomarkers for the clinical diagnosis and treatment. Given the central role of tau in tauopathies, many treatments have constantly emerged, including targeting phosphorylation, targeting aggregation, increasing microtubule stabilization, tau immunization, clearance of tau, anti-inflammatory treatment, and other therapeutics. There is still a long way to go before we obtain drug therapy targeted at multifactor mechanisms.
Keywords: Animals; Biomarkers; Brain; Disease Models, Animal; Humans; Neuroimaging; Phosphorylation; Positron-Emission Tomography; tau Proteins; Tauopathies

TDP-43 and Alzheimer's Disease Pathologic Subtype in Non-Amnestic Alzheimer's Disease Dementia. - Sahoo, Aradhana; Bejanin, Alexandre; Murray, Melissa E; Tosakulwong, Nirubol; Weigand, Stephen D; Serie, Amanda M; Senjem, Matthew L; Machulda, Mary M; Parisi, Joseph E; Boeve, Bradley F; Knopman, David S; Petersen, Ronald C; et al. (J Alzheimers Dis, 2018)
BACKGROUND: TDP-43 has been shown to be strongly associated with memory loss, smaller hippocampal volumes, and faster rates of hippocampal atrophy in Alzheimer's disease (AD) patients with an amnestic presentation. Whether TDP-43 has any clinical or anatomical associations in AD patients with non-amnestic phenotype is unknown. OBJECTIVE: To determine whether TDP-43 plays a significant role in the clinic-anatomic features of non-amnestic AD. METHODS: All cases with pathologically confirmed intermediate-high probability AD from 1996-2012 were identified and retrospectively sub-classified into amnestic versus non-amnestic dementia at the time of presentation. Neurofibrillary tangle counts were performed in those with a non-amnestic presentation using thioflavin-S microscopy in the hippocampus and three neocortical regions, and all cases were subtyped into hippocampal-sparing, limbic-predominant, and typical AD pathology. TDP-43 immunoreactivity was used to assess for the presence of TDP-43. Statistical analyses helped determine whether pathologic subtype or TDP-43 was more strongly associated with clinico-imaging features. RESULTS: Out of 172 pathologically confirmed AD cases, 36 (19%) were classified as non-amnestic. Twenty-five of these 36 (69%) had typical pathology, 0 limbic-predominant pathology, and 11 (31%) hippocampal-sparing pathology. Eleven (44%) of the 25 cases with typical pathology were TDP-43+. Of the 11 cases with hippocampal-sparing pathology, 4 (36%) were TDP-43+. There were no differences in demographic, clinical, or neuroimaging features in those with TDP-43 versus those without except for older age at onset (p = 0.02) and age at death (p = 0.02) in those with TDP-43. AD pathological subtype accounted for slightly more of the variances in the neocortex than TDP-43. CONCLUSION: In non-amnestic AD, we find little evidence that clinical or anatomical features of the disease are related to TDP-43.

A Three-Factor Structure of Cognitive Functioning Among Unimpaired Carriers and Non-Carriers of Autosomal-Dominant Alzheimer's Disease. - Guzmán-Vélez, Edmarie; Jaimes, Sehily; Aguirre-Acevedo, Daniel C; Norton, Daniel J; Papp, Kathryn V; Amariglio, Rebecca; Rentz, Dorene; Baena, Ana; Henao, Eliana; Tirado, Victoria; Munoz, Claudia; Giraldo, Margarita; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to find cognitive markers that can help identify individuals at risk for Alzheimer's disease (AD), and that can be used to reliably measure cognitive decline. OBJECTIVE: We tested whether a theoretically driven three-factor structure would characterize cognitive functioning in individuals who are genetically-determined to develop AD due to a mutation in Presenilin-1 (PSEN1) gene. We also examined whether these factors could distinguish cognitively unimpaired PSEN1 mutation carriers from age-matched non-carrier family members. METHODS: 1,395 cognitively unimpaired members of a Colombian kindred with the PSEN1 E280A mutation were included in the study. A confirmatory factor analysis examined the fit of the three-factor model comprising episodic memory (MMSE memory recall, CERAD-COL Word list recall, and Constructional praxis recall), executive function (Phonemic fluency and WCST perseverative errors), and psychomotor processing speed (TMT-A and WAIS-III Digit Symbol). RESULTS: The three-factor model provided an excellent fit for all participants (p = 0.24; RMSEA = 0.01). Further, the episodic memory (p = 0.0004, d = 0.25) and executive functioning (p = 0.001, d = 0.18) factors distinguished cognitively unimpaired carriers from non-carriers. The episodic memory factor provided the earliest indication of preclinical cognitive decline at 35 years of age, nine years before individuals' estimated age of clinical onset. CONCLUSIONS: The three theoretically derived cognitive factors provide a reliable measure of cognition and may be useful for the early detection of AD, as well as for measuring disease progression. However, longitudinal studies are needed to confirm that these factors can be used to track the progression of cognitive decline in preclinical AD.

TLR4 Gene Expression and Pro-Inflammatory Cytokines in Alzheimer's Disease and in Response to Hippocampal Deafferentation in Rodents. - Miron, Justin; Picard, Cynthia; Frappier, Josée; Dea, Doris; Théroux, Louise; Poirier, Judes (J Alzheimers Dis, 2018)
One important aspect in Alzheimer's disease pathology is the presence of chronic inflammation. Considering its role as a key receptor in the microglial innate immune system, TLR4 was shown to regulate the binding and phagocytosis of amyloid plaques by microglia in several mouse models of amyloidosis, as well as the production of pro-inflammatory cytokines. To our knowledge, TLR4 and its association with cytokines have not been thoroughly examined in the brains of subjects affected with Alzheimer's disease. Using quantitative reverse transcription polymerase chain reaction (qRT-PCR) in postmortem human brains, we observed increased expression for the TLR4 and TNF genes (p = 0.001 and p = 0.025, respectively), as well as a trend for higher IL6 gene expression in the frontal cortex of AD subjects when compared to age-matched controls. Similarly, using a mouse model of hippocampal deafferentation without amyloidosis, (i.e., the entorhinal cortex lesioned mouse), we observed significant increases in the expression of both the Tlr4 (p = 0.0367 and p = 0.0193 compared to sham-lesioned mice or to the contralateral side, respectively) and Il1b (p = 0.0055 and p = 0.0066 compared to sham-lesioned mice or to the contralateral side, respectively) genes in the deafferentation phase, but not during the ensuing reinnervation process. In conclusion, we suggest that the modulation of cytokines by TLR4 is differentially regulated whether by the presence of amyloid plaques or by the ongoing deafferentation process.

Tocotrienol-Rich Fraction of Palm Oil Improves Behavioral Impairments and Regulates Metabolic Pathways in AβPP/PS1 Mice. - Durani, Lina Wati; Hamezah, Hamizah Shahirah; Ibrahim, Nor Faeizah; Yanagisawa, Daijiro; Nasaruddin, Muhammad Luqman; Mori, Masaki; Azizan, Kamalrul Azlan; Damanhuri, Hanafi Ahmad; Makpol, Suzana; Wan Ngah, Wan Zurinah; Tooyama, Ikuo (J Alzheimers Dis, 2018)
We have recently shown that the tocotrienol-rich fraction (TRF) of palm oil, a mixture of vitamin E analogs, improves amyloid pathology in vitro and in vivo. However, precise mechanisms remain unknown. In this study, we examined the effects of long-term (10 months) TRF treatment on behavioral impairments and brain metabolites in (15 months old) AβPP/PS1 double transgenic (Tg) Alzheimer's disease (AD) mice. The open field test, Morris water maze, and novel object recognition tasks revealed improved exploratory activity, spatial learning, and recognition memory, respectively, in TRF-treated Tg mice. Brain metabolite profiling of wild-type and Tg mice treated with and without TRF was performed using ultrahigh performance liquid chromatography (UHPLC) coupled to high-resolution accurate mass (HRAM)-orbitrap tandem mass spectrometry (MS/MS). Metabolic pathway analysis found perturbed metabolic pathways that linked to AD. TRF treatment partly ameliorated metabolic perturbations in Tg mouse hippocampus. The mechanism of this pre-emptive activity may occur via modulation of metabolic pathways dependent on Aβ interaction or independent of Aβ interaction.

Translational Research in Alzheimer's and Prion Diseases. - Di Fede, Giuseppe; Giaccone, Giorgio; Salmona, Mario; Tagliavini, Fabrizio (J Alzheimers Dis, 2018)
Translational neuroscience integrates the knowledge derived by basic neuroscience with the development of new diagnostic and therapeutic tools that may be applied to clinical practice in neurological diseases. This information can be used to improve clinical trial designs and outcomes that will accelerate drug development, and to discover novel biomarkers which can be efficiently employed to early recognize neurological disorders and provide information regarding the effects of drugs on the underlying disease biology. Alzheimer's disease (AD) and prion disease are two classes of neurodegenerative disorders characterized by incomplete knowledge of the molecular mechanisms underlying their occurrence and the lack of valid biomarkers and effective treatments. For these reasons, the design of therapies that prevent or delay the onset, slow the progression, or improve the symptoms associated to these disorders is urgently needed. During the last few decades, translational research provided a framework for advancing development of new diagnostic devices and promising disease-modifying therapies for patients with prion encephalopathies and AD. In this review, we provide present evidence of how supportive can be the translational approach to the study of dementias and show some results of our preclinical studies which have been translated to the clinical application following the 'bed-to-bench-and-back' research model.

The Unexpected Role of Aβ1-42 Monomers in the Pathogenesis of Alzheimer's Disease. - Tamagno, Elena; Guglielmotto, Michela; Monteleone, Debora; Manassero, Giusi; Vasciaveo, Valeria; Tabaton, Massimo (J Alzheimers Dis, 2018)
Amyloid-β (Aβ) has been proposed as a biomarker and a drug target for the therapy of Alzheimer's disease (AD). The neurotoxic entity and relevance of each conformational form of Aβ to AD pathology is still under debate; Aβ oligomers are considered the major killer form of the peptide whereas monomers have been proposed to be involved in physiological process. Here we reviewed some different effects mediated by monomers and oligomers on mechanisms involved in AD pathogenesis such as autophagy and tau aggregation. Data reported in this review demonstrate that Aβ monomers could have a major role in sustaining the pathogenesis of AD and that AD therapy should be focused not only in the removal of oligomers but also of monomers.

Untold New Beginnings: Adult Hippocampal Neurogenesis and Alzheimer's Disease. - Teixeira, Catia M; Pallas-Bazarra, Noemí; Bolós, Marta; Terreros-Roncal, Julia; Avila, Jesús; Llorens-Martín, María (J Alzheimers Dis, 2018)
Neurogenesis occurs in a limited number of brain regions during adulthood. Of these, the hippocampus has attracted great interest due to its involvement in memory processing. Moreover, both the hippocampus and the main area that innervates this structure, namely the entorhinal cortex, show remarkable atrophy in patients with Alzheimer's disease (AD). Adult hippocampal neurogenesis is a process that continuously gives rise to newborn granule neurons in the dentate gyrus. These cells coexist with developmentally generated granule neurons in this structure, and both cooperative and competition phenomena regulate the communication between these two types of cells. Importantly, it has been revealed that GSK-3β and tau proteins, which are two of the main players driving AD pathology, are cornerstones of adult hippocampal neurogenesis regulation. We have shown that alterations either promoting or impeding the actions of these two proteins have detrimental effects on the structural plasticity of granule neurons. Of note, these impairments occur both under basal conditions and in response to detrimental and neuroprotective stimuli. Thus, in order to achieve the full effectiveness of future therapies for AD, we propose that attention be turned toward identifying the pathological and physiological actions of the proteins involved in the pathogenesis of this condition.

Usefulness of Dual-Point Amyloid PET Scans in Appropriate Use Criteria: A Multicenter Study. - Segovia, Fermín; Gómez-Río, Manuel; Sánchez-Vañó, Raquel; Górriz, Juan Manuel; Ramírez, Javier; Triviño-Ibáñez, Eva; Carnero-Pardo, Cristóbal; Martínez-Lozano, María Dolores; Sopena-Novales, Pablo (J Alzheimers Dis, 2018)
BACKGROUND: Biomarkers of neurodegeneration play a major role in the diagnosis of Alzheimer's disease (AD). Information on both amyloid-β accumulation, e.g., from amyloid positron emission tomography (PET), and downstream neuronal injury, e.g., from 18F-fluorodeoxyglucose (FDG) PET, would ideally be obtained in a single procedure. OBJECTIVE: On the basis that the parallelism between brain perfusion and glucose metabolism is well documented, the objective of this work is to evaluate whether brain perfusion estimated in a dual-point protocol of 18F-florbetaben (FBB) PET can be a surrogate of FDG PET in appropriate use criteria (AUC) for amyloid PET. METHODS: This study included 47 patients fulfilling international AUC for amyloid PET. FDG PET, early FBB (pFBB) PET (0-10 min post injection), and standard FBB (sFBB) PET (90-110 min post injection) scans were acquired. Results of clinical subjective reports and of quantitative region of interest (ROI)-based analyses were compared between procedures using statistical techniques such as Pearson's correlation coefficients and t-tests. RESULTS: pFBB and FDG visual reports on the 47 patients showed good agreement (k  >  0.74); ROI quantitative analysis indicated that both data modalities are highly correlated; and the t-test analysis does not reject the null hypothesis that data from pFBB and FDG examinations comes from independent random samples from normal distributions with equal means and variances. CONCLUSIONS: A good agreement was found between pFBB and FDG data as obtained by subjective visual and quantitative analyses. Dual-point FBB PET scans could offer complementary information (similar to that from FDG PET and FBB PET) in a single procedure, considering pFBB as a surrogate of FDG.

Using Neuropsychological Process Scores to Identify Subtle Cognitive Decline and Predict Progression to Mild Cognitive Impairment. - Thomas, Kelsey R; Edmonds, Emily C; Eppig, Joel; Salmon, David P; Bondi, Mark W (J Alzheimers Dis, 2018)
BACKGROUND: We previously operationally-defined subtle cognitive decline (SCD) in preclinical Alzheimer's disease (AD) using total scores on neuropsychological (NP) tests. NP process scores (i.e., provide information about how a total NP score was achieved) may be a useful tool for identifying early cognitive inefficiencies prior to objective impairment seen in mild cognitive impairment (MCI) and dementia. OBJECTIVE: We aimed to integrate process scores into the SCD definition to identify stages of SCD and improve early detection of those at risk for decline. METHODS: Cognitively "normal" participants from the Alzheimer's Disease Neuroimaging Initiative were classified as "early" SCD (E-SCD; >1 SD below norm-adjusted mean on 2 process scores or on 1 process score plus 1 NP total score), "late" SCD (L-SCD; existing SCD criteria of >1 SD below norm-adjusted mean on 2 NP total scores in different domains), or "no SCD" (NC). Process scores considered in the SCD criteria were word-list intrusion errors, retroactive interference, and learning slope. Cerebrospinal fluid AD biomarkers were used to examine pathologic burden across groups. RESULTS: E-SCD and L-SCD progressed to MCI 2.5-3.4 times faster than the NC group. Survival curves for E-SCD and L-SCD converged at 7-8 years after baseline. The combined (E-SCD+L-SCD) group had improved sensitivity to detect progression to MCI relative to L-SCD only. AD biomarker positivity increased across NC, SCD, and MCI groups. CONCLUSIONS: Process scores can be integrated into the SCD criteria to allow for increased sensitivity and earlier identification of cognitively normal older adults at risk for decline prior to frank impairment on NP total scores.

Utility of Amyloid and FDG-PET in Clinical Practice: Differences Between Secondary and Tertiary Care Memory Units. - Lage, Carmen; Suarez, Andrea Gonzalez; Pozueta, Ana; Riancho, Javier; Kazimierczak, Martha; Bravo, María; Jimenez Bonilla, Julio; de Arcocha Torres, Marıa; Quirce, Remedios; Banzo, Ignacio; Vázquez-Higuera, José Luis; Rabinovici, Gil D; et al. (J Alzheimers Dis, 2018)
The clinical utility of amyloid positron emission tomography (PET) has not been fully established. Our aim was to evaluate the effect of amyloid imaging on clinical decision making in a secondary care unit and compare our results with a previous study in a tertiary center following the same methods. We reviewed retrospectively 151 cognitively impaired patients who underwent amyloid (Pittsburgh compound B [PiB]) PET and were evaluated clinically before and after the scan in a secondary care unit. One hundred and fifty concurrently underwent fluorodeoxyglucose (FDG)-PET. We assessed changes between the pre- and post-PET clinical diagnosis and Alzheimer's disease treatment plan. The association between PiB/FDG results and changes in management was evaluated using χ2 and multivariate logistic regression. Concordance between classification based on scan readings and baseline diagnosis was 66% for PiB and 47% for FDG. The primary diagnosis changed after PET in 17.2% of cases. When examined independently, discordant PiB and discordant FDG were both associated with diagnostic change (p < 0.0001). However, when examined together in a multivariate logistic regression, only discordant PiB remained significant (p = 0.0002). Changes in treatment were associated with concordant PiB (p = 0.009) while FDG had no effect on treatment decisions. Based on our regression model, patients with diagnostic dilemmas, a suspected non-amyloid syndrome, and Clinical Dementia Rating <1 were more likely to benefit from amyloid PET due to a higher likelihood of diagnostic change. We found that changes in diagnosis after PET in our secondary center almost doubled those of our previous analysis of a tertiary unit (9% versus 17.2%). Our results offer some clues about the rational use of amyloid PET in a secondary care memory unit stressing its utility in mild cognitive impairment patients.

Voxel-Based Acetylcholinesterase PET Study in Early and Late Onset Alzheimer's Disease. - Hirano, Shigeki; Shinotoh, Hitoshi; Shimada, Hitoshi; Ota, Tsuneyoshi; Sato, Koichi; Tanaka, Noriko; Zhang, Ming-Rong; Higuchi, Makoto; Fukushi, Kiyoshi; Irie, Toshiaki; Kuwabara, Satoshi; Suhara, Tetsuya (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by chronic progressive cognitive decline and displays underlying brain cholinergic dysfunction, providing a rationale for treatment with cholinomimetic medication. The clinical presentations and courses of AD patients may differ by age of onset. OBJECTIVE: The objective of the present study was to illustrate the regional differences of brain acetylcholinesterase (AChE) activity as quantified by N-[11C]methylpiperidinyl-4-acetate ([11C]MP4A) and PET using parametric whole brain analysis and clarify those differences as a function of age. METHODS: 22 early onset AD (EOAD) with age at onset under 65, the remaining 26 as late onset AD (LOAD), and 16 healthy controls (HC) were enrolled. Voxel-based AChE activity estimation of [11C]MP4A PET images was conducted by arterial input and unconstrained nonlinear least-squares method with subsequent parametrical analyses. Statistical threshold was set as Family Wise Error corrected, p-value <0.05 on cluster-level and cluster extent over 30 voxels. RESULTS: Voxel-based group comparison showed that, compared to HC, both EOAD and LOAD showed cortical AChE decrement in parietal, temporal, and occipital cortices, with wider and stringent cortical involvement in the EOAD group, most prominently demonstrated in the temporal region. There was no significant correlation between age and regional cerebral AChE activity except for a small left superior temporal region in the AD group (Brodmann's area 22, Zmax = 5.13, 396 voxels), whereas no significant cluster was found in the HC counterpart. CONCLUSION: Difference in cortical cholinergic dysfunction between EOAD and LOAD may shed some light on the cholinomimetic drug efficacy in AD.

Which Risk Factors Causally Influence Dementia? A Systematic Review of Mendelian Randomization Studies. - Kuźma, Elżbieta; Hannon, Eilis; Zhou, Ang; Lourida, Ilianna; Bethel, Alison; Levine, Deborah A; Lunnon, Katie; Thompson-Coon, Jo; Hyppönen, Elina; Llewellyn, David J (J Alzheimers Dis, 2018)
BACKGROUND: Numerous risk factors for dementia are well established, though the causal nature of these associations remains unclear. OBJECTIVE: To systematically review Mendelian randomization (MR) studies investigating causal relationships between risk factors and global cognitive function or dementia. METHODS: We searched five databases from inception to February 2017 and conducted citation searches including MR studies investigating the association between any risk factor and global cognitive function, all-cause dementia or dementia subtypes. Two reviewers independently assessed titles and abstracts, full-texts, and study quality. RESULTS: We included 18 MR studies investigating education, lifestyle factors, cardiovascular factors and related biomarkers, diabetes related and other endocrine factors, and telomere length. Studies were of predominantly good quality, however eight received low ratings for sample size and statistical power. The most convincing causal evidence was found for an association of shorter telomeres with increased risk of Alzheimer's disease (AD). Causal evidence was weaker for smoking quantity, vitamin D, homocysteine, systolic blood pressure, fasting glucose, insulin sensitivity, and high-density lipoprotein cholesterol. Well-replicated associations were not present for most exposures and we cannot fully discount survival and diagnostic bias, or the potential for pleiotropic effects. CONCLUSIONS: Genetic evidence supported a causal association between telomere length and AD, whereas limited evidence for other risk factors was largely inconclusive with tentative evidence for smoking quantity, vitamin D, homocysteine, and selected metabolic markers. The lack of stronger evidence for other risk factors may reflect insufficient statistical power. Larger well-designed MR studies would therefore help establish the causal status of these dementia risk factors.

Word and Picture Version of the Free and Cued Selective Reminding Test (FCSRT): Is There Any Difference? - Arighi, Andrea; Carandini, Tiziana; Mercurio, Matteo; Carpani, Giovanni; Pietroboni, Anna Margherita; Fumagalli, Giorgio; Ghezzi, Laura; Basilico, Paola; Calvi, Alberto; Scarioni, Marta; De Riz, Milena; Fenoglio, Chiara; et al. (J Alzheimers Dis, 2018)
The Free and Cued Selective Reminding Test (FCSRT) is the most commonly used neuropsychological test to evaluate episodic memory. Two variants of FCSRT exist, using the recall of words (FCSRT-w) or pictures (FCSRT-p). Fourteen patients with mild cognitive impairment underwent neuropsychological evaluation and brain magnetic resonance. We found differences in FCSRT-w and FCSRT-p variants scores. FCSRT-p was correlated with atrophy in areas involved in visual stimuli processing while FCSRT-w was correlated to hippocampal atrophy. Our study suggests that FCSRT-w and FCSRT-p scores are not equivalent, but a larger cohort of patients is needed to validate these results.
Keywords: Aged; Aged, 80 and over; Association Learning; Cognitive Dysfunction; Cues; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation; Vocabulary

A 24-Week Multi-Modality Exercise Program Improves Executive Control in Older Adults with a Self-Reported Cognitive Complaint: Evidence from the Antisaccade Task. - Heath, Matthew; Shellington, Erin; Titheridge, Sam; Gill, Dawn P; Petrella, Robert J (J Alzheimers Dis, 2017)
Exercise programs involving aerobic and resistance training (i.e., multiple-modality) have shown promise in improving cognition and executive control in older adults at risk, or experiencing, cognitive decline. It is, however, unclear whether cognitive training within a multiple-modality program elicits an additive benefit to executive/cognitive processes. This is an important question to resolve in order to identify optimal training programs that delay, or ameliorate, executive deficits in persons at risk for further cognitive decline. In the present study, individuals with a self-reported cognitive complaint (SCC) participated in a 24-week multiple-modality (i.e., the M2 group) exercise intervention program. In addition, a separate group of individuals with a SCC completed the same aerobic and resistance training as the M2 group but also completed a cognitive-based stepping task (i.e., multiple-modality, mind-motor intervention: M4 group). Notably, pre- and post-intervention executive control was examined via the antisaccade task (i.e., eye movement mirror-symmetrical to a target). Antisaccades are an ideal tool for the study of individuals with subtle executive deficits because of its hands- and language-free nature and because the task's neural mechanisms are linked to neuropathology in cognitive decline (i.e., prefrontal cortex). Results showed that M2 and M4 group antisaccade reaction times reliably decreased from pre- to post-intervention and the magnitude of the decrease was consistent across groups. Thus, multi-modality exercise training improved executive performance in persons with a SCC independent of mind-motor training. Accordingly, we propose that multiple-modality training provides a sufficient intervention to improve executive control in persons with a SCC.

A 3-Month Aerobic Training Program Improves Brain Energy Metabolism in Mild Alzheimer's Disease: Preliminary Results from a Neuroimaging Study. - Castellano, Christian-Alexandre; Paquet, Nancy; Dionne, Isabelle J; Imbeault, Hélène; Langlois, Francis; Croteau, Etienne; Tremblay, Sébastien; Fortier, Mélanie; Matte, J Jacques; Lacombe, Guy; Fülöp, Tamás; Bocti, Christian; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Aerobic training has some benefits for delaying the onset or progression of Alzheimer's disease (AD). Little is known about the implication of the brain's two main fuels, glucose and ketones (acetoacetate), associated with thesebenefits. OBJECTIVE: To determine whether aerobic exercise training modifies brain energy metabolism in mild AD. METHODS: In this uncontrolled study, ten patients with mild AD participated in a 3-month, individualized, moderate-intensity aerobic training on a treadmill (Walking). Quantitative measurement of brain uptake of glucose (CMRglu) and acetoacetate (CMRacac) using neuroimaging and cognitive testing were done before and after the Walking program. RESULTS: Four men and six women with an average global cognitive score (MMSE) of 26/30 and an average age of 73 y completed the Walking program. Average total distance and treadmill speed were 8 km/week and 4 km/h, respectively. Compared to the Baseline, after Walking, CMRacac was three-fold higher (0.6±0.4 versus 0.2±0.1 μmol/100 g/min; p = 0.01). Plasma acetoacetate concentration and the blood-to-brain acetoacetate influx rate constant were also increased by 2-3-fold (all p≤0.03). CMRglu was unchanged after Walking (28.0±0.1 μmol/100 g/min; p = 0.96). There was a tendency toward improvement in the Stroop-color naming test (-10% completion time, p = 0.06). Performance on the Trail Making A&B tests was also directly related to plasma acetoacetate and CMRacac (all p≤0.01). CONCLUSION: In mild AD, aerobic training improved brain energy metabolism by increasing ketone uptake and utilization while maintaining brain glucose uptake, and could potentially be associated with some cognitive improvement.

ABCA1 Deficiency Affects Basal Cognitive Deficits and Dendritic Density in Mice. - Fitz, Nicholas F; Carter, Alexis Y; Tapias, Victor; Castranio, Emilie L; Kodali, Ravindra; Lefterov, Iliya; Koldamova, Radosveta (J Alzheimers Dis, 2017)
ATP-binding cassette transporter A1 (ABCA1) mediates cholesterol efflux to lipid-free apolipoproteins and regulates the generation of high density lipoproteins. Previously, we have shown that lack of Abca1 significantly increases amyloid deposition and cognitive deficits in Alzheimer's disease model mice expressing human amyloid-β protein precursor (APP). The goal of this study was to determine if ABCA1 plays a role in memory deficits caused by amyloid-β (Aβ) oligomers and examine neurite architecture of pyramidal hippocampal neurons. Our results confirm previous findings that Abca1 deficiency significantly impairs spatial memory acquisition and retention in the Morris water maze and long-term memory in novel object recognition of APP transgenic mice at a stage of early amyloid pathology. Neither test demonstrated a significant difference between Abca1ko and wild-type (WT) mice. We also examined the effect of intra-hippocampal infused Aβ oligomers on cognitive performance of Abca1ko mice, compared to control infusion of scrambled Aβ peptide. Age-matched WT mice undergoing the same infusions were also used as controls. In this model system, we found a statistically significant difference between WT and Abca1ko mice infused with scrambled Aβ, suggesting that Abca1ko mice are vulnerable to the effect of mild stresses. Moreover, examination of neurite architecture in the hippocampi revealed a significant decrease in neurite length, number of neurite segments, and branches in Abca1ko mice when compared to WT mice. We conclude that mice lacking ABCA1 have basal cognitive deficits that prevent them from coping with additional stressors, which is in part due to impairment of neurite morphology in the hippocampus.

Aberrant Co-localization of Synaptic Proteins Promoted by Alzheimer's Disease Amyloid-β Peptides: Protective Effect of Human Serum Albumin. - Domínguez-Prieto, Marta; Velasco, Ana; Vega, Lourdes; Tabernero, Arantxa; Medina, José M (J Alzheimers Dis, 2017)
Amyloid-β (Aβ), Aβ40, Aβ42, and, recently, Aβ25-35 have been directly implicated in the pathogenesis of Alzheimer's disease. We have studied the effects of Aβ on neuronal death, reactive oxygen species (ROS) production, and synaptic assembling in neurons in primary culture. Aβ25-35, Aβ40, and Aβ42 significantly decreased neuronal viability, although Aβ25-35 showed a higher effect. Aβ25-35 showed a more penetrating ability to reach mitochondria while Aβ40 did not enter the neuronal cytosol and Aβ42 was scarcely internalized. We did not observe a direct correlation between ROS production and cell death because both Aβ40 and Aβ42 decreased neuronal viability but Aβ40 did not change ROS production. Rather, ROS production seems to correlate with the penetrating ability of each Aβ. No significant differences were found between Aβ40 and Aβ42 regarding the extent of the deleterious effects of both peptides on neuronal viability or synaptophysin expression. However, Aβ40 elicited a clear delocalization of PSD-95 and synaptotagmin from prospective synapsis to the neuronal soma, suggesting the occurrence of a crucial effect of Aβ40 on synaptic disassembling. The formation of Aβ40- or Aβ42-serum albumin complexes avoided the effects of these peptides on neuronal viability, synaptophysin expression, and PSD-95/synaptotagmin disarrangement suggesting that sequestration of Aβ by albumin prevents deleterious effects of these peptides. We can conclude that Aβ borne by albumin can be safely transported through body fluids, a fact that may be compulsory for Aβ disposal by peripheral tissues.

Abnormalities of Cortical Neural Synchronization Mechanisms in Subjects with Mild Cognitive Impairment due to Alzheimer's and Parkinson's Diseases: An EEG Study. - Babiloni, Claudio; Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Cordone, Susanna; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Nobili, Flavio; Arnaldi, Dario; Famá, Francesco; et al. (J Alzheimers Dis, 2017)
The aim of this retrospective and exploratory study was that the cortical sources of resting state eyes-closed electroencephalographic (rsEEG) rhythms might reveal different abnormalities in cortical neural synchronization in groups of patients with mild cognitive impairment due to Alzheimer's disease (ADMCI) and Parkinson's disease (PDMCI) as compared to healthy subjects. Clinical and rsEEG data of 75 ADMCI, 75 PDMCI, and 75 cognitively normal elderly (Nold) subjects were available in an international archive. Age, gender, and education were carefully matched in the three groups. The Mini-Mental State Evaluation (MMSE) was matched between the ADMCI and PDMCI groups. Individual alpha frequency peak (IAF) was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were also considered. eLORETA estimated the rsEEG cortical sources. Receiver operating characteristic curve (ROC) classified these sources across individuals. Results showed that compared to the Nold group, the posterior alpha2 and alpha3 source activities were more abnormal in the ADMCI than the PDMCI group, while the parietal delta source activities were more abnormal in the PDMCI than the ADMCI group. The parietal delta and alpha sources correlated with MMSE score and correctly classified the Nold and diseased individuals (area under the ROC = 0.77-0.79). In conclusion, the PDMCI and ADMCI patients showed different features of cortical neural synchronization at delta and alpha frequencies underpinning brain arousal and vigilance in the quiet wakefulness. Future prospective cross-validation studies will have to test these rsEEG markers for clinical applications and drug discovery.

Adherence to Clinical Practice Guidelines during Dementia Work-Up in a Real-World Setting: A Study from the Registry of Dementias of Girona. - Turró-Garriga, Oriol; Calvó-Perxas, Laia; Vilalta-Franch, Joan; Hernández-Ferrándiz, Marta; Flaqué, Margarita; Linares, Marta; Cullell, Marta; Gich, Jordi; Casas, Isabel; Perkal, Héctor; Garre-Olmo, Josep (J Alzheimers Dis, 2017)
BACKGROUND: There are several position statements and clinical practice guidelines (CPG) for diagnosing dementia. OBJECTIVE: Our aims were to evaluate the adherence to CPG among specialists in the 7 memory clinics included in the Registry of Dementias of Girona (ReDeGi), and to compare the results between 2007-2011 and 2012-2015. We also determined the time and number of visits required to achieve a diagnosis, the supplementary tests ordered, and the drugs prescribed according to dementia subtypes. METHODS: Medical charts of a stratified random sample of 475 ReDeGi cases were reviewed. Basic dementia work-up was evaluated using as a reference evidence-based CPG. An Index of Adherence (AI) was calculated using the following items in the medical chart: cognitive symptomatology; functional disability evaluation; physical examination; neurological examination; psychiatric examination; brief cognitive examination; activities of daily living performance examination; blood test; structural neuroimaging (CT-scan or MRI). RESULTS: The mean AI to CPG among specialists was of 8.2 points, and it improved from 7.9 points in 2007-2011 to 8.5 points in 2012-2015 (Cohen's d = 0.46). A lower adherence was detected in the most severe cases. A dementia diagnosis required 3.5 visits, regardless of the subtype of dementia, although milder cases required more time, more visits, and more supplementary tests than severe cases. CONCLUSION: The adherence to CPG in the catchment area of the ReDeGi is high, and an epidemiological surveillance system such as the ReDeGi may help in improving it. Dementia guidelines should establish procedures adapted to clinical practice, with simplified recommendations for most severe cases.

Adult-Onset Epilepsy in Presymptomatic Alzheimer's Disease: A Retrospective Study. - DiFrancesco, Jacopo C; Tremolizzo, Lucio; Polonia, Valeria; Giussani, Giorgia; Bianchi, Elisa; Franchi, Carlotta; Nobili, Alessandro; Appollonio, Ildebrando; Beghi, Ettore; Ferrarese, Carlo (J Alzheimers Dis, 2017)
BACKGROUND: The prevalence of epilepsy with onset in adulthood increases with age, mainly due to the accumulation of brain damage. However, a significant proportion of patients experience seizures of unknown cause. Alzheimer's disease (AD) is associated with an increased risk of seizures. Seizure activity is interpreted as a secondary event related to hyperexcitability caused by amyloid-β aggregation. OBJECTIVE: Since neurodegenerative processes begin several years before clinical symptoms, epilepsy could be more frequent in the presymptomatic stages of dementia. METHODS: We retrospectively reviewed the prevalence of epilepsy of unknown origin with adult onset before cognitive decline in a large cohort of AD patients (EPS-AD) recruited based on clinical and neuropsychological data. Data of patients with epilepsy followed by AD were compared with two control groups: patients with AD without seizures (no EPS-AD) and a large reference population (RP). RESULTS: In AD patients, the prevalence of epilepsy of unknown origin, with onset in the adulthood before cognitive decline is 17.1 times higher compared with the RP (95% CI: 10.3-28.3). In EPS-AD, seizures begin on average 4.6 years (median 2.0) before the onset of cognitive symptoms and cognitive decline starts 3.6 years earlier compared with noEPS-AD. CONCLUSIONS: Neurodegenerative processes of dementia could play a key role in the pathogenesis of epilepsy in a subgroup of individuals intended to develop cognitive decline. Adult-onset epilepsy of undefined cause could thus represent a risk factor for the ongoing neurodegenerative damage, even preceding by years the onset of clinical symptoms of dementia.

Alterations of Clock Gene RNA Expression in Brain Regions of a Triple Transgenic Model of Alzheimer's Disease. - Bellanti, Francesco; Iannelli, Giuseppina; Blonda, Maria; Tamborra, Rosanna; Villani, Rosanna; Romano, Adele; Calcagnini, Silvio; Mazzoccoli, Gianluigi; Vinciguerra, Manlio; Gaetani, Silvana; Giudetti, Anna Maria; Vendemiale, Gianluigi; et al. (J Alzheimers Dis, 2017)
A disruption to circadian rhythmicity and the sleep/wake cycle constitutes a major feature of Alzheimer's disease (AD). The maintenance of circadian rhythmicity is regulated by endogenous clock genes and a number of external Zeitgebers, including light. This study investigated the light induced changes in the expression of clock genes in a triple transgenic model of AD (3×Tg-AD) and their wild type littermates (Non-Tg). Changes in gene expression were evaluated in four brain areas¾suprachiasmatic nucleus (SCN), hippocampus, frontal cortex and brainstem¾of 6- and 18-month-old Non-Tg and 3×Tg-AD mice after 12 h exposure to light or darkness. Light exposure exerted significant effects on clock gene expression in the SCN, the site of the major circadian pacemaker. These patterns of expression were disrupted in 3×Tg-AD and in 18-month-old compared with 6-month-old Non-Tg mice. In other brain areas, age rather than genotype affected gene expression; the effect of genotype was observed on hippocampal Sirt1 expression, while it modified the expression of genes regulating the negative feedback loop as well as Rorα, Csnk1ɛ and Sirt1 in the brainstem. In conclusion, during the early development of AD, there is a disruption to the normal expression of genes regulating circadian function after exposure to light, particularly in the SCN but also in extra-hypothalamic brain areas supporting circadian regulation, suggesting a severe impairment of functioning of the clock gene pathway. Even though this study did not demonstrate a direct association between these alterations in clock gene expression among brain areas with the cognitive impairments and chrono-disruption that characterize the early onset of AD, our novel results encourage further investigation aimed at testing this hypothesis.

Alzheimer's Disease Biomarkers Interactively Influence Physical Activity, Mobility, and Cognition Associations in a Non-Demented Aging Population. - Thibeau, Sherilyn; McFall, G Peggy; Camicioli, Richard; Dixon, Roger A (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) risk-reduction strategies (e.g., increasing physical activity, improving mobility) have garnered increasing attention in the literature. However, the effect of such modifiable factors on the preclinical trajectories of brain and cognitive health may be moderated by non-modifiable biomarkers associated with AD. OBJECTIVE: In a longitudinal sample of non-demented older adults, we examine the independent predictors everyday physical activity (EPA) and mobility on executive function (EF) performance and change. Next, we test whether these predictions are modified by interactions between age and AD genetic risk. METHODS: This accelerated longitudinal design included adults (n = 532, M age = 70.4, age range 53-95) from the Victoria Longitudinal Study. We tested the independent effects of EPA and Mobility (i.e., gait, balance), moderation by Apolipoprotein E (i.e., APOEɛ4+, ɛ4-) and age (young-old, middle-old, old-old), and interactions between APOE and age on performance and 9-year change in an EF latent variable. RESULTS: First, higher levels of both EPA and Mobility were associated with better EF performance and less decline. Second, the interaction between age and APOE showed that low EPA and older age was associated with poorer EF performance and steeper EF decline for APOEɛ4 + carriers, and low mobility was associated with poorer EF performance and steeper EF decline for APOEɛ4 + carriers than the non-risk carriers. CONCLUSION: In non-demented older adults, age moderated the effects of both EPA and Mobility on EF performance and change. However, this moderation occurs differentially across APOE4 status.

Alzheimer's Disease Diagnosis Relies on a Twofold Clinical-Biological Algorithm: Three Memory Clinic Case Reports. - Levy Nogueira, Marcel; Samri, Dalila; Epelbaum, Stéphane; Lista, Simone; Suppa, Per; Spies, Lothar; Hampel, Harald; Dubois, Bruno; Teichmann, Marc (J Alzheimers Dis, 2017)
The International Working Group recently provided revised criteria of Alzheimer's disease (AD) proposing that the diagnosis of typical amnesic AD should be established by a clinical-biological signature, defined by the phenotype of an "amnesic syndrome of the hippocampal type" (ASHT) combined with positive in vivo evidence of AD pathophysiology in the cerebrospinal fluid (CSF) or on amyloid PET imaging. The application and clinical value of this refined diagnostic algorithm, initially intended for research purposes, is explored in three memory clinic cases presenting with different cognitive profiles including an ASHT, hippocampal atrophy, and CSF AD-biomarker data. The case reports highlight that the isolated occurrence of one of the two proposed AD criteria, ASHT or positive pathophysiological markers, does not provide a reliable diagnosis of typical AD. It is proposed that the twofold diagnostic IWG algorithm can be applied and operationalized in memory clinic settings to improve the diagnostic accuracy of typical amnesic AD in clinical practice.

Alzheimer's Disease-Associated Cerebrospinal Fluid (CSF) Biomarkers do not Correlate with CSF Volumes or CSF Production Rate. - Edsbagge, Mikael; Andreasson, Ulf; Ambarki, Khalid; Wikkelsø, Carsten; Eklund, Anders; Blennow, Kaj; Zetterberg, Henrik; Tullberg, Mats (J Alzheimers Dis, 2017)
BACKGROUND: Neuropathologically, Alzheimer's disease (AD) is characterized by accumulation of a 42 amino acid peptide called amyloid-β (Aβ42) in extracellular senile plaques together with intraneuronal inclusions of hyperphosphorylated tau protein in neurofibrillary tangles and neuronal degeneration. These changes are reflected in the cerebrospinal fluid (CSF), the volumes and production rates of which vary considerably between individuals, by reduced concentration of Aβ42, increased concentration of phosphorylated tau (P-tau) protein, and increased concentration of total tau (T-tau) protein, respectively. OBJECTIVE: To examine the outstanding question if CSF concentrations of AD associated biomarkers are influenced by variations in CSF volumes, CSF production rate, and intracranial pressure in healthy individuals. METHODS: CSF concentrations of Aβ42, P-tau, and T-tau, as well as a number of other AD-related CSF biomarkers were analyzed together with intracranial subarachnoid, ventricular, and spinal CSF volumes, as assessed by magnetic resonance imaging volumetric measurements, and CSF production rate in 19 cognitively normal healthy subjects (mean age 70.6, SD 3.6 years). RESULTS: Negative correlations were seen between the concentrations of three CSF biomarkers (albumin ratio, Aβ38, and Aβ40), and ventricular CSF volume, but apart from this finding, no significant correlations were observed. CONCLUSION: These results speak against inter-individual variations in CSF volume and production rate as important confounds in the AD biomarker research field.

Amyloid Burden in Obstructive Sleep Apnea. - Yun, Chang-Ho; Lee, Ho-Young; Lee, Seung Ku; Kim, Hyun; Seo, Hyung Suk; Bang, Seong Ae; Kim, Sang Eun; Greve, Douglas N; Au, Rhoda; Shin, Chol; Thomas, Robert J (J Alzheimers Dis, 2017)
To test the hypothesis that excessive amyloid deposition is a biological link between obstructive sleep apnea (OSA) and Alzheimer's disease, we determined whether OSA increases cerebral amyloid burden, relative to controls, using Pittsburgh Compound B (PiB) PET imaging. The subjects were adult participants (age 50-65 years) from the Korean Genome and Epidemiology Study. Polysomnography, brain MRI including 3D images, and a detailed neuro-cognitive function test battery were done in 2011-2012. Nineteen OSA subjects (Apnea-Hypopnea Index [AHI] ≥15/h, 21.2±5.1/h; age 58.5±4.1 years; 9 male) and 19 controls (AHI 1.8±1.3/h; age 58.5±4.2 years; 9 male) underwent 60-min dynamic 11C-PiB PET. All subjects were right-handed with normal cognitive function and brain MRI. Controls were matched by age, gender, education, and APOE genotype. A voxel-wise comparison of PiB-PET images between the two groups was performed after spatial and count normalization with cerebellar gray matter as a reference. Covariates included the status of sleep duration, hypertension, diabetes, body mass index, exercise, depressive mood, smoking, and alcohol drinking. Cortical thickness on 3D MRI was also measured and compared between the two groups. The OSA group showed a higher PiB deposition in the right posterior cingulate gyrus and right temporal cortex (corrected p < 0.05). There was no area of higher uptake in the control compared with OSA. Regional differences in cortical thickness were not significant. The study suggests that OSA accelerates amyloid deposition and may contribute to the development or progression of Alzheimer's disease.

Amyloid Plaques Show Binding Capacity of Exogenous Injected Amyloid-β. - Gureviciene, Irina; Gurevicius, Kestutis; Mugantseva, Ekaterina; Kislin, Mikhail; Khiroug, Leonard; Tanila, Heikki (J Alzheimers Dis, 2017)
Amyloid plaques, although inducing damage to the immediately surrounding neuropil, have been proposed to provide a relatively innocuous way to deposit toxic soluble amyloid-β (Aβ) species. Here we address this hypothesis by exploring spread and absorption of fluorescent Aβ to pre-existing amyloid plaques after local application in wild-type mice versus APP/PS1 transgenic mice with amyloid plaques. Local intracortical or intracerebroventricular injection of fluorescently-labeled Aβ in APP/PS1 mice with a high plaque density resulted in preferential accumulation of the peptide in amyloid plaques in both conventional postmortem histology and in live imaging using two-photon microscopy. These findings support the contention that amyloid plaques may act as buffers to protect neurons from the toxic effects of momentary high concentrations of soluble Aβ oligomers.

Anticholinergic Exposure and Risk of Pneumonia in Persons with Alzheimer's Disease: A Nested Case-Control Study. - Lampela, Pasi; Tolppanen, Anna-Maija; Tanskanen, Antti; Tiihonen, Jari; Hartikainen, Sirpa; Taipale, Heidi (J Alzheimers Dis, 2017)
BACKGROUND: Risk of pneumonia is increased in persons with Alzheimer's disease (AD). In some studies, anticholinergic drugs (AC) have been associated with an increased pneumonia risk. OBJECTIVE: We analyzed the risk of pneumonia associated with ACs in persons with AD. METHODS: We performed a nested case-control study using register-based data from a Finnish nationwide MEDALZ cohort including all community-dwelling persons diagnosed with AD during 2005-2011. Cases were identified based on pneumonia diagnoses (n = 12,442) from hospital discharge and causes of death registers. Up to two controls without pneumonia were matched based on time since AD diagnoses, age, and gender for each case; AC use was measured using Anticholinergic Drug Scale. RESULTS: Use of AC was associated with an increased risk of pneumonia (adjusted odds ratio (OR) 1.36, 95% confidence interval (CI) 1.29-1.43). However, there was no increased pneumonia risk in persons using level 3 ACs. Incident use was associated with higher risk of pneumonia (OR 2.68, 95% CI 2.15-3.34) than prevalent use (OR 1.48, 95% CI 1.40-1.57). Among persons using cholinesterase inhibitors (AChEIs), risk of pneumonia was increased in persons using also ACs (OR 1.53, 95% CI 1.41-1.66). CONCLUSION: ACs were associated with an increased risk of pneumonia in persons with AD, especially at the time of initiation of these drugs. AC use was associated with increased pneumonia risk also in persons using AChEIs. This risk should be carefully considered when treating AD patients.

Antihypertensive Treatment is associated with MRI-Derived Markers of Neurodegeneration and Impaired Cognition: A Propensity-Weighted Cohort Study. - Edwards, Jodi D; Ramirez, Joel; Callahan, Brandy L; Tobe, Sheldon W; Oh, Paul; Berezuk, Courtney; Lanctôt, Krista; Swardfager, Walter; Nestor, Sean; Kiss, Alexander; Strother, Stephen; Black, Sandra E (J Alzheimers Dis, 2017)
BACKGROUND: Hypertension is an important risk factor for Alzheimer's disease (AD) and cerebral small vessel disease. Angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are common anti-hypertensive treatments, but have differential effects on cortical amyloid. OBJECTIVE: The objective of this study was to evaluate associations between anti-hypertensive treatment, brain volume, and cognition, using a propensity-weighted analysis to account for confounding by indication. METHODS: We identified a cohort of normal elderly adults and individuals with mild cognitive impairment (MCI) or AD (N = 886; mean age = 75.0) from the Alzheimer's Disease Neuroimaging Initiative. Primary outcomes were brain parenchymal fraction, total hippocampal volume, and white matter hyperintensity (WMH) volume. Secondary outcomes were standardized scores on neuropsychological tests. Propensity-weighted adjusted multivariate linear regression was used to estimate associations between anti-hypertensive treatment class and MRI volumes and cognition. RESULTS: Individuals treated with ARBs showed larger hippocampal volumes (R2 = 0.83, p = 0.05) and brain parenchymal fraction (R2 = 0.83, p = 0.01) than those treated with ACEIs. When stratified by diagnosis, this effect remained only in normal elderly adults and MCI patients, and a significant association between ARBs and lower WMH volume (R2 = 0.83, p = 0.03) emerged for AD patients only. ARBs were also associated with significantly better performance on tests of episodic and verbal memory, language, and executive function (all p < 0.05). CONCLUSIONS: Findings are consistent with evidence for a neuroprotective effect of treatment with ARBs for brain structure and cognition. This study has potential implications for the treatment of hypertension, particularly in elderly adults at risk of cognitive decline and AD.

Apolipoprotein A1 in Cerebrospinal Fluid and Plasma and Progression to Alzheimer's Disease in Non-Demented Elderly. - Slot, Rosalinde E R; Van Harten, Argonde C; Kester, Maartje I; Jongbloed, Wesley; Bouwman, Femke H; Teunissen, Charlotte E; Scheltens, Philip; Veerhuis, Robert; van der Flier, Wiesje M (J Alzheimers Dis, 2017)
BACKGROUND: HDL-cholesterol transporter Apolipoprotein A1 (ApoA1) holds neuroprotective properties, such as inhibition of amyloid-β aggregation. Low plasma ApoA1 concentrations are associated with Alzheimer's disease (AD). Little is known about ApoA1 levels in the pre-dementia stages of AD. OBJECTIVE: To investigate associations between cerebrospinal fluid (CSF) and plasma ApoA1 levels and clinical progression toward AD in non-demented elderly. METHODS: From the Amsterdam Dementia Cohort, we included 429 non-demented elderly with subjective cognitive decline (SCD; n = 206, 61±9 years, Mini-Mental State Exam (MMSE) 28±2) and mild cognitive impairment (MCI; n = 223, 67±8 years, MMSE 27±2), with a mean follow-up of 2.5±1.6 years. We used Cox proportional hazard models to investigate relations between CSF and plasma ApoA1 concentrations and clinical progression, defined as progression to MCI or AD for SCD, and progression to AD for MCI. Analyses were adjusted for age, gender, MMSE, and plasma cholesterol levels. Analyses were stratified for diagnosis and APOEɛ4 carriership. RESULTS: 117 patients (27%) showed clinical progression. One standard deviation increase of CSF ApoA1 was associated with a 30% increased risk of clinical progression (hazard ratio (HR) (95% CI)  = 1.3(1.0-1.6)). The effect appeared to be attributable to the APOEɛ4 carriers with SCD (HR 3.3(1.0-10.9)). Lower plasma ApoA1 levels were associated with an increased risk of clinical progression in APOEɛ4 carriers with SCD (HR 5.0(1.3-18.9)). CONCLUSION: Higher CSF and lower plasma ApoA1 levels were associated with an increased risk of clinical progression in APOEɛ4 carriers with SCD; suggesting that ApoA1 may be involved in the earliest stages of AD.

APP Mutations in Cerebral Amyloid Angiopathy with or without Cortical Calcifications: Report of Three Families and a Literature Review. - Sellal, François; Wallon, David; Martinez-Almoyna, Laurent; Marelli, Cecilia; Dhar, Abhinav; Oesterlé, Héléne; Rovelet-Lecrux, Anne; Rousseau, Stéphane; Kourkoulis, Christina E; Rosand, Jon; DiPucchio, Zora Y; Frosch, Matthew; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Specific APP mutations cause cerebral amyloid angiopathy (CAA) with or without Alzheimer's disease (AD). OBJECTIVE: We aimed at reporting APP mutations associated with CAA, describe the clinical, cerebrospinal fluid AD biomarkers, and neuroimaging features, and compare them with the data from the literature. METHODS: We performed a retrospective study in two French genetics laboratories by gathering all clinical and neuroimaging data from patients referred for a genetic diagnosis of CAA with an age of onset before 66 years and fulfilling the other Boston revised criteria. We studied the segregation of mutations in families and performed a comprehensive literature review of all cases reported with the same APP mutation. RESULTS: We screened APP in 61 unrelated French patients. Three mutations, located in the Aβ coding region, were detected in five patients from three families: p.Ala692Gly (Flemish), p.Glu693Lys (Italian), and p.Asp694Asn (Iowa). Patients exhibited CAA and progressive cognitive impairment associated with cortical calcifications in the Iowa and Italian mutation carriers, but not the patient carrying the Flemish mutation. CONCLUSIONS: This is the first evidence of cortical calcification in patients with an APP mutation other than the Iowa mutation. We discuss the radiological, cerebrospinal fluid, and clinical phenotype of patients carrying these mutations in the literature.

AQP4 Association with Amyloid Deposition and Astrocyte Pathology in the Tg-ArcSwe Mouse Model of Alzheimer's Disease. - Yang, Jing; Zhang, Rui; Shi, Changhe; Mao, Chengyuan; Yang, Zhihua; Suo, Zhenhe; Torp, Reidun; Xu, Yuming (J Alzheimers Dis, 2017)
Amyloid-β deposition in senile plaques is one of the main pathological changes in Alzheimer's disease (AD). We previously reported that aquaporin-4 (AQP4) is redistributed within the astrocytes in cerebral amyloid angiopathy in the tg-ArcSwe mouse model of AD, suggesting that AQP4 may participate in amyloid-β deposition. However, the role of AQP4 in plaque formation is not currently clear. The objective of the current study was to explore the AQP4 distribution within plaques in the tg-ArcSwe mice in more depth by the combined application of immunofluorescence cytochemistry and immunogold electron microscopy. In addition, the astrocyte marker, glial fibrillary acidic protein (GFAP), was studied in association with AQP4. We demonstrated a robust upregulation of AQP4 expression in areas of plaques. Compared to GFAP, AQP4 appeared predominantly at later stages of plaque formation, in older mice, and within the processes of astrocytes. In combination with GFAP, AQP4 differentiated plaques into three progression stages under light microscopy. This suggests that AQP4 expression was associated with amyloid deposition and astrocyte pathology in the Tg-ArcSwe mouse model of AD. This provides novel proof for the involvement of AQP4 in the process of amyloid deposition in AD.

Association between Cognitive Status before Surgery and Outcomes in Elderly Patients with Hip Fracture in a Dedicated Orthogeriatric Care Pathway. - Zerah, Lorene; Cohen-Bittan, Judith; Raux, Mathieu; Meziere, Anthony; Tourette, Cendrine; Neri, Christian; Verny, Marc; Riou, Bruno; Khiami, Frederic; Boddaert, Jacques (J Alzheimers Dis, 2017)
BACKGROUND: Dementia is associated with a worse prognosis of hip fracture, but the impact of a dedicated geriatric care pathway on the prognosis of these patients has not been evaluated. OBJECTIVE: According to the cognitive status before surgery, our main objective was to compare mortality rate at 6 months; secondary outcomes were to compare in-hospital complications, the risk of new institutionalization, and the ability to walk at 6 months. METHODS: Between 2009 and 2015, all patients (>70 years) admitted after hip fracture surgery into a dedicated unit of peri-operative geriatric care were included: patients with dementia (DP), without dementia (NDP), and with cognitive status not determined (CSND). Data are expressed as hazard ratio (HR) for multivariate cox analysis or odds ratio (OR) for multivariate logistic regression analysis and their 95% confidence interval (CI). RESULTS: We included 650 patients (86±6 years): 168 DP, 400 NDP, and 82 CSND. After adjustment for age, sex, comorbidities, polypharmacy, pre-fracture autonomy, time-to-surgery, and delirium, there were no significant differences for 6-month mortality (DP versus NDP: HR = 0.7[0.4-1.2], DP versus CSND: HR = 0.6[0.3-1.4], CSND versus NDP: HR = 0.8[0.4-1.7]); but DP and CSND were more likely to be newly institutionalized after 6 months compared to NDP (OR DP = 2.6[1.4-4.9], p = 0.003, OR CSND = 2.9[1.4-6.1], p = 0.004). 92% of population was walking after 6 months (63% with assistance): no difference was found between the three groups. CONCLUSION: In a dedicated geriatric care pathway, DP and CSND undergoing hip surgery have the same 6-month mortality and walking ability as NDP.

Association Between Later Life Lifestyle Factors and Alzheimer's Disease Biomarkers in Non-Demented Individuals: A Longitudinal Descriptive Cohort Study. - Reijs, Babette L R; Vos, Stephanie J B; Soininen, Hilkka; Lötjönen, Jyrki; Koikkalainen, Juha; Pikkarainen, Maria; Hall, Anette; Vanninen, Ritva; Liu, Yawu; Herukka, Sanna-Kaisa; Freund-Levi, Yvonne; Frisoni, Giovanni B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Lifestyle factors have been associated with the risk of dementia, but the association with Alzheimer's disease (AD) remains unclear. OBJECTIVE: To examine the association between later life lifestyle factors and AD biomarkers (i.e., amyloid-β 1-42 (Aβ42) and tau in cerebrospinal fluid (CSF), and hippocampal volume) in individuals with subjective cognitive decline (SCD) and mild cognitive impairment (MCI). In addition, to examine the effect of later life lifestyle factors on developing AD-type dementia in individuals with MCI. METHODS: We selected individuals with SCD (n = 111) and MCI (n = 353) from the DESCRIPA and Kuopio Longitudinal MCI studies. CSF Aβ42 and tau concentrations were assessed with ELISA assay and hippocampal volume with multi-atlas segmentation. Lifestyle was assessed by clinical interview at baseline for: social activity, physical activity, cognitive activity, smoking, alcohol consumption, and sleep. We performed logistic and Cox regression analyses adjusted for study site, age, gender, education, and diagnosis. Prediction for AD-type dementia was performed in individuals with MCI only. RESULTS: Later life lifestyle factors were not associated with AD biomarkers or with conversion to AD-type dementia. AD biomarkers were strongly associated with conversion to AD-type dementia, but these relations were not modulated by lifestyle factors. Apolipoprotein E (APOE) genotype did not influence the results. CONCLUSIONS: Later life lifestyle factors had no impact on key AD biomarkers in individuals with SCD and MCI or on conversion to AD-type dementia in MCI.

Association between Mid-Regional Proadrenomedullin Levels and Progression of Deep White Matter Lesions in the Brain Accompanying Cognitive Decline. - Kuriyama, Nagato; Ihara, Masafumi; Mizuno, Toshiki; Ozaki, Etsuko; Matsui, Daisuke; Watanabe, Isao; Koyama, Teruhide; Kondo, Masaki; Tokuda, Takahiko; Tamura, Aiko; Yamada, Kei; Akazawa, Kentaro; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Adrenomedullin (ADM) is a vasoreactive physiological peptide with anti-inflammatory effects and vasodilative and immunomodulatory actions that is widely distributed throughout the vascular system of the brain. OBJECTIVE: To investigate mid-regional proADM (MR-proADM), a stable fragment of the ADM precursor, and cerebral deep white matter lesions (DWMLs) in association with cognitive decline. METHODS: The study participants were 288 patients (194 men, 94 women) who gave consent to participate in a 5-year longitudinal survey on arteriosclerosis from 2008 to 2013. The Fazekas classification system (Grade [G] 0 [normal] to G3 [severe]) was used for the evaluation of DWMLs on brain magnetic resonance imaging (MRI). In addition, all participants were asked to undergo cognitive function tests regarding word/letter fluency, the results of which were assessed for correlations with MR-proADM levels. RESULTS: MR-proADM levels significantly increased with DWML grade progression. The odds ratio for high MR-proADM levels was 3.08 (95% confidence interval: 1.49-5.17) in the groups graded G3 on brain MRI, suggesting that a high level of MR-proADM is an independent risk factor for DWMLs. A significant inverse correlation was observed between MR-proADM levels and cognitive test scores. MR-proADM levels were significantly increased in the G3 group in 2013 compared with 2008. CONCLUSION: MR-proADM levels were significantly different between the DWML groups and inversely correlated with cognitive function test scores, suggesting that high MR-proADM levels and DWMLs are associated with cognitive decline. Therefore, the MR-proADM level may be an effective candidate as a potential diagnostic surrogate marker of cognitive decline.

Association between Plasma Ceramides and Phosphatidylcholines and Hippocampal Brain Volume in Late Onset Alzheimer's Disease. - Kim, Min; Nevado-Holgado, Alejo; Whiley, Luke; Snowden, Stuart G; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Thambisetty, Madhav; Dobson, Richard J B; Powell, John F; et al. (J Alzheimers Dis, 2017)
Lipids such as ceramides and phosphatidylcholines (PC) have been found altered in the plasma of Alzheimer's disease (AD) patients in a number of discovery studies. For this reason, the levels of 6 ceramides and 3 PCs, with different fatty acid length and saturation levels, were measured in the plasma from 412 participants (AD n = 205, Control n = 207) using mass spectrometry coupled with ultra-performance liquid chromatography. After this, associations with AD status, brain atrophy, and age-related effects were studied. In the plasma of AD participants, cross-sectional analysis revealed elevated levels of three ceramides (Cer16:0 p < 0.01, Cer18:0 p < 0.01, Cer24:1 p < 0.05). In addition, two PCs in AD plasma (PC36:5 p < 0.05, PC38:6 p < 0.05) were found to be depleted compared to the control group, with PC36:5 also associating with hippocampal atrophy (p < 0.01). Age-specific analysis further revealed that levels of Cer16:0, Cer18:0, and Cer20:0 were associated with hippocampal atrophy only in younger participants (age < 75, p < 0.05), while all 3 PCs did so in the older participants (age > 75, p < 0.05). PC36:5 was associated with AD status in the younger group (p < 0.01), while PC38:6 and 40:6 did so in the older group (p < 0.05). In this study, elevated ceramides and depleted PCs were found in the plasma from 205 AD volunteers. Our findings also suggest that dysregulation in PC and ceramide metabolism could be occurring in different stages of AD progression.

Association of Central Arterial Stiffness and Pressure Pulsatility with Mild Cognitive Impairment and Dementia: The Atherosclerosis Risk in Communities Study-Neurocognitive Study (ARIC-NCS). - Meyer, Michelle L; Palta, Priya; Tanaka, Hirofumi; Deal, Jennifer A; Wright, Jacqueline; Knopman, David S; Griswold, Michael E; Mosley, Thomas H; Heiss, Gerardo (J Alzheimers Dis, 2017)
BACKGROUND: The association of central arterial stiffness and pressure pulsatility with mild cognitive impairment (MCI) and dementia is not well characterized in the population-based setting. OBJECTIVE: The aim of this study was to quantify the cross-sectional association of arterial stiffness and pressure pulsatility with MCI and dementia among 4,461 older white and black adults from the population-based Atherosclerosis Risk in Communities Study-Neurocognitive Study. METHODS: We used race-stratified multinomial logistic regression to evaluate associations of percentile cut points of carotid-femoral pulse wave velocity, central systolic blood pressure, central pulse pressure, and pulse pressure amplification with MCI and dementia versus no cognitive impairment. RESULTS: Among whites, those with carotid-femoral pulse wave velocity or central systolic blood pressure ≥75th percentile had a higher prevalence of MCI compared to participants <75th percentile (conditional odds ratio (OR); 95% confidence interval (CI): 1.27 (1.02, 1.56) and 1.28 (1.04, 1.57), respectively) and those with central pulse pressure ≥75th percentile had a higher prevalence of MCI (OR 1.27 (95% CI: 1.03, 1.58)) and dementia (OR 1.76 (95% CI: 1.06, 2.92) compared to participants <75th percentile. Also among whites, those with pulse pressure amplification ≤25th percentile had a higher prevalence of dementia compared to participants >25th percentile (OR 1.65; (95% CI: 1.01, 2.70). Weaker associations were seen among black participants. CONCLUSION: Higher arterial stiffness and pulsatility were associated with MCI and dementia in white participants. Longitudinal characterization of the observed associations is warranted to assess whether arterial stiffness and pressure pulsatility predict MCI and dementia among older adults.

Association of Gait Speed, Psychomotor Speed, and Dementia. - Kuate-Tegueu, Callixte; Avila-Funes, José-Alberto; Simo, Nadine; Le Goff, Mélanie; Amiéva, Hélène; Dartigues, Jean-François; Tabue-Teguo, Maturin (J Alzheimers Dis, 2017)
BACKGROUND: Gait speed (GS) and psychomotor speed (PS) could be considered as two different dimensions of age-related slowness and both measures are associated with higher risk of adverse health-related outcomes among elderly people. OBJECTIVE: To determine the association between GS, PS, and incident dementia among community-dwelling older adults. METHODS: Twelve-year longitudinal study of 1,265 participants in the Bordeaux Three-City Study, a French prospective cohort designed to determine the risk of dementia and cognitive impairment attributable to cardiovascular risk factors. Participants completed a battery of cognitive tests, including time to complete the Trail Making Test A, and a walking speed test. The incidence of dementia was determined over the 12-year follow-up period. Cox proportional hazards models with delayed entry were used to estimate the cumulative risk of dementia and were adjusted for sex, education, and ApoE4 genotype. RESULTS: Mean age of participants was 74.0 years (SD 4.8). Over the 12-year follow-up, 203 participants developed dementia. GS and PS were both independent predictors of incident all-cause dementia after 12 years of follow-up. For a one SD increase of either GS or PS, the hazard ratio (HR) for Alzheimer's disease was 1.2 (95% CI = 1.02-1.32) and 1.4 (95% CI = 1.2-1.61), respectively; whereas for incident vascular dementia, the HR was 1.3 (95% CI = 1.05-1.71) and 1.5 (95% CI = 1.16-2.08), respectively. No significant interaction between GS and PS was observed. CONCLUSIONS: In older French people aged 65+, our findings showed that both low GS and PS were independently associated with risk of incident Alzheimer's disease and vascular dementia.

Association of Kidney Function Biomarkers with Brain MRI Findings: The BRINK Study. - Vemuri, Prashanthi; Knopman, David S; Jack, Clifford R; Lundt, Emily S; Weigand, Stephen D; Zuk, Samantha M; Thostenson, Kaely B; Reid, Robert I; Kantarci, Kejal; Slinin, Yelena; Lakshminarayan, Kamakshi; Davey, Cynthia S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Chronic kidney disease (CKD) studies have reported variable prevalence of brain pathologies, in part due to low inclusion of participants with moderate to severe CKD. OBJECTIVE: To measure the association between kidney function biomarkers and brain MRI findings in CKD. METHODS: In the BRINK (BRain IN Kidney Disease) study, MRI was used to measure gray matter volumes, cerebrovascular pathologies (white matter hyperintensity (WMH), infarctions, microhemorrhages), and microstructural changes using diffusion tensor imaging (DTI). We performed regression analyses with estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (UACR) as primary predictors, and joint models that included both predictors, adjusted for vascular risk factors. RESULTS: We obtained 240 baseline MRI scans (150 CKD with eGFR <45 in ml/min/1.73 m2; 16 mild CKD: eGFR 45-59; 74 controls: eGFR≥60). Lower eGFR was associated with greater WMH burden, increased odds of cortical infarctions, and worsening diffusion changes throughout the brain. In eGFR models adjusted for UACR, only cortical infarction associations persisted. However, after adjusting for eGFR, higher UACR provided additional information related to temporal lobe atrophy, increased WMH, and whole brain microstructural changes as measured by increased DTI mean diffusivity. CONCLUSIONS: Biomarkers of kidney disease (eGFR and UACR) were associated with MRI brain changes, even after accounting for vascular risk factors. UACR adds unique additional information to eGFR regarding brain structural and diffusion biomarkers. There was a greater impact of kidney function biomarkers on cerebrovascular pathologies and microstructural brain changes, suggesting that cerebrovascular etiology may be the primary driver of cognitive impairment in CKD.

Associations of CAIDE Dementia Risk Score with MRI, PIB-PET measures, and cognition. - Stephen, Ruth; Liu, Yawu; Ngandu, Tiia; Rinne, Juha O; Kemppainen, Nina; Parkkola, Riitta; Laatikainen, Tiina; Paajanen, Teemu; Hänninen, Tuomo; Strandberg, Timo; Antikainen, Riitta; Tuomilehto, Jaakko; et al. (J Alzheimers Dis, 2017)
BACKGROUND: CAIDE Dementia Risk Score is the first validated tool for estimating dementia risk based on a midlife risk profile. OBJECTIVES: This observational study investigated longitudinal associations of CAIDE Dementia Risk Score with brain MRI, amyloid burden evaluated with PIB-PET, and detailed cognition measures. METHODS: FINGER participants were at-risk elderly without dementia. CAIDE Risk Score was calculated using data from previous national surveys (mean age 52.4 years). In connection to baseline FINGER visit (on average 17.6 years later, mean age 70.1 years), 132 participants underwent MRI scans, and 48 underwent PIB-PET scans. All 1,260 participants were cognitively assessed (Neuropsychological Test Battery, NTB). Neuroimaging assessments included brain cortical thickness and volumes (Freesurfer 5.0.3), visually rated medial temporal atrophy (MTA), white matter lesions (WML), and amyloid accumulation. RESULTS: Higher CAIDE Dementia Risk Score was related to more pronounced deep WML (OR 1.22, 95% CI 1.05-1.43), lower total gray matter (β-coefficient -0.29, p = 0.001) and hippocampal volume (β-coefficient -0.28, p = 0.003), lower cortical thickness (β-coefficient -0.19, p = 0.042), and poorer cognition (β-coefficients -0.31 for total NTB score, -0.25 for executive functioning, -0.33 for processing speed, and -0.20 for memory, all p < 0.001). Higher CAIDE Dementia Risk Score including APOE genotype was additionally related to more pronounced MTA (OR 1.15, 95% CI 1.00-1.30). No associations were found with periventricular WML or amyloid accumulation. CONCLUSIONS: The CAIDE Dementia Risk Score was related to indicators of cerebrovascular changes and neurodegeneration on MRI, and cognition. The lack of association with brain amyloid accumulation needs to be verified in studies with larger sample sizes.

BACE1 Dynamics Upon Inhibition with a BACE Inhibitor and Correlation to Downstream Alzheimer's Disease Markers in Elderly Healthy Participants. - Timmers, Maarten; Barão, Soraia; Van Broeck, Bianca; Tesseur, Ina; Slemmon, John; de Waepenaert, Katja; Bogert, Jennifer; Shaw, Leslie M; Engelborghs, Sebastiaan; Moechars, Dieder; Mercken, Marc; Van Nueten, Luc; et al. (J Alzheimers Dis, 2017)
The β-site amyloid-β protein precursor (AβPP) cleaving enzyme-1 (BACE1) is the rate limiting enzyme in the generation of amyloid-β peptide (Aβ) from AβPP, one of the major pathways in Alzheimer's disease (AD) pathology. Increased BACE1 levels and activity have been reported in the brain of patients with sporadic AD. Therefore, changes of BACE1 levels in the cerebrospinal fluid (CSF) have also been investigated as a possible biomarker of the disease. We analyzed BACE1 levels in CSF of elderly healthy participants before and after chronic treatment with a BACE inhibitor (BACEi) and evaluated the correlation between BACE1 levels and downstream AD markers. Overall, BACE1 CSF levels showed strong correlations to all downstream AD markers investigated. This is the first reported finding that shows BACE1 levels in CSF were well correlated to its end product Aβ1 - 42. As previously described, BACE1 levels were strongly correlated to total-tau and phosphorylated tau levels in CSF. Generally, chronic BACE inhibition did not influence BACE1 CSF protein levels. Follow-up studies including early-stage AD pathophysiology and prodromal AD patients will help to understand the importance of measuring BACE1 routinely in daily clinical practice and AD clinical trials.

Baseline Telomere Length and Effects of a Multidomain Lifestyle Intervention on Cognition: The FINGER Randomized Controlled Trial. - Sindi, Shireen; Ngandu, Tiia; Hovatta, Iiris; Kåreholt, Ingemar; Antikainen, Riitta; Hänninen, Tuomo; Levälahti, Esko; Laatikainen, Tiina; Lindström, Jaana; Paajanen, Teemu; Peltonen, Markku; Khalsa, Dharma Singh; et al. (J Alzheimers Dis, 2017)
Leukocyte telomere length (LTL) is a biomarker of aging, and it is associated with lifestyle. It is currently unknown whether LTL is associated with the response to lifestyle interventions. The goal is to assess whether baseline LTL modified the cognitive benefits of a 2-year multidomain lifestyle intervention (exploratory analyses). The Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) was a 2-year randomized controlled trial including 1,260 people at risk of cognitive decline, aged 60-77 years identified from the general population. Participants were randomly assigned to the lifestyle intervention (diet, exercise, cognitive training, and vascular risk management) and control (general health advice) groups. Primary outcome was change in cognition (comprehensive neuropsychological test battery). Secondary outcomes were changes in cognitive domains: memory, executive functioning, and processing speed. 775 participants (392 control, 383 intervention) had baseline LTL (peripheral blood DNA). Mixed effects regression models with maximum likelihood estimation were used to analyze change in cognition as a function of randomization group, time, baseline LTL, and their interaction. Intervention and control groups did not significantly differ at baseline. Shorter LTL was related to less healthy baseline lifestyle. Intervention benefits on executive functioning were more pronounced among those with shorter baseline LTL (p-value for interaction was 0.010 adjusted for age and sex, and 0.007 additionally adjusted for baseline lifestyle factors). The FINGER intervention cognitive benefits were more pronounced with shorter baseline LTL, particularly for executive functioning, indicating that the multidomain lifestyle intervention was especially beneficial among higher-risk individuals.

BDNF Responses in Healthy Older Persons to 35 Minutes of Physical Exercise, Cognitive Training, and Mindfulness: Associations with Working Memory Function. - Håkansson, Krister; Ledreux, Aurélie; Daffner, Kirk; Terjestam, Yvonne; Bergman, Patrick; Carlsson, Roger; Kivipelto, Miia; Winblad, Bengt; Granholm, Ann-Charlotte; Mohammed, Abdul Kadir H (J Alzheimers Dis, 2017)
Brain-derived neurotrophic factor (BDNF) has a central role in brain plasticity by mediating changes in cortical thickness and synaptic density in response to physical activity and environmental enrichment. Previous studies suggest that physical exercise can augment BDNF levels, both in serum and the brain, but no other study has examined how different types of activities compare with physical exercise in their ability to affect BDNF levels. By using a balanced cross over experimental design, we exposed nineteen healthy older adults to 35-minute sessions of physical exercise, cognitive training, and mindfulness practice, and compared the resulting changes in mature BDNF levels between the three activities. We show that a single bout of physical exercise has significantly larger impact on serum BDNF levels than either cognitive training or mindfulness practice in the same persons. This is the first study on immediate BDNF effects of physical activity in older healthy humans and also the first study to demonstrate an association between serum BDNF responsivity to acute physical exercise and working memory function. We conclude that the BDNF increase we found after physical exercise more probably has a peripheral than a central origin, but that the association between post-intervention BDNF levels and cognitive function could have implications for BDNF responsivity in serum as a potential marker of cognitive health.

Blood Pressure and Hispanic/Latino Cognitive Function: Hispanic Community Health Study/Study of Latinos Results. - Tarraf, Wassim; Rodríguez, Carlos J; Daviglus, Martha L; Lamar, Melissa; Schneiderman, Neil; Gallo, Linda; Talavera, Gregory A; Kaplan, Robert C; Fornage, Myriam; Conceicao, Alan; González, Hector M (J Alzheimers Dis, 2017)
BACKGROUND: Hispanics/Latinos are at increased risk for cardiovascular disease and cognitive decline and dementias. High blood pressure (BP) has been implicated in both stroke and dementias. Associations between BP and cognition among diverse Latinos are still unpublished. OBJECTIVE: We examined associations between cognition and four BP based measures among diverse Hispanics/Latinos. We hypothesized that higher BP, particularly systolic pressure, and increased arterial stiffness (i.e., pulse pressure), would be associated with lower cognitive function. METHODS: We used baseline (2008-2011) Hispanic Community Health Study/Study of Latinos (HCHS/SOL; n = 9,019; ages 45-74 years) data to examine cognition in relation to BP measures. RESULTS: In age, sex, and education adjusted models, systolic, pulse, and mean arterial pressure were consistently negatively associated with executive function, psychomotor speed and sustained attention, verbal episodic learning and memory, speech fluency, and mental status measures. These associations were attenuated but remained statistically significant in fully adjusted models. CONCLUSION: Among middle-aged and older diverse Hispanics/Latinos, we found modest but consistent associations between indicators of arterial stiffness, and compromised blood flow and lower cognitive function. Clinical management and public health interventions to raise awareness and enhance BP management beginning in midlife could reduce disparities and improve population health by reducing cognitive decline burdens.

Blunted Respiratory Responses in the Streptozotocin-Induced Alzheimer's Disease Rat Model. - Ebel, Dalton L; Torkilsen, Christopher G; Ostrowski, Tim D (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is known for the progressive decline of cognition and memory. In addition to these disease-defining symptoms, impairment of respiratory function is frequently observed and often expressed by sleep-disordered breathing or reduced ability to adjust respiration when oxygen demand is elevated. The mechanisms for this are widely unknown. Postmortem analysis from the brainstem of AD patients reveals pathological alterations, including in nuclei responsible for respiratory control. In this study, we analyzed respiratory responses and morphological changes in brainstem nuclei following intracerebroventricular (ICV) injections of streptozotocin (STZ), a rat model commonly used to mimic sporadic AD. ICV-STZ induced significant astrogliosis in the commissural part of the nucleus tractus solitarii, an area highly involved in respiration control. The astrogliosis was identified by a significant increase in S100B-immunofluorescence that is similar to the astrogliosis found in the CA1 region of the hippocampus. Using plethysmography, the control group displayed a typical age-dependent decrease of ventilation that was absent in the STZ rat group. This is indicative of elevated minute ventilation at rest after STZ treatment. Peripheral chemoreflex responses were significantly blunted in STZ rats as seen by a reduced respiratory rate and minute ventilation to hypoxia. Central chemoreflex responses to hypercapnia, on the other hand, only decreased in respiratory rate following STZ treatment. Overall, our results show that ICV-STZ induces respiratory dysfunction at rest and in response to hypoxia. This provides a new tool to study the underlying mechanisms of breathing disorders in clinical AD.

Can Musical or Painting Interventions Improve Chronic Pain, Mood, Quality of Life, and Cognition in Patients with Mild Alzheimer's Disease? Evidence from a Randomized Controlled Trial. - Pongan, Elodie; Tillmann, Barbara; Leveque, Yohana; Trombert, Béatrice; Getenet, Jean Claude; Auguste, Nicolas; Dauphinot, Virginie; El Haouari, Hanane; Navez, Malou; Dorey, Jean-Michel; Krolak-Salmon, Pierre; Laurent, Bernard; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Among non-pharmacological therapies, musical intervention is often used for patients with Alzheimer's disease (AD) and patients presenting chronic pain. However, their efficacy is still under debate. OBJECTIVE: Our aim was to determine the efficacy of choral singing versus painting sessions on chronic pain, mood, quality of life, and cognition in AD patients. METHODS: In this multicenter randomized controlled trial, 59 mild AD patients were randomized to a 12-week singing (SG; n = 31) or painting group (PG; n = 28). Chronic pain, anxiety, depression, and quality of life were assessed before, after, and 1 month after the sessions. Cognitive abilities were assessed before and after interventions. The evolution of these different measures was assessed with mixed linear models. The primary data analysis was by intention-to-treat, and completed by a 'per protocol' approach. RESULTS: Both singing and painting interventions led to significant pain reduction (Time effect: F = 4.71; p = 0.01), reduced anxiety (Time effect: F = 10.74; p < 0.0001), improved Quality of Life (Time effect: F = 6.79; p = 0.002), improved digit span (F = 12.93; p = 0.001), and inhibitory processes (Time effect: F = 4.93; p = 0.03). Depression was reduced over time in PG only (Time x Group effect: F = 4.53; p = 0.01). Verbal Memory performance remained stable over time in SG, but decreased in PG (Time x group effect: F = 9.29; p = 0.004). CONCLUSION: Findings suggest that singing and painting interventions may reduce pain and improve mood, quality of life, and cognition in patients with mild AD, with differential effects of painting for depression and singing for memory performance.

Cerebrospinal Fluid Neurogranin as a Biomarker of Neurodegenerative Diseases: A Cross-Sectional Study. - Lista, Simone; Toschi, Nicola; Baldacci, Filippo; Zetterberg, Henrik; Blennow, Kaj; Kilimann, Ingo; Teipel, Stefan J; Cavedo, Enrica; Dos Santos, Antonio Melo; Epelbaum, Stéphane; Lamari, Foudil; Dubois, Bruno; et al. (J Alzheimers Dis, 2017)
We investigated cerebrospinal fluid (CSF) concentrations of the postsynaptic biomarker neurogranin at baseline in cognitively healthy controls (HC) compared to individuals with mild cognitive impairment (MCI), patients with Alzheimer's disease (AD) dementia, and patients with frontotemporal dementia (FTD). CSF neurogranin was quantified using an in-house immunoassay in a cross-sectional multicenter study of 108 participants [AD dementia (n = 35), FTD (n = 9), MCI (n = 41), cognitively HC (n = 23)]. CSF neurogranin concentrations were significantly higher in AD patients compared with both HC subjects and FTD patients, suggesting that increased CSF neurogranin concentrations may indicate AD-related pathophysiology. CSF neurogranin was independently associated with both total tau and hyperphosphorylated tau proteins, whereas a non-significant correlation with the 42-amino acid-long amyloid-β peptide was evident. CSF neurogranin, however, was not superior to core AD biomarkers in differentiating HC from the three diagnostic groups, and it did not improve their diagnostic accuracy. We conclude that further classification and longitudinal studies are required to shed more light into the potential role of neurogranin as a pathophysiological biomarker of neurodegenerative diseases.

Chinese Calligraphy Writing for Augmenting Attentional Control and Working Memory of Older Adults at Risk of Mild Cognitive Impairment: A Randomized Controlled Trial. - Chan, Sam C C; Chan, Chetwyn C H; Derbie, Abiot Y; Hui, Irene; Tan, Davynn G H; Pang, Marco Y C; Lau, Stephen C L; Fong, Kenneth N K (J Alzheimers Dis, 2017)
BACKGROUND: Nonpharmacological intervention for individuals with mild cognitive impairment (MCI) needs further investigation. OBJECTIVE: Test efficacy of an eight-week Chinese calligraphy writing training course in improving attentional control and working memory. METHODS: Ninety-nine participants with MCI were randomized into the eight-week calligraphy writing (n = 48) or control (tablet computer) training (n = 51). Outcomes of the interventions were attentional control, working memory, visual scan and processing speed. They were measured at baseline, post-training, and six-month follow-up. RESULTS: Calligraphy writing, when compared with control, significantly improved working memory as reflected from DST-Backward sequence (p = 0.009) and span scores (p = 0.002), and divided attention as reflected from CTT2 (p < 0.001), and at the post-training. The unique improvement in working memory (span: p < 0.001; sequence: p = 0.008) of the intervention group was also found at follow-up when comparing with those at baseline. Changes in the other outcome measures were not statistically significant. CONCLUSION: The findings provide support that Chinese calligraphy writing training for eight weeks using a cognitive approach would improve working memory and to a lesser extent attentional control functions of patients with early MCI. They also demonstrate the usefulness of using mind-and-body practice for improving specific cognitive functions.

Cholinergic Basal Forebrain Lesion Decreases Neurotrophin Signaling without Affecting Tau Hyperphosphorylation in Genetically Susceptible Mice. - Turnbull, Marion T; Coulson, Elizabeth J (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive, irreversible neurodegenerative disease that destroys memory and cognitive function. Aggregates of hyperphosphorylated tau protein are a prominent feature in the brain of patients with AD, and are a major contributor to neuronal toxicity and disease progression. However, the factors that initiate the toxic cascade that results in tau hyperphosphorylation in sporadic AD are unknown. Here we investigated whether degeneration of basal forebrain cholinergic neurons (BFCNs) and/or a resultant decrease in neurotrophin signaling cause aberrant tau hyperphosphorylation. Our results reveal that the loss of BFCNs in pre-symptomatic pR5 (P301L) tau transgenic mice results in a decrease in hippocampal brain-derived neurotrophic factor levels and reduced TrkB receptor activation. However, there was no exacerbation of the levels of phosphorylated tau or its aggregation in the hippocampus of susceptible mice. Furthermore the animals' performance in a hippocampal-dependent learning and memory task was unaltered, and no changes in hippocampal synaptic markers were observed. This suggests that tau pathology is likely to be regulated independently of BFCN degeneration and the corresponding decrease in hippocampal neurotrophin levels, although these features may still contribute to disease etiology.

Chronic Neurodegenerative Illnesses and Epilepsy in Danish Adventists and Baptists: A Nationwide Cohort Study. - Thygesen, Lau Caspar; Gimsing, Louise NØrreslet; Bautz, Andrea; Hvidt, Niels Christian; Johansen, Christoffer (J Alzheimers Dis, 2017)
BACKGROUND: Limited knowledge of the influence of lifestyle risk factors and religious living on chronic neurological diseases exist. Seventh-day Adventists (SDA) do not consume tobacco, alcohol, or pork, and many adhere to lacto-ovo-vegetarian diet, and Baptists discourage excessive use of alcohol and tobacco. OBJECTIVE: We investigated whether the incidence of four common chronic neurological illnesses: dementia, Alzheimer's disease, Parkinson's disease, and epilepsy in a large cohort of Danish Adventists and Baptists was different compared to the general Danish population. Three of the illnesses are neurodegenerative, whereas epilepsy can occur at any age. METHODS: We compared hospital admission rates for some major neurological diseases among members of the Danish Religious Societies Health Study comprising 6,532 SDA and 3,720 Baptists with the general Danish population. Standardized incidence rates (SIR) stratified by sex, age, and calendar time were calculated. RESULTS: SIR of dementia or Alzheimer's disease was significantly decreased for members of both communities (SDA, 0.78; 95% CI, 0.67-#x2013;0.90 and Baptists, 0.59; 0.47-#x2013;0.73). The SIRs of Parkinson's disease and epilepsy were not significantly different compared to the general population. CONCLUSIONS: We observe reduced incidence for dementia or Alzheimer's disease in a large cohort of members of two religious communities characterized by lifestyle recommendations. More studies are needed to disentangle the interaction between such lifestyle and other components of the religious belief system.

Clinical Response to Donepezil in Mild and Moderate Dementia: Relationship to Drug Plasma Concentration and CYP2D6 and APOE Genetic Polymorphisms. - Miranda, Luís F J R; Gomes, Karina B; Tito, Pedro A L; Silveira, Josianne N; Pianetti, Gerson A; Byrro, Ricardo M D; Peles, Patrícia R H; Pereira, Fernando H; Santos, Thiago R; Assini, Arthur G; Ribeiro, Valéria V; Moraes, Edgar N; et al. (J Alzheimers Dis, 2017)
The clinical response to donepezil in patients with mild and moderate dementia was investigated in relation to the drug plasma concentration and APOE and CYP2D6 polymorphisms. In a prospective naturalistic observational study, 42 patients with Alzheimer's disease (AD) and AD with cerebrovascular disease who took donepezil (10 mg) for 12 months were evaluated. Their DNA was genotyped, and the donepezil plasma concentrations were measured after 3, 6, and 12 months. Good responders scored ≥-1 on the Mini-Mental State Examination at 12 months in comparison to the baseline score. The study results indicated the good response pattern was influenced by the concentration of donepezil, but not by APOE and CYP2D6 polymorphisms.

The Clinical Use of Cerebrospinal Fluid Biomarkers for Alzheimer's Disease Diagnosis: The Italian Selfie. - Sancesario, Giulia M; Toniolo, Sofia; Chiasserini, Davide; Di Santo, Simona G; Zegeer, Josh; Bernardi, Gaetano; Musicco, Massimo; Caltagirone, Carlo; Parnetti, Lucilla; Bernardini, Sergio (J Alzheimers Dis, 2017)
Although the use of cerebrospinal fluid (CSF) amyloid β1-42 (Aβ42), tau (T-tau), and phosphorylated tau (p-tau181) gives added diagnostic and prognostic values, the diffusion is still limited in clinical practice and only a restricted number of patients receive an integrated clinico-biological diagnosis. By a survey, we aimed to do a "selfie" of the use and diffusion of CSF biomarkers of dementia in Italy, the standardization of pre-analytical procedures, the harmonization of ranges, and the participation to Quality Control programs. An online questionnaire was sent to the members of SIBioC and SINdem-ITALPLANED and to main neurological clinics all over Italy. In Italy, 25 laboratories provide biomarkers analysis in addition to a network of 15 neighboring hospitals. In sum, 40 neurological centers require CSF analyses. 7/20 regions (35%) lack CSF laboratories. Standardization of pre-analytical procedures is present in 62.02% of the laboratories; only 56.00% of the laboratories participate in International Quality Control. There is no harmonization of cut-offs. In Italy, the use of CSF biomarkers is still limited in clinical practice. Standardization and harmonization of normal ranges are needed. To optimize and expand the use of CSF biomarkers, a cost-benefit analysis should be promoted by scientific societies and national health services.

Cognitive Composites Domain Scores Related to Neuroimaging Biomarkers within Probable-Amnestic Mild Cognitive Impairment-Storage Subtype. - Espinosa, Ana; Alegret, Montserrat; Pesini, Pedro; Valero, Sergi; Lafuente, Asunción; Buendia, Mar; San José, Itziar; Ibarria, Marta; Tejero, Miguel A; Giménez, Joan; Ruiz, Susana; Hernandez, Isabel; et al. (J Alzheimers Dis, 2017)
The probable-amnestic (Pr-a) mild cognitive impairment (MCI)-storage subtype is a phenotype with 8.5 times more risk of conversion to dementia, mainly Alzheimer's disease (AD), than the possible non-amnestic (Pss-na) MCI. The aim of this study was to find the optimized cognitive composites (CCs) domain scores most related to neuroimaging biomarkers within Pr-aMCI-storage subtype patients. The Fundació ACE (ACE) study with 20 Pr-aMCI-storage subtype subjects (MCI) were analyzed. All subjects underwent a neuropsychological assessment, a structural MRI, FDG-PET, and PIB-PET. The adjusted hippocampal volume (aHV) on MRI, the standard uptake value ratio (SUVR) on FDG-PET and PIB-PET SUVR measures were analyzed. The construction of the CCs domain scores, and the aHV on MRI and FDG-PET SUVR measures, were replicated in the parental AB255 study database (n = 133 MCI). Partial correlations adjusted by age, gender, and education were calculated with the associated p-value among every CC domain score and the neuroimaging biomarkers. The results were replicated in the "MCI due to AD" with memory storage impairments from ADNI. Delayed Recall CC domain score was significantly correlated with PIB-PET SUVR (β= -0.61, p = 0.003) in the ACE study and also with aHV on MRI (β= 0.27, p = 0.01) and FDG-PET SUVR (β= 0.27, p = 0.01) in the AB255 study. After a median survival time of 20.6 months, 85% from the ACE MCI converted to AD. The replication of our results in the ADNI dataset also confirmed our findings. Delayed Recall is the CC domain score best correlated with neuroimaging biomarkers associated with prodromal AD diagnosis.

Cognitive Event-Related Potential, an Early Diagnosis Biomarker in Frail Elderly Subjects: The ERP-MAPT-PLUS Ancillary Study. - Bennys, Karim; Gabelle, Audrey; Berr, Claudine; De Verbizier, Delphine; Andrieu, Sandrine; Vellas, Bruno; Touchon, Jacques (J Alzheimers Dis, 2017)
BACKGROUND: By analyzing brain synaptic function, cognitive event-related potentials (ERPs) could provide powerful and innovative tools for early Alzheimer's disease (AD) diagnosis. OBJECTIVE: We investigated the relevance of the ERP-P300 component as a potential diagnosis marker in elderly subjects at risk of developing AD. METHODS: ERP-P300 was analyzed on 85 subjects recruited from the Multidomain Alzheimer Preventive Trial (MAPT). PET-AV45 brain imaging was available from 36 subjects. RESULTS: Two ERP-P300 subgroups were identified according to their PET-AV45 status: PET-Aβ positive (n = 15) and PET-Aβ negative (n = 21). In the amyloid positive group, we observed a highly significant increase in P3b latency in parietal brain regions (p = 0.0052). P3b in parietal regions correctly categorized 69.4% elderly subjects from the P300-PET Aβ positive group. Combined analysis of parietal P3b latencies and category fluency correctly classified 75% subjects from the P300-PET Aβ positive group. CONCLUSIONS: The P300 ERP presents good predictive measure of brain amyloid load and has the potential to be used as a screening instrument for preclinical AD. The incorporation of P3b latency may be used as an adjunctive tool with neuropsychological assessment (i.e., verbal category fluency) as a specific and sensitive method for preclinical assessment of AD.

Cognitive Rehabilitation in Alzheimer's Disease: A Controlled Intervention Trial. - Brueggen, Katharina; Kasper, Elisabeth; Ochmann, Sina; Pfaff, Henrike; Webel, Steffi; Schneider, Wolfgang; Teipel, Stefan (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive Rehabilitation for Alzheimer's disease (AD) is an integrative multimodal intervention. It aims to maintain autonomy and quality of life by enhancing the patients' abilities to compensate for decreased cognitive functioning. OBJECTIVE: We evaluated the feasibility of a group-based Cognitive Rehabilitation approach in mild AD dementia and assessed its effect on activities of daily living (ADL). METHODS: We included 16 patients with AD dementia in a controlled partial-randomized design. We adapted the manual-guided Cognitive Rehabilitation program (CORDIAL) to a group setting. Over the course of three months, one group received the Cognitive Rehabilitation intervention (n = 8), while the other group received a standardized Cognitive Training as an active control condition (n = 8). ADL-competence was measured as primary outcome. The secondary outcome parameters included cognitive abilities related to daily living, functional cognitive state, and non-cognitive domains, e.g., quality of life. For each scale, we assessed the interaction effect 'intervention by time', i.e., from pre-to post-intervention. RESULTS: We found no significant interaction effect of intervention by time on the primary outcome ADL-competence. The interaction effect was significant for quality of life (Cohen's d: -1.43), showing an increase in the intervention group compared with the control group. CONCLUSIONS: Our study demonstrates the feasibility of a group-based Cognitive Rehabilitation program for patients with mild AD dementia. The Cognitive Rehabilitation showed no significant effect on ADL, possibly reflecting a lack of transfer between the therapy setting and real life. However, the group setting enhanced communication skills and coping mechanisms. Effects on ADL may not have reached statistical significance due to a limited sample size. Furthermore, future studies might use an extended duration of the intervention and integrate caregivers to a greater extent to increase transfer to activities of daily living.

Cognitive-Enhancing Effects of a Polyphenols-Rich Extract from Fruits without Changes in Neuropathology in an Animal Model of Alzheimer's Disease. - Dal-Pan, Alexandre; Dudonné, Stéphanie; Bourassa, Philippe; Bourdoulous, Morgane; Tremblay, Cyntia; Desjardins, Yves; Calon, Frederic (J Alzheimers Dis, 2017)
No effective preventive treatment is available for age-related cognitive decline and Alzheimer's disease (AD). Epidemiological studies indicate that a diet rich in fruit is associated with cognitive improvement. It was thus proposed that high polyphenol concentrations found in berries can prevent cognitive impairment associated with aging and AD. Therefore, the Neurophenols project aimed at investigating the effects of a polyphenolic extract from blueberries and grapes (PEBG) in the triple-transgenic (3xTg-AD) mouse model of AD, which develops AD neuropathological markers, including amyloid-β plaques and neurofibrillary tangles, leading to memory deficits. In this study, 12-month-old 3xTg-AD and NonTg mice were fed a diet supplemented with standardized PEBG (500 or 2500 mg/kg) for 4 months (n = 15-20/group). A cognitive evaluation with the novel object recognition test was performed at 15 months of age and mice were sacrificed at 16 months of age. We observed that PEBG supplementation with doses of 500 or 2500 mg/kg prevented the decrease in novel object recognition observed in both 15-month-old 3xTg-AD mice and NonTg mice fed a control diet. Although PEBG treatment did not reduce Aβ and tau pathologies, it prevented the decrease in mature BDNF observed in 16-month-old 3xTg-AD mice. Finally, plasma concentrations of phenolic metabolites, such as dihydroxyphenyl valerolactone, a microbial metabolite of epicatechin, positively correlated with memory performances in supplemented mice. The improvement in object recognition observed in 3xTg-AD mice after PEBG administration supports the consumption of polyphenols-rich extracts to prevent memory impairment associated with age-related disease, without significant effects on classical AD neuropathology.

Co-Localization of Glia Maturation Factor with NLRP3 Inflammasome and Autophagosome Markers in Human Alzheimer's Disease Brain. - Ahmed, Mohammad Ejaz; Iyer, Shankar; Thangavel, Ramasamy; Kempuraj, Duraisamy; Selvakumar, Govindhasamy Pushpavathi; Raikwar, Sudhanshu P; Zaheer, Smita; Zaheer, Asgar (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by the presence of intracellular neurofibrillary tangles (NFTs) containing hyperphosphorylated tau, and the extracellular deposition of amyloid plaques (APs) with misfolded amyloid-β (Aβ) peptide. Glia maturation factor (GMF), a highly conserved pro-inflammatory protein, isolated and cloned in our laboratory, has been shown to activate glial cells leading to neuroinflammation and neurodegeneration in AD. We hypothesized that inflammatory reactions promoted by NLRP3-Caspase-1inflammasome pathway trigger dysfunction in autophagy and accumulation of Aβ which is amplified and regulated by GMF in AD. In this study, using immunohistochemical techniques we analyzed components of the NLRP3 inflammasome and autophagy- lysosomal markers in relation to Aβ, p-tau and GMF in human postmortem AD and age-matched non-AD brains. Tissue sections were prepared from the temporal cortex of human postmortem brains. Here, we demonstrate an increased expression of the inflammasome components NLRP3 and Caspase-1 and the products of inflammasome activation IL-1β and IL-18 along with GMF in the temporal cortex of AD brains. These inflammasome components and the pro-inflammatory cytokines co-localized with GMF in the vicinity and periphery of the APs and NFTs. Moreover, using double immunofluorescence staining, AD brain displayed an increase in the autophagy SQSTM1/p62 and LC3 positive vesicles and the lysosomal marker LAMP1 that also co-localized with GMF, Aβ and hyperphosphorylated p-tau. Our results indicate that in AD, the neuroinflammation promoted by the NLRP3 inflammasome may be amplified and regulated by GMF, which further impairs clearance of protein aggregates mediated by the auto-phagosomal pathway.

Combustion-Derived Nanoparticles in Key Brain Target Cells and Organelles in Young Urbanites: Culprit Hidden in Plain Sight in Alzheimer's Disease Development. - González-Maciel, Angelica; Reynoso-Robles, Rafael; Torres-Jardón, Ricardo; Mukherjee, Partha S; Calderón-Garcidueñas, Lilian (J Alzheimers Dis, 2017)
Millions of children and young adults are exposed to fine particulate matter (PM2.5) and ozone, associated with Alzheimer's disease (AD) risk. Mexico City (MC) children exhibit systemic and brain inflammation, low cerebrospinal fluid (CSF) Aβ1-42, breakdown of nasal, olfactory, alveolar-capillary, duodenal, and blood-brain barriers, volumetric and metabolic brain changes, attention and short-term memory deficits, and hallmarks of AD and Parkinson's disease. Airborne iron-rich strongly magnetic combustion-derived nanoparticles (CDNPs) are present in young urbanites' brains. Using transmission electron microscopy, we documented CDNPs in neurons, glia, choroid plexus, and neurovascular units of young MC residents versus matched clean air controls. CDNPs are associated with pathology in mitochondria, endoplasmic reticulum (ER), mitochondria-ER contacts (MERCs), axons,and dendrites. There is a significant difference in size and numbers between spherical CDNPs (>85%) and the angular, euhedral endogenous NPs (<15%). Spherical CDNPs (dogs 21.2±7.1 nm in diameter versus humans 29.1±11.2 nm, p = 0.002) are present in neurons, glia, choroid plexus, endothelium, nasal and olfactory epithelium, and in CSF at significantly higher in numbers in MC residents (p < 0.0001). Degenerated MERCs, abnormal mitochondria, and dilated ER are widespread, and CDNPs in close contact with neurofilaments, glial fibers, and chromatin are a potential source for altered microtubule dynamics, mitochondrial dysfunction, accumulation and aggregation of unfolded proteins, abnormal endosomal systems, altered insulin signaling, calcium homeostasis, apoptotic signaling, autophagy, and epigenetic changes. Highly oxidative, ubiquitous CDNPs constitute a novel path into AD pathogenesis. Exposed children and young adults need early neuroprotection and multidisciplinary prevention efforts to modify the course of AD at early stages.

A Common Variant in the MC1R Gene (p.V92M) is associated with Alzheimer's Disease Risk. - Tell-Marti, Gemma; Puig-Butille, Joan Anton; Potrony, Miriam; Plana, Estel; Badenas, Celia; Antonell, Anna; Sánchez-Valle, Raquel; Molinuevo, José L; Lleo, Alberto; Alcolea, Daniel; Fortea, Juan; Fernández-Santiago, Rubén; et al. (J Alzheimers Dis, 2017)
Despite the recent identification of some novel risk genes for Alzheimer's disease (AD), the genetic etiology of late-onset Alzheimer's disease (LOAD) remains largely unknown. The inclusion of these novel risk genes to the risk attributable to the APOE gene accounts for roughly half of the total genetic variance in LOAD. The evidence indicates that undiscovered genetic factors may contribute to AD susceptibility. In the present study, we sequenced the MC1R gene in 525 Spanish LOAD patients and in 160 controls. We observed that a common MC1R variant p.V92M (rs2228479), not related to pigmentation traits, was present in 72 (14%) patients and 15 (9%) controls and confers increased risk of developing LOAD (OR: 1.99, 95% CI: 1.08-3.64, p = 0.026), especially in those patients whose genetic risk could not be explained by APOE genotype. This association remains and even increased in the subset of 69 patients with typical AD cerebrospinal fluid profile (OR: 3.40 95% CI: 1.40-8.27, p = 0.007). We did not find an association between p.V92M and age of onset of AD. Further studies are necessary to elucidate the role of MC1R in brain cells through the different MC1R pathways.

Comparative Analysis of Cortical Microinfarcts and Microbleeds using 3.0-Tesla Postmortem Magnetic Resonance Images and Histopathology. - Niwa, Atsushi; Ii, Yuichiro; Shindo, Akihiro; Matsuo, Ko; Ishikawa, Hidehiro; Taniguchi, Akira; Takase, Shinichi; Maeda, Masayuki; Sakuma, Hajime; Akatsu, Hiroyasu; Hashizume, Yoshio; Tomimoto, Hidekazu (J Alzheimers Dis, 2017)
Microvascular lesions including cortical microinfarctions (CMIs) and cerebral lobar microbleeds (CMBs) are usually caused by cerebral amyloid angiopathy (CAA) in the elderly and are correlated with cognitive decline. However, their radiological-histopathological coincidence has not been revealed systematically with widely used 3-Tesla (3T) magnetic resonance imaging (MRI). The purpose of the present study is to delineate the histopathological background corresponding to MR images of these lesions. We examined formalin-fixed 10-mm thick coronal brain blocks from 10 CAA patients (five were also diagnosed with Alzheimer's disease, three with dementia with Lewy bodies, and two with CAA only) with dementia and six non CAA patients with neurodegenerative disease. Using 3T MRI, both 3D-fluid attenuated inversion recovery (FLAIR) and 3D-double inversion recovery (DIR) were examined to identify CMIs, and T2* and susceptibility-weighted images (SWI) were examined to identify CMBs. These blocks were subsequently examined histologically and immunohistochemically. In CAA patients, 48 CMIs and 6 lobar CMBs were invariably observed in close proximity to degenerated Aβ-positive blood vessels. Moreover, 16 CMIs (33%) of 48 were detected with postmortem MRI, but none were seen when the lesion size was smaller than 1 mm. In contrast, only 1 undeniable CMI was founded with MRI and histopathology in 6 non CAA patients. Small, cortical high-intensity lesions seen on 3D-FLAIR and 3D-DIR images likely represent CMIs, and low-intensity lesions in T2* and SWI correspond to CMBs with in vivo MRI. Furthermore, a close association between amyloid-laden vessels and these microvascular lesions indicated the contribution of CAA to their pathogenesis.

Comparison of Model-Based Indices of Cerebral Autoregulation and Vasomotor Reactivity Using Transcranial Doppler versus Near-Infrared Spectroscopy in Patients with Amnestic Mild Cognitive Impairment. - Marmarelis, Vasilis Z; Shin, Dae C; Tarumi, Takashi; Zhang, Rong (J Alzheimers Dis, 2017)
We recently introduced model-based "physiomarkers" of dynamic cerebral autoregulation and CO2 vasomotor reactivity as an aid for diagnosis of early-stage Alzheimer's disease (AD) [1], where significant impairment of dynamic vasomotor reactivity (DVR) was observed in early-stage AD patients relative to age-matched controls. Milder impairment of DVR was shown in patients with amnestic mild cognitive impairment (MCI) using the same approach in a subsequent study [2]. The advocated approach utilizes subject-specific data-based models of cerebral hemodynamics to quantify the dynamic effects of resting-state changes in arterial blood pressure and end-tidal CO2 (the putative inputs) upon cerebral blood flow velocity (the putative output) measured at the middle cerebral artery via transcranial Doppler (TCD). The obtained input-output models are then used to compute model-based indices of DCA and DVR from model-predicted responses to an input pressure pulse or an input CO2 pulse, respectively. In this paper, we compare these model-based indices of DVR and DCA in 46 amnestic MCI patients, relative to 20 age-matched controls, using TCD measurements with their counterparts using Near-Infrared Spectroscopy (NIRS) measurements of blood oxygenation at the lateral prefrontal cortex in 43 patients and 22 age-matched controls. The goal of the study is to assess whether NIRS measurements can be used instead of TCD measurements to obtain model-based physiomarkers with comparable diagnostic utility. The results corroborate this view in terms of the ability of either output to yield model-based physiomarkers that can differentiate the group of aMCI patients from age-matched healthy controls.

Computerized Cognitive Screen (CoCoSc): A Self-Administered Computerized Test for Screening for Cognitive Impairment in Community Social Centers. - Wong, Adrian; Fong, Ching-Hang; Mok, Vincent Chung-Tong; Leung, Kam-Tat; Tong, Raymond Kai-Yu (J Alzheimers Dis, 2017)
BACKGROUND: Computerized cognitive tests may serve as a preliminary, low-cost method to identify individuals with suspected cognitive impairment in the community. OBJECTIVE: To develop a self-administered computerized test, namely the "Computerized Cognitive Screen (CoCoSc), Hong Kong version", for screening of individuals with cognitive impairment (CI) in community settings. METHODS: The CoCoSc is a 15-min computerized cognitive screen covering memory, executive functions, orientation, attention and working memory, and prospective memory administered on a touchscreen computer. Individuals with CI and cognitively normal controls were administered the CoCoSc and the Montreal Cognitive Assessment (MoCA). Validity of the CoCoSc was assessed based on the relationship with the MoCA using Pearson correlation. Receiver operating characteristic curve (ROC) was used to examine the ability of the CoCoSc to differentiate CI from controls. RESULTS: Fifty-nine individuals with CI and 101 controls were recruited. Seventy-five (46.9%) participants had ≤6 years of education. Performance on the CoCoSc differed between normal and CI groups in both low and high education subgroups. Total scores of the CoCoSc and MoCA were significantly correlated (r = 0.71, p < 0.001). The area under ROC was 0.78, p < 0.001 for the CoCoSc total score in differentiating the CI group from the cognitively normal group. A cut-off of ≤30 on the CoCoSc was associated with a sensitivity of 0.78 and specificity of 0.69. The CoCoSc was well accepted by attendees of community social centers. CONCLUSION: The CoCoSc is a promising computerized cognitive screen for self-administration in community social centers. It is feasible for testing individuals with high or low education levels.

Consecutive Analysis of BACE1 Function on Developing and Developed Neuronal Cells. - Kamikubo, Yuji; Takasugi, Nobumasa; Niisato, Kazue; Hashimoto, Yoshie; Sakurai, Takashi (J Alzheimers Dis, 2017)
The amyloid-β protein precursor (AβPP) is cleaved by a transmembrane protease termed β-site AβPP cleavage enzyme (BACE1), which is being explored as a target for therapy and prevention of Alzheimer's disease (AD). Although genetic deletion of BACE1 results in abolished amyloid pathology in AD model mice, it also results in neurodevelopmental phenotypes such as hypomyelination and synaptic loss, observed in schizophrenia and autism-like phenotype. These lines of evidence indicate that the inhibition of BACE1 causes adverse side effects during the neurodevelopmental stage. However, the effects of the inhibition of BACE1 activity on already developed neurons remain unclear. Here, we utilized hippocampal slice cultures as an ex vivo model that enabled continuous and long-term analysis for the effect of BACE1 inhibition on neuronal circuits and synapses. Temporal changes in synaptic proteins in hippocampal slices indicated acute synaptic loss, followed by synapse formation and maintenance phases. Long-term BACE1 inhibition in the neurodevelopmental stage caused the loss of synaptic proteins but failed to alter synaptic proteins in the already developed maintenance stage. These data indicate that BACE1 function on synapses is dependent on synaptic developmental stages, and our study provides a useful model to observe the long-term effect of BACE1 activity in the brain, and to evaluate adverse effects of BACE inhibitors.

The Correlation between Inflammatory Biomarkers and Polygenic Risk Score in Alzheimer's Disease. - Morgan, Angharad R; Touchard, Samuel; O'Hagan, Caroline; Sims, Rebecca; Majounie, Elisa; Escott-Price, Valentina; Jones, Lesley; Williams, Julie; Morgan, B Paul (J Alzheimers Dis, 2017)
Plasma biomarkers to aid the early diagnosis of Alzheimer's disease (AD) or to monitor disease progression have long been sought and continue to be widely studied. Biomarkers that correlate with AD polygenic risk score, a measure of the polygenic architecture of the disease and highly predictive of AD status, would be excellent candidates. Therefore, we undertook a preliminary study to assess the association of plasma inflammatory biomarkers with an overall AD polygenic risk score as well as with an inflammation-specific AD polygenic risk score in a sample set of 93 AD cases. We measured five complement biomarkers [complement receptor 1 (CR1), clusterin, complement component 9 (C9), C1 inhibitor (C1inh), terminal complement complex (TCC)] and the benchmark inflammatory marker C-reactive protein (CRP). Plasma clusterin level showed an association with overall AD polygenic risk score, while clusterin, C1inh, and CRP levels each displayed some association with the inflammatory-specific AD polygenic risk score. The results suggest that elevated plasma levels of inflammatory biomarkers, including complement proteins, associate with polygenic risk scores in AD, further strengthening the link between genetic and biomarker disease predictors and indicating a potential role for these markers in disease prediction and patient stratification in AD.

Current Approaches and Clinician Attitudes to the Use of Cerebrospinal Fluid Biomarkers in Diagnostic Evaluation of Dementia in Europe. - Miller, Anne-Marie; Balasa, Mircea; Blennow, Kaj; Gardiner, Mary; Rutkowska, Aleksandra; Scheltens, Philip; Teunissen, Charlotte E; Visser, Pieter Jelle; Winblad, Bengt; Waldemar, Gunhild; Lawlor, Brian (J Alzheimers Dis, 2017)
BACKGROUND: BIOMARKAPD seeks to diminish the barriers associated with the clinical use of cerebrospinal fluid (CSF) biomarker analysis by reducing variation in CSF laboratory methodologies and generating consensus recommendations on their clinical interpretation and application for dementia diagnosis. OBJECTIVE: To examine the disparity in practitioner attitudes and clinical practice relating to the use of CSF biomarkers for dementia diagnosis across Europe. METHODS: Clinical dementia experts were surveyed on the prevalence of national consensus guidelines and analytical reimbursement across Europe, their biomarker platform preferences, lumbar puncture methodologies and application of reference values and cut-offs for CSF analysis. RESULTS: 74% of respondents (total n = 51) use CSF biomarkers in clinical practice and 69% perform lumbar punctures on an outpatient basis. Most use CSF biomarkers to diagnose atypical (84%) and early-onset cases of cognitive impairment (71%) and for the differential diagnosis of other dementias (69%). 82% state they are sufficiently informed about CSF biomarkers yet 61% report a lack of national consensus guidelines on their use for dementia diagnosis. 48% of countries represented do not reimburse clinical CSF analysis costs. 43% report using normal reference ranges derived from publications. CONCLUSION: Variations in attitude and practice relating to CSF biomarkers, widely recognised as barriers to their clinical acceptance, remain evident within and between countries across Europe, even in expert centres. These shortcomings must be addressed by developing consensus guidelines on CSF-related methodologies and their clinical application, to further their use for the diagnostic evaluation of dementia.

Damage to the Frontal Aslant Tract Accounts for Visuo-Constructive Deficits in Alzheimer's Disease. - Serra, Laura; Gabrielli, Giulia Bechi; Tuzzi, Elisa; Spanò, Barbara; Giulietti, Giovanni; Failoni, Virginia; Marra, Camillo; Caltagirone, Carlo; Koch, Giacomo; Cercignani, Mara; Bozzali, Marco (J Alzheimers Dis, 2017)
The frontal aslant tract (FAT) has been described as a bundle connecting the Broca's area to the supplementary motor area (SMA) and the pre-SMA in both hemispheres. The functional properties of this tract and its role in degenerative dementia, such as Alzheimer's disease (AD), still need to be fully clarified. The aim of this study was to explore the microstructural integrity of the FAT in patients with AD and its potential relationship with cognitive functioning. Twenty-three patients with AD and 25 healthy subjects (HS) were enrolled. All subjects underwent cognitive and MRI examination. MRI, including diffusion sequences, was used for probabilistic tractography analysis. We reconstructed individual FATs bilaterally and assessed their microstructural integrity using fractional anisotropy (FA), computed as both mean tract value and voxel-wise using SPM-8. Mean FA values were then used to test for correlations with cognitive measures. Mean tract FA and voxel-wise analyses revealed that patients with AD, compared to HS, had decreased FA in the FAT bilaterally. In addition, positive associations were found between FA in the FATs and patients' performance at tests for constructional praxis and visuospatial logical reasoning. The present results reveal a bilateral damage of FAT in AD patients. The association between FATs' microscopic abnormalities and constructive abilities fits well with the knowledge of a functional involvement of SMA and pre-SMA in movement sequences when executing constructive praxis tasks. The FAT is an associative bundle critically involved in the network sub-serving constructional praxis in patients with AD.

Deficit in Central Auditory Processing as a Biomarker of Pre-Clinical Alzheimer's Disease. - Tuwaig, Miranda; Savard, Mélissa; Jutras, Benoît; Poirier, Judes; Collins, D Louis; Rosa-Neto, Pedro; Fontaine, David; Breitner, John C S (J Alzheimers Dis, 2017)
Prevention of dementia due to Alzheimer's disease (d/AD) requires interventions that slow the disease process prior to symptom onset. To develop such interventions, one needs metrics that assess pre-symptomatic disease progression. Familiar measures of progression include cerebrospinal fluid (CSF) biochemical and imaging analyses, as well as cognitive testing. Changes in the latter can sometimes be difficult to distinguish from effects of "normal" aging. A different approach involves testing of "central auditory processing" (CAP), which enables comprehension of auditory stimuli amidst a distracting background (e.g., conversation in a noisy bar or restaurant). Such comprehension is often impaired in d/AD. Similarly, effortful or diminished auditory comprehension is sometimes reported by cognitively healthy elders, raising the possibility that CAP deficit may be a marker of pre-symptomatic AD. In 187 cognitively and physically healthy members of the aging, AD family history-positive PREVENT-AD cohort, we therefore evaluated whether CAP deficits were associated with known markers of AD neurodegeneration. Such markers included CSF tau concentrations and magnetic resonance imaging volumetric and cortical thickness measures in key AD-related regions. Adjusting for age, sex, education, pure-tone hearing, and APOEɛ4 status, we observed a persistent relationship between CAP scores and CSF tau levels, entorhinal and hippocampal cortex volumes, cortical thickness, and deficits in cognition (Repeatable Battery for Assessment of Neuropsychological Status total score, and several of its index scales). These cross-sectional observations suggest that CAP may serve as a novel metric for pre-symptomatic AD pathogenesis. They are therefore being followed up longitudinally with larger samples.

Deleterious Effect of Butyrylcholinesterase K-Variant in Donepezil Treatment of Mild Cognitive Impairment. - Sokolow, Sophie; Li, Xiaohui; Chen, Lucia; Taylor, Kent D; Rotter, Jerome I; Rissman, Robert A; Aisen, Paul S; Apostolova, Liana G (J Alzheimers Dis, 2017)
BACKGROUND: Donepezil is an acetylcholinesterase inhibitor frequently prescribed for the treatment of mild cognitive impairment (MCI) though not approved by the Food and Drug Administration for this indication. In Alzheimer's disease, butyrylcholinesterase (BChE) activity increases with disease progression and may replace acetylcholinesterase function. The most frequent polymorphism of BChE is the K-variant, which is associated with lower acetylcholine-hydrolyzing activity. BChE-K polymorphism has been studied in Alzheimer's disease progression and donepezil therapy, and has led to contradictory results. OBJECTIVES: To determine whether BChE-K genotype predicts response to donepezil in MCI. METHODS: We examined the association between BChE-K genotype and changes in cognitive function using the data collected during the ADCS vitamin E/donepezil clinical trial in MCI. RESULTS: We found significant interactions between BChE-K genotype and the duration of donepezil treatment, with increased changes in MMSE and CDR-SB scores compared to the common allele in MCI subjects treated during the 3-year trial. We found faster MMSE decline and CDR-SB rise in BChE-K homozygous individuals treated with donepezil compared to the untreated. We observed similar interactions between BChE-K genotype and steeper changes in MMSE and CDR-SB scores in APOE4 carriers treated with donepezil compared to controls. CONCLUSION: BChE-K polymorphisms are associated with deleterious changes in cognitive decline in MCI patients treated with donepezil for 3 years. This indicates that BChE-K genotyping should be performed to help identify subsets of subjects at risk for donepezil therapy, like those carrying APOE4. BChE-K and APOE4 carriers should not be prescribed off-label donepezil therapy for MCI management.

Detecting At-Risk Alzheimer's Disease Cases. - Fladby, Tormod; Pålhaugen, Lene; Selnes, Per; Waterloo, Knut; Bråthen, Geir; Hessen, Erik; Almdahl, Ina Selseth; Arntzen, Kjell-Arne; Auning, Eirik; Eliassen, Carl Fredrik; Espenes, Ragna; Grambaite, Ramune; et al. (J Alzheimers Dis, 2017)
While APOEɛ4 is the major genetic risk factor for Alzheimer's disease (AD), amyloid dysmetabolism is an initial or early event predicting clinical disease and is an important focus for secondary intervention trials. To improve identification of cases with increased AD risk, we evaluated recruitment procedures using pathological CSF concentrations of Aβ42 (pAβ) and APOEɛ4 as risk markers in a multi-center study in Norway. In total, 490 subjects aged 40-80 y were included after response to advertisements and media coverage or memory clinics referrals. Controls (n = 164) were classified as normal controls without first-degree relatives with dementia (NC), normal controls with first-degree relatives with dementia (NCFD), or controls scoring below norms on cognitive screening. Patients (n = 301) were classified as subjective cognitive decline or mild cognitive impairment. Subjects underwent a clinical and cognitive examination and MRI according to standardized protocols. Core biomarkers in CSF from 411 and APOE genotype from 445 subjects were obtained. Cases (both self-referrals (n = 180) and memory clinics referrals (n = 87)) had increased fractions of pAβ and APOEɛ4 frequency compared to NC. Also, NCFD had higher APOEɛ4 frequencies without increased fraction of pAβ compared to NC, and cases recruited from memory clinics had higher fractions of pAβ and APOEɛ4 frequency than self-referred. This study shows that memory clinic referrals are pAβ enriched, whereas self-referred and NCFD cases more frequently are pAβ negative but at risk (APOEɛ4 positive), suitable for primary intervention.

Development of Nasal Lipid Nanocarriers Containing Curcumin for Brain Targeting. - Vaz, Gustavo Richter; Hädrich, Gabriela; Bidone, Juliana; Rodrigues, Jamile Lima; Falkembach, Mariana Corrêa; Putaux, Jean-Luc; Hort, Mariana Appel; Monserrat, José Maria; Varela Junior, Antônio Sergio; Teixeira, Helder Ferreira; Muccillo-Baisch, Ana Luiza; Horn, Ana Paula; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Curcumin (CUR) has properties that can be useful for the treatment of Alzheimer's disease. Such properties are the inhibition of amyloid-β-protein (Aβ) aggregation, Aβ-induced inflammation, and activities of β-secretase and acetylcholinesterase. However, previous studies have revealed that CUR exhibited low bioavailability and difficulties in reaching the brain. OBJECTIVE: To overcome such drawbacks, this study aims at developing nasal lipid nanocarriers loaded with CUR to effectively target the brain. METHODS: The lipid nanocarriers (NE) were prepared using the hot solvent diffusion associated with the phase inversion temperature methods. Physico-chemical and morphological characterizations and in vitro drug release of the nanocarriers were carried out. The CUR permeation/retention was analyzed in Franz-type diffusion cell using porcine nasal mucosa. Confocal laser scan and histopathological studies were also performed. RESULTS: The results showed that the NE sizes ranged between 18 nm and 44 nm with negative zeta potential. The CUR content ranged from 0.24 to 1.50 mg/mL with an encapsulation efficiency of 99%. The profiles of CUR release indicated a biphasic kinetics. CUR-NE permeation across the porcine nasal mucosa was higher when compared to free CUR. These results have also been validated through an analysis on a confocal microscopy. In addition, no toxicity on the nasal mucosa has been observed in a histopathological analysis. CONCLUSION: These results suggest that it is possible to develop NEs with a high content of CUR and small particle size. Such an encapsulation increases the potential of CUR permeation across the porcine nasal mucosa.

Discovery and Confirmation of Diagnostic Serum Lipid Biomarkers for Alzheimer's Disease Using Direct Infusion Mass Spectrometry. - Anand, Swati; Barnes, Justin M; Young, Sydney A; Garcia, Diana M; Tolley, H Dennis; Kauwe, John S K; Graves, Steven W (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a neurodegenerative disorder lacking early biochemical diagnosis and treatment. Lipids have been implicated in neurodegenerative disorders including AD. A shotgun lipidomic approach was undertaken to determine if lipid biomarkers exist that can discriminate AD cases from controls. The discovery study involved sera from 29 different stage AD cases and 32 controls. Lipid extraction was performed using organic solvent and the samples were directly infused into a time-of-flight mass spectrometer. Differences between AD cases and controls were detected with 87 statistically significant lipid candidate markers found. These potential lipid markers were reevaluated in a second confirmatory study involving 27 cases and 30 controls. Of the 87 candidates from the first study, 35 continued to be statistically significant in the second confirmatory set. Tandem MS studies were performed and almost all confirmed markers were characterized and classified. Using a Bayesian lasso probit regression model on the confirmed markers, a multi-marker set with AUC = 0.886 was developed comparing all stages of AD with controls. Additionally, using confirmed biomarkers, multi-marker sets with AUCs >0.90 were developed for each specific AD Clinical Dementia Rating versus controls, including the earliest stage of AD. More conservative and likely more realistic statistical analyses still found multi-marker sets that appeared useful in diagnosing AD. Finally, using ordinal modeling a set of markers was developed that staged AD accurately 70% of the time, p = 0.0079. These results suggest that these serum lipidomic biomarkers may help diagnose and perhaps even stage AD.

Dissociable Effects of Aging and Mild Cognitive Impairment on Bottom-Up Audiovisual Integration. - Festa, Elena K; Katz, Andrew P; Ott, Brian R; Tremont, Geoffrey; Heindel, William C (J Alzheimers Dis, 2017)
Effective audiovisual sensory integration involves dynamic changes in functional connectivity between superior temporal sulcus and primary sensory areas. This study examined whether disrupted connectivity in early Alzheimer's disease (AD) produces impaired audiovisual integration under conditions requiring greater corticocortical interactions. Audiovisual speech integration was examined in healthy young adult controls (YC), healthy elderly controls (EC), and patients with amnestic mild cognitive impairment (MCI) using McGurk-type stimuli (providing either congruent or incongruent audiovisual speech information) under conditions differing in the strength of bottom-up support and the degree of top-down lexical asymmetry. All groups accurately identified auditory speech under congruent audiovisual conditions, and displayed high levels of visual bias under strong bottom-up incongruent conditions. Under weak bottom-up incongruent conditions, however, EC and amnestic MCI groups displayed opposite patterns of performance, with enhanced visual bias in the EC group and reduced visual bias in the MCI group relative to the YC group. Moreover, there was no overlap between the EC and MCI groups in individual visual bias scores reflecting the change in audiovisual integration from the strong to the weak stimulus conditions. Top-down lexicality influences on visual biasing were observed only in the MCI patients under weaker bottom-up conditions. Results support a deficit in bottom-up audiovisual integration in early AD attributable to disruptions in corticocortical connectivity. Given that this deficit is not simply an exacerbation of changes associated with healthy aging, tests of audiovisual speech integration may serve as sensitive and specific markers of the earliest cognitive change associated with AD.

Dissociating Normal Aging from Alzheimer's Disease: A View from Cognitive Neuroscience. - Toepper, Max (J Alzheimers Dis, 2017)
Both normal aging and Alzheimer's disease (AD) are associated with changes in cognition, grey and white matter volume, white matter integrity, neural activation, functional connectivity, and neurotransmission. Obviously, all of these changes are more pronounced in AD and proceed faster providing the basis for an AD diagnosis. Since these differences are quantitative, however, it was hypothesized that AD might simply reflect an accelerated aging process. The present article highlights the different neurocognitive changes associated with normal aging and AD and shows that, next to quantitative differences, there are multiple qualitative differences as well. These differences comprise different neurocognitive dissociations as different cognitive deficit profiles, different weights of grey and white matter atrophy, and different gradients of structural decline. These qualitative differences clearly indicate that AD cannot be simply described as accelerated aging process but on the contrary represents a solid entity.

Does Functional Connectivity Provide a Marker for Cognitive Rehabilitation Effects in Alzheimer's Disease? An Interventional Study. - Ochmann, Sina; Dyrba, Martin; Grothe, Michel J; Kasper, Elisabeth; Webel, Steffi; Hauenstein, Karlheinz; Teipel, Stefan J (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive rehabilitation (CR) is a cognitive intervention for patients with Alzheimer's disease (AD) that aims to maintain everyday competences. The analysis of functional connectivity (FC) in resting-state functional MRI has been used to investigate the effects of cognitive interventions. OBJECTIVES: We evaluated the effect of CR on the default mode network FC in a group of patients with mild AD, compared to an active control group. METHODS: We performed a three-month interventional study including 16 patients with a diagnosis of AD. The intervention group (IG) consisted of eight patients, performing twelve sessions of CR. The active control group (CG) performed a standardized cognitive training. We used a seed region placed in the posterior cingulate cortex (PCC) for FC analysis, comparing scans acquired before and after the intervention. Effects were thresholded at a significance of p < 0.001 (uncorrected) and a minimal cluster size of 50 voxels. RESULTS: The interaction of group by time showed a higher increase of PCC connectivity in IG compared to CG in the bilateral cerebellar cortex. CG revealed widespread, smaller clusters of higher FC increase compared with IG. Across all participants, an increase in quality of life was associated with connectivity increase over time in the bilateral precuneus. CONCLUSIONS: CR showed an effect on the FC of the DMN in the IG. These effects need further study in larger samples to confirm if FC analysis may suit as a surrogate marker for the effect of cognitive interventions in AD.

Down Syndrome, Partial Trisomy 21, and Absence of Alzheimer's Disease: The Role of APP. - Doran, Eric; Keator, David; Head, Elizabeth; Phelan, Michael J; Kim, Ron; Totoiu, Minodora; Barrio, Jorge R; Small, Gary W; Potkin, Steven G; Lott, Ira T (J Alzheimers Dis, 2017)
Overexpression of the amyloid precursor protein (APP) gene on chromosome 21 in Down syndrome (DS) has been linked to increased brain amyloid levels and early-onset Alzheimer's disease (AD). An elderly man with phenotypic DS and partial trisomy of chromosome 21 (PT21) lacked triplication of APP affording an opportunity to study the role of this gene in the pathogenesis of dementia. Multidisciplinary studies between ages 66-72 years comprised neuropsychological testing, independent neurological exams, amyloid PET imaging with 11C-Pittsburgh compound-B (PiB), plasma amyloid-β (Aβ) measurements, and a brain autopsy examination. The clinical phenotype was typical for DS and his intellectual disability was mild in severity. His serial neuropsychological test scores showed less than a 3% decline as compared to high functioning individuals with DS who developed dementia wherein the scores declined 17-28% per year. No dementia was detected on neurological examinations. On both PiB-PET scans, the patient with PT21 had lower PiB standard uptake values than controls with typical DS or sporadic AD. Plasma Aβ42 was lower than values for demented or non-demented adults with DS. Neuropathological findings showed only a single neuritic plaque and neurofibrillary degeneration consistent with normal aging but not AD. Taken together the findings in this rare patient with PT21 confirm the obligatory role of APP in the clinical, biochemical, and neuropathological findings of AD in DS.

Dual Mechanism of Toxicity for Extracellular Injection of Tau Oligomers versus Monomers in Human Tau Mice. - Manassero, Giusi; Guglielmotto, Michela; Monteleone, Debora; Vasciaveo, Valeria; Butenko, Olena; Tamagno, Elena; Arancio, Ottavio; Tabaton, Massimo (J Alzheimers Dis, 2017)
The mechanism of tau toxicity is still unclear. Here we report that recombinant tau oligomers and monomers, intraventricularly injected in mice with a pure human tau background, foster tau pathology through different mechanisms. Oligomeric forms of tau alter the conformation of tau in a paired helical filament-like manner. This effect occurs without tau hyperphosphorylation as well as activation of specific kinases, suggesting that oligomers of tau induce tau assembly through a nucleation effect. Monomers, in turn, induce neurodegeneration through a calpain-mediated tau cleavage that leads to accumulation of a 17 kDa neurotoxic peptide and induction of apoptotic cell death.

Early Detection of Learning Difficulties when Confronted with Novel Information in Preclinical Alzheimer's Disease Stage 1. - Tort-Merino, Adrià; Valech, Natalia; Peñaloza, Claudia; Grönholm-Nyman, Petra; León, María; Olives, Jaume; Estanga, Ainara; Ecay-Torres, Mirian; Fortea, Juan; Martínez-Lage, Pablo; Molinuevo, José L; Laine, Matti; et al. (J Alzheimers Dis, 2017)
We employed a highly demanding experimental associative learning test (the AFE-T) to explore memory functioning in Preclinical Alzheimer's Disease stage 1 (PreAD-1) and stage 2 (PreAD-2). The task consisted in the learning of unknown object/name pairs and our comprehensive setup allowed the analysis of learning curves, immediate recall, long-term forgetting rates at one week, three months, and six months, and relearning curves. Forty-nine cognitively healthy subjects were included and classified according to the presence or absence of abnormal CSF biomarkers (Control, n = 31; PreAD-1, n = 14; PreAD-2, n = 4). Control and PreAD-1 performances on the experimental test were compared by controlling for age and education. These analyses showed clear learning difficulties in PreAD-1 subjects (F = 6.98; p = 0.01). Between-group differences in long-term forgetting rates were less notable, reaching statistical significance only for the three-month cued forgetting rate (F = 4.83; p = 0.03). Similarly, relearning sessions showed only statistical trends between the groups (F = 3.22; p = 0.08). In the whole sample, significant correlations between CSF Aβ42/tau ratio and the AFE-T were found, both in the total learning score (r = 0.52; p < 0.001) and in the three-month cued forgetting rate (r = -0.38; p < 0.01). Descriptive subanalyses involving PreAD-2 suggested greater learning and recall difficulties in these subjects when compared with the PreAD-1 group. The present results suggest that explicit learning difficulties when binding information could be one of the earliest signs of the future emergence of episodic memory difficulties on the Alzheimer's disease continuum. Our findings indicate that the AFE-T is a sensitive test, capable of detecting subtle memory difficulties in PreAD-1.

Effect of APOE ε4 Genotype on Metabolic Biomarkers in Aging and Alzheimer's Disease. - Morris K, Jill; Uy, Roxanne Adeline Z; Vidoni, Eric D; Wilkins, Heather M; Archer, Ashley E; Thyfault, John P; Miles, John M; Burns, Jeffrey M (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) may have heterogeneous pathophysiological underpinnings, with risk factors including apolipoprotein rmvarep4 (APOE4) genotype and insulin resistance. We hypothesized that distinct phenotypes exist within AD. We examined APOE4 and metabolic biomarkers in 338 subjects (n = 213 nondemented (ND), n = 125 AD). We further characterized steady state free fatty acid (FFA) levels in a subset of 45 participants who had also participated in a hyperinsulinemic-euglycemic clamp. Insulin resistance (HOMA-IR) was elevated in AD versus ND (p = 0.04) and in APOE4 noncarriers versus carriers (p < 0.01). This was driven by increased fasting insulin in AD versus ND (p < 0.01) and in APOE4 non-carriers versus carriers (p = 0.01). Fasting glucose was not different. In subjects who underwent a clamp, there was a group x genotype interaction on FFA levels during hyperinsulinemia (p = 0.03). APOE4 non-carriers with AD had higher FFA levels, while APOE4 carriers with AD exhibited lower FFA levels. Metabolic dysfunction is overrepresented in individuals with AD dementia who do not carry the APOE4 allele. This suggests that important subsets of AD phenotypes may exist that diverge metabolically.

Effect of Spinal Manometers on Cerebrospinal Fluid Amyloid-β Concentration. - Toombs, Jamie; Foiani, Martha S; Paterson, Ross W; Heslegrave, Amanda; Wray, Selina; Schott, Jonathan M; Fox, Nick C; Lunn, Michael P; Blennow, Kaj; Zetterberg, Henrik (J Alzheimers Dis, 2017)
The effect of spinal manometers on cerebrospinal fluid (CSF) amyloid-β (Aβ) concentration was investigated. Pooled human CSF samples were divided in two, one half passed through a manometer into a collection tube, the other transferred directly to a collection tube. CSF was analyzed for Aβ38/40/42 using an electrochemiluminescence immunoassay. Relative to control, use of a manometer decreased Aβ38/40/42 concentration by 5.6% (±1.5SE), 4.4% (±1.7SE), and 4.3% (±2.4SE), respectively. The ratios of Aβ42 :40, Aβ42 :38, and Aβ40 :38 were not affected by manometer treatment. Factors which artificially lower CSF Aβ concentrations are relevant to clinical diagnosis for AD and study design.

The Effect of the Association between Donepezil and Choline Alphoscerate on Behavioral Disturbances in Alzheimer's Disease: Interim Results of the ASCOMALVA Trial. - Carotenuto, Anna; Rea, Raffaele; Traini, Enea; Fasanaro, Angiola Maria; Ricci, Giovanna; Manzo, Valentino; Amenta, Francesco (J Alzheimers Dis, 2017)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) are a group of psychological reactions, psychiatric symptoms, and behaviors commonly found in Alzheimer's disease (AD). Four clusters of BPSD have been described: mood disorders (depression, anxiety, and apathy), psychotic symptoms (delusions and hallucinations), aberrant motor behaviors (pacing, wandering, and other purposeless behaviors), and inappropriate behaviors (agitation, disinhibition, and euphoria). Most of them are attributed to acetylcholine deficiency. OBJECTIVE: To evaluate if a higher amount of acetylcholine obtained by associating donepezil and choline alphoscerate might have a favorable effect on BPSD. METHODS: BPSD were measured at baseline and after 24 months in 113 mild/moderate AD patients, included in the double-blind randomized trial ASCOMALVA, by the Neuropsychiatric Inventory (NPI). Two matched groups were compared: group A treated with donepezil (10 mg/day) plus choline alphoscerate (1200 mg/day), and group B treated with donepezil (10 mg/day) plus placebo. RESULTS: Data of NPI revealed a significant decrease of BPSD severity and distress of the caregiver in patients of group A compared with group B. Mood disorders (depression, anxiety and apathy) were significantly decreased in subjects treated with donepezil and choline alphoscerate, while their severity and frequency was increased in the other group. CONCLUSIONS: Patients treated with donepezil plus choline alphoscerate showed a lower level of behavioral disturbances than subjects treated with donepezil only, suggesting that the association can have beneficial effects.

The Effect of Traumatic Brain Injury History with Loss of Consciousness on Rate of Cognitive Decline Among Older Adults with Normal Cognition and Alzheimer's Disease Dementia. - Tripodis, Yorghos; Alosco, Michael L; Zirogiannis, Nikolaos; Gavett, Brandon E; Chaisson, Christine; Martin, Brett; McClean, Michael D; Mez, Jesse; Kowall, Neil; Stern, Robert A (J Alzheimers Dis, 2017)
Traumatic brain injury (TBI) is thought to be a risk factor for dementia, including dementia due to Alzheimer's disease (AD). However, the influence of TBI history on the neuropsychological course of AD is unknown and, more broadly, the effect of TBI history on age-related cognitive change is poorly understood. We examined the relationship between history of TBI with loss of consciousness (LOC) history and cognitive change in participants with normal cognition and probable AD, stratified by APOEɛ4 allele status. The sample included 706 participants (432 with normal cognition; 274 probable AD) from the National Alzheimer's Coordinating Center (NACC) dataset that completed the Uniform Data Set evaluation between 2005 and 2014. Normal and probable AD participants with a history of TBI were matched to an equal number of demographically and clinically similar participants without a TBI history. In this dataset, TBI with LOC was defined as brain trauma with brief or extended unconsciousness. For the normal and probable AD cohorts, there was an average of 3.2±1.9 and 1.8±1.1 years of follow-up, respectively. 30.8% of the normal cohort were APOEɛ4 carriers, whereas 70.8% of probable AD participants were carriers. Mixed effects regressions showed TBI with LOC history did not affect rates of cognitive change in APOEɛ4 carriers and non-carriers. Findings from this study suggest that TBI with LOC may not alter the course of cognitive function in older adults with and without probable AD. Future studies that better characterize TBI (e.g., severity, number of TBIs, history of subconconcussive exposure) are needed to clarify the association between TBI and long-term neurocognitive outcomes.

Effects of a DJ-1-Binding Compound on Spatial Learning and Memory Impairment in a Mouse Model of Alzheimer's Disease. - Kitamura, Yoshihisa; Inden, Masatoshi; Kimoto, Yasuto; Takata, Kazuyuki; Yanagisawa, Daijiro; Hijioka, Masanori; Ashihara, Eishi; Tooyama, Ikuo; Shimohama, Shun; Ariga, Hiroyoshi (J Alzheimers Dis, 2017)
Previously, DJ-1 modulator UCP0054278/comp-B was identified by virtual screening, where comp-B interacts with DJ-1 to produce antioxidant and neuroprotective responses in Parkinson's disease models. However, the effect of comp-B in an in vivo Alzheimer's disease (AD) model is yet undetermined. Thus, we examined the effect of comp-B on spatial learning, memory, and amyloid-β (Aβ) clearance in a transgenic mouse model of AD. We found that comp-B resolved the cognitive deficits, reduced insoluble Aβ42 levels, and prevented the degeneration of synaptic functions, thereby suggesting that comp-B may become a major compound for AD treatment.

The Effects of Cortical Hypometabolism and Hippocampal Atrophy on Clinical Trajectories in Mild Cognitive Impairment with Suspected Non-Alzheimer's Pathology: A Brief Report. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Caravaggio, Fernando; Shinagawa, Shunichiro; Iwata, Yusuke; Gerretsen, Philip; Kim, Julia; Takeuchi, Hiroyoshi; Patel, Raihaan; Chakravarty, M Mallar; Strafella, Antonio; et al. (J Alzheimers Dis, 2017)
The clinical and structural trajectories of suspected non-Alzheimer' pathology (SNAP) remain elusive due to its heterogeneous etiology. Baseline and longitudinal clinical (global cognition, daily functioning, symptoms of dementia, and learning memory) and hippocampal volume trajectories over two years were compared between patients with amnestic mild cognitive impairment (aMCI) with SNAP with reduced hippocampal volumes (SNAP+HIPPO) and aMCI patients with SNAP without reduced hippocampal volumes. SNAP+HIPPO showed overall worse baseline cognitive functions. Longitudinally, SNAP+HIPPO showed faster deterioration of clinical symptoms of dementia. Having both hippocampal atrophy and cortical hypometabolism without amyloid pathology may exacerbate symptoms of dementia in aMCI.

Effects of Exercise on Cognitive Function in Older People with Dementia: A Randomized Controlled Trial. - Toots, Annika; Littbrand, Håkan; Boström, Gustaf; Hörnsten, Carl; Holmberg, Henrik; Lundin-Olsson, Lillemor; Lindelöf, Nina; Nordström, Peter; Gustafson, Yngve; Rosendahl, Erik (J Alzheimers Dis, 2017)
BACKGROUND: Although physical exercise has been suggested to influence cognitive function, previous exercise studies show inconsistent results in people with dementia. OBJECTIVES: To investigate effects of exercise on cognitive function in people with dementia. METHOD: The Umeå Dementia and Exercise (UMDEX) study, a cluster-randomized controlled trial, was set in 16 nursing homes in Umeå, Sweden. One hundred-and-forty-one women and 45 men with dementia; mean age of 85 y and mean Mini-Mental State Examination (MMSE) score of 15, were randomized to a High-Intensity Functional Exercise program or a seated attention control activity. Blinded assessors measured global cognitive function using the MMSE and the Alzheimer's disease Assessment Scale - Cognitive subscale (ADAS-Cog), and executive function using Verbal fluency (VF) at baseline and 4 months (directly after intervention completion), and MMSE and VF at 7 months. RESULTS: Linear mixed models showed no between-group effects in mean difference from baseline (95% confidence intervals, CI) at 4 months in MMSE (-0.27; 95% CI -1.4 to 0.87, p = 0.644), ADAS-Cog (-1.04, 95% CI -4 to 1.92, p = 0.491), or VF (-0.53, 95% CI -1.42 to 0.35, p = 0.241) or at 7 months in MMSE (-1.15, 95% CI -2.32 to 0.03, p = 0.056) or VF (-0.18, 95% CI -1.09 to 0.74, p = 0.707). CONCLUSION: A 4-month, high-intensity functional exercise program had no superior effects on global cognition or executive function in people with dementia living in nursing homes when compared with an attention control activity.

The Effects of Gene Mutations on Default Mode Network in Familial Alzheimer's Disease. - Li, Xiaozhen; Westman, Eric; Thordardottir, Steinunn; Ståhlbom, Anne Kinhult; Almkvist, Ove; Blennow, Kaj; Wahlund, Lars-Olof; Graff, Caroline (J Alzheimers Dis, 2017)
Familial Alzheimer's disease (FAD) mutations have very high penetrance but age at onset and rate of disease progression differ. Neuroimaging and cerebrospinal fluid (CSF) examinations in mutation carriers (MCs) may provide an opportunity to identify early biomarkers that can be used to track disease progression from presymptomatic to the dementia stages of disease. The default mode network (DMN) is a resting state neuronal network composed of regions known to associate with amyloid deposition in AD. We hypothesized that functional connectivity in the DMN might change at pre-clinical stages in FAD MCs and correlate with changes in CSF biomarkers as a consequence of AD brain pathology. To test the hypothesis, we compared the functional connectivity in DMN between pre-MCs/MCs and non-carriers (NCs). No significant differences between pre-MCs and NCs were observed. When comparing all MCs with NCs, significant decreased functional connectivity in the right inferior parietal lobule, right precuneus, and left posterior cingulate cortex were found. We also found statistically significant correlations between CSF amyloid-β 42 and tau protein levels and average Z-score, a resting-state functional MRI measurement reflecting the degree of the correlation between a given voxel's time courses and the time courses corresponding to DMN, from the region with statistical difference. The observed disruption of DMN and pathological levels of AD CSF-biomarkers in FAD MCs are similar to the changes described in sporadic AD, which give further support that amyloid and tau pathology impairs neuronal and synaptic function.

The Effects of Meditation on Grey Matter Atrophy and Neurodegeneration: A Systematic Review. - Last, Nicole; Tufts, Emily; Auger, Leslie E (J Alzheimers Dis, 2017)
The present systematic review is based on the premise that a variety of neurodegenerative diseases are accompanied by grey matter atrophy in the brain and meditation may impact this. Given that age is a major risk factor for many of these progressive and neurodegenerative diseases and that the percentage of the population over the age of 65 is quickly increasing, there is an obvious need for prompt treatment and prevention advances in research. As there is currently no cure for Alzheimer's disease and other neurodegenerative diseases, many are seeking non-pharmacological treatment options in attempts to offset the disease-related cognitive and functional declines. On the basis of a growing body of research suggesting that meditation is effective in increasing grey matter volume in healthy participants, this paper systematically reviewed the literature regarding the effects of meditation on restoring grey matter volume in healthy individuals and those affected by neurodegeneration. This review searched PubMed, CINAHL, and APA PsycNET to identify original studies that included MRI imaging to measure grey matter volume in meditators and post-mindfulness-based intervention participants compared to controls. Thirteen studies were considered eligible for review and involved a wide variety of meditation techniques and included participants with and without cognitive impairment. All studies reported significant increases in grey matter volume in the meditators/intervention group, albeit in assorted regions of the brain. Limited research exists on the mechanisms through which meditation affects disease-related neurodegeneration, but preliminary evidence suggests that it may offset grey matter atrophy.

Effects of Multiple Genetic Loci on Age at Onset in Frontotemporal Dementia. - Ferrari, Raffaele; Grassi, Mario; Graziano, Francesca; Palluzzi, Fernando; Archetti, Silvana; Bonomi, Elisa; Bruni, Amalia C; Maletta, Raffaele G; Bernardi, Livia; Cupidi, Chiara; Colao, Rosanna; Rainero, Innocenzo; et al. (J Alzheimers Dis, 2017)
In frontotemporal dementia (FTD), age at disease onset (AAO) is unpredictable in both early and late-onset cases; AAO variability is found even in autosomal dominant FTD. The present study was aimed at identifying genetic modifiers modulating AAO in a large cohort of Italian FTD patients. We conducted an association analysis on 411 FTD patients, belonging to 7 Italian Centers, and for whom AAO was available. Population structure was evaluated by principal component analysis to infer continuous axes of genetic variation, and single linear regression models were applied. A genetic score (GS) was calculated on the basis of suggestive single nucleotide polymorphisms (SNPs) found by association analyses. GS showed genome-wide significant slope decrease by -3.86 (95% CI: -4.64 to -3.07, p < 2×10-16) per standard deviation of the GS for 6 SNPs mapping to genes involved in neuronal development and signaling, axonal myelinization, and glutamatergic/GABA neurotransmission. An increase of the GS was associated with a decrease of the AAO. Our data indicate that there is indeed a genetic component that underpins and modulates up to 14.5% of variability of AAO in Italian FTD. Future studies on genetic modifiers in FTD are warranted.

Effects of Regular and Long-Acting Insulin on Cognition and Alzheimer's Disease Biomarkers: A Pilot Clinical Trial. - Craft, Suzanne; Claxton, Amy; Baker, Laura D; Hanson, Angela J; Cholerton, Brenna; Trittschuh, Emily H; Dahl, Deborah; Caulder, Erin; Neth, Bryan; Montine, Thomas J; Jung, Youngkyoo; Maldjian, Joseph; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Long acting insulin detemir administered intranasally for three weeks enhanced memory for adults with Alzheimer's disease dementia (AD) or amnestic mild cognitive impairment (MCI). The investigation of longer-term administration is necessary to determine whether benefits persist, whether they are similar to benefits provided by regular insulin, and whether either form of insulin therapy affects AD biomarkers. OBJECTIVE: The present study aimed to determine whether four months of treatment with intranasal insulin detemir or regular insulin improves cognition, daily functioning, and AD biomarkers for adults with MCI or AD. METHODS: This randomized, double-blind, placebo-controlled trial included an intent-to-treat sample consisting of 36 adults diagnosed with MCI or mild to moderate AD. Participants received placebo (n = 12), 40 IU of insulin detemir (n = 12), or 40 IU of regular insulin (n = 12) daily for four months, administered with a nasal delivery device. A cognitive battery was administered at baseline and after two and four months of treatment. MRI was administered for all participants and lumbar puncture for a subset (n = 20) at baseline and four months. The primary outcome was change from baseline to four months on a memory composite (sum of Z scores for delayed list and story recall). Secondary outcomes included: global cognition (Alzheimer's Disease Assessment Scale-Cognition), daily functioning (Dementia Severity Rating Scale), MRI volume changes in AD-related regions of interest, and cerebrospinal fluid AD markers. RESULTS: The regular insulin treated group had better memory after two and four months compared with placebo (p < 0.03). No significant effects were observed for the detemir-assigned group compared with the placebo group, or for daily functioning for either group. Regular insulin treatment was associated with preserved volume on MRI. Regular insulin treatment was also associated with reduction in the tau-P181/Aβ42 ratio. CONCLUSION: Future research is warranted to examine the mechanistic basis of treatment differences, and to further assess the efficacy and safety of intranasal insulin.

Effects of Tooth Loss and the Apolipoprotein E ɛ4 Allele on Mild Memory Impairment in the Fujiwara-kyo Study of Japan: A Nested Case-Control Study. - Okamoto, Nozomi; Morikawa, Masayuki; Amano, Nobuko; Yanagi, Motokazu; Takasawa, Shin; Kurumatani, Norio (J Alzheimers Dis, 2017)
BACKGROUND: Several studies have suggested that periodontal disease can exacerbate the pro-inflammatory status of the brain. Tooth loss is one of the alternative evaluation indices of periodontal disease. There are few data on the relationship between tooth loss and memory impairment, depending on the apolipoprotein E (APOE) ɛ4 genotype. OBJECTIVE: To determine if tooth loss is associated with mild memory impairment (MMI) and if this association is modified by the presence of the APOEɛ4 allele. METHODS: A nested case-control study was conducted from 2007 to 2012 in Japan. Five hundred and thirty-seven Japanese subjects aged 65 years and over who were cognitively intact at baseline were analyzed. MMI at follow-up was evaluated. RESULTS: The median number of teeth at baseline was significantly lower in MMI participants (n = 179) than in controls (n = 358) (MMI: median 21.0, interquartile range 10.0-25.0 versus controls: 24.0, 14.0-27.0). After adjustment for demographics, vascular risk factors, and APOEɛ4 allele, the multivariate adjusted odds ratio (OR) of ≤8 teeth was 1.97 (95% confidence interval [CI], 1.13-3.44) compared to 25-32 teeth. Participants with both the presence of at least 1 APOEɛ4 allele and ≤8 teeth had a higher risk of MMI compared with those with neither (OR, 2.82; 95% CI, 1.15-6.91). Those with either risk factor alone did not have a higher risk of MMI. CONCLUSIONS: A lower number of teeth is related to risk of MMI. This may be primarily true for those individuals with an APOEɛ4 allele.

Efficacy and Safety of Donepezil in Chinese Patients with Severe Alzheimer's Disease: A Randomized Controlled Trial. - Jia, Jianping; Wei, Cuibai; Jia, Longfei; Tang, Yi; Liang, Junhua; Zhou, Aihong; Li, Fangyu; Shi, Lu; Doody, Rachelle S (J Alzheimers Dis, 2017)
BACKGROUND: Donepezil has been used worldwide for the treatment of severe Alzheimer's disease (AD). Whether it is also appropriate for severe AD in Chinese patients remains unknown. OBJECTIVE: To determine whether donepezil is effective and tolerable for Chinese patients with severe AD. METHODS: The present study was a 24-week, multicenter, double-blind, randomized, placebo-controlled, parallel-group study conducted at 38 investigational hospitals in China. Patients with severe AD were enrolled in this trial. Patients were randomly assigned in a 1:1 ratio to receive either donepezil or placebo (5 mg for 6 weeks and10 mg for the remaining 18 weeks). The efficacy for donepezil were evaluated by the SIB, the Clinician's Interview-Based Impression of Change-Plus caregiver input (CIBIC-plus) and the MMSE. Safety parameters were monitored throughout. RESULTS: A total of 313 patients included the donepezil (n = 157) and the placebo groups (n = 156). Donepezil group improved more in SIB scores (least squares [LS] mean difference: 4.8, 95% CI 1.56 to 8.08, p = 0.004) and CIBIC-plus scores (drug-placebo difference: -0.4, 95% CI -0.66 to 0.03, p = 0.04) than placebo groups at Week 24. The MMSE scores between drug and placebo groups did not differ significantly. Twenty-nine patients with serious adverse events (SAEs) were reported in donepezil (n = 11) and placebo groups (n = 18) (p = 0.08). Most SAEs were not considered drug-related. CONCLUSION: Donepezil for 24 weeks was more effective than placebo and showed good safety and tolerability in Chinese patients with severe AD. This study supports utility of the drug in severe stages of AD in the Chinese population.

Efficacy and Safety of Plasma Exchange with 5% Albumin to Modify Cerebrospinal Fluid and Plasma Amyloid-β Concentrations and Cognition Outcomes in Alzheimer's Disease Patients: A Multicenter, Randomized, Controlled Clinical Trial. - Boada, Merce; Anaya, Fernando; Ortiz, Pilar; Olazarán, Javier; Shua-Haim, Joshua R; Obisesan, Thomas O; Hernandez, Isabel; Muñoz, Joan; Buendia, Mar; Alegret, Montserrat; Lafuente, Asunción; Tárraga, Lluís; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Studies conducted in animal models and humans suggest the presence of a dynamic equilibrium of amyloid-β (Aβ) peptide between cerebrospinal fluid (CSF) and plasma compartments. OBJECTIVE: To determine whether plasma exchange (PE) with albumin replacement was able to modify Aβ concentrations in CSF and plasma as well as to improve cognition in patients with mild-moderate Alzheimer's disease (AD). METHODS: In a multicenter, randomized, patient- and rater-blind, controlled, parallel-group, phase II study, 42 AD patients were assigned (1 : 1) to PE treatment or control (sham) groups. Treated patients received a maximum of 18 PE with 5% albumin (Albutein®, Grifols) with three different schedules: two PE/weekly (three weeks), one PE/weekly (six weeks), and one PE/bi- weekly (12 weeks), plus a six-month follow-up period. Plasma and CSF Aβ1-40 and Aβ1-42 levels, as well as cognitive, functional, and behavioral measures were determined. RESULTS: CSF Aβ1-42 levels after the last PE compared to baseline were marginally higher in PE-treated group versus controls (adjusted means of variation: 75.3 versus -45.5 pg/mL; 95% CI: -19.8, 170.5 versus 135.1, 44.2; p = 0.072). Plasma Aβ1-42 levels were lower in the PE-treated group after each treatment period (p < 0.05). Plasma Aβ1-40 levels showed a saw-tooth pattern variation associated with PE. PE-treated patients scored better in the Boston Naming Test and Semantic Verbal Fluency (p < 0.05) throughout the study. Neuropsychiatric Inventory scores were higher in controls during the PE phase (p < 0.05). CONCLUSION: PE with human albumin modified CSF and plasma Aβ1-42 levels. Patients treated with PE showed improvement in memory and language functions, which persisted after PE was discontinued.

Efficacy of Antidepressants for Depression in Alzheimer's Disease: Systematic Review and Meta-Analysis. - Orgeta, Vasiliki; Tabet, Naji; Nilforooshan, Ramin; Howard, Robert (J Alzheimers Dis, 2017)
BACKGROUND: Depression is common in people with Alzheimer's disease (AD) affecting overall outcomes and decreasing quality of life. Although depression in AD is primarily treated with antidepressants, there are few randomized controlled trials (RCTs) assessing efficacy and results have been conflicting. OBJECTIVES: To systematically review evidence on efficacy of antidepressant treatments for depression in AD. METHODS: Systematic review and meta-analysis of double blind RCTs comparing antidepressants versus placebo for depression in AD. We searched MEDLINE, CINAHL, EMBASE, PsycINFO, the Cochrane Controlled Trials Register and on line national and international registers. Primary outcomes were treatment response and depressive symptoms. Secondary outcomes were cognition, acceptability, and tolerability. Risk of bias was also assessed. RESULTS: Seven studies met inclusion criteria. Three compared sertraline with placebo; one compared both sertraline and mirtazapine to placebo; imipramine, fluoxetine, and clomipramine were evaluated in one study each. In terms of response to treatment (6 studies, 297 patients treated with antidepressants and 223 with placebo), no statistically significant difference between antidepressants and placebo was found (odds ratio (OR) 1.95, 95% CI 0.97-3.92). We found no significant drug-placebo difference for depressive symptoms (5 studies, 311 patients, SMD -0.13; 95% CI -0.49 to 0.24). Overall quality of the evidence was moderate because of methodological limitations in studies and the small number of trials. CONCLUSION: Despite the importance of depression in people with AD, few RCTs are available on efficacy of antidepressants, limiting clear conclusions of their potential role. There is a need for further high quality RCTs.

Egocentric versus Allocentric Spatial Memory in Behavioral Variant Frontotemporal Dementia and Alzheimer's Disease. - Tu, Sicong; Spiers, Hugo J; Hodges, John R; Piguet, Olivier; Hornberger, Michael (J Alzheimers Dis, 2017)
BACKGROUND: Diagnosis of behavioral variant frontotemporal dementia (bvFTD) can be challenging, in particular when patients present with significant memory problems, which can increase the chance of a misdiagnosis of Alzheimer's disease (AD). Growing evidence suggests spatial orientation is a reliable cognitive marker able to differentiate these two clinical syndromes. OBJECTIVE: Assess the integrity of egocentric and allocentric heading orientation and memory in bvFTD and AD, and their clinical implications. METHOD: A cohort of 22 patients with dementia (11 bvFTD; 11 AD) and 14 healthy controls were assessed on the virtual supermarket task of spatial orientation and a battery of standardized neuropsychological measures of visual and verbal memory performance. RESULTS: Judgements of egocentric and allocentric heading direction were differentially impaired in bvFTD and AD, with AD performing significantly worse on egocentric heading judgements than bvFTD. Both patient cohorts, however, showed similar degree of impaired allocentric spatial representation, and associated hippocampal pathology. CONCLUSIONS: The findings suggest egocentric heading judgements offer a more sensitive discriminant of bvFTD and AD than allocentric map-based measures of spatial memory.

Estradiol and Cognition in the Cardiovascular Risk Factors, Aging and Dementia (CAIDE) Cohort Study. - Imtiaz, Bushra; Tolppanen, Anna Maija; Solomon, Alina; Soininen, Hilkka; Kivipelto, Miia (J Alzheimers Dis, 2017)
Cardiovascular Risk factors, Aging and Dementia (CAIDE) is a Finnish population-based study. 731 cognitively normal women had self-reported hormone therapy (HT) data in 1998 as: no use, use ≤5 years, and >5 years. Information on type of HT was only available from 1995-1998 (Prescription Register). Cognition was assessed in 1998 and 2005-2008. Long-term (>5 years) HT use, especially use of estradiol alone among women having hysterectomy with bilateral oophorectomy, was associated with better episodic memory in 1998, but not in 2005-2008. Although a strong evidence for protective effect of estradiol on cognition was not observed in our study, improved global cognition among long-term users suggests that long-term postmenopausal HT may be beneficial for some cognitive domains.

Frontal Lobe Function Correlates with One-Year Incidence of Urinary Incontinence in Elderly with Alzheimer Disease. - Sugimoto, Taiki; Yoshida, Masaki; Ono, Rei; Murata, Shunsuke; Saji, Naoki; Niida, Shumpei; Toba, Kenji; Sakurai, Takashi (J Alzheimers Dis, 2017)
BACKGROUND: Urinary incontinence (UI) is frequently observed in patients with Alzheimer's disease (AD). Although previous works highlight the association between frontal lobe-related function and UI, causal relationship is unclear. OBJECTS: To clarify the longitudinal association between frontal lobe function and the incidence of UI at 1 year in patients with AD. METHODS: The subjects were 215 continent AD patients who attended the Memory Clinic of the National Center for Geriatrics and Gerontology of Japan during the period from March 2011 to December 2014. The absence or presence of UI was operationally assigned by the dementia behavior disturbance scale subscale, which was completed by the patients' caregivers. Frontal lobe function was assessed using the Frontal Assessment Battery (FAB). Other confounding factors including demographic data, cognitive status, vitality, mood, physical performance, and use of medication (cholinesterase inhibitors, calcium channel blockers [CCBs], diuretics, alpha blockers and anticholinergic drugs) were assessed. RESULTS: During 1-year follow up (mean: 377.4±83.7 days), the incidence of UI was 12.1% (n = 26). Patients with UI had significantly lower FAB performance at baseline (no UI versus UI = 9.3±2.8 versus 7.8±2.7). In multivariate analysis, stepwise logistic regression analysis demonstrated that FAB (odds ratio [OR] = 0.79, 95% confidence interval [CI] = 0.66-0.94) and the use of CCB (OR = 2.72, 95% CI = 1.09-6.77) were significantly associated with UI at 1 year. CONCLUSION: The results of study indicate that frontal lobe dysfunction is predictor for UI in patients with AD.

Functional Connectivity in the Default Mode Network is Reduced in Association with Nocturnal Awakening in Mild Cognitive Impairment. - McKinnon, Andrew C; Duffy, Shantel L; Cross, Nathan E; Terpening, Zoe; Grunstein, Ron R; Lagopoulos, Jim; Batchelor, Jennifer; Hickie, Ian B; Lewis, Simon J G; Shine, James M; Naismith, Sharon L (J Alzheimers Dis, 2017)
BACKGROUND: Sleep disturbance is prevalent in MCI, and is a risk factor for cognitive deterioration. OBJECTIVE: To identify functional connectivity deficits in the default mode network (DMN) in patients with mild cognitive impairment (MCI) and sleep disturbance, relative to MCIs with intact sleep. METHODS: Participants comprised 47 adults aged 55 years and over, recruited from the Healthy Brain Ageing Clinic at the Brain and Mind Centre, Sydney, Australia. This sample contained 15 controls and 32 participants meeting criteria for MCI. Participants underwent resting-state fMRI and actigraphy, along with comprehensive neuropsychological, medical and psychiatric assessment. MCIs were split into two groups according to average wake after sleep onset (WASO) per night. WASO equal to or greater than 1 standard deviation (SD) above the control mean was deemed to reflect disturbed sleep. There were 11 patients in the MCI sleep-disturbed group, and 21 in the MCI sleep-intact group. RESULTS: Relative to controls, MCIs demonstrated significant connectivity reductions between parietal and temporoparietal regions, and between temporal regions. Relative to MCIs with intact sleep, MCIs with sleep disturbance demonstrated reductions in functional connectivity between temporal and parietal regions, and between temporal and temporoparietal regions. CONCLUSIONS: MCIs with nocturnal awakenings demonstrate reductions in DMN connectivity. These reductions comprise brain regions that are crucially involved in sleep and memory processes. These results strengthen our previous findings, which found reduced connectivity in MCIs with self-reported sleep disturbances. Future studies may build on these findings through incorporating complementary neuroimaging techniques and experimental manipulations of sleep.

Gender-Based Cerebral Perfusion Differences in 46,034 Functional Neuroimaging Scans. - Amen, Daniel G; Trujillo, Manuel; Keator, David; Taylor, Derek V; Willeumier, Kristen; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2017)
BACKGROUND: Studies have reported that females have widespread increases in regional cerebral blood flow, but the studies were relatively small and inconsistent. OBJECTIVE: Here we analyzed a healthy and a very large clinical psychiatric population to determine the effect of gender, using single photon emission computed tomography (SPECT). METHODS: Whole brain and region of interest (ROI) gender differences were analyzed in a total of 46,034 SPECT scans at baseline and concentration. The sample included 119 healthy subjects and 26,683 patients (60.4% male, 39.6% female); a subset of 11,587 patients had complete diagnostic information. A total of 128 regions were analyzed according to the AAL Atlas, using ROI Extract and SPSS statistical software programs, controlling for age, diagnoses, and correcting for multiple comparisons. RESULTS: Compared to males, healthy females showed significant whole brain (p < 0.01) and ROI increases in 65 baseline and 48 concentration regions (p < 0.01 corrected). Healthy males showed non-significant increases in 9 and 22 regions, respectively. In the clinical group, there were widespread significant increases in females, especially in the prefrontal and limbic regions, and specific increases in males in the inferior occipital lobes, inferior temporal lobes, and lobule 7 and Crus 2 of the cerebellum. These findings were replicated in the subset of 11,587 patients with the effect of diagnoses removed. CONCLUSIONS: Our results demonstrated significant gender differences in a healthy and clinical population. Understanding these differences is crucial in evaluating functional neuroimaging and may be useful in understanding the epidemiological gender differences among psychiatric disorders.

Genetic Deletion of Tumor Necrosis Factor-α Attenuates Amyloid-β Production and Decreases Amyloid Plaque Formation and Glial Response in the 5XFAD Model of Alzheimer's Disease. - Paouri, Evi; Tzara, Ourania; Zenelak, Sofia; Georgopoulos, Spiros (J Alzheimers Dis, 2017)
Increasing evidence suggests that neuroinflammation comprises a major characteristic of Alzheimer's disease (AD). Tumor necrosis factor-α (TNF-α) is a pleiotropic pro-inflammatory cytokine implicated in neurodegenerative diseases including AD, and has been proposed as a potent therapeutic target for AD. Although a number of studies focusing on pharmacological or genetic manipulation of TNF-α and its receptors in AD mice have provided significant knowledge regarding the role of TNF-α signaling pathway in the pathogenesis of AD, the consequences of TNF-α genetic deletion have not been thoroughly examined. Here, we focused on the effect of TNF-α deficiency on the amyloid phenotype of 5XFAD mice. Our analysis revealed that amyloid deposition, amyloid-β (Aβ) levels, and AβPP-carboxyterminal fragments are significantly reduced in the brains of 5XFAD/TNF-α-/- mice compared to the 5XFAD/TNF-α+/+. We found decreased protein levels of β- and α-secretases in the 5XFAD/TNF-α-/- brains, suggesting for an effect of TNF-α on AβPP processing and Aβ generation. We also show for the first time that TNF-α affects PS1in vivo, as 5XFAD mice lacking TNF-α expression display reduced PS1-carboxyterminal fragments implying for diminished PS1 activity. Moreover, TNF-α deficiency decreases microglial and astrocytic activation and significantly restricts the phagocytic activity of macrophages against Aβ, supporting for reduced responsiveness of phagocytes toward Aβ. Overall, our results reveal that TNF-α genetic deletion in 5XFAD mice attenuates amyloid plaque formation by lowering Aβ generation through the reduction of functionally active PS1 and β-secretase rather than promoting Aβ clearance by phagocytic cells. Our data further suggest TNF-α inhibition as a therapeutic approach for AD.

Genetically-Predicted Adult Height and Alzheimer's Disease. - Larsson, Susanna C; Traylor, Matthew; Burgess, Stephen; Markus, Hugh S (J Alzheimers Dis, 2017)
BACKGROUND: Observational studies have linked increased adult height with better cognitive performance and reduced risk of Alzheimer's disease (AD). It is unclear whether the associations are due to shared biological processes that influence height and AD or due to confounding by early life exposures or environmental factors. OBJECTIVE: To use a genetic approach to investigate the association between adult height and AD. METHODS: We selected 682 single nucleotide polymorphisms (SNPs) associated with height at genome-wide significance (p < 5×10-8) in the Genetic Investigation of ANthropometric Traits (GIANT) consortium. Summary statistics for each of these SNPs on AD were obtained from the International Genomics of Alzheimer's Project (IGAP) of 17,008 individuals with AD and 37,154 controls. The estimate of the association between genetically predicted height and AD was calculated using the inverse-variance weighted method. RESULTS: The odds ratio of AD was 0.91 (95% confidence interval, 0.86-0.95; p = 9.8×10-5) per one standard deviation increase (about 6.5 cm) in genetically predicted height based on 682 SNPs, which were clustered in 419 loci. In an analysis restricted to one SNP from each height-associated locus (n = 419 SNPs), the corresponding OR was 0.92 (95% confidence interval, 0.86-0.97; p = 4.8×10-3). CONCLUSIONS: This finding suggests that biological processes that influence adult height may have a role in the etiology of AD.

Heterogeneous Association of Alzheimer's Disease-Linked Amyloid-β and Amyloid-β Protein Precursor with Synapses. - Willén, Katarina; Sroka, Agnieszka; Takahashi, Reisuke H; Gouras, Gunnar K (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is increasingly viewed as a disease of synapses. Loss of synapses correlates better with cognitive decline than amyloid plaques and neurofibrillary tangles, the hallmark neuropathological lesions of AD. Soluble forms of amyloid-β (Aβ) have emerged as mediators of synapse dysfunction. Aβ binds to, accumulates, and aggregates in synapses. However, the anatomical and neurotransmitter specificity of Aβ and the amyloid-β protein precursor (AβPP) in AD remain poorly understood. In addition, the relative roles of Aβ and AβPP in the development of AD, at pre- versus post-synaptic compartments and axons versus dendrites, respectively, remain unclear. Here we use immunogold electron microscopy and confocal microscopy to provide evidence for heterogeneity in the localization of Aβ/AβPP. We demonstrate that Aβ binds to a subset of synapses in cultured neurons, with preferential binding to glutamatergic compared to GABAergic neurons. We also highlight the challenge of defining pre- versus post-synaptic localization of this binding by confocal microscopy. Further, endogenous Aβ42 accumulates in both glutamatergic and GABAergic AβPP/PS1 transgenic primary neurons, but at varying levels. Moreover, upon knock-out of presenilin 1 or inhibition of γ-secretase AβPP C-terminal fragments accumulate both pre- and post-synaptically; however earlier pre-synaptically, consistent with a higher rate of AβPP processing in axons. A better understanding of the synaptic and anatomical selectivity of Aβ/AβPP in AD can be important for the development of more effective new therapies for this major disease of aging.

Higher Peripheral TREM2 mRNA Levels Relate to Cognitive Deficits and Hippocampal Atrophy in Alzheimer's Disease and Amnestic Mild Cognitive Impairment. - Tan, Yi Jayne; Ng, Adeline S L; Vipin, Ashwati; Lim, Joseph K W; Chander, Russell J; Ji, Fang; Qiu, Yingwei; Ting, Simon K S; Hameed, Shahul; Lee, Tih-Shih; Zeng, Li; Kandiah, Nagaendran; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Variants in triggering receptor expressed on myeloid cells 2 (TREM2) are associated with increased Alzheimer's disease (AD) risk. Recent studies have reported inconsistent peripheral TREM2 mRNA expression levels and relationship with cognitive scores in AD and mild cognitive impairment (MCI). Additionally, no study has examined the association of peripheral TREM2 levels with neuroimaging measures in AD and MCI. OBJECTIVE: To determine peripheral TREM2 mRNA levels in AD, amnestic MCI (aMCI) and healthy controls, and the association with cognitive performance and brain structural changes. METHODS: We measured peripheral TREM2 mRNA levels in 80 AD, 30 aMCI, and 86 healthy controls using real time polymerase chain reaction. TREM2 levels were correlated with various cognitive performance and brain volumes, correcting for APOE4 status. RESULTS: TREM2 mRNA levels were significantly higher in AD compared to controls and aMCI. Levels did not differ between aMCI and controls. Corrected for APOE4, higher TREM2 levels correlated with lower Mini-Mental State Examination, Montreal Cognitive Assessment (MoCA) and episodic memory scores, and lower total grey matter and right hippocampal volumes. Whole-brain voxel-based morphometry analysis found negative association between TREM2 mRNA levels and grey matter volumes in temporal, parietal and frontal regions. AD subjects with MoCA scores ≤20 had higher TREM2 levels correlating with smaller total grey matter, left hippocampal and right hippocampal volumes. CONCLUSION: Peripheral TREM2 mRNA levels are higher in AD and are associated with AD-related cognitive deficits and hippocampal atrophy. Our findings suggest that TREM2 may be a potential non-invasive peripheral biomarker for AD diagnosis.

Hippocampal and Clinical Trajectories of Mild Cognitive Impairment with Suspected Non-Alzheimer's Disease Pathology. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Caravaggio, Fernando; Iwata, Yusuke; Gerretsen, Philip; Kim, Julia; Takeuchi, Hiroyoshi; Shinagawa, Shunichiro; Patel, Raihaan; Chakravarty, M Mallar; Graff-Guerrero, Ariel (J Alzheimers Dis, 2017)
Suspected non-Alzheimer's disease pathology (SNAP) characterizes individuals showing neurodegeneration (e.g., hypometabolism) without amyloid-β (Aβ). Findings from previous studies regarding clinical and structural trajectories of SNAP are inconsistent. Using data from the Alzheimer's Disease Neuroimaging Initiative, patients with amnestic mild cognitive impairment (MCI) were categorized into four groups: amyloid positive with hypometabolism (Aβ+ND+), amyloid only (Aβ+ND-), neither amyloid nor hypometabolism (Aβ-ND-), and SNAP (Aβ-ND+). Aβ+ND+(n = 33), Aβ+ND-(n = 32), and Aβ-ND-(n = 36) were matched to SNAP for age, gender, apolipoprotein E4 (apoE4) genotype, and scores on the Montreal Cognitive Assessment. Elderly controls (n = 40) were also matched to SNAP for age, gender, and apoE4 genotype. Longitudinal changes were compared across groups in terms of hippocampal volume, clinical symptoms, daily functioning, and cognitive functioning over a 2-year period. At baseline, no difference in cognition and functioning was observed between SNAP and Aβ+groups. SNAP showed worse clinical symptoms and impaired functioning at baseline compared to Aβ-ND-and controls. Two years of follow-up showed no differences in hippocampal volume changes between SNAP and any of the comparison groups. SNAP showed worse functional deterioration in comparison to Aβ-ND-and controls. However, Aβ+ND+ showed more severe changes in clinical symptoms in comparison to SNAP. Thus, patients with MCI and SNAP showed 1) more severe functional deterioration compared to Aβ-ND-and controls, 2) no differences with Aβ+ND-, and 3) less cognitive deterioration than Aβ+ND+. Future studies should investigate what causes SNAP, which is different from typical AD pathology and biomarker cascades.

Hippocampus and Basal Forebrain Volumetry for Dementia and Mild Cognitive Impairment Diagnosis: Could It Be Useful in Primary Care? - Teipel, Stefan J; Keller, Felix; Thyrian, Jochen R; Strohmaier, Urs; Altiner, Attila; Hoffmann, Wolfgang; Kilimann, Ingo (J Alzheimers Dis, 2017)
BACKGROUND: Once a patient or a knowledgeable informant has noticed decline in memory or other cognitive functions, initiation of early dementia assessment is recommended. Hippocampus and cholinergic basal forebrain (BF) volumetry supports the detection of prodromal and early stages of Alzheimer's disease (AD) dementia in highly selected patient populations. OBJECTIVE: To compare effect size and diagnostic accuracy of hippocampus and BF volumetry between patients recruited in highly specialized versus primary care and to assess the effect of white matter lesions as a proxy for cerebrovascular comorbidity on diagnostic accuracy. METHODS: We determined hippocampus and BF volumes and white matter lesion load from MRI scans of 71 participants included in a primary care intervention trial (clinicaltrials.gov identifier: NCT01401582) and matched 71 participants stemming from a memory clinic. Samples included healthy controls and people with mild cognitive impairment (MCI), AD dementia, mixed dementia, and non-AD related dementias. RESULTS: Volumetric measures reached similar effect sizes and cross-validated levels of accuracy in the primary care and the memory clinic samples for the discrimination of AD and mixed dementia cases from healthy controls. In the primary care MCI cases, volumetric measures reached only random guessing levels of accuracy. White matter lesions had only a modest effect on effect size and diagnostic accuracy. CONCLUSIONS: Hippocampus and BF volumetry may usefully be employed for the identification of AD and mixed dementia, but the detection of MCI does not benefit from the use of these volumetric markers in a primary care setting.

Histopathology and Florbetaben PET in Patients Incorrectly Diagnosed with Alzheimer's Disease. - Sabbagh, Marwan N; Schäuble, Barbara; Anand, Keshav; Richards, Danielle; Murayama, Shigeo; Akatsu, Hiroyasu; Takao, Masaki; Rowe, Christopher C; Masters, Colin L; Barthel, Henryk; Gertz, Hermann-Josef; Peters, Oliver; et al. (J Alzheimers Dis, 2017)
Of 57 individuals diagnosed with Alzheimer's disease (AD) in a phase III study, 13 (23%) had amyloid-β (Aβ) levels on postmortem histopathology that did not explain the dementia. Based on postmortem histopathology, a wide range of different non-AD conditions was identified, including frontotemporal dementia, hippocampal sclerosis, and dementia with Lewy bodies. Of the histopathologically Aβ negative scored cases ante-mortem Florbetaben PET scans were classified as negative for Aβ in 11 patients based on visual analysis and in all 12 quantifiable cases based on composite standardized uptake value ratios. Thus, florbetaben PET can assist physicians in the differential diagnosis of neurodegenerative disorders by reliably excluding Aβ pathology.

Impact of Recruitment Methods in Subjective Cognitive Decline. - Abdelnour, Carla; Rodríguez-Gómez, Octavio; Alegret, Montserrat; Valero, Sergi; Moreno-Grau, Sonia; Sanabria, Ángela; Hernandez, Isabel; Rosende-Roca, Maitee; Vargas, Liliana; Mauleón, Ana; Sánchez, Domingo; Espinosa, Ana; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Recruitment methods can determine sample characteristics in mild cognitive impairment and Alzheimer's disease dementia, but little is known about its influence in subjective cognitive decline (SCD). OBJECTIVE: To determine the influence of two types of recruitment methods in the characteristics of individuals with SCD. METHODS: We select and compare clinical and neuropsychological features, and frequency of APOE ɛ4 allele of 326 subjects with SCD from two cohorts: Open House Initiative (OHI) versus Memory Unit (MU). A logistic regression analysis (LRA), using gender and years of education as covariates, was used to examine the neuropsychological variables. RESULTS: The OHI sample were mostly women (75.9% versus 64.5%, p < 0.05), with higher educational level (12.15 [3.71] versus 10.70 [3.80] years, p = 0.001), and more family history of dementia (138 [62.7%] versus 44 [41.5%], p < 0.001) than the MU sample. Also, the OHI sample showed better overall neuropsychological performance than the MU sample, and after a LRA, this trend continued in automatic response inhibition capacity, abstract reasoning, and recognition memory. We did not find differences in age, depression history, and/or APOE ɛ4 allele frequency. CONCLUSION: SCD subjects showed different demographic and neuropsychological characteristics depending on the recruitment method, which should be taken into account in the design of research studies with this target population.

Improved Brain Insulin/IGF Signaling and Reduced Neuroinflammation with T3D-959 in an Experimental Model of Sporadic Alzheimer's Disease. - de la Monte, Suzanne M; Tong, Ming; Schiano, Irio; Didsbury, John (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is associated with progressive impairments in brain insulin, insulin-like growth factor (IGF), and insulin receptor substrate (IRS) signaling through Akt pathways that regulate neuronal growth, survival, metabolism, and plasticity. The intracerebral streptozotocin (i.c. STZ) model replicates the full range of abnormalities in sporadic AD. T3D-959, an orally active PPAR-delta/gamma agonist remediates neurocognitive deficits and AD neuropathology in the i.c. STZ model. OBJECTIVE: This study characterizes the effects of T3D-959 on AD biomarkers, insulin/IGF/IRS signaling through Akt pathways, and neuroinflammation in an i.c. STZ model. METHODS: Long Evans rats were treated with i.c. STZ or saline, followed by daily oral doses of T3D-959 (1 mg/kg) or saline initiated 1 day (T3D-959-E) or 7 days (T3D-959-L) later through Experimental Day 28. Protein and phospho-protein expression and pro-inflammatory cytokine activation were measured in temporal lobe homogenates by duplex or multiplex bead-based ELISAs. RESULTS: i.c. STZ treatments caused neurodegeneration with increased pTau, AβPP, Aβ42, ubiquitin, and SNAP-25, and reduced levels of synaptophysin, IGF-1 receptor (R), IRS-1, Akt, p70S6K, mTOR, and S9-GSK-3β. i.c. STZ also broadly increased neuroinflammation. T3D-959 abrogated or reduced most of the AD neuropathological and biomarker abnormalities, increased/normalized IGF-1R, IRS-1, Akt, p70S6K, and S9-GSK-3β, and decreased expression of multiple pro-inflammatory cytokines. T3D-959-E or -L effectively restored insulin/IGF signaling, whereas T3D-959-L more broadly resolved neuroinflammation. CONCLUSION: AD remediating effects of T3D-959 are potentially due to enhanced expression of key insulin/IGF signaling proteins and inhibition of GSK-3β and neuroinflammation. These effects lead to reduced neurodegeneration, cognitive impairment, and AD biomarker levels in the brain.

Improved Cerebrospinal Fluid-Based Discrimination between Alzheimer's Disease Patients and Controls after Correction for Ventricular Volumes. - van Waalwijk van Doorn, Linda J C; Gispert, Juan D; Kuiperij, H Bea; Claassen, Jurgen A H R; Arighi, Andrea; Baldeiras, Ines; Blennow, Kaj; Bozzali, Marco; Castelo-Branco, Miguel; Cavedo, Enrica; Emek-Savaş, Derya D; Eren, Erden; et al. (J Alzheimers Dis, 2017)
Cerebrospinal fluid (CSF) biomarkers may support the diagnosis of Alzheimer's disease (AD). We studied if the diagnostic power of AD CSF biomarker concentrations, i.e., Aβ42, total tau (t-tau), and phosphorylated tau (p-tau), is affected by differences in lateral ventricular volume (VV), using CSF biomarker data and magnetic resonance imaging (MRI) scans of 730 subjects, from 13 European Memory Clinics. We developed a Matlab-algorithm for standardized automated segmentation analysis of T1 weighted MRI scans in SPM8 for determining VV, and computed its ratio with total intracranial volume (TIV) as proxy for total CSF volume. The diagnostic power of CSF biomarkers (and their combination), either corrected for VV/TIV ratio or not, was determined by ROC analysis. CSF Aβ42 levels inversely correlated to VV/TIV in the whole study population (Aβ42: r = -0.28; p < 0.0001). For CSF t-tau and p-tau, this association only reached statistical significance in the combined MCI and AD group (t-tau: r = -0.15; p-tau: r = -0.13; both p < 0.01). Correction for differences in VV/TIV improved the differentiation of AD versus controls based on CSF Aβ42 alone (AUC: 0.75 versus 0.81) or in combination with t-tau (AUC: 0.81 versus 0.91). In conclusion, differences in VV may be an important confounder in interpreting CSF Aβ42 levels.

An Improved Drugs Screening System Reveals that Baicalein Ameliorates the Aβ/AMPA/NMDA-Induced Depolarization of Neurons. - Lin, Tian-Syuan; Tsai, Han-Jung; Lee, Chih-Han; Song, Yan-Qing; Huang, Rih-Sheng; Hsieh-Li, Hsiu-Mei; Liang, Mei-Chih; Lin, Yenshou (J Alzheimers Dis, 2017)
The presence of amyloid-β (Aβ) plaque and tau protein hyperphosphorylation in brain tissue is the pathological hallmark of Alzheimer's disease (AD). At least some Aβ neurotoxicity is caused by the presence of excess glutamate that has been induced by Aβ accumulation. Memantine is currently the only NMDA receptor inhibitor approved for treating moderate-to-severe AD patients. We utilized primary cortical neurons and DiBAC4(3), a slow-response voltage sensitive fluorescence dye, to create a novel system for screening herbal medicines that allows the identification of pure compounds able to ameliorate Aβ-induced abnormal depolarization. The intensity of DiBAC4(3) fluorescence was increased when primary neurons were stimulated by Aβ; furthermore, pre-treatment with memantine abolished this change. Using this system, we identified six crude extracts made from herbal medicines that effectively alleviated this Aβ-induced abnormal depolarization. Among these herbal medicines, one pure compound, baicalein, which was known to be present in Scutellaria baricalensis and is known to improve memory using an AD mouse model, was identified by our assay. However, the compound's molecular mechanism remained unknown. We found that baicalein, in addition to inhibiting Aβ-induced depolarization, possibly functions as an antagonist of AMPA and NMDA receptors. Taken together, we have established a system/platform to identify herbal medicines that ameliorate Aβ-induced depolarization of neurons. Equally important, baicalein is a candidate drug with great potential for the treatment of AD patients.

Increased Carbohydrate Intake is Associated with Poorer Performance in Verbal Memory and Attention in an APOE Genotype-Dependent Manner. - Gardener, Samantha L; Rainey-Smith, Stephanie R; Sohrabi, Hamid R; Weinborn, Michael; Verdile, Giuseppe; Fernando, W M A D Binosha; Lim, Yen Ying; Harrington, Karra; Burnham, Samantha; Taddei, Kevin; Masters, Colin L; Macaulay, Stuart L; et al. (J Alzheimers Dis, 2017)
Evidence suggests that a diet low in carbohydrates can impact on cognitive performance among those with Alzheimer's disease (AD). However, there is a lack of data assessing this relationship among cognitively normal (CN) older adults at increased future risk of developing AD due to carriage of the apolipoprotein E (APOE) ɛ4 allele. We assessed the cross-sectional association between carbohydrate intake, cognitive performance, and cerebral amyloid-β (Aβ) load in CN older adults, genotyped for APOEɛ4 allele carrier status. Greater carbohydrate intake was associated with poorer performance in verbal memory in APOEɛ4 allele non-carriers, and poorer performance in attention in APOEɛ4 allele carriers. There were no associations between carbohydrate intake and cerebral Aβ load. These results provide support to the idea that decreasing carbohydrate intake may offer neurocognitive benefits, with specific cognitive domains affected in an APOE genotype-dependent manner. These findings warrant further investigation utilizing a longitudinal study design.

Increased Plasma Homocysteine Level is Associated with Executive Dysfunction in Type 2 Diabetic Patients with Mild Cognitive Impairment. - Tian, Sai; Han, Jing; Huang, Rong; Sun, Jie; Cai, Rongrong; Shen, Yanjue; Wang, Shaohua (J Alzheimers Dis, 2017)
BACKGROUND: Homocysteine (Hcy) is involved in the pathogenesis of type 2 diabetes mellitus (T2DM) and Alzheimer's disease. OBJECTIVE: We aimed to investigate the role of Hcy in T2DM patients with mild cognitive impairment (MCI), and to determine whether methylene tetrahydrofolate reductase (MTHFR) C677T or cystathionine beta-synthase (CBS) 844ins68 polymorphism is related to T2DM-associated MCI. METHODS: We recruited 285 T2DM patients and divided them into two groups, 140 patients with MCI, and 145 healthy-cognition controls, on the basis of Montreal Cognitive Assessment (MoCA) scores. Demographic characteristics, clinical parameters, and neuropsychological tests were assessed. MTHFR C677T and CBS 844ins68 polymorphisms were analyzed. RESULTS: The MCI group exhibited significantly higher plasma total Hcy (tHcy) levels than control group (p < 0.001). Plasma tHcy level was negatively correlated with MoCA scores (p = 0.002), but positively associated with Trail Making Test A and B scores (p = 0.044; p = 0.005, respectively). Multivariable logistic regression model showed that high tHcy level was an independent factor for MCI in T2DM patients. No significant difference was observed in the genotype or allele distributions of MTHFR and CBS between MCI and control groups. We did not find significant MCI risks in MTHFR T allele compared with C allele, and in CBS I allele compared with D allele (OR = 1.361, p = 0.067; OR = 1.048, p = 0.909, respectively). CONCLUSION: Increased plasma tHcy level was significantly related to T2DM-associated MCI, especially executive dysfunction. Further investigation with a large population size should be conducted to confirm these findings.

Inflection Point in Course of Mild Cognitive Impairment: Increased Functional Connectivity of Default Mode Network. - Tao, Wuhai; Li, Xin; Zhang, Junying; Chen, Yaojing; Ma, Chao; Liu, Zhen; Yang, Caishui; Wang, Wenxiao; Chen, Kewei; Wang, Jun; Zhang, Zhanjun (J Alzheimers Dis, 2017)
The alteration of the default mode network (DMN) functional connectivity (FC) has been reported in patients with amnestic mild cognitive impairment (aMCI) as a predictor of Alzheimer's disease (AD). However, no studies exist that examined stage-dependent DMN FC changes throughout the course of aMCI. The present study aims to characterize patterns of DMN FC over three aMCI stages as first defined. Utilizing the extreme groups approach on the performance of memory tasks, aMCI subjects were divided into mild, moderate, and severe stages. Independent component analysis was used to assess DMN for individual patients in each of the three cross-sectionally defined stages. Instead of finding that continued monotonic decline was the case for the hippocampus volume, which we also investigated in this study, we observed an increase in DMN functional connectivity from mild aMCI to moderate aMCI and a decrease to severe aMCI, mainly in the left precuneus and superior parietal lobe. Moreover, the FC was significantly associated with cognitive performance. Though a longitudinal study is needed to confirm these results, our cross-sectional finding is that non-linear FC changes in DMN could be a characteristic of prodromal early disease development.

Insulin Resistance and Future Cognitive Performance and Cognitive Decline in Elderly Patients with Cardiovascular Disease. - Lutski, Miri; Weinstein, Galit; Goldbourt, Uri; Tanne, David (J Alzheimers Dis, 2017)
BACKGROUND: The role of insulin resistance (IR) in the pathogenesis of cognitive performance is not yet clear. OBJECTIVE: To examine the associations between IR and cognitive performance and change in cognitive functions two decades later in individuals with cardiovascular disease with and without diabetes. METHODS: A subset of 489 surviving patients (mean age at baseline 57.7±6.5 y) with coronary heart disease who previously participated in the secondary prevention Bezafibrate Infarction Prevention (BIP trial; 1990-1997), were included in the current neurocognitive study. Biochemical parameters including IR (using the homeostasis model of assessment; HOMA-IR) were measured at baseline. During 2004-2008, computerized cognitive assessment and atherosclerosis parameters were measured (T1; n = 558; mean age 72.6±6.4 years). A second cognitive assessment was performed during 2011-2013 (T2; n = 351; mean age 77.2±6.4 years). Cognitive function, overall and in specific domains, was assessed. We used linear regression models and linear mixed models to evaluate the differences in cognitive performance and decline, respectively. RESULTS: Controlling for potential confounders, IR (top HOMA-IR quartile versus others) was associated with subsequent poorer cognitive performance overall (β= -4.45±Standard Error (SE) 1.54; p = 0.004) and on tests of memory and executive function among non-diabetic patients (β= -7.16±2.38; p = 0.003 and β= -3.33±1.84; p = 0.073, respectively). Moreover, among non-diabetic patients, IR was related to a greater decline overall (β= -0.17±0.06; p = 0.008), and in memory (β= -0.22±0.10; p = 0.024) and executive function (β= -0.19±0.08; p = 0.012). The observed associations did not differ after excluding subjects with prevalent stroke or dementia. CONCLUSION: IR is related to subsequent poorer cognitive performance and greater cognitive decline among patients with cardiovascular disease with and without diabetes.

Intracerebroventricular Streptozotocin Induces Obesity and Dementia in Lewis Rats. - Bloch, Konstantin; Gil-Ad, Irit; Vanichkin, Alexey; Hornfeld, Shay Henry; Koroukhov, Nickolay; Taler, Michal; Vardi, Pnina; Weizman, Abraham (J Alzheimers Dis, 2017)
BACKGROUND: Animal models of dementia associated with metabolic abnormalities play an important role in understanding the bidirectional relationships between these pathologies. Rodent strains develop cognitive dysfunctions without alteration of peripheral metabolism following intracerebroventricular administration of streptozotocin (icv-STZ). OBJECTIVE: We aimed to estimate the effect of icv-STZ on cognitive functions and peripheral metabolism in Lewis rats, which are rarely used for the induction of cognitive abnormalities. METHODS: Inbred adult Lewis rats were treated with single icv-STZ (3 mg/kg). Cognitive functions were assessed using Morris water maze (MWM) test and locomotion by the Open Field test. Metabolic alterations were studied using histological and biochemical analysis of brain and peripheral tissues. RESULTS: The icv-STZ induced rapid weight decline during the first two weeks. Thereafter, the rats showed an accelerated weight gain. Three months after the icv-STZ treatment, the rats were severely obese and revealed fatty liver, pancreatic islet hypertrophy, significantly elevated levels of blood insulin, leptin, and adiponectin, but intact peripheral glucose homeostasis. The icv-STZ rats expressed amyloid-β deposits in blood vessels of leptomeningeal area, microgliosis, astrogliosis, and spongiosis in fimbria-fornix area of hippocampus. Locomotor activities of icv-STZ treated and sham-operated rats were similar. In the MWM test, the icv-STZ treated rats demonstrated severely impaired spatial learning during both acquisition and reversal phases. CONCLUSIONS: Icv-STZ treated Lewis rats develop severe dementia associated with obesity and peripheral metabolic abnormalities. This animal model may be useful for exploring the pathophysiological relationship between obesity and dementia and provides a new tool for development of effective therapy.

Intracranial Arterial 4D Flow in Individuals with Mild Cognitive Impairment is Associated with Cognitive Performance and Amyloid Positivity. - Berman, Sara E; Clark, Lindsay R; Rivera-Rivera, Leonardo A; Norton, Derek; Racine, Annie M; Rowley, Howard A; Bendlin, Barbara B; Blennow, Kaj; Zetterberg, Henrik; Carlsson, Cynthia M; Asthana, Sanjay; Turski, Patrick; et al. (J Alzheimers Dis, 2017)
It is becoming increasingly recognized that cerebrovascular disease is a contributing factor in the pathogenesis of Alzheimer's disease (AD). A unique 4D-Flow magnetic resonance imaging (MRI) technique, phase contrast vastly undersampled isotropic projection imaging (PC VIPR), enables examination of angiographic and quantitative metrics of blood flow in the arteries of the Circle of Willis within a single MRI acquisition. Thirty-eight participants with mild cognitive impairment (MCI) underwent a comprehensive neuroimaging protocol (including 4D-Flow imaging) and a standard neuropsychological battery. A subset of participants (n = 22) also underwent lumbar puncture and had cerebrospinal fluid (CSF) assayed for AD biomarkers. Cut-offs for biomarker positivity in CSF resulting from a receiver operating characteristic curve analysis of AD cases and controls from the larger Wisconsin Alzheimer's Disease Research Center cohort were used to classify MCI participants as biomarker positive or negative on amyloid-β (Aβ42), total-tau and total-tau/Aβ42 ratio. Internal carotid artery (ICA) and middle cerebral artery (MCA) mean flow were associated with executive functioning performance, with lower mean flow corresponding to worse performance. MCI participants who were biomarker positive for Aβ42 had lower ICA mean flow than did those who were Aβ42 negative. In sum, mean ICA and MCA arterial flow was associated with cognitive performance in participants with MCI and lower flow in the ICA was associated with amyloid positivity. This provides further evidence for vascular health as a contributing factor in the etiopathogenesis of AD, and could represent a point to intervene in the disease process.

Investigation on the Role of BDNF in the Benefits of Blueberry Extracts for the Improvement of Learning and Memory in Alzheimer's Disease Mouse Model. - Tan, Long; Yang, Hongpeng; Pang, Wei; Li, Haiqiang; Liu, Wei; Sun, Shoudan; Song, Nan; Zhang, Wanqi; Jiang, Yugang (J Alzheimers Dis, 2017)
BACKGROUND: Blueberry (BB) can provide a wide range of antioxidant benefits for AD. There is evidence that BB extracts could improve brain functions. However, the details are still unknown. OBJECTIVE: In the present study, we aimed to investigate the possible mechanism involved in the improvement of learning and memory capacity from BB extracts in AD. METHODS: APP/PS1 transgenic mice were fed BB extracts for 16 weeks. The capacity of learning and memory was assessed by Morris water maze (MWM) test, and long-term potentiation (LTP) was determined to evaluate hippocampal neuronal plasticity at the end of administration. Pathological changes in the brain were observed, and the expressions of brain-derived neurotrophic factor (BDNF) and extracellular signal-related kinase (ERK1/2) were determined to explore the mechanism of BB extract-induced benefits. RESULTS: AD mice exhibited more difficulties to learn and remember the exact position of the platform in the MWM test. The data showed that AD mice lacked effective learning in the platform search. In contrast, AD mice exhibited better performance both in the training phase and probe test of MWM after the BB treatment. Moreover, LTP was enhanced and the neuron loss was alleviated with BB treatment, while we did not find any obvious effect on the elimination of amyloid-β. In the AD mice, the expression of ERK1/2 was significantly increased (p < 0.05), while the level of BDNF was decreased (p < 0.05). CONCLUSIONS: BB treatment was beneficial for the improvement of learning and memory of AD, and these effects might be related to the regulation of BDNF.

Iron Concentration in Deep Gray Matter Structures is Associated with Worse Visual Memory Performance in Healthy Young Adults. - Darnai, Gergely; Nagy, Szilvia Anett; Horváth, Réka; Ács, Péter; Perlaki, Gábor; Orsi, Gergely; Kovács, Norbert; Altbäcker, Anna; Plózer, Enikő; Tényi, Dalma; Weintraut, Rita; Schwarcz, Attila; et al. (J Alzheimers Dis, 2017)
Abnormally high deposition of iron can contribute to neurodegenerative disorders with cognitive impairment. Since previous studies investigating cognition-brain iron accumulation relationships focused on elderly people, our aim was to explore the association between iron concentration in subcortical nuclei and two types of memory performances in a healthy young population. Gender difference was found only in the globus pallidus. Our results showed that iron load characterized by R2* value on the MRI in the caudate and putamen was related to visual memory, while verbal memory was unrelated to iron concentration.

Left Frontal Hub Connectivity during Memory Performance Supports Reserve in Aging and Mild Cognitive Impairment. - Franzmeier, Nicolai; Hartmann, Julia C; Taylor, Alexander N W; Araque Caballero, Miguel Á; Simon-Vermot, Lee; Buerger, Katharina; Kambeitz-Ilankovic, Lana M; Ertl-Wagner, Birgit; Mueller, Claudia; Catak, Cihan; Janowitz, Daniel; Stahl, Robert; et al. (J Alzheimers Dis, 2017)
Reserve in aging and Alzheimer's disease (AD) is defined as maintaining cognition at a relatively high level in the presence of neurodegeneration, an ability often associated with higher education among other life factors. Recent evidence suggests that higher resting-state functional connectivity within the frontoparietal control network, specifically the left frontal cortex (LFC) hub, contributes to higher reserve. Following up these previous resting-state fMRI findings, we probed memory-task related functional connectivity of the LFC hub as a neural substrate of reserve. In elderly controls (CN, n = 37) and patients with mild cognitive impairment (MCI, n = 17), we assessed global connectivity of the LFC hub during successful face-name association learning, using generalized psychophysiological interaction analyses. Reserve was quantified as residualized memory performance, accounted for gender and proxies of neurodegeneration (age, hippocampus atrophy, and APOE genotype). We found that greater education was associated with higher LFC-connectivity in both CN and MCI during successful memory. Furthermore, higher LFC-connectivity predicted higher residualized memory (i.e., reserve). These results suggest that higher LFC-connectivity contributes to reserve in both healthy and pathological aging.

Low Cognitive Awareness, but Not Complaint, is a Good Marker of Preclinical Alzheimer's Disease. - Cacciamani, Federica; Tandetnik, Caroline; Gagliardi, Geoffroy; Bertin, Hugo; Habert, Marie-Odile; Hampel, Harald; Boukadida, Laurie; Révillon, Marie; Epelbaum, Stéphane; Dubois, Bruno (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive decline (SCD) may result from many conditions, including Alzheimer's disease (AD). OBJECTIVE: In this study, we searched for a specific pattern of SCD in asymptomatic individuals at risk for AD. METHODS: Cognitively normal older adults (N = 318) reporting SCD and their informants were enrolled in the INSIGHT-PreAD cohort. We examined the relationship between six SCD measures and both cognitive scores and AD neuroimaging markers (amyloid burden, hippocampal atrophy and brain hypometabolism). An awareness of cognitive decline index (ACDI) has been introduced based on the subject-informant discrepancy in a questionnaire of SCD and participants with low versus high awareness were compared. RESULTS: Scores in the INSIGHT-PreAD SCD questionnaires did not correlate with AD neuroimaging markers. As well, no correlation has been found between SCD measures and cognitive scores. Comparing subjects with a low (n = 19) and high (n = 86) level of awareness, no significant difference in terms of demography, neuropsychiatric symptoms, autonomy, quality of life, cognition, and hippocampal volume was found. However, the "low awareness" group showed greater amyloid burden and lower cortical metabolism, compared to the "high awareness" group. CONCLUSION: This study provided additional evidence that reporting SCD by itself is not a specific symptom of preclinical AD. Conversely, a low cognitive awareness (namely, when subjects report fewer difficulties than their relatives do) may represent a very early form of anosognosia and serve as a specific indicator of preclinical AD. This finding is of key importance as an enrichment factor to consider in both clinical practice and research trials.

Low Florbetapir PET Uptake and Normal Aβ1-42 Cerebrospinal Fluid in an APP Ala713Thr Mutation Carrier. - Lombardi, Gemma; Berti, Valentina; Tedde, Andrea; Bagnoli, Silvia; Piaceri, Irene; Polito, Cristina; Lucidi, Giulia; Ferrari, Camilla; Ginestroni, Andrea; Moretti, Marco; Pupi, Alberto; Nacmias, Benedetta; et al. (J Alzheimers Dis, 2017)
According to the literature, the APP Ala713Thr mutation is associated with Alzheimer's disease and cerebral amyloid angiopathy. We describe a case of dementia clinically compatible with frontotemporal dementia in an APP Ala713Thr mutation carrier in which both [18F]Florbetapir PET uptake and Aβ1-42 cerebrospinal fluid levels were normal. Further evidences are required to establish if this association is only incidental.
Keywords: Alanine; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Aniline Compounds; Brain; Ethylene Glycols; Humans; Male; Middle Aged; Mutation; Peptide Fragments; Positron-Emission Tomography; Threonine

Macrophage Migration Inhibitory Factor is Associated with Biomarkers of Alzheimer's Disease Pathology and Predicts Cognitive Decline in Mild Cognitive Impairment and Mild Dementia. - Oikonomidi, Aikaterini; Tautvydaitė, Domilė; Gholamrezaee, Mehdi M; Henry, Hugues; Bacher, Michael; Popp, Julius (J Alzheimers Dis, 2017)
BACKGROUND: Macrophage migration inhibitory factor (MIF) is a pro-inflammatory protein playing a regulatory role in the immune response. First evidence from in vitro and animal studies suggests that MIF may be involved in the development of Alzheimer's disease (AD) pathology. OBJECTIVE: To address in older subjects (i) the relationships between AD pathology and MIF plasma and cerebrospinal fluid (CSF) levels; and (ii) to investigate whether increased MIF-related systemic and CNS inflammation is associated with clinical disease progression. METHODS: CSF and plasma concentrations of MIF as well as biomarkers of amyloid, neuronal injury, and tau hyperphosphorylation (CSF Aβ1-42, tau, and ptau, respectively) were assessed in 97 subjects with MCI or mild dementia (cognitive impairment, CI) and 52 healthy volunteers with normal cognition. Clinical and neuropsychological evaluations were performed at inclusion and at follow up visits. RESULTS: CSF MIF levels were higher in participants with CI with an AD CSF biomarker profile, but not in CI with a non-AD profile, compared to the healthy controls. Higher MIF CSF levels were associated with higher CSF tau and ptau and lower CSF Aβ1-42 after adjusting for potential confounders. In CI, MIF CSF independently predicted cognitive decline at a follow-up visit after controlling for potential confounders including CSF Aβ1-42 and tau levels. CONCLUSION: Our study provides evidence that MIF-related inflammation is related to amyloid pathology, tau hyperphosphorylation, and neuronal injury at the early clinical stages of AD. Higher MIF CSF levels are associated with accelerated cognitive decline in MCI and mild dementia.

The Mechanisms of Action of Curcumin in Alzheimer's Disease. - Tang, Mengxi; Taghibiglou, Changiz (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a neurodegenerative disorder of the elderly. As the prevalence of AD rises in the 21st century, there is an urgent need for the development of effective pharmacotherapies. Currently, drug treatments target the symptoms of the disease and do not modify or halt the disease progress. Thus, natural compounds have been investigated for their ability to treat AD. This review examines the efficacy of curcumin, a polyphenol derived from turmeric herb, to treat AD. We summarize the in vivo and in vitro research describing the mechanisms of action in which curcumin modifies AD pathology: curcumin inhibits the formation and promotes the disaggregation of amyloid-β plaques, attenuates the hyperphosphorylation of tau and enhances its clearance, binds copper, lowers cholesterol, modifies microglial activity, inhibits acetylcholinesterase, mediates the insulin signaling pathway, and is an antioxidant. In conclusion, curcumin has the potential to be more efficacious than current treatments. However, its usefulness as a therapeutic agent may be hindered by its low bioavailability. If the challenge of low bioavailability is overcome, curcumin-based medications for AD may be in the horizon.

Memory Correlates of Alzheimer's Disease Cerebrospinal Fluid Markers: A Longitudinal Cohort Study. - Reijs, Babette L R; Ramakers, Inez H G B; Köhler, Sebastian; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Nathan, Pradeep J; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Vandenberghe, Rik; Johannsen, Peter; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Performance on episodic, semantic, and working memory tests is impaired in Alzheimer's disease (AD)-type dementia, but it is unclear which type of memory test is most strongly associated with early AD biomarkers in cerebrospinal fluid (CSF), and most useful for monitoring disease progression. OBJECTIVE: To examine the association between amyloid-β 1-42 (Aβ42) and tau in CSF with performance on different memory domains at baseline, and how these CSF markers are related with memory decline. METHODS: We included 263 individuals with normal cognition, mild cognitive impairment, AD-type dementia, and non-AD dementia from the European EDAR study. Assessment included CSF Aβ42 and t-tau analyses with INNO-BIA AlzBio3 Luminex assay, the CERAD wordlist learning and delayed recall, animal fluency test, and the CANTAB Paired Associates Learning (PAL) and Spatial Working Memory tasks. Follow-up assessments were performed within 3 years after baseline. RESULTS: At baseline, decreased CSF Aβ42 correlated most strongly with the PAL total errors adjusted and the wordlist delayed recall and increased CSF t-tau with the wordlist delayed recall. Over time, decreased CSF Aβ42 was associated with decline on the wordlist learning, whereas increased CSF t-tau were associated with decline in scores on the wordlist learning, wordlist delayed recall, and animal fluency. Associations were independent of baseline diagnosis. CONCLUSION: Tests assessing episodic verbal and visuospatial memory are most useful for detection of AD pathology. Tests for episodic verbal memory and semantic memory are most useful for tracking memory decline.

Metabolic and Growth Rate Alterations in Lymphoblastic Cell Lines Discriminate Between Down Syndrome and Alzheimer's Disease. - Coskun, Pinar; Helguera, Pablo; Nemati, Zahra; Bohannan, Ryan C; Thomas, Jean; Samuel, Schriner E; Argueta, Jocelyn; Doran, Eric; Wallace, Douglas C; Lott, Ira T; Busciglio, Jorge (J Alzheimers Dis, 2017)
BACKGROUND: Deficits in mitochondrial function and oxidative stress play pivotal roles in Down syndrome (DS) and Alzheimer's disease (AD) and these alterations in mitochondria occur systemically in both conditions. OBJECTIVE: We hypothesized that peripheral cells of elder subjects with DS exhibit disease-specific and dementia-specific metabolic features. To test this, we performed a comprehensive analysis of energy metabolism in lymphoblastic-cell-lines (LCLs) derived from subjects belonging to four groups: DS-with-dementia (DSAD), DS-without-dementia (DS), sporadic AD, and age-matched controls. METHODS: LCLs were studied under regular or minimal feeding regimes with galactose or glucose as primary carbohydrate sources. We assessed metabolism under glycolysis or oxidative phosphorylation by quantifying cell viability, oxidative stress, ATP levels, mitochondrial membrane potential (MMP), mitochondrial calcium uptake, and autophagy. RESULTS: DS and DSAD LCLs showed slower growth rates under minimal feeding. DS LCLs mainly dependent on mitochondrial respiration exhibited significantly slower growth and higher levels of oxidative stress compared to other groups. While ATP levels (under mitochondrial inhibitors) and mitochondrial calcium uptake were significantly reduced in DSAD and AD cells, MMP was decreased in DS, DSAD, and AD LCLs. Finally, DS LCLs showed markedly reduced levels of the autophagy marker LC3-II, underscoring the close association between metabolic dysfunction and impaired autophagy in DS. CONCLUSION: There are significant mitochondrial functional changes in LCLs derived from DS, DSAD, and AD patients. Several parameters analyzed were consistently different between DS, DSAD, and AD lines suggesting that metabolic indicators between LCL groups may be utilized as biomarkers of disease progression and/or treatment outcomes.

A Metal-Free Method for Producing MRI Contrast at Amyloid-β. - Hilt, Silvia; Tang, Tang; Walton, Jeffrey H; Budamagunta, Madhu; Maezawa, Izumi; Kálai, Tamás; Hideg, Kálmán; Singh, Vikrant; Wulff, Heike; Gong, Qizhi; Jin, Lee-Way; Louie, Angelique; et al. (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is characterized by depositions of the amyloid-β (Aβ) peptide in the brain. The disease process develops over decades, with substantial neurological loss occurring before a clinical diagnosis of dementia can be rendered. It is therefore imperative to develop methods that permit early detection and monitoring of disease progression. In addition, the multifactorial pathogenesis of AD has identified several potential avenues for AD intervention. Thus, evaluation of therapeutic candidates over lengthy trial periods also demands a practical, noninvasive method for measuring Aβ in the brain. Magnetic resonance imaging (MRI) is the obvious choice for such measurements, but contrast enhancement for Aβ has only been achieved using Gd(III)-based agents. There is great interest in gadolinium-free methods to image the brain. In this study, we provide the first demonstration that a nitroxide-based small-molecule produces MRI contrast in brain specimens with elevated levels of Aβ. The molecule is comprised of a  fluorene (a molecule with high affinity for Aβ) and a nitroxide spin label (a paramagnetic MRI contrast species). Labeling of brain specimens with the spin-labeled fluorene produces negative contrast in samples from AD model mice whereas no negative contrast is seen in specimens harvested from wild-type mice. Injection of spin-labeled fluorene into live mice resulted in good brain penetration, with the compound able to generate contrast 24-h post injection. These results provide a proof of concept method that can be used for early, noninvasive, gadolinium-free detection of amyloid plaques by MRI.

Methionine Sulfoxide Reductase-B3 (MsrB3) Protein Associates with Synaptic Vesicles and its Expression Changes in the Hippocampi of Alzheimer's Disease Patients. - Adams, Stephanie L; Benayoun, Laurent; Tilton, Kathy; Chavez, Olivia R; Himali, Jayandra J; Blusztajn, Jan Krzysztof; Seshadri, Sudha; Delalle, Ivana (J Alzheimers Dis, 2017)
Genome-wide association studies (GWAS) identified susceptibility loci associated with decreased hippocampal volume, and found hippocampal subfield-specific effects at MSRB3 (methionine sulfoxide reductase-B3). The MSRB3 locus was also linked to increased risk for late onset Alzheimer's disease (AD). In this study, we uncovered novel sites of MsrB3 expression in CA pyramidal layer and arteriolar walls by using automated immunohistochemistry on hippocampal sections from 23 individuals accompanied by neuropathology reports and clinical dementia rating scores. Controls, cognitively intact subjects with no hippocampal neurofibrillary tangles, exhibited MsrB3 signal as distinct but rare puncta in CA1 pyramidal neuronal somata. In CA3, however, MsrB3-immunoreactivity was strongest in the neuropil of the pyramidal layer. These patterns were replicated in rodent hippocampi where ultrastructural and immunohistofluorescence analysis revealed MsrB3 signal associated with synaptic vesicles and colocalized with mossy fiber terminals. In AD subjects, the number of CA1 pyramidal neurons with frequent, rather than rare, MsrB3-immunoreactive somatic puncta increased in comparison to controls. This change in CA1 phenotype correlated with the occurrence of AD pathological hallmarks. Moreover, the intensity of MsrB3 signal in the neuropil of CA3 pyramidal layer correlated with the signal pattern in neurons of CA1 pyramidal layer that was characteristic of cognitively intact individuals. Finally, MsrB3 signal in the arteriolar walls in the hippocampal white matter decreased in AD patients. This characterization of GWAS-implicated MSRB3 protein expression in human hippocampus suggests that patterns of neuronal and vascular MsrB3 protein expression reflect or underlie pathology associated with AD.

The Methylenetetrahydrofolate Reductase C677T Polymorphism and Risk for Late-Onset Alzheimer's disease: Further Evidence in an Italian Multicenter Study. - Stoccoro, Andrea; Tannorella, Pierpaola; Salluzzo, Maria Grazia; Ferri, Raffaele; Romano, Corrado; Nacmias, Benedetta; Siciliano, Gabriele; Migliore, Lucia; Coppedè, Fabio (J Alzheimers Dis, 2017)
BACKGROUND: A functional polymorphism in the methylenetetrahydrofolate reductase (MTHFR) gene, namely C677T (rs1801133), results in increased Hcy levels and has been associated with risk of late-onset Alzheimer's disease (LOAD). Many investigators reported association between rs1801133 and LOAD risk in Asian populations and in carriers of the apolipoprotein E (APOE) ɛ4 allele, but recent meta-analyses suggest a contribution also in other populations, including Caucasians and/or northern Africans. OBJECTIVE: To further address this issue, we performed a relatively large case-control study, including 581 LOAD patients and 468 matched controls of Italian origin. APOE data were available for a subgroup of almost 600 subjects. METHODS: Genotyping for rs1801133 was performed with PCR-RFLP techniques. RESULTS: In the total population, the MTHFR 677T allele (OR = 1.20; 95% CI = 1.01-1.43) and carriers of the MTHFR 677T allele (CT+TT versus CC: OR = 1.34; 95% CI = 1.03-1.73) resulted in increased LOAD risk. Similarly, in APOEɛ4 carriers, we observed an increased frequency of MTHFR 677CT carriers (CT versus CC: OR = 2.82; 95% CI = 1.25-6.32). Very interestingly, also in non-APOEɛ4 carriers, both MTHFR 677T allele (OR = 1.38; 95% CI = 1.03-1.85) and MTHFR 677TT genotype (OR = 2.08; 95% CI = 1.11-3.90) were associated with LOAD. All these associations survived after corrections for age, gender, and multiple testing. CONCLUSIONS: The present results suggest that the MTHFR C677T polymorphism is likely a LOAD risk factor in our cohort, either in APOEɛ4 or in non-APOEɛ4 carriers.

Microglial and Neuronal TDP-43 Pathology in Anti-IgLON5-Related Tauopathy. - Cagnin, Annachiara; Mariotto, Sara; Fiorini, Michele; Gaule, Marina; Bonetto, Nicola; Tagliapietra, Matteo; Buratti, Emanuele; Zanusso, Gianluigi; Ferrari, Sergio; Monaco, Salvatore (J Alzheimers Dis, 2017)
A novel neuronal tauopathy, mainly confined to hypothalamus and brainstem tegmentum, has recently been reported in patients with autoantibodies to the neuronal cell-adhesion molecule IgLON5. We describe a patient with anti-IgLON5 syndrome, who presented with dysautonomia and sleep disorder, followed by subacute dementia. Postmortem brain examination disclosed neuronal tau pathology prevailing in the hippocampus, amygdala, and locus coeruleus, in addition to microglial/neuronal TDP-43 pathology, with overexpression of aberrantly phosphorylated forms and neurotoxic truncated fragments, in basal ganglia, nucleus basalis, thalamus, and midbrain. These findings suggest that neurodegeneration in anti-IgLON5 syndrome might also occur via a microglia-triggered non-cell autonomous pathway.

Midlife Metabolic Profile and the Risk of Late-Life Cognitive Decline. - Tortelli, Rosanna; Lozupone, Madia; Guerra, Vito; Barulli, Maria Rosaria; Imbimbo, Bruno P; Capozzo, Rosa; Grasso, Alessandra; Tursi, Marianna; Di Dio, Cristina; Sardone, Rodolfo; Giannelli, Gianluigi; Seripa, Davide; et al. (J Alzheimers Dis, 2017)
Among metabolic syndrome components, the effects of higher plasma glucose levels on cognitive decline (CD) have been considered in few studies. We evaluated the associations among midlife glycemia, total cholesterol, high-density lipoprotein cholesterol, triglycerides, midlife insulin resistance [homeostasis model assessment for insulin resistance (HOMA-index)], and CD in the older subjects of the population-based MICOL Study (Castellana Grotte, Italy) at baseline (M1) and at follow-ups seven (M2) and twenty years later (M3). At M1, a dementia risk score and a composite cardiovascular risk score for dementia were calculated. For 797 subjects out of 833, we obtained a Mini-Mental State Examination (MMSE) score at M3, subdividing these subjects in three cognitive functioning subgroups: normal cognition, mild CD, and moderate-severe CD. Mean fasting glycemia at baseline was significantly higher in moderate-severe CD subgroup (114.6±71.4 mg/dl) than in the normal cognition subgroup (101.2±20.6). Adjusting for gender, age, and other metabolic components, higher fasting glycemia values both at M1 [odds ratio (OR) = 1.31; 95% confidence interval (CI): 1.08-1.59] and M2 (OR = 1.26; 95% CI: 1.01-1.57) were associated with an increased risk of moderate-severe CD. Mean HOMA index value was significantly higher in the moderate-severe CD subgroup (5.7±9.4) compared to the normal cognition subgroup (2.9±1.4) at M1. The dementia risk probability (MMSE < 24) increased moving through higher categories of the dementia risk score and decreased as long as the cardiovascular score increased. The present findings highlighted the indication to control blood glucose levels, regardless of a diagnosis of diabetes mellitus, as early as midlife for prevention of late-life dementia.

Mitochondria in Excitatory and Inhibitory Synapses have Similar Susceptibility to Amyloid-β Peptides Modeling Alzheimer's Disease. - Amorim, João A; Canas, Paula M; Tomé, Angelo R; Rolo, Anabela P; Agostinho, Paula; Palmeira, Carlos M; Cunha, Rodrigo A (J Alzheimers Dis, 2017)
Mitochondrial dysfunction is proposed to trigger memory deficits and synaptic damage at the onset of Alzheimer's disease (AD). However, it is unknown how mitochondria dysfunction might trigger synaptotoxicity and if a differential susceptibility of mitochondria located in synapses underlies the greater glutamatergic than GABAergic synaptotoxicity in early AD. Hippocampal synaptosomes (purified synapses) of a rat model of early AD, typified by selective memory deficits two weeks after intracerebroventricular injection of amyloid-β peptides (Aβ1-42, 2 nmol), simultaneously displayed three mitochondria-associated deleterious alterations: 1) hampered metabolism (decreased MTT reduction); 2) increased oxygen radical production (increased hydrogen peroxide production); 3) increased caspase-3 activity. The direct exposure of hippocampal synaptosomes to Aβ1-42 (500 nM) similarly decreased mitochondrial membrane potential (TMRM+ fluorescence) and increased mitochondria-derived oxygen radicals (MitoTraker®red-CM-H2Xros fluorescence) in individual glutamatergic (vesicular glutamate transporter-immunopositive) and GABAergic (vesicular GABA transporter-immunopositive) synaptosomes. However, significantly more glutamatergic than GABAergic synaptosomes were endowed with mitochondria (Tom20-immunopositive). These results indicate that dysfunctional mitochondria located in synapses can trigger synaptotoxicity through multifaceted mechanisms and that it is not the susceptibility of mitochondria to Aβ but more likely a different impact of dysfunctional mitochondria that underlies the greater sensitivity to synaptotoxicity of glutamatergic than GABA synapses in early AD.

Mitochondrial Aspects of Synaptic Dysfunction in Alzheimer's Disease. - Cai, Qian; Tammineni, Prasad (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is characterized by brain deposition of amyloid plaques and tau neurofibrillary tangles along with steady cognitive decline. Synaptic damage, an early pathological event, correlates strongly with cognitive deficits and memory loss. Mitochondria are essential organelles for synaptic function. Neurons utilize specialized mechanisms to drive mitochondrial trafficking to synapses in which mitochondria buffer Ca2+ and serve as local energy sources by supplying ATP to sustain neurotransmitter release. Mitochondrial abnormalities are one of the earliest and prominent features in AD patient brains. Amyloid-β (Aβ) and tau both trigger mitochondrial alterations. Accumulating evidence suggests that mitochondrial perturbation acts as a key factor that is involved in synaptic failure and degeneration in AD. The importance of mitochondria in supporting synaptic function has made them a promising target of new therapeutic strategies for AD. Here, we review the molecular mechanisms regulating mitochondrial function at synapses, highlight recent findings on the disturbance of mitochondrial dynamics and transport in AD, and discuss how these alterations impact synaptic vesicle release and thus contribute to synaptic pathology associated with AD.

Mitochondrial Dysfunction and Synaptic Transmission Failure in Alzheimer's Disease. - Guo, Lan; Tian, Jing; Du, Heng (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder, in which multiple risk factors converge. Despite the complexity of the etiology of the disease, synaptic failure is the pathological basis of cognitive impairment, the cardinal sign of AD. Decreased synaptic density, compromised synaptic transmission, and defected synaptic plasticity are hallmark synaptic pathologies accompanying AD. However, the mechanisms by which synapses are injured in AD-related conditions have not been fully elucidated. Mitochondria are a critical organelle in neurons. The pivotal role of mitochondria in supporting synaptic function and the concomitant occurrence of mitochondrial dysfunction with synaptic stress in postmortem AD brains as well as AD animal models seem to lend the credibility to the hypothesis that mitochondrial defects underlie synaptic failure in AD. This concept is further strengthened by the protective effect of mitochondrial medicine on synaptic function against the toxicity of amyloid-β, a key player in the pathogenesis of AD. In this review, we focus on the association between mitochondrial dysfunction and synaptic transmission deficits in AD. Impaired mitochondrial energy production, deregulated mitochondrial calcium handling, excess mitochondrial reactive oxygen species generation and release play a crucial role in mediating synaptic transmission deregulation in AD. The understanding of the role of mitochondrial dysfunction in synaptic stress may lead to novel therapeutic strategies for the treatment of AD through the protection of synaptic transmission by targeting to mitochondrial deficits.

Modeling the Relationships Among Late-Life Body Mass Index, Cerebrovascular Disease, and Alzheimer's Disease Neuropathology in an Autopsy Sample of 1,421 Subjects from the National Alzheimer's Coordinating Center Data Set. - Alosco, Michael L; Duskin, Jonathan; Besser, Lilah M; Martin, Brett; Chaisson, Christine E; Gunstad, John; Kowall, Neil W; McKee, Ann C; Stern, Robert A; Tripodis, Yorghos (J Alzheimers Dis, 2017)
The relationship between late-life body mass index (BMI) and Alzheimer's disease (AD) is poorly understood due to the lack of research in samples with autopsy-confirmed AD neuropathology (ADNP). The role of cerebrovascular disease (CVD) in the interplay between late-life BMI and ADNP is unclear. We conducted a retrospective longitudinal investigation and used joint modeling of linear mixed effects to investigate causal relationships among repeated antemortem BMI measurements, CVD (quantified neuropathologically), and ADNP in an autopsy sample of subjects across the AD clinical continuum. The sample included 1,421 subjects from the National Alzheimer's Coordinating Center's Uniform Data Set and Neuropathology Data Set with diagnoses of normal cognition (NC; n = 234), mild cognitive impairment (MCI; n = 201), or AD dementia (n = 986). ADNP was defined as moderate to frequent neuritic plaques and Braak stageIII-VI. Ischemic Injury Scale (IIS) operationalized CVD. Joint modeling examined relationships among BMI, IIS, and ADNP in the overall sample and stratified by initial visit Clinical Dementia Rating score. Subject-specific random intercept for BMI was the predictor for ADNP due to minimal BMI change (p = 0.3028). Analyses controlling for demographic variables and APOE ɛ4 showed lower late-life BMI predicted increased odds of ADNP in the overall sample (p < 0.001), and in subjects with CDR of 0 (p = 0.0021) and 0.5 (p = 0.0012), but not ≥1.0 (p = 0.2012). Although higher IIS predicted greater odds of ADNP (p < 0.0001), BMI did not predict IIS (p = 0.2814). The current findings confirm lower late-life BMI confers increased odds for ADNP. Lower late-life BMI may be a preclinical indicator of underlying ADNP.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Autopsy; Body Mass Index; Cerebrovascular Disorders; Datasets as Topic; Female; Humans; Male; National Institute on Aging (U.S.); Neuropathology; Neuropsychological Tests; Retrospective Studies; United States

Motor Phenotype in Neurodegenerative Disorders: Gait and Balance Platform Study Design Protocol for the Ontario Neurodegenerative Research Initiative (ONDRI). - Montero-Odasso, Manuel; Pieruccini-Faria, Frederico; Bartha, Robert; Black, Sandra E; Finger, Elizabeth; Freedman, Morris; Greenberg, Barry; Grimes, David A; Hegele, Robert A; Hudson, Christopher; Kleinstiver, Peter W; Lang, Anthony E; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The association of cognitive and motor impairments in Alzheimer's disease and other neurodegenerative diseases is thought to be related to damage in the common brain networks shared by cognitive and cortical motor control processes. These common brain networks play a pivotal role in selecting movements and postural synergies that meet an individual's needs. Pathology in this "highest level" of motor control produces abnormalities of gait and posture referred to as highest-level gait disorders. Impairments in cognition and mobility, including falls, are present in almost all neurodegenerative diseases, suggesting common mechanisms that still need to be unraveled. OBJECTIVE: To identify motor-cognitive profiles across neurodegenerative diseases in a large cohort of patients. METHODS: Cohort study that includes up to 500 participants, followed every year for three years, across five neurodegenerative disease groups: Alzheimer's disease/mild cognitive impairment, frontotemporal degeneration, vascular cognitive impairment, amyotrophic lateral sclerosis, and Parkinson's disease. Gait and balance will be assessed using accelerometers and electronic walkways, evaluated at different levels of cognitive and sensory complexity, using the dual-task paradigm. RESULTS: Comparison of cognitive and motor performances across neurodegenerative groups will allow the identification of motor-cognitive phenotypes through the standardized evaluation of gait and balance characteristics. CONCLUSIONS: As part of the Ontario Neurodegenerative Research Initiative (ONDRI), the gait and balance platform aims to identify motor-cognitive profiles across neurodegenerative diseases. Gait assessment, particularly while dual-tasking, will help dissect the cognitive and motor contribution in mobility and cognitive decline, progression to dementia syndromes, and future adverse outcomes including falls and mortality.

Motoric Cognitive Risk Syndrome: Association with Incident Dementia and Disability. - Doi, Takehiko; Shimada, Hiroyuki; Makizako, Hyuma; Tsutsumimoto, Kota; Verghese, Joe; Suzuki, Takao (J Alzheimers Dis, 2017)
BACKGROUND: It is important to examine the etiology of motoric cognitive risk syndrome (MCR) and its association with dementia and disability to obtain biological insights and to develop preventive strategies. OBJECTIVE: This study aimed to examine the association of MCR with incidence of dementia and disability in a Japanese community-dwelling sample of older adults. METHODS: Participants were 4,235 older adults (50% women, mean age: 72.0 years). MCR was diagnosed at baseline using established criteria in non-demented seniors with self-reported cognitive complaints and slow gait. Incident cases of dementia were identified from insurance data monthly. Disability was regarded as certification by long-term care insurance. RESULTS: At baseline, 265 participants (6.3%) met criteria for MCR. During follow-up (mean duration: 29 months), there were 138 incident cases of dementia (3.3%) and 207 incident cases of disability (4.9%). Cox-proportional hazards models, adjusted for demographical data, lifestyle, and medical conditions, showed that presence of MCR at baseline was a major risk factor for developing dementia (HR 2.49, 95% CI 1.52-4.10, p < 0.001). MCR also predicted risk for disability (HR 1.69, 95% CI 1.08-2.02, p < 0.001). CONCLUSIONS: MCR is helpful in the short-term prediction of risk for dementia and disability in the elderly Japanese population. Identification of seniors with MCR is recommended for early detection and instituting preventive measures for reducing the risk of dementia and disability.

A Multi-Cohort Study of ApoE ɛ4 and Amyloid-β Effects on the Hippocampus in Alzheimer's Disease. - Khan, Wasim; Giampietro, Vincent; Banaschewski, Tobias; Barker, Gareth J; Bokde, Arun L W; Büchel, Christian; Conrod, Patricia; Flor, Herta; Frouin, Vincent; Garavan, Hugh; Gowland, Penny; Heinz, Anreas; et al. (J Alzheimers Dis, 2017)
The apolipoprotein E (APOE) gene has been consistently shown to modulate the risk of Alzheimer's disease (AD). Here, using an AD and normal aging dataset primarily consisting of three AD multi-center studies (n = 1,781), we compared the effect of APOE and amyloid-β (Aβ) on baseline hippocampal volumes in AD patients, mild cognitive impairment (MCI) subjects, and healthy controls. A large sample of healthy adolescents (n = 1,387) was also used to compared hippocampal volumes between APOE groups. Subjects had undergone a magnetic resonance imaging (MRI) scan and APOE genotyping. Hippocampal volumes were processed using FreeSurfer. In the AD and normal aging dataset, hippocampal comparisons were performed in each APOE group and in ɛ4 carriers with positron emission tomography Aβ who were dichotomized (Aβ+/Aβ-) using previous cut-offs. We found a linear reduction in hippocampal volumes with ɛ4 carriers possessing the smallest volumes, ɛ3 carriers possessing intermediate volumes, and ɛ2 carriers possessing the largest volumes. Moreover, AD and MCI ɛ4 carriers possessed the smallest hippocampal volumes and control ɛ2 carriers possessed the largest hippocampal volumes. Subjects with both APOE ɛ4 and Aβ+ had the lowest hippocampal volumes when compared to Aβ- ɛ4 carriers, suggesting a synergistic relationship between APOE ɛ4 and Aβ. However, we found no hippocampal volume differences between APOE groups in healthy 14-year-old adolescents. Our findings suggest that the strongest neuroanatomic effect of APOE ɛ4 on the hippocampus is observed in AD and groups most at risk of developing the disease, whereas hippocampi of old and young healthy individuals remain unaffected.

Multiple Mechanisms Linking Type 2 Diabetes and Alzheimer's Disease: Testosterone as a Modifier. - Asih, Prita R; Tegg, Michelle L; Sohrabi, Hamid; Carruthers, Malcolm; Gandy, Samuel E; Saad, Farid; Verdile, Giuseppe; Ittner, Lars M; Martins, Ralph N (J Alzheimers Dis, 2017)
Evidence in support of links between type-2 diabetes mellitus (T2DM) and Alzheimer's disease (AD) has increased considerably in recent years. AD pathological hallmarks include the accumulation of extracellular amyloid-β (Aβ) and intracellular hyperphosphorylated tau in the brain, which are hypothesized to promote inflammation, oxidative stress, and neuronal loss. T2DM exhibits many AD pathological features, including reduced brain insulin uptake, lipid dysregulation, inflammation, oxidative stress, and depression; T2DM has also been shown to increase AD risk, and with increasing age, the prevalence of both conditions increases. In addition, amylin deposition in the pancreas is more common in AD than in normal aging, and although there is no significant increase in cerebral Aβ deposition in T2DM, the extent of Aβ accumulation in AD correlates with T2DM duration. Given these similarities and correlations, there may be common underlying mechanism(s) that predispose to both T2DM and AD. In other studies, an age-related gradual loss of testosterone and an increase in testosterone resistance has been shown in men; low testosterone levels can also occur in women. In this review, we focus on the evidence for low testosterone levels contributing to an increased risk of T2DM and AD, and the potential of testosterone treatment in reducing this risk in both men and women. However, such testosterone treatment may need to be long-term, and would need regular monitoring to maintain testosterone at physiological levels. It is possible that a combination of testosterone therapy together with a healthy lifestyle approach, including improved diet and exercise, may significantly reduce AD risk.

Neural Basis of Apathy in Patients with Amnestic Mild Cognitive Impairment. - Kazui, Hiroaki; Takahashi, Ryuichi; Yamamoto, Yuki; Yoshiyama, Kenji; Kanemoto, Hideki; Suzuki, Yukiko; Sato, Shunsuke; Azuma, Shingo; Suehiro, Takashi; Shimosegawa, Eku; Ishii, Kazunari; Tanaka, Toshihisa (J Alzheimers Dis, 2017)
BACKGROUND: Although apathy is associated with damage to the frontal and temporal lobes in Alzheimer's disease (AD), the crucial regions for apathy in patients with amnestic mild cognitive impairment (aMCI) are unknown. OBJECTIVE: To identify brain regions associated with apathy in aMCI patients. METHODS: The subjects of this study were 98 aMCI patients who were entered in our dementia registry between March 1, 2009 and April 30, 2015 and who satisfied our criteria for aMCI. The association between the apathy score of the Neuropsychiatric Inventory and regional gray matter volume was analyzed using voxel-based morphometry. The association between apathy score and regional cerebral blood flow (rCBF) measured with single photon emission computed tomography (SPECT) was analyzed using Statistical Parametric Mapping. RESULTS: The aMCI patients were classified into aMCI with and without "SPECT images suggestive of AD" (aMCI-AD+ and aMCI-AD-, respectively) based on the Z-score summation analysis method. In aMCI-AD+ (n = 31), apathy was significantly and negatively correlated with gray matter volume in the right caudate nucleus and with rCBF in five regions (left posterior-medial frontal lobe, right superior frontal lobe, bilateral culmen-fusiform gyri, and left occipital lobe). In aMCI-AD-(n = 67), apathy was significantly and negatively correlated with gray matter volumes in five regions but it was not correlated with rCBF in any regions. CONCLUSION: In patients with a high probability of being in the aMCI stage of AD, apathy was associated with atrophy of the right caudate nucleus and hypoperfusion in the frontal, temporal and occipital lobes.

Nitrosylation of Vesicular Transporters in Brain of Amyloid Precursor Protein/Presenilin 1 Double Transgenic Mice. - Wang, Ying; Zhou, Zhu; Tan, Hua; Zhu, Shenghua; Wang, Yiran; Sun, Yingxia; Li, Xin-Min; Wang, Jun-Feng (J Alzheimers Dis, 2017)
Nitric oxide can attack thiol groups of cysteine residues in proteins and induce protein cysteine S-nitrosylation. Cholinergic and glutamatergic systems are dysregulated in Alzheimer's disease. Vesicular acetylcholine transporter (VAChT) and vesicular glutamate transporter 1 (VGLUT1) are important in packaging acetylcholine and glutamate into vesicles, which is an important step for neurotransmission. Previously we found that VAChT and VGLUT1 can be nitrosylated and that S-nitrosylation of these transporters inhibits vesicular uptake of acetylcholine and glutamate. To understand the role of VAChT and VGLUT1 nitrosylation in the pathophysiological development of Alzheimer's disease, we analyzed nitrosylation of VAChT and VGLUT1 in brain of amyloid precursor protein (APP) and presenilin 1 (PS1) double transgenic mice, an animal model for Alzheimer's disease. Using a Morris water maze test, we found that 9- and 12-month-old APP/PS1 mice showed memory deficit, compared to wild type mice. We further found that total protein nitrosylation was increased in frontal cortex and hippocampus of 9- and 12-month-old APP/PS1 mice. Although nitrosylation of VAChT and VGLUT1 was not changed in hippocampus of 9- and 12-month-old APP/PS1 mice, nitrosylation of VAChT and VGLUT1 was significantly increased in frontal cortex of APP/PS1 mice at these ages. We also found that nitrosylation of VAChT and VGLUT1 was increased in hippocampus (but not frontal cortex) of 3-month-old APP/PS1 mice. These findings suggest that nitrosylation of VAChT and VGLUT1 may be associated with dysfunctional acetylcholinergic and glutamatergic neurotransmission in Alzheimer's disease.

No Genetic Overlap Between Circulating Iron Levels and Alzheimer's Disease. - Lupton, Michelle K; Benyamin, Beben; Proitsi, Petroula; Nyholt, Dale R; Ferreira, Manuel A; Montgomery, Grant W; Heath, Andrew C; Madden, Pamela A; Medland, Sarah E; Gordon, Scott D; Lovestone, Simon; Tsolaki, Magda; et al. (J Alzheimers Dis, 2017)
Iron deposition in the brain is a prominent feature of Alzheimer's disease (AD). Recently, peripheral iron measures have also been shown to be associated with AD status. However, it is not known whether these associations are causal: do elevated or depleted iron levels throughout life have an effect on AD risk? We evaluate the effects of peripheral iron on AD risk using a genetic profile score approach by testing whether variants affecting iron, transferrin, or ferritin levels selected from GWAS meta-analysis of approximately 24,000 individuals are also associated with AD risk in an independent case-control cohort (n∼10,000). Conversely, we test whether AD risk variants from a GWAS meta-analysis of approximately 54,000 account for any variance in iron measures (n∼9,000). We do not identify a genetic relationship, suggesting that peripheral iron is not causal in the initiation of AD pathology.

Non-Phosphorylated Tau as a Potential Biomarker of Alzheimer's Disease: Analytical and Diagnostic Characterization. - Lewczuk, Piotr; Lelental, Natalia; Lachmann, Ingolf; Holzer, Max; Flach, Katharina; Brandner, Sebastian; Engelborghs, Sebastiaan; Teunissen, Charlotte E; Zetterberg, Henrik; Molinuevo, José Luis; Mroczko, Barbara; Blennow, Kaj; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Virtually nothing is known about a potential diagnostic role of non-phospho-epitopes of Tau (Non-P-Tau) in cerebrospinal fluid (CSF). OBJECTIVE: To establish and analytically and clinically characterize the first assay capable to measure concentrations of Non-P-Tau in human CSF. METHODS: An antibody (1G2) was developed that selectively binds to the Tau molecule non-phosphorylated at the positions T175 and T181, and was used in establishing a sandwich ELISA capable to measure Non-P-Tau in human CSF, following analytical and clinical validation of the method. RESULTS: The 1G2 antibody shows decreasing reactivity to tau peptides containing phosphorylation mainly at positions T175 and T181. Detection limit of the assay is 25 pg/ml; the coefficients of variation (CVs) of the optical densities of the repeated standard curves were between 3.6-15.9%. Median intra-assay imprecision of double measurements was 4.8%; inter-assay imprecision was in the range of 11.2% - 15.3%. Non-P-Tau concentrations are stable in the CSF samples sent to distinct laboratories under ambient temperature; inter-laboratory variation was approximately 30%. The Non-P-Tau CSF concentrations were highly significantly increased in patients with Alzheimer's disease in stage of mild cognitive impairment or dementia (AD/MCI, n = 58, 109.2±32.0 pg/mL) compared to the non-demented Controls (n = 42, 62.1±9.3 pg/mL, p < 0.001). At the cut-off of 78.3 pg/mL, the sensitivity and the specificity were 94.8% and 97.6%, respectively. CONCLUSION: For the first time, an assay is reported to reliably measure concentrations of non-phosphorylated Tau in human CSF.

Novel Blood-Based Biomarkers of Cognition, Stress, and Physical or Cognitive Training in Older Adults at Risk of Dementia: Preliminary Evidence for a Role of BDNF, Irisin, and the Kynurenine Pathway. - Küster, Olivia C; Laptinskaya, Daria; Fissler, Patrick; Schnack, Cathrin; Zügel, Martina; Nold, Verena; Thurm, Franka; Pleiner, Sina; Karabatsiakis, Alexander; von Einem, Björn; Weydt, Patrick; Liesener, André; et al. (J Alzheimers Dis, 2017)
Psychosocial stress and physical, cognitive, and social activity predict the risk of cognitive decline and dementia. The aim of this study was to elucidate brain-derived neurotrophic factor (BDNF), irisin, and the kynurenine pathway (KP) as potential underlying biological correlates. We evaluated associations of irisin and the KP with BDNF in serum and with cognition, stress, and activities. Furthermore, changes in serum concentrations of BDNF, irisin, and KP metabolites were investigated after physical or cognitive training. Forty-seven older adults at risk of dementia were assigned to 10 weeks of physical training, cognitive training, or a wait-list control condition. Previous physical, cognitive, and social activities and stressful life events were recorded; global cognition, episodic memory, and executive functions were assessed. Serum levels of L-kynurenine, kynurenic acid, 3-hydroxykynurenine (3-HK), and quinolinic acid (QUIN) were determined by validated assays based on liquid chromatography coupled to tandem mass spectrometry. BDNF and irisin serum levels were determined with enzyme-linked immunosorbent assays. BDNF and irisin correlated positively with global cognition and episodic memory, while the neurotoxic metabolite QUIN correlated negatively with executive functions. Stressful life events were associated with reduced BDNF and increased 3-HK. 3-HK decreased after cognitive training, while BDNF tended to increase after physical training. This suggests that psychosocial stress as well as cognitive and physical training may impact BDNF serum levels and the KP. Irisin and QUIN may constitute novel serum biomarkers of cognitive impairment, in addition to BDNF. Larger scale trials are needed to replicate and extend these novel findings.

A Novel Loss-of-Function GRN Mutation p.(Tyr229*): Clinical and Neuropathological Features. - Kuuluvainen, Liina; Pöyhönen, Minna; Pasanen, Petra; Siitonen, Maija; Rummukainen, Jaana; Tienari, Pentti J; Paetau, Anders; Myllykangas, Liisa (J Alzheimers Dis, 2017)
Mutations in the progranulin (GRN) gene represent about 5-10% of frontotemporal lobar degeneration (FTLD). We describe a proband with a novel GRN mutation c.687T>A, p.(Tyr229*), presenting with dyspraxia, dysgraphia, and dysphasia at the age of 60 and a very severe FTLD neuropathological phenotype with TDP43 inclusions. The nephew of the proband had signs of dementia and personality changes at the age of 60 and showed similar but milder FTLD pathology. Three other family members had had early-onset dementia. Gene expression studies showed decreased GRN gene expression in mutation carriers' blood samples. In conclusion, we describe a novel GRN, p.(Tyr229*) mutation, resulting in haploinsufficiency of GRN and a severe neuropathologic FTLD phenotype.

Novel Phospho-Tau Monoclonal Antibody Generated Using a Liposomal Vaccine, with Enhanced Recognition of a Conformational Tauopathy Epitope. - Theunis, Clara; Adolfsson, Oskar; Crespo-Biel, Natalia; Piorkowska, Kasia; Pihlgren, Maria; Hickman, David T; Gafner, Valerie; Borghgraef, Peter; Devijver, Herman; Pfeifer, Andrea; Van Leuven, Fred; Muhs, Andreas (J Alzheimers Dis, 2017)
The microtubule-associated protein Tau is an intrinsically unfolded, very soluble neuronal protein. Under still unknown circumstances, Tau protein forms soluble oligomers and insoluble aggregates that are closely linked to the cause and progression of various brain pathologies, including Alzheimer's disease. Previously we reported the development of liposome-based vaccines and their efficacy and safety in preclinical mouse models for tauopathy. Here we report the use of a liposomal vaccine for the generation of a monoclonal antibody with particular characteristics that makes it a valuable tool for fundamental studies as well as a candidate antibody for diagnostic and therapeutic applications. The specificity and affinity of antibody ACI-5400 were characterized by a panel of methods: (i) measuring the selectivity for a specific phospho-Tau epitope known to be associated with tauopathy, (ii) performing a combination of peptide and protein binding assays, (iii) staining of brain sections from mouse preclinical tauopathy models and from human subjects representing six different tauopathies, and (iv) evaluating the selective binding to pathological epitopes on extracts from tauopathy brains in non-denaturing sandwich assays. We conclude that the ACI-5400 antibody binds to protein Tau phosphorylated at S396 and favors a conformation that is typically present in the brain of tauopathy patients, including Alzheimer's disease.

A Novel PSEN1 K311R Mutation Discovered in Chinese Families with Late-Onset Alzheimer's Disease Affects Amyloid-β Production and Tau Phosphorylation. - Dong, Jing; Qin, Wei; Wei, Cuibai; Tang, Yi; Wang, Qi; Jia, Jianping (J Alzheimers Dis, 2017)
BACKGROUND: Presenilin-1 (PSEN1) is the most frequently mutated gene in familial Alzheimer's disease (AD), whereas only several novel mutations have been reported in China and functional studies were seldom conducted. OBJECTIVE: We describe a novel PSEN1 K311R mutation in two Chinese families with late-onset AD and its functional impact on amyloid-β protein precursor (AβPP) processing and tau phosphorylation. METHODS: The mutation was detected by direct sequencing of PSEN1 exon 9. HEK293 cells stably expressing wild-type APP695 (HEK293-APP695wt) were transfected with plasmids containing human wild-type PSEN1, PSEN1 K311R mutation, and PSEN1 E280A mutation to compare the K311R mutation's effects on AβPP processing with other groups. In addition, each group of cells were co-transfected with plasmids harboring PSEN1 and human wild-type MAPT complementary DNA to study the mutation's impacts on tau phosphorylation. RESULTS: The K311R mutation was detected in probands of two late-onset AD families. Expression of the K311R or E280A mutation increased amyloid-β (Aβ)42 levels but decreased Aβ40 levels, resulting in an overall increase in the Aβ42/Aβ40 ratio compared to those in wild-type PSEN1 transfected cells (p < 0.05). The K311R or E280A mutation also increased the levels of phosphorylated tau compared to wild-type PSEN1 (p < 0.05). CONCLUSION: The K311R mutation might contribute to AD pathogenesis by overproducing toxic Aβ species and enhancing tau phosphorylation. Further in-depth studies are needed to decipher the pathogenic mechanisms of the K311R mutation in terms of AβPP cleavage, tau phosphorylation, and other presenilin-1 mediated functional pathways.

One-Year Evolution of Behavioral and Psychological Symptoms of Dementia in Patients Initially Hospitalized in Cognitive Behavioral Units: The EVITAL Prospective Cohort. - Rouch, Isabelle; Pongan, Elodie; Trombert, Béatrice; Fabre, Florence; Auguste, Nicolas; Sellier, Claire; Freulon, Magalie; Jacqueline, Sophie; Federico, Denis; Mouchoux, Christelle; Martin-Gaujard, Géraldine; Krolak-Salmon, Pierre; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The 2008-2012 French Alzheimer's Plan has provided hospital Cognitive and Behavioral Units (CBU) to improve the management of patients with productive behavioral and psychological symptoms of dementia (BPSD). Little is known concerning the behavioral outcome of these patients after discharge. OBJECTIVE: The present study investigated the long-term evolution of BPSD over one year after CBU discharge. METHODS: The EVITAL cohort included 221 participants admitted to the CBUs of 3 French hospitals. BPSD were collected using the Neuropsychiatric Inventory (NPI) at admission and 3, 6, and 12 months after hospitalization. The global NPI score evolution was assessed using a linear mixed-effect model. A four-factor model of the NPI including behavioral dyscontrol, psychosis, mood, and agitation subscores was also analyzed. RESULTS: Our analysis focused on 148 patients followed up during 12 months and evaluated at each visit. The global NPI score was 48.5 (SD 21.7) at baseline, 28.8 (SD 18.7) at 3-month, 23.2 (SD 16.4) at 6-month and 20.9 (SD 15.9) at 12-month follow-up. The score significantly decreased from baseline to follow-up (F = 109.3 p < 0.0001). Moreover, the decrease was observed for each NPI subscores. The Clinical Dementia Rating (CDR) scale score was significantly linked to the baseline NPI score (t = 2.76, p = 0.009). Conversely, the NPI decline was observed whatever the CDR level. CONCLUSION: The present study showed a decrease in the global NPI score and all its subscores during the year following the CBU hospitalization, regardless of the initial CDR score.

Oxidative Stress, Synaptic Dysfunction, and Alzheimer's Disease. - Tönnies, Eric; Trushina, Eugenia (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a devastating neurodegenerative disorder without a cure. Most AD cases are sporadic where age represents the greatest risk factor. Lack of understanding of the disease mechanism hinders the development of efficacious therapeutic approaches. The loss of synapses in the affected brain regions correlates best with cognitive impairment in AD patients and has been considered as the early mechanism that precedes neuronal loss. Oxidative stress has been recognized as a contributing factor in aging and in the progression of multiple neurodegenerative diseases including AD. Increased production of reactive oxygen species (ROS) associated with age- and disease-dependent loss of mitochondrial function, altered metal homeostasis, and reduced antioxidant defense directly affect synaptic activity and neurotransmission in neurons leading to cognitive dysfunction. In addition, molecular targets affected by ROS include nuclear and mitochondrial DNA, lipids, proteins, calcium homeostasis, mitochondrial dynamics and function, cellular architecture, receptor trafficking and endocytosis, and energy homeostasis. Abnormal cellular metabolism in turn could affect the production and accumulation of amyloid-β (Aβ) and hyperphosphorylated Tau protein, which independently could exacerbate mitochondrial dysfunction and ROS production, thereby contributing to a vicious cycle. While mounting evidence implicates ROS in the AD etiology, clinical trials with antioxidant therapies have not produced consistent results. In this review, we will discuss the role of oxidative stress in synaptic dysfunction in AD, innovative therapeutic strategies evolved based on a better understanding of the complexity of molecular mechanisms of AD, and the dual role ROS play in health and disease.

PCSK9 Promotes oxLDL-Induced PC12 Cell Apoptosis Through the Bcl-2/Bax-Caspase 9/3 Signaling Pathway. - Liu, Lu-Shan; Bai, Xue-Qin; Gao, Ya; Wu, Qi; Ren, Zhong; Li, Qing; Pan, Li-Hong; He, Ni-Ya; Peng, Juan; Tang, Zhi-Han (J Alzheimers Dis, 2017)
BACKGROUND: Hyperlipidemia is a risk factor for neurodegenerative diseases. Proprotein convertase subtilisin / Kexin type 9 (PCSK9) degrades hepatic low-density lipoprotein receptor (LDLR) to regulate lipid metabolism. It is unclear if PCSK9 plays a role in neurodegenerative diseases. OBJECTIVE: This study was designed to determine whether PCSK9 is crucial between hyperlipidemia and Alzheimer's disease. The interrelationship between PCSK9 and neuronal apoptosis was explored in PC12 cells in response to treatment with oxidized low-density lipoprotein (oxLDL). METHODS: Cultured PC12 cells were serum-starved and incubated with different concentrations of oxLDL for 24 h. Intracytoplasmic lipid droplets were observed by oil red O staining. Morphological assessment of apoptotic cells was performed using Hoechst 33258 staining and flow cytometry analysis. The expression of mRNA and protein was detected by reverse-transcription polymerase chain reaction (RT-PCR) and western blot analyses, respectively. Transfection of small interfering RNA (siRNA) into PC12 cells was conducted using HiperFect Transfection Reagent. Concentrations of Aβ40 and Aβ42 were detected by enzyme-linked immunosorbent assay (ELISA) kit. RESULTS: Intracellular lipid content, the number of apoptotic cells, and PCSK9 expression were increased in PC12 cells after oxLDL treatment. Transfection with PCSK9 siRNA reduced the oxLDL-induced apoptosis of PC12 cells. We further confirmed the involvement of Bcl-2/Bax-Caspase (9, 3) signaling pathway in the regulation of PC12 cells apoptosis.β-Secretase 1, another target gene of PCSK9, was downregulated in PC12 cells in response to oxLDL treatment. Aβ40 and Aβ42 contents were also decreased. CONCLUSION: PCSK9 promotes oxLDL-induced PC12 cell apoptosis through the Bcl-2/Bax-Caspase 9/3 signaling pathway.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Animals; Apoptosis; bcl-2-Associated X Protein; Caspases; Culture Media, Serum-Free; Dose-Response Relationship, Drug; Flow Cytometry; Lipid Metabolism; Lipoproteins, LDL; PC12 Cells; Peptide Fragments; Proprotein Convertase 9; Proto-Oncogene Proteins c-bcl-2; Rats; RNA, Messenger; RNA, Small Interfering; Signal Transduction; Transfection

PE859, A Novel Curcumin Derivative, Inhibits Amyloid-β and Tau Aggregation, and Ameliorates Cognitive Dysfunction in Senescence-Accelerated Mouse Prone 8. - Okuda, Michiaki; Fujita, Yuki; Hijikuro, Ichiro; Wada, Mei; Uemura, Takuya; Kobayashi, Yukako; Waku, Tomonori; Tanaka, Naoki; Nishimoto, Takaaki; Izumi, Yasuhiko; Kume, Toshiaki; Akaike, Akinori; et al. (J Alzheimers Dis, 2017)
Aggregation of amyloid-β (Aβ) and tau plays a crucial role in the onset and progression of Alzheimer's disease (AD). Therefore, the inhibition of Aβ and tau aggregation may represent a potential therapeutic target for AD. Herein, we designed and synthesized both Aβ and tau dual aggregation inhibitors based on the structure of curcumin and developed the novel curcumin derivative PE859. In this study, we investigated the inhibitory activity of PE859 on Aβ aggregationin vitro and the therapeutic effects of PE859 on cognitive dysfunction via dual inhibition of Aβ and tau aggregation in vivo. PE859 inhibited Aβ aggregation in vitro and protected cultured cells from Aβ-induced cytotoxicity. Furthermore, PE859 ameliorated cognitive dysfunction and reduced the amount of aggregated Aβ and tau in brains of senescence-accelerated mouse prone 8 (SAMP8). These results warrant consideration of PE859 as a candidate drug for AD.

Perception and Reality of Cognitive Function: Information Processing Speed, Perceived Memory Function, and Perceived Task Difficulty in Older Adults. - Torrens-Burton, Anna; Basoudan, Nasreen; Bayer, Antony J; Tales, Andrea (J Alzheimers Dis, 2017)
This study examines the relationships between two measures of information processing speed associated with executive function (Trail Making Test and a computer-based visual search test), the perceived difficulty of the tasks, and perceived memory function (measured by the Memory Functioning Questionnaire) in older adults (aged 50+ y) with normal general health, cognition (Montreal Cognitive Assessment score of 26+), and mood. The participants were recruited from the community rather than through clinical services, and none had ever sought or received help from a health professional for a memory complaint or mental health problem. For both the trail making and the visual search tests, mean information processing speed was not correlated significantly with perceived memory function. Some individuals did, however, reveal substantially slower information processing speeds (outliers) that may have clinical significance and indicate those who may benefit most from further assessment and follow up. For the trail making, but not the visual search task, higher levels of subjective memory dysfunction were associated with a greater perception of task difficulty. The relationship between actual information processing speed and perceived task difficulty also varied with respect to the task used. These findings highlight the importance of taking into account the type of task and metacognition factors when examining the integrity of information processing speed in older adults, particularly as this measure is now specifically cited as a key cognitive subdomain within the diagnostic framework for neurocognitive disorders.

PET Tau and Amyloid-β Burden in Mild Alzheimer's Disease: Divergent Relationship with Age, Cognition, and Cerebrospinal Fluid Biomarkers. - Koychev, Ivan; Gunn, Roger N; Firouzian, Azadeh; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil; Sahakian, Barbara J; Rowe, James B; Thomas, Alan; Rochester, Lynn; Ffytche, Dominic; Howard, Robert; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Combining PET amyloid-β (Aβ) and tau imaging may be critical for tracking disease progression in Alzheimer's disease (AD). OBJECTIVE: We sought to characterize the relationship between Aβ and tau ligands as well as with other measures of pathology. METHODS: We conducted a multi-center observational study in early AD (MMSE >20) participants aged 50 to 85 y. The schedule included cognitive assessments (ADAS-Cog) and CSF measurement of Aβ and tau at baseline and 6 months; PET-CT imaging with Aβ ([18F]AV45) and tau ([18F]AV1451) ligands at baseline. RESULTS: 22 participants took part in the study with 20 completing its 6-month duration and 12 having both tau and amyloid PET. The PET biomarker analysis revealed a strong negative correlation between age and tau in multiple regions. Entorhinal cortex tau and age interacted significantly in terms of cognitive change over 6 months which may have been to older participants deteriorating faster despite lower levels of cortical tau. Cortical Aβ associated with entorhinal cortex tau while CSF tau/Aβ ratio correlated strongly with cortical tau but not Aβ. CONCLUSION: The negative relationship between age and cortical tau whereby younger patients with mild AD had relatively greater tau burden is potentially important. It suggests that younger-age onset AD may be primarily driven by tau pathology while AD developing later may depend on a multitude of pathological mechanisms. These data also suggest that PET-tau performs better than PET-amyloid in predicting the best validated AD diagnostic marker- the CSF total tau/Aβ ratio.

Physical Exercise with Music Maintains Activities of Daily Living in Patients with Dementia: Mihama-Kiho Project Part 21. - Satoh, Masayuki; Ogawa, Jun-Ichi; Tokita, Tomoko; Nakaguchi, Noriko; Nakao, Koji; Kida, Hirotaka; Tomimoto, Hidekazu (J Alzheimers Dis, 2017)
BACKGROUND: Recent studies suggest that combined non-pharmacological interventions are more beneficial than single interventions for primary and secondary prevention of dementia. We previously reported enhanced effects of physical exercise with music (ExM) on cognitive function in normal elderly people compared to exercise alone. OBJECTIVE: To identify if ExM improves cognitive function and activities of daily livings (ADLs) in dementia patients over cognitive stimulation (CS). METHODS: We enrolled 85 patients with mild to moderate dementia. Forty-three subjects performed ExM developed by the Yamaha Music Foundation, and 42 subjects performed cognitive stimulation using portable game consoles and drills involving easy calculations, mazes, and mistake-searching in pictures. Interventions were performed once a week for 40 minutes. Before and after the six-month intervention, patients were assessed using neuropsychological batteries, and ADLs were assessed by patients' caregivers using the functional independence measure (FIM). Voxel-based specific regional analysis system for Alzheimer's disease (VSRAD) was used to assess medial temporal lobe atrophy. RESULTS: Twenty-three subjects dropped out during the intervention. Thirty-one patients from each group were analyzed. Post-intervention, both groups showed significantly improved visuospatial function. Significant benefits were observed in psychomotor speed or memory in the ExM or CS groups, respectively. FIM scores, reflecting ADLs, and VSRAD scores were significantly preserved in the ExM group, but significantly worsened in the CS group. CONCLUSIONS: ExM produced greater positive effects on cognitive function and ADLs in patients with mild to moderate dementia than CS, excluding memory. Optimal interventions for dementia will likely be achieved by combining ExMand CS.

Plasma Amyloid-β and Alzheimer's Disease-Related Changes in Late-Life Depression. - Yamazaki, Chiemi; Tamaoki, Toshio; Nunomura, Akihiko; Tamai, Kenichi; Yasuda, Kazuyuki; Motohashi, Nobutaka (J Alzheimers Dis, 2017)
To elucidate an involvement of amyloid dysmetabolism in the pathophysiology of depression, we investigated associations of plasma amyloid-β (Aβ) levels with Alzheimer's disease-related changes in neuroimaging and cognitive dysfunction in patients with late-life depression. Higher plasma Aβ40, but not Aβ42 nor Aβ40/Aβ42 ratio, was associated with higher degree of parahippocampal atrophy and lower verbal fluency performance. Indeed, high plasma Aβ40 predicted poor cognitive prognosis of depressed patients with mild cognitive impairment. As an anti-depressive treatment, electroconvulsive therapy (ECT) resulted in a marginally significant reduction of plasma Aβ40 compared to pharmacotherapy alone, suggesting protective effects of ECT against amyloid dysmetabolism.

Plasma Amyloid-β Peptides in Type 2 Diabetes: A Matched Case-Control Study. - Peters, Kirsten E; Davis, Wendy A; Taddei, Kevin; Martins, Ralph N; Masters, Colin L; Davis, Timothy M E; Bruce, David G (J Alzheimers Dis, 2017)
BACKGROUND: Plasma amyloid-β (Aβ) levels have rarely been investigated in type 2 diabetes despite its known associations with Alzheimer's disease. OBJECTIVE: To compare blood plasma Aβ concentrations (Aβ40 and Aβ42) in cognitively normal individuals with and without type 2 diabetes. METHODS: Plasma Aβ40 and Aβ42 were measured in 194 participants with diabetes recruited from the community-based Fremantle Diabetes Study Phase II cohort (mean age 71 years, 59% males) and 194 age-, sex-, and APOEɛ4 allele-matched, control subjects without diabetes from the Australian Imaging, Biomarkers and Lifestyle Study using a multiplex microsphere-based immunoassay. RESULTS: Plasma Aβ40 and Aβ42 were normally distributed in the controls but were bimodal in the participants with diabetes. Median Aβ40 and Aβ42 concentrations were significantly lower in those with type 2 diabetes (Aβ40 median [inter-quartile range]: 125.0 [52.6-148.3] versus 149.3 [134.0-165.6] pg/mL; Aβ42: 26.9 [14.5-38.3] versus 33.6 [28.0-38.9] pg/mL, both p < 0.001) while the ratio Aβ42:Aβ40 was significantly higher (0.26 [0.23-0.32] versus 0.22 [0.19-0.25], p < 0.001). After adjustment, participants with diabetes and plasma Aβ40 levels in the low peak of the bimodal distribution were significantly more likely to have normal to high estimated glomerular filtration rates (odds ratio (95% CI): 2.40 (1.20-4.80), p = 0.013) although the group with diabetes had lower renal function overall. CONCLUSION: Type 2 diabetes is associated with altered plasma concentrations of Aβ peptides and is an important source of variation that needs to be taken into account when considering plasma Aβ peptides as biomarkers for Alzheimer's disease.

Plasma Tau Association with Brain Atrophy in Mild Cognitive Impairment and Alzheimer's Disease. - Deters, Kacie D; Risacher, Shannon L; Kim, Sungeun; Nho, Kwangsik; West, John D; Blennow, Kaj; Zetterberg, Henrik; Shaw, Leslie M; Trojanowski, John Q; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2017)
BACKGROUND: Peripheral (plasma) and central (cerebrospinal fluid, CSF) measures of tau are higher in Alzheimer's disease (AD) relative to prodromal stages and controls. While elevated CSF tau concentrations have been shown to be associated with lower grey matter density (GMD) in AD-specific regions, this correlation has yet to be examined for plasma in a large study. OBJECTIVE: Determine the neuroanatomical correlates of plasma tau using voxel-based analysis. METHODS: Cross-sectional data for 508 ADNI participants were collected for clinical, plasma total-tau (t-tau), CSF amyloid (Aβ42) and tau, and MRI variables. The relationship between plasma tau and GMD and between CSF t-tau and GMD were assessed on a voxel-by-voxel basis using regression models. Age, sex, APOEɛ4 status, diagnosis, and total intracranial volume were used as covariates where appropriate. Participants were defined as amyloid positive (Aβ+) if CSF Aβ42 was <192 pg/mL. RESULTS: Plasma tau was negatively correlated with GMD in the medial temporal lobe (MTL), precuneus, thalamus, and striatum. The associations with thalamus and striatum were independent of diagnosis. A negative correlation also existed between plasma tau and GMD in Aβ+ participants in the MTL, precuneus, and frontal lobe. When compared to CSF t-tau, plasma tau showed a notably different associated brain atrophy pattern, with only small overlapping regions in the fusiform gyrus. CONCLUSION: Plasma tau may serve as a non-specific marker for neurodegeneration but is still relevant to AD considering low GMD was associated with plasma tau in Aβ+ participants and not Aβ-participants.

Potentially Inappropriate Medication in Community-Dwelling Primary Care Patients who were Screened Positive for Dementia. - Wucherer, Diana; Eichler, Tilly; Hertel, Johannes; Kilimann, Ingo; Richter, Steffen; Michalowsky, Bernhard; Thyrian, Jochen René; Teipel, Stefan; Hoffmann, Wolfgang (J Alzheimers Dis, 2017)
BACKGROUND: Potentially inappropriate medication (PIM) in older people is a risk factor for adverse drug effects. This risk is even higher in older people with dementia (PWD). OBJECTIVE: Our study aimed to determine (1) the prevalence of PIM among primary care patients who were screened positive for dementia and (2) the sociodemographic and clinical variables associated with the use of PIM. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized, controlled intervention study to implement and evaluate an innovative concept of collaborative dementia care management in Germany. The comprehensive baseline assessment includes a home medication review. The present analyses are based on the data from 448 study participants (age 70+, DemTect <9). PIMs were identified using the list of Potentially Inappropriate Medications in the Elderly (Priscus). RESULTS: (1) A total of 99 study participants (22%) received at least one PIM. The highest prevalence was found for antidepressants, benzodiazepines, and analgetics. The most frequently prescribed PIMs were amitriptyline, etoricoxib, and doxazosin. (2) Use of a PIM was significantly associated with a diagnosis of a mental or behavioral disorder. CONCLUSIONS: The prescription rate of PIMs for community-dwelling PWD was comparable with the rates found for the general population of older people in Germany (20-29%). Antidepressants with anticholinergic properties and long-acting benzodiazepines were the most prescribed PIMs, despite having an unfavorable benefit-risk ratio. This high prevalence of PIM prescriptions in a vulnerable population of PWD indicates that standard care for dementia should include careful medication review and management.

Precuneus Failures in Subjects of the PSEN1 E280A Family at Risk of Developing Alzheimer's Disease Detected Using Quantitative Electroencephalography. - Ochoa, John Fredy; Alonso, Joan Francesc; Duque, Jon Edinson; Tobón, Carlos Andrés; Baena, Ana; Lopera, Francisco; Mañanas, Miguel Angel; Hernández, Alher Mauricio (J Alzheimers Dis, 2017)
BACKGROUND: Presenilin-1 (PSEN1) mutations are the most common cause of familial early onset Alzheimer's disease (AD). The PSEN1 E280A (E280A) mutation has an autosomal dominant inheritance and is involved in the production of amyloid-β. The largest family group of carriers with E280A mutation is found in Antioquia, Colombia. The study of mutation carriers provides a unique opportunity to identify brain changes in stages previous to AD. Electroencephalography (EEG) is a low cost and minimally invasiveness technique that enables the following of brain changes in AD. OBJECTIVE: To examine how previous reported differences in EEG for Theta and Alpha-2 rhythms in E280A subjects are related to specific regions in cortex and could be tracked across different ages. METHODS: EEG signals were acquired during resting state from non-carriers and carriers, asymptomatic and symptomatic subjects from E280A kindred from Antioquia, Colombia. Independent component analysis (ICA) and inverse solution methods were used to locate brain regions related to differences in Theta and Alpha-2 bands. RESULTS: ICA identified two components, mainly related to the Precuneus, where the differences in Theta and Alpha-2 exist simultaneously at asymptomatic and symptomatic stages. When the ratio between Theta and Alpha-2 is used, significant correlations exist with age and a composite cognitive scale. CONCLUSION: Theta and Alpha-2 rhythms are altered in E280A subjects. The alterations are possible to track at Precuneus regions using EEG, ICA, and inverse solution methods.

Predictors of Discharge Destinations and Three-Month Evolution of Patients Initially Hospitalized in a Cognitive Behavioral Unit. - Pongan, Elodie; Dorey, Jean-Michel; Krolak-Salmon, Pierre; Federico, Denis; Sellier, Claire; Auguste, Nicolas; Fabre, Florence; Laurent, Bernard; Trombert-Paviot, Béatrice; Rouch, Isabelle (J Alzheimers Dis, 2017)
BACKGROUND: Previous studies showed that a third of patients living at home entered an institution after hospitalization in Cognitive and Behavioral Units (CBUs). OBJECTIVE: The main objective of this study was to identify predictors of discharge destination for these patients. The secondary objective was to estimate whether institutionalization can have an impact on a patient's long-term prognosis. METHODS: The study population was selected from the EVITAL study and included 140 participants living at home before hospitalization in CBUs. Factors favoring nursing-home admission were investigated and the impact of discharge destinations (i.e., home or nursing home) on patients' prognosis was examined. RESULTS: Institutionalized patients were more likely to be women (F = 4.7; p = 0.03), with a higher dementia severity (F = 9.82; p = 0.007), often living alone (F = 19.69; p = 0.001), with a caregiver other than spouse (F = 8.93; p = 0.003), and with a higher patient quality of life (QoL) according to the caregiver (F = 11.73; p = 0.001). When using multivariate logistic linear regressions, we showed a relationship between marital status (OR = 0.19, 95% CI: 0.08-0.43, p < 0.001), dementia severity (OR = 0.15, 95% CI: 0.03-0.79, p = 0.03), QoL (OR = 0.88, 95% CI: 0.79-0.98, p = 0.017), and institutionalization. At three months, a higher overall rate of rehospitalization (F = 12.21; p < 0.001) and rehospitalization for behavioral and psychological symptoms of dementia (F = 6.76; p = 0.006) were observed for patients staying at home after CBU discharge. CONCLUSION: Our study allows for a better understanding of the institutionalization risk factors of the patients hospitalized in CBUs. Identification of these factors could help clinicians to better support patients and to help the transition to be smoother. Moreover, our results suggest that prognosis of institutionalized patients is not unfavorable when compared with patients staying at home.

A Preliminary Study on the Feasibility of Using a Virtual Reality Cognitive Training Application for Remote Detection of Mild Cognitive Impairment. - Zygouris, Stelios; Ntovas, Konstantinos; Giakoumis, Dimitrios; Votis, Konstantinos; Doumpoulakis, Stefanos; Segkouli, Sofia; Karagiannidis, Charalampos; Tzovaras, Dimitrios; Tsolaki, Magda (J Alzheimers Dis, 2017)
BACKGROUND: It has been demonstrated that virtual reality (VR) applications can be used for the detection of mild cognitive impairment (MCI). OBJECTIVE: The aim of this study is to provide a preliminary investigation on whether a VR cognitive training application can be used to detect MCI in persons using the application at home without the help of an examiner. METHODS: Two groups, one of healthy older adults (n = 6) and one of MCI patients (n = 6) were recruited from Thessaloniki day centers for cognitive disorders and provided with a tablet PC with custom software enabling the self-administration of the Virtual Super Market (VSM) cognitive training exercise. The average performance (from 20 administrations of the exercise) of the two groups was compared and was also correlated with performance in established neuropsychological tests. RESULTS: Average performance in terms of duration to complete the given exercise differed significantly between healthy(μ  = 247.41 s/ sd = 89.006) and MCI (μ= 454.52 s/ sd = 177.604) groups, yielding a correct classification rate of 91.8% with a sensitivity and specificity of 94% and 89% respectively for MCI detection. Average performance also correlated significantly with performance in Functional Cognitive Assessment Scale (FUCAS), Test of Everyday Attention (TEA), and Rey Osterrieth Complex Figure test (ROCFT). DISCUSSION: The VR application exhibited very high accuracy in detecting MCI while all participants were able to operate the tablet and application on their own. Diagnostic accuracy was improved compared to a previous study using data from only one administration of the exercise. The results of the present study suggest that remote MCI detection through VR applications can be feasible.

Protein Expression of BACE1 is Downregulated by Donepezil in Alzheimer's Disease Platelets. - Sarno, Tamires Alves; Talib, Leda Leme; Joaquim, Helena Passarelli Giroud; Bram, Jessyka Maria de França; Gattaz, Wagner Farid; Forlenza, Orestes Vicente (J Alzheimers Dis, 2017)
BACKGROUND: Abnormal amyloid-β protein precursor (AβPP) metabolism is a key feature of Alzheimer's disease (AD). Platelets contain most of the enzymatic machinery required for AβPP processing, and correlates of intracerebral abnormalities have been demonstrated in platelets of patients with AD. Thus, AβPP-related molecules in platelets may be regarded as peripheral markers of AD. OBJECTIVE: We sought to determine the protein expression of the AβPP secretases (ADAM10, BACE1, and PSEN1) and AβPP ratio in platelets of patients with mild or moderate AD compared to healthy controls. We further determined whether the protein expression of these markers might be modified by chronic treatment with donepezil. METHODS: Platelet samples were obtained from patients and controls at baseline and after 3 and 6 months of continuous treatment with therapeutic doses of donepezil. The protein expression of platelet markers was determined by western blotting. RESULTS: AD patients had a significant decrease in AβPP ratio, ADAM10, and PSEN1 compared to controls at baseline, but these differences were not modified by the treatment. Nonetheless, a significant reduction in the protein expression of BACE1 was observed in patients treated with donepezil for 6 months. CONCLUSION: Our results corroborate previous findings from our group and others of decreased AβPP ratio and protein expression of ADAM10 in AD. We further show that PSEN1 is decreased in AD platelets, and that the protein expression of BACE1 is downregulated by chronic treatment with donepezil. This effect may be interpreted as evidence of disease modification.

Reduction of RPT6/S8 (a Proteasome Component) and Proteasome Activity in the Cortex is associated with Cognitive Impairment in Lewy Body Dementia. - Alghamdi, Amani; Vallortigara, Julie; Howlett, David R; Broadstock, Martin; Hortobágyi, Tibor; Ballard, Clive; Thomas, Alan J; O'Brien, John T; Aarsland, Dag; Attems, Johannes; Francis, Paul T; Whitfield, David R (J Alzheimers Dis, 2017)
Lewy body dementia is the second most common neurodegenerative dementia and is pathologically characterized by α-synuclein positive cytoplasmic inclusions, with varying amounts of amyloid-β (Aβ) and hyperphosphorylated tau (tau) aggregates in addition to synaptic loss. A dysfunctional ubiquitin proteasome system (UPS), the major proteolytic pathway responsible for the clearance of short lived proteins, may be a mediating factor of disease progression and of the development of α-synuclein aggregates. In the present study, protein expression of a key component of the UPS, the RPT6 subunit of the 19S regulatory complex was determined. Furthermore, the main proteolytic-like (chymotrypsin- and PGPH-) activities have also been analyzed. The middle frontal (Brodmann, BA9), inferior parietal (BA40), and anterior cingulate (BA24) gyrus' cortex were selected as regions of interest from Parkinson's disease dementia (PDD, n = 31), dementia with Lewy bodies (DLB, n = 44), Alzheimer's disease (AD, n = 16), and control (n = 24) brains. Clinical and pathological data available included the MMSE score. DLB, PDD, and AD were characterized by significant reductions of RPT6 (one-way ANOVA, p < 0.001; Bonferroni post hoc test) in prefrontal cortex and parietal cortex compared with controls. Strong associations were observed between RPT6 levels in prefrontal, parietal cortex, and anterior cingulate gyrus and cognitive impairment (p = 0.001, p = 0.001, and p = 0.008, respectively). These findings highlight the involvement of the UPS in Lewy body dementia and indicate that targeting the UPS may have the potential to slow down or reduce the progression of cognitive impairment in DLB and PDD.

Relation of Odor Identification with Alzheimer's Disease Markers in Cerebrospinal Fluid and Cognition. - Reijs, Babette L R; Ramakers, Inez H G B; Elias-Sonnenschein, Lyzel; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Johannsen, Peter; Vanderstichele, Hugo; Verhey, Frans; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Impaired olfactory function is an early characteristic of Alzheimer's disease (AD), but it remains unclear if odor identification also relates to early markers of AD in cerebrospinal fluid (CSF). OBJECTIVE: To investigate the association between odor identification and amyloid-β 1-42 (Aβ42) and total tau (t-tau) concentrations in CSF. In addition, to examine the relation between odor identification and cognitive function at baseline and at follow-up, and whether these associations are moderated by CSF Aβ42 and t-tau and apolipoprotein E (APOE) genotype. METHODS: We included 160 individuals (40 with normal cognition, 45 with mild cognitive impairment (MCI), 42 with AD-type dementia, and 26 individuals with non-AD dementia) from the EDAR study. Individuals were recruited from six memory clinics across Europe. Odor identification was tested with the brief University of Pennsylvania Smell Identification Test. CSF Aβ42 and t-tau were assessed with INNO-BIA AlzBio3 Luminex assay. Neuropsychological assessment included tests for verbal memory, verbal fluency, attention, executive function, and visuoconstruction. Follow-up was performed within 3 years after baseline. RESULTS: Lower odor identification scores correlated with increased CSF t-tau concentrations and with lower scores on all cognitive measures at baseline independent of diagnostic group. Lower odor identification scores predicted decline on the MMSE in the total group, and decline on wordlist learning and delayed recall in APOE ɛ4 carriers and in individuals with abnormal Aβ42. CONCLUSION: Odor identification impairment may be an indicator of neuronal injury rather than amyloid pathology.

The Relationships Between Components of Metabolic Syndrome and Mild Cognitive Impairment Subtypes: A Cross-Sectional Study of Japanese Older Adults. - Bae, Seongryu; Shimada, Hiroyuki; Lee, Sangyoon; Makizako, Hyuma; Lee, Sungchul; Harada, Kazuhiro; Doi, Takehiko; Tsutsumimoto, Kota; Hotta, Ryo; Nakakubo, Sho; Park, Hyuntae; Suzuki, Takao (J Alzheimers Dis, 2017)
BACKGROUND: The associations between components of metabolic syndrome (MetS) and mild cognitive impairment (MCI) subtypes remain unclear. OBJECTIVE: The study aim was to identify the prevalence of MetS for MCI subtypes and to investigate sex differences in the association between MetS and MCI subtypes in older Japanese adults. METHODS: The study analyzed data from 3,312 men and women aged 70 years or more. MetS was diagnosed according to International Diabetes Federation criteria. Participants completed cognitive tests and were categorized into normal cognition, amnestic MCI (aMCI), and non-amnestic MCI (naMCI). The associations between MetS and its components and MCI subtypes were analyzed using multiple logistic regression. RESULTS: MetS prevalence was greater in participants with naMCI (men: p = 0.030; women: p = 0.040). Participants with naMCI showed higher odds ratios (OR) of MetS (men: 2.45, 95% confidence intervals (CI): 1.13-5.32; women: OR: 1.94, 95% CI: 1.12-3.39) compared with participants with normal cognition. MetS was not associated with aMCI. Analysis of MetS components showed that raised glucose (OR: 1.62, 95% CI: 1.19-2.22) and reduced high-density lipoprotein cholesterol (OR: 1.97, 95% CI: 1.25-3.12) were associated with naMCI in men. In women, raised blood pressure (OR: 1.42, 95% CI: 1.03-1.94) and raised glucose (OR: 1.32, 95% CI: 1.02-1.71) were associated with naMCI. CONCLUSION: MetS was associated only with naMCI regardless of sex, which suggests etiologic differences in MCI subtypes. We also found sex differences in the relationship between naMCI risk and MetS and its components.

Rhamnolipids, Microbial Virulence Factors, in Alzheimer's Disease. - Andreadou, Eleni; Pantazaki, Anastasia A; Daniilidou, Makrina; Tsolaki, Magda (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) has been attributed to chronic bacterial infections. The recognition of human microbiota as a substantial contributor to health and disease is relatively recent and growing. During evolution, mammals live in a symbiotic state with myriads of microorganisms that survive at a diversity of tissue micro-surroundings. Microbes produce a plethora of secretory products [amyloids, lipopolysaccharides, virulence factors rhamnolipids (RLs), toxins, and a great number of neuroactive compounds]. The contribution of infectious microbial components to the pathophysiology of the human central nervous system including AD is considered potentially substantial, but the involvement of the RLs has never been reported. Here, RLs were isolated from serum and identified through various conventional methods including the colorimetric orcinol method, thin-layer chromatography, attenuated total reflection Fourier transform infrared (ATR-FTIR), and dot blot using antibodies against RLs. Dot blot demonstrated elevated RL levels in sera of AD patients compared to controls (p = 0.014). Moreover, ELISA showed similarly elevated RL levels in cerebrospinal fluid of both AD (0.188 versus 0.080) (p = 0.04) and mild cognitive impairment (0.188 versus 0.129) (p = 0.088) patients compared to healthy, and are well-correlated with the AD stages severity assessed using the Mini-Mental State Examination. These results provide conclusive evidence for the newly-reported implication of RLs in AD, adding it to the list of bacterial components, opening new avenues for AD investigation. Moreover, they strengthen and vindicate the divergence of research toward the exploration of bacterial involvement in AD generation and progression.

Risk of Mortality Associated with Antipsychotic Monotherapy and Polypharmacy Among Community-Dwelling Persons with Alzheimer's Disease. - Koponen, Marjaana; Taipale, Heidi; Lavikainen, Piia; Tanskanen, Antti; Tiihonen, Jari; Tolppanen, Anna-Maija; Ahonen, Riitta; Hartikainen, Sirpa (J Alzheimers Dis, 2017)
We aimed to analyze the risk of non-cancer mortality according to duration of antipsychotic use and to compare the risk associated with polypharmacy and monotherapy among community-dwellers with Alzheimer's disease (AD). The risk of mortality between most frequently used antipsychotic drugs was compared. Data from a nationwide register-based MEDALZ study that included all 70,718 community-dwellers newly diagnosed with AD during 2005-2011 in Finland was utilized. Death, excluding cancer as direct cause of death, was extracted from Causes of Death Register. Incident antipsychotic use was compared with time without antipsychotics with Cox proportional hazard models. Antipsychotic use was associated with an increased risk of mortality (adjusted hazard ratio [aHR] 1.61; 95% Confidence Interval [CI] 1.53-1.70). The absolute difference in mortality rate was 4.58 (95% CI 4.53-4.63) deaths per 100 person-years. The risk of mortality was increased from the first days of use and attenuated gradually but remained increased even after two years of use (aHR 1.30; 95% CI 1.16-1.46). Compared with nonuse, antipsychotic polypharmacy (aHR 2.88; 95% CI 2.38-3.49) was associated with an increased risk of mortality than monotherapy (aHR 1.57; 95% CI 1.49-1.66). Haloperidol was associated with higher risk of mortality (aHR 1.52; 95% CI 1.14-2.02) and quetiapine with lower risk (aHR 0.84; 95% CI 0.75-0.94) compared with risperidone. In conclusion, the findings support current treatment guidelines on having a high threshold for antipsychotic initiation among persons with AD. Antipsychotic polypharmacy and long-term use should be avoided and drug choice should be weighed against risk/benefit evidence.

The Road Less Traveled: Alternative Pathways for Action-Verb Processing in Parkinson's Disease. - Abrevaya, Sofía; Sedeño, Lucas; Fitipaldi, Sol; Pineda, David; Lopera, Francisco; Buritica, Omar; Villegas, Andrés; Bustamante, Catalina; Gomez, Diana; Trujillo, Natalia; Pautassi, Ricardo; Ibáñez, Agustín; et al. (J Alzheimers Dis, 2017)
Action verbs are critically embodied in motor brain networks. In Parkinson's disease (PD), damage to the latter compromises access to such words. However, patients are not fully incapable of processing them, as their performance is far from floor level. Here we tested the hypothesis that action-verb processing in PD may rely on alternative disembodied semantic circuits. Seventeen PD patients and 15 healthy controls listened to action verbs and nouns during functional MRI scanning. Using cluster-mass analysis with a permutation test, we assessed task-related functional connectivity considering seeds differentially engaged by action and non-action words (namely, putamen and M1 versus posterior superior temporal lobe, respectively). The putamen seed showed reduced connectivity within the basal ganglia in patients for both lexical categories. However, only action verbs recruited different cortical networks in each group. Specifically, the M1 seed exhibited more anterior connectivity for controls and more posterior connectivity for patients, with no differences in the temporal seed. Moreover, the patients' level of basal ganglia atrophy positively correlated with their reliance on M1-posterior connectivity during action-verb processing. PD patients seem to have processed action verbs via non-motor cortical networks subserving amodal semantics. Such circuits may afford alternative pathways to process words when default embodied mechanisms are disturbed. Moreover, the greater the level of basal ganglia atrophy, the greater the patients' reliance on this alternative route. Our findings offer new insights into differential neurofunctional mechanisms recruited to process action semantics in PD.

The Role of ADAM10 in Alzheimer's Disease. - Yuan, Xiang-Zhen; Sun, Sen; Tan, Chen-Chen; Yu, Jin-Tai; Tan, Lan (J Alzheimers Dis, 2017)
As a member of the A Disintegrin And Metalloproteinase (ADAM) family, ADAM10 has been identified as the constitutive α-secretase in the process of amyloid-β protein precursor (AβPP) cleavage and plays a critical role in reducing the generation of the amyloid-β (Aβ) peptides. Recent studies have demonstrated its beneficial role in alleviating the pathologic impairment in Alzheimer's disease (AD) both in vitro and in vivo. However, the role of ADAM10 in AD and the underlying molecular mechanisms are still not well established. Increasing evidence indicates that ADAM10 not only reduces the generation of Aβ but may also affect the pathology of AD through potential mechanisms including reducing tau pathology, maintaining normal synaptic functions, and promoting hippocampal neurogenesis and the homeostasis of neuronal networks. Mechanistically, ADAM10 regulates these functions by interacting with postsynaptic substrates in brain, especially synaptic cell receptors and adhesion molecules. Furthermore, ADAM10 protein in platelets seems to be a promising biomarker for AD diagnosis. This review will summarize the role of ADAM10 in AD and highlight its functions besides its role as the α-secretase in AβPP cleavage. Meanwhile, we will discuss the therapeutic potential of ADAM10 in treating AD.

Role of Niemann-Pick Type C Disease Mutations in Dementia. - Cupidi, Chiara; Frangipane, Francesca; Gallo, Maura; Clodomiro, Alessandra; Colao, Rosanna; Bernardi, Livia; Anfossi, Maria; Conidi, Maria Elena; Vasso, Franca; Curcio, Sabrina Anna Maria; Mirabelli, Maria; Smirne, Nicoletta; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Several neurological and systemic diseases can cause dementia, beyond Alzheimer's disease. Rare genetic causes are often responsible for dementia with atypical features. Recently, mutations causative for Niemann-Pick type C disease (NPC) have also been implicated in neurodegenerative diseases. NPC is an autosomal recessive lipid storage disorder caused by mutations in NPC1 and NPC2 genes. In adults, clinical presentation mimicking other neurodegenerative diseases makes diagnosis difficult. Recent evidence suggests that heterozygous mutations in NPC genes may take on etiological significance. OBJECTIVE: To investigate the presence of NPC1 and NPC2 mutations in adults affected by neurodegenerative dementia plus. METHODS: We performed a genetic screening on 50 patients using a wide clinical and biochemical approach to characterize the phenotype of mutated patients. RESULTS: Sequencing analysis revealed four different and known heterozygous mutations in NPC1 and NPC2 genes. Patient 1 carried the p. F284LfsX26 in NPC1 and was affected by progressive supranuclear palsy-like syndrome. The remaining three patients showed a corticobasal syndrome and harbored the c.441+1G>A variant of NPC2 (patient 2), the missense p.N222 S mutation associated with the c.1947+8G>C variant in the splice region of intron 12 in NPC1 (patient 3), and the p.V30M mutation in NPC2 (patient 4), respectively. Filipin staining was abnormal in patients 1 and 2. mRNA analysis revealed an altered splicing of the NPC2 gene in patient 2. CONCLUSIONS: Heterozygous mutations of NPC1 and NPC2 genes could contribute to dementia plus, at least in a subset of patients. We highlight the occurrence of NPC1 and NPC2 heterozygous variants in dementia-plus as pathological event.

Secular Trends in the Incidence of Dementia in a Multi-Ethnic Community. - Noble, James M; Schupf, Nicole; Manly, Jennifer J; Andrews, Howard; Tang, Ming-Xin; Mayeux, Richard (J Alzheimers Dis, 2017)
BACKGROUND: Determination of secular trends in cognitive aging is important for prioritization of resources, services, and research in aging populations. Prior studies have identified declining dementia incidence associated with changes in cardiovascular risk factors and increased educational attainment. However, few studies have examined these factors in multi-ethnic cohorts. OBJECTIVE: To identify secular trends in the incidence rate of dementia in an elderly population. METHODS: Participants in this study were drawn from the Washington Heights-Inwood Columbia Aging Project, a multi-ethnic cohort study of northern Manhattan residents aged 65 years and older. Cox proportional hazards models were used to examine differences in the incidence of dementia in cohorts recruited in 1992 and 1999, with age at dementia or age at last follow-up visit as the "time-to-event" variable. RESULTS: Overall, there was a 41% reduction in the hazard ratio for dementia among participants in the 1999 cohort compared with those in the 1992 cohort, adjusting for age, sex, race, and baseline memory complaints (HR = 0.59). The reduction in incidence was greatest among non-Hispanic Whites and African-Americans and lowest among Hispanic participants (HRs = 0.60, 0.52 and 0.64, respectively), and was associated with increases in level of educational attainment, especially among African-Americans. Reduction in incidence of dementia was also greater among persons 75 years or older than among younger participants (HR = 0.52 versus HR = 0.69). CONCLUSIONS: Our results support previous findings that secular trends in dementia incidence are changing, including in aging minority populations.

Selenoprotein S Reduces Endoplasmic Reticulum Stress-Induced Phosphorylation of Tau: Potential Role in Selenate Mitigation of Tau Pathology. - Rueli, Rachel H L H; Torres, Daniel J; Dewing, Andrea S T; Kiyohara, Arlene C; Barayuga, Stephanie M; Bellinger, Miyoko T; Uyehara-Lock, Jane H; White, Lon R; Moreira, Paula I; Berry, Marla J; Perry, George; Bellinger, Frederick P (J Alzheimers Dis, 2017)
Previous studies demonstrated that selenium in the form of sodium selenate reduces neurofibrillary tangle formation in Alzheimer's disease models. Hyperphosphorylation of tau, which leads to formation of neurofibrillary tangles in Alzheimer's disease, is increased by endoplasmic reticulum (ER) stress. Selenoprotein S (SelS) is part of an ER membrane complex that removes misfolded proteins from the ER as a means to reduce ER stress. Selenate, as with other forms of selenium, will increase selenoprotein expression. We therefore proposed that increased SelS expression by selenate would contribute to the beneficial actions of selenate in Alzheimer's disease. SelS expression increased with ER stress and decreased under conditions of elevated glucose concentrations in the SH-SY5Y neuronal cell line. Reducing expression of SelS with siRNA promoted cell death in response to ER stress. Selenate increased SelS expression, which significantly correlated with decreased tau phosphorylation. Restricting SelS expression during ER stress conditions increased tau phosphorylation, and also promoted aggregation of phosphorylated tau in neurites and soma. In human postmortem brain, SelS expression coincided with neurofibrillary tangles, but not with amyloid-β plaques. These results indicate that selenate can alter phosphorylation of tau by increasing expression of SelS in Alzheimer's disease and potentially other neurodegenerative disorders.

Sensing of Alzheimer's Disease and Multiple Sclerosis Using Nano-Bio Interfaces. - Hajipour, Mohammad Javad; Ghasemi, Forough; Aghaverdi, Haniyeh; Raoufi, Mohammad; Linne, Uwe; Atyabi, Fatemeh; Nabipour, Iraj; Azhdarzadeh, Morteza; Derakhshankhah, Hossein; Lotfabadi, Alireza; Bargahi, Afshar; Alekhamis, Zahra; et al. (J Alzheimers Dis, 2017)
It is well understood that patients with different diseases may have a variety of specific proteins (e.g., type, amount, and configuration) in their plasmas. When nanoparticles (NPs) are exposed to these plasmas, the resulting coronas may incorporate some of the disease-specific proteins. Using gold (Au) NPs with different surface properties and corona composition, we have developed a colorimetric sensor array for the discrimination and detection of two neurodegenerative diseases, Alzheimer's disease (AD) and multiple sclerosis (MS). Applying a variety of techniques, including UV-visible spectra, array response analyses and liquid chromatography-tandem mass spectrometry, we found the corona-NP complexes, obtained from different human serums, had distinct protein composition, including some specific proteins that are known as AD and MS biomarkers. The array responses, analyzed by chemometrics and statistical methods, demonstrate promising capabilities of the sensor to unambiguously identify and discriminate AD and MS. The developed sensor array might enable a simple, inexpensive and rapid detection/discrimination of neurodegenerative diseases.

Sex-Dependent Associations of Serum Uric Acid with Brain Function During Aging. - Kueider, Alexandra M; An, Yang; Tanaka, Toshiko; Kitner-Triolo, Melissa H; Studenski, Stephanie; Ferrucci, Luigi; Thambisetty, Madhav (J Alzheimers Dis, 2017)
Serum uric acid (SUA) is an abundant natural antioxidant capable of reducing cellular oxidation, a major cause of neurodegenerative disease. In line with this, SUA levels are lower in Alzheimer's disease; however, the association between SUA and cognition remains unclear. Results from studies examining the effects of SUA on cognition may be difficult to interpret in the context of normal versus pathological aging. This study examined sex-specific associations of baseline SUA with cognition during aging. Data from dementia-free participants initially aged 26-99 (N = 1,451) recruited for the Baltimore Longitudinal Study of Aging (BLSA), were used in the current analyses. SUA was assessed using blood samples collected during research visits. Cognition was measured using five composite scores (verbal memory, attention, executive function, language, and visuospatial ability). At the first study visit, compared with women, men were older, more likely to be White, had more years of education, higher baseline SUA levels, and higher cardiovascular risk scores. Higher baseline SUA was associated with attenuated declines in attention (β= 0.006; p = 0.03) and visuospatial abilities (β= 0.007; p = 0.01) in men. There was a trend to suggest higher baseline SUA in men was associated with attenuated declines in language, but this finding did not reach statistical significance (p = 0.09). There were no significant findings with SUA and cognition in women. In this sample of cognitively healthy, community-dwelling adults, we found that higher SUA levels at baseline were associated with attenuated declines in attention and visuospatial abilities in men. SUA was not associated with cognition or change in cognition over time in women.

Shear-Induced Amyloid Formation in the Brain: II. An Experimental System for Monitoring Amyloid Shear Processes and Investigating Potential Spinal Tap Problems. - Trumbore, Conrad N (J Alzheimers Dis, 2017)
Liquid sheared amyloid-β (Aβ) initiates amyloid cascade reactions, producing unstable, potentially toxic oligomers. There is a need for new analytical tools with which to study these oligomers. A very small bore capillary flow system is proposed as a tool for studying the effects of liquid shear in amyloid research. This simple system consists of injecting a short cylindrical liquid sample plug containing dissolved amyloid into a liquid mobile phase flowing through an empty, very small internal diameter capillary tube. For liquid samples containing a single protein sample, under conditions in which there is laminar flow and limited sample protein molecular diffusion, chromatograms monitoring the optical protein absorbance of capillary effluent contain either one or two peaks, depending on the mobile phase flow rate. By controlling the sample diffusion times through changes in flow rate and/or capillary diameter, this tool can be used to generate aliquot samples with precise, reproducible amounts of shear for exploring the effects of variable shear on amyloid systems. The tool can be used for producing in-capillary stopped flow spectra of shear-stressed Aβ monomers as well as for kinetic studies of Aβ dimer- and oligomer-forming reactions between shear stressed Aβ monomers. Many other experiments are suggested using this experimental tool for studying the effects of shear on different Aβ and other amyloid systems, including testing for potentially serious amyloid sampling errors in spinal tap quantitative analysis. The technique has potential as both a laboratory research and a clinical tool.

Situation Model for Situation-Aware Assistance of Dementia Patients in Outdoor Mobility. - Yordanova, Kristina; Koldrack, Philipp; Heine, Christina; Henkel, Ron; Martin, Mike; Teipel, Stefan; Kirste, Thomas (J Alzheimers Dis, 2017)
BACKGROUND: Dementia impairs spatial orientation and route planning, thus often affecting the patient's ability to move outdoors and maintain social activities. Situation-aware deliberative assistive technology devices (ATD) can substitute impaired cognitive function in order to maintain one's level of social activity. To build such a system, one needs domain knowledge about the patient's situation and needs. We call this collection of knowledge situation model. OBJECTIVE: To construct a situation model for the outdoor mobility of people with dementia (PwD). The model serves two purposes: 1) as a knowledge base from which to build an ATD describing the mobility of PwD; and 2) as a codebook for the annotation of the recorded behavior. METHODS: We perform systematic knowledge elicitation to obtain the relevant knowledge. The OBO Edit tool is used for implementing and validating the situation model. The model is evaluated by using it as a codebook for annotating the behavior of PwD during a mobility study and interrater agreement is computed. In addition, clinical experts perform manual evaluation and curation of the model. RESULTS: The situation model consists of 101 concepts with 11 relation types between them. The results from the annotation showed substantial overlapping between two annotators (Cohen's kappa of 0.61). CONCLUSION: The situation model is a first attempt to systematically collect and organize information related to the outdoor mobility of PwD for the purposes of situation-aware assistance. The model is the base for building an ATD able to provide situation-aware assistance and to potentially improve the quality of life of PwD.

Skin Autofluorescence Examination as a Diagnostic Tool for Mild Cognitive Impairment in Healthy People. - Igase, Michiya; Ohara, Maya; Igase, Keiji; Kato, Takeaki; Okada, Yoko; Ochi, Masayuki; Tabara, Yasuharu; Kohara, Katsuhiko; Ohyagi, Yasumasa (J Alzheimers Dis, 2017)
BACKGROUND: Accumulation of advanced glycation endproducts (AGEs) is thought to be involved in the pathogenesis of dementia, especially Alzheimer's disease. Tissue AGE accumulation can be estimated using the relative simple noninvasive measurement of skin autofluorescence (SAF), a method based on the fluorescent properties of some AGEs. However, possible involvement of tissue AGE accumulation in mild cognitive impairment (MCI) has not been fully investigated. OBJECTIVE: We investigated whether tissue AGE accumulation estimated by SAF is associated with mild cognitive impairment. METHODS: We analyzed 226 community-dwelling subjects. In addition to several atherosclerosis-related clinical parameters, MCI screening test, assessment of brain atrophy, and SAF were performed on people aged > 40 years. MCI was assessed using the Japanese version of the MCI screening method. Atrophy of the brain was assessed by examining the temporal horn area (THA) by brain MRI. RESULTS: SAF was significantly higher in participants with MCI than in those with normal cognitive function (2.56±0.55 versus 2.10±0.41; p < 0.001). Logistic regression analyses with adjustment for confounding factors including age and THA showed that high SAF > 2.27 was significantly related to the presence of MCI (odds, 6.402; 95% CI, 1.590-25.773, p = 0.009). CONCLUSION: We found an association between SAF and MCI, which was independent of brain atrophy, in healthy subjects.

Is Sleep Disruption a Risk Factor for Alzheimer's Disease? - Macedo, Arthur Cassa; Balouch, Sara; Tabet, Naji (J Alzheimers Dis, 2017)
Sleep disturbances are routinely encountered in Alzheimer's disease (AD) and affect about 25-40% of patients in the mild-to-moderate stages of the disease. In many, sleep pathology may represent a symptom of the underlying neurodegeneration. However, a history of sleep disruption occurring years prior to onset of cognitive symptoms could represent a potential risk factor for AD. The aim of the present narrative review was to evaluate current evidence linking sleep disturbances with AD development and to understand the mechanisms that may contribute to this. Although the mechanisms by which poor sleep may contribute to AD genesis is not fully understood, emerging evidence linking disturbances in the sleep wake cycle with Aβ deposition is shedding light on the relationship between sleep pathology and the subsequent development of AD. Aβ burden appears to be enhanced by sleep-wake cycle disruptions and is suspected as being an important mechanism by which sleep disruptions contribute in AD development. Other mechanisms triggered by sleep disruption may also be involved in AD development, such as brain hypoxia, oxidative stress, circadian activity rhythms disturbances, overexpression of orexins, and blood-brain barrier impairment. Further understanding of the link between sleep disturbances and future development of AD is still needed before sleep disturbances are clearly marked as a preventable risk factor for AD. In these circumstances, early lifestyle interventions to help increase the quantity and quality of sleep may have a favorable outcome on decreasing the incidence of AD and this needs to be investigated further.

Sleep-Wake Profile in Dementia with Lewy Bodies, Alzheimer's Disease, and Normal Aging. - Cagnin, Annachiara; Fragiacomo, Federica; Camporese, Giulia; Turco, Matteo; Bussè, Cinzia; Ermani, Mario; Montagnese, Sara (J Alzheimers Dis, 2017)
BACKGROUND: Alterations of the sleep-wake cycle are common features of neurodegenerative dementia. OBJECTIVES: To study differences in sleep-wake profiles in dementia with Lewy bodies (DLB), Alzheimer's disease (AD), and healthy controls. METHODS: 30 DLB and 32 AD patients, and 33 healthy elderly participants were studied. Patients were evaluated for global cognitive impairment, extrapyramidal signs, fluctuations of attention, and behavioral disorders. A comprehensive sleep-wake profile was obtained including a set of questionnaires [Pittsburgh Sleep Quality Index (PSQI), REM Sleep Behavior Disorder Single-Question screen (RBD1Q), Epworth Sleepiness Scale (ESS)] and 12-day sleep diaries. RESULTS: Patients were matched for age, gender, and disease severity. DLB patients showed more severe daytime somnolence/dysfunction due to somnolence, and a higher proportion of RBD-like symptoms (70%) compared to AD and controls (p < 0.001), regardless of the presence of psychoactive drug treatment. As for sleep timing, DLB patients had a greater number of daytime naps and longer night sleep, with the latter being associated with use of clonazepam. The severity of fluctuations was associated with the presence of RBD (Clinician Assessment of Fluctuation score = RBD+: 5.2±3.7; RBD-: 2.1±3.2, p = 0.04). AD patients reported the best sleep-wake profile, while healthy controls declared the poorest sleep quality, although sleep timing and the quality of wakefulness were comparable between AD and controls. DISCUSSION: RBD and daytime fluctuations of attention may coexist in DLB and even reciprocally potentiate each other. Self-reports of sleep quality may lead to an underestimation of sleep disturbances in AD, possibly influenced by anosognosia, compared to normal elderly individuals who complain mainly of insomnia.

Social Representation of Dementia: An Analysis of 5,792 Consecutive Cases Evaluated in a Memory Clinic. - Cañabate, Pilar; Martínez, Gabriel; Rosende-Roca, Maitee; Moreno, Mariola; Preckler, Silvia; Valero, Sergi; Sotolongo, Oscar; Hernandez, Isabel; Alegret, Montserrat; Ortega, Gemma; Espinosa, Ana; Mauleón, Ana; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Different interpretations of cognitive impairment and dementia due to differences in health structures, such as cultural differences could affect the diagnosis and treatment of the condition. it is reasonable to expect that the social and family impact of the disease and coping strategies will differ among societies. OBJECTIVE: The general aim of this study is to understand the social representations of dementia, its associated practices, and the effects they imply. METHODS: People diagnosed with clinical dementia and their families were assessed from 2005 to 2015 in the memory clinic of the Fundació ACE, Institut Català de Neurociències Aplicades in Barcelona, Spain. RESULTS: 9,898 people were examined and 5,792 were diagnosed with dementia. For those with a caregiver (71%), the decision-making fell on the person with dementia in 16.2% of the cases; and for those without a caregiver, in 26.4% of the cases the family did not perceive the deficits as a disease, which led to multiple risk situations (74.6%). CONCLUSIONS: The recognition of dementia as part of aging is common among families. Consequently, risk situations may arise and diagnosis and access to treatment may be delayed. The incorporation of a social appraisal to the diagnostic process is a necessity to evaluate these situations.

State of Play in Alzheimer's Disease Genetics. - Zhu, Jin-Bao; Tan, Chen-Chen; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2017)
Alzheimer's disease (AD), the main form of dementia in the elderly, is the most common progressive neurodegenerative disease characterized by rapidly progressive cognitive dysfunction and behavior impairment. AD exhibits a considerable heritability and great advances have been made in approaches to searching the genetic etiology of AD. In AD genetic studies, methods have developed from classic linkage-based and candidate-gene-based association studies to genome-wide association studies (GWAS) and next generation sequencing (NGS). The identification of new susceptibility genes has provided deeper insights to understand the mechanisms underlying AD. In addition to searching novel genes associated with AD in large samples, the NGS technologies can also be used to shed light on the 'black matter' discovery even in smaller samples. The shift in AD genetics between traditional studies and individual sequencing will allow biomaterials of each patient as the central unit of genetic studies. This review will cover genetic findings in AD and consequences of AD genetic findings. Firstly, we will discuss the discovery of mutations in APP, PSEN1, PSEN2, APOE, and ADAM10. Then we will summarize and evaluate the information obtained from GWAS of AD. Finally, we will outline the efforts to identify rare variants associated with AD using NGS.

Subjective Cognitive Complaints in Cognitively Healthy Older Adults and Their Relationship to Cognitive Performance and Depressive Symptoms. - Marková, Hana; Andel, Ross; Stepankova, Hana; Kopecek, Miloslav; Nikolai, Tomas; Hort, Jakub; Thomas-Antérion, Catherine; Vyhnálek, Martin (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive complaints (SCCs) may be an early marker of prodromal Alzheimer's disease. OBJECTIVES: Using a 10-item yes/no SCCs questionnaire (Le Questionnaire de Plainte Cognitive [QPC]), we evaluated the prevalence and distribution of SCCs in cognitively healthy Czech older adults and examined total score and specific QPC items in relation to depressive symptomology and cognitive performance. METHODS: A sample of 340 cognitively healthy older community-dwelling volunteers aged 60 or older from the third wave of the longitudinal project National Normative Study of Cognitive Determinants of Healthy Aging, who underwent a comprehensive neuropsychological assessment and completed the QPC and the 15-item Geriatric Depression Scale (GDS-15). Regression analysis was controlled for age when GDS-15 was the outcome and for age and GDS-15 with cognitive domains as the outcome. RESULTS: 71% reported 1 + SCCs, with prevalence of individual complaints ranging from 4% to 40%. The number of SCCs was associated with GDS-15 (p < 0.001). Personality change (p < 0.001) and Limitation in daily activities (p = 0.002) were significantly associated with higher GDS-15 score and Spatial orientation difficulties (p = 0.019) and Impression of worse memory in comparison to peers (p = 0.012) were significantly associated with lower memory performance. CONCLUSIONS: We identified some cognitive complaints that were very common in our sample. Overall, a higher number of SCCs in well cognitively functioning individuals was most closely related to depressive symptomatology, while some specific complaints reflected lower memory performance and should be considered when screening for people at risk of cognitive decline.

Successful Object Encoding Induces Increased Directed Connectivity in Presymptomatic Early-Onset Alzheimer's Disease. - Ochoa, John Fredy; Alonso, Joan Francesc; Duque, Jon Edinson; Tobón, Carlos Andrés; Mañanas, Miguel Angel; Lopera, Francisco; Hernández, Alher Mauricio (J Alzheimers Dis, 2017)
BACKGROUND: Recent studies report increases in neural activity in brain regions critical to episodic memory at preclinical stages of Alzheimer's disease (AD). Although electroencephalography (EEG) is widely used in AD studies, given its non-invasiveness and low cost, there is a need to translate the findings in other neuroimaging methods to EEG. OBJECTIVE: To examine how the previous findings using functional magnetic resonance imaging (fMRI) at preclinical stage in presenilin-1 E280A mutation carriers could be assessed and extended, using EEG and a connectivity approach. METHODS: EEG signals were acquired during resting and encoding in 30 normal cognitive young subjects, from an autosomal dominant early-onset AD kindred from Antioquia, Colombia. Regions of the brain previously reported as hyperactive were used for connectivity analysis. RESULTS: Mutation carriers exhibited increasing connectivity at analyzed regions. Among them, the right precuneus exhibited the highest changes in connectivity. CONCLUSION: Increased connectivity in hyperactive cerebral regions is seen in individuals, genetically-determined to develop AD, at preclinical stage. The use of a connectivity approach and a widely available neuroimaging technique opens the possibility to increase the use of EEG in early detection of preclinical AD.

Synaptic Membrane Synthesis in Rats Depends on Dietary Sufficiency of Vitamin C, Vitamin E, and Selenium: Relevance for Alzheimer's Disease. - Cansev, Mehmet; Turkyilmaz, Mesut; Sijben, John W C; Sevinc, Cansu; Broersen, Laus M; van Wijk, Nick (J Alzheimers Dis, 2017)
Chronic consumption of a diet enriched with nutritional precursors of phospholipids, including uridine and the polyunsaturated fatty acids, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), was shown previously to enhance levels of brain phospholipids and synaptic proteins in rodents. Vitamin C, vitamin E, and selenium may directly affect the breakdown or synthesis of membrane phospholipids. The present study investigated the necessity of antioxidants for the effectiveness of supplementation with uridine plus DHA and EPA (as fish oil) in rats. Rats were randomized to four treatment groups and received, for 6 weeks, one of four experimental diets, i.e., a diet low in antioxidants, a diet high in antioxidants, a diet low in antioxidants supplemented with DHA+EPA+uridine, or a diet high in antioxidants supplemented with DHA+EPA+uridine. On completion of dietary treatment, rats were sacrificed, and brain levels of phospholipids, synaptic proteins, and two enzymes involved in phospholipid synthesis (choline-phosphate cytidylyltransferase, PCYT1A, and choline/ethanolamine phosphotransferase, CEPT1) were analyzed. Levels of phospholipids, the pre- and post-synaptic proteins Synapsin-1 and PSD95, and the enzymes PCYT1A and CEPT1 were significantly enhanced by combined supplementation of DHA+EPA+uridine and antioxidants and not enhanced by supplementation of DHA+EPA+uridine with insufficient antioxidant levels. Our data suggest that dietary vitamin C, vitamin E, and selenium are essential for the phospholipid precursors' effects on increasing levels of membrane phospholipids and synaptic proteins, the indirect indicators of synaptogenesis. Their concomitant supply may be relevant in Alzheimer's disease patients, because the disease is characterized by synapse loss and lower plasma and brain levels of phospholipid precursors and antioxidants.

Tai Chi Chuan and Baduanjin Increase Grey Matter Volume in Older Adults: A Brain Imaging Study. - Tao, Jing; Liu, Jiao; Liu, Weilin; Huang, Jia; Xue, Xiehua; Chen, Xiangli; Wu, Jinsong; Zheng, Guohua; Chen, Bai; Li, Ming; Sun, Sharon; Jorgenson, Kristen; et al. (J Alzheimers Dis, 2017)
The aim of this study is to investigate and compare how 12-weeks of Tai Chi Chuan and Baduanjin exercise can modulate brain structure and memory function in older adults. Magnetic resonance imaging and memory function measurements (Wechsler Memory Scale-Chinese revised, WMS-CR) were applied at both the beginning and end of the study. Results showed that both Tai Chi Chuan and Baduanjin could significantly increase grey matter volume (GMV) in the insula, medial temporal lobe, and putamen after 12-weeks of exercise. No significant differences were observed in GMV between the Tai Chi Chuan and Baduanjin groups. We also found that compared to healthy controls, Tai Chi Chuan and Baduanjin significantly improved visual reproduction subscores on the WMS-CR. Baduanjin also improved mental control, recognition, touch, and comprehension memory subscores of the WMS-CR compared to the control group. Memory quotient and visual reproduction subscores were both associated with GMV increases in the putamen and hippocampus. Our results demonstrate the potential of Tai Chi Chuan and Baduanjin exercise for the prevention of memory deficits in older adults.

Tau Rather than TDP-43 Proteins are Potential Cerebrospinal Fluid Biomarkers for Frontotemporal Lobar Degeneration Subtypes: A Pilot Study. - Kuiperij, H Bea; Versleijen, Alexandra A M; Beenes, Marijke; Verwey, Nicolaas A; Benussi, Luisa; Paterlini, Anna; Binetti, Giuliano; Teunissen, Charlotte E; Raaphorst, Joost; Schelhaas, Helenius J; Küsters, Benno; Pijnenburg, Yolande A L; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Frontotemporal dementia (FTD) is a heterogeneous disease both at the clinical, genetic, and pathobiological level. The underlying pathological spectrum (termed FTLD, frontotemporal lobar degeneration) is in most cases defined by accumulation of either tau (FTLD-tau) or TDP-43 proteins (FTLD-TDP). Biomarkers to differentiate these subtypes are not yet available, whereas these are essential requirements to study the natural course of disease and for homogeneous inclusion of patients in clinical studies. OBJECTIVE: To study if a combination of total (t-) and phosphorylated (p-)tau, and t-TDP-43 and p-TDP-43 proteins in cerebrospinal fluid (CSF) is suitable to discriminate FTLD-tau and FTLD-TDP subtypes. METHODS: We developed immunoassays for the quantification of t-TDP-43 and p-TDP-43 proteins and used commercially available assays for the quantification of t-tau and p-tau proteins. We quantified these proteins in ventricular CSF samples from neuropathologically defined FTLD-tau and FTLD-TDP cases to study the reflection of underlying brain pathology in CSF composition, and in lumbar CSF samples from FTLD-tau and FTLD-TDP patients to study the diagnostic potential of CSF biomarkers. RESULTS: In ventricular CSF, t-TDP-43 and t-tau levels, when combined into one model, were significantly different between neuropathologically-defined FTLD-tau and FTLD-TDP cases. In a pilot study using lumbar CSF, the p-tau/t-tau ratio, but not t-TDP-43 levels, were significantly different between FTLD-TDP and FTLD-tau patients. CONCLUSION: We conclude that with current available methods, CSF tau, rather than TDP-43 proteins, may have diagnostic value in the differentiation of FTLD patients with either tau or TDP-43 pathology.

TFP5, a Peptide Inhibitor of Aberrant and Hyperactive Cdk5/p25, Attenuates Pathological Phenotypes and Restores Synaptic Function in CK-p25Tg Mice. - Shukla, Varsha; Seo, Jinsoo; Binukumar, B K; Amin, Niranjana D; Reddy, Preethi; Grant, Philip; Kuntz, Susan; Kesavapany, Sashi; Steiner, Joseph; Mishra, Santosh K; Tsai, Li-Huei; Pant, Harish C (J Alzheimers Dis, 2017)
It has been reported that cyclin-dependent kinase 5 (cdk5), a critical neuronal kinase, is hyperactivated in Alzheimer's disease (AD) and may be, in part, responsible for the hallmark pathology of amyloid plaques and neurofibrillary tangles (NFTs). It has been proposed by several laboratories that hyperactive cdk5 results from the overexpression of p25 (a truncated fragment of p35, the normal cdk5 regulator), which, when complexed to cdk5, induces hyperactivity, hyperphosphorylated tau/NFTs, amyloid-β plaques, and neuronal death. It has previously been shown that intraperitoneal (i.p.) injections of a modified truncated 24-aa peptide (TFP5), derived from the cdk5 activator p35, penetrated the blood-brain barrier and significantly rescued AD-like pathology in 5XFAD model mice. The principal pathology in the 5XFAD mutant, however, is extensive amyloid plaques; hence, as a proof of concept, we believe it is essential to demonstrate the peptide's efficacy in a mouse model expressing high levels of p25, such as the inducible CK-p25Tg model mouse that overexpresses p25 in CamKII positive neurons. Using a modified TFP5 treatment, here we show that peptide i.p. injections in these mice decrease cdk5 hyperactivity, tau, neurofilament-M/H hyperphosphorylation, and restore synaptic function and behavior (i.e., spatial working memory, motor deficit using Rota-rod). It is noteworthy that TFP5 does not inhibit endogenous cdk5/p35 activity, nor other cdks in vivo suggesting it might have no toxic side effects, and may serve as an excellent therapeutic candidate for neurodegenerative disorders expressing abnormally high brain levels of p25 and hyperactive cdk5.

Tocotrienol-Rich Fraction Modulates Amyloid Pathology and Improves Cognitive Function in AβPP/PS1 Mice. - Ibrahim, Nor Faeizah; Yanagisawa, Daijiro; Durani, Lina Wati; Hamezah, Hamizah Shahirah; Damanhuri, Hanafi Ahmad; Wan Ngah, Wan Zurinah; Tsuji, Mayumi; Kiuchi, Yuji; Ono, Kenjiro; Tooyama, Ikuo (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common cause of dementia. The cardinal neuropathological characteristic of AD is the accumulation of amyloid-β (Aβ) into extracellular plaques that ultimately disrupt neuronal function and lead to neurodegeneration. One possible therapeutic strategy therefore is to prevent Aβ aggregation. Previous studies have suggested that vitamin E analogs slow AD progression in humans. In the present study, we investigated the effects of the tocotrienol-rich fraction (TRF), a mixture of vitamin E analogs from palm oil, on amyloid pathology in vitro and in vivo. TRF treatment dose-dependently inhibited the formation of Aβ fibrils and Aβ oligomers in vitro. Moreover, daily TRF supplementation to AβPPswe/PS1dE9 double transgenic mice for 10 months attenuated Aβ immunoreactive depositions and thioflavin-S-positive fibrillar type plaques in the brain, and eventually improved cognitive function in the novel object recognition test compared with control AβPPswe/PS1dE9 mice. The present result indicates that TRF reduced amyloid pathology and improved cognitive functions, and suggests that TRF is a potential therapeutic agent for AD.

Transport of Non-Transferrin Bound Iron to the Brain: Implications for Alzheimer's Disease. - Tripathi, Ajai K; Karmakar, Shilpita; Asthana, Abhishek; Ashok, Ajay; Desai, Vilok; Baksi, Shounak; Singh, Neena (J Alzheimers Dis, 2017)
A direct correlation between brain iron and Alzheimer's disease (AD) raises questions regarding the transport of non-transferrin-bound iron (NTBI), a toxic but less researched pool of circulating iron that is likely to increase due to pathological and/or iatrogenic systemic iron overload. Here, we compared the distribution of radiolabeled-NTBI (59Fe-NTBI) and transferrin-bound iron (59Fe-Tf) in mouse models of iron overload in the absence or presence of inflammation. Following a short pulse, most of the 59Fe-NTBI was taken up by the liver, followed by the kidney, pancreas, and heart. Notably, a strong signal of 59Fe-NTBI was detected in the brain ventricular system after 2 h, and the brain parenchyma after 24 h. 59Fe-Tf accumulated mainly in the femur and spleen, and was transported to the brain at a much slower rate than 59Fe-NTBI. In the kidney, 59Fe-NTBI was detected in the cortex after 2 h, and outer medulla after 24 hours. Most of the 59Fe-NTBI and 59Fe-Tf from the kidney was reabsorbed; negligible amount was excreted in the urine. Acute inflammation increased the uptake of 59Fe-NTBI by the kidney and brain from 2-24 hours. Chronic inflammation, on the other hand, resulted in sequestration of iron in the liver and kidney, reducing its transport to the brain. These observations provide direct evidence for the transport of NTBI to the brain, and reveal a complex interplay between inflammation and brain iron homeostasis. Further studies are necessary to determine whether transient increase in NTBI due to systemic iron overload is a risk factor for AD.

Treadmill Exercise Exerts Neuroprotection and Regulates Microglial Polarization and Oxidative Stress in a Streptozotocin-Induced Rat Model of Sporadic Alzheimer's Disease. - Lu, Yujiao; Dong, Yan; Tucker, Donovan; Wang, Ruimin; Ahmed, Mohammad Ejaz; Brann, Darrell; Zhang, Quanguang (J Alzheimers Dis, 2017)
Recent work has suggested that exercise may be beneficial in preventing or ameliorating symptoms of several neurological disorders, although the mechanism is not entirely understood. The current study was designed to examine the potential beneficial effect of treadmill exercise upon cognitive function in a streptozotocin (STZ)-induced rat model of Alzheimer's disease (AD). Animals underwent treadmill exercise (30 min/day, 5 days/week) for 4 weeks after bilateral STZ intracerebroventricular injection (2.4 mg/kg). We demonstrated that treadmill exercise significantly attenuated STZ-induced neurodegeneration in the rat hippocampal CA1 region and strongly preserved hippocampal-dependent cognitive functioning. Further mechanistic investigation displayed a marked suppression of STZ-induced amyloid-β accumulation and tau phosphorylation. Intriguingly, treadmill exercise remarkably inhibited reactive gliosis following STZ insult and effectively shifted activated microglia from a pro-inflammatory M1 to an anti-inflammatory M2 phenotype, which was correlated with a significantly reduced expression of pro-inflammatory mediators and a corresponding enhancement of anti-inflammatory cytokine expression in the hippocampus. Furthermore, treadmill exercise caused a robust suppression of oxidative damage as evidenced by significantly reduced peroxynitrite production, lipid peroxidation, and oxidized DNA damage. Finally, treadmill exercise strongly attenuated STZ-induced mitochondrial dysfunction manifested by a dramatically elevated intra-mitochondrial cytochrome c oxidase activity and ATP synthesis, and markedly inhibited neuronal apoptosis in the hippocampus. These findings demonstrate that treadmill exercise has a multifactorial effect to attenuate many of the pathological processes that play a key role in AD, and provide further support for the beneficial role of exercise as a potential therapeutic option in AD treatment.

Two Novel Mutations in the First Transmembrane Domain of Presenilin1 Cause Young-Onset Alzheimer's Disease. - Liu, Collin Y; Ohki, Yu; Tomita, Taisuke; Osawa, Satoko; Reed, Bruce R; Jagust, William; Van Berlo, Victoria; Jin, Lee-Way; Chui, Helena C; Coppola, Giovanni; Ringman, John M (J Alzheimers Dis, 2017)
BACKGROUND: The presenilin-1 protein (PS1) is the catalytic unit of γ-secretase implicated in the production of abnormally long forms of amyloid-β (Aβ), including Aβ42, proteins thought critical in the pathogenesis of Alzheimer's disease (AD). In AD of autosomal dominant inheritance, the majority of pathogenic mutations have been found in the PSEN1 gene within which the location of the mutation can provide clues as to the mechanism of pathogenesis. OBJECTIVE: To describe clinical features of two novel mutations in the transmembrane portion 1 (TMD-1) of PSEN1 as well as biochemical features in one and neuropathological findings in the other. METHODS: Two index patients with young onset AD with an autosomal dominant pattern of inheritance underwent clinical and imaging assessments, as well as PSEN1 sequencing. Postmortem examination was completed in one patient. An artificial construct in which the P88L mutation was introduced was created to examine its effects on γ-secretase cleavage. RESULTS: Two novel variants in TMD-1 (P88L and V89L) were identified in affected probands. The neuropathological findings of AD were confirmed in the V89L mutation. Both patients presented around age 40 with early short-term memory deficits followed by seizures and corticospinal tract signs. The P88L mutation additionally featured early myoclonus followed by Parkinsonism. The causal role of the P88L mutation is supported by demonstration that this mutation dramatically increased Aβ42 and decreased APP and Notch intracellular domain production in vitro. CONCLUSION: Changes in a single amino acid in codons 88 and 89 of TMD-1 can result in young-onset AD. The TMD-1 of PS1 is a region important for the γ-secretase cleavage of Aβ.

Urine Formaldehyde Predicts Cognitive Impairment in Post-Stroke Dementia and Alzheimer's Disease. - Tong, Zhiqian; Wang, Weishan; Luo, Wenhong; Lv, Jihui; Li, Hui; Luo, Hongjun; Jia, Jianping; He, Rongqiao (J Alzheimers Dis, 2017)
Although Alzheimer's disease (AD) was first described over 100 years ago, there is still no suitable biomarker for diagnosing AD in easily collectable samples (e.g., blood plasma, saliva, and urine). Here, we investigated the relationship between morning urine formaldehyde concentration and cognitive impairment in patients with post-stroke dementia (PSD) or AD in this cross-sectional survey for 7 years. Cognitive abilities of the study participants (n = 577, four groups: 231 controls, 61 stroke, 65 PSD, and 220 AD) were assessed by Mini-Mental State Examination (MMSE). Morning urine formaldehyde concentrations were measured by high performance liquid chromatography (HPLC). Gender- and age-matched participants were selected from the four groups (n = 42 in each group). Both semicarbazide-sensitive amine oxidase (SSAO, a formaldehyde-generating enzyme) and formaldehyde levels in the blood and urine were analyzed by using an enzyme-linked immunosorbent assay (ELISA) and HPLC, respectively. We found that morning urine formaldehyde levels were inversely correlated with MMSE scores. The threshold value (the best Cut-Off value) of formaldehyde concentration for predicting cognitive impairment was 0.0418 mM in patients with PSD (Sensitivity: 92.3%; Specificity: 77.1%), and 0.0449 mM in patients with AD (Sensitivity: 94.1%; Specificity: 81.8%), respectively. The results of biochemical analysis revealed that the observed increase in urine formaldehyde resulted from an overexpression of SSAO in the blood. The findings suggest that measuring the concentration of formaldehyde in overnight fasting urine could be used as a potentially noninvasive method for evaluating the likelihood of ensuing cognitive impairment or dementia.

The Utilization of Robotic Pets in Dementia Care. - Petersen, Sandra; Houston, Susan; Qin, Huanying; Tague, Corey; Studley, Jill (J Alzheimers Dis, 2017)
BACKGROUND: Behavioral problems may affect individuals with dementia, increasing the cost and burden of care. Pet therapy has been known to be emotionally beneficial for many years. Robotic pets have been shown to have similar positive effects without the negative aspects of traditional pets. Robotic pet therapy offers an alternative to traditional pet therapy. OBJECTIVE: The study rigorously assesses the effectiveness of the PARO robotic pet, an FDA approved biofeedback device, in treating dementia-related symptoms. METHODS: A randomized block design with repeated measurements guided the study. Before and after measures included reliable, valid tools such as: RAID, CSDD, GDS, pulse rate, pulse oximetry, and GSR. Participants interacted with the PARO robotic pet, and the control group received standard activity programs. Five urban secure dementia units comprised the setting. RESULTS: 61 patients, with 77% females, average 83.4 years in age, were randomized into control and treatment groups. Compared to the control group, RAID, CSDD, GSR, and pulse oximetry were increased in the treatment group, while pulse rate, pain medication, and psychoactive medication use were decreased. The changes in GSR, pulse oximetry, and pulse rate over time were plotted for both groups. The difference between groups was consistent throughout the 12-week study for pulse oximetry and pulse rate, while GSR had several weeks when changes were similar between groups. CONCLUSIONS: Treatment with the PARO robot decreased stress and anxiety in the treatment group and resulted in reductions in the use of psychoactive medications and pain medications in elderly clients with dementia.

Violation of Laws in Frontotemporal Dementia: A Multicenter Study in Japan. - Shinagawa, Shunichiro; Shigenobu, Kazue; Tagai, Kenji; Fukuhara, Ryuji; Kamimura, Naoto; Mori, Takaaki; Yoshiyama, Kenji; Kazui, Hiroaki; Nakayama, Kazuhiko; Ikeda, Manabu (J Alzheimers Dis, 2017)
Although violations of laws, such as shoplifting, are considered to be common in frontotemporal dementia (FTD) patients, there have been few studies on this subject and the frequencies and types of such violations have not been clarified. The objective of this study was to conduct a retrospective investigation of FTD patients in the psychiatry departments of multiple institutions to determine the types and frequencies of any law violations and compare them with those of AD patients. All patients were examined between January 2011 and December 2015 at the specialized dementia outpatient clinics of 10 facilities (5 psychiatry departments of university hospitals, 5 psychiatric hospitals). According to diagnostic criteria, 73 behavior variant FTD (bvFTD) patients, 84 semantic variant of primary progressive aphasia (svPPA) patients, and 255 age- and sex-matched AD subjects as the control group were selected. The findings revealed a higher rate of law violations in the bvFTD and svPPA patients before the initial consultation as compared to the AD group (bvFTD: 33%, svPPA: 21%, AD: 6%) and that many patients had been referred due to such violations. Laws had been broken 4 times or 5 or more times in several cases in the FTD group before the initial consultation. Regarding rates for different types of violation, in bvFTD subjects, the highest rate was for theft, followed by nuisance acts and hit and run. In svPPA, theft had the highest rate, followed by ignoring road signs. There was no gender difference in law violations but they were more frequent when the disease was severe at the initial consultation in the FTD group. As the rates of law violations after the initial consultation were lower than before it, interventions were considered to have been effective. These findings may be useful for future prevention as well as to the legal system.

Visit-to-Visit Blood Pressure Variability and Alzheimer's Disease: Links and Risks. - Nagai, Michiaki; Dote, Keigo; Kato, Masaya; Sasaki, Shota; Oda, Noboru; Kagawa, Eisuke; Nakano, Yoshinori; Yamane, Aya; Higashihara, Tasuku; Miyauchi, Shunsuke; Tsuchiya, Akane (J Alzheimers Dis, 2017)
While hypertension has been shown to be a risk factor for vascular dementia, several studies have also demonstrated that hypertension also increases the risk of Alzheimer's disease (AD). Although the relationship between visit-to-visit blood pressure variability (VVV) and cognitive impairment, including AD, have been provided, the mechanisms remain poorly understood. This review paper focuses on the relationship of VVV with AD and summarizes the pathophysiology underlying that relationship, which appears to be mediated by arterial stiffness.

Voluptuary Habits and Risk of Frontotemporal Dementia: A Case Control Retrospective Study. - Tremolizzo, Lucio; Bianchi, Elisa; Susani, Emanuela; Pupillo, Elisabetta; Messina, Paolo; Aliprandi, Angelo; Salmaggi, Andrea; Cosseddu, Maura; Pilotto, Andrea; Borroni, Barbara; Padovani, Alessandro; Bonomini, Cristina; et al. (J Alzheimers Dis, 2017)
Alcohol, coffee, and tobacco consumption was assessed on 151 FTD outpatients and 151 matched controls in a multicenter retrospective case-control design. No association was found for smoking and coffee intake. The risk of FTD was decreased by alcohol consumption (adj. OR 0.30, 95% CI 0.14-0.63); risk reduction was significant in current alcohol consumers (adj. OR 0.22, 95% CI 0.10-0.51). The risk of FTD inversely correlated with the duration of exposure (adj. OR 0.88, 95% CI 0.81-0.95, for every 5 years of exposure increase). Retrospective information and the unknown amount of consumed alcohol are limits of the present work.

von Economo Neuron Density and Thalamus Volumes in Behavioral Deficits in Frontotemporal Dementia Cases with and without a C9ORF72 Repeat Expansion. - Yang, Yue; Halliday, Glenda M; Hodges, John R; Tan, Rachel H (J Alzheimers Dis, 2017)
BACKGROUND: The early and selective loss of von Economo neurons in the anterior cingulate cortex has been linked to behavioral deficits in frontotemporal dementia (FTD). Importantly, whether these neurons are also targeted in patients with the C9ORF72 repeat expansion has yet to be established. This is of particular interest given the recent evidence highlighting the thalamus rather than anterior cingulate cortex as a region of significant degeneration in patients with the C9ORF72 repeat expansion. OBJECTIVE: To assess the von Economo neuron density and thalamus volumes in behavioral variant FTD (bvFTD) cases with the C9ORF72 repeat expansion, sporadic bvFTD, sporadic ALS, and controls. METHODS: Volumetric and quantitative cell counting methods were employed to assess the von Economo neuron density and thalamus volumes in 37 pathologically-confirmed cases comprised of patients with bvFTD (n = 13) cases with the C9ORF72 repeat expansion (62% with psychosis), sporadic bvFTD (n = 8), sporadic amyotrophic lateral sclerosis (n = 7) and controls (n = 9). RESULTS: von Economo neuron density was significantly reduced in sporadic bvFTD cases only. Thalamus degeneration was identified only in bvFTD cases with the C9ORF72 repeat expansion, and to a similar extent in cases with and without psychosis. No significant difference in von Economo neuron density or thalamus degeneration was seen between bvFTD cases with or without the C9ORF72 repeat expansion. CONCLUSION: The present histological findings converge with neuroimaging results to corroborate the anterior cingulate cortex as a core region involved in sporadic bvFTD, and the thalamus as a major region targeted in patients with the C9ORF72 expansion.

What Can Quantitative Gait Analysis Tell Us about Dementia and Its Subtypes? A Structured Review. - Mc Ardle, Ríona; Morris, Rosie; Wilson, Joanna; Galna, Brook; Thomas, Alan J; Rochester, Lynn (J Alzheimers Dis, 2017)
Distinguishing dementia subtypes can be difficult due to similarities in clinical presentation. There is increasing interest in discrete gait characteristics as markers to aid diagnostic algorithms in dementia. This structured review explores the differences in quantitative gait characteristics between dementia and healthy controls, and between four dementia subtypes under single-task conditions: Alzheimer's disease (AD), dementia with Lewy bodies and Parkinson's disease dementia, and vascular dementia. Twenty-six papers out of an initial 5,211 were reviewed and interpreted using a validated model of gait. Dementia was associated with gait characteristics grouped by slower pace, impaired rhythm, and increased variability compared to normal aging. Only four studies compared two or more dementia subtypes. People with AD are less impaired in pace, rhythm, and variability domains of gait compared to non-AD dementias. Results demonstrate the potential of gait as a clinical marker to discriminate between dementia subtypes. Larger studies using a more comprehensive battery of gait characteristics and better characterized dementia sub-types are required.

Young to Middle-Aged Dogs with High Amyloid-β Levels in Cerebrospinal Fluid are Impaired on Learning in Standard Cognition tests. - Borghys, Herman; Van Broeck, Bianca; Dhuyvetter, Deborah; Jacobs, Tom; de Waepenaert, Katja; Erkens, Tim; Brooks, Melissa; Thevarkunnel, Sandy; Araujo, Joseph A (J Alzheimers Dis, 2017)
Understanding differences in Alzheimer's disease biomarkers before the pathology becomes evident can contribute to an improved understanding of disease pathogenesis and treatment. A decrease in amyloid-β (Aβ)42 in cerebrospinal fluid (CSF) is suggested to be a biomarker for Aβ deposition in brain. However, the relevance of CSF Aβ levels prior to deposition is not entirely known. Dogs are similar to man with respect to amyloid-β protein precursor (AβPP)-processing, age-related amyloid plaque deposition, and cognitive dysfunction. In the current study, we evaluated the relation between CSF Aβ42 levels and cognitive performance in young to middle-aged dogs (1.5-7 years old). Additionally, CSF sAβPPα and sAβPPβ were measured to evaluate AβPP processing, and CSF cytokines were measured to determine the immune status of the brain. We identified two groups of dogs showing consistently low or high CSF Aβ42 levels. Based on prior studies, it was assumed that at this age no cerebral amyloid plaques were likely to be present. The cognitive performance was evaluated in standard cognition tests. Low or high Aβ concentrations coincided with low or high sAβPPα, sAβPPβ, and CXCL-1 levels, respectively. Dogs with high Aβ concentrations showed significant learning impairments on delayed non-match to position (DNMP), object discrimination, and reversal learning compared to dogs with low Aβ concentrations. Our data support the hypothesis that high levels of CSF Aβ in dogs coincide with lower cognitive performance prior to amyloid deposition. Further experiments are needed to investigate this link, as well as the relevance with respect to Alzheimer's disease pathology progression.

ABCA7 Genotypes Confer Alzheimer's Disease Risk by Modulating Amyloid-β Pathology. - Zhao, Qing-Fei; Wan, Yu; Wang, Hui-Fu; Sun, Fu-Rong; Hao, Xiao-Ke; Tan, Meng-Shan; Tan, Chen-Chen; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
ABCA7 gene has been identified as a strong genetic locus for Alzheimer's disease (AD) susceptibility in genome wide association studies (GWAS). However, the possible roles of ABCA7 variants in AD pathology were not specifically assessed. Using tagger methods, we extracted 15 targeted ABCA7 loci to investigate their associations with cerebrospinal fluid (CSF) and neuroimaging markers in Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset. Finally, although we did not detect any significant associations of previously published GWAS SNPs (rs3764650 and rs78117248) with all the CSF (Aβ1 - 42, T-tau, and P-tau) and neuroimaging markers, three other variants (rs3752242, rs3752240, and rs4147912) at ABCA7 loci were detected to show significant associations with amyloid deposition on AV-45 PET in brain. Moreover, haplotype and subgroup analysis confirmed these significant findings. Furthermore, there were no remarkable correlations between ABCA7 variants and neuronal degeneration biomarkers (elevated CSF tau, brain structure atrophy, and hypometabolism on imaging) in this study. Thus, our study suggested that ABCA7 genotypes contribute to the AD risk through involvement in amyloid-β deposition on in vivo imaging, but not in tau pathology, brain atrophy, or decreased glucose metabolism.

Activation of p53 in Down Syndrome and in the Ts65Dn Mouse Brain is Associated with a Pro-Apoptotic Phenotype. - Tramutola, Antonella; Pupo, Gilda; Di Domenico, Fabio; Barone, Eugenio; Arena, Andrea; Lanzillotta, Chiara; Broekaart, Diede; Blarzino, Carla; Head, Elizabeth; Butterfield, D Allan; Perluigi, Marzia (J Alzheimers Dis, 2016)
Down syndrome (DS) is the most common genetic cause of intellectual disability, resulting from trisomy of chromosome 21. The main feature of DS neuropathology includes early onset of Alzheimer's disease (AD), with deposition of senile plaques and tangles. We hypothesized that apoptosis may be activated in the presence of AD neuropathology in DS, thus we measured proteins associated with upstream and downstream pathways of p53 in the frontal cortex from DS cases with and without AD pathology and from Ts65Dn mice, at different ages. We observed increased acetylation and phosphorylation of p53, coupled to reduced MDM2/p53 complex level and lower levels of SIRT1. Activation of p53 was associated with a number of targets (BAX, PARP1, caspase-3, p21, heat shock proteins, and PGC1α) that were modulated in both DS and DS/AD compared with age-matched controls. In particular, the most relevant changes (increased p-p53 and acetyl-p53 and reduced formation of MDM2/p53 complex) were found to be modified only in the presence of AD pathology in DS. In addition, a similar pattern of alterations in the p53 pathway was found in Ts65Dn mice. These results suggest that p53 may integrate different signals, which can result in a pro-apoptotic-phenotype contributing to AD neuropathology in people with DS.
Keywords: Acetylation; Alzheimer Disease; Animals; Apoptosis; Blotting, Western; Disease Models, Animal; Down Syndrome; Female; Frontal Lobe; Humans; Immunoprecipitation; Male; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Middle Aged; Phenotype; Phosphorylation; Tumor Suppressor Protein p53; Young Adult

Active Cigarette Smoking in Cognitively-Normal Elders and Probable Alzheimer's Disease is Associated with Elevated Cerebrospinal Fluid Oxidative Stress Biomarkers. - Durazzo, Timothy C; Korecka, Magdalena; Trojanowski, John Q; Weiner, Michael W; O' Hara, Ruth; Ashford, John W; Shaw, Leslie M (J Alzheimers Dis, 2016)
Neurodegenerative diseases and chronic cigarette smoking are associated with increased cerebral oxidative stress (OxS). Elevated F2-isoprostane levels in biological fluid is a recognized marker of OxS. This study assessed the association of active cigarette smoking with F2-isoprostane in concentrations in cognitively-normal elders (CN), and those with mild cognitive impairment (MCI) and probable Alzheimer's disease (AD). Smoking and non-smoking CN (n = 83), MCI (n = 164), and probable AD (n = 101) were compared on cerebrospinal fluid (CSF) iPF2α-III and 8,12, iso-iPF2α-VI F2-isoprostane concentrations. Associations between F2-isoprostane levels and hippocampal volumes were also evaluated. In CN and AD, smokers had higher iPF2α-III concentration; overall, smoking AD showed the highest iPF2α-III concentration across groups. Smoking and non-smoking MCI did not differ on iPF2α-III concentration. No group differences were apparent on 8,12, iso-iPF2α-VI concentration, but across AD, higher 8,12, iso-iPF2α-VI level was related to smaller left and total hippocampal volumes. Results indicate that active cigarette smoking in CN and probable AD is associated with increased central nervous system OxS. Further investigation of factors mediating/moderating the absence of smoking effects on CSF F2-isoprostane levels in MCI is warranted. In AD, increasing magnitude of OxS appeared to be related to smaller hippocampal volume. This study contributes additional novel information to the mounting body of evidence that cigarette smoking is associated with adverse effects on the human central nervous system across the lifespan.

Administering Cognitive Tests Through Touch Screen Tablet Devices: Potential Issues. - Jenkins, Amy; Lindsay, Stephen; Eslambolchilar, Parisa; Thornton, Ian M; Tales, Andrea (J Alzheimers Dis, 2016)
Mobile technologies, such as tablet devices, open up new possibilities for health-related diagnosis, monitoring, and intervention for older adults and healthcare practitioners. Current evaluations of cognitive integrity typically occur within clinical settings, such as memory clinics, using pen and paper or computer-based tests. In the present study, we investigate the challenges associated with transferring such tests to touch-based, mobile technology platforms from an older adult perspective. Problems may include individual variability in technical familiarity and acceptance; various factors influencing usability; acceptability; response characteristics and thus validity per se of a given test. For the results of mobile technology-based tests of reaction time to be valid and related to disease status rather than extraneous variables, it is imperative the whole test process is investigated in order to determine potential effects before the test is fully developed. Researchers have emphasized the importance of including the 'user' in the evaluation of such devices; thus we performed a focus group-based qualitative assessment of the processes involved in the administration and performance of a tablet-based version of a typical test of attention and information processing speed (a multi-item localization task), to younger and older adults. We report that although the test was regarded positively, indicating that using a tablet for the delivery of such tests is feasible, it is important for developers to consider factors surrounding user expectations, performance feedback, and physical response requirements and to use this information to inform further research into such applications.

Alcohol Consumption and Incident Dementia: Evidence from the Sydney Memory and Ageing Study. - Heffernan, Megan; Mather, Karen A; Xu, Jing; Assareh, Amelia A; Kochan, Nicole A; Reppermund, Simone; Draper, Brian; Trollor, Julian N; Sachdev, Perminder; Brodaty, Henry (J Alzheimers Dis, 2016)
Alcohol consumption is a potentially modifiable risk factor for dementia, but the literature is not completely consistent. This inconsistency may be partly due to an interaction with the apolipoprotein E (APOE) genotype, an established risk factor for Alzheimer's dementia. The aim of this study was to examine whether alcohol consumption is associated with incident dementia or decline in specific cognitive domains over 4 years, and if this effect is modified by APOEɛ4 status. Non-demented community dwelling older adults (70-90 years) from an ongoing longitudinal study were assessed for cognitive impairment in attention/processing speed, language, executive function, visuospatial ability, and memory. Incident dementia was diagnosed according to DSM-IV criteria. Compared to those who did not drink in the previous 12 months, neither low consumption (HR 0.64 95% CI 0.3-1.4) or risky consumption (HR 0.58 95% CI 0.2-1.5) was associated with incident dementia. Carriers of the APOEɛ4 allele were more likely to develop dementia, but there was no significant interaction with alcohol consumption.

Alterations in Phase-Related Prefrontal Activation During Cognitive Tasks and Nicotinic α4β2 Receptor Availability in Alzheimer's Disease. - Oboshi, Yumi; Kikuchi, Mitsuru; Terada, Tatsuhiro; Yoshikawa, Etsuji; Bunai, Tomoyasu; Ouchi, Yasuomi (J Alzheimers Dis, 2016)
BACKGROUND: Evidence shows that the cholinergic system plays an important role in regulating working memory and that working memory-related prefrontal activation decreases with age and neuronal degeneration, such as Alzheimer's disease (AD). However, the relation between attention-related α4β2 nicotinic cholinergic function and task-induced prefrontal activation especially time course-related activation remains to be explored. OBJECTIVE: We aimed to elucidate the relationship between changes in task-induced oxy-hemoglobin concentration (cerebral blood flow, CBF) in the prefrontal cortex and the availability of α4β2 nicotinic receptors in the brain of AD patients in light of their task performance. METHODS: Eleven mild-to-moderate AD patients and eleven normal elderly subjects underwent the near-infrared spectroscopy during easy and difficult working memory tasks for estimating prefrontal CBF changes and positron emission tomography with the α4β2 tracer [18F]2FA-85380 ([18F]2FA) for measuring the α4β2 nicotinic receptor binding. RESULTS: Significant correlations between mean oxy-hemoglobin concentration in the channels with significant [group] main effects and prefrontal [18F]2FA binding were observed during the early easy task period in the normal group and during the late difficult task in the AD group. In addition, those prefrontal CBF responses were significantly correlated with not correct performance but the execution time to spend. CONCLUSION: The α4β2 nicotinic acetylcholine receptors in the prefrontal cortex play an important role in increasing prefrontal activation when attending to novel stimuli, irrespective of the accuracy of the outcome. A delay in the cholinergic-induced increase in prefrontal activation in AD patients might explain their delayed responses in the cognitive task.

Amyloid-β Reduces Exosome Release from Astrocytes by Enhancing JNK Phosphorylation. - Abdullah, Mohammad; Takase, Hiroshi; Nunome, Mari; Enomoto, Hiroyuki; Ito, Jin-Ichi; Gong, Jian-Sheng; Michikawa, Makoto (J Alzheimers Dis, 2016)
Exosomes are small extracellular vesicles secreted by variety of cell types such as neurons, astrocytes, and oligodendrocytes. It is suggested that exosomes play essential role in the maintenance of the neuronal functions and also in the clearance of amyloid-β (Aβ) from the brain. Aβ is well known to cause neuronal cell death, whereas little is known about its effect on astrocytes. In this study, we examined the effect of Aβ on release of exosomes from astrocytes in culture. We analyzed release of exosomes and apoE, both of which are known to remove/clear Aβ from the brain, in the culture medium of astrocytes. We found that exosome and apoE-HDL were successfully separated by density gradient ultracentrifugation demonstrated by distribution of their specific markers, flotillin and HSP90, and cholesterol, and morphological analysis using electron microscopy. Exosome release was significantly reduced by Aβ1-42 treatment in cultured astrocytes accompanied by an increased JNK phosphorylation. Whereas, apoE-HDL release remained unchanged. A JNK inhibitor restored the decreased levels of exosome release induced by Aβ treatment to levels similar to those of control, suggesting that Aβ1-42 inhibits exosome release via stimulation of JNK signal pathway. Because exosomes are shown to remove Aβ in the brain, our findings suggest that increased Aβ levels in the brain may impair the exosome-mediated Aβ clearance pathway.

The Anti-Prion Antibody 15B3 Detects Toxic Amyloid-β Oligomers. - Stravalaci, Matteo; Tapella, Laura; Beeg, Marten; Rossi, Alessandro; Joshi, Pooja; Pizzi, Erika; Mazzanti, Michele; Balducci, Claudia; Forloni, Gianluigi; Biasini, Emiliano; Salmona, Mario; Diomede, Luisa; et al. (J Alzheimers Dis, 2016)
15B3 is a monoclonal IgM antibody that selectively detects pathological aggregates of the prion protein (PrP). We report the unexpected finding that 15B3 also recognizes oligomeric but not monomeric forms of amyloid-β (Aβ)42, an aggregating peptide implicated in the pathogenesis of Alzheimer's disease (AD). The 15B3 antibody: i) inhibits the binding of synthetic Aβ42 oligomers to recombinant PrP and neuronal membranes; ii) prevents oligomer-induced membrane depolarization; iii) antagonizes the inhibitory effects of oligomers on the physiological pharyngeal contractions of the nematode Caenorhabditis elegans; and iv) counteracts the memory deficits induced by intracerebroventricular injection of Aβ42 oligomers in mice. Thus this antibody binds to pathologically relevant forms of Aβ, and offers a potential research, diagnostic, and therapeutic tool for AD.

Apo J and Apo D: Complementary or Antagonistic Roles in Alzheimer's Disease? - Del Valle, Eva; Navarro, Ana; Martínez-Pinilla, Eva; Torices, Silvia; Tolivia, Jorge (J Alzheimers Dis, 2016)
Apolipoprotein D (Apo D) and Apolipoprotein J (Apo J) are among the only nine apolipoproteins synthesized in the nervous system. Apart from development, these apolipoproteins are implicated in the normal aging process as well as in different neuropathologies as Alzheimer's disease (AD), where a neuroprotective role has been postulated. Different authors have proposed that Apo D and Apo J could be biomarkers for AD but as far as we know, there are no studies about the relationship between them as well as their expression pattern along the progression of the disease. In this paper, using double immunohistochemistry techniques, we have demonstrated that Apo D is mainly located in glial cells while Apo J expression preferentially occurs in neurons; both proteins are also present in AD diffuse and mature senile plaques but without signal overlap. In addition, we have observed that Apo J and Apo D immunostaining shows a positive correlation with the progression of the disease and the Braak's stages. These results suggest complementary and cell-dependent neuroprotective roles for each apolipoprotein during AD progress.

Application of the IWG-2 Diagnostic Criteria for Alzheimer's Disease to the ADNI. - Wang, Hui-Fu; Tan, Lan; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Liu, Ying; Wang, Chong; Tsai, Richard M; Jia, Jian-Ping; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: The International Working Group (IWG) recently proposed the revised diagnostic criteria for Alzheimer's disease (AD) to define and refine several types of AD, and to reclassify AD-related biomarkers into diagnostic and progression markers, but its performance is not known. OBJECTIVE: This study was designed to describe the application of the revised IWG criteria in the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, and to ascertain whether diagnostic and progression markers show significant differences in their relationships to AD severity and progression. METHODS: Based on the requirements of the refined criteria, 857 ADNI subjects with memory evaluation and at least one pathophysiological marker (CSF or amyloid imaging biomarkers) were eligible and reclassified in this study, and we calculated the associations of diagnostic (CSF and amyloid PET) and progression markers (MRI and fluorodeoxyglucose-PET) with AD severity and progression respectively. RESULTS: The majority (84.2% ) of ADNI AD group (n = 117) and 173 MCI (37.4% ) subjects in ADNI met the definition of typical AD; and 105 cognitively normal (41.0% ) individuals were diagnosed as asymptomatic AD. Furthermore, diagnostic and progression markers showed significant differences when correlated to AD severity and progression. CONCLUSION: A large proportion of AD dementia subjects were categorized as typical AD, and the revised criteria could identify typical AD from MCI status as well as asymptomatic AD at the asymptomatic stage. Moreover, the significant differences between diagnostic and progression markers further supported the new biomarkers categorization in the refined criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognitive Dysfunction; Databases, Factual; Disease Progression; Female; Humans; Longitudinal Studies; Male; Multicenter Studies as Topic; Neuroimaging; Psychiatric Status Rating Scales; tau Proteins

Artificial Neural Networks Link One-Carbon Metabolism to Gene-Promoter Methylation in Alzheimer's Disease. - Grossi, Enzo; Stoccoro, Andrea; Tannorella, Pierpaola; Migliore, Lucia; Coppedè, Fabio (J Alzheimers Dis, 2016)
BACKGROUND: There is increasing interest in DNA methylation studies in Alzheimer's disease (AD), but little is still known concerning the relationship between gene-promoter methylation and circulating biomarkers of one-carbon metabolism in patients. OBJECTIVE: To detect the connections among circulating folate, homocysteine (hcy) and vitamin B12 levels and promoter methylation levels of PSEN1, BACE1, DNMT1, DNMT3A, DNMT3B, and MTHFR genes in blood DNA. METHODS: We applied a data mining system called Auto Contractive Map to an existing database of 100 AD and 100 control individuals. RESULTS: Low vitamin B12 was linked to the AD condition, to low folates, and to high hcy. Low PSEN1 methylation was linked to low folate levels as well as to low promoter methylation of BACE1 and DNMTs genes. Low hcy was linked to controls, to high folates and vitamin B12, as well as to high methylation levels of most of the studied genes. CONCLUSIONS: The present pilot study suggests that promoter methylation levels of the studied genes are linked to circulating levels of folates, hcy, and vitamin B12.

Association between Coffee Consumption and Incident Risk of Disabling Dementia in Elderly Japanese: The Ohsaki Cohort 2006 Study. - Sugiyama, Kemmyo; Tomata, Yasutake; Kaiho, Yu; Honkura, Kenji; Sugawara, Yumi; Tsuji, Ichiro (J Alzheimers Dis, 2016)
Epidemiological studies of the association between coffee consumption and dementia have yielded inconsistent results. Therefore, we investigated the association between coffee consumption and incident risk of dementia in an elderly Japanese population. 23,091 subjects aged ≥65 y living in Ohsaki City, northeastern Japan, responded to the baseline survey in 2006. Of these, we analyzed 13,137 subjects who gave informed consent and were not disabled at baseline. The outcome was the incidence of disabling dementia defined by usage of the Long-term Care Insurance database. We used the Cox proportional hazards regression model for multivariate analysis. During 5.7 y of follow-up period, we identified 1,107 cases of incident dementia. Overall, coffee consumption was significantly associated with a lower risk of incident dementia. The multivariate-adjusted HRs for the incidence of dementia according to coffee consumption categories (never, occasionally, 1-2 cups/d, and ≥3 cups/d) were 1.00, 0.73 (95% CI, 0.62-0.86), 0.72 (95% CI, 0.61-0.84), and 0.82 (95% CI, 0.65-1.02; p for trend = 0.009), respectively. In addition, this significant inverse association was more remarkable among women, non-smokers, and non-drinkers. Coffee consumption is significantly associated with a lower risk of incident dementia.
Keywords: Aged; Aged, 80 and over; Coffee; Dementia; Female; Health Surveys; Humans; Incidence; Japan; Male; Prospective Studies; Risk Factors

Association Between Smoking and Cholinergic Basal Forebrain Volume in Healthy Aging and Prodromal and Dementia Stages of Alzheimer's Disease. - Teipel, Stefan; Grothe, Michel J (J Alzheimers Dis, 2016)
BACKGROUND: Smoking has been found associated with decreased cerebral volumes in healthy adults and in various neuropsychiatric disorders. OBJECTIVE: We aimed to determine whether chronic nicotine exposure through smoking is associated with reduced volume of cortically projecting cholinergic basal forebrain nuclei in healthy aging, mild cognitive impairment (MCI), and dementia stages of Alzheimer's disease (AD). METHODS: We retrieved cross-sectional data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database including 179 cognitively normal elderly subjects, 270 subjects with early stage MCI, 136 subjects in later, more advanced, stage of MCI, and 86 subjects in dementia stages of AD. We determined the association between past or current smoking versus lifetime non-smoker status on the volumes of the basal forebrain determined from volumetric MRI scans. Hippocampus volume was used as a control region. Significant effects were controlled for mediating or moderating effects of respiratory and cardiovascular morbidity. RESULTS: In cognitively healthy individuals and early MCI, past or current smoking was significantly associated with smaller basal forebrain volume. This effect was independent from age, sex, or cardiovascular or respiratory morbidity. Hippocampus volume was not associated with smoking. In late MCI and AD dementia, smoking was not associated with basal forebrain or hippocampus volumes. CONCLUSIONS: Our findings suggest that chronic nicotine exposure through smoking may lead to atrophy of cholinergic input areas of the basal forebrain. This effect may account for an increased risk of AD dementia onset with smoking by exhausting the cholinergic system reserve capacity.

Association of Coffee Consumption with MRI Markers and Cognitive Function: A Population-Based Study. - Araújo, Larissa Fortunato; Mirza, Saira Saeed; Bos, Daniel; Niessen, Wiro J; Barreto, Sandhi Maria; van der Lugt, Aad; Vernooij, Meike W; Hofman, Albert; Tiemeier, Henning; Ikram, M Arfan (J Alzheimers Dis, 2016)
BACKGROUND: Coffee is one of the most widely consumed beverages worldwide and has been of considerable interest in research on cognition and dementia. OBJECTIVE: To investigate the effect of coffee on preclinical brain MRI markers of dementia and cognitive performance. METHODS: In 2,914 participants from the population-based Rotterdam Study (mean age: 59.3±7.2 years, 55% females), we assessed coffee consumption, performed brain MRI, and assessed cognition at baseline. To study cognitive change, cognitive assessment was repeated after 5 years of follow-up. Coffee consumption was analyzed continuously (per cup increase) and in categories (0-1, >1-3, >3 cups/day). Using logistic and linear regression, associations of coffee consumption with lacunar infarcts and brain tissue volumes on MRI, and cognitive performance (cross-sectional and longitudinal) were investigated, adjusting for relevant confounders. RESULTS: We found that higher coffee consumption was associated with a lower prevalence of lacunar infarcts [odds ratio per cup increase: 0.88 (95% CI:0.79;0.98)], and smaller hippocampal volume [difference: -0.01 (95% CI:-0.02;0.00)]. Also, we found that the highest category of coffee consumption was associated with better performance on the Letter Digit Substitution Task [difference: 1.13(95% CI:0.39;1.88)], Word Fluency test [0.74(95% CI:0.04,1.45)], Stroop interference task [1.82(95% CI:0.23;3.41)], and worse performance on the 15-Word Learning test delayed recall [-0.38(95% CI:-0.74;-0.02)]. These associations were not found when cognition was analyzed longitudinally. CONCLUSION: We found complex associations between coffee consumption, brain structure, and cognition. Higher coffee consumption was cross-sectionally associated with a lower occurrence of lacunar infarcts and better executive function, but also with smaller hippocampal volume and worse memory function.

Association of Frontotemporal Dementia GWAS Loci with Late-Onset Alzheimer's Disease in a Northern Han Chinese Population. - Tan, Chen-Chen; Wan, Yu; Tan, Meng-Shan; Zhang, Wei; Wang, Zi-Xuan; Sun, Fu-Rong; Miao, Dan; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Both Alzheimer's disease (AD) and frontotemporal dementia (FTD) are a class of neurodegenerative diseases. Strong similarities in cerebrospinal fluid biomarker, imaging markers, and disease progression profiles suggest that some or most of the pathophysiology is shared between AD and FTD. A recent large genome-wide association study reported several single nucleotide polymorphisms (SNPs) at the RAB38, RAB38/CTSC, HLA-DRA/HLA-DRB5, and BTNL2 in association with FTD. OBJECTIVE: To explore whether these SNPs are associated with AD risk. METHODS: We conducted a case-control study to investigate the association of FTD-associated loci in 2338 Han Chinese subjects. RESULTS: We observed significant differences in genotype distributions of rs302668 (pc = 0.025), rs9268877 (pc = 0.025), rs9268856 (p <  0.001), and rs1980493 (pc = 0.045) between cases and controls. The SNPs rs16913634 for RAB38/CTSC was unrelated to LOAD risk (p = 0.088). CONCLUSION: The SNPs rs302668 in RAB38, rs9268877 and rs9268856 polymorphism in HLA-DRA/HLA-DRB5, and rs1980493 polymorphism in BTNL2 might play a role in the susceptibility to late-onset AD in the Han Chinese population.
Keywords: Age of Onset; Aged; Alzheimer Disease; Apolipoprotein E4; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Genotyping Techniques; Humans; Linkage Disequilibrium; Male; Mental Status Schedule; Polymorphism, Single Nucleotide

Association of Physical Function with Clinical and Subclinical Brain Disease: The Framingham Offspring Study. - Camargo, Erica C; Weinstein, Galit; Beiser, Alexa S; Tan, Zaldy S; DeCarli, Charles; Kelly-Hayes, Margaret; Kase, Carlos; Murabito, Joanne M; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Handgrip strength and gait speed are simple measures of physical capability and have been associated with current and future health outcomes. However, studies on their associations with brain structure and function in middle-aged adults are lacking. OBJECTIVE: To assess the relationship of fast-paced walking speed and handgrip strength with risk of dementia, Alzheimer's disease (AD), and stroke, as well as the cross-sectional associations with cognitive and brain magnetic resonance imaging (MRI) measures in a middle-aged community sample. METHODS: Framingham Offspring (n = 2,176; mean age 62, 54% female) had physical function, brain MRI, and cognitive evaluations between 1999 and 2005 and were followed-up for incident dementia AD and stroke until 11 years later. We related walking speed and handgrip strength to incident dementia, AD, and stroke using Cox models, and to brain and cognitive measures using multivariable linear and logistic regression. Models were adjusted for age, sex, education, and vascular risk factors. RESULTS: Slow walking and weak handgrip were associated with more than 2.5-fold increase in risk of AD. Weaker handgrip was associated with an increased risk of incident stroke (HR 1.74, 95% CI: 1.12-2.70/SDU, p = 0.01) in persons ≥65 years. Both measures were associated with lower total brain volume and poorer performance on tests of visual memory, language, executive function, and visuoperceptual function. Slower gait was also related to poorer verbal memory, and weaker handgrip to poorer abstraction. CONCLUSION: Tests of walking speed and handgrip strength may serve as clinical markers of brain structure and function and may improve dementia risk prediction.

Association of Plasma Aβ40 Peptides, But Not Aβ42, with Coronary Artery Disease and Diabetes Mellitus. - Roeben, Benjamin; Maetzler, Walter; Vanmechelen, Eugeen; Schulte, Claudia; Heinzel, Sebastian; Stellos, Konstantinos; Godau, Jana; Huber, Heiko; Brockmann, Kathrin; Wurster, Isabel; Gaenslen, Alexandra; Grüner, Eva; et al. (J Alzheimers Dis, 2016)
BACKGROUND/OBJECTIVE: Plasma levels of amyloid-beta (Aβ) 1-40 peptide have been proposed to be associated with cardiovascular mortality in patients with coronary artery disease (CAD). Therefore, we aimed to investigate the association of plasma Aβ levels with CAD, cardiovascular risk factors (CVRF), and APOE genotype in non-demented elderly individuals. METHODS: Plasma Aβ1 - 40 and Aβ1 - 42 levels of 526 individuals (mean age of 63.0±7.3 years) were quantified with the INNO-BIA plasma Aβ forms assay based on multiplextrademark technique. APOE genotype was determined with an established protocol. Presence of CAD and CVRFs were ascertained using a questionnaire and/or medical records. RESULTS: Plasma Aβ1 - 40 levels were significantly higher in individuals with CAD (p = 0.043) and, independently, in individuals with diabetes mellitus (DM) type 2 (p = 0.001) while accounting for age- and gender-effects. Plasma Aβ1 - 42 levels were higher in APOEɛ4 carriers (p = 0.004), but were neither relevantly associated with CAD nor with any CVRF. Plasma Aβ1 - 40 showed no association with APOE genotype. DISCUSSION: Our findings argue for an association of circulating plasma Aβ1 - 40 peptides with incident CAD and DM. Further investigations are needed to entangle the role of Aβ1 - 40 role in the pathophysiology of cardiovascular disease independent of its known role in Alzheimer's disease.

Association of Platelet Serotonin Levels in Alzheimer's Disease with Clinical and Cerebrospinal Fluid Markers. - Tajeddinn, Walid; Fereshtehnejad, Seyed-Mohammad; Seed Ahmed, Mohammed; Yoshitake, Takashi; Kehr, Jan; Shahnaz, Tasmin; Milovanovic, Micha; Behbahani, Homira; Höglund, Kina; Winblad, Bengt; Cedazo-Minguez, Angel; Jelic, Vesna; et al. (J Alzheimers Dis, 2016)
INTRODUCTION: Serotonin (5-HT) is involved in the pathology of Alzheimer's disease (AD). OBJECTIVE: We aimed to measure 5-HT level in platelets in AD and explore its association with cerebrospinal fluid (CSF), AD biomarkers (amyloid-β 1-42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau)), and clinical symptoms. METHODS: 15 patients with AD and 20 patients with subjective cognitive impairment (SCI) were included. 5-HT metabolites were measured, in a specific fraction, using high performance liquid chromatography with electrochemical detection (HPLC-ECD). RESULTS: Significantly lower 5-HT concentrations were observed in AD patients compared to SCI patients both after normalization against total protein (p = 0.008) or platelet count (p = 0.019). SCI patients with lower 5-HT level have higher AD CSF biomarkers, total tau (p = 0.026) and tau/Aβ42 ratio (p = 0.001), compared to those with high 5-HT levels. CONCLUSION: AD patients have reduced platelet 5-HT levels. In SCI, lower 5-HT content was associated with a higher AD-CSF biomarker burden.

Associations between Serum Omega-3 Fatty Acid Levels and Cognitive Functions among Community-Dwelling Octogenarians in Okinawa, Japan: The KOCOA Study. - Nishihira, Junko; Tokashiki, Takashi; Higashiuesato, Yasushi; Willcox, Donald Craig; Mattek, Nora; Shinto, Lynne; Ohya, Yusuke; Dodge, Hiroko H (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies have found frequent consumption of fatty fish is protective against cognitive decline. However, the association between circulating omega-3 polyunsaturated fatty acid (PUFA) levels and cognitive functions among the oldest old is not well known. OBJECTIVE: To examine the association between serum PUFA levels and cognitive function among community-dwelling, non-demented elderly aged over 80 years old. METHODS: The data came from the Keys to Optimal Cognitive Aging (KOCOA) study; an ongoing cohort of relatively healthy volunteers aged over 80 years old, living in Okinawa, Japan. One hundred eighty five participants (mean age 84.1±3.4 years) assessed in 2011 who were free from frank dementia (defined as Clinical Dementia Rating <1.0) were used for the current cross-sectional study. We examined whether serum omega-3 PUFAs (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]), arachidonic acid (AA), EPA/AA ratio, DHA/AA ratio, and DHA+EPA are associated with (1) age and (2) global cognitive function (Japanese MMSE) and executive function (Verbal Fluency Letter). Data was analyzed univariately by t-test and multivariately by cumulative logistic regression models controlling for age, gender, years of education, obesity, hypertension, diabetes, and dyslipidemia. RESULTS: Serum DHA levels decreased with increasing age (p = 0.04). Higher global cognitive function was associated with higher levels of serum EPA (p = 0.03) and DHA + EPA (p = 0.03) after controlling for confounders. CONCLUSIONS: Higher serum EPA and DHA + EPA levels were independently associated with better scores on global cognitive function among the oldest old, free from dementia. Longitudinal follow-up studies are warranted.
Keywords: Age Factors; Aged, 80 and over; Arachidonic Acid; Blood Chemical Analysis; Cognition; Cross-Sectional Studies; Educational Status; Fatty Acids, Omega-3; Female; Humans; Japan; Logistic Models; Male; Mental Status Schedule; Obesity; Prospective Studies; Sex Factors

Behavioral and Electrophysiological Correlates of Memory Binding Deficits in Patients at Different Risk Levels for Alzheimer's Disease. - Pietto, Marcos; Parra, Mario A; Trujillo, Natalia; Flores, Facundo; García, Adolfo M; Bustin, Julian; Richly, Pablo; Manes, Facundo; Lopera, Francisco; Ibáñez, Agustín; Baez, Sandra (J Alzheimers Dis, 2016)
Deficits in visual short-term memory (VSTM) binding have been proposed as an early and specific marker for Alzheimer's disease (AD). However, no studies have explored the neural correlates of this domain in clinical categories involving prodromal stages with different risk levels of conversion to AD. We assessed underlying electrophysiological modulations in patients with mild cognitive impairment (MCI), patients in the MCI stages of familial AD carrying the mutation E280A of the presenilin-1 gene (MCI-FAD), and healthy controls. Moreover, we compared the behavioral performance and neural correlates of both patient groups. Participants completed a change-detection VSTM task assessing recognition of changes between shapes or shape-color bindings, presented in two consecutive arrays (i.e., study and test) while event related potentials (ERPs) were recorded. Changes always occurred in the test array and consisted of new features replacing studied features (shape-only) or features swapping across items (shape-color binding). Both MCI and MCI-FAD patients performed worse than controls in the shape-color binding condition. Early electrophysiological activity (100-250 ms) was significantly reduced in both clinical groups, particularly over fronto-central and parieto-occipital regions. However, shape-color binding performance and their reduced neural correlates were similar between MCI and MCI-FAD. Our results support the validity of the VSTM binding test and their neural correlates in the early detection of AD and highlight the importance of studies comparing samples at different risk for AD conversion. The combined analysis of behavioral and ERP data gleaned with the VSTM binding task can offer a valuable memory biomarker for AD.

Beneficial Effects of an Integrated Psychostimulation Program in Patients with Alzheimer's Disease. - Ibarria, Marta; Alegret, Montserrat; Valero, Sergi; Morera, Amèrica; Guitart, Marina; Cañabate, Pilar; Moreno, Mariola; Lara, Susana; Diego, Susana; Hernández, Joan; Tantinyá, Natàlia; Vera, Maribel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The existing pharmacological treatments for Alzheimer's disease (AD) can only slow the progression of symptoms or delay admission to long-term care facilities. The beneficial effects of non-drug treatments are poorly studied. OBJECTIVE: To describe the effects of an Integrated Psychostimulation Program (IPP) in patients with mild-moderate AD treated with acetylcholinesterase inhibitors; and to identify factors related to greater benefit of the IPP. METHODS: 206 patients (mean age = 75.9 years; MMSE = 19.6) were evaluated before starting the IPP and 3, 6, 9, and 12 months later. Measures included: Mini-Mental State Examination (MMSE), Cognitive Subscale of Alzheimer's Disease Assessment Scale (ADAS-Cog), Rapid Disability Rating Scale (RDRS-2), and Neuropsychiatric Inventory Questionnaire (NPI-Q). RESULTS: Patients remained cognitively stable (MMSE/ADAS-Cog) for more than 6 months and significantly worsened at 9-month and 12-month follow-ups, without clinically significant functional changes (RDRS-2) or psychiatric symptoms(NPI-Q). The mean annual change on MMSE and ADAS-Cog were 2.06 and 3.56 points, respectively, lower than the annual decline demonstrated previously in similar patients (2.4 and 4.5, respectively). 42.7% of patients maintained or improved global cognitive scores between baseline and 12-month follow-up. The patients who maintained cognitive functions were older than those who did not (77.5 versus 74.7 years). CONCLUSIONS: The IPP may be an effective treatment to maintain cognition, functionality, and psychiatric symptoms in AD patients pharmacologically treated, and older age seems to increase beneficial effects of IPP.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Cognition; Combined Modality Therapy; Disease Progression; Female; Humans; Male; Neuropsychological Tests; Psychotherapy; Severity of Illness Index; Treatment Outcome

Biomarkers Differentiating Dementia with Lewy Bodies from Other Dementias: A Meta-Analysis. - Mishima, Aki; Nihashi, Takashi; Ando, Yoshio; Kawai, Hisashi; Kato, Takashi; Ito, Kengo; Terasawa, Teruhiko (J Alzheimers Dis, 2016)
BACKGROUND: Several nuclear imaging and cerebrospinal fluid (CSF) biomarkers are under investigation, aimed at facilitating the differential diagnosis of dementias. OBJECTIVE: To quantitatively synthesize data on test performance in differentiating dementia with Lewy bodies (DLB) from other dementias. METHODS: We searched PubMed (January 2000- March 2015) for English-language publications that assessed a selected set of five imaging and three CSF biomarkers for this purpose. We meta-analyzed measures of agreement between biomarker results and clinical diagnosis. RESULTS: Forty-five publications were eligible. The majority of evidence was based on studies that enrolled representative disease populations. For differentiating between DLB and Alzheimer's disease (AD) or other dementias, metaiodobenzylguanidine scintigraphy and dopamine transporter (DAT) single photon emission computed tomography (SPECT) showed, respectively, excellent (summary kappa = 0.85; 95% confidence interval [95% CI], 0.74-0.96) and good (summary kappa = 0.71; 95% CI, 0.43-0.99) agreement. Metaiodobenzylguanidine scintigraphy appeared superior to fluorodeoxyglucose- positron emission tomography (summary kappa = 0.53; 95% CI, 0.36-0.69) and cerebral blood flow SPECT (summary kappa = 0.40; 95% CI, 0.33-0.47). For differentiating DLB from AD, CSF t-tau levels (summary kappa = 0.68; 95% CI, 0.55-0.82) performed comparably to metaiodobenzylguanidine scintigraphy and DAT SPECT. Sparse direct comparative evidence failed to corroborate these indirect comparisons. CONCLUSION: Metaiodobenzylguanidine scintigraphy and DAT SPECT are highly concordant with clinical diagnosis in differentiating DLB from other dementias. However, given the limitations in the study design, the applicability of these results to real-world differential diagnosis remains unclear. Prospective studies targeting patients with atypical presentations that adopt gold standard tests would reliably estimate the true test performance of these promising biomarkers.
Keywords: Biomarkers; Dementia; Diagnosis, Differential; Humans; Lewy Bodies; PubMed; Radionuclide Imaging; Retrospective Studies

Blood-Based Biomarker Candidates of Cerebral Amyloid Using PiB PET in Non-Demented Elderly. - Westwood, Sarah; Leoni, Emanuela; Hye, Abdul; Lynham, Steven; Khondoker, Mizanur R; Ashton, Nicholas J; Kiddle, Steven J; Baird, Alison L; Sainz-Fuertes, Ricardo; Leung, Rufina; Graf, John; Hehir, Cristina Tan; et al. (J Alzheimers Dis, 2016)
Increasingly, clinical trials for Alzheimer's disease (AD) are being conducted earlier in the disease phase and with biomarker confirmation using in vivo amyloid PET imaging or CSF tau and Aβ measures to quantify pathology. However, making such a pre-clinical AD diagnosis is relatively costly and the screening failure rate is likely to be high. Having a blood-based marker that would reduce such costs and accelerate clinical trials through identifying potential participants with likely pre-clinical AD would be a substantial advance. In order to seek such a candidate biomarker, discovery phase proteomic analyses using 2DGE and gel-free LC-MS/MS for high and low molecular weight analytes were conducted on longitudinal plasma samples collected over a 12-year period from non-demented older individuals who exhibited a range of 11C-PiB PET measures of amyloid load. We then sought to extend our discovery findings by investigating whether our candidate biomarkers were also associated with brain amyloid burden in disease, in an independent cohort. Seven plasma proteins, including A2M, Apo-A1, and multiple complement proteins, were identified as pre-clinical biomarkers of amyloid burden and were consistent across three time points (p <  0.05). Five of these proteins also correlated with brain amyloid measures at different stages of the disease (q <  0.1). Here we show that it is possible to detect a plasma based biomarker signature indicative of AD pathology at a stage long before the onset of clinical disease manifestation. As in previous studies, acute phase reactants and inflammatory markers dominate this signature.

Brain-Specific Basal and Novelty-Induced Alternations in PI3K-Akt and MAPK/ERK Signaling in a Middle-Aged AβPP/PS1 Mouse Model of Alzheimer's Disease. - Guillot, Florence; Kemppainen, Susanna; Lavasseur, Gregoire; Miettinen, Pasi O; Laroche, Serge; Tanila, Heikki; Davis, Sabrina (J Alzheimers Dis, 2016)
Although it is well established that insulin/IGF and BDNF signaling are dysfunctionally regulated in Alzheimer's disease, there are very few studies documenting changes in major target proteins in different murine models of the disease. We investigated a panel of proteins in the PI3K-Akt and MAPK/ERK cascades in parietal cortex, dentate gyrus and CA1 in 13-month-old AβPP/PS1 transgenic mice to determine whether amyloid pathology is associated with basal dysregulation of these proteins or following exposure to novelty. The most striking effect we found was that there was little common regulation of proteins either by pathology alone or exposure to novelty across the three structures, suggesting dysfunctional mechanisms that occur simultaneously have important structure specificity. CA1 shared certain dysfunctional regulation of proteins in the MAPK/ERK cascade, but shared dysfunctional regulation of the PI3K/Akt cascade with the dentate gyrus. Changes in ERK/CREB in transgenic mice did not result in coordinated dysfunction of the downstream transcription factor, Egr1, as it was overexpressed in a normal manner following exposure to novelty. In the PI3K-Akt cascade, there was a flagrant increase in the levels of proteins associated with inflammation, such as NFκB, and structure specific regulation of proteins associated with autophagy, such as mTOR and FOXO1 and lack of regulation of Beclin-1. Finally, Beclin-1 was increased by novelty in wild-type mice but deficient in transgenic mice. Results are interpreted in terms of structure-specific dysfunctional regulation of signaling mechanisms associated with Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Gene Expression Regulation; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mitogen-Activated Protein Kinase Kinases; Mutation; Oncogene Protein v-akt; Phosphatidylinositol 3-Kinases; Presenilin-1; Signal Transduction

Bridging Integrator 1 (BIN1) Genotypes Mediate Alzheimer's Disease Risk by Altering Neuronal Degeneration. - Wang, Hui-Fu; Wan, Yu; Hao, Xiao-Ke; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Tan, Lin; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Bridging integrator 1 (BIN1) has been identified as one of the most associated loci for Alzheimer's disease (AD), and recently was reported to modulate tau pathology to mediate AD in vitro. However, the effects of BIN1 on the AD related biomarkers in AD continuum were not specifically assessed. OBJECTIVE: We explored the effects of BIN1 loci on AD specific biomarkers (CSF proteins, brain structures, glucose and amyloid-β (Aβ) metabolisms) to investigate the role BIN1 in AD pathogenesis. METHODS: We calculated the associations of BIN1 loci with these markers at baseline and follow-up in multiple linear models in 812 ADNI subjects. RESULTS: BIN1 loci were significantly associated with the levels of T-tau (rs744373: pc = 0.047, rs13031703: pc = 0.042) and P-tau (rs744373: pc = 0.044, rs13031703: pc = 0.019), but not with Aβ in CSF test. BIN1 genotypes were strongly related to atrophy of hippocampus (rs7561528: pc = 0.011), CA1 (rs1469980: pc = 0.029) and parahippocampus (rs72838284, pc = 0.017) on MRI, and to glucose metabolism on FDG-PET, but not to Aβ deposition on AV45-PET imaging. Furthermore, haplotype and subgroup analysis confirmed these significant findings. In addition, the loci associated with these markers were also identified to influence the risk for AD in the meta-analysis of 74 046 European individuals. CONCLUSION: This study supported that BIN1 contributes to the risk of AD by altering neural degeneration (abnormal tau, brain atrophy and glucose metabolism) but not Aβ pathology.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Databases, Factual; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Glucose; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Degeneration; Nuclear Proteins; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Risk; tau Proteins; Tumor Suppressor Proteins

Capillary amyloid-β protein deposition in a population-based study (Vantaa 85+). - Mäkelä, Mira; Paetau, Anders; Polvikoski, Tuomo; Myllykangas, Liisa; Tanskanen, Maarit (J Alzheimers Dis, 2016)
BACKGROUND: Capillary amyloid-β (capAβ) deposition in the cerebral cortex is the neuropathological feature providing the basis for categorizing cerebral amyloid angiopathy (CAA) into two distinct types, CAA-Type1 with capAβ and CAA-Type2 without capAβ. OBJECTIVE: We investigated the neuropathological and clinical characteristics of capAβ deposition in a prospective population-based study. METHODS: Vantaa 85+ includes 601 individuals aged ≥85 years, of which 300 were studied clinically and neuropathologically. 278 subjects were analyzed for the apolipoprotein E (APOE) genotype. The diagnosis of capAβ was determined using immunohistochemistry against Aβ, and of CAA using Congo red confirmed by Aβ immunohistochemistry, both analyzed in six brain areas. The severity of capAβ was graded semi-quantitatively, and the severity of CAA was based on the percentage of affected vessels. Alzheimer's disease (AD)-type neuropathology (CERAD score and Braak stage) was analyzed using standard methods. RESULTS: CAA-Type1 was present in 86/300, CAA-Type2 in 135/300, and 79/300 had no CAA. CapAβ was most frequent in the occipital lobe (79/86). CAA-Type1 was associated with the severity of CAA (p <  0.001), dementia (p <  0.001), severe AD-type neuropathology (p-value 0.09 for CERAD C and 0.017 for Braak stages V-VI), and APOE ɛ4 allele carrier status (p <  0.001). CONCLUSIONS: This population-based study confirmed the presence of distinct CAA-Type1 and its association with the severity of CAA, severe AD-type neuropathology, and the APOE ɛ4 carrier status. Both the severity and localization of the deposition seemed to determine the clinical significance of capAβ.
Keywords: Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Autopsy; Capillaries; Cerebral Amyloid Angiopathy; Female; Finland; Genotype; Humans; Immunohistochemistry; Logistic Models; Male; Multivariate Analysis; Occipital Lobe; Prospective Studies; Severity of Illness Index

Cerebral Glucose Metabolism is Associated with Verbal but not Visual Memory Performance in Community-Dwelling Older Adults. - Gardener, Samantha L; Sohrabi, Hamid R; Shen, Kai-Kai; Rainey-Smith, Stephanie R; Weinborn, Michael; Bates, Kristyn A; Shah, Tejal; Foster, Jonathan K; Lenzo, Nat; Salvado, Olivier; Laske, Christoph; Laws, Simon M; et al. (J Alzheimers Dis, 2016)
Increasing evidence suggests that Alzheimer's disease (AD) sufferers show region-specific reductions in cerebral glucose metabolism, as measured by [18F]-fluoro-2-deoxyglucose positron emission tomography (18F-FDG PET). We investigated preclinical disease stage by cross-sectionally examining the association between global cognition, verbal and visual memory, and 18F-FDG PET standardized uptake value ratio (SUVR) in 43 healthy control individuals, subsequently focusing on differences between subjective memory complainers and non-memory complainers. The 18F-FDG PET regions of interest investigated include the hippocampus, amygdala, posterior cingulate, superior parietal, entorhinal cortices, frontal cortex, temporal cortex, and inferior parietal region. In the cohort as a whole, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in both the left hippocampus and right amygdala. There were no associations observed between global cognition, delayed recall in logical memory, or visual reproduction and 18F-FDG PET SUVR. Following stratification of the cohort into subjective memory complainers and non-complainers, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in the right amygdala in those with subjective memory complaints. There were no significant associations observed in non-memory complainers between 18F-FDG PET SUVR in regions of interest and cognitive performance. We observed subjective memory complaint-specific associations between 18F-FDG PET SUVR and immediate verbal memory performance in our cohort, however found no associations between delayed recall of verbal memory performance or visual memory performance. It is here argued that the neural mechanisms underlying verbal and visual memory performance may in fact differ in their pathways, and the characteristic reduction of 18F-FDG PET SUVR observed in this and previous studies likely reflects the pathophysiological changes in specific brain regions that occur in preclinical AD.

Cerebrospinal Fluid Alzheimer's Disease Biomarkers Across the Spectrum of Lewy Body Diseases: Results from a Large Multicenter Cohort. - van Steenoven, Inger; Aarsland, Dag; Weintraub, Daniel; Londos, Elisabet; Blanc, Frédéric; van der Flier, Wiesje M; Teunissen, Charlotte E; Mollenhauer, Brit; Fladby, Tormod; Kramberger, Milica G; Bonanni, Laura; Lemstra, Afina W (J Alzheimers Dis, 2016)
BACKGROUND: Concomitant Alzheimer's disease (AD) pathology is observed in Lewy body diseases (LBD), but the clinical impact is unknown. Only a few biomarker studies in LBD exist and have included small cohorts from single centers. OBJECTIVE: We aimed to evaluate the prevalence of abnormal cerebrospinal fluid (CSF) AD biomarkers across the spectrum of LBD in a large multicenter cohort and to assess whether an AD biomarker profile was associated with demographic and clinical differences in dementia with Lewy bodies (DLB). METHODS: We included 375 DLB patients, 164 Parkinson's disease (PD) patients without dementia, and 55 PD patients with dementia (PDD) from 10 centers. CSF amyloid-beta42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau) values were dichotomized as abnormal or normal according to locally available cut-off values. A CSF AD profile was defined as abnormal Aβ42 combined with abnormal t-tau and/or p-tau. RESULTS: A substantial proportion of DLB patients had abnormal values for CSF Aβ42, t-tau, and p-tau, while abnormal values were uncommon in PD without dementia. Patients with PDD had values in between. A CSF AD profile was observed in 25% of DLB patients, compared with only 9% of PDD and 3% of PD without dementia. Within DLB, patients with a CSF AD profile were older, more often female, performed worse on the Mini-Mental State Examination, and had shorter disease duration compared with patients with normal CSF. CONCLUSION: A CSF AD profile is more common in DLB compared with PDD and PD, and is associated with more severe cognitive impairment in DLB.

Cerebrospinal Fluid Alzheimer's Disease Biomarkers in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Wacongne, Anne; Ayrignac, Xavier; Charif, Mahmoud; Fourcade, Genevieve; Azakri, Souhayla; Le Floch, Anne; Bouly, Stephane; Marelli, Cecilia; Arquizan, Caroline; Hirtz, Christophe; Gabelle, Audrey; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Decreased cerebrospinal fluid (CSF) amyloid-β 1-40 (Aβ40) and amyloid-β 1-42 (Aβ42) and increased total and phosphorylated tau (t-tau, p-tau) concentrations have been described in cerebral amyloid angiopathy (CAA). OBJECTIVE: Our aim was to analyze these biomarkers in patients with CAA-related inflammation (CAA-I). METHODS: We prospectively recruited nine patients with acute phase CAA-I fulfilling Chung criteria. CSF was analyzed for t-tau, p-tau, Aβ42, and Aβ40. Data were compared to controls (n = 14), patients with Alzheimer's disease (AD, n = 42), CAA (n = 10), and primary angiitis of the central nervous system (PACNS, n = 3). RESULTS: For the CAA-I group, statistically significant differences were: lower Aβ42 (p = 0.00053) compared to the control group; lower t-tau (p = 0.018), p-tau (p <  0.001), and Aβ40 (p <  0.001) compared to AD; lower Aβ42 (p = 0.027) compared to CAA; lower Aβ42 (p = 0.012) compared to PACNS. Nearly significantly lower Aβ40 (p = 0.051) and higher t-tau (p = 0.051) were seen in CAA-I compared to controls. CONCLUSION: CSF biomarkers profile similar to that of CAA was observed in CAA-I (with even lower levels of Aβ42 compared to CAA). Based on our findings, high p-tau seems more specific for AD, whereas low Aβ42 differentiates CAA-I from CAA, PACNS, and controls, and low Aβ40 differentiates CAA-I from AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Retrospective Studies; tau Proteins

Cerebrospinal Fluid Alzheimer's Disease Biomarkers in Isolated Supratentorial Cortical Superficial Siderosis. - Renard, Dimitri; Gabelle, Audrey; Hirtz, Christophe; Demattei, Christophe; Thouvenot, Eric; Lehmann, Sylvain (J Alzheimers Dis, 2016)
We evaluated cerebrospinal fluid amyloid-β 1-40 (Aβ40), amyloid-β 1-42 (Aβ42), total and phosphorylated-tau (t-tau and p-tau) in patients with symptomatic isolated cortical supratentorial superficial siderosis (SS), by prospectively recruiting ten patients with SS in the absence of pre-existing cognitive dysfunction, and comparing biomarkers with lobar hematoma cerebral amyloid angiopathy patients (LH-CAA, n = 13), Alzheimer's disease patients (AD, n = 42), and controls (n = 16). Compared to controls, SS patients showed statistically significant higher t-tau (p = 0.019) and lower Aβ42 (p = 0.0084). Compared to other groups, SS showed statistically significant lower t-tau, p-tau, and Aβ40 compared to AD (p = 0.0063, p = 0.0004, and p = 0022, respectively), and higher p-tau compared to LH-CAA (p = 0.012).

Cerebrospinal Fluid Biomarkers in Highly Exposed PM2.5 Urbanites: The Risk of Alzheimer's and Parkinson's Diseases in Young Mexico City Residents. - Calderón-Garcidueñas, Lilian; Avila-Ramírez, José; Calderón-Garcidueñas, Ana; González-Heredia, Tonatiuh; Acuña-Ayala, Hilda; Chao, Chih-Kai; Thompson, Charles; Ruiz-Ramos, Rubén; Cortés-González, Victor; Martínez-Martínez, Luz; García-Pérez, Mario Alberto; Reis, Jacques; et al. (J Alzheimers Dis, 2016)
Exposure to fine particulate matter (PM2.5) and ozone (O3) above US EPA standards is associated with Alzheimer's disease (AD) risk, while Mn toxicity induces parkinsonism. Mexico City Metropolitan Area (MCMA) children have pre- and postnatal sustained and high exposures to PM2.5, O3, polycyclic aromatic hydrocarbons, and metals. Young MCMA residents exhibit frontal tau hyperphosphorylation and amyloid-β (Aβ)1 - 42 diffuse plaques, and aggregated and hyperphosphorylated α-synuclein in olfactory nerves and key brainstem nuclei. We measured total prion protein (TPrP), total tau (T-tau), tau phosphorylated at threonine 181 (P-Tau), Aβ1-42, α-synuclein (t-α-syn and d-α-synuclein), BDNF, insulin, leptin, and/or inflammatory mediators, in 129 normal CSF samples from MCMA and clean air controls. Aβ1-42 and BDNF concentrations were significantly lower in MCMA children versus controls (p = 0.005 and 0.02, respectively). TPrP increased with cumulative PM2.5 up to 5 μg/m3 and then decreased, regardless of cumulative value or age (R2 = 0.56). TPrP strongly correlated with T-Tau and P-Tau, while d-α-synuclein showed a significant correlation with TNFα, IL10, and IL6 in MCMA children. Total synuclein showed an increment in childhood years related to cumulated PM2.5, followed by a decrease after age 12 years (R2 = 0.47), while d-α-synuclein exhibited a tendency to increase with cumulated PM2.5 (R2 = 0.30). CSF Aβ1-42, BDNF, α-synuclein, and TPrP changes are evolving in young MCMA urbanites historically showing underperformance in cognitive processes, odor identification deficits, downregulation of frontal cellular PrP, and neuropathological AD and PD hallmarks. Neuroprotection of young MCMA residents ought to be a public health priority.

Changes in Brain Volume with Bapineuzumab in Mild to Moderate Alzheimer's Disease. - Novak, Gerald; Fox, Nick; Clegg, Shona; Nielsen, Casper; Einstein, Steven; Lu, Yuan; Tudor, Iulia Cristina; Gregg, Keith; Di, Jianing; Collins, Peter; Wyman, Bradley T; Yuen, Eric; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Bapineuzumab, an anti-amyloid-β monoclonal antibody, was evaluated in two placebo-controlled trials in APOE*ɛ4 carriers and noncarriers, respectively, with Alzheimer's disease. OBJECTIVES: A volumetric magnetic resonance imaging substudy was performed to determine if bapineuzumab altered brain volume rate of change. METHODS: Bapineuzumab dosages included 0.5 mg/kg in carriers and 0.5 or 1.0 mg/kg in noncarriers, every 13 weeks for 78 weeks. Volumetric outcomes included annualized brain, ventricular, and mean hippocampal boundary shift integrals (BBSI; VBSI; HBSI) up to Week 71. Treatment differences were estimated using mixed models for repeated measures. RESULTS: For BBSI and HBSI, there were no significant treatment-related differences within either study, but, compared to pooled carriers and noncarriers receiving placebo, noncarriers receiving1.0 mg/kg bapineuzumab had greater increases in these measures. Bapineuzumab-treated patients showed significantly greater VBSI rates compared with placebo for 0.5 mg/kg in carriers and 1.0 mg/kg (but not 0.5 mg/kg) in noncarriers. CONCLUSIONS: Bapineuzumab produced an increase in ventricular volume compared with placebo. Etiology for this increase is unclear but may be related to amyloid-β clearance or its consequences.
Keywords: Aged; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Apolipoprotein E4; Brain; Double-Blind Method; Female; Heterozygote; Humans; Least-Squares Analysis; Magnetic Resonance Imaging; Male; Nootropic Agents; Organ Size; Severity of Illness Index; Treatment Outcome

Characterization of Amyloid-β Deposits in Bovine Brains. - Vallino Costassa, Elena; Fiorini, Michele; Zanusso, Gianluigi; Peletto, Simone; Acutis, Pierluigi; Baioni, Elisa; Maurella, Cristiana; Tagliavini, Fabrizio; Catania, Marcella; Gallo, Marina; Faro, Monica Lo; Chieppa, Maria Novella; et al. (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) deposits are seen in aged individuals of many mammalian species that possess the same aminoacid sequence as humans. This study describes Aβ deposition in 102 clinically characterized cattle brains from animals aged 0 to 20 years. Extracellular and intracellular Aβ deposition was detected with 4G8 antibody in the cortex, hippocampus, and cerebellum. X-34 staining failed to stain Aβ deposits, indicating the non β-pleated nature of these deposits. Western blot analysis and surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF) mass spectrometry revealed in Tris, Triton, and formic acid fractions the presence of different Aβ peptides, characterized mainly by C-terminally truncated forms. Exploration of the genetic variability of APOE, PSEN1, and PSEN2 genes involved in Alzheimer's disease pathogenesis revealed several previously unreported polymorphisms. This study demonstrates certain similarities between Aβ deposition patterns exhibited in cattle brains and those in the human brain in early stages of aging. Furthermore, the identification of the same Aβ peptides reported in humans, but unable to form aggregates, supports the hypothesis that cattle may be protected against amyloid plaque formation.
Keywords: Aging; Amyloid beta-Peptides; Animals; Apolipoproteins E; Blotting, Western; Brain; Cattle; Extracellular Space; Gene Frequency; Genotyping Techniques; Glial Fibrillary Acidic Protein; Immunohistochemistry; Intracellular Space; Neuroglia; Neurons; Polymorphism, Genetic; Presenilin-1; Presenilin-2; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization

Cholesteryl Ester Transfer Protein Intimately Involved in Dyslipidemia-Related Susceptibility to Cognitive Deficits in Type 2 Diabetic Patients. - Sun, Jie; Cai, Rongrong; Huang, Rong; Wang, Pin; Tian, Sai; Sun, Haixia; Xia, Wenqing; Wang, Shaohua (J Alzheimers Dis, 2016)
BACKGROUND: Cholesteryl ester transfer protein (CETP) is involved in diabetic dyslipidemia. OBJECTIVE: We aim to test the hypothesis that CETP might be of importance in mediating dyslipidemia-related susceptibility to cognitive deficits in diabetic patients. METHODS: We recruited 190 type 2 diabetic patients and divided them into two groups according to the Montreal Cognitive Assessment (MoCA) score. The association between CETP and cognitive decline was analyzed with logistic regression and stratification. RESULTS: There were 110 diabetic patients with mild cognition impairment (MCI) and 80 healthy cognition subjects as controls. Dyslipidemia is more common among diabetic patients with MCI; they had a significant increase of serum CETP concentrations, which was negatively correlated with MoCA (r = -0.638; p < 0.001). Negative correlations were also found between the serum CETP concentration with the Auditory Verbal Learning Test (r = -0.266; p = 0.008), indicating memory deficit. Logistic regression analysis revealed that CETP concentration was an independent factor of diabetic MCI (p < 0.001). Further stratification study showed that high serum levels of CETP was an independent risk factor of MCI in diabetic patients with a low density lipoproteins level ≥2.59 mmol/L, or high density lipoproteins level ≤1.0 mmol/L for men and ≤1.3 mmol/L for women, or TG level ≥1.7 mmol/L, after adjusting for age, sex, education, and glucose control (all ps < 0.05). CONCLUSIONS: CETP was intimately involved in dyslipidemia-related susceptibility to cognitive decline, especially memory function in type 2 diabetic patients.

Chronic Traumatic Encephalopathy Presenting as Alzheimer's Disease in a Retired Soccer Player. - Grinberg, Lea T; Anghinah, Renato; Nascimento, Camila Fernandes; Amaro, Edson; Leite, Renata P; Martin, Maria da Graça M; Naslavsky, Michel S; Takada, Leonel T; Filho, Wilson Jacob; Pasqualucci, Carlos A; Nitrini, Ricardo (J Alzheimers Dis, 2016)
The relationship between soccer and chronic traumatic encephalopathy (CTE) is not well established. We report clinicopathological correlations in an 83-year-old retired center-back soccer player, with no history of concussion, manifesting typical Alzheimer-type dementia. Examination revealed mixed pathology including widespread CTE, moderate Alzheimer's disease, hippocampal sclerosis, and TDP-43 proteinopathy. This case adds to a few CTE cases described in soccer players. Furthermore, it corroborates that CTE may present clinically as typical Alzheimer-type dementia. Further studies investigating the extent to which soccer is a risk for CTE are needed.

Cigarette Smoke-Induced Alterations in Frontal White Matter Lipid Profiles Demonstrated by MALDI-Imaging Mass Spectrometry: Relevance to Alzheimer's Disease. - Nunez, Kavin; Kay, Jared; Krotow, Alexander; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis has shown that smokers have significantly increased risks for Alzheimer's disease (AD), and neuroimaging studies showed that smoking alters white matter (WM) structural integrity. OBJECTIVE: Herein, we characterize the effects of cigarette smoke (CS) exposures and withdrawal on WM myelin lipid composition using matrix assisted laser desorption and ionization-imaging mass spectrometry (MALDI-IMS). METHODS: Young adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). Frontal lobe WM was examined for indices of lipid and protein oxidation and lipid profile alterations by MALDI-IMS. Lipid ions were identified by MS/MS with the LIPID MAPS prediction tools database. Inter-group comparisons were made using principal component analysis and R-generated heatmap. RESULTS: CS increased lipid and protein adducts such that higher levels were present in CS8 compared with CS4 samples. CS8 + R reversed CS8 effects and normalized the levels of oxidative stress. MALDI-IMS demonstrated striking CS-associated alterations in WM lipid profiles characterized by either reductions or increases in phospholipids (phosphatidylinositol, phosphatidylserine, phosphatidylcholine, or phosphatidylethanolamine) and sphingolipids (sulfatides), and partial reversal of CS's inhibitory effects with recovery. The heatmap hierarchical dendrogram and PCA distinguished CS exposure, duration, and withdrawal effects on WM lipid profiles. CONCLUSION: CS-mediated WM degeneration is associated with lipid peroxidation, protein oxidative injury, and alterations in myelin lipid composition, including shifts in phospholipids and sphingolipids needed for membrane integrity, plasticity, and intracellular signaling. Future goals are to delineate WM abnormalities in AD using MALDI-IMS, and couple the findings with MRI-mass spectroscopy to improve in vivo diagnostics and early detection of brain biochemical responses to treatment.
Keywords: Aldehydes; Analysis of Variance; Animals; Dinoprost; Disease Models, Animal; Enzyme-Linked Immunosorbent Assay; Frontal Lobe; Lipid Metabolism; Male; Mice; Phospholipids; Principal Component Analysis; Protein Carbonylation; Smoking; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Substance Withdrawal Syndrome; White Matter

Circadian Disruption Reveals a Correlation of an Oxidative GSH/GSSG Redox Shift with Learning and Impaired Memory in an Alzheimer's Disease Mouse Model. - LeVault, Kelsey R; Tischkau, Shelley A; Brewer, Gregory J (J Alzheimers Dis, 2016)
It is unclear whether pre-symptomatic Alzheimer's disease (AD) causes circadian disruption or whether circadian disruption accelerates AD pathogenesis. In order to examine the sensitivity of learning and memory to circadian disruption, we altered normal lighting phases by an 8 h shortening of the dark period every 3 days (jet lag) in the APPSwDI NOS2-/- model of AD (AD-Tg) at a young age (4-5 months), when memory is not yet affected compared to non-transgenic (non-Tg) mice. Analysis of activity in 12-12 h lighting or constant darkness showed only minor differences between AD-Tg and non-Tg mice. Jet lag greatly reduced activity in both genotypes during the normal dark time. Learning on the Morris water maze was significantly impaired only in the AD-Tg mice exposed to jet lag. However, memory 3 days after training was impaired in both genotypes. Jet lag caused a decrease of glutathione (GSH) levels that tended to be more pronounced in AD-Tg than in non-Tg brains and an associated increase in NADH levels in both genotypes. Lower brain GSH levels after jet lag correlated with poor performance on the maze. These data indicate that the combination of the environmental stress of circadian disruption together with latent stress of the mutant amyloid and NOS2 knockout contributes to cognitive deficits that correlate with lower GSH levels.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Brain; Chromatography, High Pressure Liquid; Chronobiology Disorders; Disease Models, Animal; Gene Expression Regulation; Glutathione; Glutathione Disulfide; Humans; Memory Disorders; Mice; Mice, Transgenic; Mutation; NADP; Nitric Oxide Synthase Type II; Oxidation-Reduction

Circulating microRNAs as Biomarkers of Alzheimer's Disease: A Systematic Review. - Wu, Helen Zong Ying; Ong, Kwok Leung; Seeher, Katrin; Armstrong, Nicola J; Thalamuthu, Anbupalam; Brodaty, Henry; Sachdev, Perminder; Mather, Karen (J Alzheimers Dis, 2016)
BACKGROUND: In recent years, microRNAs (miRNA), a class of non-coding RNA known to regulate protein expression post-transcriptionally, have been recognized as novel biomarkers of diseases. OBJECTIVE: In this systematic review, we identify miRNAs that are differentially expressed in Alzheimer's disease (AD) and/or mild cognitive impairment (MCI) and evaluate their accuracy as potential blood biomarkers. METHODS: Eligible studies of miRNAs in peripheral blood distinguishing patients with AD or MCI from cognitively normal controls were identified through standardized search strategies in Medline, PubMed, and Embase. MiRNAs that were differentially expressed were identified and where available their sensitivity and specificity for AD or MCI extracted from the retrieved studies. RESULTS: Eighteen studies investigated the diagnostic value of miRNAs as peripheral biomarkers of AD/MCI. Twenty miRNAs were significantly upregulated and 32 miRNAs downregulated in AD compared to controls in ten AD studies. Nine miRNAs were consistently dysregulated in more than one study. Of the 8 MCI studies, only one miRNA, miR-132, was consistently upregulated in three independent studies. Of the studies that reported diagnostic accuracy data, the majority of miRNA panels and individual miRNAs had a sensitivity and specificity greater than 0.75. CONCLUSION: Individual studies suggest that miRNAs can differentiate patients with AD/MCI from cognitively normal controls with modest accuracy. However, the literature is constrained by methodological differences between studies, with few studies assessing the same miRNAs. To become potential biomarkers for AD, further studies with standardized study designs for replication and validation are required. Results from this review may help researchers select candidate miRNAs for further investigation.
Keywords: Alzheimer Disease; Biomarkers; Databases, Bibliographic; Humans; MicroRNAs

Clinical Dementia Rating Scale Detects White Matter Changes in Older Adults at Risk for Alzheimer's Disease. - Chang, Yu-Ling; Yen, Yu-Shiuan; Chen, Ta-Fu; Yan, Sui-Hing; Tseng, Wen-Yih Isaac (J Alzheimers Dis, 2016)
This study investigated the putative changes in regional gray matter and cingulum bundle segments in mild cognitive impairment (MCI) by using two diagnostic criteria. Participants comprised 50 older adults with MCI and 22 healthy older controls (HC). The older adults with MCI were further divided into two groups defined by a global Clinical Dementia Rating (CDR) score of 0.5 and with (the CDR/NPT MCI group) or without (the CDR MCI group) objective cognitive impairments determined using neuropsychological tests (NPTs). Comparable regional gray matter integrity was observed among the three groups. However, the integrity of the right inferior segment of the cingulum bundle in the two MCI groups was more reduced than that in the HC group, and the CDR/NPT MCI group exhibited additional disruption in the left inferior cingulum bundle. The results also demonstrated that neuropsychological measures have greater predictive value for changes in white matter beyond the contribution of an informant-based instrument alone. Overall, the findings confirm the utility of informant-based assessment in detecting microstructural brain changes in high-risk older adults, even before objective cognitive impairment is evident. The findings also suggest that combining the neuropsychological measures with the informant-based assessment provided the greatest predictive value in assessing white matter disruption. The essential role of the white matter measurement as a biomarker for detecting individuals at a high risk of developing dementia was highlighted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognition Disorders; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory; Middle Aged; Neuropsychological Tests; Risk Factors; White Matter

Cognitive Profile and its Association with Neuroimaging Markers of Non-Demented Cerebral Amyloid Angiopathy Patients in a Stroke Unit. - Xiong, Li; Davidsdottir, Sigurros; Reijmer, Yael D; Shoamanesh, Ashkan; Roongpiboonsopit, Duangnapa; Thanprasertsuk, Sekh; Martinez-Ramirez, Sergi; Charidimou, Andreas; Ayres, Alison M; Fotiadis, Panagiotis; Gurol, Edip; Blacker, Deborah L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Cerebral amyloid angiopathy (CAA) is increasingly recognized as a cause of cognitive impairment in the elderly, but the cognitive profile in patients with the disease has not been well characterized. OBJECTIVE: To characterize the neuropsychological profile of CAA patients without dementia and to determine the association between cognitive performance in different domains and neuroimaging lesions characteristic of CAA. METHODS: Fifty-eight non-demented CAA patients were compared to 138 cognitively normal subjects using a standard neuropsychological test battery. Total brain volume (TBV), white matter hyperintensities, number of lobar cerebral microbleeds, hippocampal volume, and cortical superficial siderosis in all CAA patients were assessed. The association between these neuroimaging markers and neuropsychological performance in different cognitive domains in the CAA group were analyzed. RESULTS: Patients with CAA had significantly worse performance on all individual neuropsychological domains tested, when compared to the cognitive normal group. The cognitive decline of CAA patients was most noticeable in tests for processing speed with a Z score of -1.92±1.56 (mean±SD), then followed by executive function (-0.93±1.01), episodic memory (-0.87±1.29), semantic fluency (-0.73±1.06), and attention (-0.42±0.98). TBV of the CAA patients was correlated with processing speed (β= 0.335, p = 0.03) and executive function (β= 0.394, p = 0.01). CONCLUSIONS: Non-demented patients with CAA had cognitive deficits in multiple areas. Lower TBV was related to slower processing speed and worse executive function.
Keywords: Aged; Atrophy; Brain; Cerebral Amyloid Angiopathy; Cognition; Cognition Disorders; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Stroke

Cognitive Reserve in Alzheimer's Dementia: Diagnostic Accuracy of a Testing-the-Limits Paradigm. - Küster, Olivia C; Kösel, Jonas; Spohn, Stephanie; Schurig, Niklas; Tumani, Hayrettin; von Arnim, Christine A F; Uttner, Ingo (J Alzheimers Dis, 2016)
Individuals with higher cognitive reserve are more able to cope with pathological brain alterations, potentially due to the application of more efficient cognitive strategies. The extent to which an individual's cognitive performance can be increased by advantageous conditions differs substantially between patients with Alzheimer's dementia (AD) and healthy older adults and can be assessed with the Testing-the-Limits (TtL) approach. Thus, TtL has been proposed as a tool for the early diagnosis of AD. Here, we report the diagnostic accuracy of a memory TtL paradigm to discriminate between AD patients and controls. The TtL paradigm was administered to 57 patients with clinically diagnosed AD and 94 controls. It consisted of a pre-test condition, representing baseline cognitive performance, the presentation of an encoding strategy, and two subsequent post-test conditions, representing learning potential. Receiver operating characteristic (ROC) curves were analyzed for each condition in order to receive optimal cutoff points along with their sensitivity and specificity and to compare the diagnostic accuracy of the conditions. Differentiation between AD patients and controls, indicated by the area under the ROC curve, increased significantly for the TtL post-test and total error scores compared to the pre-test score. The combined error score in the two post-tests could differentiate between AD patients and controls with a sensitivity of 0.93 and a specificity of 0.80. The presented approach can be carried out in 25 minutes and thus constitutes a time- and cost-effective way to diagnose AD with high accuracy.

Community-Dwelling People Screened Positive for Dementia in Primary Care: A Comprehensive, Multivariate Descriptive Analysis Using Data from the DelpHi-Study. - Thyrian, Jochen René; Eichler, Tilly; Michalowsky, Bernhard; Wucherer, Diana; Reimann, Melanie; Hertel, Johannes; Richter, Steffen; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: Efficient help and care for people with dementia (PWD) is dependent on knowledge about PWD in primary care. OBJECTIVE: This analysis comprehensively describes community-dwelling PWD in primary care with respect to various dementia care specific variables. METHODS: The analyses are based on baseline data of the ongoing general practitioner-based, randomized, controlled intervention trial DelpHi-MV (Dementia: life- and person-centered help). 6,838 patients were screened for dementia in 136 GP practices; 17.1% were screened positive, 54.4% of those agreed to participate and data could be assessed in n = 516 subjects. We assessed age, sex, living situation, cognitive status, functional status, level of impairment, comorbidities, formal diagnosis of dementia, depression, neuropsychiatric symptoms, quality of life, utilization of medical support, and pharmacological therapy. RESULTS: Concerning clinical-, dementia-, and health-related variables, the sample under examination was on average mildly cognitively and functionally impaired (MMSE, m = 22.2; BADL, m = 3.7). A level of care was assigned in 38.0%. Depression was identified in 15.4% and other frequent comorbidities were high blood pressure (83.3%), coronary heart diseases (37.1%), cerebrovascular diseases (22.3%), among others. In 48.6%, neuropsychiatric symptoms were present in a clinically relevant severity. Pharmacological treatment with antidementia medication was received by 25.8% and antidepressant medication by 14.0%. Utilization of services was generally low. CONCLUSION: The comprehensive description of people screened positive for dementia in primary care reveals a complex and unique population of patients. They are considerably underdiagnosed and in their majority mildly to moderately affected. More in-depth analyses are needed to study relations, associations and interactions between different variables.

Comorbid Mild Cognitive Impairment and Depressive Symptoms Predict Future Dementia in Community Older Adults: A 24-Month Follow-Up Longitudinal Study. - Makizako, Hyuma; Shimada, Hiroyuki; Doi, Takehiko; Tsutsumimoto, Kota; Hotta, Ryo; Nakakubo, Sho; Makino, Keitaro; Suzuki, Takao (J Alzheimers Dis, 2016)
BACKGROUND: Older adults with mild cognitive impairment (MCI) are non-demented, but demonstrate cognitive dysfunction, and have significantly higher risk of progressing to dementia. A better understanding of more sensitive risk factors, such as combination of cognitive and psychological status, for progression of MCI to dementia may be crucial for prevention of development of dementia. OBJECTIVE: To examine MCI, depressive symptoms, and comorbid MCI and depressive symptoms as risk factors for development of dementia. METHODS: A total of 3,663 community-dwelling older people were included in this prospective longitudinal study. MCI was determined by age- and education-adjusted objective cognitive impairment using computerized comprehensive cognitive measures including memory, attention/executive function, and processing speed. Depressive symptoms were measured using the 15-item Geriatric Depression Scale (GDS) and defined by a GDS score of 6 or more. RESULTS: During the 24-month follow-up period, 72 participants (2.0%) developed dementia. Baseline MCI was significantly associated with an increased risk of incident dementia (hazard ratio [HR], 3.2; 95% confidence interval [CI], 1.8-5.5) but depressive symptoms were not (2.0; 1.0-4.2) after adjusting for age, sex, education, prescribed medications, and walking speed. Participants with comorbid MCI and depressive symptoms at baseline had a higher risk of developing dementia (HR, 4.8; 2.3-10.5). CONCLUSION: Although MCI and depressive symptoms may be associated with increased risk for incident dementia independently, comorbid MCI and depressive symptoms have a significantly greater impact on dementia development among community-dwelling older adults.

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics. - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples. OBJECTIVE: To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers. METHODS: Three matrices were validated in this study: (A) human pooled CSF, (B) Aβ peptides spiked into human prediluted plasma, and (C) Aβ peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study. RESULTS: NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects. CONCLUSION: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
Keywords: Amyloid beta-Peptides; Animals; Anti-Bacterial Agents; Biomarkers; Cattle; Clinical Chemistry Tests; Dementia; Humans; Peptide Fragments; Quality Control; Reference Standards; Serum Albumin, Bovine; Sodium Azide; tau Proteins; Time Factors; Tissue Preservation

Connected Language in Late Middle-Aged Adults at Risk for Alzheimer's Disease. - Mueller, Kimberly Diggle; Koscik, Rebecca L; Turkstra, Lyn S; Riedeman, Sarah K; LaRue, Asenath; Clark, Lindsay R; Hermann, Bruce; Sager, Mark A; Johnson, Sterling C (J Alzheimers Dis, 2016)
Connected language is often impaired among people with Alzheimer's disease (AD), yet little is known about when language difficulties first emerge on the path to a clinical diagnosis. The objective of this study was to determine whether individuals with psychometric (preclinical) evidence of amnestic mild cognitive impairment (pMCI) showed deficits in connected language measures. Participants were 39 pMCI and 39 cognitively healthy (CH) adults drawn from the Wisconsin Registry for Alzheimer's Prevention, who were matched for age, literacy, and sex. Participants completed a connected language task in which they described the Cookie Theft picture from the Boston Diagnostic Aphasia Examination. Language samples were analyzed across three language domains: content, syntactic complexity, and speech fluency. Paired t-tests were used to compare CH and pMCI groups on all variables, and Cohen's d effect sizes were calculated for each comparison. The CH and pMCI groups differed significantly on measures of content (e.g., CH group produced more semantic units, more unique words and had larger idea density, on average, than the pMCI group). The picture description findings are consistent with previous retrospective studies showing semantic language differences in adults with autopsy-confirmed AD. Given that these comparisons are between cognitively healthy and pMCI individuals (before a clinical MCI diagnosis), these findings may represent subtle language difficulty in spontaneous speech, and may be predictive of larger language changes over time.

Consequences of Anosognosia on the Cost of Caregivers' Care in Alzheimer's Disease. - Turró-Garriga, Oriol; Garre-Olmo, Josep; Reñé-Ramírez, Ramón; Calvó-Perxas, Laia; Gascón-Bayarri, Jordi; Conde-Sala, Josep-Lluís (J Alzheimers Dis, 2016)
BACKGROUND: Anosognosia is common in patients with Alzheimer's disease (AD) and it is frequently related to an increase in time of care demand. OBJECTIVE: The aim of the study was to examine the effect of anosognosia on the total costs of informal care in patients with AD. METHODS: This was a prospective longitudinal study with community-dwelling AD patients. Anosognosia, time of informal care, and the use of support services (e.g., day care centers) were recorded at baseline and after 24 months. The cost of informal caregiving was calculated as 'market price'. RESULTS: At baseline, the prevalence of anosognosia was 54.3% (n = 221), and 43.9% were classified as mild-AD. The average time of care was 5 h/day±2.4 (IADL: 1.3 h/day±1.4 and BADL: 3.6 h/day±1.5). Thirty percent of the patients used home care services, and 25.1% attended a day care center. Patients with anosognosia received more time of care and were more likely to use support services than did their no-anosognosia peers, including institutionalization. The mean cost of support services was 490.4€ /month (SD = 413.1€; range = 25-2,212.38€), while the overall cost of care (support services plus informal care) was 1,787€ /month (SD = 972.4€), ranging from 834.1€ in mild-AD without anosognosia patients, to 2,424.8€ in severe-AD with incident anosognosia patients. CONCLUSIONS: Anosognosia was associated with an increased number of hours of informal care, and a greater use of support services, regardless of the severity of the dementia, which lead to an increase of the total family-care costs.

Contribution of the Cholinergic System to Verbal Memory Performance in Mild Cognitive Impairment. - Peter, Jessica; Lahr, Jacob; Minkova, Lora; Lauer, Eliza; Grothe, Michel J; Teipel, Stefan; Köstering, Lena; Kaller, Christoph P; Heimbach, Bernhard; Hüll, Michael; Normann, Claus; Nissen, Christoph; et al. (J Alzheimers Dis, 2016)
Acetylcholine is critically involved in modulating learning and memory function, which both decline in neurodegeneration. It remains unclear to what extent structural and functional changes in the cholinergic system contribute to episodic memory dysfunction in mild cognitive impairment (MCI), in addition to hippocampal degeneration. A better understanding is critical, given that the cholinergic system is the main target of current symptomatic treatment in mild to moderate Alzheimer's disease. We simultaneously assessed the structural and functional integrity of the cholinergic system in 20 patients with MCI and 20 matched healthy controls and examined their effect on verbal episodic memory via multivariate regression analyses. Mediating effects of either cholinergic function or hippocampal volume on the relationship between cholinergic structure and episodic memory were computed. In MCI, a less intact structure and function of the cholinergic system was found. A smaller cholinergic structure was significantly correlated with a functionally more active cholinergic system in patients, but not in controls. This association was not modulated by age or disease severity, arguing against compensational processes. Further analyses indicated that neither functional nor structural changes in the cholinergic system influence verbal episodic memory at the MCI stage. In fact, those associations were fully mediated by hippocampal volume. Although the cholinergic system is structurally and functionally altered in MCI, episodic memory dysfunction results primarily from hippocampal neurodegeneration, which may explain the inefficiency of cholinergic treatment at this disease stage.

Course and Determinants of Anosognosia in Alzheimer's Disease: A 12-Month Follow-up. - Turró-Garriga, Oriol; Garre-Olmo, Josep; Calvó-Perxas, Laia; Reñé-Ramírez, Ramón; Gascón-Bayarri, Jordi; Conde-Sala, Josep Lluís (J Alzheimers Dis, 2016)
Anosognosia in Alzheimer's disease (AD) has been associated with greater cognitive impairment and more behavioural and psychological symptoms of dementia (BPSD). This study examines the incidence, persistence, and remission rates of anosognosia over a 12-month period, as well as the related risk factors. This was an observational 12-month prospective study. The longitudinal sample comprised 177 patients with mild or moderate AD, and their respective caregivers. Anosognosia was assessed using the Anosognosia Questionnaire in Dementia, and we also evaluated cognitive status (Mini-Mental State Examination), functional disability (Disability Assessment in Dementia), and the presence of BPSD (Neuropsychiatric Inventory). Multinomial logistic regression was used to determine the variables associated with the incidence, persistence and remission of anosognosia. The prevalence of anosognosia was 39.5% (95% CI = 32.1-47.1) at baseline. At 12 months, incidence was 38.3% (95% CI = 28.6-48.0), persistence was 80.0% (95% CI = 69.9-90.1) and remission was 20.0% (95% CI = 9.9-30.1). The regression model identified lower age, more education, and the presence of delusions as variables associated with incidence, and more education, lower instrumental DAD score, and disinhibition as variables associated with persistence. No variables were associated with remission (n = 14). The presence of anosognosia in AD patients is high. Education and certain neuropsychiatric symptoms may explain a greater and earlier incidence of anosognosia. However, anosognosia also increases with greater cognitive impairment and disease severity.
Keywords: Age Factors; Aged; Agnosia; Alzheimer Disease; Disability Evaluation; Disease Progression; Educational Status; Female; Follow-Up Studies; Humans; Incidence; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests; Prevalence; Prospective Studies; Risk Factors; Severity of Illness Index

Decreased Levels of VAMP2 and Monomeric Alpha-Synuclein Correlate with Duration of Dementia. - Vallortigara, Julie; Whitfield, David; Quelch, William; Alghamdi, Amani; Howlett, David; Hortobágyi, Tibor; Johnson, Mary; Attems, Johannes; O'Brien, John T; Thomas, Alan; Ballard, Clive G; Aarsland, Dag; et al. (J Alzheimers Dis, 2016)
Alpha-synuclein (α-syn) aggregations are the key pathological hallmark of dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), but are also frequently present in Alzheimer's disease (AD). Much remains unknown about the role of α-syn in the synapse and the wider role of synaptic dysfunction in these dementias. Changes in concentrations of key 'SNAP (Soluble N-ethylmaleimide Sensitive Factor Attachment Protein) Receptor' (SNARE) proteins as a consequence of alterations in the aggregation state of α-syn may contribute to synaptic dysfunction in patients with DLB, PDD, and AD and result in impaired cognition. We have studied a large cohort (n = 130) of autopsy confirmed DLB, PDD, AD, and control brains. Using semi-quantitative western blotting, we have demonstrated significant changes across the diagnostic groups of DLB, PDD, and AD in the SNARE and vesicle proteins syntaxin, Munc18, VAMP2, and monomeric α-syn in the prefrontal cortex, with a significant reduction of Munc18 in AD patients (p <  0.001). This correlated to the final MMSE score before death (p = 0.016). We also identified a significant negative correlation between the duration of dementia and the levels of the binding partners VAMP2 (p = 0.0004) and monomeric α-syn (p = 0.0002). Our findings may indicate that an upregulation of SNARE complex related proteins occurs in the early stages of disease as an attempt at compensating for failing synapses, prior to widespread deposition of pathological α-syn.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Amyloid beta-Peptides; Analysis of Variance; Cognition Disorders; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Regression Analysis; Synaptophysin; tau Proteins; Vesicle-Associated Membrane Protein 2

Depressive Symptoms and Small Hippocampal Volume Accelerate the Progression to Dementia from Mild Cognitive Impairment. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Chakravarty, M Mallar; Caravaggio, Fernando; Takeuchi, Hiroyoshi; Gerretsen, Philip; Iwata, Yusuke; Patel, Raihaan; Mulsant, Benoit H; Graff-Guerrero, Ariel (J Alzheimers Dis, 2016)
Previous studies have highlighted that decreased hippocampal volume, an early neural correlate of dementia, is commonly observed in patients with mild cognitive impairment (MCI). However, it is unclear whether neurodegenerative and resultant clinical trajectories are accelerated in MCI patients with concomitant depressive symptoms, leading to a faster conversion to dementia stages than those who are not depressed. No longitudinal study has investigated whether depressed amnestic MCI (DEP+aMCI) patients show an earlier onset of progression to dementia than non-depressed amnestic MCI (DEP-aMCI) patients and whether progressive hippocampal volume reductions are related in the conversion process. Using data from Alzheimer's Disease Neuroimaging Initiative, we examined 2-year follow-up data from 38 DEP+aMCI patients and 38 matched DEP-aMCI patients and compared their ages of conversion from aMCI to AD and trajectories of progressive hippocampal volume changes. DEP+ and DEP- patients were defined as having baseline Geriatric Depression Scale scores of 5 or above and 0, respectively. DEP+ converters showed earlier ages of conversion to dementia (p = 0.009) and greater left hippocampal volume loss than both DEP- converters and DEP+ non-converters over the 2-year period (p = 0.003, p = 0.001, respectively). These findings could not be explained by changes in total brain volume, differences in their clinical symptoms of dementia, daily functioning, or apolipoprotein E4 genotypes. No difference in conversion rate to dementia or progressive hippocampal volume change was found between DEP+ patients and DEP-patients, which suggested depressive symptoms themselves may not lead to progression of dementia from MCI. In conclusion, there is a synergistic effect of depressive symptoms and smaller left hippocampal volume in MCI patients that accelerates conversion to dementia.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dementia; Depression; Disease Progression; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Psychiatric Status Rating Scales

Detection of Striatal Amyloid Plaques with [18F]flutemetamol: Validation with Postmortem Histopathology. - Beach, Thomas G; Thal, Dietmar Rudolf; Zanette, Michelle; Smith, Adrian; Buckley, Christopher (J Alzheimers Dis, 2016)
Amyloid imaging is limited by an inconsistent relationship between cerebral cortex amyloid- β (Aβ) plaques and dementia. Autopsy studies suggest that Aβ plaques first appear in the cerebral cortex while subcortical plaques are present only later in the disease course. The presence of abundant plaques in both cortex and striatum is more strongly correlated with the presence of dementia than cortical Aβ plaques alone. Additionally, detection of striatal plaques may allow, for the first time, pathology-based clinical staging of AD. Striatal plaques are reportedly identifiable by amyloid imaging but the accuracy and reliability of striatal amyloid imaging has never been tested against postmortem histopathology. To determine this, we correlated the presence of histopathologically-demonstrated striatal Aβ deposits with a visually positive panel consensus decision of a positive [18F]flutemetamol striatal PET signal in 68 subjects that later came to autopsy. The sensitivity of [18F]flutemetamol PET striatal amyloid imaging, for several defined density levels of histological striatal Aβ deposits, ranged between 69% and 87% while the specificity ranged between 96% and 100%. Sensitivity increased with higher histological density thresholds while the reverse was found for specificity. In general, as compared with PET alone, PET with CT had slightly higher sensitivities but slightly lower specificities. In conclusion, amyloid imaging of the striatum with [18F]flutemetamol PET has reasonable accuracy for the detection of histologically-demonstrated striatal Aβ plaques when present at moderate or frequent densities. Amyloid imaging of the cerebral cortex and striatum together may allow for a more accurate clinicopathological diagnosis of AD and enable pathology-based clinical staging of AD.

Developing Cognitive Markers of Alzheimer's Disease for Primary Care: Implications for Behavioral and Global Prevention. - Levy, Boaz; Tsoy, Elena; Gable, Samuel (J Alzheimers Dis, 2016)
A comprehensive approach to the prevention of Alzheimer's disease (AD) warrants a synergy across multiple domains and procedures. Whereas the study of biological markers has mobilized major activity in the field, the development of cognitive markers is largely ignored, despite the unique advantages they may offer. Cognitive markers essentially assess the core clinical feature that biological markers intend to predict. In this respect, cognitive markers expand the foundation of preclinical diagnostics and disease staging in a manner that integrates both physiological and psychological factors. In addition, the cost-effective implementation of cognitive markers makes them remarkably conducive to community-wide screenings, and thereby a vital component of any global blueprint for prevention. Specifically, in the primary care setting, cognitive markers may provide effective gate keeping for more invasive, labor intensive, and expensive procedures. From this perspective, cognitive markers may provide the first step for identifying preclinical treatment recipients in general public. Moreover, the detection of preclinical decline via cognitive markers can increase awareness of AD risk and the motivation for making protective lifestyle changes. The behavioral approach might be expedient for prevention in light of the compelling evidence of lifestyle amelioration of AD risk. In an integrative view, incorporating cognitive markers to primary care may facilitate a synergetic development in preventive interventions that carries epidemiological significance. This paper addresses the theoretical, methodological, and pragmatic aspects of this prospect.

Development and Validation of the RxDx-Dementia Risk Index to Predict Dementia in Patients with Type 2 Diabetes and Hypertension. - Mehta, Hemalkumar B; Mehta, Vinay; Tsai, Chu-Lin; Chen, Hua; Aparasu, Rajender R; Johnson, Michael L (J Alzheimers Dis, 2016)
BACKGROUND: Elderly patients with type 2 diabetes mellitus and hypertension are at high risk for developing dementia. In addition to comorbid disease conditions (Dx), prescription drugs (Rx) are important risk factors for dementia. OBJECTIVE: Develop and validate the RxDx-Dementia risk index by combining diagnosis and prescription information in a single risk index to predict incident dementia, and compare its performance with diagnosis-based Charlson comorbidity score (CCS) and prescription-based chronic disease score (CDS). METHODS: Elderly patients diagnosed with type 2 diabetes mellitus and hypertension, and without prior dementia were identified from the Clinical Practice Research Datalink (2003-2012). A Cox proportional hazard model was constructed to model the time to dementia by incorporating age, gender, and 31 RxDx disease conditions as independent variables. Points were assigned to risk factors to obtain summary risk score. Discrimination and calibration of the risk index were evaluated. Different risk indices were compared against RxDx-Dementia risk index using c-statistic, net reclassification improvement (NRI) and integrated discrimination improvement (IDI). RESULTS: Of 133,176 patients with type 2 diabetes mellitus and hypertension, 3.42% patients developed dementia.The c-statistics value for RxDx-Dementia risk index was 0.806 (95% CI, 0.799-0.812). Based on the c-statistics, NRI and IDI values, the RxDx-Dementia risk index performed better compared to CCS, CDS, and their combinations. CONCLUSION: The RxDx-Dementia risk index can be a useful tool to identify hypertensive and diabetic patients who are at high risk of developing dementia. This has implications for clinical management of patients with multiple comorbid conditions as well as risk adjustment for database studies.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Dementia; Diabetes Mellitus, Type 2; Female; Humans; Hypertension; Male; Middle Aged; Predictive Value of Tests; Prescription Drugs; Proportional Hazards Models; Reproducibility of Results; Risk Assessment; Risk Factors

Diagnosis of Dementia in the Specialist Setting: A Comparison Between the Swedish Dementia Registry (SveDem) and the Registry of Dementias of Girona (ReDeGi). - Garre-Olmo, Josep; Garcia-Ptacek, Sara; Calvó-Perxas, Laia; Turró-Garriga, Oriol; López-Pousa, Secundino; Eriksdotter, Maria (J Alzheimers Dis, 2016)
The aim of this study was to compare the frequency of dementia diagnoses from two dementia registries in Europe. Patients registered between 2007 and 2013 in the Swedish Dementia Registry (SveDem; Sweden) and in the Registry of Dementias of Girona (ReDeGi; North-East of Spain) were selected. We compared sociodemographic data, Mini-Mental State Examination (MMSE) scores, dementia subtype, and medication consumption of 22,384 cases from SveDem and 5,032 cases from ReDeGi. The average age (78.1 years SveDem versus 79.7 years ReDeGi) and the gender (female 58.2% SveDem versus 61.5% ReDeGi) did not greatly differ. MMSE score at diagnosis was higher for SveDem cases (22.1 versus 17.8). Alzheimer's disease (AD) accounted for the main dementia subtype (36.6% SveDem versus 55.6% ReDeGi). The proportion of vascular dementia (VaD) and mixed dementia was higher in SveDem (18.8% versus 6.4% and 24.9 versus 13.4%), with an odds ratio (OR) and 95% confidence interval (CI) for SveDem relative to the ReDeGi of 3.41 (3.03-3.84) for VaD, and 2.15 (1.97-2.35) for mixed dementia. This was at the expense of a lower frequency of AD in SveDem (OR 0.41; 95% CI 0.39-0.44). Other dementia diagnoses such as frontotemporal dementia or dementia with Lewy bodies did not significantly differ between registries (2.3% versus 2.9%; 1.9 versus 3.1%). Large differences in medication consumption at the time of dementia diagnosis were detected (4.7 treatments SveDem versus 6.8 ReDeGi). Northern and southern European dementia cohorts differ in demographic characteristics, MMSE score at diagnosis, and drug treatment profile.

Different Clinical and Neuroimaging Characteristics in Early Stage Parkinson's Disease with Dementia and Dementia with Lewy Bodies. - Takemoto, Mami; Sato, Kota; Hatanaka, Noriko; Yamashita, Toru; Ohta, Yasuyuki; Hishikawa, Nozomi; Abe, Koji (J Alzheimers Dis, 2016)
Parkinson's disease with dementia (PDD) and dementia with Lewy bodies (DLB) both commonly exhibit brain Lewy body pathology and similar end-stage symptoms, but early symptoms differ. To clarify these differences, we compared the demographic characteristics, symptoms, cognitive and affective functioning, activities of daily life, and neuroimaging results between PDD (n = 52) and DLB (n = 46) patients. In measures of cognitive functioning, PDD patients had worse Hasegawa dementia scale-revised (HDS-R) scores (11.2±4.8) and better frontal assessment battery (FAB) scores (11.3±4.1) compared with DLB (17.0±6.4, p = 0.013 and 8.6±4.7, p = 0.039, respectively). DLB patients performed worse than PDD patients in "orientation to place" tasks. In affective functions, DLB patients had worse GDS (7.6±3.4) and ABS (9.9±5.3) scores than PDD patients (5.1±4.1 and 4.8±3.0, respectively). 99mTc-ECD images showed greater CBF in the whole cingulate gyrus and a lower CBF in the precuneus area in DLB than in PDD. These results suggest that PDD patients' lower average scores for "repetition" (MMSE), "recent memory" (HDS-R), and "lexical fluency" (FAB) were related to lower CBF in the cingulate gyrus than in DLB. Furthermore, DLB patients' poorer average subscale scores of "orientation to place" (MMSE) and "similarities", "conflicting instructions", and "go-no go" (FAB) tasks may be related to the lower CBF in the precuneus area in DLB than PDD.

Different Patterns of Correlation between Grey and White Matter Integrity Account for Behavioral and Psychological Symptoms in Alzheimer's Disease. - Makovac, Elena; Serra, Laura; Spanò, Barbara; Giulietti, Giovanni; Torso, Mario; Cercignani, Mara; Caltagirone, Carlo; Bozzali, Marco (J Alzheimers Dis, 2016)
Behavioral disorders and psychological symptoms (BPSD) in Alzheimer's disease (AD) are known to correlate with grey matter (GM) atrophy and, as shown recently, also with white matter (WM) damage. WM damage and its relationship with GM atrophy are reported in AD, reinforcing the interpretation of the AD pathology in light of a disconnection syndrome. It remains uncertain whether this disconnection might account also for different BPSD observable in AD. Here, we tested the hypothesis of different patterns of association between WM damage of the corpus callosum (CC) and GM atrophy in AD patients exhibiting one of the following BPSD clusters: Mood (i.e., anxiety and depression; ADmood), Frontal (i.e., dishinibition and elation; ADfrontal), and Psychotic (delusions and hallucinations; ADpsychotic) related symptoms, as well as AD patients without BPSD. Overall, this study brings to light the strict relationship between WM alterations in different parts of the CC and GM atrophy in AD patients exhibiting BPSD, supporting the hypothesis that such symptoms are likely to be caused by characteristic patterns of neurodegeneration of WM and GM, rather than being a reactive response to accumulation of cognitive disabilities, and should therefore be regarded as potential markers of diagnostic and prognostic value in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Brain; Depression; Female; Gray Matter; Hallucinations; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; White Matter

Dihydropyridine Derivatives Modulate Heat Shock Responses and have a Neuroprotective Effect in a Transgenic Mouse Model of Alzheimer's Disease. - Kasza, Ágnes; Hunya, Ákos; Frank, Zsuzsa; Fülöp, Ferenc; Török, Zsolt; Balogh, Gábor; Sántha, Miklós; Bálind, Árpád; Bernáth, Sándor; Blundell, Katie L I M; Prodromou, Chrisostomos; Horváth, Ibolya; et al. (J Alzheimers Dis, 2016)
Heat shock proteins (Hsps) have chaperone activity and play a pivotal role in the homeostasis of proteins by preventing misfolding, by clearing aggregated and damaged proteins from cells, and by maintaining proteins in an active state. Alzheimer's disease (AD) is thought to be caused by amyloid-β peptide that triggers tau hyperphosphorylation, which is neurotoxic. Although proteostasis capacity declines with age and facilitates the manifestation of neurodegenerative diseases such as AD, the upregulation of chaperones improves prognosis. Our research goal is to identify potent Hsp co-inducers that enhance protein homeostasis for the treatment of AD, especially 1,4-dihydropyridine derivatives optimized for their ability to modulate cellular stress responses. Based on favorable toxicological data and Hsp co-inducing activity, LA1011 was selected for the in vivo analysis of its neuroprotective effect in the APPxPS1 mouse model of AD. Here, we report that 6 months of LA1011 administration effectively improved the spatial learning and memory functions in wild type mice and eliminated neurodegeneration in double mutant mice. Furthermore, Hsp co-inducer therapy preserves the number of neurons, increases dendritic spine density, and reduces tau pathology and amyloid plaque formation in transgenic AD mice. In conclusion, the Hsp co-inducer LA1011 is neuroprotective and therefore is a potential pharmaceutical candidate for the therapy of neurodegenerative diseases, particularly AD.

Distinct Patterns of Cognitive Aging Modified by Education Level and Gender among Adults with Limited or No Formal Education: A Normative Study of the Mini-Mental State Examination. - Xie, Haiqun; Zhang, Chengguo; Wang, Yukai; Huang, Shuyun; Cui, Wei; Yang, Wenbin; Koski, Lisa; Xu, Xiping; Li, Youbao; Zheng, Meili; He, Mingli; Fu, Jia; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is increasingly prevalent due to rapid aging of the population, but under-recognized among people with low education levels. This is partly due to a lack of appropriate and precise normative data, which underestimates cognitive aging in the use of screening tools for dementia. OBJECTIVE: We aimed to improve the precision of screening for cognitive impairment, by characterizing the patterns of cognitive aging and derived normative data of the Mini-Mental State Examination (MMSE) for illiterate and low-educated populations. METHODS: This community-based study included data from 2,280 individuals aged 40 years or older from two rural areas. Multiple linear modeling examined the effect of aging on cognition reflected by the MMSE, stratified by education level and gender. Threshold effect of age on cognition was performed using a smoothing function. RESULTS: The majority of participants (60.4%) were illiterate or had attended only primary school (24.6%). The effect of aging on cognition varied by gender and education. Primary-school educated females and males remained cognitively stable up to 62 and 71 years of age, respectively, with MMSE score declining 0.4 and 0.8 points/year in females and males thereafter. Illiterates females scored 2.3 points lower than illiterate males, and scores for both declined 0.2 points/year. According to these results, normative data stratified by age, education and gender was generated. CONCLUSION: This study suggests gender and educational differences exist in cognitive aging among adults with limited or no formal education. To improve screening precision for cognitive impairment with the use of MMSE in low-educated population, age, gender, and education level should be considered.
Keywords: Adult; Aged; Aged, 80 and over; China; Cognition Disorders; Cognitive Aging; Educational Status; Female; Humans; Male; Mental Status Schedule; Middle Aged; Reference Values; Rural Population; Sex Characteristics

Divergent Longitudinal Propagation of White Matter Degradation in Logopenic and Semantic Variants of Primary Progressive Aphasia. - Tu, Sicong; Leyton, Cristian E; Hodges, John R; Piguet, Olivier; Hornberger, Michael (J Alzheimers Dis, 2016)
BACKGROUND: Clinico-pathological distinction of primary progressive aphasia (PPA) can be challenging at clinic presentation. In particular, cross-sectional neuroimaging signatures across the logopenic (lvPPA) and semantic (svPPA) variants are difficult to establish, with longitudinal profiles showing greater divergence. OBJECTIVE: Assess longitudinal propagation of white matter degradation in lvPPA and svPPA to determine disease progression over time, and whether this reflects distinct underlying pathology. METHOD: A cohort of 27 patients with dementia (12 lvPPA; 15 svPPA) and 12 healthy controls were assessed at baseline and 1-year follow-up on the Addenbrooke's Cognitive Examination-Revised and Sydney Language Battery. Diffusion weighted images were collected at both time-points and analyzed for longitudinal white matter change using DTI-TK and TBSS. RESULTS: LvPPA patients showed a significant decline in naming and repetition, over 1 year, while svPPA patients declined in naming and comprehension. Longitudinal imaging revealed widespread bilateral degradation of white matter tracts in lvPPA over a 1-year period with early involvement of the left posterior inferior longitudinal fasciculus (ILF). SvPPA demonstrated focal left lateralized white matter degradation involving the uncinate fasciculus (UF) and anterior ILF, propagating to the right UF with disease progression. CONCLUSIONS: LvPPA and svPPA cohorts showed distinct longitudinal cognitive and white matter profiles. We propose differences in multi-centric and focal white matter dysfunction in lvPPA and svPPA, respectively, reflect underlying pathological differences. The clinical relevance of white matter degradation and mechanisms underlying disease propagation are discussed.
Keywords: Aged; Analysis of Variance; Aphasia, Primary Progressive; Brain; Cohort Studies; Cross-Sectional Studies; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Names; Neuropsychological Tests; Semantics

Diversity of Cognitive Phenotypes Associated with C9ORF72 Hexanucleotide Expansion. - Gómez-Tortosa, Estrella; Prieto-Jurczynska, Cristina; Serrano, Soledad; Franco-Macías, Emilio; Olivié, Laura; Gallego, Jesús; Guerrero-López, Rosa; Trujillo-Tiebas, María José; Ayuso, Carmen; García Ruiz, Pedro; Pérez-Pérez, Julián; Sainz, María José (J Alzheimers Dis, 2016)
For diagnostic purposes, we screened for the C9ORF72 mutation in a) 162 FTLD cases, and b) 145 cases with other diagnoses but with some frontotemporal features or manifestations previously reported in C9 carriers. Ten cases (onset 50 to 75 years) harbored the expansion: seven had FTLD syndromes (4.3% of total, 11% of familial cases), and three (2%) had a different diagnosis. All positive cases had family history of dementia, psychiatric disease, or ALS, but only 20% of families with mixed FTLD/ALS phenotypes carried the expansion. Language impairment was the most common symptom, followed by behavioral changes, memory deficits, and parkinsonism. C9ORF72 mutation has a low frequency in our dementia series and very diverse clinical manifestations.
Keywords: Adult; Age of Onset; Apolipoprotein E4; Cognition; DNA Repeat Expansion; Family; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Association Studies; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Male; Middle Aged; Prevalence; Proteins; Spain

Does the Interplay Between Aging and Neuroinflammation Modulate Alzheimer's Disease Clinical Phenotypes? A Clinico-Pathological Perspective. - Taipa, Ricardo; Sousa, Ana Luísa; Melo Pires, Manuel; Sousa, Nuno (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder and is the most common cause of dementia worldwide. Cumulative data suggests that neuroinflammation plays a prominent and early role in AD, and there is compelling data from different research groups of age-associated dysregulation of the neuroimmune system. From the clinical point of view, despite clinical resemblance and neuropathological findings, there are important differences between the group of patients with sporadic early-onset (<65 years old) and late-onset AD (>65 years old). Thus, it seems important to understand the age-dependent relationship between neuroinflammation and the underlying biology of AD in order to identify potential explanations for clinical heterogeneity, interpret biomarkers, and promote the best treatment to different clinical AD phenotypes. The study of the delicate balance between pro-inflammatory or anti-inflammatory sides of immune players in the different ages of onset of AD would be important to understand treatment efficacy in clinical trials and eventually, not only direct treatment to early disease stages, but also the possibility of establishing different treatment approaches depending on the age of the patient. In this review, we would like to summarize what is currently known about the interplay between "normal" age associated inflammatory changes and AD pathological mechanisms, and also the potential differences between early-onset and late-onset AD taking into account the age-related neuroimmune background at disease onset.

Drawing Disorders in Alzheimer's Disease and Other Forms of Dementia. - Trojano, Luigi; Gainotti, Guido (J Alzheimers Dis, 2016)
Drawing is a multicomponential process that can be impaired by many kinds of brain lesions. Drawing disorders are very common in Alzheimer's disease and other forms of dementia, and can provide clinical information for the distinction of the different dementing diseases. In our review we started from an overview of the neural and cognitive bases of drawing, and from a recollection of the drawing tasks more frequently used for assessing individuals with dementia. Then, we analyzed drawing disorders in dementia, paying special attention to those observed in Alzheimer's disease, from the prodromal stages of the amnesic mild cognitive impairment to the stages of full-blown dementia, both in the sporadic forms with late onset in the entorhino-hippocampal structures and in those with early onset in the posterior neocortical structures. We reviewed the drawing features that could differentiate Alzheimer's disease from vascular dementia and from the most frequent forms of degenerative dementia, namely frontotemporal dementia and Lewy body disease. Finally, we examined some peculiar aspects of drawing disorders in dementia, such as perseverations, rotations, and closing-in. We argue that a careful analysis of drawing errors helps to differentiate the different forms of dementia more than overall accuracy in drawing.

Dysregulation and diagnostic potential of microRNA in Alzheimer's disease. - Pan, Yaoqian; Liu, Ruizhu; Terpstra, Erin; Wang, Yanqing; Qiao, Fangfang; Wang, Jin; Tong, Yigang; Pan, Bo (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is one of the most common neurodegenerative diseases and is considered to be the main cause of cognitive impairment in elderly people. The major symptom of AD is progressive dementia that eventually results in dysfunction of daily life. Due to the fact that AD has a long period of incubation before clinical symptoms emerge, the available therapeutic treatments can only improve the symptoms but not delay the progression of AD. Therefore, there is an urgent need to explore effective diagnostic approaches to catch and better treat the disease before clinical symptoms appear. Recent research revealed that abnormal expression of certain miRNA could have a crucial role in the pathological process of neurodegenerative disease including AD. Furthermore, given that AD patients show increased level of miRNAs in the blood and cerebrospinal fluid, miRNAs are considered promising non-invasive candidates for AD diagnosis and prognosis. Here, we reviewed the current research related to implications of miRNAs during the development of AD, summarized of actively used approaches to identifying potential miRNA biomarkers in body fluids, and discussed the diagnostic potential of microRNAs as biomarkers for AD.
Keywords: Aged; Alzheimer Disease; Biomarkers; Disease Progression; Humans; MicroRNAs; Prognosis

Early Postmenopausal Transdermal 17β-Estradiol Therapy and Amyloid-β Deposition. - Kantarci, Kejal; Lowe, Val J; Lesnick, Timothy G; Tosakulwong, Nirubol; Bailey, Kent R; Fields, Julie A; Shuster, Lynne T; Zuk, Samantha M; Senjem, Matthew L; Mielke, Michelle M; Gleason, Carey; Jack, Clifford R; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It remains controversial whether hormone therapy in recently postmenopausal women modifies the risk of Alzheimer's disease (AD). OBJECTIVE: To investigate the effects of hormone therapy on amyloid-β deposition in recently postmenopausal women. METHODS: Participants within 5-36 months past menopause in the Kronos Early Estrogen Prevention Study, a randomized, double blinded placebo-controlled clinical trial, were randomized to: 1) 0.45 mg/day oral conjugated equine estrogens (CEE); 2) 50μg/day transdermal 17β-estradiol; or 3) placebo pills and patch for four years. Oral progesterone (200 mg/day) was given to active treatment groups for 12 days each month. 11C Pittsburgh compound B (PiB) PET imaging was performed in 68 of the 118 participants at Mayo Clinic approximately seven years post randomization and three years after stopping randomized treatment. PiB Standard unit value ratio (SUVR) was calculated. RESULTS: Women (age = 52-65) randomized to transdermal 17β-estradiol (n = 21) had lower PiB SUVR compared to placebo (n = 30) after adjusting for age [odds ratio (95% CI) = 0.31(0.11-0.83)]. In the APOEɛ4 carriers, transdermal 17β-estradiol treated women (n = 10) had lower PiB SUVR compared to either placebo (n = 5) [odds ratio (95% CI) = 0.04(0.004-0.44)], or the oral CEE treated group (n = 3) [odds ratio (95% CI) = 0.01(0.0006-0.23)] after adjusting for age. Hormone therapy was not associated with PiB SUVR in the APOEɛ4 non-carriers. CONCLUSION: In this pilot study, transdermal 17β-estradiol therapy in recently postmenopausal women was associated with a reduced amyloid-β deposition, particularly in APOEɛ4 carriers. This finding may have important implications for the prevention of AD in postmenopausal women, and needs to be confirmed in a larger sample.

Economic Analysis of Formal Care, Informal Care, and Productivity Losses in Primary Care Patients who Screened Positive for Dementia in Germany. - Michalowsky, Bernhard; Thyrian, Jochen René; Eichler, Tilly; Hertel, Johannes; Wucherer, Diana; Flessa, Steffen; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: The majority of people with dementia (PwD) live at home and require professional formal care and informal care that is generally provided by close relatives. OBJECTIVE: To determine the utilization and costs of formal and informal care for PwD, indirect costs because of productivity losses of caregivers, and the associations between cost, socio-demographic and clinical variables. METHODS: The analysis includes the data of 262 community-dwelling PwD and their caregivers. Socio-demographics, clinical variables, and the utilization of formal care were assessed within the baseline assessment. To evaluate informal care costs, the Resource Utilization in Dementia (RUD) questionnaire was used. Costs were calculated from a social perspective. Associations were evaluated using multiple linear and logistic regression models. RESULTS: Formal care services were utilized less (26.3%) than informal care (85.1%), resulting in a cost ratio of one to ten(1,646 €; 16,473 €, respectively). In total, 29% of caregivers were employed, and every seventh (14.3%) experienced productivity losses, which corresponded to 1,258 € annually. Whereas increasing deficits in daily living activities were associated with higher formal and higher informal costs, living alone was significantly associated with higher formal care costs and the employment of a caregiver was associated with lower informal care costs. CONCLUSION: Informal care contributes the most to total care costs. Living alone is a major cost driver for formal costs because of the lower availability of potential informal care. The availability of informal care is limited and productivity losses are increased when a caregiver is employed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Germany; Health Care Costs; Home Care Services; Humans; Male; Patient Care; Sensitivity and Specificity; Surveys and Questionnaires

EEG Markers of Dementia with Lewy Bodies: A Multicenter Cohort Study. - Bonanni, Laura; Franciotti, Raffaella; Nobili, Flavio; Kramberger, Milica G; Taylor, John-Paul; Garcia-Ptacek, Sara; Falasca, N Walter; Famá, Francesco; Cromarty, Ruth; Onofrj, Marco; Aarsland, Dag (J Alzheimers Dis, 2016)
Quantitative EEG (QEEG) has demonstrated good discriminative capacity for dementia with Lewy bodies (DLB) diagnosis as compared to Alzheimer's disease (AD) with a predictive value of 100% in a single cohort study. EEG in DLB was characterized by a dominant frequency (DF) in pre-alpha (5.5-7.5 Hz), theta, or delta bands and DF variability (DFV) >1.2 Hz, frequency prevalence (FP) pre-alpha in >40% and FP alpha in <32% of the epochs. To validate the aforementioned QEEG findings in independent cohorts of clinically diagnosed DLB versus AD patients, we analyzed EEG traces of 79 DLB and 133 AD patients (MMSE >20) collected from four European Centers. EEG traces from 19 scalp derivations were acquired as at least 10 min continuous signals and epoched in off-setting as series of 2-second-long epochs, subsequently processed by Fast Fourier Transform (frequency resolution 0.5 Hz). DLB patients showed EEG specific abnormalities in posterior derivations characterized by DF <8 Hz FP pre-alpha >50%, FP alpha <25%. DFV was >0.5 Hz. AD patients displayed stable alpha DF, DFV <0.5 Hz, FP pre-alpha <30%, and FP alpha >55%. DLB and AD differed for DF (p < 10-6), DFV (p < 0.05), FP pre-alpha (p < 10-12) and FP alpha (p < 10-12). Discriminant analysis detected specific cut-offs for every EEG mathematical descriptor; DF = 8, DFV = 2.2 Hz, FP pre-alpha=33%, FP alpha = 41% for posterior derivations. If at least one of the cut-off values was met, the percentage of DLB and AD patients correctly classified was 90% and 64%, respectively. The findings in this multicenter study support the validity of QEEG analysis as a tool for diagnosis in DLB patients.

Effect of Anserine/Carnosine Supplementation on Verbal Episodic Memory in Elderly People. - Hisatsune, Tatsuhiro; Kaneko, Jun; Kurashige, Hiroki; Cao, Yuan; Satsu, Hideo; Totsuka, Mamoru; Katakura, Yoshinori; Imabayashi, Etsuko; Matsuda, Hiroshi (J Alzheimers Dis, 2016)
Our goal in this study was to determine whether or not anserine/carnosine supplementation (ACS) is capable of preserving cognitive function of elderly people. In a double-blind randomized controlled trial, volunteers were randomly assigned to an ACS or placebo group at a 1:1 ratio. The ACS group took 1.0 g of an anserine/carnosine (3:1) formula daily for 3 months. Participants were evaluated by psychological tests before and after the 3-month supplementation period. Thirty-nine healthy elderly volunteers (60-78 years old) completed the follow-up tests. Among the tests, delayed recall verbal memory assessed by the Wechsler Memory Scale-Logical Memory showed significant preservation in the ACS group, compared to the placebo group (p = 0.0128). Blood analysis revealed a decreased secretion of inflammatory cytokines, including CCL-2 and IL-8, in the ACS group. MRI analysis using arterial spin labeling showed a suppression in the age-related decline in brain blood flow in the posterior cingulate cortex area in the ACS group, compared to the placebo group (p = 0.0248). In another randomized controlled trial, delayed recall verbal memory showed significant preservation in the ACS group, compared to the placebo group (p = 0.0202). These results collectively suggest that ACS may preserve verbal episodic memory and brain perfusion in elderly people, although further study is needed.
Keywords: Adult; Aged; Aging; Anserine; Brain; Carnosine; Cytokines; Dietary Supplements; Double-Blind Method; Female; Gene Expression Regulation; Humans; Image Processing, Computer-Assisted; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Oligonucleotide Array Sequence Analysis; Verbal Learning

Efficacy and Safety of ABT-126 in Subjects with Mild-to-Moderate Alzheimer's Disease on Stable Doses of Acetylcholinesterase Inhibitors: A Randomized, Double-Blind, Placebo-Controlled Study. - Florian, Hana; Meier, Andreas; Gauthier, Serge; Lipschitz, Stanley; Lin, Yunzhi; Tang, Qi; Othman, Ahmed A; Robieson, Weining Z; Gault, Laura M (J Alzheimers Dis, 2016)
BACKGROUND: ABT-126 is a potent, selective α7 nicotinic acetylcholine receptor agonist with putative procognitive effects as a monotherapy in treating Alzheimer's disease (AD). OBJECTIVE: This randomized, double-blind, placebo-controlled multicenter study (NCT01549834) investigated the efficacy and safety of ABT-126 in subjects with mild-to-moderate AD who were taking stable doses of acetylcholinesterase inhibitors (AChEIs). METHODS: Subjects received 25 mg ABT-126 (n = 143), 75 mg ABT-126 (n = 145), or placebo (n = 146) once daily for 24 weeks. Subjects who completed the 24-week double-blind study were eligible to enroll in a 28-week open-label extension study (NCT01690195) and received 75 mg ABT-126 daily. The primary efficacy endpoint was the change from baseline to week 24 in the 11-item total score of the Alzheimer's Disease Assessment Scale- Cognitive Subscale (ADAS-Cog). RESULTS: Neither dose of ABT-126 demonstrated significant improvement compared with placebo in the primary efficacy endpoint. However, 25 mg ABT-126 demonstrated significant improvement compared with placebo in ADAS-Cog scores at week 4 (least squares mean difference, -1.21; standard error, 0.51; p <  0.010, one-sided); 75 mg ABT-126 did not demonstrate significant improvements in ADAS-Cog scores compared with placebo at any time point. A treatment effect was not observed for any secondary efficacy measures of cognition, function, or global improvement. ABT-126 was generally well tolerated; the most common adverse events were agitation, constipation, diarrhea, fall, and headache. CONCLUSIONS: Overall, the efficacy profile of ABT-126 did not warrant further development as add-on therapy to AChEIs to treat mild-to-moderate AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Disease Progression; Dose-Response Relationship, Drug; Double-Blind Method; Female; Humans; Indans; International Cooperation; Male; Medication Adherence; Middle Aged; Piperidines; Psychiatric Status Rating Scales; Treatment Outcome

Efficacy and Safety of Crocus sativus L. in Patients with Mild Cognitive Impairment: One Year Single-Blind Randomized, with Parallel Groups, Clinical Trial. - Tsolaki, Magda; Karathanasi, Elina; Lazarou, Ioulietta; Dovas, Kostas; Verykouki, Eleni; Karacostas, Anastasios; Georgiadis, Kostas; Tsolaki, Anthoula; Adam, Katerina; Kompatsiaris, Ioannis; Sinakos, Zacharias (J Alzheimers Dis, 2016)
There is evidence to suggest the efficacy of Crocus (saffron) in the management of cognitive decline. This study examined the efficacy of Crocus in patients with amnesic and multi domain MCI (aMCImd). The participants included 17 patients on Crocus and 18 on a waiting list, who were examined with a short neuropsychological battery, MRI 3T, while some patients were examined via 256-channel electroencephalogram (HD-EEG) at baseline and after 12 months. The results showed that patients on Crocus had improved Mini-Mental State Examination scores (p = 0.015), while the control group deteriorated. Also, MRI, EEG, and ERP showed improvement in specific domains. This led us to conclude that Crocus is a good choice for management of aMCImd.

Efficacy and Safety of Sustained Release Donepezil High Dose versus Immediate Release Donepezil Standard Dose in Japanese Patients with Severe Alzheimer's Disease: A Randomized, Double-Blind Trial. - Homma, Akira; Atarashi, Hirotsugu; Kubota, Naoki; Nakai, Kenya; Takase, Takao (J Alzheimers Dis, 2016)
BACKGROUND: Donepezil is an established treatment for mild, moderate, and severe Alzheimer's disease (AD). An international study demonstrated superior efficacy of sustained release (SR) 23 mg/day donepezil over immediate release (IR) 10 mg/day donepezil for cognitive function, but not global function in moderate-to-severe AD. OBJECTIVE: To demonstrate the superiority of SR 23 mg/day donepezil over IR 10 mg/day donepezil in Japanese patients with severe AD (SAD). METHODS: In this multicenter, randomized, double-blind, parallel-group study, Japanese outpatients with SAD were randomly assigned to continue IR 10 mg/day or switch to SR 23 mg/day for 24 weeks. Endpoints included the Severe Impairment Battery (SIB), Clinician's Interview-Based Impression of Change Plus Caregiver Input (CIBIC-plus), and safety. RESULTS: Overall, 166 and 185 patients were randomized to receive IR 10 mg/day and SR 23 mg/day, respectively. SR 23 mg/day was not statistically superior to IR 10 mg/day by SIB (least squares mean difference [LSMD]: 0.0; 95% confidence interval [CI]: -1.7, 1.8; p = 0.981) or CIBIC-plus (LSMD: 0.2; 95% CI: 0.0, 0.4; p = 0.080). Common adverse events in the SR 23 mg group were decreased appetite, vomiting, diarrhea, and contusion. Safety findings were consistent with known safety profiles of donepezil. CONCLUSION: SR 23 mg/day donepezil was not superior to IR 10 mg/day donepezil regarding the efficacy endpoints for Japanese SAD. Considering that a 10 mg/day dose is approved for SAD in Japan, the present findings suggest that IR 10 mg/day donepezil is the optimal dosage for Japanese patients with SAD.
Keywords: Aged; Alzheimer Disease; Cholinesterase Inhibitors; Delayed-Action Preparations; Double-Blind Method; Female; Humans; Indans; Japan; Male; Mental Status Schedule; Nootropic Agents; Outpatients; Piperidines; Psychiatric Status Rating Scales; Severity of Illness Index; Treatment Outcome

Empirically Defining Trajectories of Late-Life Cognitive and Functional Decline. - Hochstetler, Helen; Trzepacz, Paula T; Wang, Shufang; Yu, Peng; Case, Michael; Henley, David B; Degenhardt, Elisabeth; Leoutsakos, Jeannie-Marie; Lyketsos, Constantine G (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is associated with variable cognitive and functional decline, and it is difficult to predict who will develop the disease and how they will progress. OBJECTIVE: This exploratory study aimed to define latent classes from participants in the Alzheimer's Disease Neuroimaging Initiative (ADNI) database who had similar growth patterns of both cognitive and functional change using Growth Mixture Modeling (GMM), identify characteristics associated with those trajectories, and develop a decision tree using clinical predictors to determine which trajectory, as determined by GMM, individuals will most likely follow. METHODS: We used ADNI early mild cognitive impairment (EMCI), late MCI (LMCI), AD dementia, and healthy control (HC) participants with known amyloid-β status and follow-up assessments on the Alzheimer's Disease Assessment Scale - Cognitive Subscale or the Functional Activities Questionnaire (FAQ) up to 24 months postbaseline. GMM defined trajectories. Classification and Regression Tree (CART) used certain baseline variables to predict likely trajectory path. RESULTS: GMM identified three trajectory classes (C): C1 (n = 162, 13.6%) highest baseline impairment and steepest pattern of cognitive/functional decline; C3 (n = 819, 68.7%) lowest baseline impairment and minimal change on both; C2 (n = 211, 17.7%) intermediate pattern, worsening on both, but less steep than C1. C3 had fewer amyloid- or apolipoprotein-E ɛ4 (APOE4) positive and more healthy controls (HC) or EMCI cases. CART analysis identified two decision nodes using the FAQ to predict likely class with 82.3% estimated accuracy. CONCLUSIONS: Cognitive/functional change followed three trajectories with greater baseline impairment and amyloid and APOE4 positivity associated with greater progression. FAQ may predict trajectory class.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoprotein E4; Cognition Disorders; Databases, Factual; Dementia; Disease Progression; Female; Follow-Up Studies; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Surveys and Questionnaires

Enalapril Alone or Co-Administered with Losartan Rescues Cerebrovascular Dysfunction, but not Mnemonic Deficits or Amyloidosis in a Mouse Model of Alzheimer's Disease. - Ongali, Brice; Nicolakakis, Nektaria; Tong, Xing-Kang; Aboulkassim, Tahar; Imboden, Hans; Hamel, Edith (J Alzheimers Dis, 2016)
The co-administration of angiotensin converting enzyme inhibitors (ACEi) and angiotensin II (AngII) receptor blockers (ARB) that bind angiotensin type 1 receptors (AT1R) may protect from Alzheimer's disease (AD) better than each treatment taken alone. We tested the curative potential of the non brain-penetrant ACEi enalapril (3 mg/kg/day) administered for 3 months either alone or in combination with the brain penetrant ARB losartan (10 mg/kg/day) in aged (∼15 months) transgenic mice overexpressing a mutated form of the human amyloid-β protein precursor (AβPP, thereafter APP mice). We studied cerebrovascular function, protein levels of oxidative stress markers (superoxide dismutases SOD1, SOD2 and the NADPH oxidase subunit p67phox), amyloid-β (Aβ) pathology, astrogliosis, cholinergic innervation, AT1R and angiotensin IV receptor (AT4R) levels, together with cognitive performance. Both treatments normalized cerebrovascular reactivity and p67phox protein levels, but they did not reduce the cerebrovascular levels of SOD1. Combined treatment normalized cerebrovascular SOD2 levels, significantly attenuated astrogliosis, but did not reduce the increased levels of cerebrovascular AT1R. Yet, combined therapy enhanced thioflavin-S labeled Aβ plaque burden, a tendency not significant when Aβ1 - 42 plaque load was considered. None of the treatments rescued cognitive deficits, cortical AT4R or cholinergic innervation. We conclude that both treatments normalized cerebrovascular function by inhibiting the AngII-induced oxidative stress cascade, and that the positive effects of the combined therapy on astrogliosis were likely due to the ability of losartan to enter brain parenchyma. However, enalapril did not potentiate, and may even dampen, the reported cognitive benefits of losartan, raising caution when selecting the most appropriate antihypertensive therapy in AD patients.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloidosis; Analysis of Variance; Animals; Antihypertensive Agents; Cerebrovascular Disorders; Cholinesterases; Disease Models, Animal; Drug Combinations; Enalapril; Female; Glial Fibrillary Acidic Protein; Humans; Losartan; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Mutation

Evolution of the Antidepressant Prescribing in Alzheimer's Disease and Related Disorders Between 2010 and 2014: Results from the French National Database on Alzheimer's Disease (BNA). - David, Renaud; Manera, Valeria; Fabre, Roxane; Pradier, Christian; Robert, Philippe; Tifratene, Karim (J Alzheimers Dis, 2016)
BACKGROUND: Safety warnings from health authorities are currently intended to limit the use of psychotropic agents in dementia-related conditions. Evidence concerning the use of antidepressants in dementia is, however, scarce and contradictory. OBJECTIVE: To evaluate antidepressant use among individuals with Alzheimer's disease (AD) and related disorders in the French population between 2010 and 2014. METHOD: Antidepressant prescriptions in individuals with AD, mixed dementia (MD), and vascular dementia (VaD) in the French National Alzheimer Database between 2010 and 2014 were analyzed (N = 199,544). RESULTS: Multivariate analysis showed an annual significant increase (p < 0.001) in the prescription rate of antidepressants from 26% (2010) to 31% (2014), and identified female gender, younger age, higher education, living in long-term facilities, more severe cognitive decline, and presence of vascular signs (VaD and MD) as associated factors for antidepressant prescribing. CONCLUSION: The annual increase of antidepressant prescribing among individuals with AD, MD, and VaD in French specialized settings may be partially related to the lack of current valuable medications for dementia-related behavioral symptoms.

Examining the Relationship Between Autobiographical Memory Impairment and Carer Burden in Dementia Syndromes. - Kumfor, Fiona; Teo, Drusilla; Miller, Laurie; Lah, Suncica; Mioshi, Eneida; Hodges, John R; Piguet, Olivier; Irish, Muireann (J Alzheimers Dis, 2016)
BACKGROUND: Autobiographical memory (ABM) refers to the capacity to remember one's own past, and is known to be central for supporting one's identity and sense of self. This capacity is commonly affected in Alzheimer's disease (AD), as well as semantic dementia (SD) and behavioral-variant frontotemporal dementia (bvFTD). Importantly, ABM plays a critical social function, facilitating relationship intimacy and empathy, and thus loss of ABM may also negatively affect families and carers. OBJECTIVE: To explore the relationship between ABM disruption and carer burden in AD, SD, and bvFTD, and establish whether characteristic ABM profiles differentially relate to carer burden across dementia syndromes. METHODS: We recruited 12 AD, 10 SD, and 13 bvFTD patients and their primary carer. All participants completed the Autobiographical Interview to assess memory for recent and remote events. Carers completed: the Zarit Burden Interview; Depression, Anxiety and Stress Scale (DASS-21); and the Intimate Bond Measure (IBM). RESULTS: In AD, loss of recent ABM was associated with worse psychological wellbeing of carers on the DASS-21. In contrast in SD, remote ABM dysfunction was associated with SD patients showing greater controlling behavior within their intimate relationships. In bvFTD, surprisingly, despite pervasive ABM impairment, no relationship between extent of ABM loss and carer burden was observed. CONCLUSION: These preliminary results reveal that ABM impairment impacts on patients' families and carers and suggest that these influences vary according to the pattern of ABM dysfunction. Disease-specific interventions focusing on preserved aspects of ABM may improve quality of life for both patients and carers.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; Analysis of Variance; Behavioral Symptoms; Caregivers; Female; Frontotemporal Dementia; Humans; Male; Memory Disorders; Memory, Episodic; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Statistics as Topic

Expression of Tau Produces Aberrant Plasma Membrane Blebbing in Glial Cells Through RhoA-ROCK-Dependent F-Actin Remodeling. - Torres-Cruz, Francisco M; Rodríguez-Cruz, Fanny; Escobar-Herrera, Jaime; Barragán-Andrade, Norma; Basurto-Islas, Gustavo; Ripova, Daniela; Avila, Jesús; Garcia-Sierra, Francisco (J Alzheimers Dis, 2016)
Abnormal aggregation of Tau in glial cells has been reported in Alzheimer's disease (AD) and other tauopathies; however, the pathological significance of these aggregates remains unsolved to date. In this study, we evaluated whether full-length Tau (Tau441) and its aspartic acid421-truncated Tau variant (Tau421) produce alterations in the normal organization of the cytoskeleton and plasma membrane (PM) when transiently expressed in cultured C6-glial cells. Forty-eight hours post-transfection, abnormal microtubule bundling was observed in the majority of the cells, which expressed either Tau441 or Tau421. Moreover, both variants of Tau produced extensive PM blebbing associated with cortical redistribution of filamentous actin (F-Actin). These effects were reverted when Tau-expressing cells were incubated with drugs that depolymerize F-Actin. In addition, when glial cells showing Tau-induced PM blebbing were incubated with inhibitors of the Rho-associated protein kinase (ROCK) signaling pathway, both formation of abnormal PM blebs and F-Actin remodeling were avoided. All of these effects were initiated upstream by abnormal Tau-induced microtubule bundling, which may release the microtubule-bound guanine nucleotide exchange factor-H1 (GEF-H1) into the cytoplasm in order to activate its major effector RhoA-GTPase. These results may represent a new mechanism of Tau toxicity in which Tau-induced microtubule bundling produces activation of the Rho-GTPase-ROCK pathway that in turn mediates the remodeling of cortical Actin and PM blebbing. In AD and other tauopathies, these Tau-induced abnormalities may occur and contribute to the impairment of glial activity.

Functional Connectivity of Ventral and Dorsal Visual Streams in Posterior Cortical Atrophy. - Migliaccio, Raffaella; Gallea, Cécile; Kas, Aurélie; Perlbarg, Vincent; Samri, Dalila; Trotta, Laura; Michon, Agnès; Lacomblez, Lucette; Dubois, Bruno; Lehéricy, Stéphane; Bartolomeo, Paolo (J Alzheimers Dis, 2016)
BACKGROUND: Posterior cortical atrophy (PCA) induces progressive dysfunction of ventral and dorsal visual networks. Little is known, however, about corresponding changes in functional connectivity (FC). OBJECTIVES: To investigate FC changes in the visual networks, their relationship with cortical atrophy, and the association with Alzheimer's disease (AD) pathology. METHODS: Ten PCA patients and 28 age-matched controls participated in the study. Using resting state fMRI, we measured FC in ventral and dorsal cortical visual networks, defined on the basis of a priori knowledge of long-range white matter connections. To assess the relationships with AD, we determined AD biomarkers in cerebrospinal fluid and FC in the default mode network (DMN), which is vulnerable to AD pathology. Voxel-based morphometry analysis assessed the pattern of grey matter (GM) atrophy. RESULTS: PCA patients showed GM atrophy in bilateral occipital and inferior parietal regions. PCA patients had lower FC levels in a ventral network than controls, but higher FC in inferior components of the dorsal network. In particular, the increased connectivity correlated with greater GM atrophy in occipital regions. All PCA patients had positive cerebrospinal fluid biomarkers for AD; however, FC in global DMN did not differ from controls. CONCLUSIONS: FC in PCA reflects brain structure in a non-univocal way. Hyperconnectivity of dorsal networks may indicate aberrant communication in response to posterior brain atrophy or processes of neural resilience during the initial stage of brain dysfunction. The lack of difference from controls in global DMN FC highlights the atypical nature of PCA with respect to typical AD.
Keywords: Aged; Alzheimer Disease; Atrophy; Case-Control Studies; Cerebral Cortex; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Oxygen; Visual Pathways

Genetic Counseling and Testing for Alzheimer's Disease and Frontotemporal Lobar Degeneration: An Italian Consensus Protocol. - Bocchetta, Martina; Mega, Anna; Bernardi, Livia; Di Maria, Emilio; Benussi, Luisa; Binetti, Giuliano; Borroni, Barbara; Colao, Rosanna; Di Fede, Giuseppe; Fostinelli, Silvia; Galimberti, Daniela; Gennarelli, Massimo; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Genetic testing of familial Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) is attracting interest thanks to innovative primary prevention clinical trials and increased request for information by at-risk individuals. However, ethical, social, and psychological implications are paramount and genetic testing must be supported by structured genetic counseling. In Italy, practice parameters and guidelines for genetic counseling in dementia are not available. OBJECTIVE: To develop a nationally harmonized protocol for genetic counseling and testing of familial AD and FTLD. METHODS: Activities were carried out in the context of the Italian Dominantly Inherited Alzheimer's and Frontotemporal Network (IT-DIAfN) project, a national network of centers of excellence with expertise in managing patients with familial AD and FTLD. A survey of the literature on genetic counseling protocols and guidelines was conducted. Local protocols for genetic counseling were surveyed. Differences and commonalities among protocols were identified and discussed among project partners. Consensus was reached following implicit aggregation methods. RESULTS: Consensus was reached on a protocol for patients with clinically diagnosed familial AD or FTLD and a distinct protocol for their at-risk relatives. Genetic counseling should be provided by a multidisciplinary team including a geneticist, a neurologist/geriatrician, and a psychologist/psychiatrist, according to the following schedule: (i) initial consultation with tailored information on the genetics of the dementias; (ii) clinical, psychological, and cognitive assessment; if deemed appropriate (iii) genetic testing following a structured decision tree for gene mutation search; (iv) genetic testing result disclosure; (v) psychological support follow-up. CONCLUSION: This genetic counseling protocol provides Italian centers with a line of shared practice for dealing with the requests for genetic testing for familial AD and FTLD from patients and at-risk relatives, who may also be eligible participants for novel prevention clinical trials.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Consensus; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Peptide Fragments; Psychiatric Status Rating Scales

Genetics of Frontotemporal Lobar Degeneration: From the Bench to the Clinic. - Tang, Shan-Shan; Li, Jun; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
Frontotemporal lobar degeneration (FTLD) is a clinically heterogeneous neurodegenerative disease with a strong genetic component. In this review, we summarize most common mutations in MAPT, GRN, and C90RF72, as well as less common mutations in VCP, CHMP2B, TARDBP, FUS gene and so on. Several guidelines have been developed to help gene testing based on genotype-phenotype correlation, the underlying histopathological subtypes, and the neuroanatomic associations. Furthermore, we also summarize molecular pathways implicated by genes and novel targets for FTLD prevention and management in recent years.

Greater specificity for cerebrospinal fluid P-tau231 over P-tau181 in the differentiation of healthy controls from Alzheimer's disease. - Spiegel, Jonathan; Pirraglia, Elizabeth; Osorio, Ricardo S; Glodzik, Lidia; Li, Yi; Tsui, Wai; Saint Louis, Leslie A; Randall, Catherine; Butler, Tracy; Xu, Jinfeng; Zinkowski, Raymond P; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of phosphorylated-tau (P-tau) 231 and P-tau181 are two biomarkers for the identification of tau pathology as related to Alzheimer's disease (AD). While both are pathologically validated, their relative diagnostic performances are not well known. This cross-sectional diagnostic study of 87 normal (NL) subjects and 28 AD subjects compared CSF P-tau231 with CSF P-tau181. Logistic regression modeling demonstrated that the P-tau231 was superior to the P-tau181 in the diagnostic classifications. At a fixed 85% sensitivity cutoff, the ROC analysis shows that P-tau231 has greater overall specificity than P-tau181. While both P-tau analytes demonstrated equivalent negative predictive accuracies, P-tau231 yielded significantly fewer false positives. Moreover, P-tau231, but not P-tau181, demonstrated sensitivity to the E4 genotype. A postmortem validation with 9 AD subjects confirmed the superiority of the CSF P-tau231 specificity. This study suggests that P-tau231 has the potential to improve the CSF tau biomarker diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Middle Aged; Phosphorylation; ROC Curve; Sensitivity and Specificity; tau Proteins

Greater than the Sum of Its Parts: δ can be Constructed from Item Level Data. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
"δ", a latent variable constructed from cognitive performance and functional status measures, can accurately diagnose dementia. The minimal assessment needed is unknown. We have constructed a δ homolog, "dTEXAS", from Telephone Executive Assessment Scale (TEXAS) items, and validated it in a convenience sample of Japanese persons (n = 176). dTEXAS scores correlated strongly with both Instrumental Activities of Daily Living (IADL) (r = -0.86, p <  0.001) and Clinical Dementia Rating Scale (CDR) (r = 0.71, p <  0.001). Constructed independently of their diagnoses, dTEXAS scores accurately distinguished dementia versus controls (area under the receiver operating curve [(AUC; ROC) = 0.92], dementia versus mild cognitive impairment (MCI) (AUC = 0.80) and controls versus MCI (AUC = 0.74). These AUCs are higher than those of multiple observed executive measures, as reported recently by Matsuoka et al., 2014. A dTEXAS score of -0.58 best discriminated between dementia versus controls with 90.1% sensitivity and 80.0% specificity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Executive Function; Female; Humans; Japan; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; ROC Curve; United States

GSK-3β is Dephosphorylated by PP2A in a Leu309 Methylation-Independent Manner. - Chu, Dandan; Tan, Jianxin; Xie, Shutao; Jin, Nana; Yin, Xiaomin; Gong, Cheng-Xin; Iqbal, Khalid; Liu, Fei (J Alzheimers Dis, 2016)
Hyperphosphorylation of tau is pivotally involved in the pathogenesis of Alzheimer's disease (AD) and related tauopathies. Glycogen synthase kinase-3β (GSK-3β) and protein phosphate 2A (PP2A) are crucial enzymes to regulate tau phosphorylation. GSK-3β activity is regulated by its inhibitory phosphorylation at Ser9. We previously reported the cross-talk between GSK-3β and PP2A signaling and showed that PP2A could dephosphorylate GSK-3β at Ser9. Here, we investigated the dephosphorylation of GSK-3β in brain extracts in the presence of phosphatase inhibitors and found that a PP2A-like phosphatase activity was required for dephosphorylation of GSK-3β at Ser9. PP2A interacted with GSK-3β and suppressed its Ser9 phosphorylation in vitro and in HEK-293FT cells. Activity of PP2A negatively correlated to the level of phosphorylated GSK-3β in kainic acid-induced excitotoxic mouse brain. Alteration of methylation of the catalytic subunit of PP2A (PP2Ac) at Leu309 did not affect GSK-3β phosphorylation. These findings suggest that Leu309 methylation is not required for PP2A to dephosphorylate GSK-3β at Ser9.
Keywords: Animals; Brain; Carboxylic Ester Hydrolases; Cell Line, Transformed; Dose-Response Relationship, Drug; Enzyme Inhibitors; Excitatory Amino Acid Agonists; Glycogen Synthase Kinase 3; Glycogen Synthase Kinase 3 beta; Humans; Kainic Acid; Leucine; Luminescent Proteins; Male; Methylation; Mice; Phosphorylation; Protein O-Methyltransferase; Protein Phosphatase 2; RNA, Small Interfering; Serine; tau Proteins

Heterogeneous Language Profiles in Patients with Primary Progressive Aphasia due to Alzheimer's Disease. - Louwersheimer, Eva; Keulen, M Antoinette; Steenwijk, Martijn D; Wattjes, Mike P; Jiskoot, Lize C; Vrenken, Hugo; Teunissen, Charlotte E; van Berckel, Bart N M; van der Flier, Wiesje M; Scheltens, Philip; van Swieten, John C; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
BACKGROUND: The logopenic variant of Primary Progressive Aphasia (lvPPA) is associated with underlying Alzheimer's disease (AD) pathology and characterized by impaired single word retrieval and repetition of phrases and sentences. OBJECTIVE: We set out to study whether logopenic aphasia is indeed the prototypic language profile in PPA patients with biomarker evidence of underlying AD pathology and to correlate language profiles with cortical atrophy patterns on MRI. METHODS: Inclusion criteria: (I) clinical diagnosis of PPA; (II) CSF profile and/or PiB-PET scan indicative for amyloid pathology; (III) availability of expert language evaluation. Based on language evaluation, patients were classified as lvPPA (fulfilling lvPPA core criteria), lvPPA extended (fulfilling core criteria plus other language disturbances), or PPA unclassifiable (not fulfilling lvPPA core criteria). Cortical atrophy patterns on MRI were visually rated and quantitative measurements of cortical thickness were performed using FreeSurfer. RESULTS: We included 22 patients (age 67±7 years, 50% female, MMSE 21±6). 41% were classified as lvPPA, 36% as lvPPA extended with additional deficits in language comprehension and/or confrontation naming, and 23% as PPA unclassifiable. By both qualitative and quantitative measurements, patients with lvPPA showed mild global cortical atrophy on MRI, whereas patients with lvPPA extended showed more focal cortical atrophy, predominantly at the left tempo-parietal side. For PPA unclassifiable, qualitative measurements revealed a heterogeneous atrophy pattern. CONCLUSION: Although most patients fulfilled the lvPPA criteria, we found that their language profiles were heterogeneous. The clinical and radiological spectrum of PPA due to underlying AD pathology is broader than pure lvPPA.
Keywords: Aged; Alzheimer Disease; Aphasia, Primary Progressive; Atrophy; Biomarkers; Brain; Female; Humans; Language; Language Tests; Magnetic Resonance Imaging; Male; Mental Status Schedule; Organ Size; Positron-Emission Tomography; Retrospective Studies

High-Sodium Diet Has Opposing Effects on Mean Arterial Blood Pressure and Cerebral Perfusion in a Transgenic Mouse Model of Alzheimer's Disease. - Taheri, Saeid; Yu, Jin; Zhu, Hong; Kindy, Mark S (J Alzheimers Dis, 2016)
BACKGROUND: Cerebral ionic homeostasis impairment, especially Ca2+, has been observed in Alzheimer's disease (AD) and also with hypertension. Hypertension and AD both have been implicated in impaired cerebral autoregulation. However, the relationship between the ionic homeostasis impairment in AD and hypertension and cerebral blood flow (CBF) autoregulation is not clear. OBJECTIVE: To test the hypothesis that a high-salt diet regimen influences the accumulation of amyloid-β (Aβand CBF) and CBF, exacerbates cognitive decline, and increases the propensity to AD. METHODS: Double transgenic mice harboring the amyloid-β protein precursor (APPswe), and presenilin-1 (PSEN1) along with control littermates, 2 months of age at initiation of special diet, were divided into 4 groups: Group A, APP/PS1 and Group B, controls fed a high-sodium (4.00%) chow diet for 3 months; Group C, APP/PS1 and Group D, controls fed a low-sodium (0.08%) regular chow diet for 3 months. Mean arterial blood pressure (MAP) and CBF were measured noninvasively using the tail MAP measurement device and magnetic resonance imaging, respectively. Aβ plaques numbers in the cortex and hippocampus of APP/PS1 were quantified. RESULTS: In contrary to controls, APP/PS1 mice fed a high-salt diet did not show markedly elevated mean systolic and diastolic blood pressure (134±4.8 compared with 162±2.8 mmHg, and 114±5.0 compared with 137±20 mmHg, p< 0.0001). However, a high-salt diet increased CBF in both APP/PS1 and controls and did not alter the cerebral tissue integrity. Aβ plaques were significantly reduced in the cortex and hippocampus of mice fed a high-salt diet. CONCLUSION: These data suggest that a high-salt diet differently affects MAP and CBF in APP/PS1 mice and controls.

Homocysteine and Alzheimer's Disease: Evidence for a Causal Link from Mendelian Randomization. - Hu, Qingting; Teng, Wenhui; Li, Jiajia; Hao, Fangfang; Wang, Naidong (J Alzheimers Dis, 2016)
BACKGROUND/OBJECTIVE: The relationship between plasma homocysteine (Hcy) levels and Alzheimer's disease (AD) has been studied for many years, but remains controversial. While a recent meta-analysis of epidemiological studies, which included observational studies, indicated that homocysteine may be a risk factor for AD, there remains a need to further demonstrate this link due to the large degree of heterogeneity between studies. Epidemiological studies have certain limitations, as their results can be affected by confounding factors and reverse causation. In this study, we evaluated the relationship between plasma homocysteine and AD by using a Mendelian randomization method to avoid problems of confounding bias and reverse causality. METHODS: We searched the PubMed and EMBASE databases for reports regarding the MTHFR C677T polymorphism (rs1801133) from the time of their inception to September 2015. These reports were combined with related observational studies, and used to evaluate the effect of MTHFR C677T (rs1801133) on the risk for AD. A recent meta-analysis of genome-wide association studies had previously suggested a relationship between homocysteine and MTHFR C677T (rs 1801133). RESULTS: Our met-analysis included 34 studies with 9397 subjects, and demonstrated a significant relationship between plasma total homocysteine levels and the risk for AD (OR = 3.37; 95% CI = 1.90-5.95; p = 2.9×10-5). CONCLUSION: Our meta-analysis demonstrated a causal link between plasma total homocysteine and the risk for AD, and provides a new insight into the etiology and prevention of AD.

The Identification of Aluminum in Human Brain Tissue Using Lumogallion and Fluorescence Microscopy. - Mirza, Ambreen; King, Andrew; Troakes, Claire; Exley, Christopher (J Alzheimers Dis, 2016)
Aluminum in human brain tissue is implicated in the etiologies of neurodegenerative diseases including Alzheimer's disease. While methods for the accurate and precise measurement of aluminum in human brain tissue are widely acknowledged, the same cannot be said for the visualization of aluminum. Herein we have used transversely-heated graphite furnace atomic absorption spectrometry to measure aluminum in the brain of a donor with Alzheimer's disease, and we have developed and validated fluorescence microscopy and the fluor lumogallion to show the presence of aluminum in the same tissue. Aluminum is observed as characteristic orange fluorescence that is neither reproduced by other metals nor explained by autofluorescence. This new and relatively simple method to visualize aluminum in human brain tissue should enable more rigorous testing of the aluminum hypothesis of Alzheimer's disease (and other neurological conditions) in the future.

Identification of Physician-Diagnosed Alzheimer's Disease and Related Dementias in Population-Based Administrative Data: A Validation Study Using Family Physicians' Electronic Medical Records. - Jaakkimainen, R Liisa; Bronskill, Susan E; Tierney, Mary C; Herrmann, Nathan; Green, Diane; Young, Jacqueline; Ivers, Noah; Butt, Debra; Widdifield, Jessica; Tu, Karen (J Alzheimers Dis, 2016)
BACKGROUND: Population-based surveillance of Alzheimer's and related dementias (AD-RD) incidence and prevalence is important for chronic disease management and health system capacity planning. Algorithms based on health administrative data have been successfully developed for many chronic conditions. The increasing use of electronic medical records (EMRs) by family physicians (FPs) provides a novel reference standard by which to evaluate these algorithms as FPs are the first point of contact and providers of ongoing medical care for persons with AD-RD. OBJECTIVE: We used FP EMR data as the reference standard to evaluate the accuracy of population-based health administrative data in identifying older adults with AD-RD over time. METHODS: This retrospective chart abstraction study used a random sample of EMRs for 3,404 adults over 65 years of age from 83 community-based FPs in Ontario, Canada. AD-RD patients identified in the EMR were used as the reference standard against which algorithms identifying cases of AD-RD in administrative databases were compared. RESULTS: The highest performing algorithm was "one hospitalization code OR (three physician claims codes at least 30 days apart in a two year period) OR a prescription filled for an AD-RD specific medication" with sensitivity 79.3% (confidence interval (CI) 72.9-85.8%), specificity 99.1% (CI 98.8-99.4%), positive predictive value 80.4% (CI 74.0-86.8%), and negative predictive value 99.0% (CI 98.7-99.4%). This resulted in an age- and sex-adjusted incidence of 18.1 per 1,000 persons and adjusted prevalence of 72.0 per 1,000 persons in 2010/11. CONCLUSION: Algorithms developed from health administrative data are sensitive and specific for identifying older adults with AD-RD.

Immunization Against Specific Fragments of Neurotrophin p75 Receptor Protects Forebrain Cholinergic Neurons in the Olfactory Bulbectomized Mice. - Bobkova, Natalia; Vorobyov, Vasily; Medvinskaya, Natalia; Nesterova, Inna; Tatarnikova, Olga; Nekrasov, Pavel; Samokhin, Alexander; Deev, Alexander; Sengpiel, Frank; Koroev, Dmitry; Volpina, Olga (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by progressive cognitive impairment associated with marked cholinergic neuron loss and amyloid-β (Aβ) peptide accumulation in the brain. The cytotoxicity in AD is mediated, at least in part, by Aβ binding with the extracellular domain of the p75 neurotrophin receptor (p75NTR), localized predominantly in the membranes of acetylcholine-producing neurons in the basal forebrain. Hypothesizing that an open unstructured loop of p75NTR might be the effective site for Aβ binding, we have immunized both olfactory bulbectomized (OBX) and sham-operated (SO) mice (n = 82 and 49, respectively) with synthetic peptides, structurally similar to different parts of the loops, aiming to block them by specific antibodies. OBX-mice have been shown in previous studies, and confirmed in the present one, to be characterized by typical behavioral, morphological, and biochemical AD hallmarks, including cholinergic deficits in forebrain neurons. Immunization of OBX- or SO-mice with KLH conjugated fragments of p75NTR induced high titers of specific serum antibodies for each of nine chosen fragments. However, maximal protective effects on spatial memory, evaluated in a Morris water maze, and on activity of choline acetyltransferase in forebrain neurons, detected by immunoreactivity to specific antibodies, were revealed only for peptides with amino acid residue sequences of 155-164 and 167-176. We conclude that the approach based on immunological blockade of specific p75NTR sites, linked with the cytotoxicity, is a useful and effective tool for study of AD-associated mechanisms and for development of highly selective therapy of cholinergic malfunctioning in AD patients.

Immunization with Small Amyloid-β-derived Cyclopeptide Conjugates Diminishes Amyloid-β-Induced Neurodegeneration in Mice. - Mulder, Cornelis K; Dong, Yun; Brugghe, Humphrey F; Timmermans, Hans A M; Tilstra, Wichard; Westdijk, Janny; van Riet, Elly; van Steeg, Harry; Hoogerhout, Peter; Eisel, Ulrich L M (J Alzheimers Dis, 2016)
BACKGROUND: Soluble oligomeric (misfolded) species of amyloid-β (Aβ) are the main mediators of toxicity in Alzheimer's disease (AD). These oligomers subsequently form aggregates of insoluble fibrils that precipitate as extracellular and perivascular plaques in the brain. Active immunization against Aβ is a promising disease modifying strategy. However, eliciting an immune response against Aβ in general may interfere with its biological function and was shown to cause unwanted side-effects. Therefore, we have developed a novel experimental vaccine based on conformational neo-epitopes that are exposed in the misfolded oligomeric Aβ, inducing a specific antibody response. OBJECTIVE: Here we investigate the protective effects of the experimental vaccine against oligomeric Aβ1-42-induced neuronal fiber loss in vivo. METHODS: C57BL/6 mice were immunized or mock-immunized. Antibody responses were measured by enzyme-linked immunosorbent assay. Next, mice received a stereotactic injection of oligomeric Aβ1-42 into the nucleus basalis of Meynert (NBM) on one side of the brain (lesion side), and scrambled Aβ1-42 peptide in the contralateral NBM (control side). The densities of choline acetyltransferase-stained cholinergic fibers origination from the NBM were measured in the parietal neocortex postmortem. The percentage of fiber loss in the lesion side was determined relative to the control side of the brain. RESULTS: Immunized responders (79%) showed 23% less cholinergic fiber loss (p = 0.01) relative to mock-immunized mice. Moreover, fiber loss in immunized responders correlated negatively with the measured antibody responses (R2 = 0.29, p = 0.02). CONCLUSION: These results may provide a lead towards a (prophylactic) vaccine to prevent or at least attenuate (early onset) AD symptoms.

Incidence and Duration of Cumulative Bisphosphonate Use among Community-Dwelling Persons with or without Alzheimer's Disease. - Tiihonen, Miia; Taipale, Heidi; Tanskanen, Antti; Tiihonen, Jari; Hartikainen, Sirpa (J Alzheimers Dis, 2016)
We studied the incidence and duration of cumulative bisphosphonate use among older Finnish women and men with or without Alzheimer's disease (AD). The MEDALZ-2005 cohort is a nationwide sample of all persons with clinically diagnosed AD on 31 December 2005 and their age-, gender-, and region of residence-matched control persons without AD. Information on bisphosphonate use by persons with an AD diagnosis and their controls without AD during 2002-2009 was obtained from the prescription register database containing reimbursed medications. A total of 6,041 (11.8%) persons used bisphosphonates during the 8-year follow-up. Bisphosphonates were more commonly used among persons without AD (n = 3121, 12.3%) than among persons with AD (n = 2,920, 11.2%) (p = 0.001). The median duration of bisphosphonate use was 743 days (IQR). Among persons with AD, the median duration of use was 777 days (IQR) and among persons without AD, 701 days (IQR) (p = 0.011). People without AD more often used bisphosphonate combination preparations including vitamin D than did people with AD (p <  0.0001). Bisphosphonate use was more common among people without AD who had comorbidities, asthma/COPD, or rheumatoid arthritis compared with users with AD. Short-term users were more likely to be male, at least 80 years old, and not having AD. Although the incidence of bisphosphonate use was slightly higher among persons without AD, the cumulative duration of bisphosphonate use was longer in persons with AD. Short-term use was associated with male gender, older age, and not having AD.

The Incidence of Benzodiazepine and Related Drug Use in Persons with and without Alzheimer's Disease. - Saarelainen, Laura; Taipale, Heidi; Koponen, Marjaana; Tanskanen, Antti; Tolppanen, Anna-Maija; Tiihonen, Jari; Hartikainen, Sirpa (J Alzheimers Dis, 2016)
BACKGROUND: Benzodiazepines and related drugs (BZDR) are occasionally used to treat certain symptoms of Alzheimer's disease (AD). However, the risks related to BZDR use are high in older persons. Although frequent BZDR use has been reported in persons with AD, no previous study has focused specifically on the incidence of BZDR use in this population. OBJECTIVE: We investigated the incidence of BZDR use in persons with and without AD during a five-year follow-up. METHODS: The Finnish nationwide, register-based MEDALZ cohort includes all AD cases who received a clinically verified AD diagnosis in 2005-2011 (n = 70,718) and their matched comparison persons. Incidence of BZDR, including benzodiazepines (lorazepam, oxazepam, temazepam, alprazolam, chlordiazepoxide, diazepam, and nitrazepam) and Z-drugs (zolpidem and zopiclone), use was investigated in the cohort from two years before to three years after the diagnosis of AD. Further, initial BZDRs were investigated. RESULTS: The incidence of BZDR use was higher in persons with AD starting from 12 months before the diagnosis and peaked at six months after the diagnosis of AD (incidence rate ratio [IRR] = 2.6, 95% confidence interval [CI] = 2.5-2.8). Benzodiazepines were more frequently initiated by persons with AD, with the incidence peaking at six months after the diagnosis (IRR = 4.5, 95% CI = 4.1-4.9) and remaining over three times higher than in comparison persons until three years after the diagnosis. CONCLUSION: Early symptomatic treatment with BZDRs is contrary to AD treatment guidelines. As BZDRs impair cognition, the observed early treatment with BZDRs may complicate the monitoring of AD treatment effectiveness.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Benzodiazepines; Cohort Studies; Female; Finland; Humans; Incidence; Male; Middle Aged; Substance-Related Disorders

Increased Intrinsic Activity of Medial-Temporal Lobe Subregions is Associated with Decreased Cortical Thickness of Medial-Parietal Areas in Patients with Alzheimer's Disease Dementia. - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Myers, Nicholas E; Ortner, Marion; Kurz, Alexander; Förstl, Hans; Zimmer, Claus; Grimmer, Timo; Akhrif, Atae; Wohlschläger, Afra M; Riedl, Valentin; et al. (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), disrupted connectivity between medial-parietal cortices and medial-temporal lobes (MTL) is linked with increased MTL local functional connectivity, and parietal atrophy is associated with increased MTL memory activation. We hypothesized that intrinsic activity in MTL subregions is increased and associated with medial-parietal degeneration and impaired memory in AD. To test this hypothesis, resting-state-functional and structural-MRI was assessed in 22 healthy controls, 22 mild cognitive impairment patients, and 21 AD-dementia patients. Intrinsic activity was measured by power-spectrum density of blood-oxygenation-level-dependent signal, medial-parietal degeneration by cortical thinning. In AD-dementia patients, intrinsic activity was increased for several right MTL subregions. Raised intrinsic activity in dentate gyrus and cornu ammonis 1 was associated with cortical thinning in posterior cingulate cortices, and at-trend with impaired delayed recall. Critically, increased intrinsic activity in the right entorhinal cortex was associated with ipsilateral posterior cingulate degeneration. Our results provide evidence that in AD, intrinsic activity in MTL subregions is increased and associated with medial-parietal atrophy. Results fit a model in which medial-parietal degeneration contributes to MTL dysconnectivity from medial-parietal cortices, potentially underpinning disinhibition-like changes in MTL activity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory Disorders; Middle Aged; Nerve Net; Parietal Lobe; Temporal Lobe

Increased Total Homocysteine Levels Predict the Risk of Incident Dementia Independent of Cerebral Small-Vessel Diseases and Vascular Risk Factors. - Miwa, Kaori; Tanaka, Makiko; Okazaki, Shuhei; Yagita, Yoshiki; Sakaguchi, Manabu; Mochizuki, Hideki; Kitagawa, Kazuo (J Alzheimers Dis, 2016)
BACKGROUND: Homocysteine has been identified as a potential risk factor for stroke, cerebral small-vessel diseases (SVD), and dementia. OBJECTIVE: The present study aimed to investigate the predictive value of homocysteine levels on incident dementia while simultaneously controlling for MRI findings and vascular risk factors. METHODS: Within a Japanese cohort of participants with vascular risk factors in an observational study, we evaluated the association between baseline total homocysteine (tHcy) levels (per 1 μmol/L and the tertile of tHcy), the prevalence of MRI-findings at baseline, and incident all-cause dementia. Baseline brain MRI was used to determine SVD (lacunas, white matter hyperintensities, and cerebral microbleeds [CMBs]) and atrophy (medial-temporal lobe atrophy and bicaudate ratio). Logistic regression analyses were used to estimate the cross-sectional association between tHcy and each of MRI findings. Cox proportional hazards analyses were performed to estimate the longitudinal association between tHcy and dementia. RESULTS: In the 643 subjects (age: 67.2 ± 8.4 years, male: 59% ; education: 12.9 ± 2.6 years), multivariable analyses adjusted for several potential confounders, including estimated glomerular filtration rate (eGFR) and intima-media thickness, showed that highest tHcy tertile was associated with lacunas, CMBs, and strictly deep CMBs. During the mean 7.3-year follow-up (range: 2-13), 47 patients were diagnosed with dementia (Alzheimer's disease: 24; vascular dementia: 18; mixed-type: 3; other: 2). After adjusting for age, gender, APOE ɛ4, education, BMI, MMSE, hypertension, cerebrovascular events, eGFR, and MRI-findings, tHcy level (hazard ratios [HR]: 1.08, p = 0.043) and the highest tertile of tHcy (HR: 2.50, p = 0.047) for all-cause dementia remained significant. CONCLUSIONS: Our results provide additional evidence of tHcy that contributes to increased susceptibility to dementia risk.
Keywords: Aged; Carotid Intima-Media Thickness; Cerebral Small Vessel Diseases; Dementia; Female; Homocysteine; Humans; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Predictive Value of Tests; Proportional Hazards Models; Risk Factors; Statistics, Nonparametric

Insight into the Dissociation of Behavior from Histology in Synucleinopathies and in Related Neurodegenerative Diseases. - Sekiyama, Kazunari; Takamatsu, Yoshiki; Koike, Wakako; Waragai, Masaaki; Takenouchi, Takato; Sugama, Shuei; Hashimoto, Makoto (J Alzheimers Dis, 2016)
Recent clinical trials using immunization approaches against Alzheimer's disease (AD) have failed to demonstrate improved cognitive functions in patients, despite potent suppression in the formation of both senile plaques and other amyloid-β deposits in postmortem brains. Similarly, we observed that treatment with ibuprofen, a non-steroidal anti-inflammatory drug, was effective in improving the histopathology, such as reducing both protein aggregation and glial activation, in the brains of transgenic mice expressing dementia with Lewy bodies-linked P123H β-synuclein. In contrast, only a small improvement in cognitive functions was observed in these mice. Collectively, it is predicted that histology does not correlate with behavior that is resilient and resistant to therapeutic stimuli. Notably, such a 'discrepancy between histology and behavior' is reminiscent of AD-like pathologies and incidental Lewy bodies, which are frequently encountered in postmortem brains of the elderly who had been asymptomatic for memory loss and Parkinsonism during their lives. We suggest that 'the discrepancy between histology and behavior' may be a universal feature that is associated with various aspects of neurodegenerative diseases. Furthermore, given that the cognitive reserve is specifically observed in human brains, human behavior may be evolutionally distinct from that in other animals, thus, contributing to the differential efficiency of therapy between human and lower animals, an important issue in the therapy of neurodegenerative diseases. Overall, it is important to better understand 'the discrepancy between histology and behavior' in the mechanism of neurodegeneration for the development of effective therapies against neurodegenerative diseases.

Integrating Biomarkers for Underlying Alzheimer's Disease in Mild Cognitive Impairment in Daily Practice: Comparison of a Clinical Decision Support System with Individual Biomarkers. - Rhodius-Meester, Hanneke F M; Koikkalainen, Juha; Mattila, Jussi; Teunissen, Charlotte E; Barkhof, Frederik; Lemstra, Afina W; Scheltens, Philip; Lötjönen, Jyrki; van der Flier, Wiesje M (J Alzheimers Dis, 2016)
BACKGROUND: Recent criteria allow biomarkers to provide evidence of Alzheimer's disease (AD) pathophysiology. How they should be implemented in daily practice remains unclear, especially in mild cognitive impairment (MCI) patients. OBJECTIVE: We evaluated how a clinical decision support system such as the PredictAD tool can aid clinicians to integrate biomarker evidence to support AD diagnosis. METHODS: With available data on demographics, cerebrospinal fluid (CSF), and MRI, we trained the PredictAD tool on a reference population of 246 controls and 491 AD patients. We then applied the identified algorithm to 211 MCI patients. For comparison, we also classified patients based on individual biomarkers (MRI; CSF) and the NIA-AA criteria. Progression to dementia was used as outcome measure. RESULTS: After a median follow up of 3 years, 72 (34%) MCI patients remained stable and 139 (66%) progressed to AD. The PredictAD tool assigned a likelihood of underlying AD to each patient (AUC 0.82). Excluding patients with missing data resulted in an AUC of 0.87. According to the NIA-AA criteria, half of the MCI patients had uninformative biomarkers, precluding an assignment of AD likelihood. A minority (41%) was assigned to high or low AD likelihood with good predictive value. The individual biomarkers showed best value for CSF total tau (AUC 0.86). CONCLUSION: The ability of the PredictAD tool to identify AD pathophysiology was comparable to individual biomarkers. The PredictAD tool has the advantage that it assigns likelihood to all patients, regardless of missing or conflicting data, allowing clinicians to integrate biomarker data in daily practice.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Cohort Studies; Decision Support Systems, Clinical; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Outcome Assessment (Health Care); Predictive Value of Tests

Intranasal Administration of a Polyethylenimine-Conjugated Scavenger Peptide Reduces Amyloid-β Accumulation in a Mouse Model of Alzheimer's Disease. - Lin, Chih-Yun; Cheng, Yu-Sung; Liao, Tai-Yan; Lin, Chen; Chen, Zih-Ten; Twu, Woan-Ing; Chang, Chi-Wei; Tan, David Tat-Wei; Liu, Ren-Shyan; Tu, Pang-Hsien; Chen, Rita P-Y (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) aggregation in the brain plays a central and initiatory role in pathogenesis and/or progression of Alzheimer's disease (AD). Inhibiting Aβ aggregation is a potential strategy in the prevention of AD. A scavenger peptide, V24P(10-40), designed to decrease Aβ accumulation in the brain, was conjugated to polyethylenimine (PEI) and tested as a preventive/therapeutic strategy for AD in this study. This PEI-conjugated V24P(10-40) peptide was delivered intranasally, as nasal drops, to four-month-old APP/PS1 double transgenic mice for four or eight months. Compared with control values, peptide treatment for four months significantly reduced the amount of GdnHCl-extracted Aβ40 and Aβ42 in the mice's hippocampus and cortex. After treatment for eight months, amyloid load, as quantified by Pittsburgh compound B microPET imaging, was significantly decreased in the mice's hippocampus, cortex, amygdala, and olfactory bulb. Our data suggest that this intranasally delivered scavenger peptide is effective in decreasing Aβ accumulation in the brain of AD transgenic mice. Nasal application of peptide drops is easy to use and could be further developed to prevent and treat AD.

Life's Simple 7's Cardiovascular Health Metrics are Associated with Hispanic/Latino Neurocognitive Function: HCHS/SOL Results. - González, Hector M; Tarraf, Wassim; Gouskova, Natalia; Rodríguez, Carlos J; Rundek, Tatjana; Grober, Ellen; Pirzada, Amber; González, Patricia; Lutsey, Pamela L; Camacho, Alvaro; Daviglus, Martha L; Wright, Clinton; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Hispanics/Latinos are purportedly at increased risk for neurocognitive decline and dementias. Without dementia cures, low-cost, well-tolerated public health means for mitigating neurocognitive decline are needed. OBJECTIVE: We examined associations between neurocognition and cardiovascular health (CVH) metrics (Life's Simple 7; LS7) among diverse Hispanics/Latinos. We hypothesized that higher LS7 would be associated with healthier brain function (neurocognitive performance). METHODS: We used baseline (2008-2011) Hispanic Community Health Study/Study of Latinos (HCHS/SOL; N = 9,623; ages 45-74 years) to examine neurocognition in relation to CVH LS7 scores. RESULTS: In age and sex adjusted models, a one unit LS7 score increase (range = 0-14) was associated with higher neurocognitive function on the B-SEVLT sum (0.23 [p < 0.01]; range = 3-42), B-SEVLT recall (0.12 [p < 0.01]; range = 0-15), Word Fluency (phonemic; 0.46 (p < 0.01); range = 0-49), and Digit Symbol Substitution (0.49 (p < 0.01); range = 0-83) tests, respectively. Stated differently, a change from the minimum LS7 (0) to maximum LS7 (14) score corresponded to higher scores on verbal learning (4.62) and memory (2.24), verbal fluency (7.0), and psychomotor processing speed (12). In fully adjusted models the associations were attenuated, but remained statistically significant. Incremental adjustments indicated that Latino background and, to a lesser extent, education were primary contributors to the evinced attenuations. CONCLUSIONS: We found that higher neurocognitive function was associated with better LS7 CVH metrics among middle-aged and older Hispanics/Latinos. Associations between neurocognitive function and LS7 were strongest among two at-risk groups for neurocognitive decline and dementia, women and Hispanics/Latinos with lower education. Public health efforts to reduce cardiovascular disease morbidity and mortality may have additional neurocognitive benefits among at-risk Hispanics/Latinos.

Limiting Factors of Brain Donation in Neurodegenerative Diseases: The Example of French Memory Clinics. - Le Bouc, Raphael; Marelli, Cecilia; Beaufils, Emilie; Berr, Claudine; Hommet, Caroline; Touchon, Jacques; Pasquier, Florence; Deramecourt, Vincent (J Alzheimers Dis, 2016)
Postmortem neuropathological examination of the brain is essential in neurodegenerative diseases, to ensure accurate diagnosis, to obtain an a posteriori critical assessment of the adequacy of clinical care, and to validate new biomarkers, but is only rarely performed. The purpose of this study was to assess factors limiting brain donation, such as reluctance of physicians to seek donation consent, opposition from patients and families, and organizational constraints. We conducted a survey across French memory clinics and major neuropathological centers. Few postmortem examinations were performed annually, as less than one third of the centers had performed at least five autopsies, and 41% had performed none. The main limiting factor was the lack of donation requests made by physicians, as half of them never approach patients for brain donation. Reasons for not seeking donation consent often include discomfort broaching the subject and lack of awareness of the medical and scientific benefit of postmortems (77%), organizational constraints (61%), and overestimation of families' negative reaction (51%). Family refusals represented a second major obstacle, and were often caused by misconceptions. Identifying and addressing these biases early could help improve physicians' rate of making requests and the public's awareness about the importance of brain donation.
Keywords: Autopsy; Brain; France; Health Knowledge, Attitudes, Practice; Humans; Neurodegenerative Diseases; Physicians; Retrospective Studies

Living Alone with Dementia: Prevalence, Correlates and the Utilization of Health and Nursing Care Services. - Eichler, Tilly; Hoffmann, Wolfgang; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Dreier, Adina; Thyrian, Jochen René (J Alzheimers Dis, 2016)
BACKGROUND: Little is known about the proportion and the characteristics of community-dwelling people with dementia (PWD) living alone in Germany. OBJECTIVES: To analyze the prevalence of PWD living alone (with and without the support of an informal caregiver) and socio-demographical and clinical characteristics as well as health and nursing care utilization associated with living alone. METHODS: DelpHi-MV (Dementia: Life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, randomized controlled intervention trial. The present analyses are based on baseline data of 511 patients (≥70 years, community-dwelling) who had screened positive for dementia (DemTect <9). RESULTS: N = 251 (51%) of the patients lived alone. PWD living alone were statistically significantly more often female, older, and more often widowed than those not living alone. About 9% of the patients (n = 24) were not supported by any informal caregiver. Regarding the clinical variables (cognitive and functional impairment, depression, falls, number of drug-related problems, malnutrition, quality of life), there were no statistically significant group differences. Patients living alone utilized professional services such as home care, help with medication, home-delivered meals, or housekeeping assistance significantly more often. Multivariate analyses confirmed these findings. CONCLUSION: Our results reveal the high proportion of PWD living alone in Germany. PWD living alone did not seem to be at an increased health risk. Our findings indicate that living alone with dementia is possible. In order to ensure the sufficient provision of health and nursing care services for PWD living alone, providers should consider the present results for future planning.

The Longitudinal Association Between a Discrepancy Measure of Anosognosia in Patients with Dementia, Caregiver Burden and Depression. - Perales, Jaime; Turró-Garriga, Oriol; Gascón-Bayarri, Jordi; Reñé-Ramírez, Ramón; Conde-Sala, Josep Lluís (J Alzheimers Dis, 2016)
BACKGROUND: According to cross-sectional studies, there is an association between anosognosia in people with dementia and caregiver's burden and depression. Anosognosia in patients may be a cause of caregiver burden and depression. However, variability in caregiver anosognosia ratings may exist as caregivers with burden and depression may have a more pessimistic view of the patients' health. OBJECTIVE: To assess the variability of caregiver anosognosia ratings of patients with dementia using a widely used anosognosia scale and its longitudinal relationship with caregiver burden and depression. METHODS: A convenience cohort of 221 consecutive dementia outpatient and caregiver dyads was followed up at 12 and 24 months. The main instruments used were the Anosognosia Questionnaire-Dementia (AQ-D), Caregiver Burden Interview, and Geriatric Depression Scale. Linear mixed models were used including time as a factor in every model. Multivariate analyses controlled for caregiver's socio-demographic and possible confounding factors. RESULTS: Attrition at 12 and 24 months was 24.9% and 42.5% respectively. Patients at baseline were on average 77.8 years of age, 63.3% were women, and 63.3% had < 5 years of education. In the bivariate analyses, caregiver burden, depression, and gender were associated with caregiver ratings of total, cognitive, and personality AQ-D of the patient at different time points. Multivariate analyses revealed burden as the caregiver variable most consistently associated with total, cognitive, and personality caregiver AQ-D ratings of the patient. CONCLUSION: Some caregiver characteristics, especially burden, are associated with caregiver ratings of AQ-D with regard to the patient.

Longitudinal Changes in Functional Brain Connectivity Predicts Conversion to Alzheimer's Disease. - Serra, Laura; Cercignani, Mara; Mastropasqua, Chiara; Torso, Mario; Spanò, Barbara; Makovac, Elena; Viola, Vanda; Giulietti, Giovanni; Marra, Camillo; Caltagirone, Carlo; Bozzali, Marco (J Alzheimers Dis, 2016)
This longitudinal study investigates the modifications in structure and function occurring to typical Alzheimer's disease (AD) brains over a 2-year follow-up, from pre-dementia stages of disease, with the aim of identifying biomarkers of prognostic value. Thirty-one patients with amnestic mild cognitive impairment were recruited and followed-up with clinical, neuropsychological, and MRI assessments. Patients were retrospectively classified as AD Converters or Non-Converters, and the data compared between groups. Cross-sectional MRI data at baseline, assessing volume and functional connectivity abnormalities, confirmed previous findings, showing a more severe pattern of regional grey matter atrophy and default-mode network disconnection in Converters than in Non-Converters. Longitudinally, Converters showed more grey matter atrophy in the frontotemporal areas, accompanied by increased connectivity in the precuneus. Discriminant analysis revealed that functional connectivity of the precuneus within the default mode network at baseline is the parameter able to correctly classify patients in Converters and Non-Converters with high sensitivity, specificity, and accuracy.
Keywords: Aged; Alzheimer Disease; Atrophy; Brain; Brain Mapping; Cognitive Dysfunction; Cross-Sectional Studies; Discriminant Analysis; Disease Progression; Female; Follow-Up Studies; Gray Matter; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neural Pathways; Neuropsychological Tests; Prognosis; Rest

Longitudinal Protein Changes in Blood Plasma Associated with the Rate of Cognitive Decline in Alzheimer's Disease. - Sattlecker, Martina; Khondoker, Mizanur; Proitsi, Petroula; Williams, Stephen; Soininen, Hilkka; Kłoszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Dobson, Richard Jb (J Alzheimers Dis, 2016)
Biomarkers of Alzheimer's disease (AD) progression are needed to support the development of urgently needed disease modifying drugs. We employed a SOMAscan assay for quantifying 1,001 proteins in blood samples from 90 AD subjects, 37 stable mild cognitive impaired (MCI) subjects, 39 MCI subjects converting to AD within a year and 69 controls at baseline and one year follow up. We used linear mixed effects models to identify proteins changing significantly over one year with the rate of cognitive decline, which was quantified as the reduction in Mini Mental State Examination (MMSE) scores. Additionally, we investigated proteins changing differently across disease groups and during the conversion from MCI to AD. We found that levels of proteins belonging to the complement cascade increase significantly in fast declining AD patients. Longitudinal changes in the complement cascade might be a surrogate biomarker for disease progression. We also found that members of the cytokine-cytokine receptor interaction pathway change during AD when compared to healthy aging subjects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Cognition; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Linear Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests

Longitudinal Relationships between Caloric Expenditure and Gray Matter in the Cardiovascular Health Study. - Raji, Cyrus A; Merrill, David A; Eyre, Harris; Mallam, Sravya; Torosyan, Nare; Erickson, Kirk I; Lopez, Oscar L; Becker, James T; Carmichael, Owen T; Gach, H Michael; Thompson, Paul M; Longstreth, W T; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Physical activity (PA) can be neuroprotective and reduce the risk for Alzheimer's disease (AD). In assessing physical activity, caloric expenditure is a proxy marker reflecting the sum total of multiple physical activity types conducted by an individual. OBJECTIVE: To assess caloric expenditure, as a proxy marker of PA, as a predictive measure of gray matter (GM) volumes in the normal and cognitively impaired elderly persons. METHODS: All subjects in this study were recruited from the Institutional Review Board approved Cardiovascular Health Study (CHS), a multisite population-based longitudinal study in persons aged 65 and older. We analyzed a sub-sample of CHS participants 876 subjects (mean age 78.3, 57.5% F, 42.5% M) who had i) energy output assessed as kilocalories (kcal) per week using the standardized Minnesota Leisure-Time Activities questionnaire, ii) cognitive assessments for clinical classification of normal cognition, mild cognitive impairment (MCI), and AD, and iii) volumetric MR imaging of the brain. Voxel-based morphometry modeled the relationship between kcal/week and GM volumes while accounting for standard covariates including head size, age, sex, white matter hyperintensity lesions, MCI or AD status, and site. Multiple comparisons were controlled using a False Discovery Rate of 5 percent. RESULTS: Higher energy output, from a variety of physical activity types, was associated with larger GM volumes in frontal, temporal, and parietal lobes, as well as hippocampus, thalamus, and basal ganglia. High levels of caloric expenditure moderated neurodegeneration-associated volume loss in the precuneus, posterior cingulate, and cerebellar vermis. CONCLUSION: Increasing energy output from a variety of physical activities is related to larger gray matter volumes in the elderly, regardless of cognitive status.

Low Prevalence of Mixed Dementia in a Cohort of 2,000 Elderly Patients in a Memory Clinic Setting. - Claus, Jules J; Staekenborg, Salka S; Roorda, Jelmen J; Stevens, Martijn; Herderschee, Dirk; van Maarschalkerweerd, Willy; Schuurmans, Lilly; Tielkes, Caroline E M; Koster, Pieter; Bavinck, Chris; Scheltens, Philip (J Alzheimers Dis, 2016)
BACKGROUND: It is generally assumed that with increasing age, pathology in clinically diagnosed Alzheimer's disease (AD) becomes more mixed, i.e., co-existence of amyloid plaques and cerebrovascular pathology. OBJECTIVE: To test the hypothesis of increasing prevalence of mixed dementia in late-onset clinically diagnosed Alzheimer's disease (AD) in a single-center memory clinic population. METHODS: Patients included had diagnoses of AD (n = 832), subjective cognitive impairment (SCI, n = 333), mild cognitive impairment (MCI, n = 492), vascular dementia (VaD, n = 57), other dementia (n = 53), or other diagnosis (n = 233). Prevalence of severe white matter lesions (WML) was defined as a score of 2 or higher on the Fazekas-scale on brain computed tomography to classify AD patients as having mixed dementia. We examined the effect of age on WML using multiple linear regression analysis, and AD patients were compared to SCI to determine the effect of disease on WML. RESULTS: Prevalence of severe WML was 33.6% in AD patients (mixed dementia), 11.4% in SCI, 22.7% in MCI, 75.4% in VaD, 3.8% in other dementia, and 15.5% in other diagnosis. With increasing age there was a significant and similar increase of WML scores in SCI, MCI, AD, other dementia, and other diagnosis, indicating no effect modification by AD. The difference between AD patients and SCI averaged 0.16 on the WML score and difference in percentage severe WML between AD and SCI patients was 15% across all ages. CONCLUSION: We found a low prevalence of mixed dementia. Furthermore, severe WML in AD was largely explained by age rather than effect of disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Prevalence; Regression Analysis; Risk Factors; Tomography Scanners, X-Ray Computed

Lower Prevalence of Alzheimer's Disease among Tibetans: Association with Religious and Genetic Factors. - Huang, Fukai; Shang, Ying; Luo, Yuandai; Wu, Peng; Huang, Xue; Tan, Xiaohui; Lu, Xingyi; Zhen, Lifang; Hu, Xianda (J Alzheimers Dis, 2016)
BACKGROUND: The prevalence of dementia differs among racial groups, the highest prevalence being in Latin America (8.5%) compared to sub-Saharan African regions (2-4%). The most common type of dementia is Alzheimer's disease (AD). OBJECTIVE: To estimate the prevalence of AD in the Qinghai-Tibet plateau and to investigate the related factors. METHODS: This was a cross-sectional, multistage cluster sampling design survey. Data was collected from May 2014 to September 2014 from 4,060 Tibetan aged >60 years. Participants underwent clinical examinations and neuropsychological evaluations. MALDI-TOF was used to test the genotypes of CLU, TFAM, TP53INP1, IGHV1-67, CR1, ApoE, and BIN1. Logistic regression models were used to ascertain the associations with AD. RESULTS: The prevalence of AD among Tibetan individuals aged >60 years was 1.33% (95% CI: 0.98-1.69). The CLU haplotypes AA+GA (odds ratio (OR) = 4.483; 95% CI: 1.069-18.792) of rs2279590 was correlated with AD. The CLU haplotypes GG+GC (OR = 0.184; 95% CI: 0.038-0.888) of rs9331888 and kowtow (OR = 0.203; 95% CI 0.046-0.896) were negatively correlated with AD. CONCLUSION: A low prevalence of AD was found in Tibetans from the Qinghai-Tibet plateau. Multivariate analysis might suggest that regular "mind-body" religious meditative activities may be negatively associated with AD in this population, as well as the CLU genotype at rs9331888.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Clusterin; Cognition Disorders; Cross-Sectional Studies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Psychiatric Status Rating Scales; Religion; Risk Factors; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Tibet

MAPT H1 Haplotype is Associated with Late-Onset Alzheimer's Disease Risk in APOEɛ4 Noncarriers: Results from the Dementia Genetics Spanish Consortium. - Pastor, Pau; Moreno, Fermín; Clarimón, Jordi; Ruiz, Agustin; Combarros, Onofre; Calero, Miguel; López de Munain, Adolfo; Bullido, Maria J; de Pancorbo, Marian M; Carro, Eva; Antonell, Anna; Coto, Eliecer; et al. (J Alzheimers Dis, 2016)
The MAPT H1 haplotype has been linked to several disorders, but its relationship with Alzheimer's disease (AD) remains controversial. A rare variant in MAPT (p.A152T) has been linked with frontotemporal dementia (FTD) and AD. We genotyped H1/H2 and p.A152T MAPT in 11,572 subjects from Spain (4,327 AD, 563 FTD, 648 Parkinson's disease (PD), 84 progressive supranuclear palsy (PSP), and 5,950 healthy controls). Additionally, we included 101 individuals from 21 families with genetic FTD. MAPT p.A152T was borderline significantly associated with FTD [odds ratio (OR) = 2.03; p = 0.063], but not with AD. MAPT H1 haplotype was associated with AD risk (OR = 1.12; p = 0.0005). Stratification analysis showed that this association was mainly driven by APOE ɛ4 noncarriers (OR = 1.14; p = 0.0025). MAPT H1 was also associated with risk for PD (OR = 1.30; p = 0.0003) and PSP (OR = 3.18; p = 8.59 × 10-8) but not FTD. Our results suggest that the MAPT H1 haplotype increases the risk of PD, PSP, and non-APOE ɛ4 AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Frontotemporal Dementia; Genetic Predisposition to Disease; Haplotypes; Humans; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Spain; tau Proteins

Measuring Information Processing Speed in Mild Cognitive Impairment: Clinical Versus Research Dichotomy. - Haworth, Judy; Phillips, Michelle; Newson, Margaret; Rogers, Peter J; Torrens-Burton, Anna; Tales, Andrea (J Alzheimers Dis, 2016)
A substantial body of research evidence is indicative of disproportionately slowed information processing speed in a wide range of multi-trial, computer-based, neuroimaging- and electroencephalography-based reaction time (RT) tests in Alzheimer's disease and mild cognitive impairment (MCI). However, in what is arguably a dichotomy between research evidence and clinical practice, RT associated with different brain functions is rarely assessed as part of their diagnosis. Indeed, often only the time taken to perform a single, specific task, commonly the Trail making test (TMT), is measured. In clinical practice therefore, there can be a failure to assess adequately the integrity of the rapid, serial information processing and response, necessary for efficient, appropriate, and safe interaction with the environment. We examined whether a typical research-based RT task could at least match the TMT in differentiating amnestic MCI (aMCI) from cognitively healthy aging at group level. As aMCI is a heterogeneous group, typically containing only a proportion of individuals for whom aMCI represents the early stages of dementia, we examined the ability of each test to provide intra-group performance variation. The results indicate that as well as significant slowing in performance of the operations involved in TMT part B (but not part A), individuals with aMCI also experience significant slowing in RT compared to controls. The results also suggest that research-typical RT tests may be superior to the TMT in differentiating between cognitively healthy aging and aMCI at group level and in revealing the performance variability one would expect from an etiologically heterogeneous disorder such as aMCI.
Keywords: Aged; Aged, 80 and over; Attention; Cognitive Dysfunction; Electroencephalography; Female; Humans; Male; Mental Processes; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Photic Stimulation; Reaction Time; Residence Characteristics

Memory Impairment at Initial Clinical Presentation in Posterior Cortical Atrophy. - Ahmed, Samrah; Baker, Ian; Husain, Masud; Thompson, Sian; Kipps, Christopher; Hornberger, Michael; Hodges, John R; Butler, Christopher R (J Alzheimers Dis, 2016)
Posterior cortical atrophy (PCA) is characterized by core visuospatial and visuoperceptual deficits, and predominant atrophy in the parieto-occipital cortex. The most common underlying pathology is Alzheimer's disease (AD). Existing diagnostic criteria suggest that episodic memory is relatively preserved. The aim of this study was to examine memory performance at initial clinical presentation in PCA, compared to early-onset AD patients (EOAD). 15 PCA patients and 32 EOAD patients, and 34 healthy controls were entered into the study. Patients were tested on the Addenbrooke's Cognitive Examination (ACE-R), consisting of subscales in memory and visuospatial skills. PCA and EOAD patients were significantly impaired compared to controls on the ACE total score (p < 0.001), visuospatial skills (p < 0.001), and memory (p < 0.001). Consistent with the salient diagnostic deficits, PCA patients were significantly more impaired on visuospatial skills compared to EOAD patients (p < 0.001). However, there was no significant difference between patient groups in memory. Further analysis of learning, recall, and recognition components of the memory subscale showed that EOAD and PCA patients were significantly impaired compared to controls on all three components (p < 0.001), however, there was no significant difference between EOAD and PCA patients. The results of this study show that memory is impaired in the majority of PCA patients at clinical presentation. The findings suggest that memory impairment must be considered in assessment and management of PCA. Further study into memory in PCA is warranted, since the ACE-R is a brief screening tool and is likely to underestimate the presence of memory impairment.

Moving from the Dish to the Clinical Practice: A Decade of Lessons and Perspectives from the Pre-Clinical and Clinical Stem Cell Studies for Alzheimer's Disease. - Salem, Haitham; Rocha, Natalia Pessoa; Colpo, Gabriela Delevati; Teixeira, Antonio Lucio (J Alzheimers Dis, 2016)
To date, there is no definitive treatment for Alzheimer's disease (AD). The realm of stem cells is very promising in regenerative medicine, particularly neurodegenerative disorders. Various types of stem cells have been used in multiple trials on AD models, trying to find an innovative management of this disease. In this systematic review, we trace the published preclinical and clinical data throughout the last decade, to show how much knowledge we gained so far in this field and the future perspectives of stem cells in AD treatment.

Naphthoquinone-Tryptophan Hybrid Inhibits Aggregation of the Tau-Derived Peptide PHF6 and Reduces Neurotoxicity. - Frenkel-Pinter, Moran; Tal, Sharon; Scherzer-Attali, Roni; Abu-Hussien, Malak; Alyagor, Idan; Eisenbaum, Tal; Gazit, Ehud; Segal, Daniel (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD), are a group of disorders characterized neuropathologically by intracellular toxic accumulations of abnormal protein aggregates formed by misfolding of the microtubule-associated protein tau. Since protein self-assembly appears to be an initial key step in the pathology of this group of diseases, intervening in this process can be both a prophylactic measure and a means for modifying the course of the disease for therapeutic purposes. We and others have shown that aromatic small molecules can be effective inhibitors of aggregation of various protein assemblies, by binding to the aromatic core in aggregation-prone motifs and preventing their self-assembly. Specifically, we have designed a series of small aromatic naphthoquinone-tryptophan hybrid molecules as candidate aggregation inhibitors of β -sheet based assembly and demonstrated their efficacy toward inhibiting aggregation of the amyloid-β peptide, another culprit of AD, as well as of various other aggregative proteins involved in other protein misfolding diseases. Here we tested whether a leading naphthoquinone-tryptophan hybrid molecule, namely NQTrp, can be repurposed as an inhibitor of the aggregation of the tau protein in vitro and in vivo. We show that the molecule inhibits the in vitro assembly of PHF6, the aggregation-prone fragment of tau protein, reduces hyperphosphorylated tau deposits and ameliorates tauopathy-related behavioral defect in an established transgenic Drosophila model expressing human tau. We suggest that NQTrp, or optimized versions of it, could act as novel disease modifying drugs for AD and other tauopathies.
Keywords: Animals; Carrier Proteins; Disease Models, Animal; Drosophila; Drosophila Proteins; Eye; Female; Humans; Immunoprecipitation; In Vitro Techniques; Larva; Locomotion; Mice, Transgenic; Microscopy, Electron, Scanning; Naphthoquinones; Neurotoxicity Syndromes; Protein Aggregates; Retinal Pigments; tau Proteins; Tryptophan

National Trends in Outpatient Antihypertensive Prescribing in People with Dementia in the United States. - Tan, Edwin C K; Bell, J Simon; Lu, Christine Y; Toh, Sengwee (J Alzheimers Dis, 2016)
OBJECTIVE: The objectives were to investigate national trends in outpatient antihypertensive prescribing in people with dementia in the United States between 2006 and 2012, and to investigate clinical and demographic factors associated with different antihypertensive prescribing patterns. METHODS: This was an analysis of the National Ambulatory Medical Care Survey (NAMCS) and the outpatient department component of the National Hospital Ambulatory Medical Care Survey (NHAMCS). Outpatient visits by people aged ≥65 years with documented dementia were analyzed. Complex samples multivariate logistic regression was conducted to estimate temporal trends and adjusted odds ratios (AORs) with 95% confidence intervals (CIs) for factors associated with prescribing of antihypertensives, multiple antihypertensives and different antihypertensive classes. RESULTS: There was a statistically significant increase in the proportion of physician visits by older people with dementia with a documented diagnosis of hypertension from 49.3% (95% CI: 41.3% -57.4%) in 2006 to 55.7% (95% CI: 50.2% -61.2%) in 2012. There were non-significant increases in overall antihypertensive use and the use of multiple antihypertensive classes. Male sex was associated with any antihypertensive use (AOR 1.37, 95% CI 1.02-1.84) and multiple antihypertensive class use (AOR 1.52, 95% CI 1.14-2.04). Black race (AOR 2.04, 95% CI 1.12-3.71) and Midwest residence (AOR 2.03, 95% CI 1.46-2.82) were associated with multiple antihypertensive use. CONCLUSION: There was an increase in documented hypertension in physician visits by older people with dementia from 2006 to 2012, but minimal increases in overall antihypertensive use. Various demographic and clinical factors were associated with the prescribing of antihypertensives in people with dementia.

Neurophysiological assessment of Alzheimer's disease individuals by a single electroencephalographic marker. - Lizio, Roberta; Del Percio, Claudio; Marzano, Nicola; Soricelli, Andrea; Yener, Görsev G; Başar, Erol; Mundi, Ciro; De Rosa, Salvatore; Triggiani, Antonio Ivano; Ferri, Raffaele; Arnaldi, Dario; Nobili, Flavio Mariano; et al. (J Alzheimers Dis, 2016)
Here we presented a single electroencephalographic (EEG) marker for a neurophysiological assessment of Alzheimer's disease (AD) patients already diagnosed by current guidelines. The ability of the EEG marker to classify 127 AD individuals and 121 matched cognitively intact normal elderly (Nold) individuals was tested. Furthermore, its relationship to AD patients' cognitive status and structural brain integrity was examined. Low-resolution brain electromagnetic tomography (LORETA) freeware estimated cortical sources of resting state eyes-closed EEG rhythms. The EEG marker was defined as the ratio between the activity of parieto-occipital cortical sources of delta (2-4 Hz) and low-frequency alpha (8-10.5 Hz) rhythms. Results showed 77.2% of sensitivity in the recognition of the AD individuals; 65% of specificity in the recognition of the Nold individuals; and 0.75 of area under the receiver-operating characteristic curve. Compared to the AD subgroup with the EEG maker within one standard deviation of the Nold mean (EEG-), the AD subgroup with EEG+ showed lower global cognitive status, as revealed by Mini-Mental State Evaluation score, and more abnormal values of white-matter and cerebrospinal fluid normalized volumes, as revealed by structural magnetic resonance imaging. We posit that cognitive and functional status being equal, AD patients with EEG+ should receive special clinical attention due to a neurophysiological "frailty". EEG+ label can be also used in clinical trials (i) to form homogeneous groups of AD patients diagnosed by current guidelines and (ii) as end-point to evaluate intervention effects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain Mapping; Case-Control Studies; Cognition Disorders; Electroencephalography; Female; Humans; Italy; Magnetic Resonance Imaging; Male; Middle Aged; Occipital Lobe; Rest; ROC Curve; Turkey

Neuropsychological Features of Microbleeds and Cortical Microinfarct Detected by High Resolution Magnetic Resonance Imaging. - Ueda, Yukito; Satoh, Masayuki; Tabei, Ken-Ichi; Kida, Hirotaka; Ii, Yuichiro; Asahi, Masaru; Maeda, Masayuki; Sakuma, Hajime; Tomimoto, Hidekazu (J Alzheimers Dis, 2016)
BACKGROUND: Lobar microbleeds (MBs) and cortical microinfarct (CMI) are caused by cerebral amyloid angiopathy in the elderly and increase in number in Alzheimer's disease. OBJECTIVE: The aim of this study is to elucidate the effects of lobar MBs and CMIs on cognitive function. METHODS: The subjects were outpatients who visited the memory clinic of Mie University Hospital. Among 120 subjects, 109 patients fulfilled the inclusion criteria. We quantitatively estimated MBs and CMIs using double inversion recovery and 3D FLAIR images of 3T MRI. Neuropsychological assessments included intellectual, memory, constructional, and frontal lobe function. RESULTS: Of the 109 patients, MBs and CMIs were observed in 68 (62%) and 17 (16%) subjects, respectively. Of the 68 patients with MBs, lobar MBs were found in 28, deep MBs in 8 and mixed MBs in 31. In each age group, the number of MBs increased in patients with CMI (CMI+ group) than those without CMI (CMI- group), and MBs and CMIs additively decreased MMSE scores. In psychological screens, the MBs+ group with more than 10 MBs showed significantly lower scores of category- and letter-WF than MB- group. The CMI+ group showed significantly worse scores than CMI- group in Japanese Raven's coloured progressive matrices, Trail Making Test-A, category- and letter-word fluency and copy and drawing of figures. CONCLUSION: Lobar MBs and CMIs in the elderly frequently coexisted with each other and additively contributed to cognitive impairment, which is mainly predisposed to frontal lobe function.

Neuropsychological Markers of Medial Perirhinal and Entorhinal Cortex Functioning are Impaired Twelve Years Preceding Diagnosis of Alzheimer's Dementia. - Hirni, Daniela I; Kivisaari, Sasa L; Krumm, Sabine; Monsch, Andreas U; Berres, Manfred; Oeksuez, Fatma; Reinhardt, Julia; Ulmer, Stephan; Kressig, Reto W; Stippich, Christoph; Taylor, Kirsten I (J Alzheimers Dis, 2016)
Neurofibrillary pathology in Alzheimer's dementia (AD) is associated with cognitive impairments and cortical thinning, and begins in medial perirhinal cortex (mPRC) before entering entorhinal cortex (ERC). Thus, mPRC dysfunction (e.g., semantic object memory impairments) may predate or accompany ERC (i.e., episodic memory) dysfunction in the preclinical course of typical AD. We developed formulae estimating mPRC and ERC integrity (i.e., cortical thickness) using common neuropsychological tests in 31 healthy individuals and 58 early AD patients. These formulae estimated the longitudinal courses of mPRC and ERC functioning in independent groups of 28 optimally healthy individuals who developed AD (NC-AD) over 2.8-13.4 years and 28 pairwise-matched, stable, healthy individuals (NC-NC). Mixed models demonstrated significantly worse NC-AD than NC-NC estimated mPRC and ERC functioning at the earliest observation, 12 years preceding diagnosis, and a significant decline 4 years preceding the AD diagnosis. These findings demonstrate that specific neuropsychological impairments occur early in the course of preclinical AD and that tasks measuring mPRC functioning may serve as additional, powerful markers of preclinical AD.

Normal Amplitude of Electroretinography and Visual Evoked Potential Responses in AβPP/PS1 Mice. - Leinonen, Henri; Lipponen, Arto; Gurevicius, Kestutis; Tanila, Heikki (J Alzheimers Dis, 2016)
Alzheimer's disease has been shown to affect vision in human patients and animal models. This may pose the risk of bias in behavior studies and therefore requires comprehensive investigation. We recorded electroretinography (ERG) under isoflurane anesthesia and visual evoked potentials (VEP) in awake amyloid expressing AβPPswe/PS1dE9 (AβPP/PS1) and wild-type littermate mice at a symptomatic age. The VEPs in response to patterned stimuli were normal in AβPP/PS1 mice. They also showed normal ERG amplitude but slightly shortened ERG latency in dark-adapted conditions. Our results indicate subtle changes in visual processing in aged male AβPP/PS1 mice specifically at a retinal level.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Contrast Sensitivity; Disease Models, Animal; Electroencephalography; Electroretinography; Evoked Potentials, Visual; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Photic Stimulation; Presenilin-1; Reaction Time

A Novel and Intelligent Home Monitoring System for Care Support of Elders with Cognitive Impairment. - Lazarou, Ioulietta; Karakostas, Anastasios; Stavropoulos, Thanos G; Tsompanidis, Theodoros; Meditskos, Georgios; Kompatsiaris, Ioannis; Tsolaki, Magda (J Alzheimers Dis, 2016)
BACKGROUND: Assistive technology, in the form of a smart home environment, is employed to support people with dementia. OBJECTIVES: To propose a system for continuous and objective remote monitoring of problematic daily living activity areas and design personalized interventions based on system feedback and clinical observations for improving cognitive function and health-related quality of life. METHODS: The assistive technology of the proposed system, including wearable, sleep, object motion, presence, and utility usage sensors, was methodically deployed at four different home installations of people with cognitive impairment. Detection of sleep patterns, physical activity, and activities of daily living, based on the collected sensor data and analytics, was available at all times through comprehensive data visualization solutions. Combined with clinical observation, targeted psychosocial interventions were introduced to enhance the participants' quality of life and improve their cognitive functions and daily functionality. Meanwhile, participants and their caregivers were able to visualize a reduced set of information tailored to their needs. RESULTS: Overall, paired-sample t-test analysis of monitored qualities revealed improvement for all participants in neuropsychological assessment. Moreover, improvement was detected from the beginning to the end of the trial, in physical condition and in the domains of sleep. Detecting abnormalities via the system, for example in sleep quality, such as REM sleep, has proved to be critical to assess current status, drive interventions, and evaluate improvements in a reliable manner. CONCLUSION: It has been proved that the proposed system is suitable to support clinicians to reliably drive and evaluate clinical interventions toward quality of life improvement of people with cognitive impairment.

A Novel Liposomal Nanoparticle for the Imaging of Amyloid Plaque by Magnetic Resonance Imaging. - Tanifum, Eric A; Ghaghada, Ketan; Vollert, Craig; Head, Elizabeth; Eriksen, Jason L; Annapragada, Ananth (J Alzheimers Dis, 2016)
Amyloid binding molecules with greater hydrophilicity than existing ligands were synthesized. The lead candidate ET6-21 bound amyloid fibrils, and amyloid deposits in dog brain and human brain tissue ex vivo. The ligand was used to prepare novel amyloid-targeted liposomal nanoparticles. The preparation was tested in the Tg2576 and TetO/APP mouse models of amyloid deposition. Gd chelates and Indocyanine green were included in the particles for visualization by MRI and near-infrared microscopy. Upon intravenous injection, the particles successfully traversed the blood-brain barrier in these mice, and bound to the plaques. Magnetic resonance imaging (T1-MRI) conducted 4 days after injection demonstrated elevated signal in the brains of mice with amyloid plaques present. No signal was observed in amyloid-negative mice, or in amyloid-positive mice injected with an untargeted version of the same agent. The MRI results were confirmed by immunohistochemical and fluorescent microscopic examination of mouse brain sections, showing colocalization of the fluorescent tags and amyloid deposits.

Novel Selective Calpain 1 Inhibitors as Potential Therapeutics in Alzheimer's Disease. - Fà, Mauro; Zhang, Hong; Staniszewski, Agnieszka; Saeed, Faisal; Shen, Li W; Schiefer, Isaac T; Siklos, Marton I; Tapadar, Subhasish; Litosh, Vladislav A; Libien, Jenny; Petukhov, Pavel A; Teich, Andrew F; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease, one of the most important brain pathologies associated with neurodegenerative processes, is related to overactivation of calpain-mediated proteolysis. Previous data showed a compelling efficacy of calpain inhibition against abnormal synaptic plasticity and memory produced by the excess of amyloid-β, a distinctive marker of the disease. Moreover, a beneficial effect of calpain inhibitors in Alzheimer's disease is predictable by the occurrence of calpain hyperactivation leading to impairment of memory-related pathways following abnormal calcium influxes that might ensue independently of amyloid-β elevation. However, molecules currently available as effective calpain inhibitors lack adequate selectivity. This work is aimed at characterizing the efficacy of a novel class of epoxide-based inhibitors, synthesized to display improved selectivity and potency towards calpain 1 compared to the prototype epoxide-based generic calpain inhibitor E64. Both functional and preliminary toxicological investigations proved the efficacy, potency, and safety of the novel and selective calpain inhibitors NYC438 and NYC488 as possible therapeutics against the disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cysteine Proteinase Inhibitors; Disease Models, Animal; Dose-Response Relationship, Drug; Fear; Glycoproteins; Hippocampus; Humans; In Vitro Techniques; Long-Term Potentiation; Maze Learning; Memory; Mice; Mice, Inbred ICR; Mice, Transgenic; Mutation; Patch-Clamp Techniques; Peptide Fragments; Presenilin-1; Spectrin

N-Terminal Pro-B-Type Natriuretic Peptide and Risk of Future Cognitive Impairment in the REGARDS Cohort. - Cushman, Mary; Callas, Peter W; McClure, Leslie A; Unverzagt, Frederick W; Howard, Virginia J; Gillett, Sarah R; Thacker, Evan L; Wadley, Virginia G (J Alzheimers Dis, 2016)
BACKGROUND: Improved understanding of the etiology of cognitive impairment is needed to develop effective preventive interventions. Higher amino-terminal pro-B-type natriuretic peptide (NT-proBNP) is a biomarker of cardiac dysfunction associated with risk of cardiovascular diseases and stroke in apparently healthy people. OBJECTIVE: To study the association of NT-proBNP with risk of incident cognitive impairment. METHODS: The Reasons for Geographic and Racial Differences in Stroke is a national cohort study of 30,239 black and white Americans age 45 and older at baseline, enrolled in 2003-7. Among participants without prebaseline stroke or cognitive impairment, baseline NT-proBNP was measured in 470 cases of incident cognitive impairment and 557 controls. Cases were participants scoring below the 6th percentile of demographically-adjusted means on at least 2 of 3 serially administered tests (word list learning, word list recall and semantic fluency) over 3.5 years follow-up. RESULTS: Adjusting for age, gender, race, region of residence, education, and income, there was an increased odds ratio of incident cognitive impairment with increasing NT-proBNP; participants in the 4th versus 1st quartile (>127 versus ≤33 pg/ml) had a 1.69-fold increased odds (95% CI 1.11-2.58). Adjustment for cardiovascular risk factors and presence of an apolipoprotein E4 allele had no substantial impact on the odds ratio. Results did not differ by age, race, gender, or presence of an apolipoprotein E4 allele. CONCLUSION: Higher NT-pro-BNP was associated with incident cognitive impairment in this prospective study, independent of atherogenic and Alzheimer's disease risk factors. Future work should clarify pathophysiologic connections of NT-proBNP and cognitive dysfunction.

Nutritional Status is Associated with Faster Cognitive Decline and Worse Functional Impairment in the Progression of Dementia: The Cache County Dementia Progression Study1. - Sanders, Chelsea; Behrens, Stephanie; Schwartz, Sarah; Wengreen, Heidi; Corcoran, Chris D; Lyketsos, Constantine G; Tschanz, JoAnn T (J Alzheimers Dis, 2016)
Nutritional status may be a modifiable factor in the progression of dementia. We examined the association of nutritional status and rate of cognitive and functional decline in a U.S. population-based sample. Study design was an observational longitudinal study with annual follow-ups up to 6 years of 292 persons with dementia (72% Alzheimer's disease, 56% female) in Cache County, UT using the Mini-Mental State Exam (MMSE), Clinical Dementia Rating Sum of Boxes (CDR-sb), and modified Mini Nutritional Assessment (mMNA). mMNA scores declined by approximately 0.50 points/year, suggesting increasing risk for malnutrition. Lower mMNA score predicted faster rate of decline on the MMSE at earlier follow-up times, but slower decline at later follow-up times, whereas higher mMNA scores had the opposite pattern (mMNA by time β= 0.22, p = 0.017; mMNA by time2 β= -0.04, p = 0.04). Lower mMNA score was associated with greater impairment on the CDR-sb over the course of dementia (β= 0.35, p <  0.001). Assessment of malnutrition may be useful in predicting rates of progression in dementia and may provide a target for clinical intervention.
Keywords: Age of Onset; Aged, 80 and over; Alzheimer Disease; Dementia, Vascular; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Mental Status Schedule; Nutritional Status; Severity of Illness Index; Sex Factors; Utah

Nutritional Status of Patients with Alzheimer's Disease and Their Caregivers. - Tombini, Mario; Sicari, Maura; Pellegrino, Giovanni; Ursini, Francesca; Insardá, Pasqualina; Di Lazzaro, Vincenzo (J Alzheimers Dis, 2016)
BACKGROUND: Malnutrition is one of the most important conditions that negatively affects the health of elder people, particularly in patients with dementia. OBJECTIVE: To provide an assessment of nutritional status of patients affected by Alzheimer's disease (AD) living at home and of their caregivers by means of Mini Nutritional Assessment (MNA), and to explore the influence of different factors on nutrition. METHODS: 90 patients affected by AD living at home and 90 age- and sex-matched caregivers were enrolled. Patients and caregivers, coming from an urban-rural fringe of Southern Italy, were assessed using full MNA, Mini-Mental State Examination, Geriatric Depression Scale- short form, Activity of Daily Living, and Instrumental Activities of Daily Living scales. RESULTS: Malnutrition was found with high prevalence in patients affected by AD of different severity (more than 95% of patients were malnourished or at risk of malnutrition), and associated with reduced functional status. An altered nutrition was also recognized with high rate in the group of caregivers (23.3% were malnourished and 41.1% at risk of malnutrition) and the worse nutritional condition was correlated with higher age and lower functional and cognitive status and education. A positive correlation between MNA score of AD patients and caregivers was found. CONCLUSION: Corrective measures should be taken in order to early identify nutritional deficiencies and risk of malnutrition observed with high rate in both groups of AD patients and their caregivers; in these subjects a nutrition education program and intervention policies are mandatory to restore nutritional status.

Oculodentodigital dysplasia with massive brain calcification and a new mutation of GJA1 gene. - Tumminelli, Gemma; Di Donato, Ilaria; Guida, Valentina; Rufa, Alessandra; De Luca, Alessandro; Federico, Antonio (J Alzheimers Dis, 2016)
Oculodentodigital dysplasia (ODDD) [MIM 164200] is a rare disorder caused by mutations in the gap junction alpha 1 (GJA1) gene encoding for connexin 43 (Cx43). Typical signs include type III syndactyly, microphtalmia, microdontia, and neurological disturbances. We report a 59-year-old man having clinical symptoms and signs suggestive of ODDD, with some rarely reported features, that is the presence of gross calcifications of basal ganglia and cerebellar nuclei. Mutation analysis of GJA1 gene identified an unreported heterozygous missense mutation [NM_000165.3:c.124 G>C;p.(Glu42Gln)], which may be thought to alter the brain microvessels leading to massive calcifications, as in primary familial brain calcification.
Keywords: Basal Ganglia; Calcinosis; Connexin 43; Craniofacial Abnormalities; DNA Mutational Analysis; Eye Abnormalities; Fingers; Foot Deformities, Congenital; Humans; Male; Middle Aged; Mutation, Missense; Syndactyly; Tomography, X-Ray Computed; Tooth Abnormalities

An Oral Aβ Vaccine Using a Recombinant Adeno-Associated Virus Vector in Aged Monkeys: Reduction in Plaque Amyloid and Increase in Aβ Oligomers. - Hara, Hideo; Ono, Fumiko; Nakamura, Shinichiro; Matsumoto, Shin-Ei; Jin, Haifeng; Hattori, Nobutaka; Tabira, Takeshi (J Alzheimers Dis, 2016)
With the objective to improve the amyloid-β (Aβ) targeting immunotherapy, we investigated the safety and efficacy of an oral vaccine with recombinant adeno-associated virus vector carrying a signal sequence and Aβ1-43 cDNA (rAAV/Aβ) in old non-human primates, 12 African green and 10 cynomolgus monkeys. The enteric-dissolving coated capsules containing rAAV/Aβ were orally administered once or twice, then monkeys' conditions were carefully observed with complete blood count and laboratory examinations of the sera. General conditions, food intake, water intake, stool conditions, body weight changes, and menstruation cycles were not significantly altered, and laboratory tests and pathological examinations of the systemic organs were unremarkable. Pathological examinations of the brain showed significant reduction of the amyloid plaque burden and intracellular Aβ without inflammatory or hemorrhagic changes in the brain. However, soluble Aβ and some Aβ oligomers were increased in rAAV-treated monkey brains without changes of the neuronal density and vascular amyloidosis. Thus, this vaccine seems to be safe in general, but we must be cautious about the increase of Aβ oligomers after vaccination. This vaccine may be recommended at a very early stage of Alzheimer's disease when little amyloid is deposited.

Palmomental Reflex a Relevant Sign in Early Alzheimer's Disease Diagnosis? - Gabelle, Audrey; Gutierrez, Laure-Anne; Dartigues, Jean-François; Ritchie, Karen; Touchon, Jacques; Berr, Claudine (J Alzheimers Dis, 2016)
BACKGROUND: Sophisticated and expensive biomarkers are proposed for the diagnostic of Alzheimer's disease (AD). The amyloid process seems to be early in AD, and brain amyloid load affects the frontal lobe. OBJECTIVE: To determine if certain simple clinical signs, especially frontal-related signs, could help reach an earlier and better diagnosis. METHODS: In the frame of the 3-City cohort, we conducted a nested case-control study comparing incident cases of AD to controls matched for age, gender, and education. The standardized neurological exam included extrapyramidal signs (akinesia, rigidity, rest tremor), pyramidal symptoms (spastic rigidity, Babinski reflex), primitive reflexes (snout, palmomental reflex grasping), and tremor (essential, intentional, head) at the time of diagnosis and two years before. RESULTS: We compared 106 incident AD subjects (mean age at diagnosis 82.2 (SD = 5.9); median MMSE at diagnosis = 23) to 208 matched controls. In patients younger than 80, palmomental reflexes were more frequent in AD than controls, two years before diagnosis (25.0 versus 7.0% , p = 0.03) and at time of diagnosis (30.3 versus 12.3% , p = 0.02). No difference was observed for other signs two years before diagnosis or for patients older than 80. CONCLUSION: Before diagnosis, the clinical examination of AD patients is not strictly normal; the primitive reflexes appear to be pathological. It might be in connection with the frontal amyloid load at an early stage of the disease. Clinical examination can reveal simple and interesting signs that deserve consideration as well as the other more invasive and expensive biomarkers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Early Diagnosis; Female; Follow-Up Studies; France; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Reflex

A Pathway Based Classification Method for Analyzing Gene Expression for Alzheimer's Disease Diagnosis. - Voyle, Nicola; Keohane, Aoife; Newhouse, Stephen; Lunnon, Katie; Johnston, Caroline; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Hodges, Angela; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies indicate that gene expression levels in blood may be able to differentiate subjects with Alzheimer's disease (AD) from normal elderly controls and mild cognitively impaired (MCI) subjects. However, there is limited replicability at the single marker level. A pathway-based interpretation of gene expression may prove more robust. OBJECTIVES: This study aimed to investigate whether a case/control classification model built on pathway level data was more robust than a gene level model and may consequently perform better in test data. The study used two batches of gene expression data from the AddNeuroMed (ANM) and Dementia Case Registry (DCR) cohorts. METHODS: Our study used Illumina Human HT-12 Expression BeadChips to collect gene expression from blood samples. Random forest modeling with recursive feature elimination was used to predict case/control status. Age and APOE ɛ4 status were used as covariates for all analysis. RESULTS: Gene and pathway level models performed similarly to each other and to a model based on demographic information only. CONCLUSIONS: Any potential increase in concordance from the novel pathway level approach used here has not lead to a greater predictive ability in these datasets. However, we have only tested one method for creating pathway level scores. Further, we have been able to benchmark pathways against genes in datasets that had been extensively harmonized. Further work should focus on the use of alternative methods for creating pathway level scores, in particular those that incorporate pathway topology, and the use of an endophenotype based approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Cohort Studies; Datasets as Topic; Female; Gene Expression; Gene Expression Profiling; Humans; Male; Models, Genetic; Oligonucleotide Array Sequence Analysis; Signal Transduction

PDE5 Exists in Human Neurons and is a Viable Therapeutic Target for Neurologic Disease. - Teich, Andrew F; Sakurai, Mikako; Patel, Mitesh; Holman, Cameron; Saeed, Faisal; Fiorito, Jole; Arancio, Ottavio (J Alzheimers Dis, 2016)
Phosphodiesterase 5 (PDE5) is a critical component of the cGMP-PKG axis of cellular signaling in neurons, and inhibition of PDE5 has been shown to be therapeutic in a wide range of neurologic conditions in animal models. However, enthusiasm for PDE5 inhibitors in humans is limited by data suggesting that PDE5 may not exist in human neurons. Here, we first show that past attempts to quantify PDE5 mRNA were flawed due to the use of incorrect primers, and that when correct primers are used, PDE5 mRNA is detectable in human brain tissue. We then show that PDE5 protein exists in human brain by western blot and ELISA. Most importantly, we performed immunohistochemistry and demonstrate that PDE5 is present in human neurons. We hope that this work will trigger a renewed interest in the development of PDE5 inhibitors for neurologic disease.
Keywords: Blotting, Western; Brain; Cyclic Nucleotide Phosphodiesterases, Type 5; DNA Primers; Enzyme-Linked Immunosorbent Assay; Humans; Immunohistochemistry; Nervous System Diseases; Neurons; Phosphodiesterase 5 Inhibitors; Polymerase Chain Reaction; RNA, Messenger

Pharmacological Modulations of the Serotonergic System in a Cell-Model of Familial Alzheimer's Disease. - Tajeddinn, Walid; Persson, Torbjörn; Calvo-Garrido, Javier; Seed Ahmed, Mohammed; Maioli, Silvia; Vijayaraghavan, Swetha; Kazokoglu, Mehmet Selim; Parrado-Fernández, Cristina; Yoshitake, Takashi; Kehr, Jan; Francis, Paul; Winblad, Bengt; et al. (J Alzheimers Dis, 2016)
Serotonin (5-HT) plays a central role in the integrity of different brain functions. The 5-HT homeostasis is regulated by many factors, including serotonin transporter (SERT), monoamine oxidase enzyme (MAO), and several 5-HT receptors, including the 5-HT1B. There is little knowledge how the dynamics of this system is affected by the amyloid-β (Aβ) burden of Alzheimer's disease (AD) pathology. SH-SY5Y neuroblastoma cells transfected with the amyloid precursor protein (APP) gene containing the Swedish mutations causing familial AD (APPswe), were used as a model to explore the effect of Aβ pathology on 5-HT1B and related molecules including the receptor adaptor protein (p11), SERT and MAOA gene expression, and MAOA activity after treatment with selective serotonin reuptake inhibitor (SSRI) (sertraline), and a 5-HT1B receptor antagonist. Sertraline led more than 70 fold increase of 5-HT1B gene expression (p < 0.001), an increased serotonin turnover in both APPswe and control cells and reduced intracellular serotonin levels by 75% in APPswe cells but not in controls (p > 0.05). Treatment with the 5-HT1B receptor antagonist increased SERT gene-expression in control cells but not in the APPswe cells. 5-HT and 5-HT1B antagonist treatment resulted in different p11 expression patterns in APPswe cells compared to controls. Although MAOA gene expression was not changed by APPswe overexpression, adding 5-HT lead to a significant increase in MAOA gene expression in APPswe but not control cells. These findings suggest that the sensitivity of the 5-HT1B receptor and related systems is affected by APPswe overexpression, with potential relevance for pharmacologic intervention in AD. This may at least partly explain the lack of effect of SSRIs in patients with AD and depression.

A Phase II Study of Fornix Deep Brain Stimulation in Mild Alzheimer's Disease. - Lozano, Andres M; Fosdick, Lisa; Chakravarty, M Mallar; Leoutsakos, Jeannie-Marie; Munro, Cynthia; Oh, Esther; Drake, Kristen E; Lyman, Christopher H; Rosenberg, Paul B; Anderson, William S; Tang-Wai, David F; Pendergrass, Jo Cara; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Deep brain stimulation (DBS) is used to modulate the activity of dysfunctional brain circuits. The safety and efficacy of DBS in dementia is unknown. OBJECTIVE: To assess DBS of memory circuits as a treatment for patients with mild Alzheimer's disease (AD). METHODS: We evaluated active "on" versus sham "off" bilateral DBS directed at the fornix-a major fiber bundle in the brain's memory circuit-in a randomized, double-blind trial (ClinicalTrials.gov NCT01608061) in 42 patients with mild AD. We measured cognitive function and cerebral glucose metabolism up to 12 months post-implantation. RESULTS: Surgery and electrical stimulation were safe and well tolerated. There were no significant differences in the primary cognitive outcomes (ADAS-Cog 13, CDR-SB) in the "on" versus "off" stimulation group at 12 months for the whole cohort. Patients receiving stimulation showed increased metabolism at 6 months but this was not significant at 12 months. On post-hoc analysis, there was a significant interaction between age and treatment outcome: in contrast to patients  CONCLUSION: DBS for AD was safe and associated with increased cerebral glucose metabolism. There were no differences in cognitive outcomes for participants as a whole, but participants aged≥65 years may have derived benefit while there was possible worsening in patients below age 65 years with stimulation.

Plasma Ceramides and Neuropsychiatric Symptoms of Alzheimer's Disease. - Xing, Yi; Tang, Yi; Zhao, Lina; Wang, Qi; Qin, Wei; Zhang, Jin-Lan; Jia, Jianping (J Alzheimers Dis, 2016)
BACKGROUND: Various evidence demonstrates the influences of ceramides on Alzheimer's disease (AD) pathogenesis. Furthermore, increased ceramides were also suggested to be related to cognitive decline. However, the association between ceramides and neuropsychiatric symptoms of AD remains unclear. OBJECTIVE: This study sought to investigate the association between plasma ceramide levels and multiple neuropsychiatric symptoms in AD. METHODS: A total of 98 patients and 92 cognitively normal controls participated in this study, including 56 with mild AD and 42 with moderate to severe AD. The Neuropsychiatric Inventory (NPI) was used to assess neuropsychiatric symptoms. Considering the influences of dementia severity on ceramide levels and neuropsychiatric symptoms, a subgroup analysis was conducted by dementia severity. RESULTS: Except for C24 : 0, all ceramide species were significantly higher in AD patients than in controls. After controlling for confounding factors, the C16 : 0 and C20 : 0 levels were positively associated with delusions, and the quartiles of C22 : 0 and C24 : 0 were positively associated with depression. In the subgroup analysis, association between ceramide species and delusions were only observed in mild AD, and the association between ceramides and depression were prominent in moderate to severe AD. In mild AD, after controlling for age, gender, anti-dementia medications, diabetes status, and ApoE ɛ4 status, the C16 : 0, C20 : 0, and quartiles of C24 : 1 were associated with delusions. In moderate to severe AD, depression was associated with C22 : 0 and C24 : 0. CONCLUSION: There were stage-specific associations between ceramides and neuropsychiatric symptoms of AD. The potential mechanisms deserve further investigation.

Plasma Phospholipid and Sphingolipid Alterations in Presenilin1 Mutation Carriers: A Pilot Study. - Chatterjee, Pratishtha; Lim, Wei L F; Shui, Guanghou; Gupta, Veer B; James, Ian; Fagan, Anne M; Xiong, Chengjie; Sohrabi, Hamid R; Taddei, Kevin; Brown, Belinda M; Benzinger, Tammie; Masters, Colin; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: Aberrant lipid metabolism has been implicated in sporadic Alzheimer's disease (AD). The current study investigated plasma phospholipid and sphingolipid profiles in individuals carrying PSEN1 mutations responsible for autosomal dominant AD (ADAD). METHODS: Study participants evaluated were from the Perth and Melbourne sites of the Dominantly Inherited Alzheimer Network (DIAN) study. Plasma phospholipid and sphingolipid profiles were measured using liquid chromatography coupled with mass spectrometry in 20 PSEN1 mutation carriers (MC; eight of whom were symptomatic and twelve asymptomatic, based on Clinical Dementia Rating scores) and compared with six non carriers (NC) using linear mixed models. Further, AD gold standard biomarker data obtained from the DIAN database were correlated with lipid species significantly altered between MC and NC, using Spearman's correlation coefficient. RESULTS: One-hundred and thirty-nine plasma phospholipid and sphingolipid species were measured. Significantly altered species in MC compared to NC primarily belonged to choline and ethanolamine containing phospholipid classes and ceramides. Further phosphatidylcholine species (34:6, 36:5, 40:6) correlated with cerebrospinal fluid tau (p <  0.05), and plasmalogen ethanolamine species (34:2, 36:,4) correlated with both cerebrospinal fluid tau and brain amyloid load within the MC group (p <  0.05). CONCLUSION: These findings indicate altered phospholipid and sphingolipid metabolism in ADAD and provide insight into the pathomolecular changes occurring with ADAD pathogenesis. Further, findings reported in this study allow comparison of lipid alterations in ADAD with those reported previously in sporadic AD. The findings observed in the current pilot study warrant validation in the larger DIAN cohort.
Keywords: Adult; Alzheimer Disease; Apolipoproteins E; Female; Humans; Linear Models; Male; Middle Aged; Mutation; Phospholipids; Pilot Projects; Presenilin-1; Sphingolipids

Possible Involvement of Adiponectin, the Anti-Diabetes Molecule, in the Pathogenesis of Alzheimer's Disease. - Waragai, Masaaki; Adame, Anthony; Trinh, Ivy; Sekiyama, Kazunari; Takamatsu, Yoshiki; Une, Kaori; Masliah, Eliezer; Hashimoto, Makoto (J Alzheimers Dis, 2016)
Adiponectin (APN) is protective in animal models of neurodegenerative diseases, but the role of APN in human brain has not been established. Using an enzyme-linked immunosorbent assay, we found that APN was significantly decreased in cerebrospinal fluid (CSF) of patients with Alzheimer's disease (AD), compared to those in patients with mild cognitive impairment (MCI) and in normal controls (NC), despite elevation of APN in serum of patients with MCI and AD compared to that in NC. The discrepancy of CSF APN from serum APN in AD may suggest some critical actions of APN in the pathogenesis of AD. Indeed, it was histologically observed that APN was co-localized with tau in neurofibrillary tangles and immunoblot analysis showed that the functional trimers of APN were significantly decreased in AD compared to those in NC. Collectively, a loss of function of APN may be involved in the pathogenesis of AD.

A Potential VEP Biomarker for Mild Cognitive Impairment: Evidence from Selective Visual Deficit of Higher-Level Dorsal Pathway. - Yamasaki, Takao; Horie, Shizuka; Ohyagi, Yasumasa; Tanaka, Eri; Nakamura, Norimichi; Goto, Yoshinobu; Kanba, Shigenobu; Kira, Jun-Ichi; Tobimatsu, Shozo (J Alzheimers Dis, 2016)
Visual dysfunctions are common in Alzheimer's disease (AD). Our aim was to establish a neurophysiological biomarker for amnestic mild cognitive impairment (aMCI). Visual evoked potentials (VEPs) were recorded in aMCI patients who later developed AD (n = 15) and in healthy older (n = 15) and younger controls (n = 15). Visual stimuli were optimized to separately activate lower and higher levels of the ventral and dorsal streams. We compared VEP parameters across the three groups of participants and conducted a linear correlation analysis between VEPs and data from neuropsychological tests. We then used a receiver operating characteristic (ROC) analysis to discriminate those with aMCI from those who were healthy older adults. The latency and phase of VEPs to lower-level stimuli (chromatic and achromatic gratings) were significantly affected by age but not by cognitive decline. Conversely, VEP latencies for higher-ventral (faces and kanji-words) and dorsal (kana-words and optic flow motion) stimuli were not affected by age, but they were significantly prolonged in aMCI patients. Interestingly, VEPs for higher-dorsal stimuli were related to outcomes of neuropsychological tests. Furthermore, the ROC analysis showed that the highest areas under the curve were obtained for VEP latencies in response to higher-dorsal stimuli. These results suggest aMCI-related functional impairment specific to higher-level visual processing. Further, dysfunction in the higher-level of the dorsal stream could be an early indicator of cognitive decline. Therefore, we conclude that VEPs associated with higher-level dorsal stream activity can be a sensitive biomarker for early detection of aMCI.

Preliminary Study of Plasma Exosomal Tau as a Potential Biomarker for Chronic Traumatic Encephalopathy. - Stern, Robert A; Tripodis, Yorghos; Baugh, Christine M; Fritts, Nathan G; Martin, Brett M; Chaisson, Christine; Cantu, Robert C; Joyce, James A; Shah, Sahil; Ikezu, Tsuneya; Zhang, Jing; Gercel-Taylor, Cicek; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Chronic traumatic encephalopathy (CTE) is a tauopathy associated with prior exposure to repetitive head impacts, such as those incurred through American football and other collision sports. Diagnosis is made through neuropathological examination. Many of the clinical features of CTE are common in the general population, with and without a history of head impact exposure, making clinical diagnosis difficult. As is now common in the diagnosis of other neurodegenerative disorders, such as Alzheimer's disease, there is a need for methods to diagnose CTE during life through objective biomarkers. OBJECTIVE: The aim of this study was to examine tau-positive exosomes in plasma as a potential CTE biomarker. METHODS: Subjects were 78 former National Football League (NFL) players and 16 controls. Extracellular vesicles were isolated from plasma. Fluorescent nanoparticle tracking analysis was used to determine the number of vesicles staining positive for tau. RESULTS: The NFL group had higher exosomal tau than the control group (p <  0.0001). Exosomal tau discriminated between the groups, with 82% sensitivity, 100% specificity, 100% positive predictive value, and 53% negative predictive value. Within the NFL group, higher exosomal tau was associated with worse performance on tests of memory (p = 0.0126) and psychomotor speed (p = 0.0093). CONCLUSION: These preliminary findings suggest that exosomal tau in plasma may be an accurate, noninvasive CTE biomarker.
Keywords: Adult; Aged; Analysis of Variance; Case-Control Studies; Chronic Traumatic Encephalopathy; Extracellular Vesicles; Humans; Male; Middle Aged; Plasma; tau Proteins

Prevalence and Risk Factor of Cognitive Impairment were Different between Urban and Rural Population: A Community-Based Study. - Tang, Hui-Dong; Zhou, Yi; Gao, Xiang; Liang, Liang; Hou, Miao-Miao; Qiao, Yuan; Ma, Jian-Fang; Chen, Sheng-Di (J Alzheimers Dis, 2016)
BACKGROUND: China is facing a continuously rising numbers of people with cognitive impairment (CI). OBJECTIVES: To investigate the prevalence and risk factors of CI among elderly people living in rural and urban communities. METHODS: We conducted a face-to-face survey of CI on 7,900 individuals aged 50 years or older meeting inclusion criteria in the Malu (rural community, n = 4,429) and Wuliqiao (urban community, n = 3,471) communities of Shanghai. The Mini-Mental State Examination (MMSE) was used to evaluate the cognitive function. Information on demographic features and potential risk factors for CI was collected during the interview. Multivariate logistic regression was performed to identify risk factors associated with CI. RESULTS: Based on the education modified MMSE score, we identified 329 CI cases in rural community and 227 in urban community. The prevalence of CI was 7.43% in rural population and 6.54% in urban population (p = 0.13). In the urban population, risk of having CI was associated with age (OR = 1.04; 95% CI: 1.01-1.08), lack of physical activities (OR = 2.25; 95% CI: 1.11-4.57), presence of diabetes mellitus (OR = 1.79; 95% CI: 1.04-3.07), and having three or more children (OR = 2.39; 95% CI: 1.27-4.50). In contrast, factors associated with rural populations included female gender (OR = 2.03; 95% CI: 1.08-3.82), age (OR = 1.06; 95% CI: 1.03-1.08), exposure to pesticides (OR = 4.68; 95% CI: 1.27-17.21), history of encephalitis or meningitis (OR = 6.02; 95% CI: 1.92-18.85) and head trauma (OR = 1.89; 95% CI: 1.10-3.24). CONCLUSIONS: Urban rural and populations showed different risk factors for CI, suggesting that different preventive strategies in these areas should be performed.
Keywords: Aged; Aged, 80 and over; China; Cognition Disorders; Female; Humans; Logistic Models; Male; Mental Status Schedule; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Rural Population; Urban Population

Prevention Trials in Alzheimer's Disease: Current Status and Future Perspectives. - Wang, Jun; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most common form of dementia in the elderly. Over the past 20 years, both pharmacological and lifestyle interventions have been studied for AD prevention, but the overall results have been disappointing. The majority of disappointing results have raised questions and great challenges for the future of AD prevention trials. Ongoing advances in the knowledge of pathogenesis, in the identification of novel targets, in improved outcome measures, and in identification and validation of biomarkers may lead to effective strategies for AD prevention. In this paper, we review the selection of participants and interventions, trial design, outcome assessments, and promising biomarkers in prevention trials, and summarize the lessons learned from completed trials and perspectives from ongoing trials in AD prevention. Selection of optimal participants and interventions, coupled with more refined outcomes and more efficient trial design, may have the capacity to deliver a new era of preventive discovery in this challenging area.
Keywords: Alzheimer Disease; Biomarkers; Clinical Trials as Topic; Humans

Primary Progressive Aphasia in the Network of French Alzheimer Plan Memory Centers. - Magnin, Eloi; Démonet, Jean-François; Wallon, David; Dumurgier, Julien; Troussière, Anne-Cécile; Jager, Alain; Duron, Emmanuelle; Gabelle, Audrey; de la Sayette, Vincent; Volpe-Gillot, Lisette; Tio, Gregory; Evain, Sarah; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Few demographical data about primary progressive aphasia (PPA) are available, and most knowledge regarding PPA is based on tertiary centers' results. OBJECTIVE: Our aims were to describe demographical characteristics of the PPA population in a large sample of PPA patients from the network of French Alzheimer plan memory centers (Sample 1), and to describe the stratification of cerebrospinal fluid (CSF) biomarkers in two different samples of PPA patients (Samples 2 and 3). METHODS: All registered PPA patients in the French Alzheimer's disease (AD) databank (Sample 1: n = 2,035) and a subsample (Sample 2: n = 65) derived from a multicentric prospective cohort with CSF biomarker analysis were analyzed. A multicentric retrospective cohort from language expert tertiary centers (Sample 3: n = 97) with CSF biomarker analysis was added. Sample 3 was added to replicate the CSF results of the Sample 2 and to evaluate repartition of AD pathology in the three variant of PPA according to the latest classification. RESULTS: Non-Fluent/Agrammatic, Logopenic, and Unclassifiable PPA patients (NF/A-Logo-Unclass PPA) were older and more frequent than Semantic PPA patients (2.2 versus 0.8/100,000 inhabitants; p < 0.00001). Male predominance occurred after the age of 80 (p < 0.00001). A higher level of education was observed in the PPA population compared to a typical amnesic AD group. No demographical significant difference between PPA due to AD and not due to AD was observed. The Logopenic variant was most frequent with 85% of AD CSF biomarker profiles (35% in NF/A PPA; 20% in Semantic PPA). CONCLUSION: PPA occurs also in an elderly population, especially in male patients over 80. CSF biomarkers are useful to stratify PPA. The epidemiology of PPA should be further investigated to confirm gender and cognitive reserve role in PPA to better understand the factors and mechanisms leading to this language-predominant deficit during neurodegenerative diseases.

Primary Progressive Orofacial Apraxia: A Ten-Year Long Follow-Up Case Report. - Trebbastoni, Alessandro; D'Antonio, Fabrizia; de Lena, Carlo; Onesti, Emanuela; John, Bev; Inghilleri, Maurizio (J Alzheimers Dis, 2016)
Orofacial apraxia (OA) as the main symptom in neurodegenerative disorders has not been yet reported. We present the case of a woman with a 22-month long history of isolated OA, studied with cerebrospinal fluid biomarkers and repeated clinical, neuropsychological, and morpho-functional evaluations. Baseline morpho-functional neuroimages revealed a left frontal operculum hypoperfusion with a widespread fronto-temporal involvement at follow-up. Cerebrospinal fluid concentrations of tau and amyloid-β were normal. The ten-year long clinical observation disclosed progressive OA worsening and the late onset of frontal functions impairment and extrapyramidal signs. The early and late stages of a neurodegenerative syndrome with OA as the main clinical feature were characterized.

Prion Protein-Hemin Interaction Upregulates Hemoglobin Synthesis: Implications for Cerebral Hemorrhage and Sporadic Creutzfeldt-Jakob Disease. - Tripathi, Ajai K; Singh, Neena (J Alzheimers Dis, 2016)
Hemin is known to induce endocytosis of prion-protein (PrP(C)) from the neuronal plasma membrane, potentially limiting propagation of the disease causing PrP-scrapie (PrP(Sc)) isoform. Hemin is therefore an attractive disease-modifying option for sporadic Creutzfeldt-Jakob disease (sCJD), a human prion disorder with no effective treatment. The hemin-PrP(C) interaction is also of interest in cerebral-hemorrhage (CH), a condition where potentially toxic hemin molecules come in contact with neuronal PrP(C). Interestingly, PrP(C) is upregulated in penumbric neurons surrounding CH and is known to confer neuroprotection in a dose-dependent manner. The underlying mechanism, however, is not clear. Here, we report that hemin binds PrP(C) on diverse cell lines, resulting in its aggregation or degradation in a cell-type specific manner. Surprisingly, the hemin-PrP(C) interaction upregulates Hb synthesis in hematopoietic cells, a response reversed by deleting the hemin-binding octa-peptide repeat region of PrP(C). A similar response is noted in brain organotypic cultures where exposure to hemin induces significantly more α-globin in wild-type (PrP(+/+)) relative to PrP-knock-out (PrP(-/-)) samples. Furthermore, red blood cells and brain tissue from PrP(-/-) mice show significantly less α-globin relative to PrP(+/+) controls, indicating a positive effect of PrP(C) on Hb synthesis under physiological conditions as well. Surprisingly, levels of α-globin are significantly higher in sCJD brain tissue relative to controls, suggesting compensatory upregulation of Hb synthesis by surviving neurons or misregulation in diseased brains. These observations reveal a unique function of PrP(C) that is likely to impact the therapeutic management of CH and sCJD.
Keywords: Animals; Brain; Cell Line, Tumor; Creutzfeldt-Jakob Syndrome; Endocytosis; Ferritins; Green Fluorescent Proteins; Hemin; Hemoglobins; Humans; In Vitro Techniques; Leukemia, Erythroblastic, Acute; Mice; Mice, Transgenic; Neuroblastoma; Neuroglia; Neurons; Organ Culture Techniques; Prion Proteins; Transfection; Up-Regulation

PRNP P39L Variant is a Rare Cause of Frontotemporal Dementia in Italian Population. - Oldoni, Emanuela; Fumagalli, Giorgio G; Serpente, Maria; Fenoglio, Chiara; Scarioni, Marta; Arighi, Andrea; Bruno, Giuseppe; Talarico, Giuseppina; Confaloni, Annamaria; Piscopo, Paola; Nacmias, Benedetta; Sorbi, Sandro; et al. (J Alzheimers Dis, 2016)
The missense P39L variant in the prion protein gene (PRNP) has recently been associated with frontotemporal dementia (FTD). Here, we analyzed the presence of the P39L variant in 761 patients with FTD and 719 controls and found a single carrier among patients. The patient was a 67-year-old male, with a positive family history for dementia, who developed apathy, short term memory deficit, and postural instability at 66. Clinical and instrumental workup excluded prion disease. At MRI, bilateral frontal lobe atrophy was present. A diagnosis of FTD was made, with a mainly apathetic phenotype. The PRNP P39L mutation may be an extremely rare cause of FTD (0.13%).
Keywords: Aged; Atrophy; Frontal Lobe; Frontotemporal Dementia; Genetic Predisposition to Disease; Humans; Italy; Language; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Neuropsychological Tests; Prion Proteins; Prions; Temporal Lobe

Prognostic Significance of Mild Cognitive Impairment Subtypes for Dementia and Mortality: Data from the NEDICES Cohort. - Bermejo-Pareja, Félix; Contador, Israel; Trincado, Rocío; Lora, David; Sánchez-Ferro, Álvaro; Mitchell, Alex J; Boycheva, Elina; Herrero, Alejandro; Hernández-Gallego, Jesús; Llamas, Sara; Villarejo Galende, Alberto; Benito-León, Julián (J Alzheimers Dis, 2016)
BACKGROUND: The predictive value of diverse subtypes of mild cognitive impairment (MCI) for dementia and death is highly variable. OBJECTIVE: To compare the predictive value of several MCI subtypes in progression to dementia and/or mortality in the NEDICES (Neurological Disorders in Central Spain) elderly cohort. METHODS: Retrospect algorithmic MCI subgroups were established in a non-dementia baseline NEDICES cohort using Spanish adaptations of the original Mini-Mental State Examination (MMSE-37) and Pfeffer's Functional Activities Questionnaire (Pfeffer-11). The presence of MCI was defined according two cognitive criteria: using two cut-offs points on the total MMSE-37 score. Five cognitive domains were used to establish the MCI subtypes. Functional capacity (Pfeffer-11) was preserved or minimally impaired in all MCI participants. The incident dementia diagnoses were established by specialists and the mortality data obtained from Spanish official registries. RESULTS: 3,411 participants without dementia were assessed in 1994-5. The baseline prevalence of MCI varied according to the MCI definition (4.3%-31.8%). The follow-up was a mean of 3.2 years (1997-8). The dementia incidence varied between 14.9 and 71.8 per 1,000/person-years. The dementia conversion rate was increased in almost all MCI subgroups (p >  0.01), and mortality rate was raised only in four MCI subtypes. The amnestic-multi-domain MCI (aMd-MCI) had the best dementia predictive accuracy (highest positive likelihood ratio and highest clinical utility when negative). CONCLUSIONS: Those with aMd-MCI were at greatest risk of progression to dementia, as in other surveys and might be explored with increased attention in MCI research and in dementia preventive trials.
Keywords: Aged; Aged, 80 and over; Algorithms; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Spain

Progression of Extrapyramidal Signs in Alzheimer's Disease: Clinical and Neuropathological Correlates. - Tosto, Giuseppe; Monsell, Sarah E; Hawes, Stephen E; Bruno, Giuseppe; Mayeux, Richard (J Alzheimers Dis, 2016)
BACKGROUND: Extrapyramidal signs (EPS) are frequent in Alzheimer's disease (AD) and core manifestation of related diseases, i.e., dementia with Lewy bodies and Parkinson's disease; furthermore, Lewy bodies and AD-type pathology occur in all three conditions. OBJECTIVE: To identify clusters of EPS progression over time and their clinical and neuropathological correlates. METHODS: 3,502 AD patients with longitudinal assessment from the National Alzheimer's Coordinating Center database were included; 394 provided neuropathological data. k-means algorithm was employed to identify clusters of EPS progression and those were compared in terms of cognitive profile, neuropsychiatric features and neuropathological findings. RESULTS: Three clusters of EPS progression were identified: no/low (n = 1,583), medium (n = 1,259), and high (n = 660) EPS burden. Compared to those with no/low and medium EPS, those with high EPS had greater cognitive and neuropsychiatric impairment, specifically hallucinations. Despite similar AD-pathology across the three clusters, the high EPS cluster had a significantly number of subjects diagnosed with dementia with Lewy bodies. CONCLUSIONS: Cluster analysis of EPS progression over time identified different subgroups of AD patients with distinct clinical and neuropathological features.
Keywords: Aged; Algorithms; Alzheimer Disease; Cluster Analysis; Databases, Factual; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Severity of Illness Index

Psychotropic Drug Prescription in Patients with Dementia: Nursing Home Residents Versus Patients Living at Home. - Jacquin-Piques, Agnès; Sacco, Guillaume; Tavassoli, Neda; Rouaud, Olivier; Bejot, Yannick; Giroud, Maurice; Robert, Philippe; Vellas, Bruno; Bonin-Guillaume, Sylvie (J Alzheimers Dis, 2016)
BACKGROUND: Psychotropic drugs are frequently prescribed in nursing homes (NH). Nonetheless, we hoped that institutionalization decreases the number of psychotropic drug classes prescribed, because NH residents may have more psychosocial interventions than patients living at home. OBJECTIVE: The aim was to compare the type and number of psychotropic drugs prescribed in elderly NH residents with dementia with those in community-living patients. METHODS: This cross-sectional study included elderly patients (at least 75 years old) with dementia recorded in the National Alzheimer's data Bank ("Banque Nationale Alzheimer") during the year 2012 and who were taking at least one psychotropic drug. Psychotropic drugs were classified as follows: antidepressant, anxiolytic, hypnotic, and antipsychotic drugs. Patients were classified into three categories of dementia severity according to the MMSE score. RESULTS: Among the 50,932 patients with dementia recorded in the BNA, 40.1% had at least one psychotropic drug prescribed. Most of the patients who were treated by at least one psychotropic drug class had antidepressant therapy (69.0%), whatever their residence type, and 16.1% were treated with antipsychotics. Among the study population, 51.9% of the NH residents and 67.4% of the patients living at home had only one psychotropic drug class prescribed. Living in a NH was significantly associated with the more frequent prescription of anxiolytic, hypnotic, and antipsychotic drugs, and with a greater number of psychotropic drug classes prescribed, whatever the severity of the dementia. CONCLUSION: We underlined the more frequent prescription of psychotropic drugs in NH residents regardless of MMSE scores.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cross-Sectional Studies; Databases, Factual; Dementia; Drug Prescriptions; Female; Humans; Male; Nursing Homes; Psychotropic Drugs; Residence Characteristics

Quantitative phosphoproteomic analyses of the inferior parietal lobule from three different pathological stages of Alzheimer's disease. - Triplett, Judy C; Swomley, Aaron M; Cai, Jian; Klein, Jon B; Butterfield, D Allan (J Alzheimers Dis, 2016)
Alzheimer's disease (AD), the most common age-related neurodegenerative disorder, is clinically characterized by progressive neuronal loss resulting in loss of memory and dementia. AD is histopathologically characterized by the extensive distribution of senile plaques and neurofibrillary tangles, and synapse loss. Amnestic mild cognitive impairment (MCI) is generally accepted to be an early stage of AD. MCI subjects have pathology and symptoms that fall on the scale intermediately between 'normal' cognition with little or no pathology and AD. A rare number of individuals, who exhibit normal cognition on psychometric tests but whose brains show widespread postmortem AD pathology, are classified as 'asymptomatic' or 'preclinical' AD (PCAD). In this study, we evaluated changes in protein phosphorylation states in the inferior parietal lobule of subjects with AD, MCI, PCAD, and control brain using a 2-D PAGE proteomics approach in conjunction with Pro-Q Diamond phosphoprotein staining. Statistically significant changes in phosphorylation levels were found in 19 proteins involved in energy metabolism, neuronal plasticity, signal transduction, and oxidative stress response. Changes in the disease state phosphoproteome may provide insights into underlying mechanisms for the preservation of memory with expansive AD pathology in PCAD and the progressive memory loss in amnestic MCI that escalates to the dementia and the characteristic pathology of AD brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Disease Progression; Female; Humans; Male; Memory; Neurofibrillary Tangles; Oxidative Stress; Parietal Lobe; Phosphorylation; Plaque, Amyloid; Proteome

Reduction of Amyloid-β Plasma Levels by Hemodialysis: An Anti-Amyloid Treatment Strategy? - Tholen, Susanne; Schmaderer, Christoph; Chmielewski, Stefan; Förstl, Hans; Heemann, Uwe; Baumann, Marcus; Steubl, Dominik; Grimmer, Timo (J Alzheimers Dis, 2016)
BACKGROUND: Cognitive impairment in hemodialysis patients is common, but the underlying pathogenesis remains unclear. Alzheimer's disease is the most common cause of dementia in the general elderly population. Histopathological hallmarks are, among others, senile plaques, which consist of amyloid-β (Aβ). OBJECTIVE: To measure plasma levels of Aβ42 and Aβ40 during hemodialysis and to examine potential associations with cognitive performance in cognitively impaired hemodialysis patients. METHODS: Plasma samples of 26 hemodialysis patients were collected shortly before, after 50% of dialysis time, and at the end of a dialysis session. Aβ42 and Aβ40 levels were measured by a high-sensitivity ELISA for human amyloid-β. Cognition was tested under standardized conditions using the Montreal Cognitive Assessment (MoCA) as proposed previously. RESULTS: Clearance rates of both peptides during one dialysis session were 22% and 35% for Aβ42 and Aβ40, respectively. Aβ42 but not Aβ40 baseline levels were significantly associated with MoCA test results (r = 0.654, p = 0.001). CONCLUSION: In cognitively impaired hemodialysis patients plasma Aβ42 levels were associated with cognitive performance and both Aβ42 and Aβ40 plasma levels could be effectively reduced by dialysis. By inducing peripheral Aβ sink, hemodialysis may be considered as an anti-amyloid treatment strategy.
Keywords: Adult; Aged; Aged, 80 and over; Amyloid beta-Peptides; Cognition Disorders; Enzyme-Linked Immunosorbent Assay; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Renal Dialysis

Regular Benzodiazepine and Z-Substance Use and Risk of Dementia: An Analysis of German Claims Data. - Gomm, Willy; von Holt, Klaus; Thomé, Friederike; Broich, Karl; Maier, Wolfgang; Weckbecker, Klaus; Fink, Anne; Doblhammer, Gabriele; Haenisch, Britta (J Alzheimers Dis, 2016)
BACKGROUND: While acute detrimental effects of benzodiazepine (BDZ), and BDZ and related z-substance (BDZR) use on cognition and memory are known, the association of BDZR use and risk of dementia in the elderly is controversially discussed. Previous studies on cohort or claims data mostly show an increased risk for dementia with the use of BDZs or BDZRs. For Germany, analyses on large population-based data sets are missing. OBJECTIVE: To evaluate the association between regular BDZR use and incident any dementia in a large German claims data set. METHODS: Using longitudinal German public health insurance data from 2004 to 2011 we analyzed the association between regular BDZR use (versus no BDZR use) and incident dementia in a case-control design. We examined patient samples aged≥60 years that were free of dementia at baseline. To address potential protopathic bias we introduced a lag time between BDZR prescription and dementia diagnosis. Odds ratios were calculated applying conditional logistic regression, adjusted for potential confounding factors such as comorbidities and polypharmacy. RESULTS: The regular use of BDZRs was associated with a significant increased risk of incident dementia for patients aged≥60 years (adjusted odds ratio [OR] 1.21, 95% confidence interval [CI] 1.13-1.29). The association was slightly stronger for long-acting substances than for short-acting ones. A trend for increased risk for dementia with higher exposure was observed. CONCLUSION: The restricted use of BDZRs may contribute to dementia prevention in the elderly.

Relative Alterations in Blood-Based Levels of Sestrin in Alzheimer's Disease and Mild Cognitive Impairment Patients. - Rai, Nitish; Kumar, Rahul; Desai, Gaurav Rajesh; Venugopalan, G; Shekhar, Shashank; Chatterjee, Prasun; Tripathi, Manjari; Upadhyay, Ashish Datt; Dwivedi, Sadanand; Dey, Aparajit B; Dey, Sharmistha (J Alzheimers Dis, 2016)
Sestrins (sesn) are highly conserved proteins that play an important neuroprotective role, in part as a consequence of their antioxidative capacity, which prevents reactive oxygen species formation. In this study, we evaluated the concentrations of sesn1 and sesn2 in the serum of 41 Alzheimer's disease (AD) patients, 27 mild cognitive impairment (MCI), and 60 elderly controls, by surface plasmon resonance, which was validated by using western blot. Moreover, the mRNA level of sestrins in all the study groups was determined by real time polymerase chain reaction. The results showed significant overexpression of serum sesn2 protein and mRNA levels in the AD group compared to MCI and elderly control groups. A difference in serum sesn2 concentration between MCI and the control group was also evident. ROC analysis showed highly sensitive, selective cutoff values for sens2 in the differentiation of AD, MCI, and controls. No significant difference in sesn1 level was observed among the study groups. This study highlights the important role of sesn2 in the progression of the AD, indicating its potential utility as a protein marker in this devastating disease.

The Role of Physical Fitness in the Neurocognitive Performance of Task Switching in Older Persons with Mild Cognitive Impairment. - Tsai, Chia-Liang; Pai, Ming-Chyi; Ukropec, Jozef; Ukropcová, Barbara (J Alzheimers Dis, 2016)
Although elderly people with amnestic mild cognitive impairment (aMCI) have been found to show impaired behavioral performance in task switching, no research has yet explored the electrophysiological mechanisms and the potential correlation between physical fitness and neurocognitive (i.e., behavioral and electrophysiological) performance in aMCI. The present study was thus aimed to examine whether there are differences in electrophysiological (i.e., event-related potential) performance between aMCI participants and controls when performing a task-switching paradigm, and to investigate the role of physical fitness in the relationship between neurocognitive performance and aMCI. Sixty participants were classified into aMCI (n = 30) and control (n = 30) groups, and performed a task-switching paradigm with concomitant electrophysiological recording, as well as underwent senior functional physical fitness tests. The aMCI group showed comparable scores on most parts of the physical fitness tests, but reduced lower body flexibility and VO2max as compared to the control group. When performing the task-switching paradigm, the aMCI group showed slower reaction times in the heterogeneous condition and larger global switching costs, although no significant difference was observed in accuracy rates between the two groups. In addition, the aMCI group showed significantly prolonged P3 latencies in the homogeneous and heterogeneous conditions, and a smaller P3 amplitude only in the heterogeneous condition. The level of cardiorespiratory fitness was significantly correlated with P3 amplitude in the aMCI group, particularly in the heterogeneous condition of the task-switching paradigm. These results show that the aMCI group exhibited abnormalities in their neurocognitive performance when performing the task-switching paradigm and such a deficit was likely associated with reduced cardiorespiratory fitness, which was shown to be the important predictor of neurocognitive performance.

Safety and Efficacy of Medical Cannabis Oil for Behavioral and Psychological Symptoms of Dementia: An-Open Label, Add-On, Pilot Study. - Shelef, Assaf; Barak, Yoram; Berger, Uri; Paleacu, Diana; Tadger, Shelly; Plopsky, Igor; Baruch, Yehuda (J Alzheimers Dis, 2016)
BACKGROUND: Tetrahydrocannabinol (THC) is a potential treatment for Alzheimer's disease (AD). OBJECTIVE: To measure efficacy and safety of medical cannabis oil (MCO) containing THC as an add-on to pharmacotherapy, in relieving behavioral and psychological symptoms of dementia (BPSD). METHODS: Eleven AD patients were recruited to an open label, 4 weeks, prospective trial. RESULTS: Ten patients completed the trial. Significant reduction in CGI severity score (6.5 to 5.7; p <  0.01) and NPI score were recorded (44.4 to 12.8; p <  0.01). NPI domains of significant decrease were: Delusions, agitation/aggression, irritability, apathy, sleep and caregiver distress. CONCLUSION: Adding MCO to AD patients' pharmacotherapy is safe and a promising treatment option.
Keywords: Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Cognition Disorders; Dementia; Female; Humans; Male; Medical Marijuana; Neuropsychological Tests; Outcome Assessment (Health Care); Physical Examination; Pilot Projects; Prospective Studies; Psychiatric Status Rating Scales

Salidroside, a Bioactive Compound of Rhodiola Rosea, Ameliorates Memory and Emotional Behavior in Adult Mice. - Palmeri, Agostino; Mammana, Leonardo; Tropea, Maria Rosaria; Gulisano, Walter; Puzzo, Daniela (J Alzheimers Dis, 2016)
Rhodiola Rosea (R. Rosea) is a plant used in traditional popular medicine to enhance cognition and physical performance. R. Rosea medicinal properties have been related to its capability to act as an adaptogen, i.e., a substance able to increase the organism's resistance to a variety of chemical, biological, and physical stressors in a non-specific way. These adaptogen properties have been mainly attributed to the glycoside salidroside, one of the bioactive compounds present in the standardized extracts of R. Rosea. Here, we aimed to investigate whether a single dose of salidroside is able to affect memory and emotional behavior in wild type adult mice. We performed fear conditioning to assess cued and contextual memory, elevated plus maze and open field to evaluate anxiety, and tail suspension test to evaluate depression. Our results showed that a single i.p. administration of salidroside was able to enhance fear memory and exerted an anxiolytic and antidepressant effect. These data confirmed the adaptogenic effect of R. Rosea bioactive compounds in animal models and suggest that salidroside might represent an interesting pharmacological tool to ameliorate cognition and counteract mood disorders.
Keywords: Animals; Anti-Anxiety Agents; Antidepressive Agents; Anxiety Disorders; Conditioning (Psychology); Depressive Disorder; Disease Models, Animal; Drug Evaluation, Preclinical; Exploratory Behavior; Fear; Female; Freezing Reaction, Cataleptic; Glucosides; Male; Maze Learning; Memory; Mice, Inbred C57BL; Motor Activity; Nootropic Agents; Phenols; Phytotherapy; Plant Extracts; Rhodiola

The Savvy Caregiver Program: A Probe Multicenter Randomized Controlled Pilot Trial in Caregivers of Patients Affected by Alzheimer's Disease. - Sepe-Monti, Micaela; Vanacore, Nicola; Bartorelli, Luisa; Tognetti, Alessandra; Giubilei, Franco (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a major cause of disability in the elderly, leading to a considerable burden on caregivers and high costs to society. Psycho-education programs such as the Savvy Caregiver Program (SCP) are reported to be a successful means of reducing caregivers' distress through various intervention strategies. The aim of the present study was to assess the efficacy of the SCP in reducing the burden and psychological symptoms in caregivers of AD patients and to analyze the coping strategies adopted by the caregivers. The study was designed as a multicenter, randomized, controlled, pilot clinical trial. One hundred and sixty-four caregivers of patients with probable AD were randomized. The SCP was structured in six, weekly, two-hour sessions. All the clinical scales were administered before treatment, two weeks and six months after treatment. Caregivers in the SCP group displayed better coping strategies adopted to positive attitudes, and they tended to be less anxious and less depressed than those in the control group. However, caregiver burden levels were not reduced in SCP caregivers. The patients of SCP caregivers received a lower number of new prescriptions of neuroleptics during the 6 months of follow-up than the patients of control caregivers and apathy was the neuropsychiatric symptom that improved most as a result of the SCP. The results of this study suggest that the SCP may improve coping strategies of caregivers of people affected by AD, influencing their psychological symptoms and those of their patients.

Screening for Mild Cognitive Impairment: Comparison of "MCI Specific" Screening Instruments. - O'Caoimh, Rónán; Timmons, Suzanne; Molloy, D William (J Alzheimers Dis, 2016)
BACKGROUND: Sensitive and specific instruments are required to screen for cognitive impairment (CI) in busy clinical practice. The Montreal Cognitive Assessment (MoCA) is widely validated but few studies compare it to tests designed specifically to detect mild cognitive impairment (MCI). OBJECTIVE: Comparison of two "MCI specific" screens: the Quick Mild Cognitive Impairment screen (Qmci) and MoCA. METHODS: Patients with subjective memory complaints (SMC; n = 73), MCI (n = 103), or dementia (n = 274), were referred to a university hospital memory clinic and underwent comprehensive assessment. Caregivers, without cognitive symptoms, were recruited as normal controls (n = 101). RESULTS: The Qmci was more accurate than the MoCA in differentiating MCI from controls, area under the curve (AUC) of 0.90 versus 0.80, p = 0.009. The Qmci had greater (AUC 0.81), albeit non-significant, accuracy than the MoCA (AUC 0.73) in separating MCI from SMC, p = 0.09. At its recommended cut-off (<62/100), the Qmci had a sensitivity of 90% and specificity of 87% for CI (MCI/dementia). Raising the cut-off to <65 optimized sensitivity (94%), reducing specificity (80%). At <26/30 the MoCA had better sensitivity (96%) but poor specificity (58%). A MoCA cut-off of <24 provided the optimal balance. Median Qmci administration time was 4.5 (±1.3) minutes compared with 9.5 (±2.8) for the MoCA. CONCLUSIONS: Although both tests distinguish MCI from dementia, the Qmci is particularly accurate in separating MCI from normal cognition and has shorter administration times, suggesting it is more useful in busy hospital clinics. This study reaffirms the high sensitivity of the MoCA but suggests a lower cut-off (<24) in this setting.
Keywords: Aged; Aged, 80 and over; Area Under Curve; Cognitive Dysfunction; Dementia; Diagnosis, Differential; Female; Humans; Male; Neuropsychological Tests; Perception; ROC Curve; Sensitivity and Specificity; Time Factors

Searching for Primary Predictors of Conversion from Mild Cognitive Impairment to Alzheimer's Disease: A Multivariate Follow-Up Study. - López, María Eugenia; Turrero, Agustín; Cuesta, Pablo; López-Sanz, David; Bruña, Ricardo; Marcos, Alberto; Gil, Pedro; Yus, Miguel; Barabash, Ana; Cabranes, José Antonio; Maestú, Fernando; Fernández, Alberto (J Alzheimers Dis, 2016)
Recent proposals of diagnostic criteria within the healthy aging-Alzheimer's disease (AD) continuum stressed the role of biomarker information. More importantly, such information might be critical to predict those mild cognitive impairment (MCI) patients at a higher risk of conversion to AD. Usually, follow-up studies utilize a reduced number of potential markers although the conversion phenomenon may be deemed as multifactorial in essence. In addition, not only biological but also cognitive markers may play an important role. Considering this background, we investigated the role of cognitive reserve, cognitive performance in neuropsychological testing, hippocampal volumes, APOE genotype, and magnetoencephalography power sources to predict the conversion to AD in a sample of 33 MCI patients. MCIs were followed up during a 2-year period and divided into two subgroups according to their outcome: The "stable" MCI group (sMCI, 21 subjects) and the "progressive" MCI group (pMCI, 12 subjects). Baseline multifactorial information was submitted to a hierarchical logistic regression analysis to build a predictive model of conversion to AD. Results indicated that the combination of left hippocampal volume, occipital cortex theta power, and clock drawing copy subtest scores predicted conversion to AD with a 100% of sensitivity and 94.7% of specificity. According to these results it might be suggested that anatomical, cognitive, and neurophysiological markers may be considered as "first order" predictors of progression to AD, while APOE or cognitive reserve proxies might play a more secondary role.

Self-Perceived Quality of Life Among Patients with Alzheimer's Disease: Two Longitudinal Models of Analysis. - Conde-Sala, Josep L; Turró-Garriga, Oriol; Portellano-Ortiz, Cristina; Viñas-Diez, Vanesa; Gascón-Bayarri, Jordi; Reñé-Ramírez, Ramón (J Alzheimers Dis, 2016)
The objective was to analyze the factors that influence self-perceived quality of life (QoL) in patients with Alzheimer's disease (AD), contrasting two different longitudinal models. A total of 127 patients were followed up over 24 months. The instruments applied were: Quality of Life in Alzheimer's Disease scale (QoL-AD), Geriatric Depression Scale-15, Anosognosia Questionnaire-Dementia, Disability Assessment in Dementia, Neuropsychiatric Inventory, and the Mini-Mental State Examination. Two models for grouping patients were tested: 1) Baseline score on the QoL-AD (QoL-Baseline), and 2) Difference in QoL-AD score between baseline and follow-up (QoL-Change). Generalized estimating equations were used to analyze longitudinal data, and multinomial regression analyses were performed. Over the follow-up period the QoL-Baseline model showed greater variability between groups (Wald χ2 = 172.3, p < 0.001) than did the QoL-Change model (Wald χ2  = 1.7, p = 0.427). In the QoL-Baseline model the predictive factors were greater depression (odds ratio [OR] = 1.20; 95% CI: 1.00- 1.45) and lower functional ability (OR = 0.92; 95% CI: 0.85- 0.99) for the Low QoL group (< 33 QoL-AD), and less depression (OR = 0.68; 95% CI: 0.52- 0.88), more anosognosia (OR = 1.07; 95% CI: 1.01- 1.13), and fewer neuropsychiatric symptoms (OR = 0.95; 95% CI: 0.91- 0.99) for the High-QoL group (>37 QoL-AD). The model based on baseline scores (QoL-Baseline) was better than the QoL-Change model in terms of identifying trajectories and predictors of QoL in AD.

Shear-Induced Amyloid Formation in the Brain: I. Potential Vascular and Parenchymal Processes. - Trumbore, Conrad N (J Alzheimers Dis, 2016)
Shear distortion of amyloid-beta (Aβ) solutions accelerates amyloid cascade reactions that may yield different toxic oligomers than those formed in quiescent solutions. Recent experiments indicate that cerebrospinal fluid (CSF) and interstitial fluid (ISF) containing Aβ flow through narrow brain perivascular pathways and brain parenchyma. This paper suggests that such flow causes shear distortion of Aβ molecules involving conformation changes that may be one of the initiating events in the etiology of Alzheimer's disease. Aβ shearing can occur in or around brain arteries and arterioles and is suggested as the origin of cerebral amyloid angiopathy deposits in cerebrovascular walls. Comparatively low flow rates of ISF within the narrow extracellular spaces (ECS) of the brain parenchyma are suggested as a possible initiating factor in both the formation of neurotoxic Aβ42 oligomers and amyloid fibrils. Aβ42 in slow-flowing ISF can gain significant shear energy at or near the walls of tortuous brain ECS flow paths, promoting the formation of a shear-distorted, excited state hydrophobic Aβ42* conformation. This Aβ42* molecule could possibly be involved in one of two paths, one involving rapid adsorption to a brain membrane surface, ultimately forming neurotoxic oligomers on membranes, and the other ultimately forming plaque within the ECS flow pathways. Rising Aβ concentrations combined with shear at or near critical brain membranes are proposed as contributing factors to Alzheimer's disease neurotoxicity. These hypotheses may be applicable in other neurodegenerative diseases, including tauopathies and alpha-synucleinopathies, in which shear-distorted proteins also may form in the brain ECS.

Specific Binding of Cu(II) Ions to Amyloid-Beta Peptides Bound to Aggregation-Inhibiting Molecules or SDS Micelles Creates Complexes that Generate Radical Oxygen Species. - Tiiman, Ann; Luo, Jinghui; Wallin, Cecilia; Olsson, Lisa; Lindgren, Joel; Jarvet, Jϋri; Per, Roos; Sholts, Sabrina B; Rahimipour, Shai; Abrahams, Jan Pieter; Karlström, Amelie Eriksson; Gräslund, Astrid; et al. (J Alzheimers Dis, 2016)
Aggregation of the amyloid-beta (Aβ) peptide into insoluble plaques is a major factor in Alzheimer's disease (AD) pathology. Another major factor in AD is arguably metal ions, as metal dyshomeostasis is observed in AD patients, metal ions modulate Aβ aggregation, and AD plaques contain numerous metals including redox-active Cu and Fe ions. In vivo, Aβ is found in various cellular locations including membranes. So far, Cu(II)/Aβ interactions and ROS generation have not been investigated in a membrane environment. Here, we study Cu(II) and Zn(II) interactions with Aβ bound to SDS micelles or to engineered aggregation-inhibiting molecules (the cyclic peptide CP-2 and the ZAβ3(12-58)Y18L Affibody molecule). In all studied systems the Aβ N-terminal segment was found to be unbound, unstructured, and free to bind metal ions. In SDS micelles, Aβ was found to bind Cu(II) and Zn(II) with the same ligands and the same KD as in aqueous solution. ROS was generated in all Cu(II)/Aβ complexes. These results indicate that binding of Aβ to membranes, drugs, and other entities that do not interact with the Aβ N-terminal part, appears not to compromise the N-terminal segment's ability to bind metal ions, nor impede the capacity of N-terminally bound Cu(II) to generate ROS.

Stability of Progranulin Under Pre-Analytical Conditions in Serum and Cerebrospinal Fluid. - Willemse, Eline A J; Durieux-Lu, Sisi; van der Flier, Wiesje M; Pijnenburg, Yolande A L; de Jonge, Robert; Teunissen, Charlotte E (J Alzheimers Dis, 2016)
Progranulin (PGRN) levels in blood and cerebrospinal fluid (CSF) are increasingly studied as potential markers for neurodegenerative disorders. We aimed to 1) characterize two commercially available PGRN ELISAs on several assay validation parameters, 2) assess the stability of PGRN in serum and CSF under pre-analytical conditions, and 3) compare stability in the two assays. Intra- and inter-assay variation, inter-lot variation, linearity, lower limit of detection, and kit correlations were assessed for the Adipogen and R&D PGRN ELISA kits. Blood and serum samples were experimentally exposed to ≤9 freeze/thaw cycles, delayed processing for ≤24 h at room temperature and 4°C, and to temperature stability tests for ≤3 weeks at -20°C, 4°C, room temperature, and 37°C. Both commercial PGRN ELISA kits showed acceptable ranges for intra- and inter-assay variation, where the R&D kit performed more accurate than the Adipogen kit, especially for inter-assay variation (intra-assay serum: 6.7 and 8.3%, respectively; inter-assay serum: 9.2 and 21.0%; intra-assay CSF: 3.6 and 12.0%; inter-assay CSF: 16.0 and 44.5%). Absolute serum PGRN concentrations were 1.9-fold higher in Adipogen than R&D (p < 0.001) and strongly correlated between both kits (ρ= 0.86, p < 0.0001) and CSF PGRN levels were on the borderline of detection in both kits. PGRN was typically stable under all pre-analytical conditions addressed, although two weeks at 37°C resulted in decreased PGRN concentrations in CSF, only when using the Adipogen kit. These results support further examination of PGRN as a potential marker in neurodegenerative diseases, since PGRN is stable in serum and CSF and can be measured using ELISA kits from several providers.

The Synergistic Roles of the Chronic Prenatal and Offspring Stress Exposures in Impairing Offspring Learning and Memory. - Tang, Wei; Cheng, Juan; Wang, Zheng-Yu; Chen, Ke-Yang; Han, Zhen-Min; Wang, Qi-Hong; Yao, Yu-You (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), extensive experimental studies have demonstrated a negative impact of chronic stress during various stages of life (including prenatal phase) on some aspects of AD pathology. Nevertheless, presently, few studies have been involved in the learning and memory impairments, as well as neuropathology elicited by the chronic prenatal stress (CPS) and the chronic offspring stress (COS) exposures simultaneously, particularly for the adult male APPswe/PS1dE9 murine offspring. Therefore, the aim of the present study was to investigate the influence of CPS on learning and memory impairments induced by COS in 6-month-old male APPswe/PS1dE9 offspring mice and the related mechanism. Our study firstly demonstrates that 14-day exposure to CPS could exacerbate the learning and memory impairments, as well as neuropathological damages in the CA3 regions of the hippocampus and cortex neurons, which is induced by the 28-day exposure to COS in 6-month-old male APPswe/PS1dE9 offspring mice. In addition, CPS could potentiate the production of AβPP, Aβ42, and corticosterone in 6-month-old male APPswe/PS1dE9 offspring that also suffer COS. In conclusion, our novel findings strongly implicate the synergistic roles of the CPS and COS exposures in impairing offspring learning and memory. Moreover, CPS potentiating the production of Aβ42 might be mediated by glucocorticoids through increasing the expression of APP and BACE1 gene.

T3D-959: A Multi-Faceted Disease Remedial Drug Candidate for the Treatment of Alzheimer's Disease. - Tong, Ming; Deochand, Chetram; Didsbury, John; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: T3D-959, a dual PPAR-δ/PPAR γ nuclear receptor agonist and former diabetes drug candidate, has been repositioned as an Alzheimer's disease (AD)-modifying therapy. OBJECTIVE: This study examines the effectiveness and mechanisms of T3D-959's therapeutic effects using in vivo and ex vivo rat models of sporadic AD. METHODS: A sporadic AD model was generated by intracerebral (i.c.) administration of streptozotocin (STZ). Control and i.c. STZ treated rats were gavaged with saline or T3D-959 (0.3 to 3.0 mg/kg/day) for 28 days. Spatial learning and memory were evaluated using the Morris water maze test. Frontal lobe slice cultures generated 24 hours after i.c. STZ or vehicle were used to study early effects of T3D-959 (0.5-1.0 μM) on viability and molecular markers of AD. RESULTS: T3D-959 significantly improved spatial learning and memory in i.c STZ-treated rats. Mechanistically, T3D-959 significantly improved culture viability and brain morphology, reduced levels of oxidative stress and Aβ, and normalized expression of phospho-tau, choline acetyltransferase, and myelin-associated glycoprotein. Protective effects occurred even at the lowest tested dose of T3D-959. CONCLUSIONS: Pre-clinical proof of concept has been demonstrated that T3D-959 can improve multiple pathologies of AD resulting in significant improvements in cognitive function and molecular and biochemical indices of neurodegeneration. These results support the theses that (1) effective disease modification in AD can be achieved by targeting relevant nuclear receptors, and (2) treating AD as a metabolic disease has the potential to be disease remedial. A Phase 2a trial of T3D-959 in mild-to-moderate AD patients has been initiated (ClinicalTrials.gov identifier NCT02560753).
Keywords: Alzheimer Disease; Analysis of Variance; Animals; Animals, Newborn; Antibiotics, Antineoplastic; Antipsychotic Agents; Blood Glucose; Body Weight; Brain; Choline O-Acetyltransferase; Disease Models, Animal; Dose-Response Relationship, Drug; Glial Fibrillary Acidic Protein; Glucosephosphate Dehydrogenase; In Vitro Techniques; Maze Learning; Myelin Basic Protein; Neurotoxicity Syndromes; Organ Culture Techniques; PPAR delta; PPAR gamma; Rats; Rats, Long-Evans; Spatial Learning; Streptozocin

A TgCRND8 Mouse Model of Alzheimer's Disease Exhibits Sexual Dimorphisms in Behavioral Indices of Cognitive Reserve. - Granger, Matthew W; Franko, Bettina; Taylor, Matthew W; Messier, Claude; George-Hyslop, Peter St; Bennett, Steffany A L (J Alzheimers Dis, 2016)
Cognitive decline is sexually dimorphic in Alzheimer's disease (AD). Men show higher incidences of amnestic mild cognitive impairment yet women disproportionally phenoconvert to AD. It is hypothesized that men maintain greater cognitive reserve than women under comparable amyloid-β (Aβ) challenge. One behavioral aspect of cognitive reserve in mice is the capacity to cope with Aβ-associated stereotypies by switching to increasingly effective navigational search strategies in the Morris water maze. To explore inherent sex differences in this paradigm, however, we require an AβPP mouse model wherein behavioral flexibility is impaired earlier in females than males despite equivalent Aβ load. Here, we show that when F1 C57Bl/6×C3H/HeJ TgCRND8 mice are placed on C57Bl/6 background, N5 Tg males and females exhibit equivalent Aβ pathologies at 2, 4, 6, and 8 months of age yet females display learning and memory deficits earlier than males. We further show that this N5 line does not carry the autosomal recessive pde6brd1 mutation that impairs visual acuity and that the estrous cycle is not disrupted on this genetic background. At 5.5 months of age, Tg males, but not females, compensate for Aβ-associated stereotypic behaviors (i.e., hyperactive tight circling) by alternating navigational search strategies and adopting increasingly productive spatial search strategies. Females fail to overcome Aβ-associated stereotypies and do not efficiently switch from systematic to spatial learning strategies. Together, these data identify a novel AβPP mouse model that can be used for preclinical testing of interventions targeting sexual dimorphisms in behavioral indices of cognitive reserve.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognitive Reserve; Cyclic Nucleotide Phosphodiesterases, Type 6; Disease Models, Animal; Female; Humans; Male; Maze Learning; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Plaque, Amyloid; Psychomotor Performance; Sex Characteristics; Spatial Memory; Spatial Navigation; Survival Analysis

Time Orientation and 10 Years Risk of Dementia in Elderly Adults: The Three-City Study. - Dumurgier, Julien; Dartigues, Jean-François; Gabelle, Audrey; Paquet, Claire; Prevot, Magali; Hugon, Jacques; Tzourio, Christophe (J Alzheimers Dis, 2016)
Time disorientation is commonly observed in dementia, however very little is known about the pathological significance of minor time errors in community-dwelling population. Our objective was to investigate the relationship between time orientation and risk of dementia in a population of older adults. Analyses relies on 8611 dementia-free subjects from the Three-City Study, France. Participants were followed up for 10 years for incident dementia. Time orientation was assessed by asking for the date, the day of the week, the month, the season and the year. At baseline, 905 subjects made at least one error in time orientation. During 57,073 person-years of follow-up, 827 participants developed dementia. After controlling for age, gender and education level, subjects with one error in time had a greater risk of dementia (hazard ratio [HR] 1.44 [1.18-1.77]), while those with at least 2 errors had a more than three-fold increased risk (HR 3.10 [1.98-4.83]). This association was particularly marked for the diagnosis of probable Alzheimer's disease. Time disorientation was associated with an increased risk of dementia in a large population of cognitively normal older people followed during up to 10 years and should not be underestimated in clinical setting.

Tobacco Smoke Exposure Impairs Brain Insulin/IGF Signaling: Potential Co-Factor Role in Neurodegeneration. - Deochand, Chetram; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Human studies suggest tobacco smoking is a risk factor for cognitive impairment and neurodegeneration, including Alzheimer's disease (AD). However, experimental data linking tobacco smoke exposures to underlying mediators of neurodegeneration, including impairments in brain insulin and insulin-like growth factor (IGF) signaling in AD are lacking. OBJECTIVE: This study tests the hypothesis that cigarette smoke (CS) exposures can impair brain insulin/IGF signaling and alter expression of AD-associated proteins. METHODS: Adult male A/J mice were exposed to air for 8 weeks (A8), CS for 4 or 8 weeks (CS4, CS8), or CS8 followed by 2 weeks recovery (CS8+R). Gene expression was measured by qRT-PCR analysis and proteins were measured by multiplex bead-based or direct binding duplex ELISAs. RESULTS: CS exposure effects on insulin/IGF and insulin receptor substrate (IRS) proteins and phosphorylated proteins were striking compared with the mRNA. The main consequences of CS4 or CS8 exposures were to significantly reduce insulin R, IGF-1R, IRS-1, and tyrosine phosphorylated insulin R and IGF-1R proteins. Paradoxically, these effects were even greater in the CS8+R group. In addition, relative levels of S312-IRS-1, which inhibits downstream signaling, were increased in the CS4, CS8, and CS8+R groups. Correspondingly, CS and CS8+R exposures inhibited expression of proteins and phosphoproteins required for signaling through Akt, PRAS40, and/or p70S6K, increased AβPP-Aβ, and reduced ASPH protein, which is a target of insulin/IGF-1 signaling. CONCLUSION: Secondhand CS exposures caused molecular and biochemical abnormalities in brain that overlap with the findings in AD, and many of these effects were sustained or worsened despite short-term CS withdrawal.
Keywords: Animals; Brain; Insulin; Male; Mice; Nerve Degeneration; Neurons; Phosphorylation; Receptor, IGF Type 1; Signal Transduction; Somatomedins; Tobacco Smoke Pollution

Tobacco Smoke-Induced Brain White Matter Myelin Dysfunction: Potential Co-Factor Role of Smoking in Neurodegeneration. - Yu, Rosa; Deochand, Chetram; Krotow, Alexander; Leão, Raiane; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis studies showed that smokers have increased risk for developing Alzheimer's disease (AD) compared with non-smokers, and neuroimaging studies revealed that smoking damages white matter structural integrity. OBJECTIVE: The present study characterizes the effects of side-stream (second hand) cigarette smoke (CS) exposures on the expression of genes that regulate oligodendrocyte myelin-synthesis, maturation, and maintenance and neuroglial functions. METHODS: Adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). The frontal lobes were used for histology and qRT-PCR analysis. RESULTS: Luxol fast blue, Hematoxylin and Eosin stained histological sections revealed CS-associated reductions in myelin staining intensity and narrowing of the corpus callosum. CS exposures broadly decreased mRNA levels of immature and mature oligodendrocyte myelin-associated, neuroglial, and oligodendrocyte-related transcription factors. These effects were more prominent in the CS8 compared with CS4 group, suggesting that molecular abnormalities linked to white matter atrophy and myelin loss worsen with duration of CS exposure. Recovery normalized or upregulated less than 25% of the suppressed genes; in most cases, inhibition of gene expression was either sustained or exacerbated. CONCLUSION: CS exposures broadly inhibit expression of genes needed for myelin synthesis and maintenance. These adverse effects often were not reversed by short-term CS withdrawal. The results support the hypothesis that smoking contributes to white matter degeneration, and therefore could be a key risk factor for a number of neurodegenerative diseases, including AD.
Keywords: 2',3'-Cyclic-Nucleotide Phosphodiesterases; AC133 Antigen; Animals; Antigens, CD; Brain; Disease Models, Animal; Galactosylceramides; Gene Expression Regulation; Glycoproteins; Leukoencephalopathies; Male; Mice; Nerve Degeneration; Nerve Tissue Proteins; Neuroglia; Neurons; Oligodendroglia; Papain; Peptides; Smoking; Tobacco; Transcription Factors

Transcriptional Analysis of Blood Lymphocytes and Skin Fibroblasts, Keratinocytes, and Endothelial Cells as a Potential Biomarker for Alzheimer's Disease. - Mukhamedyarov, Marat A; Rizvanov, Albert A; Yakupov, Eduard Z; Zefirov, Andrey L; Kiyasov, Andrey P; Reis, Helton J; Teixeira, Antônio L; Vieira, Luciene B; Lima, Luciana M; Salafutdinov, Ilnur I; Petukhova, Elena O; Khaiboullina, Svetlana F; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a devastating and progressive form of dementia that is typically associated with a build-up of amyloid-β plaques and hyperphosphorylated and misfolded tau protein in the brain. Presently, there is no single test that confirms AD; therefore, a definitive diagnosis is only made after a comprehensive medical evaluation, which includes medical history, cognitive tests, and a neurological examination and/or brain imaging. Additionally, the protracted prodromal phase of the disease makes selection of control subjects for clinical trials challenging. In this study we have utilized a gene-expression array to screen blood and skin punch biopsy (fibroblasts, keratinocytes, and endothelial cells) for transcriptional differences that may lead to a greater understanding of AD as well as identify potential biomarkers. Our analysis identified 129 differentially expressed genes from blood of dementia cases when compared to healthy individuals, and four differentially expressed punch biopsy genes between AD subjects and controls. Additionally, we identified a set of genes in both tissue compartments that showed transcriptional variation in AD but were largely stable in controls. The translational products of these variable genes are involved in the maintenance of the Golgi structure, regulation of lipid metabolism, DNA repair, and chromatin remodeling. Our analysis potentially identifies specific genes in both tissue compartments that may ultimately lead to useful biomarkers and may provide new insight into the pathophysiology of AD.

Unmet Needs of Community-Dwelling Primary Care Patients with Dementia in Germany: Prevalence and Correlates. - Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Teipel, Stefan; Kilimann, Ingo; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: To provide an optimal care for persons with dementia (PWD), their individual unmet needs have to be identified and comprehensively addressed. OBJECTIVES: Present analyses aim to describe the number and types of unmet needs of German primary care patients screened positive for dementia and factors associated with the number of unmet needs. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized controlled intervention trial. Analyses are based on the baseline data of 227 PWD (≥70 years, living at home) of the intervention group who had screened positive for dementia (DemTect<9) and received a standardized computer-assisted needs assessment. RESULTS: PWD had on average 8.77±5.04 unmet needs (Range = 0-31). More than 90% of the PWD had three or more unmet needs. Unmet needs were identified across all predefined 26 subcategories. The majority of unmet needs occurred in the domains "nursing treatment and care" (38%), "social counseling and legal support" (20%), and "pharmacological treatment and care" (15%). More impairment in the activities of daily living was the only factor that was significantly associated with a higher number of unmet needs, independent of age, gender, living situation, presence of an informal caregiver, cognitive impairment, and depression. CONCLUSIONS: Present results demonstrate that community-dwelling PWD had a broad range of varying unmet needs. These findings emphasize the importance of a comprehensive needs assessment that allows the identification of individual needs as the basis for a tailored intervention- such as Dementia Care Management- that can address these needs.
Keywords: Aged, 80 and over; Caregivers; Cross-Sectional Studies; Dementia; Depression; Female; Germany; Health Services Needs and Demand; Humans; Male; Needs Assessment; Prevalence

Vascular Risk Factors and Cognition in Parkinson's Disease. - Pilotto, Andrea; Turrone, Rosanna; Liepelt-Scarfone, Inga; Bianchi, Marta; Poli, Loris; Borroni, Barbara; Alberici, Antonella; Premi, Enrico; Formenti, Anna; Bigni, Barbara; Cosseddu, Maura; Cottini, Elisabetta; et al. (J Alzheimers Dis, 2016)
Vascular risk factors have been associated with cognitive deficits and incident dementia in the general population, but their role on cognitive dysfunction in Parkinson's disease (PD) is still unclear. The present study addresses the single and cumulative effect of vascular risk factors on cognition in PD patients, taking clinical confounders into account. Standardized neuropsychological assessment was performed in 238 consecutive PD patients. We evaluated the association of single and cumulative vascular risk factors (smoking, diabetes, hypercholesterolemia, hypertension, and heart disease), with the diagnosis of PD normal cognition (PDNC, n = 94), mild cognitive impairment (PD-MCI, n = 111), and dementia (PDD, n = 33). The association between single neuropsychological tests and vascular risk factors was evaluated with covariance analyses adjusted for age at onset, educational levels, gender, disease duration, and motor performance. Age, educational levels, disease duration, and motor function were significantly different between PDNC, PD-MCI, and PDD. Heart disease was the only vascular factor significantly more prevalent in PDD compared with PDNC in adjusted analyses. Performance of tests assessing executive and attention functions were significantly worse in patients with hypertension, heart disease, and/or diabetes (p <  0.05). Heart disease is associated with dementia in PD, suggesting a potential window of intervention. Vascular risk factors act especially on attention and executive functions in PD. Vascular risk stratification may be useful in order to identify PD patients with a greater risk of developing dementia. These findings need to be verified in longitudinal studies.
Keywords: Age of Onset; Aged; Attention; Disability Evaluation; Educational Status; Executive Function; Female; Humans; Male; Motor Activity; Neuropsychological Tests; Parkinson Disease; Prevalence; Risk Factors; Sex Factors; Time Factors; Vascular Diseases

Ventilatory Response to Hypercapnia Predicts Dementia with Lewy Bodies in Late-Onset Major Depressive Disorder. - Takahashi, Sho; Mizukami, Katsuyoshi; Arai, Tetsuaki; Ogawa, Ryoko; Kikuchi, Norihiro; Hattori, Satoshi; Darby, David; Asada, Takashi (J Alzheimers Dis, 2016)
BACKGROUND: Studies have shown that developing major depressive disorder (MDD) at 50 years of age or older can predict dementia. Depression is particularly common in dementia with Lewy bodies (DLB), and occasionally occurs before the onset of extrapyramidal symptoms. Moreover, systemic autonomic dysfunction, including an abnormal ventilatory response to hypercapnia (VRH), is common in patients with DLB. OBJECTIVE: Here, we aimed to determine whether the VRH is useful for distinguishing depression that is predictive of DLB from other types of MDD. METHODS: Participants were 35 consecutive patients with first onset MDD at 50 years or older with bradykinesia. After diagnosing the clinical subtype of MDD according to DSM-IV criteria, each subject underwent a battery of psychological tests, autonomic examinations including VRH, brain magnetic resonance imaging, and 123I-meta-iodobenzylguanidine scintigraphy. RESULTS: Longitudinal follow-up showed that all 18 patients with abnormal VRH results developed DLB, whereas none of the 17 patients with normal VRH results converted to DLB within the study period (sensitivity: 100% , specificity: 100%). Additionally, over half of the DLB converters showed abnormalities on other autonomic examinations. For converters, the most common MDD subtype had psychotic and melancholic features simultaneously. The frequency of hypersensitivity to psychotropics was higher in converters than it was in non-converters. CONCLUSION: In the present study, patients with abnormal VRH results were very likely to develop DLB. Thus, for patients with late-onset MDD accompanied by bradykinesia, the VRH in combination with the clinical subtype of MDD or hypersensitivity to psychotropics may be useful for diagnosing prodromal DLB.
Keywords: 3-Iodobenzylguanidine; Aged; Aged, 80 and over; Depressive Disorder, Major; Follow-Up Studies; Heart Rate; Humans; Hypercapnia; Hypotension, Orthostatic; Kaplan-Meier Estimate; Lewy Body Disease; Middle Aged; Partial Pressure; Psychiatric Status Rating Scales; Retrospective Studies; Ventilators, Mechanical

White Matter and Hippocampal Volume Predict the Risk of Dementia in Patients with Cerebral Small Vessel Disease: The RUN DMC Study. - van Uden, Ingeborg W M; van der Holst, Helena M; Tuladhar, Anil M; van Norden, Anouk G W; de Laat, Karlijn F; Rutten-Jacobs, Loes C A; Norris, David G; Claassen, Jurgen A H R; van Dijk, Ewoud J; Kessels, Roy P C; de Leeuw, Frank-Erik (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between cerebral small vessel disease (SVD) and dementia has been studied without considering white matter (WM) volume, the microstructural integrity of the WM surrounding the SVD, and grey matter (GM). OBJECTIVE: We prospectively investigated the relationship between these structures and the risk of dementia, and formed a prediction model to investigate which characteristics (macro- or microstructural) explained most of the variance. METHODS: The RUN DMC study is a prospective cohort study among 503 non-demented participants with an age between 50 and 85 years at baseline, with baseline assessment in 2006 and follow-up assessment in 2012. Two were lost to follow-up (yielding a 99.6% response-rate). Cox regression analysis was used, to calculate hazard ratios for dementia, of baseline MRI characteristics. Tract-Based Spatial Statistics (TBSS) analysis was used to assess the added value of microstructural integrity of the WM. RESULTS: Mean age at baseline was 65.6 years (SD 8.8) and 56.8% was male. 43 participants developed dementia (8.6%), resulting in a 5.5-year cumulative risk of 11.1% (95% CI 7.7-14.6). Low WM and hippocampal volume are significant predictors for dementia. WM, WM hyperintensities, and hippocampal volume explained most of the variance. TBSS analyses showed no additional value of diffusion parameters. CONCLUSIONS: WM and hippocampal volume were the main predictors for the development of incident dementia at 5-year follow-up in elderly with SVD. There was no additional diagnostic value of the diffusion tensor imaging parameters on top of the macrostructural characteristics.
Keywords: Aged; Cerebral Small Vessel Diseases; Cohort Studies; Dementia; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Statistics, Nonparametric; White Matter

δ Scores are Exportable Across Cultural and Linguistic Boundaries. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
The latent variable "δ", can accurately diagnose dementia. Its generalizability across populations is unknown. We constructed a δ homolog ("dT2J") in data collected by the Texas Alzheimer's Research and Care Consortium (TARCC). From this, we calculated a composite d-score "d". We then tested d's generalizability across random subsets of TARCC participants and to a convenience sample of elderly Japanese persons with normal cognition (NC), mild cognitive impairment (MCI), and dementia (AD) (n = 176). dT2J was indicated by Instrumental Activities of Daily Living and psychometric measures. Embedded in this battery were the Mini-Mental Status Examination (MMSE) and an executive clock-drawing task (CLOX). Only MMSE and CLOX were available in both TARCC and the Japanese cohort. Therefore, a second composite variable, "T2J", was constructed solely from the factor loadings of CLOX and MMSE on d. The diagnostic accuracy of T2J was estimated in the validation sample, the remainder of the TARCC cohort, and in the Japanese sample. The areas under the receiver operating curve (AUC; ROC) for T2J were compared in each sample, and against d in TARCC. The AUCs for T2J were statistically indiscriminable within TARCC, and in Japanese persons. In Japanese persons, AUCs for T2J were 0.97 for the discrimination between AD versus NC, 0.86 for AD versus MCI, and 0.79 for NC versus MCI. The AUCs for T2J in Japanese persons were higher than any individual psychometric measure in that sample. Valid d-score composites can be abstracted from a subset of δ's indicators. Moreover, those composites are exportable across cultural and linguistic boundaries.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Cognitive Dysfunction; Cohort Studies; Culture; Executive Function; Female; Humans; Linguistics; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reproducibility of Results; ROC Curve; Texas

Alzheimer's Disease Normative Cerebrospinal Fluid Biomarkers Validated in PET Amyloid-β Characterized Subjects from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study. - Li, Qiao-Xin; Villemagne, Victor L; Doecke, James D; Rembach, Alan; Sarros, Shannon; Varghese, Shiji; McGlade, Amelia; Laughton, Katrina M; Pertile, Kelly K; Fowler, Christopher J; Rumble, Rebecca L; Trounson, Brett O; et al. (J Alzheimers Dis, 2015)
BACKGROUND: The cerebrospinal fluid (CSF) amyloid-β (Aβ)1-42, total-tau (T-tau), and phosphorylated-tau (P-tau181P) profile has been established as a valuable biomarker for Alzheimer's disease (AD). OBJECTIVE: The current study aimed to determine CSF biomarker cut-points using positron emission tomography (PET) Aβ imaging screened subjects from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging, as well as correlate CSF analyte cut-points across a range of PET Aβ amyloid ligands. METHODS: Aβ pathology was determined by PET imaging, utilizing 11C-Pittsburgh Compound B, 18F-flutemetamol, or 18F-florbetapir, in 157 AIBL participants who also underwent CSF collection. Using an INNOTEST assay, cut-points were established (Aβ1-42 >544 ng/L, T-tau <407 ng/L, and P-tau181P <78 ng/L) employing a rank based method to define a "positive" CSF in the sub-cohort of amyloid-PET negative healthy participants (n = 97), and compared with the presence of PET demonstrated AD pathology. RESULTS: CSF Aβ1-42 was the strongest individual biomarker, detecting cognitively impaired PET positive mild cognitive impairment (MCI)/AD with 85% sensitivity and 91% specificity. The ratio of P-tau181P or T-tau to Aβ1-42 provided greater accuracy, predicting MCI/AD with Aβ pathology with ≥92% sensitivity and specificity. Cross-validated accuracy, using all three biomarkers or the ratio of P-tau or T-tau to Aβ1-42 to predict MCI/AD, reached ≥92% sensitivity and specificity. CONCLUSIONS: CSF Aβ1-42 levels and analyte combination ratios demonstrated very high correlation with PET Aβ imaging. Our study offers additional support for CSF biomarkers in the early and accurate detection of AD pathology, including enrichment of patient cohorts for treatment trials even at the pre-symptomatic stage.

Amyloid-β and Tau Dynamics in Human Brain Interstitial Fluid in Patients with Suspected Normal Pressure Hydrocephalus. - Herukka, Sanna-Kaisa; Rummukainen, Jaana; Ihalainen, Jouni; von Und Zu Fraunberg, Mikael; Koivisto, Anne M; Nerg, Ossi; Puli, Lakshman K; Seppälä, Toni T; Zetterberg, Henrik; Pyykkö, Okko T; Helisalmi, Seppo; Tanila, Heikki; et al. (J Alzheimers Dis, 2015)
Background: Amyloid-β (Aβ1-42), total tau (T-tau), and phosphorylated tau (P-tau181) in the cerebrospinal fluid (CSF) are the most promising biomarkers of Alzheimer's disease (AD). Still, little is known about the dynamics of these molecules in the living brain. In a transgenic mouse brain, soluble Aβ decreases with increasing age and advanced Aβ pathology as seen similarly in CSF. Objective: To assess the relationship between AD-related pathological changes in human brain tissue, ventricular and lumbar CSF, and brain interstitial fluid (ISF). Methods: Altogether 11 patients with suspected idiopathic normal pressure hydrocephalus underwent frontal cortical brain biopsy, 24-h intraventricular pressure monitoring, and a microdialysis procedure. AD-related biomarkers were analyzed from brain tissue, CSF, and ISF. Results: ISF T-tau levels decreased strongly within the first 12 h, then plateauing until the end of the experiment. Aβ1-42 and P-tau181 remained stable during the experiment (n = 3). T-tau and P-tau were higher in the ISF than in ventricular or lumbar CSF, while Aβ1-42 levels were within similar range in both CSF and ISF samples. ISF P-tau correlated with the ventricular CSF T-tau (r = 0.70, p = 0.017) and P-tau181 (r = 0.64, p = 0.034). Five patients with amyloid pathology in the brain biopsy tended to reveal lower ISF Aβ1-42 levels than those six without amyloid pathology. Conclusions: This is the first study to report ISF Aβ and tau levels in the human brain without significant brain injury. The set-up used enables sampling from the brain ISF for at least 24 h without causing adverse effects due to the microdialysis procedure to follow the dynamics of the key molecules in AD pathogenesis in the living brain at various stages of the disease.

APOE Affects the Volume and Shape of the Amygdala and the Hippocampus in Mild Cognitive Impairment and Alzheimer's Disease: Age Matters. - Tang, Xiaoying; Holland, Dominic; Dale, Anders M; Miller, Michael I (J Alzheimers Dis, 2015)
This paper examines how age intervenes in the effects of APOE ɛ4 allele on the volume and shape morphometrics of the hippocampus and the amygdala in mild cognitive impairment (MCI) and Alzheimer's disease. We evaluate the structural morphological differences between ɛ4 carriers and non-carriers in two age-dependent subgroups; younger than 75 years (Young-Old) and older than 80 years (Very-Old). While we show that the four structures of interest atrophy significantly in the ɛ4 carriers, relative to the non-carriers, of the Young-Old group, this effect is not observed in their Very-Old counterparts. The structures in the right hemisphere are found to be more affected by the APOE genotype than those in the left hemisphere and we identify the relevant regions in which significant atrophy occurs to be parts of the basolateral, centromedial, and lateral nucleus subregions of the amygdala and the CA1 and subiculum subregions of the hippocampus. We also observe that the APOE genotype only affects MCI patients that deteriorated to dementia within 3 years while leaving their "non-converting" counterparts unaffected.

The APOE Gene is Differentially Methylated in Alzheimer's Disease. - Foraker, Jessica; Millard, Steven P; Leong, Lesley; Thomson, Zachary; Chen, Sunny; Keene, C Dirk; Bekris, Lynn M; Yu, Chang-En (J Alzheimers Dis, 2015)
The ɛ4 allele of the human apolipoprotein E gene (APOE) is a well-proven genetic risk factor for the late onset form of Alzheimer's disease (AD). However, the biological mechanisms through which the ɛ4 allele contributes to disease pathophysiology are incompletely understood. The three common alleles of APOE, ɛ2, ɛ3 and ɛ4, are defined by two single nucleotide polymorphisms (SNPs) that reside in the coding region of exon 4, which overlaps with a well-defined CpG island (CGI). Both SNPs change not only the protein codon but also the quantity of CpG dinucleotides, primary sites for DNA methylation. Thus, we hypothesize that the presence of an ɛ4 allele changes the DNA methylation landscape of the APOE CGI and that such epigenetic alteration contributes to AD susceptibility. To explore the relationship between APOE genotype, AD risk, and DNA methylation of the APOE CGI, we applied bisulfite pyrosequencing and evaluated methylation profiles of postmortem brain from 15 AD and 10 control subjects. We observed a tissue-specific decrease in DNA methylation with AD and identified two AD-specific differentially methylated regions (DMRs), which were also associated with APOE genotype. We further demonstrated that one DMR was completely un-methylated in a sub-population of genomes, possibly due to a subset of brain cells carrying deviated APOE methylation profiles. These data suggest that the APOE CGI is differentially methylated in AD brain in a tissue- and APOE-genotype-specific manner. Such epigenetic alteration might contribute to neural cell dysfunction in AD brain.

A Blood-Based, 7-Metabolite Signature for the Early Diagnosis of Alzheimer's Disease. - Olazarán, Javier; Gil-de-Gómez, Luis; Rodríguez-Martín, Andrés; Valentí-Soler, Meritxell; Frades-Payo, Belén; Marín-Muñoz, Juan; Antúnez, Carmen; Frank-García, Ana; Jiménez, Carmen Acedo; Gracia, Lorenzo Morlén; Torregrossa, Roberto Petidier; Guisasola, María Concepción; et al. (J Alzheimers Dis, 2015)
Accurate blood-based biomarkers of Alzheimer's disease (AD) could constitute simple, inexpensive, and non-invasive tools for the early diagnosis and treatment of this devastating neurodegenerative disease. We sought to develop a robust AD biomarker panel by identifying alterations in plasma metabolites that persist throughout the continuum of AD pathophysiology. Using a multicenter, cross-sectional study design, we based our analysis on metabolites whose levels were altered both in AD patients and in patients with amnestic mild cognitive impairment (aMCI), the earliest identifiable stage of AD. UPLC coupled to mass spectrometry was used to independently compare the levels of 495 plasma metabolites in aMCI (n = 58) and AD (n = 100) patients with those of normal cognition controls (NC, n = 93). Metabolite alterations common to both aMCI and AD patients were used to generate a logistic regression model that accurately distinguished AD from NC patients. The final panel consisted of seven metabolites: three amino acids (glutamic acid, alanine, and aspartic acid), one non-esterified fatty acid (22:6n-3, DHA), one bile acid (deoxycholic acid), one phosphatidylethanolamine [PE(36:4)], and one sphingomyelin [SM(39:1)]. Detailed analysis ruled out the influence of potential confounding variables, including comorbidities and treatments, on each of the seven biomarkers. The final model accurately distinguished AD from NC patients (AUC, 0.918). Importantly, the model also distinguished aMCI from NC patients (AUC, 0.826), indicating its potential diagnostic utility in early disease stages. These findings describe a sensitive biomarker panel that may facilitate the specific detection of early-stage AD through the analysis of plasma samples.

Comorbid Depression and Diabetes as a Risk for Mild Cognitive Impairment and Alzheimer's Disease in Elderly Mexican Americans. - Johnson, Leigh A; Gamboa, Adriana; Vintimilla, Raul; Cheatwood, Austin J; Grant, Alyann; Trivedi, Ashesh; Edwards, Melissa; Hall, James R; O'Bryant, Sid E (J Alzheimers Dis, 2015)
BACKGROUND: The links between diabetes, depression, and Alzheimer's disease (AD) has been established, but they are still poorly understood. However, little research has examined the effect that comorbidity of depression and diabetes has on cognitive impairment in an ethnically diverse sample. OBJECTIVE: The purpose of this study was to investigate the relationship between comorbid diabetes and depression on cognitive dysfunction; and examine the relationship in an ethnically diverse population. METHODS AND RESULTS: Analyses of data from 2,436 participants (914 men and 1,522 women) of three separate cohorts: HABLE, FRONTIER, and TARCC. In the HABLE cohort, comorbidity (odds ratio [OR] = 3.008; 95% CI = 1.358-6.667), age (OR = 1.138; 95% CI = 1.093-1.185), and education (OR = 0.915; 95% CI = 0.852-0.982) increased the risk of mild cognitive impairment (MCI) diagnosis among elderly Mexican American. In the TARCC cohort, results showed an increase risk of MCI in both non-Hispanic whites (OR = 18.795; 95% CI = 2.229-158.485) and Mexican Americans (OR = 8.417; 95% CI = 2.967-23.878). Finally, results in the FRONTIER cohort showed that in elderly Mexican Americans, comorbidity (OR = 2.754; 95% CI = 1.084-6.995) and age (OR = 1.069; 95% CI = 1.023-1.118) significantly increased risk of MCI. In non-Hispanic whites, comorbidity did not significantly increase risk of MCI. CONCLUSIONS: Among elderly Mexican Americans, comorbid depression and diabetes significantly increased risk for MCI and AD across cohorts. Effects of comorbid diabetes and depression on MCI were inconclusive. Our results support the link between comorbid diabetes and depression and risk for cognitive decline among Mexican Americans. This finding is of critical importance as the Hispanic population is at higher risk of developing AD.

The Continuing Failure of Bexarotene in Alzheimer's Disease Mice. - Balducci, Claudia; Paladini, Alessandra; Micotti, Edoardo; Tolomeo, Daniele; La Vitola, Pietro; Grigoli, Emanuele; Richardson, Jill C; Forloni, Gianluigi (J Alzheimers Dis, 2015)
Alzheimer's disease (AD) is the most common form of dementia characterized by synaptic dysfunction, memory loss, neuroinflammation, and neuronal cell death. Amyloid-β (Aβ), recognized as the main culprit of AD, aggregates and accumulates in the extracellular compartment as neuritic plaques, after deregulation of its production or clearance. Apolipoprotein E (ApoE) plays a major role in Aβ clearance and its expression is transcriptionally regulated by the liver X receptor and retinoid X receptors (RXRs) system. Bexarotene (BEXA), an RXR agonist, that increases ApoE expression and microglia phagocytosis and has been proposed as a promising therapy for AD, resolving both the amyloid pathology and memory loss. Despite the first compelling report, however, multiple failures have been documented, raising concern about whether BEXA could in fact become a novel disease-modifying strategy for AD. To help clarify this, we investigated the effect of BEXA in vivo at multiple levels in TASTPM transgenic mice. Seven-day oral administration of BEXA to these mice did not achieve any significant memory improvement, plaque reduction, or enhancement of microglial cell activation. No differences were found when specifically investigating the microglial phagocytic state in vivo. In addition, a brain structural analysis with magnetic resonance did not detect any BEXA-mediated change in the volume reduction of the main affected brain areas in our mice. These results suggest that BEXA has no beneficial effect on the multi-factorial pathologic phenotype of AD mice.

Correcting for the Absence of a Gold Standard Improves Diagnostic Accuracy of Biomarkers in Alzheimer's Disease. - Coart, Els; Barrado, Leandro García; Duits, Flora H; Scheltens, Philip; van der Flier, Wiesje M; Teunissen, Charlotte E; van der Vies, Saskia M; Burzykowski, Tomasz (J Alzheimers Dis, 2015)
BACKGROUND: Studies investigating the diagnostic accuracy of biomarkers for Alzheimer's disease (AD) are typically performed using the clinical diagnosis or amyloid-β positron emission tomography as the reference test. However, neither can be considered a gold standard or a perfect reference test for AD. Not accounting for errors in the reference test is known to cause bias in the diagnostic accuracy of biomarkers. OBJECTIVE: To determine the diagnostic accuracy of AD biomarkers while taking the imperfectness of the reference test into account. METHODS: To determine the diagnostic accuracy of AD biomarkers and taking the imperfectness of the reference test into account, we have developed a Bayesian method. This method establishes the biomarkers' true value in predicting the AD-pathology status by combining the reference test and the biomarker data with available information on the reliability of the reference test. The new methodology was applied to two clinical datasets to establish the joint accuracy of three cerebrospinal fluid biomarkers (amyloid-β1-42, Total tau, and P-tau181) by including the clinical diagnosis as imperfect reference test into the analysis. RESULTS: The area under the receiver-operating-characteristics curve to discriminate between AD and controls, increases from 0.949 (with 95% credible interval [0.935,0.960]) to 0.990 ([0.985,0.995]) and from 0.870 ([0.817,0.912]) to 0.975 ([0.943,0.990]) for the cohorts, respectively. CONCLUSIONS: Use of the Bayesian methodology enables an improved estimate of the exact diagnostic value of AD biomarkers and overcomes the lack of a gold standard for AD. Using the new method will increase the diagnostic confidence for early stages of AD.

A Critical Proton MR Spectroscopy Marker of Alzheimer's Disease Early Neurodegenerative Change: Low Hippocampal NAA/Cr Ratio Impacts APOE ɛ4 Mexico City Children and Their Parents. - Calderón-Garcidueñas, Lilian; Mora-Tiscareño, Antonieta; Sánchez, Gastón Melo; Rodríguez-Díaz, Joel; Torres-Jardón, Ricardo; Styner, Martin; Mukherjee, Partha S; Lin, Weili; Jewells, Valerie (J Alzheimers Dis, 2015)
Severe air pollution exposures produce systemic, respiratory, myocardial, and brain inflammation and Alzheimer's disease (AD) hallmarks in clinically healthy children. We tested whether hippocampal metabolite ratios are associated with contrasting levels of air pollution, APOE, and body mass index (BMI) in paired healthy children and one parent sharing the same APOE alleles. We used 1H-MRS to interrogate bilateral hippocampal single-voxel in 57 children (12.45 ± 3.4 years) and their 48 parents (37.5 ± 6.78 years) from a low pollution city versus Mexico City (MC). NAA/Cr, Cho/Cr, and mI/Cr metabolite ratios were analyzed. The right hippocampus NAA/Cr ratio was significantly different between cohorts (p = 0.007). The NAA/Cr ratio in right hippocampus in controls versus APOE ɛ4 MC children and in left hippocampus in MC APOE ɛ4 parents versus their children was significantly different after adjusting for age, gender, and BMI (p = 0.027 and 0.01, respectively). The NAA/Cr ratio is considered reflective of neuronal density/functional integrity/loss of synapses/higher pTau burden, thus a significant decrease in hippocampal NAA/Cr ratios may constitute a spectral marker of early neurodegeneration in young urbanites. Decreases in NAA/Cr correlate well with cognitive function, behavioral symptoms, and dementia severity; thus, since the progression of AD starts decades before clinical diagnosis, our findings support the hypothesis that under chronic exposures to fine particulate matter and ozone above the standards, neurodegenerative processes start in childhood and APOE ɛ4 carriers are at higher risk. Gene and environmental factors are critical in the development of AD and the identification and neuroprotection of young urbanites at high risk must become a public health priority.

Differential Effects of Meal Challenges on Cognition, Metabolism, and Biomarkers for Apolipoprotein E ɛ4 Carriers and Adults with Mild Cognitive Impairment. - Hanson, Angela J; Bayer, Jennifer L; Baker, Laura D; Cholerton, Brenna; VanFossen, Brian; Trittschuh, Emily; Rissman, Robert A; Donohue, Michael C; Moghadam, Setareh H; Plymate, Stephen R; Craft, Suzanne (J Alzheimers Dis, 2015)
BACKGROUND: High intake of saturated fat (SF) and glycemic index (GI) foods is a risk factor for sporadic Alzheimer's disease. Meal challenges may elucidate mechanisms that contribute to this risk, enabling development of targeted interventions. OBJECTIVE: To assess cognitive and metabolic changes after a meal high in SF and GI calories (HIGH) versus a meal low in these macronutrients (LOW) in older adults with and without cognitive impairment, and with and without the apolipoprotein E4 risk factor. METHODS: 46 adults with either cognitive impairment (CI) or normal cognition (NC) ingested a LOW (25% total fat, 7% SF, GI <55) and a HIGH meal (50% total fat, 25% SF, GI >70) in a blinded random fashion. Participants then underwent cognitive testing and blood sampling for metabolic and Alzheimer's disease biomarkers. Data were analyzed using repeated measures ANOVA and Spearman correlations. RESULTS: E4-adults with NC demonstrated lower delayed memory scores after the HIGH compared to the LOW meal, whereas normal E4+ and CI E4- groups had higher scores after the HIGH meal (ANOVA p = 0.03). These findings were associated with meal-induced changes in glucose (p = 0.05), insulin (p = 0.004), triglycerides (p <  0.01), and plasma Aβ42 (p = 0.05). CONCLUSIONS: These preliminary data suggest that cognitive performance of adults without CI may worsen following high SF and sugar meals, whereas adults with CI or those at risk for CI due to E4 status may benefit acutely from such meals. Furthermore, plasma Aβ was affected by meal type, suggesting a relationship between metabolic response and amyloid regulation.

C9orf72 nucleotide repeat structures initiate molecular cascades of disease. - Haeusler, Aaron R; Donnelly, Christopher J; Periz, Goran; Simko, Eric A J; Shaw, Patrick G; Kim, Min-Sik; Maragakis, Nicholas J; Troncoso, Juan C; Pandey, Akhilesh; Sattler, Rita; Rothstein, Jeffrey D; Wang, Jiou (Nature, 2014)
A hexanucleotide repeat expansion (HRE), (GGGGCC)n, in C9orf72 is the most common genetic cause of the neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Here we identify a molecular mechanism by which structural polymorphism of the HRE leads to ALS/FTD pathology and defects. The HRE forms DNA and RNA G-quadruplexes with distinct structures and promotes RNA•DNA hybrids (R-loops). The structural polymorphism causes a repeat-length-dependent accumulation of transcripts aborted in the HRE region. These transcribed repeats bind to ribonucleoproteins in a conformation-dependent manner. Specifically, nucleolin, an essential nucleolar protein, preferentially binds the HRE G-quadruplex, and patient cells show evidence of nucleolar stress. Our results demonstrate that distinct C9orf72 HRE structural polymorphism at both DNA and RNA levels initiates molecular cascades leading to ALS/FTD pathologies, and provide the basis for a mechanistic model for repeat-associated neurodegenerative diseases.
Keywords: Amyotrophic Lateral Sclerosis; B-Lymphocytes; Base Sequence; Cell Nucleolus; DNA; DNA Repeat Expansion; Frontotemporal Dementia; G-Quadruplexes; HEK293 Cells; Humans; Models, Molecular; Neurons; Open Reading Frames; Phosphoproteins; Ribonucleoproteins; RNA; RNA-Binding Proteins; Stress, Physiological; Transcription, Genetic

Phase 3 trials of solanezumab for mild-to-moderate Alzheimer's disease. - Doody, Rachelle S; Thomas, Ronald G; Farlow, Martin; Iwatsubo, Takeshi; Vellas, Bruno; Joffe, Steven; Kieburtz, Karl; Raman, Rema; Sun, Xiaoying; Aisen, Paul S; Siemers, Eric; Liu-Seifert, Hong; et al. (N Engl J Med, 2014)
BACKGROUND: Alzheimer's disease is characterized by amyloid-beta plaques, neurofibrillary tangles, gliosis, and neuronal loss. Solanezumab, a humanized monoclonal antibody, preferentially binds soluble forms of amyloid and in preclinical studies promoted its clearance from the brain. METHODS: In two phase 3, double-blind trials (EXPEDITION 1 and EXPEDITION 2), we randomly assigned 1012 and 1040 patients, respectively, with mild-to-moderate Alzheimer's disease to receive placebo or solanezumab (administered intravenously at a dose of 400 mg) every 4 weeks for 18 months. The primary outcomes were the changes from baseline to week 80 in scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11; range, 0 to 70, with higher scores indicating greater cognitive impairment) and the Alzheimer's Disease Cooperative Study-Activities of Daily Living scale (ADCS-ADL; range, 0 to 78, with lower scores indicating worse functioning). After analysis of data from EXPEDITION 1, the primary outcome for EXPEDITION 2 was revised to the change in scores on the 14-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog14; range, 0 to 90, with higher scores indicating greater impairment), in patients with mild Alzheimer's disease. RESULTS: Neither study showed significant improvement in the primary outcomes. The modeled difference between groups (solanezumab group minus placebo group) in the change from baseline was -0.8 points for the ADAS-cog11 score (95% confidence interval [CI], -2.1 to 0.5; P=0.24) and -0.4 points for the ADCS-ADL score (95% CI, -2.3 to 1.4; P=0.64) in EXPEDITION 1 and -1.3 points (95% CI, -2.5 to 0.3; P=0.06) and 1.6 points (95% CI, -0.2 to 3.3; P=0.08), respectively, in EXPEDITION 2. Between-group differences in the changes in the ADAS-cog14 score were -1.7 points in patients with mild Alzheimer's disease (95% CI, -3.5 to 0.1; P=0.06) and -1.5 in patients with moderate Alzheimer's disease (95% CI, -4.1 to 1.1; P=0.26). In the combined safety data set, the incidence of amyloid-related imaging abnormalities with edema or hemorrhage was 0.9% with solanezumab and 0.4% with placebo for edema (P=0.27) and 4.9% and 5.6%, respectively, for hemorrhage (P=0.49). CONCLUSIONS: Solanezumab, a humanized monoclonal antibody that binds amyloid, failed to improve cognition or functional ability. (Funded by Eli Lilly; EXPEDITION 1 and 2 ClinicalTrials.gov numbers, NCT00905372 and NCT00904683.).
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Cognition; Double-Blind Method; Female; Humans; Intention to Treat Analysis; Male; Neuropsychological Tests; Severity of Illness Index; tau Proteins; Treatment Failure

Plasma phospholipids identify antecedent memory impairment in older adults. - Mapstone, Mark; Cheema, Amrita K; Fiandaca, Massimo S; Zhong, Xiaogang; Mhyre, Timothy R; MacArthur, Linda H; Hall, William J; Fisher, Susan G; Peterson, Derick R; Haley, James M; Nazar, Michael D; Rich, Steven A; et al. (Nat Med, 2014)
Alzheimer's disease causes a progressive dementia that currently affects over 35 million individuals worldwide and is expected to affect 115 million by 2050 (ref. 1). There are no cures or disease-modifying therapies, and this may be due to our inability to detect the disease before it has progressed to produce evident memory loss and functional decline. Biomarkers of preclinical disease will be critical to the development of disease-modifying or even preventative therapies. Unfortunately, current biomarkers for early disease, including cerebrospinal fluid tau and amyloid-β levels, structural and functional magnetic resonance imaging and the recent use of brain amyloid imaging or inflammaging, are limited because they are either invasive, time-consuming or expensive. Blood-based biomarkers may be a more attractive option, but none can currently detect preclinical Alzheimer's disease with the required sensitivity and specificity. Herein, we describe our lipidomic approach to detecting preclinical Alzheimer's disease in a group of cognitively normal older adults. We discovered and validated a set of ten lipids from peripheral blood that predicted phenoconversion to either amnestic mild cognitive impairment or Alzheimer's disease within a 2-3 year timeframe with over 90% accuracy. This biomarker panel, reflecting cell membrane integrity, may be sensitive to early neurodegeneration of preclinical Alzheimer's disease.
Keywords: Aged; Alzheimer Disease; Asparagine; Biomarkers; Carnitine; Cohort Studies; Dipeptides; Female; Humans; Longitudinal Studies; Lysophosphatidylcholines; Malates; Male; Memory Disorders; Metabolome; Mild Cognitive Impairment; Neuropsychological Tests; Phosphatidylcholines; Phosphatidylinositols; Phospholipids; Proline; Prospective Studies; Sensitivity and Specificity; Sphingomyelins; Ursodeoxycholic Acid

Ten-year effects of the advanced cognitive training for independent and vital elderly cognitive training trial on cognition and everyday functioning in older adults. - Rebok, George W; Ball, Karlene; Guey, Lin T; Jones, Richard N; Kim, Hae-Young; King, Jonathan W; Marsiske, Michael; Morris, John N; Tennstedt, Sharon L; Unverzagt, Frederick W; Willis, Sherry L (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine the effects of cognitive training on cognitive abilities and everyday function over 10 years. DESIGN: Ten-year follow-up of a randomized, controlled single-blind trial (Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE)) with three intervention groups and a no-contact control group. SETTING: Six U.S. cities. PARTICIPANTS: A volunteer sample of 2,832 persons (mean baseline age 73.6; 26% African American) living independently. INTERVENTION: Ten training sessions for memory, reasoning, or speed of processing; four sessions of booster training 11 and 35 months after initial training. MEASUREMENTS: Objectively measured cognitive abilities and self-reported and performance-based measures of everyday function. RESULTS: Participants in each intervention group reported less difficulty with instrumental activities of daily living (IADLs) (memory: effect size = 0.48, 99% confidence interval (CI) = 0.12-0.84; reasoning: effect size = 0.38, 99% CI = 0.02-0.74; speed of processing: effect size = 0.36, 99% CI = 0.01-0.72). At a mean age of 82, approximately 60% of trained participants, versus 50% of controls (P < .05), were at or above their baseline level of self-reported IADL function at 10 years. The reasoning and speed-of-processing interventions maintained their effects on their targeted cognitive abilities at 10 years (reasoning: effect size = 0.23, 99% CI = 0.09-0.38; speed of processing: effect size = 0.66, 99% CI = 0.43-0.88). Memory training effects were no longer maintained for memory performance. Booster training produced additional and durable improvement for the reasoning intervention for reasoning performance (effect size = 0.21, 99% CI = 0.01-0.41) and the speed-of-processing intervention for speed-of-processing performance (effect size = 0.62, 99% CI = 0.31-0.93). CONCLUSION: Each Advanced Cognitive Training for Independent and Vital Elderly cognitive intervention resulted in less decline in self-reported IADL compared with the control group. Reasoning and speed, but not memory, training resulted in improved targeted cognitive abilities for 10 years.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cognition Disorders; Cognitive Therapy; Female; Follow-Up Studies; Humans; Independent Living; Male; Memory Disorders; Mental Processes; Single-Blind Method; United States

A three-dimensional human neural cell culture model of Alzheimer's disease. - Choi, Se Hoon; Kim, Young Hye; Hebisch, Matthias; Sliwinski, Christopher; Lee, Seungkyu; D'Avanzo, Carla; Chen, Hechao; Hooli, Basavaraj; Asselin, Caroline; Muffat, Julien; Klee, Justin B; Zhang, Can; et al. (Nature, 2014)
Alzheimer's disease is the most common form of dementia, characterized by two pathological hallmarks: amyloid-β plaques and neurofibrillary tangles. The amyloid hypothesis of Alzheimer's disease posits that the excessive accumulation of amyloid-β peptide leads to neurofibrillary tangles composed of aggregated hyperphosphorylated tau. However, to date, no single disease model has serially linked these two pathological events using human neuronal cells. Mouse models with familial Alzheimer's disease (FAD) mutations exhibit amyloid-β-induced synaptic and memory deficits but they do not fully recapitulate other key pathological events of Alzheimer's disease, including distinct neurofibrillary tangle pathology. Human neurons derived from Alzheimer's disease patients have shown elevated levels of toxic amyloid-β species and phosphorylated tau but did not demonstrate amyloid-β plaques or neurofibrillary tangles. Here we report that FAD mutations in β-amyloid precursor protein and presenilin 1 are able to induce robust extracellular deposition of amyloid-β, including amyloid-β plaques, in a human neural stem-cell-derived three-dimensional (3D) culture system. More importantly, the 3D-differentiated neuronal cells expressing FAD mutations exhibited high levels of detergent-resistant, silver-positive aggregates of phosphorylated tau in the soma and neurites, as well as filamentous tau, as detected by immunoelectron microscopy. Inhibition of amyloid-β generation with β- or γ-secretase inhibitors not only decreased amyloid-β pathology, but also attenuated tauopathy. We also found that glycogen synthase kinase 3 (GSK3) regulated amyloid-β-mediated tau phosphorylation. We have successfully recapitulated amyloid-β and tau pathology in a single 3D human neural cell culture system. Our unique strategy for recapitulating Alzheimer's disease pathology in a 3D neural cell culture model should also serve to facilitate the development of more precise human neural cell models of other neurodegenerative disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Culture Techniques; Cell Differentiation; Drug Evaluation, Preclinical; Extracellular Space; Glycogen Synthase Kinase 3; Humans; Microtubule-Associated Proteins; Models, Biological; Neural Stem Cells; Neurites; Phosphorylation; Presenilin-1; Protein Aggregation, Pathological; Reproducibility of Results; tau Proteins

Two phase 3 trials of bapineuzumab in mild-to-moderate Alzheimer's disease. - Salloway, Stephen; Sperling, Reisa; Fox, Nick C; Blennow, Kaj; Klunk, William; Raskind, Murray; Sabbagh, Marwan; Honig, Lawrence S; Porsteinsson, Anton P; Ferris, Steven; Reichert, Marcel; Ketter, Nzeera; et al. (N Engl J Med, 2014)
BACKGROUND: Bapineuzumab, a humanized anti-amyloid-beta monoclonal antibody, is in clinical development for the treatment of Alzheimer's disease. METHODS: We conducted two double-blind, randomized, placebo-controlled, phase 3 trials involving patients with mild-to-moderate Alzheimer's disease--one involving 1121 carriers of the apolipoprotein E (APOE) ε4 allele and the other involving 1331 noncarriers. Bapineuzumab or placebo, with doses varying by study, was administered by intravenous infusion every 13 weeks for 78 weeks. The primary outcome measures were scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11, with scores ranging from 0 to 70 and higher scores indicating greater impairment) and the Disability Assessment for Dementia (DAD, with scores ranging from 0 to 100 and higher scores indicating less impairment). A total of 1090 carriers and 1114 noncarriers were included in the efficacy analysis. Secondary outcome measures included findings on positron-emission tomographic amyloid imaging with the use of Pittsburgh compound B (PIB-PET) and cerebrospinal fluid phosphorylated tau (phospho-tau) concentrations. RESULTS: There were no significant between-group differences in the primary outcomes. At week 78, the between-group differences in the change from baseline in the ADAS-cog11 and DAD scores (bapineuzumab group minus placebo group) were -0.2 (P=0.80) and -1.2 (P=0.34), respectively, in the carrier study; the corresponding differences in the noncarrier study were -0.3 (P=0.64) and 2.8 (P=0.07) with the 0.5-mg-per-kilogram dose of bapineuzumab and 0.4 (P=0.62) and 0.9 (P=0.55) with the 1.0-mg-per-kilogram dose. The major safety finding was amyloid-related imaging abnormalities with edema among patients receiving bapineuzumab, which increased with bapineuzumab dose and APOE ε4 allele number and which led to discontinuation of the 2.0-mg-per-kilogram dose. Between-group differences were observed with respect to PIB-PET and cerebrospinal fluid phospho-tau concentrations in APOE ε4 allele carriers but not in noncarriers. CONCLUSIONS: Bapineuzumab did not improve clinical outcomes in patients with Alzheimer's disease, despite treatment differences in biomarkers observed in APOE ε4 carriers. (Funded by Janssen Alzheimer Immunotherapy and Pfizer; Bapineuzumab 301 and 302 ClinicalTrials.gov numbers, NCT00575055 and NCT00574132, and EudraCT number, 2009-012748-17.).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Brain; Cognition; Double-Blind Method; Edema; Female; Humans; Intention to Treat Analysis; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Failure

Alzheimer's disease risk gene CD33 inhibits microglial uptake of amyloid beta. - Griciuc, Ana; Serrano-Pozo, Alberto; Parrado, Antonio R; Lesinski, Andrea N; Asselin, Caroline N; Mullin, Kristina; Hooli, Basavaraj; Choi, Se Hoon; Hyman, Bradley T; Tanzi, Rudolph E (Neuron, 2013)
The transmembrane protein CD33 is a sialic acid-binding immunoglobulin-like lectin that regulates innate immunity but has no known functions in the brain. We have previously shown that the CD33 gene is a risk factor for Alzheimer's disease (AD). Here, we observed increased expression of CD33 in microglial cells in AD brain. The minor allele of the CD33 SNP rs3865444, which confers protection against AD, was associated with reductions in both CD33 expression and insoluble amyloid beta 42 (Aβ42) levels in AD brain. Furthermore, the numbers of CD33-immunoreactive microglia were positively correlated with insoluble Aβ42 levels and plaque burden in AD brain. CD33 inhibited uptake and clearance of Aβ42 in microglial cell cultures. Finally, brain levels of insoluble Aβ42 as well as amyloid plaque burden were markedly reduced in APP(Swe)/PS1(ΔE9)/CD33(-/-) mice. Therefore, CD33 inactivation mitigates Aβ pathology and CD33 inhibition could represent a novel therapy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Case-Control Studies; Disease Models, Animal; Genetic Predisposition to Disease; Humans; Matched-Pair Analysis; Mice; Mice, Inbred C57BL; Mice, Knockout; Mice, Transgenic; Microglia; Polymorphism, Single Nucleotide; Reference Values; RNA, Messenger; Sialic Acid Binding Ig-like Lectin 3

Anti-amyloid β autoantibodies in cerebral amyloid angiopathy-related inflammation: implications for amyloid-modifying therapies. - Piazza, Fabrizio; Greenberg, Steven M; Savoiardo, Mario; Gardinetti, Margherita; Chiapparini, Luisa; Raicher, Irina; Nitrini, Ricardo; Sakaguchi, Hideya; Brioschi, Monica; Billo, Giuseppe; Colombo, Antonio; Lanzani, Francesca; et al. (Ann Neurol, 2013)
OBJECTIVE: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is characterized by vasogenic edema and multiple cortical/subcortical microbleeds, sharing several aspects with the recently defined amyloid-related imaging abnormalities (ARIA) reported in Alzheimer's disease (AD) passive immunization therapies. Herein, we investigated the role of anti-amyloid β (Aβ) autoantibodies in the acute and remission phases of CAA-ri. METHODS: We used a novel ultrasensitive technique on patients from a retrospective multicenter case-control study, and evaluated the anti-Aβ autoantibody concentration in the cerebrospinal fluid (CSF) of 10 CAA-ri, 8 CAA, 14 multiple sclerosis, and 25 control subjects. Levels of soluble Aβ40, Aβ42, tau, P-181 tau, and APOE genotype were also investigated. RESULTS: During the acute phase of CAA-ri, anti-Aβ autoantibodies were specifically increased and directly correlated with Aβ mobilization, together with augmented tau and P-181 tau. Following clinical and radiological remission, autoantibodies progressively returned to control levels, and both soluble Aβ and axonal degeneration markers decreased in parallel. INTERPRETATION: Our data support the hypothesis that the pathogenesis of CAA-ri may be mediated by a selective autoimmune reaction against cerebrovascular Aβ, directly related to autoantibody concentration and soluble Aβ. The CSF dosage of anti-Aβ autoantibodies with the technique here described can thus be proposed as a valid alternative tool for the diagnosis of CAA-ri. Moreover, given the similarities between ARIA developing spontaneously and those observed during immunization trials, anti-Aβ autoantibodies can be considered as novel potential biomarkers in future amyloid-modifying therapies for the treatment of AD and CAA.
Keywords: Adult; Aged; Amyloid beta-Peptides; Apolipoproteins E; Autoantibodies; Brain; Case-Control Studies; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; Phosphorylation; Retrospective Studies; Steroids; tau Proteins

Integrated systems approach identifies genetic nodes and networks in late-onset Alzheimer's disease. - Zhang, Bin; Gaiteri, Chris; Bodea, Liviu-Gabriel; Wang, Zhi; McElwee, Joshua; Podtelezhnikov, Alexei A; Zhang, Chunsheng; Xie, Tao; Tran, Linh; Dobrin, Radu; Fluder, Eugene; Clurman, Bruce; et al. (Cell, 2013)
The genetics of complex disease produce alterations in the molecular interactions of cellular pathways whose collective effect may become clear through the organized structure of molecular networks. To characterize molecular systems associated with late-onset Alzheimer's disease (LOAD), we constructed gene-regulatory networks in 1,647 postmortem brain tissues from LOAD patients and nondemented subjects, and we demonstrate that LOAD reconfigures specific portions of the molecular interaction structure. Through an integrative network-based approach, we rank-ordered these network structures for relevance to LOAD pathology, highlighting an immune- and microglia-specific module that is dominated by genes involved in pathogen phagocytosis, contains TYROBP as a key regulator, and is upregulated in LOAD. Mouse microglia cells overexpressing intact or truncated TYROBP revealed expression changes that significantly overlapped the human brain TYROBP network. Thus the causal network structure is a useful predictor of response to gene perturbations and presents a framework to test models of disease mechanisms underlying LOAD.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Animals; Bayes Theorem; Brain; Gene Regulatory Networks; Humans; Membrane Proteins; Mice; Microglia

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Modeling Alzheimer's disease with iPSCs reveals stress phenotypes associated with intracellular Aβ and differential drug responsiveness. - Kondo, Takayuki; Asai, Masashi; Tsukita, Kayoko; Kutoku, Yumiko; Ohsawa, Yutaka; Sunada, Yoshihide; Imamura, Keiko; Egawa, Naohiro; Yahata, Naoki; Okita, Keisuke; Takahashi, Kazutoshi; Asaka, Isao; et al. (Cell Stem Cell, 2013)
Oligomeric forms of amyloid-β peptide (Aβ) are thought to play a pivotal role in the pathogenesis of Alzheimer's disease (AD), but the mechanism involved is still unclear. Here, we generated induced pluripotent stem cells (iPSCs) from familial and sporadic AD patients and differentiated them into neural cells. Aβ oligomers accumulated in iPSC-derived neurons and astrocytes in cells from patients with a familial amyloid precursor protein (APP)-E693Δ mutation and sporadic AD, leading to endoplasmic reticulum (ER) and oxidative stress. The accumulated Aβ oligomers were not proteolytically resistant, and docosahexaenoic acid (DHA) treatment alleviated the stress responses in the AD neural cells. Differential manifestation of ER stress and DHA responsiveness may help explain variable clinical results obtained with the use of DHA treatment and suggests that DHA may in fact be effective for a subset of patients. It also illustrates how patient-specific iPSCs can be useful for analyzing AD pathogenesis and evaluating drugs.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Differentiation; Cerebral Cortex; Docosahexaenoic Acids; Humans; Induced Pluripotent Stem Cells; Intracellular Space; Models, Biological; Mutant Proteins; Neurons; Oxidative Stress; Phenotype; Protein Structure, Quaternary

Tracking pathophysiological processes in Alzheimer's disease: an updated hypothetical model of dynamic biomarkers. - Jack, Clifford R; Knopman, David S; Jagust, William J; Petersen, Ronald C; Weiner, Michael W; Aisen, Paul S; Shaw, Leslie M; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Lesnick, Timothy G; Pankratz, Vernon S; et al. (Lancet Neurol, 2013)
In 2010, we put forward a hypothetical model of the major biomarkers of Alzheimer's disease (AD). The model was received with interest because we described the temporal evolution of AD biomarkers in relation to each other and to the onset and progression of clinical symptoms. Since then, evidence has accumulated that supports the major assumptions of this model. Evidence has also appeared that challenges some of our assumptions, which has allowed us to modify our original model. Refinements to our model include indexing of individuals by time rather than clinical symptom severity; incorporation of interindividual variability in cognitive impairment associated with progression of AD pathophysiology; modifications of the specific temporal ordering of some biomarkers; and recognition that the two major proteinopathies underlying AD biomarker changes, amyloid β (Aβ) and tau, might be initiated independently in sporadic AD, in which we hypothesise that an incident Aβ pathophysiology can accelerate antecedent limbic and brainstem tauopathy.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Humans; Models, Biological; Nonlinear Dynamics; tau Proteins

Demonstrated brain insulin resistance in Alzheimer's disease patients is associated with IGF-1 resistance, IRS-1 dysregulation, and cognitive decline. - Talbot, Konrad; Wang, Hoau-Yan; Kazi, Hala; Han, Li-Ying; Bakshi, Kalindi P; Stucky, Andres; Fuino, Robert L; Kawaguchi, Krista R; Samoyedny, Andrew J; Wilson, Robert S; Arvanitakis, Zoe; Schneider, Julie A; et al. (J Clin Invest, 2012)
While a potential causal factor in Alzheimer's disease (AD), brain insulin resistance has not been demonstrated directly in that disorder. We provide such a demonstration here by showing that the hippocampal formation (HF) and, to a lesser degree, the cerebellar cortex in AD cases without diabetes exhibit markedly reduced responses to insulin signaling in the IR→IRS-1→PI3K signaling pathway with greatly reduced responses to IGF-1 in the IGF-1R→IRS-2→PI3K signaling pathway. Reduced insulin responses were maximal at the level of IRS-1 and were consistently associated with basal elevations in IRS-1 phosphorylated at serine 616 (IRS-1 pS⁶¹⁶) and IRS-1 pS⁶³⁶/⁶³⁹. In the HF, these candidate biomarkers of brain insulin resistance increased commonly and progressively from normal cases to mild cognitively impaired cases to AD cases regardless of diabetes or APOE ε4 status. Levels of IRS-1 pS⁶¹⁶ and IRS-1 pS⁶³⁶/⁶³⁹ and their activated kinases correlated positively with those of oligomeric Aβ plaques and were negatively associated with episodic and working memory, even after adjusting for Aβ plaques, neurofibrillary tangles, and APOE ε4. Brain insulin resistance thus appears to be an early and common feature of AD, a phenomenon accompanied by IGF-1 resistance and closely associated with IRS-1 dysfunction potentially triggered by Aβ oligomers and yet promoting cognitive decline independent of classic AD pathology.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain; Cerebellar Cortex; Cognition Disorders; Diabetes Complications; Drug Resistance; Female; Glucose; Hippocampus; Humans; Insulin; Insulin Receptor Substrate Proteins; Insulin Resistance; Insulin-Like Growth Factor I; Male; Middle Aged; Phosphorylation; Phosphoserine; Protein Processing, Post-Translational; Recombinant Proteins; Signal Transduction

An epigenetic blockade of cognitive functions in the neurodegenerating brain. - Gräff, Johannes; Rei, Damien; Guan, Ji-Song; Wang, Wen-Yuan; Seo, Jinsoo; Hennig, Krista M; Nieland, Thomas J F; Fass, Daniel M; Kao, Patricia F; Kahn, Martin; Su, Susan C; Samiei, Alireza; et al. (Nature, 2012)
Cognitive decline is a debilitating feature of most neurodegenerative diseases of the central nervous system, including Alzheimer's disease. The causes leading to such impairment are only poorly understood and effective treatments are slow to emerge. Here we show that cognitive capacities in the neurodegenerating brain are constrained by an epigenetic blockade of gene transcription that is potentially reversible. This blockade is mediated by histone deacetylase 2, which is increased by Alzheimer's-disease-related neurotoxic insults in vitro, in two mouse models of neurodegeneration and in patients with Alzheimer's disease. Histone deacetylase 2 associates with and reduces the histone acetylation of genes important for learning and memory, which show a concomitant decrease in expression. Importantly, reversing the build-up of histone deacetylase 2 by short-hairpin-RNA-mediated knockdown unlocks the repression of these genes, reinstates structural and synaptic plasticity, and abolishes neurodegeneration-associated memory impairments. These findings advocate for the development of selective inhibitors of histone deacetylase 2 and suggest that cognitive capacities following neurodegeneration are not entirely lost, but merely impaired by this epigenetic blockade.
Keywords: Acetylation; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Epigenesis, Genetic; Gene Expression Regulation; Gene Knockdown Techniques; Hippocampus; Histone Deacetylase 2; Histones; Humans; Hydrogen Peroxide; Memory Disorders; Mice; Neurodegenerative Diseases; Neuronal Plasticity; Peptide Fragments; Phosphorylation; Promoter Regions, Genetic; Receptors, Glucocorticoid; RNA Polymerase II

A mutation in APP protects against Alzheimer's disease and age-related cognitive decline. - Jonsson, Thorlakur; Atwal, Jasvinder K; Steinberg, Stacy; Snaedal, Jon; Jonsson, Palmi V; Bjornsson, Sigurbjorn; Stefansson, Hreinn; Sulem, Patrick; Gudbjartsson, Daniel; Maloney, Janice; Hoyte, Kwame; Gustafson, Amy; et al. (Nature, 2012)
The prevalence of dementia in the Western world in people over the age of 60 has been estimated to be greater than 5%, about two-thirds of which are due to Alzheimer's disease. The age-specific prevalence of Alzheimer's disease nearly doubles every 5 years after age 65, leading to a prevalence of greater than 25% in those over the age of 90 (ref. 3). Here, to search for low-frequency variants in the amyloid-β precursor protein (APP) gene with a significant effect on the risk of Alzheimer's disease, we studied coding variants in APP in a set of whole-genome sequence data from 1,795 Icelanders. We found a coding mutation (A673T) in the APP gene that protects against Alzheimer's disease and cognitive decline in the elderly without Alzheimer's disease. This substitution is adjacent to the aspartyl protease β-site in APP, and results in an approximately 40% reduction in the formation of amyloidogenic peptides in vitro. The strong protective effect of the A673T substitution against Alzheimer's disease provides proof of principle for the hypothesis that reducing the β-cleavage of APP may protect against the disease. Furthermore, as the A673T allele also protects against cognitive decline in the elderly without Alzheimer's disease, the two may be mediated through the same or similar mechanisms.
Keywords: Aging; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognition; Cognition Disorders; Genetic Predisposition to Disease; HEK293 Cells; Humans; Mutation; Plaque, Amyloid

National Institute on Aging-Alzheimer's Association guidelines for the neuropathologic assessment of Alzheimer's disease. - Hyman, Bradley T; Phelps, Creighton H; Beach, Thomas G; Bigio, Eileen H; Cairns, Nigel J; Carrillo, Maria C; Dickson, Dennis W; Duyckaerts, Charles; Frosch, Matthew P; Masliah, Eliezer; Mirra, Suzanne S; Nelson, Peter T; et al. (Alzheimers Dement, 2012)
A consensus panel from the United States and Europe was convened recently to update and revise the 1997 consensus guidelines for the neuropathologic evaluation of Alzheimer's disease (AD) and other diseases of brain that are common in the elderly. The new guidelines recognize the pre-clinical stage of AD, enhance the assessment of AD to include amyloid accumulation as well as neurofibrillary change and neuritic plaques, establish protocols for the neuropathologic assessment of Lewy body disease, vascular brain injury, hippocampal sclerosis, and TDP-43 inclusions, and recommend standard approaches for the workup of cases and their clinico-pathologic correlation.
Keywords: Alzheimer Disease; Brain; Consensus Development Conferences, NIH as Topic; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Neuroinflammation, hyperphosphorylated tau, diffuse amyloid plaques, and down-regulation of the cellular prion protein in air pollution exposed children and young adults. - Calderón-Garcidueñas, Lilian; Kavanaugh, Michael; Block, Michelle; D'Angiulli, Amedeo; Delgado-Chávez, Ricardo; Torres-Jardón, Ricardo; González-Maciel, Angelica; Reynoso-Robles, Rafael; Osnaya, Norma; Villarreal-Calderon, Rodolfo; Guo, Ruixin; Hua, Zhaowei; et al. (J Alzheimers Dis, 2012)
Air pollution exposures have been linked to neuroinflammation and neuropathology. Autopsy samples of the frontal cortex from control (n = 8) and pollution-exposed (n = 35) children and young adults were analyzed by RT-PCR (n = 43) and microarray analysis (n = 12) for gene expression changes in oxidative stress, DNA damage signaling, NFκB signaling, inflammation, and neurodegeneration pathways. The effect of apolipoprotein E (APOE) genotype on the presence of protein aggregates associated with Alzheimer's disease (AD) pathology was also explored. Exposed urbanites displayed differential (>2-fold) regulation of 134 genes. Forty percent exhibited tau hyperphosphorylation with pre-tangle material and 51% had amyloid-β (Aβ) diffuse plaques compared with 0% in controls. APOE4 carriers had greater hyperphosphorylated tau and diffuse Aβ plaques versus E3 carriers (Q = 7.82, p = 0.005). Upregulated gene network clusters included IL1, NFκB, TNF, IFN, and TLRs. A 15-fold frontal down-regulation of the prion-related protein (PrP(C)) was seen in highly exposed subjects. The down-regulation of the PrP(C) is critical given its important roles for neuroprotection, neurodegeneration, and mood disorder states. Elevation of indices of neuroinflammation and oxidative stress, down-regulation of the PrP(C) and AD-associated pathology are present in young megacity residents. The inducible regulation of gene expression suggests they are evolving different mechanisms in an attempt to cope with the constant state of inflammation and oxidative stress related to their environmental exposures. Together, these data support a role for air pollution in CNS damage and its impact upon the developing brain and the potential etiology of AD and mood disorders.
Keywords: Adolescent; Adult; Age Factors; Air Pollution; Child; Child, Preschool; Cohort Studies; Down-Regulation; Encephalitis; Female; Frontal Lobe; Gene Regulatory Networks; Humans; Infant; Male; Mexico; Phosphorylation; Plaque, Amyloid; Prions; tau Proteins; Young Adult

The diagnosis of dementia due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - McKhann, Guy M; Knopman, David S; Chertkow, Howard; Hyman, Bradley T; Jack, Clifford R; Kawas, Claudia H; Klunk, William E; Koroshetz, Walter J; Manly, Jennifer J; Mayeux, Richard; Mohs, Richard C; Morris, John C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of revising the 1984 criteria for Alzheimer's disease (AD) dementia. The workgroup sought to ensure that the revised criteria would be flexible enough to be used by both general healthcare providers without access to neuropsychological testing, advanced imaging, and cerebrospinal fluid measures, and specialized investigators involved in research or in clinical trial studies who would have these tools available. We present criteria for all-cause dementia and for AD dementia. We retained the general framework of probable AD dementia from the 1984 criteria. On the basis of the past 27 years of experience, we made several changes in the clinical criteria for the diagnosis. We also retained the term possible AD dementia, but redefined it in a manner more focused than before. Biomarker evidence was also integrated into the diagnostic formulations for probable and possible AD dementia for use in research settings. The core clinical criteria for AD dementia will continue to be the cornerstone of the diagnosis in clinical practice, but biomarker evidence is expected to enhance the pathophysiological specificity of the diagnosis of AD dementia. Much work lies ahead for validating the biomarker diagnosis of AD dementia.
Keywords: Alzheimer Disease; Biomarkers; Diagnosis, Differential; Diagnostic Imaging; Disease Progression; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

The diagnosis of mild cognitive impairment due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Albert, Marilyn S; DeKosky, Steven T; Dickson, Dennis; Dubois, Bruno; Feldman, Howard H; Fox, Nick C; Gamst, Anthony; Holtzman, David M; Jagust, William J; Petersen, Ronald C; Snyder, Peter J; Carrillo, Maria C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of developing criteria for the symptomatic predementia phase of Alzheimer's disease (AD), referred to in this article as mild cognitive impairment due to AD. The workgroup developed the following two sets of criteria: (1) core clinical criteria that could be used by healthcare providers without access to advanced imaging techniques or cerebrospinal fluid analysis, and (2) research criteria that could be used in clinical research settings, including clinical trials. The second set of criteria incorporate the use of biomarkers based on imaging and cerebrospinal fluid measures. The final set of criteria for mild cognitive impairment due to AD has four levels of certainty, depending on the presence and nature of the biomarker findings. Considerable work is needed to validate the criteria that use biomarkers and to standardize biomarker analysis for use in community settings.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Diagnosis, Differential; Diagnostic Imaging; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Evidence for ordering of Alzheimer disease biomarkers. - Jack, Clifford R; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Aisen, Paul S; Trojanowski, John Q; Shaw, Leslie M; Bernstein, Matthew A; Petersen, Ronald C; Weiner, Michael W; Knopman, David S (Arch Neurol, 2011)
OBJECTIVE: To empirically assess the concept that Alzheimer disease (AD) biomarkers significantly depart from normality in a temporally ordered manner. DESIGN: Validation sample. SETTING: Multisite, referral centers. PARTICIPANTS: A total of 401 elderly participants in the Alzheimer's Disease Neuroimaging Initiative who were cognitively normal, who had mild cognitive impairment, or who had AD dementia. We compared the proportions of 3 AD biomarker values (the Aβ42 level in cerebrospinal fluid [CSF], the total tau level in CSF, and the hippocampal volume adjusted for intracranial volume [hereafter referred to as the adjusted hippocampal volume]) that were abnormal as cognitive impairment worsened. Cut points demarcating normal vs abnormal for each biomarker were established by maximizing diagnostic accuracy in independent autopsy samples. MAIN OUTCOME MEASURES: Three AD biomarkers (ie, the CSF Aβ42 level, the CSF total tau level, and the adjusted hippocampal volume). RESULTS: Within each clinical group of the entire sample (n = 401), the CSF Aβ42 level was abnormal more often than was the CSF total tau level or the adjusted hippocampal volume. Among the 298 participants with both baseline and 12-month data, the proportion of participants with an abnormal Aβ42 level did not change from baseline to 12 months in any group. The proportion of participants with an abnormal total tau level increased from baseline to 12 months in cognitively normal participants (P = .05) but not in participants with mild cognitive impairment or AD dementia. For 209 participants with an abnormal CSF Aβ42 level at baseline, the percentage with an abnormal adjusted hippocampal volume but normal CSF total tau level increased from baseline to 12 months in participants with mild cognitive impairment. No change in the percentage of MCI participants with an abnormal total tau level was seen between baseline and 12 months. CONCLUSIONS: A reduction in the CSF Aβ42 level denotes a pathophysiological process that significantly departs from normality (ie, becomes dynamic) early, whereas the CSF total tau level and the adjusted hippocampal volume are biomarkers of downstream pathophysiological processes. The CSF total tau level becomes dynamic before the adjusted hippocampal volume, but the hippocampal volume is more dynamic in the clinically symptomatic mild cognitive impairment and AD dementia phases of the disease than is the CSF total tau level.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Hippocampus; Humans; Longitudinal Studies; Male; Mild Cognitive Impairment; tau Proteins

Report of the task force on designing clinical trials in early (predementia) AD. - Aisen, P S; Andrieu, S; Sampaio, C; Carrillo, M; Khachaturian, Z S; Dubois, B; Feldman, H H; Petersen, R C; Siemers, E; Doody, R S; Hendrix, S B; Grundman, M; et al. (Neurology, 2011)
BACKGROUND: A large number of promising candidate disease-modifying treatments for Alzheimer disease (AD) continue to advance into phase II and phase III testing. However, most completed trials have failed to demonstrate efficacy, and there is growing concern that methodologic difficulties may contribute to these clinical trial failures. The optimal time to intervene with such treatments is probably in the years prior to the onset of dementia, before the neuropathology has progressed to the advanced stage corresponding to clinical dementia. METHOD: An international task force of individuals from academia, industry, nonprofit foundations, and regulatory agencies was convened to discuss optimal trial design in early (predementia) AD. RESULTS: General consensus was reached on key principles involving the scope of the AD diagnosis, the selection of subjects for trials, outcome measures, and analytical methods. CONCLUSION: A consensus has been achieved in support of the testing of candidate treatments in the early (predementia) AD population.
Keywords: Advisory Committees; Alzheimer Disease; Amyloidogenic Proteins; Biomarkers; Clinical Trials as Topic; Cognition; Consensus; Disease Progression; Drug Industry; Early Diagnosis; Europe; Humans; Indans; International Cooperation; Nootropic Agents; Outcome Assessment (Health Care); Patient Selection; Piperidines; Positron-Emission Tomography; Research Design; Treatment Outcome; United States; United States Food and Drug Administration; Vitamin E

Stages of the pathologic process in Alzheimer disease: age categories from 1 to 100 years. - Braak, Heiko; Thal, Dietmar R; Ghebremedhin, Estifanos; Del Tredici, Kelly (J Neuropathol Exp Neurol, 2011)
Two thousand three hundred and thirty two nonselected brains from 1- to 100-year-old individuals were examined using immunocytochemistry (AT8) and Gallyas silver staining for abnormal tau; immunocytochemistry (4G8) and Campbell-Switzer staining were used for the detection ofβ-amyloid. A total of 342 cases was negative in the Gallyas stain but when restaged for AT8 only 10 were immunonegative. Fifty-eight cases had subcortical tau predominantly in the locus coeruleus, but there was no abnormal cortical tau (subcortical Stages a-c). Cortical involvement (abnormal tau in neurites) was identified first in the transentorhinal region (Stage 1a, 38 cases). Transentorhinal pyramidal cells displayed pretangle material (Stage 1b, 236 cases). Pretangles gradually became argyrophilic neurofibrillary tangles (NFTs) that progressed in parallel with NFT Stages I to VI. Pretangles restricted to subcortical sites were seen chiefly at younger ages. Of the total cases, 1,031 (44.2%) had β-amyloid plaques. The first plaques occurred in the neocortex after the onset of tauopathy in the brainstem. Plaques generally developed in the 40s in 4% of all cases, culminating in their tenth decade (75%). β-amyloid plaques and NFTs were significantly correlated (p < 0.0001). These data suggest that tauopathy associated with sporadic Alzheimer disease may begin earlier than previously thought and possibly in the lower brainstem rather than in the transentorhinal region.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Child; Child, Preschool; Cohort Studies; Disease Progression; Female; Humans; Infant; Male; Middle Aged; Neurofibrillary Tangles; Neurons; Silver Staining; Statistics, Nonparametric; tau Proteins; Young Adult

Toward defining the preclinical stages of Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Sperling, Reisa A; Aisen, Paul S; Beckett, Laurel A; Bennett, David A; Craft, Suzanne; Fagan, Anne M; Iwatsubo, Takeshi; Jack, Clifford R; Kaye, Jeffrey; Montine, Thomas J; Park, Denise C; Reiman, Eric M; et al. (Alzheimers Dement, 2011)
The pathophysiological process of Alzheimer's disease (AD) is thought to begin many years before the diagnosis of AD dementia. This long "preclinical" phase of AD would provide a critical opportunity for therapeutic intervention; however, we need to further elucidate the link between the pathological cascade of AD and the emergence of clinical symptoms. The National Institute on Aging and the Alzheimer's Association convened an international workgroup to review the biomarker, epidemiological, and neuropsychological evidence, and to develop recommendations to determine the factors which best predict the risk of progression from "normal" cognition to mild cognitive impairment and AD dementia. We propose a conceptual framework and operational research criteria, based on the prevailing scientific evidence to date, to test and refine these models with longitudinal clinical research studies. These recommendations are solely intended for research purposes and do not have any clinical implications at this time. It is hoped that these recommendations will provide a common rubric to advance the study of preclinical AD, and ultimately, aid the field in moving toward earlier intervention at a stage of AD when some disease-modifying therapies may be most efficacious.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; United States

Alzheimer's Disease Neuroimaging Initiative (ADNI): clinical characterization. - Petersen, R C; Aisen, P S; Beckett, L A; Donohue, M C; Gamst, A C; Harvey, D J; Jack, C R; Jagust, W J; Shaw, L M; Toga, A W; Trojanowski, J Q; Weiner, M W (Neurology, 2010)
BACKGROUND: Neuroimaging measures and chemical biomarkers may be important indices of clinical progression in normal aging and mild cognitive impairment (MCI) and need to be evaluated longitudinally. OBJECTIVE: To characterize cross-sectionally and longitudinally clinical measures in normal controls, subjects with MCI, and subjects with mild Alzheimer disease (AD) to enable the assessment of the utility of neuroimaging and chemical biomarker measures. METHODS: A total of 819 subjects (229 cognitively normal, 398 with MCI, and 192 with AD) were enrolled at baseline and followed for 12 months using standard cognitive and functional measures typical of clinical trials. RESULTS: The subjects with MCI were more memory impaired than the cognitively normal subjects but not as impaired as the subjects with AD. Nonmemory cognitive measures were only minimally impaired in the subjects with MCI. The subjects with MCI progressed to dementia in 12 months at a rate of 16.5% per year. Approximately 50% of the subjects with MCI were on antidementia therapies. There was minimal movement on the Alzheimer's Disease Assessment Scale-Cognitive Subscale for the normal control subjects, slight movement for the subjects with MCI of 1.1, and a modest change for the subjects with AD of 4.3. Baseline CSF measures of Abeta-42 separated the 3 groups as expected and successfully predicted the 12-month change in cognitive measures. CONCLUSION: The Alzheimer's Disease Neuroimaging Initiative has successfully recruited cohorts of cognitively normal subjects, subjects with mild cognitive impairment (MCI), and subjects with Alzheimer disease with anticipated baseline characteristics. The 12-month progression rate of MCI was as predicted, and the CSF measures heralded progression of clinical measures over 12 months.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cross-Sectional Studies; Diagnostic Imaging; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged

Genetic evidence implicates the immune system and cholesterol metabolism in the aetiology of Alzheimer's disease. - Jones, Lesley; Holmans, Peter A; Hamshere, Marian L; Harold, Denise; Moskvina, Valentina; Ivanov, Dobril; Pocklington, Andrew; Abraham, Richard; Hollingworth, Paul; Sims, Rebecca; Gerrish, Amy; Pahwa, Jaspreet Singh; et al. (PLoS One, 2010)
BACKGROUND: Late Onset Alzheimer's disease (LOAD) is the leading cause of dementia. Recent large genome-wide association studies (GWAS) identified the first strongly supported LOAD susceptibility genes since the discovery of the involvement of APOE in the early 1990s. We have now exploited these GWAS datasets to uncover key LOAD pathophysiological processes. METHODOLOGY: We applied a recently developed tool for mining GWAS data for biologically meaningful information to a LOAD GWAS dataset. The principal findings were then tested in an independent GWAS dataset. PRINCIPAL FINDINGS: We found a significant overrepresentation of association signals in pathways related to cholesterol metabolism and the immune response in both of the two largest genome-wide association studies for LOAD. SIGNIFICANCE: Processes related to cholesterol metabolism and the innate immune response have previously been implicated by pathological and epidemiological studies of Alzheimer's disease, but it has been unclear whether those findings reflected primary aetiological events or consequences of the disease process. Our independent evidence from two large studies now demonstrates that these processes are aetiologically relevant, and suggests that they may be suitable targets for novel and existing therapeutic approaches.
Keywords: Alzheimer Disease; Apolipoproteins E; Cholesterol; Chromosome Mapping; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Immune System; Polymorphism, Single Nucleotide

National Institutes of Health State-of-the-Science Conference statement: preventing alzheimer disease and cognitive decline. - Daviglus, Martha L; Bell, Carl C; Berrettini, Wade; Bowen, Phyllis E; Connolly, E Sander; Cox, Nancy Jean; Dunbar-Jacob, Jacqueline M; Granieri, Evelyn C; Hunt, Gail; McGarry, Kathleen; Patel, Dinesh; Potosky, Arnold L; et al. (Ann Intern Med, 2010)
The National Institute on Aging and the Office of Medical Applications of Research of the National Institutes of Health convened a State-of-the-Science Conference on 26-28 April 2010 to assess the available scientific evidence on prevention of cognitive decline and Alzheimer disease. This article provides the panel's assessment of the available evidence.
Keywords: Aged; Alzheimer Disease; Cognition Disorders; Evidence-Based Medicine; Humans; Risk Factors; Risk Reduction Behavior